(1 -> 3)-beta-D-glucan and mannan guided early termination of antifungal therapy in ICU patients: a prospective randomized intervention study (REDUCE-AM) - Erb, T.; Mihai, Sidonia; Cipa, Franziska; Herbst, Larissa; Strauss, Richard; Castellanos, Ixchel; Lang, K.; Ganslmayer, Marion; Willam, Carsten; Rath, Anca; Diesch, Katharina; Held, Jürgen (MYCOSES, 2020)
CRIS-Team WoS Importer:2020-10-02

(1 -> 3)-beta-D-Glucan-guided antifungal therapy in adults with sepsis: the CandiSep randomized clinical trial - Bloos, Frank; Held, Jürgen; Kluge, Stefan; Simon, Philipp; Kogelmann, Klaus; De Heer, Geraldine; Kuhn, Sven-Olaf; Jarczak, Dominik; Motsch, Johann; Hempel, Gunther; Weiler, Norbert; Weyland, Andreas; et al. (Intensive Care Medicine, 2022)
Purpose: To investigate whether (1 -> 3)-beta-d-Glucan (BDG)-guidance shortens time to antifungal therapy and thereby reduces mortality of sepsis patients with high risk of invasive Candida infection (ICI).
CRIS-Team WoS Importer:2022-07-01

(1,3)-β-D-glucan-based diagnosis of invasive Candida infection versus culture-based diagnosis in patients with sepsis and with an increased risk of invasive Candida infection (CandiSep): study protocol for a randomized controlled trial - Bloos, Frank; Held, Jürgen; Schlattmann, Peter; Brillinger, Nicole; Kurzai, Oliver; Cornely, Oliver A.; Thomas-Rueddel, Daniel (Trials, 2018)
BACKGROUND: The time to diagnosis of invasive Candida infection (ICI) is often too long to initiate timely antifungal therapy in patients with sepsis. Elevated serum (1,3)-β-D-glucan (BDG) concentrations have a high diagnostic sensitivity for detecting ICI. However, the clinical significance of elevated BDG concentrations is unclear in critically ill patients. The goal of this study is to investigate whether measurement of BDG in patients with sepsis and a high risk for ICI can be used to decrease the time to empiric antifungal therapy and thus, increase survival. METHODS/DESIGN: This prospective multicenter open randomized controlled trial is being conducted in 19 German intensive care units. All adult patients with severe sepsis or septic shock and an increased risk for ICI are eligible for enrolment. Risk factors are total parenteral nutrition, previous abdominal surgery, previous antimicrobial therapy, and renal replacement therapy. Patients with proven ICI or those already treated with systemic antifungal substances are excluded. Patients are allocated to a BDG or standard care group. The standard care group receives targeted antifungal therapy as necessary. In the BDG group, BDG serum samples are taken after randomization and 24 h later. Antifungal therapy is initiated if BDG is ≥80 pg/ml in at least one sample. We plan to enroll 312 patients. The primary outcome is 28-day mortality. Other outcomes include antifungal-free survival within 28 days after enrolment, time to antifungal therapy, and the diagnostic performance of BDG compared to other laboratory tests for early ICI diagnosis. The statistical analysis will be performed according to the intent-to-treat principle. DISCUSSION: Because of the high risk of death, American guidelines recommend empiric antifungal therapy in sepsis patients with a high risk of ICI despite the limited evidence for such a recommendation. In contrast, empiric antifungal therapy is not recommended by European guidelines. BDG may offer a way out of this dilemma since BDG potentially identifies patients in need of early antifungals. However, the evidence for such an approach is inconclusive. This clinical study will generate solid evidence for health-care providers and authors of guidelines for the use of BDG in critically ill patients. TRIAL REGISTRATION: Clinicaltrials.gov, NCT02734550 . Registered 12 April 2016.
EVALuna2:34577

23Na magnetic resonance imaging-determined tissue sodium in healthy subjects and hypertensive patients - Kopp, Christoph; Linz, Peter; Dahlmann, Anke; Hammon, Matthias; Jantsch, Jonathan; Mueller, Dominik N.; Schmieder, Roland; Cavallaro, Alexander Josef; Eckardt, Kai-Uwe; Uder, Michael; Luft, Friedrich C.; Titze, Jens (Hypertension, 2013)
High dietary salt intake is associated with hypertension; the prevalence of salt-sensitive hypertension increases with age. We hypothesized that tissue Na might accumulate in hypertensive patients and that aging might be accompanied by Na deposition in tissue. We implemented Na magnetic resonance imaging to measure Na content of soft tissues in vivo earlier, but had not studied essential hypertension. We report on a cohort of 56 healthy control men and women, and 57 men and women with essential hypertension. The ages ranged from 22 to 90 years. Na magnetic resonance imaging measurements were made at the level of the calf. We observed age-dependent increases in Na content in muscle in men, whereas muscle Na content did not change with age in women. We estimated water content with conventional MRI and found no age-related increases in muscle water in men, despite remarkable Na accumulation, indicating water-free Na storage in muscle. With increasing age, there was Na deposition in the skin in both women and men; however, skin Na content remained lower in women. Similarly, this sex difference was found in skin water content, which was lower in women than in men. In contrast to muscle, increasing Na content was paralleled with increasing skin water content. When controlled for age, we found that patients with refractory hypertension had increased tissue Na content, compared with normotensive controls. These observations suggest that Na magnetic resonance imaging could have utility in assessing the role of tissue Na storage for cardiovascular morbidity and mortality in longitudinal studies. © 2013 American Heart Association, Inc.
CRIS-Team Scopus Importer:2023-03-08
Keywords: aging; gender difference; hypertension; salt; sodium MRI

Absence of Siglec-H in MCMV Infection Elevates Interferon Alpha Production but Does Not Enhance Viral Clearance - Puttur, Franz; Arnold-Schrauf, Catharina; Lahl, Katharina; Solmaz, Gulhas; Lindenberg, Marc; Mayer, Christian Thomas; Gohmert, Melanie; Swallow, Maxine; Van Helt, Christopher; Schmitt, Heike; Nitschke, Lars; Lambrecht, Bart N.; et al. (PLoS Pathogens, 2013)
Plasmacytoid dendritic cells (pDCs) express the I-type lectin receptor Siglec-H and produce interferon alpha (IFN alpha), a critical antiviral cytokine during the acute phase of murine cytomegalovirus (MCMV) infection. The ligands and biological functions of Siglec-H still remain incompletely defined in vivo. Thus, we generated a novel bacterial artificial chromosome (BAC)-transgenic "pDCre" mouse which expresses Cre recombinase under the control of the Siglec-H promoter. By crossing these mice with a Rosa26 reporter strain, a representative fraction of Siglec-H+ pDCs is terminally labeled with red fluorescent protein (RFP). Interestingly, systemic MCMV infection of these mice causes the downregulation of Siglec-H surface expression. This decline occurs in a TLR9- and MyD88-dependent manner. To elucidate the functional role of Siglec-H during MCMV infection, we utilized a novel Siglec-H deficient mouse strain. In the absence of Siglec-H, the low infection rate of pDCs with MCMV remained unchanged, and pDC activation was still intact. Strikingly, Siglec-H deficiency induced a significant increase in serum IFNa levels following systemic MCMV infection. Although Siglec-H modulates anti-viral IFNa production, the control of viral replication was unchanged in vivo. The novel mouse models will be valuable to shed further light on pDC biology in future studies.

A CCL1/CCR8-dependent feed-forward mechanism drives ILC2 functions in type 2-mediated inflammation - Knipfer, Lisa; Schulz-Kuhnt, Anja; Kindermann, Markus; Greif, Vicky; Symowski, Cornelia; Vöhringer, David; Neurath, Markus; Atreya, Imke; Wirtz, Stefan (Journal of Experimental Medicine, 2019)
Group 2 innate lymphoid cells (ILC2s) possess indispensable roles during type 2-mediated inflammatory diseases. Although their physiological and detrimental immune functions seem to depend on the anatomical compartment they reside, their tissue tropism and the molecular and immunological processes regulating the self-renewal of the local pool of ILC2s in the context of inflammation or infection are incompletely understood. Here, we analyzed the role of the CC-chemokine receptor CCR8 for the biological functions of ILC2s. In vitro and in vivo experiments indicated that CCR8 is in comparison to the related molecule CCR4 less important for migration of these cells. However, we found that activated mouse and human ILC2s produce the CCR8 ligand CCL1 and are a major source of CCL1 in vivo. CCL1 signaling to ILC2s regulates their proliferation and supports their capacity to protect against helminthic infections. In summary, we identify a novel chemokine receptor-dependent mechanism by which ILC2s are regulated during type 2 responses.
CRIS-Team Scopus Importer:2019-12-13

Acetate, a metabolic product of Heligmosomoides polygyrus, facilitates intestinal epithelial barrier breakdown in a FFAR2-dependent manner - Schälter, Fabian; Frech, Michael; Dürholz, Kerstin; Lucas, Sébastien; Sarter-Zaiss, Kerstin; Lebon, Luc; Esser-Von-Bieren, Julia; Dubey, Lalit Kumar; Vöhringer, David; Schett, Georg; Harris, Nicola L.; Zaiss, Mario (International Journal For Parasitology, 2022)

Activation and regulation of endogenous retroviral genes in the human pituitary gland and related endocrine tumours - Buslei, R.; Strissel, Pamela; Henke, Christine; Schey, Regina; Lang, Nadine; Ruebner, M.; Stolt, Claus; Fabry, Ben; Buchfelder, Michael; Strick, Reiner (Neuropathology and Applied Neurobiology, 2015)
Adenohypophysis (AH) hormone-producing cells represent the origin of diverse groups of pituitary adenomas (PA). Deregulation of hypothalamic hormone receptors, growth factors and cAMP signalling have been implicated in the aetiology of PA. Endogenous retroviruses (ERVs) are derived from past exogenous retroviral infections and represent more than 8% of the human genome. Some ERV genes encode open reading frames and produce functional proteins, for example, the ERVW-1 envelope gene Syncytin-1, essential for placentogenesis, but also deregulated in human tumours. Data concerning ERV expression in the AH and related endocrine tumours are missing.Syncytin-1 protein was analysed in normal AH (n = 15) and compared with five PA subtypes (n = 117) by immunohistochemistry. Absolute gene expression of 20 ERV functional envelope genes and ERVW-5 gag was measured. PA tissues were examined for Syncytin-1 and the cAMP signalling marker phospho-CREB-Ser133 using immunohistochemistry. Isolated primary human PA cells were treated with different hormones. Murine embryonic and adult pituitary gland ERV expressions were compared with human AH.Syncytin-1 protein colocalized with corticotropic cells of AH. In contrast, all PA demonstrated significant Syncytin-1 protein overexpression, supporting deregulation. All other ERV genes showed significant up-regulations in different PA subtypes. Phospho-CREB-Ser133 and Syncytin-1 colocalized in PA cells. Cultivated primary PA cells with ACTH or CRH induced their respective receptors and ERV genes. Syncytin-A/-B, murine orthologues to human Syncytin-1/-2, localized to embryonic and adult pituitary glands demonstrating functional mammalian conservation.Deregulated ERV genes may contribute to PA development via cAMP signalling.
EVALuna2:4955

Activation of STAT6 in Intestinal Epithelial Cells Predisposes to Gut Inflammation - Westermann, Stefanie; Radtke, Daniel; Kramer, Lisa; Wirtz, Stefan; Vöhringer, David (European Journal of Immunology, 2024)
Ulcerative colitis (UC) is an inflammatory bowel disease (IBD) often associated with a Type 2 immune response. Although previous reports hint at a role for signal transducer and activator of transcription (STAT) 6 signaling in non-immune cells, the contribution of STAT6-activation particularly in intestinal epithelial cells (IECs) is still unknown. Dextran sodium sulfate (DSS)-induced colitis is a model for UC in mice that we applied here on animals with expression of a constitutively active version of STAT6 in IECs (VillinCre_STAT6vt mice). We report increased pathology and mortality due to enhanced and systemic inflammation in these mice. Bulk RNA sequencing of colonic tissue from naïve VillinCre_STAT6vt mice showed differential expression of more than 140 genes compared to control mice. Gene set enrichment analysis revealed STAT6-regulated expression of the unfolded protein response, MTORC- and MYC-signaling, and protein secretion pathways. A comparison of gene expression in the colon of naïve VillinCre_STAT6vt mice and a human single-cell RNA sequencing dataset of a patient cohort with IBD revealed overlapping changes in the epithelial and macrophage compartment compared to corresponding controls. In conclusion, we found that activation of STAT6 in the intestinal epithelium predisposes to exacerbated colitis and gut inflammation.
CRIS-Team Scopus Importer:2025-02-04
Keywords: dextran sodium sulfate; gasdermin C; inflammatory bowel disease; LGR4; STAT6; ulcerative colitis

Adaptive immune responses are larger and functionally preserved in a hypervaccinated individual - Kocher, Katharina; Moosmann, Carolin; Drost, Felix; Schülein, Christine; Irrgang, Pascal; Steininger, Philipp; Zhong, Jahn; Träger, Johannes; Spriewald, Bernd; Bock, Christoph; Busch, Dirk H.; Bogdan, Christian; et al. (Lancet Infectious Diseases, 2024)
CRIS-Team Scopus Importer:2024-03-29

A Dual-Pathogen Mitral Valve Endocarditis Caused by Coxiella burnetii and Streptococcus gordonii—Which Came First? - Kaemmerer, Ann-Sophie; Ciotola, Francesco; Geißdörfer, Walter; Harig, Frank; Mattner, Jochen; Seitz, Tatjana; Suleiman, Mathieu; Weyand, Michael; Heim, Christian (Pathogens, 2023)
Infective endocarditis (IE) is still a life-threatening disease with high morbidity and mortality. While usually caused by a single bacterium, poly-microbial infective endocarditis (IE) is rare. Here, we report a (blood-culture-negative) dual pathogen mitral valve IE caused by Coxiella burnetii and Streptococcus gordonii: A 53-year-old woman was presented to an internal medicine department with abdominal pain for further evaluation. Within the diagnostic work up, transthoracic echocardiography (TTE) revealed an irregularly shaped echogenic mass (5 × 13 mm) adherent to the edge of the posterior mitral valve leaflet and protruding into the left atrium. As infected endocarditis was suspected, blood cultures were initially obtained, but they remained negative. Chronic Q fever infection was diagnosed using serologic testing. After the occurrence of cerebral thromboembolic events, the patient was admitted for mitral valve surgery. Intraoperatively, a massively destructed mitral valve with adhering vegetations was noted. Examination of the mitral valve by broad-range bacterial polymerase chain reaction (PCR) and amplicon sequencing confirmed Coxiella burnetii infection and yielded Streptococcus gordonii as the second pathogen. Based on the detailed diagnosis, appropriate antibiotic therapy of both pathogens was initiated, and the patient could be discharged uneventfully on the 11th postoperative day after a successful minimal-invasive mitral valve replacement.
CRIS-Team Scopus Importer:2023-10-20
Keywords: blood-culture-negative endocarditis; Coxiella burnetii; dual-pathogen endocarditis; endocarditis; minimally invasive mitral valve replacement; polymicrobial infective endocarditis; Q fever; Streptococcus gordonii

A genome-wide CRISPR functional survey of the human phagocytosis molecular machinery - Essletzbichler, Patrick; Sedlyarov, Vitaly; Frommelt, Fabian; Soulat, Didier; Heinz, Leonhard X.; Stefanovic, Adrijana; Neumayer, Benedikt; Superti-Furga, Giulio (Life Science Alliance, 2023)
Phagocytosis, the process by which cells engulf large particles, plays a vital role in driving tissue clearance and host defense. Its dysregulation is connected to autoimmunity, toxic accumulation of proteins, and increased risks for infections. Despite its im-portance, we lack full understanding of all molecular components involved in the process. To create a functional map in human cells, we performed a genome-wide CRISPRko FACS screen that identified 716 genes. Mapping those hits to a comprehensive protein-protein interaction network annotated for functional cellular processes allowed retrieval of protein complexes iden-tified multiple times and detection of missing phagocytosis regulators. In addition to known components, such as the Arp2/3 complex, the vacuolar-ATPase-Rag machinery, and the Wave-2 complex, we identified and validated new phagocytosis-relevant functions, including the oligosaccharyltransferase complex (MAGT1/SLC58A1, DDOST, STT3B, and RPN2) and the hypusine pathway (eIF5A, DHPS, and DOHH). Overall, our phagocytosis network comprises elements of cargo uptake, shuffling, and biotransformation through the cell, providing a resource for the identification of potential novel drivers for diseases of the endo-lysosomal system. Our approach of integrating protein-protein interaction offers a broadly applicable way to functionally in-terpret genome-wide screens.
CRIS-Team WoS Importer:2023-02-24

Age-related changes in the local milieu of inflamed tissues cause aberrant neutrophil trafficking and subsequent remote organ damage - Barkaway, Anna; Rolas, Loïc; Joulia, Régis; Bodkin, Jennifer; Lenn, Tchern; Owen-Woods, Charlotte; Reglero-Real, Natalia; Stein, Monja; Vázquez-Martínez, Laura; Girbl, Tamara; Poston, Robin N.; Golding, Matthew; et al. (Immunity, 2021)
Aging is associated with dysregulated immune functions. Here, we investigated the impact of age on neutrophil diapedesis. Using confocal intravital microscopy, we found that in aged mice, neutrophils adhered to vascular endothelium in inflamed tissues but exhibited a high frequency of reverse transendothelial migration (rTEM). This retrograde breaching of the endothelium by neutrophils was governed by enhanced production of the chemokine CXCL1 from mast cells that localized at endothelial cell (EC) junctions. Increased EC expression of the atypical chemokine receptor 1 (ACKR1) supported this pro-inflammatory milieu in aged venules. Accumulation of CXCL1 caused desensitization of the chemokine receptor CXCR2 on neutrophils and loss of neutrophil directional motility within EC junctions. Fluorescent tracking revealed that in aged mice, neutrophils undergoing rTEM re-entered the circulation and disseminated to the lungs where they caused vascular leakage. Thus, neutrophils stemming from a local inflammatory site contribute to remote organ damage, with implication to the dysregulated systemic inflammation associated with aging.
CRIS-Team Scopus Importer:2021-07-16
Keywords: ACKR1; aging; chemokines; CXCR2; diapedesis; endothelium; extravasation; inflammation; mast cells; Neutrophils

A helminth enzyme subverts macrophage-mediated immunity by epigenetic targeting of prostaglandin synthesis - Bohnacker, Sina; Henkel, Fiona D.R.; Hartung, Franziska; Geerlof, Arie; Riemer, Sandra; Prodjinotho, Ulrich F.; Salah, Eya Ben; Dias Mourão, André Santos; Bohn, Stefan; Teder, Tarvi; Thomas, Dominique; Gurke, Robert; et al. (Science immunology, 2024)
The molecular mechanisms by which worm parasites evade host immunity are incompletely understood. In a mouse model of intestinal helminth infection using Heligmosomoides polygyrus bakeri (Hpb), we show that helminthic glutamate dehydrogenase (heGDH) drives parasite chronicity by suppressing macrophage-mediated host defense. Combining RNA-seq, ChIP-seq, and targeted lipidomics, we identify prostaglandin E2 (PGE2) as a major immune regulatory mechanism of heGDH. The induction of PGE2 and other immunoregulatory factors, including IL-12 family cytokines and indoleamine 2,3-dioxygenase 1, by heGDH required p300-mediated histone acetylation, whereas the enzyme’s catalytic activity suppressed the synthesis of type 2–promoting leukotrienes by macrophages via 2-hydroxyglutarate. By contrast, the induction of immunoregulatory factors involved the heGDH N terminus by potentially mediating interactions with cellular targets (CD64 and GPNMB) identified by proteomics. Type 2 cytokines counteracted suppressive effects of heGDH on host defense, indicating that type 2 immunity can limit helminth-driven immune evasion. Thus, helminths harness a ubiquitous metabolic enzyme to epigenetically target type 2 macrophage activation and establish chronicity.
CRIS-Team Scopus Importer:2025-02-04

A HIGH-THROUGHPUT WORKFLOW FOR THE FUNCTIONAL SCREENING AND CHARACTERIZATION OF CLINICALLY RELEVANT MHC CLASS I-RESTRICTED T CELL RECEPTORS FOR ADOPTIVE T CELL THERAPY - D'Ippolito, E.; Scheu, S.; Wagner, K.; Kazeroonian, A.; Hochholzer, A.; Graml, F.; Hamed, N.; Hammel, M.; Andrae, I.; Moosmann, Carolin; Boga, E.; Triebert, A. -K.; et al. (HUMAN GENE THERAPY, 2022)
CRIS-Team WoS Importer:2022-10-21

A hypomorphic IgH-chain allele affects development of B-cell subsets and favours receptor editing - Brenner, Sven; Drewel, Diana; Steinbart, Thomas; Weisel, Florian; Härtel, Eric; Pötzsch, Sonja; Welzel, Heike; Brandl, Andreas; Yu, Philipp; Mudde, Geert C; Schweizer, Astrid; Nitschke, Lars; et al. (EMBO Journal, 2011)
The quality and quantity of BCR signals impact on cell fate decisions of B lymphocytes. Here, we describe novel gene-targeted mice, which in the context of normal VDJ recombination show hypomorphic expression of immunoglobulin l heavy chain (mu HC) mRNA levels and hence lower pre-BCR and BCR levels. Hypomorphic expression of mu HC leads to augmented selection processes at all stages of B-cell development, noticeably at the expansion of pre-B cells, the positive selection of immature B lymphocytes in the bone marrow and the selection of the follicular (FO), marginal zone (MZ) and B1 B-lymphocyte compartment in peripheral lymphoid organs. Immature as well as mature FO and MZ B lymphocytes in the peripheral lymphoid organs express lower levels of the receptor for B-cell activating factor (BAFF). In addition, hypomorphic expression of the BCR favours receptor editing. Together, our results highlight the critical importance of pre-BCR and BCR receptor levels for the normal development of B-lymphocyte subpopulations in the context of intact VDJ recombination and a diverse antibody repertoire. The EMBO Journal (2011) 30, 2705-2718. doi:10.1038/emboj.2011.168; Published online 27 May 20
Keywords: BAFF; B-cell development; B-cell receptor; receptor editing

A monoclonal Trd chain supports the development of the complete set of functional γδ T cell lineages - Hahn, Anne Maria; Vogg, Lisa; Brey, Stefanie; Schneider, Andrea; Schäfer, Simon; Palmisano, Ralf; Pavlova, Anna; Sandrock, Inga; Tan, Likai; Fichtner, Alina S.; Prinz, Immo; Ravens, Sarina; et al. (Cell Reports, 2023)
The clonal selection theory describes key features of adaptive immune responses of B and T cells. For αβ T cells and B cells, antigen recognition and selection principles are known at a detailed molecular level. The precise role of the antigen receptor in γδ T cells remains less well understood. To better understand the role of the γδ T cell receptor (TCR), we generate an orthotopic TCRδ transgenic mouse model. We demonstrate a multi-layered functionality of γδ TCRs and diverse roles of CDR3δ-mediated selection during γδ T cell development. Whereas epithelial populations using Vγ5 or Vγ7 chains are almost unaffected in their biology in the presence of the transgenic TCRδ chain, pairing with Vγ1 positively selects γδ T cell subpopulations with distinct programs in several organs, thereby distorting the repertoire. In conclusion, our data support dictation of developmental tropism together with adaptive-like recognition principles in a single antigen receptor.
CRIS-Team Scopus Importer:2023-03-24
Keywords: CP: Immunology

A mutation within the SH2 domain of slp-76 regulates the tissue distribution and cytokine production of iNKT cells in mice - Danzer, Claudia Agnes; Koller, Anna; Baier, Julia; Arnold, Harald; Giessler, Claudia; Opoka, Robert; Schmidt, Stephanie; Willers, Maike; Mihai, Sidonia; Parsch, Hans; Wirtz, Stefan; Daniel, Christoph; et al. (European Journal of Immunology, 2016)
TCR ligation is critical for the selection, activation, and integrin expression of T lymphocytes. Here, we explored the role of the TCR adaptor protein slp-76 on iNKT-cell biology. Compared to B6 controls, slp-76(ace/ace) mice carrying a missense mutation (Thr428Ile) within the SH2-domain of slp-76 showed an increase in iNKT cells in the thymus and lymph nodes, but a decrease in iNKT cells in spleens and livers, along with reduced ADAP expression and cytokine response. A comparable reduction in iNKT cells was observed in the livers and spleens of ADAP-deficient mice. Like ADAP(-/-) iNKT cells, slp-76(ace/ace) iNKT cells were characterized by enhanced CD11b expression, correlating with an impaired induction of the TCR immediate-early gene Nur77 and a decreased adhesion to ICAM-1. Furthermore, CD11b-intrinsic effects inhibited cytokine release, concanavalin A-mediated inflammation, and iNKT-cell accumulation in the liver. Unlike B6 and ADAP(-/-) mice, the expression of the transcription factors Id3 and PLZF was reduced, whereas NP-1-expression was enhanced in slp-76(ace/ace) mice. Blockade of NP-1 decreased the recovery of iNKT cells from peripheral lymph nodes, identifying NP-1 as an iNKT-cell-specific adhesion factor. Thus, slp-76 contributes to the regulation of the tissue distribution, PLZF, and cytokine expression of iNKT cells via ADAP-dependent and -independent mechanisms.
EVALuna2:2050

Amyloidogenic amyloid-?-peptide variants induce microbial agglutination and exert antimicrobial activity - Spitzer, Philipp; Condic, Mateja; Herrmann, Martin; Oberstein, Timo; Scharin-Mehlmann, Marina; Gilbert, Daniel; Friedrich, Oliver; Groemer, Teja; Kornhuber, Johannes; Lang, Roland; Maler, Juan Manuel (Scientific Reports, 2016)
Amyloid-? (A?) peptides are the main components of the plaques found in the brains of patients with Alzheimer's disease. However, A? peptides are also detectable in secretory compartments and peripheral blood contains a complex mixture of more than 40 different modified and/or N- and C-terminally truncated A? peptides. Recently, anti-infective properties of A? peptides have been reported. Here, we investigated the interaction of A? peptides of different lengths with various bacterial strains and the yeast Candida albicans. The amyloidogenic peptides A?1-42, A?2-42, and A?3p-42 but not the non-amyloidogenic peptides A?1-40 and A?2-40 bound to microbial surfaces. As observed by immunocytochemistry, scanning electron microscopy and Gram staining, treatment of several bacterial strains and Candida albicans with A? peptide variants ending at position 42 (A?x-42) caused the formation of large agglutinates. These aggregates were not detected after incubation with A?x-40. Furthermore, A?x-42 exerted an antimicrobial activity on all tested pathogens, killing up to 80% of microorganisms within 6 h. A?1-40 only had a moderate antimicrobial activity against C. albicans. Agglutination of A?1-42 was accelerated in the presence of microorganisms. These data demonstrate that the amyloidogenic A?x-42 variants have antimicrobial activity and may therefore act as antimicrobial peptides in the immune system.
EVALuna2:7714

Analysis of Corynebacterium diphtheriae macrophage interaction: Dispensability of corynomycolic acids for inhibition of phagolysosome maturation and identification of a new gene involved in synthesis of the corynomycolic acid layer - Ott, Lisa; Hacker, Elena; Kunert, Timo; Karrington, Ian Alexander; Etschel, Philipp; Lang, Roland; Wiesmann, Veit; Wittenberg, Thomas; Singh, Albel; Varela, Cristian; Bhatt, Apoorva; Sangal, Vartul; et al. (PLoS ONE, 2017)
EVALuna2:7740

Analysis of factors contributing to variation in the C57BL/6J fecal microbiota across German animal facilities. - Günther, Claudia; Rausch, Philipp; Basic, Marijana; Batra, Arvind; Bischoff, Stephan C.; Blauth, Michael; Clavel, Thomas; Glaesner, Joachim; Gopalakrishnan, Shreya; Grassl, Guntram A.; Haller, Dirk; Hirose, Misa; et al. (International Journal of Medical Microbiology, 2016)
The intestinal microbiota is involved in many physiological processes and it is increasingly recognized that differences in community composition can influence the outcome of a variety of murine models used in biomedical research. In an effort to describe and account for the variation in intestinal microbiota composition across the animal facilities of participating members of the DFG Priority Program 1656 "Intestinal Microbiota", we performed a survey of C57BL/6J mice from 21 different mouse rooms/facilities located at 13 different institutions across Germany. Fresh feces was sampled from five mice per room/facility using standardized procedures, followed by extraction and 16S rRNA gene profiling (V1-V2 region, Illumina MiSeq) at both the DNA and RNA (reverse transcribed to cDNA) level. In order to determine the variables contributing to bacterial community differences, we collected detailed questionnaires of animal husbandry practices and incorporated this information into our analyses. We identified considerable variation in a number of descriptive aspects including the proportions of major phyla, alpha- and beta diversity, all of which displayed significant associations to specific aspects of husbandry. Salient findings include a reduction in alpha diversity with the use of irradiated chow, an increase in inter-individual variability (beta diversity) with respect to barrier access and open cages and an increase in bacterial community divergence with time since importing from a vendor. We further observe a high degree of facility-level individuality, which is likely due to each facility harboring its own unique combination of multiple varying attributes of animal husbandry. While it is important to account and control for such differences between facilities, the documentation of such diversity may also serve as a valuable future resource for investigating the origins of microbial-driven host phenotypes.
Keywords: 16S rRNA gene; C57BL/6J; Gut microbiota; Mouse husbandry

Analysis of factors contributing to variation in the C57BL/6J fecal microbiota across German animal facilities - Günther, Claudia; Rausch, Philipp; Basic, Marijana; Batra, Arvind; Bischoff, Stephan C.; Blaut, Michael; Clavel, Thomas; Gläsner, Joachim; Gopalakrishnan, Shreya; Grassl, Guntram A.; Haller, Dirk; Hirose, Misa; et al. (International Journal of Medical Microbiology, 2016)
The intestinal microbiota is involved in many physiological processes and it is increasingly recognized that differences in community composition can influence the outcome of a variety of murine models used in biomedical research. In an effort to describe and account for the variation in intestinal microbiota composition across the animal facilities of participating members of the DFG Priority Program 1656 "Intestinal Microbiota", we performed a survey of C57BL/6J mice from 21 different mouse rooms/facilities located at 13 different institutions across Germany. Fresh feces was sampled from five mice per room/facility using standardized procedures, followed by extraction and 16S rRNA gene profiling (V1-V2 region, Illumina MiSeq) at both the DNA and RNA (reverse transcribed to cDNA) level. In order to determine the variables contributing to bacterial community differences, we collected detailed questionnaires of animal husbandry practices and incorporated this information into our analyses. We identified considerable variation in a number of descriptive aspects including the proportions of major phyla, alpha- and beta diversity, all of which displayed significant associations to specific aspects of husbandry. Salient findings include a reduction in alpha diversity with the use of irradiated chow, an increase in inter-individual variability (beta diversity) with respect to barrier access and open cages and an increase in bacterial community divergence with time since importing from a vendor. We further observe a high degree of facility-level individuality, which is likely due to each facility harboring its own unique combination of multiple varying attributes of animal husbandry. While it is important to account and control for such differences between facilities, the documentation of such diversity may also serve as a valuable future resource for investigating the origins of microbial-driven host phenotypes.
Keywords: 16S rRNA gene; C57BL/6J; Gut microbiota; Mouse husbandry

Analysis of factors contributing to variation in the C57BL/6J fecal microbiota across German animal facilities - Rausch, Philipp; Basic, Marijana; Batra, Arvind; Bischoff, Stephan C.; Blaut, Michael; Clavel, Thomas; Glaesner, Joachim; Gopalakrishnan, Shreya; Grass, Guntram A.; Günther, Claudia; Haller, Dirk; Hirose, Misa; et al. (International Journal of Medical Microbiology, 2016)
The intestinal microbiota is involved in many physiological processes and it is increasingly recognized that differences in community composition can influence the outcome of a variety of murine models used in biomedical research. In an effort to describe and account for the variation in intestinal microbiota composition across the animal facilities of participating members of the DFG Priority Program 1656 "Intestinal Microbiota", we performed a survey of C57BL/6J mice from 21 different mouse rooms/facilities located at 13 different institutions across Germany. Fresh feces was sampled from five mice per room/facility using standardized procedures, followed by extraction and 16S rRNA gene profiling (V1-V2 region, Illumina MiSeq) at both the DNA and RNA (reverse transcribed to cDNA) level. In order to determine the variables contributing to bacterial community differences, we collected detailed questionnaires of animal husbandry practices and incorporated this information into our analyses. We identified considerable variation in a number of descriptive aspects including the proportions of major phyla, alpha- and beta diversity, all of which displayed significant associations to specific aspects of husbandry. Salient findings include a reduction in alpha diversity with the use of irradiated chow, an increase in inter-individual variability (beta diversity) with respect to barrier access and open cages and an increase in bacterial community divergence with time since importing from a vendor. We further observe a high degree of facility-level individuality, which is likely due to each facility harboring its own unique combination of multiple varying attributes of animal husbandry. While it is important to account and control for such differences between facilities, the documentation of such diversity may also serve as a valuable future resource for investigating the origins of microbial-driven host phenotypes.
EVALuna2:2061

Analysis of the effectiveness of hygiene measures and COVID-19 vaccination at a tertiary-care university hospital during the first two years of the SARS-CoV-2 pandemic - Niekrens, Valentin; Kunz, Bernd; Werner, Markus; Valenza, Giuseppe; Seggewies, Christof; Bogdan, Christian; Esse, Jan (Heliyon, 2024)
Objective: Assessment of the effectiveness of protective measures at a tertiary-care hospital during the SARS-CoV-2 infection waves to provide advice for future pandemics. Design: Retrospective cohort study among hospital staff using in-house surveillance data. Setting: University Hospital Erlangen (UKER), a tertiary-care provider in Bavaria, Germany. Methods: We outline the preventive measures introduced at UKER and retrospectively assess their effectiveness using anonymized monitoring data that were collected during the SARS-CoV-2 pandemic from February 2020 to the end of January 2022. Analysed data includes the incidence of SARS-CoV-2 infections among employees, the frequency of high-risk contacts with infected patients or staff members and breakthrough infections considering the context of exposure. Results: The cumulative incidence of SARS-CoV-2 infections among UKER employees was higher before, but lower after the vaccination campaign when compared to the general population. Healthcare workers (HCW), notably physicians and nurses, were especially at risk of infection compared to other UKER employees with less direct patient contact (OR 1.36 [95% CI 1.18-1.57 p < 0.001]). Breakthrough infections mostly occurred after exposure during private life, i.e. in situations without protective equipment. The frequency of high-risk contacts during direct patient care remained stable after SARS-CoV-2 vaccination. Prior to vaccination, 5.2% of HCW with direct patient care tested positive for SARS-CoV-2 within 14 days. After vaccination until the onset of the Omicron wave, conversion rate dropped to 0%. Conclusions: This study provides real-world data on the effectiveness of vaccination, contact tracing, personal protective equipment and general hygiene measures during the SARS-CoV-2 pandemic. Based on our findings, we recommend a protective approach combining all these preventive measures.
CRIS-Team Scopus Importer:2025-02-04
Keywords: BNT162b2; Breakthrough infection; Hospital hygiene; Infection prevention; Personal protective equipment; Surveillance

An anti-inflammatory eicosanoid switch mediates the suppression of type-2 inflammation by helminth larval products - de los Reyes Jiménez, Marta; Lechner, Antonie; Alessandrini, Francesca; Bohnacker, Sina; Schindela, Sonja; Trompette, Aurélien; Haimerl, Pascal; Thomas, Dominique; Henkel, Fiona; Mourão, André; Geerlof, Arie; da Costa, Clarissa Prazeres; et al. (Science Translational Medicine, 2020)
Eicosanoids are key mediators of type-2 inflammation, e.g., in allergy and asthma. Helminth products have been suggested as remedies against inflammatory diseases, but their effects on eicosanoids are unknown. Here, we show that larval products of the helminth Heligmosomoides polygyrus bakeri (HpbE), known to modulate type-2 responses, trigger a broad anti-inflammatory eicosanoid shift by suppressing the 5-lipoxygenase pathway, but inducing the cyclooxygenase (COX) pathway. In human macrophages and granulocytes, the HpbE-driven induction of the COX pathway resulted in the production of anti-inflammatory mediators [e.g., prostaglandin E2 (PGE2) and IL-10] and suppressed chemotaxis. HpbE also abrogated the chemotaxis of granulocytes from patients suffering from aspirin-exacerbated respiratory disease (AERD), a severe type-2 inflammatory condition. Intranasal treatment with HpbE extract attenuated allergic airway inflammation in mice, and intranasal transfer of HpbE-conditioned macrophages led to reduced airway eosinophilia in a COX/PGE2-dependent fashion. The induction of regulatory mediators in macrophages depended on p38 mitogen-activated protein kinase (MAPK), hypoxia-inducible factor-1α (HIF-1α), and Hpb glutamate dehydrogenase (GDH), which we identify as a major immunoregulatory protein in HpbE. Hpb GDH activity was required for anti-inflammatory effects of HpbE in macrophages, and local administration of recombinant Hpb GDH to the airways abrogated allergic airway inflammation in mice. Thus, a metabolic enzyme present in helminth larvae can suppress type-2 inflammation by inducing an anti-inflammatory eicosanoid switch, which has important implications for the therapy of allergy and asthma.
CRIS-Team Scopus Importer:2020-05-05

Anaplasma phagocytophilum Induces TLR- and MyD88-Dependent Signaling in In Vitro Generated Murine Neutrophils - Muller, Beate J.; Westheider, Arne; Birkner, Katharina; Seelig, Birte; Kirschnek, Susanne; Bogdan, Christian; Von Loewenich, Friederike D. (Frontiers in Cellular and Infection Microbiology, 2021)
Anaplasma phagocytophilum is a tick-transmitted obligate intracellular Gram-negative bacterium that replicates in neutrophils. It elicits febrile disease in humans and in animals. In a mouse model, elimination of A. phagocytophilum required CD4+ T cells, but was independent of IFN-γ and other classical antibacterial effector mechanisms. Further, mice deficient for immune recognition and signaling via Toll-like receptor (TLR) 2, TLR4 or MyD88 were unimpaired in pathogen control. In contrast, animals lacking adaptor molecules of Nod-like receptors (NLR) such as RIP2 or ASC showed delayed clearance of A. phagocytophilum. In the present study, we investigated the contribution of further pattern recognition receptor (PRR) pathways to the control of A. phagocytophilum in vivo. Mice deficient for the NLR NOD2 had elevated bacterial loads in the early phase of infection, but were unimpaired in pathogen elimination. In contrast, animals lacking adaptor proteins of different C-type lectin receptors (CLR) such as DAP12, Fc-receptor γ-chain (FcRγ) and SYK controlled A. phagocytophilum as efficiently as wild-type mice. Further, we investigated which PRR pathways are involved in the sensing of A. phagocytophilum by in vitro generated Hoxb8 murine neutrophils. In vitro, recognition of A. phagocytophilum by murine neutrophils was dependent on TLR- and MyD88 signaling. However, it remained intact in the absence of the NLR NOD1, NOD2 and NALP3 and of the CLR adaptor molecules DAP12 and FcRγ. From these results, we conclude that TLR rather than NLR or CLR are critical for the detection of A. phagocytophilum by neutrophils although in vivo defective TLR-signaling is compensated probably because of the redundancy of the immune system.
CRIS-Team Scopus Importer:2021-04-02
Keywords: Anaplasma phagocytophilum; chemokine; CLR; cytokine; iNOS; MyD88; NLR; TLR

A newly identified secreted larval antigen elicits basophil-dependent protective immunity against N. brasiliensis infection - Thuma, Natalie; Döhler, Daniela; Mielenz, Dirk; Sticht, Heinrich; Radtke, Daniel; Reimann, Lena; Warscheid, Bettina; Vöhringer, David (Frontiers in Immunology, 2022)
Hookworms infect more that 400 million people and cause significant socio-economic burden on endemic countries. The lack of efficient vaccines and the emergence of anthelminthic drug resistance are of major concern. Free-living hookworm larvae infect their hosts via the skin and live as adult worms in the small intestine where they feed on host tissue and blood. Excretory/secretory (E/S) products, released by helminths as they migrate through their host, are thought to play a key role in facilitating infection and successful establishment of parasitism. However, E/S products can also elicit protective immune responses that might be harnessed for vaccine development. By performing Western blots with serum of Nippostrongylus brasiliensis (Nb) infected mice as a model for human hookworm infection, we identified a largely overlapping set of IgG1- and IgE-reactive antigens in E/S from infective L3 stage larvae. Mass spectrometry analysis led to the identification of a new protein family with 6 paralogues in the Nb genome which we termed Nb-LSA1 for “Nippostrongylus brasiliensis larval secreted protein 1”. The recombinantly expressed 17 kDa family member Nb-LSA1a was recognized by antibodies in the serum of Nb immune mice. Immunization of mice with Nb-LSA1a in alum elicited a strong IgG1 response but no detectable antigen-specific IgE. Most importantly, immunized mice were largely protected against a challenge Nb infection. This effect was dependent on the presence of basophils and occurred before the parasites reached the intestine. Therefore, basophils appear to play a critical role for rapid control of infection with L3 stage larvae in mice immunized with a single secreted larval protein. A better understanding of basophil-mediated protective immunity and identification of potent larval antigens of human hookworms could help to develop promising vaccination strategies.
CRIS-Team Scopus Importer:2022-09-30
Keywords: basophils; CAP domain; hookworms; immunization; SCP/TAPS protein

Anhydrotetracycline-peptide conjugates as representatives for ligand-based transactivating systems - Lochner, Susanne; Einsiedel, Jürgen; Schaefer, Gesa; Berens, Christian; Hillen, Wolfgang; Gmeiner, Peter (Bioorganic & Medicinal Chemistry, 2010)
Bioconjugates of anhydrotetracycline and minimal activation sequences (VP1, VP2) derived from the Herpes simplex virus protein VP16 were synthesized. Different ligation strategies were applied and the resulting molecules tested in HeLa cells expressing the reverse transactivator rtTA-S3 for activity. The data clearly demonstrate that the atc-peptide conjugates are able to penetrate the cell membrane. Furthermore, binding to and induction of rtTA-S3 were detected. Structure-activity relationships indicated that the biological activity of the atc-peptide strongly depends on the specific linker used. The N-terminally linked oxime derivative 10 proved excellent activity when the increase of luciferace activity indicated a transcriptional activation substantially exceeding the inducing properties of anhydrotetracycline. © 2010 Elsevier Ltd. All rights reserved.

A Novel Inhibitor against the Bromodomain Protein 1 of the Malaria Pathogen Plasmodium Falciparum - Amann, Marius; Warstat, Robin; Rechten, Kay; Theuer, Philip; Schustereder, Magdalena; Clavey, Sophie; Breit, Bernhard; Einsle, Oliver; Hügle, Martin; Petter, Michaela; Günther, Stefan (ChemMedChem, 2025)
The rise of drug resistances in malaria necessitates the exploration of novel therapeutic strategies. Targeting epigenetic pathways could open new, promising treatment avenues. In this study, the focus is on the essential Bromodomain protein 1 (PfBDP1) of the malaria pathogen Plasmodium falciparum. Utilizing the pan-selective bromodomain inhibitor MPM6, a potent initial hit is identified and it is subsequently developed into a nanomolar binder. Through a combination of virtual docking, isothermal titration calorimetry, and X-ray crystallography, the molecular interactions of the new inhibitors with the bromodomain (BRD) of the protein (PfBDP1-BRD) are elucidated. The findings include the first co-crystallized inhibitors with the structures of PfBRD1-BRD as well as the bromodomain of the close homologous protein of Plasmodium vivax (PvBDP1-BRD). The structures provide new insights into their binding mechanisms. Further validation using conditional knockdown of PfBDP1 in P. falciparum demonstrates parasite sensitivity to the inhibitor, underscoring its potential in a targeted therapeutic approach against malaria.
CRIS-Team Scopus Importer:2025-04-18
Keywords: Antiprotozoal agents; bromodomain; drug discovery; inhibitors; Plasmodium

A Novel, Stress-Responsive and Clinically Predictive Humanized Mouse Model of Atopic Dermatitis: Autologous Th2-Polarized Lymphocytes Suffice to Induce Characteristic Lesions in Healthy Non-Atopic Human Skin Xenotransplants In Vivo - Satzinger, S.; Willenborg, S.; Ding, X.; Vöhringer, David; Eming, S. A. (JOURNAL OF INVESTIGATIVE DERMATOLOGY, 2022)
CRIS-Team WoS Importer:2023-03-10

A Novel Thymoma-Associated Immunodeficiency with Increased Naive T Cells and Reduced CD247 Expression - Christopoulos, Petros; Dopfer, Elaine P.; Malkovsky, Miroslav; Esser, Philipp R.; Schaefer, Hans-Eckart; Marx, Alexander; Kock, Sylvia; Rupp, Nicole; Lorenz, Myriam R.; Schwarz, Klaus; Harder, Jan; Martin, Stefan F.; et al. (Journal of Immunology, 2015)
The mechanisms underlying thymoma-associated immunodeficiency are largely unknown, and the significance of increased blood ?? ? cells often remains elusive. In this study we address these questions based on an index patient with thymoma, chronic visceral leishmaniasis, myasthenia gravis, and a marked increase of rare ?? T cell subsets in the peripheral blood. This patient showed cutaneous anergy, even though he had normal numbers of peripheral blood total lymphocytes as well as CD4(+) and CD8(+) T cells. Despite his chronic infection, analyses of immunophenotypes and spectratyping of his lymphocytes revealed an unusual accumulation of naive ?? and ?? T cells, suggesting a generalized T cell activation defect. Functional studies in vitro demonstrated substantially diminished IL-2 and IFN-? production following TCR stimulation of his "untouched" naive CD4(+) T cells. Biochemical analysis revealed that his ?? and ?? T cells carried an altered TCR complex with reduced amounts of the ?-chain (CD247). No mutations were found in the CD247 gene that encodes the homodimeric ? protein. The diminished presence of CD247 and increased numbers of ?? T cells were also observed in thymocyte populations obtained from three other thymoma patients. Thus, our findings describe a novel type of a clinically relevant acquired T cell immunodeficiency in thymoma patients that is distinct from Good's syndrome. Its characteristics are an accumulation of CD247-deficient, hyporresponsive naive ?? and ?? T cells and an increased susceptibility to infections.
EVALuna2:7674

Antiapoptotic activity of Coxiella burnetii effector protein AnkG is controlled by p32-dependent trafficking - Eckart, Rita; Bisle, Stephanie; Schulze-Luehrmann, Jan; Wittmann, Irene; Jantsch, Jonathan; Schmid, Benedikt; Berens, Christian; Lührmann, Anja (Infection and Immunity, 2014)
Intracellular bacterial pathogens frequently inhibit host cell apoptosis to ensure survival of their host, thereby allowing bacterial propagation. The obligate intracellular pathogen Coxiella burnetii displays antiapoptotic activity which depends on a functional type IV secretion system (T4SS). Accordingly, antiapoptotic T4SS effector proteins, like AnkG, have been identified. AnkG inhibits pathogen-induced apoptosis, possibly by binding to the host cell mitochondrial protein p32 (gC1qR). However, the molecular mechanism of AnkG activity remains unknown. Here, we demonstrate that ectopically expressed AnkG associates with mitochondria and traffics into the nucleus after apoptosis induction, although AnkG lacks a predicted nuclear localization signal. We identified the p32 interaction region in AnkG and constructed an AnkG mutant (AnkG) unable to bind to p32. By using this mutant, we found that intracellular localization and trafficking of AnkG into the nucleus are dependent on binding to p32. Furthermore, we demonstrated that nuclear localization of AnkG but not binding to p32 is required for apoptosis inhibition. Thus, the antiapoptotic activity of AnkG is controlled by p32-mediated intracellular trafficking, which, in turn, seems to be regulated by host cell processes that sense stress. © 2014, American Society for Microbiology.

Antibacterial Effect of a 4x Cu-TiO2 Coating Simulating Acute Periprosthetic Infection-An Animal Model - Mauerer, Andreas; Stenglein, Stefanie; Schulz-Drost, Stefan; Schoerner, Christoph; Taylor, Dominic; Krinner, Sebastian; Heidenau, Frank; Adler, Werner; Forst, Raimund (Molecules, 2017)
The purpose of our study was to investigate the antibacterial effect of a spacer (Ti6Al4V) coated with 4x Cu-TiO? in an animal model simulating an acute periprosthetic infection by Staphylococcus aureus. Ti6Al4 bolts contaminated with Staphylococcus aureus were implanted into the femoral condyle of rabbits (n = 36) divided into 3 groups. After one week in group 1 (control) the bolts were removed without any replacement. In group2 Ti6Al4V bolts with a 4x Cu-TiO? coating and in group 3 beads of a gentamicin-PMMA chain were imbedded into the borehole. Microbiological investigation was performed at the primary surgery, at the revision surgery and after scarification of the rabbits 3 weeks after the first surgery. Blood tests were conducted weekly. The initial overall infection rate was 88.9%. In group 2 and 3 a significant decrease of the infection rate was shown in contrast to the control group. The C-reactive protein (CRP) levels declined one week after the first surgery except in the control group where the CRP level even increased. This is the first in vivo study that demonstrated the antibacterial effects of a fourfold Cu-TiO? coating. For the future, the coating investigated could be a promising option in the treatment of implant-associated infections.
EVALuna2:15853

Antigen targeting of Fc receptors induces strong and functional relevant T cell responses in vivo independent of ITAM signaling but dependent on dendritic cell subsets - Lehmann, Christian; Baranska, A.; Heidkamp, Gordon Frederik; Amon, Lukas; Seeling, Michaela; Soulat, D.; Krug, A. B.; Ravetch, J. V.; Leusen, J. H. W.; Nimmerjahn, Falk; Dudziak, Diana (EUROPEAN JOURNAL OF IMMUNOLOGY, 2019)
CRIS-Team WoS Importer:2019-10-08

Antigen targeting of Fc-receptors induces strong T cell responses in vivo independent of ITAM signaling but dependent on dendritic cell subset - Lehmann, C. H. K.; Baranska, A.; Heidkamp, G. F.; Heger, L.; Neubert, K.; Lühr, Jennifer; Hoffmann, Alana; Reimer, Katharina; Brückner, Christin; Beck, S.; Seeling, M.; Kießling, Melissa; et al. (2017)
EVALuna2:33396

Antigen targeting of Fc-receptors induces strong T cell responses in vivo independent of ITAM signaling but dependent on dendritic cell subsets - Lehmann, Christian; Baranska, A.; Heidkamp, Gordon Frederik; Heger, Lukas; Neubert, K.; Lühr, Jennifer; Hoffmann, Alana; Reimer, Katharina; Brückner, Christin; Beck, S.; Seeling, Michaela; Kießling, Melissa; et al. (2017)
EVALuna2:33397

Antigen targeting of Fc-receptors induces strong T cell responses in vivo independent of ITAM signalling - Lehmann, Christian; Baranska, Anna; Heidkamp, Gordon Frederik; Kiessling, M.; Soulat, Didier; Krug, A.; Ravetch, J. V.; Leusen, J. H.; Nimmerjahn, Falk; Dudziak, Diana (JOURNAL OF INVESTIGATIVE DERMATOLOGY, 2016)
Created from Fastlane, WoS look-up

Antigen targeting of Fc-receptors induces strong T cell responses in vivo independent of ITAM signalling - Lehmann, Christian; Baranska, Anna; Heidkamp, Gordon Frederik; Kiessling, M.; Soulat, D.; Krug, A.; Ravetch, J. V.; Leusen, J. H.; Nimmerjahn, Falk; Dudziak, Diana (Journal of Investigative Dermatology, 2016)

Anti-TNF immunotherapy reduces CD8+ T cell-mediated antimicrobial activity against Mycobacterium tuberculosis in humans. - Bruns, Heiko; Bruns, Heiko; Meinken, Christoph; Schauenberg, Philipp; Haerter, Georg; Kern, Peter; Modlin, Robert L.; Antoni, Christian; Stenger, Steffen (Journal of Clinical Investigation, 2009)
The incidence of tuberculosis is increased during treatment of autoimmune diseases with anti-TNF antibodies. This is a significant clinical complication, but also provides a unique model to study immune mechanisms in human tuberculosis. Given the key role for cell-mediated immunity in host defense against Mycobacterium tuberculosis, we hypothesized that anti-TNF treatment impairs T cell-directed antimicrobial activity. Anti-TNF therapy reduced the expression in lymphocytes of perforin and granulysin, 2 components of the T cell-mediated antimicrobial response to intracellular pathogens. Specifically, M. tuberculosis-reactive CD8+CCR7-CD45RA+ effector memory T cells (TEMRA cells) expressed the highest levels of granulysin, lysed M. tuberculosis, and infected macrophages and mediated an antimicrobial activity against intracellular M. tuberculosis. Furthermore, TEMRA cells expressed cell surface TNF and bound the anti-TNF therapeutic infliximab in vitro, making them susceptible to complement-mediated lysis. Immune therapy with anti-TNF was associated with reduced numbers of CD8+ TEMRA cells and decreased antimicrobial activity against M. tuberculosis, which could be rescued by the addition of CD8+ TEMRA cells. These results suggest that anti-TNF therapy triggers a reduction of CD8+ TEMRA cells with antimicrobial activity against M. tuberculosis, providing insight into the mechanism whereby key effector T cell subsets contribute to host defense against tuberculosis.

ApiAP2 Transcription Factors in Apicomplexan Parasites - Jeninga, Myriam; Quinn, Jennifer; Petter, Michaela (Pathogens, 2019)
Apicomplexan parasites are protozoan organisms that are characterised by complex life cycles and they include medically important species, such as the malaria parasite Plasmodium and the causative agents of toxoplasmosis (Toxoplasma gondii) and cryptosporidiosis (Cryptosporidium spp.). Apicomplexan parasites can infect one or more hosts, in which they differentiate into several morphologically and metabolically distinct life cycle stages. These developmental transitions rely on changes in gene expression. In the last few years, the important roles of different members of the ApiAP2 transcription factor family in regulating life cycle transitions and other aspects of parasite biology have become apparent. Here, we review recent progress in our understanding of the different members of the ApiAP2 transcription factor family in apicomplexan parasites.
CRIS-Team WoS Importer:2019-07-30

A point mutation in the Ncr1 signal peptide impairs the development of innate lymphoid cell subsets - Almeida, Francisca F.; Tognarelli, Sara; Marcais, Antoine; Kueh, Andrew J.; Friede, Miriam E.; Liao, Yang; Willis, Simon N.; Luong, Kylie; Faure, Fabrice; Mercier, Francois E.; Galluso, Justine; Firth, Matthew; et al. (OncoImmunology, 2018)
NKp46 (CD335) is a surface receptor shared by both human and mouse natural killer (NK) cells and innate lymphoid cells (ILCs) that transduces activating signals necessary to eliminate virus-infected cells and tumors. Here, we describe a spontaneous point mutation of cysteine to arginine (C14R) in the signal peptide of the NKp46 protein in congenic Ly5.1 mice and the newly generated NCRB6C14R strain. Ly5.1C14R NK cells expressed similar levels of Ncr1 mRNA as C57BL/6, but showed impaired surface NKp46 and reduced ability to control melanoma tumors in vivo. Expression of the mutant NKp46C14R in 293T cells showed that NKp46 protein trafficking to the cell surface was compromised. Although Ly5.1C14R mice had normal number of NK cells, they showed an increased number of early maturation stage NK cells. CD49a+ILC1s were also increased but these cells lacked the expression of TRAIL. ILC3s that expressed NKp46 were not detectable and were not apparent when examined by T-bet expression. Thus, the C14R mutation reveals that NKp46 is important for NK cell and ILC differentiation, maturation and function. Significance Innate lymphoid cells (ILCs) play important roles in immune protection. Various subsets of ILCs express the activating receptor NKp46 which is capable of recognizing pathogen derived and tumor ligands and is necessary for immune protection. Here, we describe a spontaneous point mutation in the signal peptide of the NKp46 protein in congenic Ly5.1 mice which are widely used for tracking cells in vivo. This Ncr1 C14R mutation impairs NKp46 surface expression resulting in destabilization of Ncr1 and accumulation of NKp46 in the endoplasmic reticulum. Loss of stable NKp46 expression impaired the maturation of NKp46+ ILCs and altered the expression of TRAIL and T-bet in ILC1 and ILC3, respectively.
EVALuna2:36432

Application of Next-Generation Sequencing to Enterobacter Hormaechei Subspecies Analysis during a Neonatal Intensive Care Unit Outbreak - Morhart, Patrick; Gerlach, Roman; Kunz, Caroline; Held, Jürgen; Valenza, Giuseppe; Wölfle, Joachim; Reutter, Heiko Martin; Hanslik, Gregor J.; Fahlbusch, Fabian B. (Children, 2023)
Introduction: The Enterobacter cloacae complex (ECC) species are potential neonatal pathogens, and ECC strains are among the most commonly encountered Enterobacter spp. associated with nosocomial bloodstream infections. Outbreaks caused by ECC can lead to significant morbidity and mortality in susceptible neonates. At the molecular level, ECC exhibits genomic heterogeneity, with six closely related species and subspecies. Genetic variability poses a challenge in accurately identifying outbreaks by determining the clonality of ECC isolates. This difficulty is further compounded by the limitations of the commonly used molecular typing methods, such as pulsed field gel electrophoresis, which do not provide reliable accuracy in distinguishing between ECC strains and can lead to incorrect conclusions. Next-generation sequencing (NGS) offers superior resolution in determining strain relatedness. Therefore, we investigated the clinical pertinence of incorporating NGS into existing bundle measures to enhance patient management during an outbreak of ECC in a level-3 neonatal intensive care unit (NICU) in Germany. Methods: As the standard of care, all neonates on the NICU received weekly microbiological swabs (nasopharyngeal and rectal) and analysis of endotracheal secretion, where feasible. During the 2.5-month outbreak, colonisation with ECC was detected in n = 10 neonates. The phylogenetic relationship and potential antimicrobial resistance genes as well as mobile genetic elements were identified via bacterial whole-genome sequencing (WGS) using Illumina MiSeq followed by in silico data analysis. Results: Although all ECC isolates exhibited almost identical antimicrobial susceptibility patterns, the WGS data revealed the involvement of four different ECC clones. The isolates could be characterised as Enterobacter hormaechei subspecies steigerwaltii (n = 6, clonal), subsp. hoffmannii (n = 3, two clones) and subsp. oharae (n = 1). Despite the collection of environmental samples, no source of this diffuse outbreak could be identified. A new standardised operating procedure was implemented to enhance the management of neonates colonised with MRGN. This collaborative approach involved both parents and medical professionals and successfully prevented further transmission of ECC. Conclusions: Initially, it was believed that the NICU outbreak was caused by a single ECC clone due to the similarity in antibiotic resistance. However, our findings show that antibiotic susceptibility patterns can be misleading in investigating outbreaks of multi-drug-resistant ECC. In contrast, bacterial WGS accurately identified ECC at the clonal level, which significantly helped to delineate the nature of the observed outbreak.
CRIS-Team Scopus Importer:2023-11-03
Keywords: ECC; Enterobacter; MRGN; NGS; NICU; WGS

Applying an Inducible Expression System to Study Interference of Bacterial Virulence Factors with Intracellular Signaling - Berens, Christian; Bisle, Stephanie; Klingenbeck, Leonie; Lührmann, Anja (Journal of Visualized Experiments, 2015)
The technique presented here allows one to analyze at which step a target protein, or alternatively a small molecule, interacts with the components of a signaling pathway. The method is based, on the one hand, on the inducible expression of a specific protein to initiate a signaling event at a defined and predetermined step in the selected signaling cascade. Concomitant expression, on the other hand, of the gene of interest then allows the investigator to evaluate if the activity of the expressed target protein is located upstream or downstream of the initiated signaling event, depending on the readout of the signaling pathway that is obtained. Here, the apoptotic cascade was selected as a defined signaling pathway to demonstrate protocol functionality. Pathogenic bacteria, such as Coxiella burnetii, translocate effector proteins that interfere with host cell death induction in the host cell to ensure bacterial survival in the cell and to promote their dissemination in the organism. The C. burnetii effector protein CaeB effectively inhibits host cell death after induction of apoptosis with UV-light or with staurosporine. To narrow down at which step CaeB interferes with the propagation of the apoptotic signal, selected proteins with well-characterized pro-apoptotic activity were expressed transiently in a doxycycline-inducible manner. If CaeB acts upstream of these proteins, apoptosis will proceed unhindered. If CaeB acts downstream, cell death will be inhibited. The test proteins selected were Bax, which acts at the level of the mitochondria, and caspase 3, which is the major executioner protease. CaeB interferes with cell death induced by Bax expression, but not by caspase 3 expression. CaeB, thus, interacts with the apoptotic cascade between these two proteins.
EVALuna2:7695

A randomized controlled phase IIb wound healing trial of cutaneous leishmaniasis ulcers with 0.045% pharmaceutical chlorite (DAC N-055) with and without bipolar high frequency electro-cauterization versus intralesional antimony in Afghanistan - Stahl, Hans-Christian; Ahmadi, Faridullah; Schleicher, Ulrike; Sauerborn, Rainer; Bermejo, Justo Lorenzo; Amirih, Mohammed Latif; Sakhayee, Ibrahim; Bogdan, Christian; Stahl, Kurt-Wilhelm (BMC Infectious Diseases, 2014)
A previously published proof of principle phase IIa trial with 113 patients from Kabul showed that bipolar high-frequency (HF) electro-cauterization (EC) of cutaneous leishmaniasis (CL) ulcers and subsequent moist wound treatment (MWT) closed 85% of all Leishmania (L.) tropica lesions within 60 days.A three-armed phase IIb, randomized and controlled clinical trial was performed in Mazar-e-Sharif. L. tropica- or L. major-infected CL patients received intradermal sodium stibogluconate (SSG) (Group I); HF-EC followed by MWT with 0.045% DAC N-055 (Group II); or MWT with 0.045% DAC N-055 in basic crème alone (Group III). The primary outcome was complete epithelialisation before day 75 after treatment start.87 patients enrolled in the trial were randomized into group I (n = 24), II (n = 32) and III (n = 31). The per-protocol analysis of 69 (79%) patients revealed complete epithelialisation before day 75 in 15 (of 23; 65%) patients of Group I, in 23 (of 23; 100%) patients of Group II, and in 20 (of 23; 87%) patients of Group III (p = 0.004, Fisher's Exact Test). In the per-protocol analysis, wound closure times were significantly different between all regimens in a pair-wise comparison (p = 0.000039, Log-Rank (Mantel-Cox) test). In the intention-to-treat analysis wound survival times in Group II were significantly different from those in Group I (p = 0.000040, Log-Rank (Mantel-Cox) test). Re-ulcerations occurred in four (17%), three (13%) and seven (30%) patients of Group I, II or III, respectively (p = 0.312, Pearson Chi-Square Test).Treatment of CL ulcers with bipolar HF-EC followed by MWT with 0.045% DAC N-055 or with DAC N-055 alone showed shorter wound closure times than with the standard SSG therapy. The results merit further exploration in larger trials in the light of our current knowledge of in vitro and in vivo activities of chlorite. Clinicaltrials.gov ID: NCT00996463. Registered: 15th October 2009.
EVALuna2:7639

Arginase 1 functions as anti-resolvin in inflammatory bowel disease - Nuese, B.; Gänsbauer, Maximilian; Baier, J.; Mattner, Jochen; Gerlach, Roman; Wirtz, Stefan; Rauh, Manfred (EUROPEAN JOURNAL OF IMMUNOLOGY, 2022)
CRIS-Team WoS Importer:2023-01-27

Arginase 1 of myeloid cells accounts for disease chronicity in Leishmania mexicana-infected mice - Rai, Baplu; Debus, Andrea; Liang Chunguang,; Kunz, Meik; Rauh, Manfred; Bogdan, Christian; Schleicher, Ulrike (EUROPEAN JOURNAL OF IMMUNOLOGY, 2021)
CRIS-Team WoS Importer:2022-03-11

Arginase expression impedes the resolution of intestinal inflammation by altering the fecal microbiome and the metabolome - Baier, Julia; Gänsbauer, Maximilian; Giessler, Claudia; Arnold, Harald; Muske, Mercedes; Schleicher, Ulrike; Lukassen, Sören; Ekici, Arif Bülent; Rauh, Manfred; Daniel, Christoph; Hartmann, Arndt; Schmid, Benjamin; et al. (Journal of Clinical Investigation, 2020)
Arginase 1 (Arg1), which converts L-arginine into ornithine and urea, exerts pleiotropic immunoregulatory effects. However, the function of Arg1 in inflammatory bowel disease (IBD) remains poorly characterized. Here, we found that Arg1 expression correlated with the degree of inflammation in intestinal tissues from IBD patients. In mice, Arg1 was upregulated in an IL-4-/IL-13- and intestinal microbiota-dependent manner. Tie2-Cre+/-Arg1fl/fl mice lacking Arg1 in hematopoietic and endothelial cells recovered faster from experimental colitis than Arg1-expressing littermates. This correlated with decreased vessel density, compositional changes in intestinal microbiota, diminished infiltration by myeloid cells and an accumulation of intraluminal polyamines that promote epithelial healing. The pro-resolving effect of Arg1-deletion was reduced by an L-arginine-free diet, but rescued by simultaneous deletion of other L-arginine-metabolizing enzymes such as Arg2 or Nos2, demonstrating that protection from colitis requires L-arginine. Fecal microbiota transfers from Tie2-Cre+/-Arg1fl/fl mice into wild-type recipients ameliorated intestinal inflammation while transfers from wild-type littermates into Arg1-deficient mice prevented an advanced recovery from colitis. Thus, an increased availability of L-arginine as well as altered intestinal microbiota and metabolic products account for the accelerated resolution from colitis in the absence of Arg1. Consequently, the metabolism of L-arginine may serve as target for clinical intervention in IBD patients.<br

A Severe Case of Tuberculosis Radiologically and Endoscopically Mimicking Colorectal Cancer with Peritoneal Carcinomatosis - Rath, Timo; Atreya, Raja; Geissdorfer, Walter; Lang, Roland; Nägel, Andreas; Neurath, Markus (Case Reports in Gastrointestinal Medicine, 2017)
Although generally rising in incidence, intestinal tuberculosis is still rare in western countries and due to unspecific manifestations mainly as ulcerations on endoscopy, diagnosis of intestinal tuberculosis is challenging. Within this report, we describe a case of severe intestinal tuberculosis radiologically and endoscopically masquerading as colorectal cancer with peritoneal carcinomatosis. Our case exemplifies that intestinal tuberculosis needs to be considered as a differential diagnosis in patients at risk and that undelayed and sensitive diagnosis of intestinal tuberculosis is of central importance for avoiding unfavorable disease outcome.
EVALuna2:33728

A Specific Reduction in Aβ1-42 vs. a Universal Loss of Aβ Peptides in CSF Differentiates Alzheimer's Disease From Meningitis and Multiple Sclerosis - Spitzer, Philipp; Lang, Roland; Oberstein, Timo; Lewczuk, Piotr; Ermann, Natalia; Huttner, Hagen; Masouris, Ilias; Kornhuber, Johannes; Koedel, Uwe; Maler, Juan M. (Frontiers in Aging Neuroscience, 2018)
A reduced concentration of Aβ1-42 in CSF is one of the established biomarkers of Alzheimer's disease. Reduced CSF concentrations of Aβ1-42 have also been shown in multiple sclerosis, viral encephalitis and bacterial meningitis. As neuroinflammation is one of the neuropathological hallmarks of Alzheimer's disease, an infectious origin of the disease has been proposed. According to this hypothesis, amyloid pathology is a consequence of a microbial infection and the resulting immune defense. Accordingly, changes in CSF levels of amyloid-β peptides should be similar in AD and inflammatory brain diseases. Aβ1-42 and Aβ1-40 levels were measured in cerebrospinal fluid by ELISA and Western blotting in 34 patients with bacterial meningitis (n = 9), multiple sclerosis (n = 5) or Alzheimer's disease (n = 9) and in suitable controls (n = 11). Reduced concentrations of Aβ1-42 were detected in patients with bacterial meningitis, multiple sclerosis and Alzheimer's disease. However, due to a concurrent reduction in Aβ1-40 in multiple sclerosis and meningitis patients, the ratio of Aβ1-42/Aβ1-40 was reduced only in the CSF of Alzheimer's disease patients. Urea-SDS-PAGE followed by Western blotting revealed that all Aβ peptide variants are reduced in bacterial meningitis, whereas in Alzheimer's disease, only Aβ1-42 is reduced. These results have two implications. First, they confirm the discriminatory diagnostic power of the Aβ1-42/Aβ1-40 ratio. Second, the differential pattern of Aβ peptide reductions suggests that the amyloid pathology in meningitis and multiple sclerosis differs from that in AD and does not support the notion of AD as an infection-triggered immunopathology.
EVALuna2:36428

Aspergillus fumigatus Spores Are Not Able to Penetrate Silicone Breast Implant Shells - Horch, Raymund E.; Krappmann, Sven; Duemig, Michaela; Schmitz, Marweh; Kengelbach-Weigand, Annika; Schubert, Dirk W.; Kremser, Thomas; Bogdan, Christian; Ludolph, Ingo (Annals of Plastic Surgery, 2019)
Bacterial contamination is hypothesized to be one reason for the development of capsular contracture after alloplastic breast reconstruction using silicone breast implants. The role of fungal colonization or infection in this context as well as the question if microorganisms can penetrate the shell of silicone breast implants remains an unresolved question to date. Therefore, the aim of this study was to assess whether fungal spores are able to penetrate the shell of silicone implants. In an experimental in vitro setup with different arrangements of growth compartments, silicone chambers were placed in culture dishes filled with Aspergillus minimal medium or liquid culture medium. Inoculation was performed with conidia of Aspergillus fumigatus and incubated for seven days. On a daily basis, plates were inspected for conidial germination and hyphal growth. In none of the different experimental settings nutrients or hyphae of Aspergillus fumigatus were able to penetrate the silicone material.ConclusionsFungal spores and hyphae do not permeate through an intact silicone shell used in breast implants; thus, the silicone material serves as an impenetrable barrie
Keywords: Aspergillus fumigatus; penetration; silicone implants; breast

A spinal epidural abscess due to Streptobacillus moniliformis infection following a rat bite: case report - Hammer, Alexander; Wolff, Dorit; Geißdörfer, Walter; Schrey, Michael; Ziegler, Renate; Steiner, Hans-Herbert; Bogdan, Christian (Journal of Neurosurgery-Spine, 2017)
The authors describe the case of a 40-year-old man suffering from an epidural abscess in the thoracic spine due to a rarely isolated pathogen, Streptobacillus moniliformis, the causative agent of rat bite fever. Besides diffuse abdominal pain, ataxia, paresthesia, hypesthesia, and enhanced reflexes of the lower extremities, the patient suffered from a decreased sensation of bladder filling. His history was also positive for a rat bite 6 weeks earlier. Magnetic resonance imaging showed an epidural, space-occupying lesion compressing the spinal cord at the vertebral levels of T6-8. Neurosurgery revealed an epidural abscess, which was drained via laminectomy (T-7) and excision of the ligamentum flavum (T6-8). The etiological agent S. moniliformis was identified by 16S rRNA-based polymerase chain reaction and sequencing as well as by culture and mass spectrometry. Treatment with penicillin G led to complete resolution of the abscess and clinical recovery of the patient, who regained his bladder-filling sensation and free walking ability. This case demonstrates that careful attention to the patient's history is essential in suspecting unusual bacterial pathogens as the cause of an epidural abscess and initiating the optimal diagnostic procedure and antimicrobial therapy.
EVALuna2:7753

Autoantigen-specific CD4+ T cells acquire an exhausted phenotype and persist in human antigen-specific autoimmune diseases - Saggau, Carina; Bacher, Petra; Esser, Daniela; Rasa, Mahdi; Meise, Silja; Mohr, Nicola; Kohlstedt, Nora; Hutloff, Andreas; Schacht, Sarah Sophie; Dargvainiene, Justina; Martini, Gabriela Rios; Stürner, Klarissa H.; et al. (Immunity, 2024)
Pro-inflammatory autoantigen-specific CD4+ T helper (auto-Th) cells are central orchestrators of autoimmune diseases (AIDs). We aimed to characterize these cells in human AIDs with defined autoantigens by combining human leukocyte antigen (HLA)-tetramer-based and activation-based multidimensional ex vivo analyses. In aquaporin4-antibody-positive neuromyelitis optica spectrum disorder (AQP4-NMOSD) patients, auto-Th cells expressed CD154, but proliferative capacity and pro-inflammatory cytokines were strongly reduced. Instead, exhaustion-associated co-inhibitory receptors were expressed together with FOXP3, the canonical regulatory T cell (Treg) transcription factor. Auto-Th cells responded in vitro to checkpoint inhibition and provided potent B cell help. Cells with the same exhaustion-like (ThEx) phenotype were identified in soluble liver antigen (SLA)-antibody-autoimmune hepatitis and BP180-antibody-positive bullous pemphigoid, AIDs of the liver and skin, respectively. While originally described in cancer and chronic infection, our data point to T cell exhaustion as a common mechanism of adaptation to chronic (self-)stimulation across AID types and link exhausted CD4+ T cells to humoral autoimmune responses, with implications for therapeutic targeting.
CRIS-Team Scopus Importer:2024-10-18
Keywords: antigen-reactive T cell enrichment; ARTE; autoantigen-specific T cells; autoimmune disease; autoimmune hepatitis; bullous pemphigoid; CD154; CD4 T cell exhaustion; Foxp3; MOGAD; neuromyelitis optica

Automated detection and staging of malaria parasites from cytological smears using convolutional neural networks. - Davidson, Mira S; Andradi-Brown, Clare; Yahiya, Sabrina; Chmielewski, Jill; O’Donnell, Aidan J; Gurung, Pratima; Jeninga, Myriam; Prommana, Parichat; Dean, Andrew P.; Petter, Michaela; Uthaipibull, Chairat; Boyle, Michelle J; et al. (Biological Imaging, 2021)
Microscopic examination of blood smears remains the gold standard for laboratory inspection and diagnosis of malaria. Smear inspection is, however, time-consuming and dependent on trained microscopists with results varying in accuracy. We sought to develop an automated image analysis method to improve accuracy and standardization of smear inspection that retains capacity for expert confirmation and image archiving. Here, we present a machine learning method that achieves red blood cell (RBC) detection, differentiation between infected/uninfected cells, and parasite life stage categorization from unprocessed, heterogeneous smear images. Based on a pretrained Faster Region-Based Convolutional Neural Networks (R-CNN) model for RBC detection, our model performs accurately, with an average precision of 0.99 at an intersection-over-union threshold of 0.5. Application of a residual neural network-50 model to infected cells also performs accurately, with an area under the receiver operating characteristic curve of 0.98. Finally, combining our method with a regression model successfully recapitulates intraerythrocytic developmental cycle with accurate lifecycle stage categorization. Combined with a mobile-friendly web-based interface, called PlasmoCount, our method permits rapid navigation through and review of results for quality assurance. By standardizing assessment of Giemsa smears, our method markedly improves inspection reproducibility and presents a realistic route to both routine lab and future field-based automated malaria diagnosis.
EVALuna2:519458

Axonal Degeneration Is Regulated by a Transcriptional Program that Coordinates Expression of Pro- and Anti-degenerative Factors - Maor-Nof, Maya; Romi, Erez; Shalom, Hadas Sar; Ulisse, Valeria; Raanan, Calanit; Nof, Aviv; Leshkowitz, Dena; Lang, Roland; Yaron, Avraham (Neuron, 2016)
Developmental neuronal cell death and axonal elimination are controlled by transcriptional programs, of which their nature and the function of their components remain elusive. Here, we identified the dual specificity phosphatase Dusp16 as part of trophic deprivation-induced transcriptome in sensory neurons. Ablation of Dusp16 enhanced axonal degeneration in response to trophic withdrawal, suggesting that it has a protective function. Moreover, axonal skin innervation was severely reduced while neuronal elimination was increased in the Dusp16 knockout. Mechanistically, Dusp16 negatively regulates the transcription factor p53 and antagonizes the expression of the pro-degenerative factor, Puma (p53 upregulated modulator of apoptosis). Co-ablation of Puma with Dusp16 protected axons from rapid degeneration and specifically reversed axonal innervation loss early in development with no effect on neuronal deficits. Overall, these results reveal that physiological axonal elimination is regulated by a transcriptional program that integrates regressive and progressive elements and identify Dusp16 as a new axonal preserving factor.
EVALuna2:7745

Background Paper for the update of meningococcal vaccination recommendations in Germany: use of the serogroup B vaccine in persons at increased risk for meningococcal disease - Hellenbrand, Wiebke; Koch, Judith; Harder, Thomas; Bogdan, Christian; Heininger, Ulrich; Tenenbaum, Tobias; Terhardt, Martin; Vogel, Ulrich; Wichmann, Ole; Von Kries, Ruediger (Bundesgesundheitsblatt, Gesundheitsforschung, Gesundheitsschutz, 2015)
In December 2013 Bexsero® became available in Germany for vaccination against serogroup B meningococci (MenB). In August 2015 the German Standing Committee on Vaccination (STIKO) endorsed a recommendation for use of this vaccine in persons at increased risk of invasive meningococcal disease (IMD). This background paper summarizes the evidence underlying the recommendation. Bexsero® is based on surface protein antigens expressed by about 80% of circulating serogroup B meningococci in Germany. The paper reviews available data on immunogenicity and safety of Bexsero® in healthy children and adolescents; data in persons with underlying illness and on the effectiveness in preventing clinical outcomes are thus far unavailable.STIKO recommends MenB vaccination for the following persons based on an individual risk assessment: (1) Persons with congenital or acquired immune deficiency or suppression. Among these, persons with terminal complement defects and properdin deficiency, including those under eculizumab therapy, are at highest risk with reported invasive meningococcal disease (IMD) incidences up 10,000-fold higher than in the general population. Persons with asplenia were estimated to have a 20-30-fold increased risk of IMD, while the risk in individuals with other immune defects such as HIV infection or hypogammaglobulinaemia was estimated at no more than 5-10-fold higher than the background risk. (2) Laboratory staff with a risk of exposure to N. meningitidis aerosols, for whom an up to 271-fold increased risk for IMD has been reported. (3) Unvaccinated household (-like) contacts of a MenB IMD index case, who have a roughly 100-200-fold increased IMD risk in the year after the contact despite chemoprophylaxis. Because the risk is highest in the first 3 months and full protective immunity requires more than one dose (particularly in infants and toddlers), MenB vaccine should be administered as soon as possible following identification of the serogroup of the index case.
EVALuna2:7680

Background paper to the updated pneumococcal vaccination recommendation for older adults in Germany - Falkenhorst, G.; Remschmidt, C.; Harder, T.; Wichmann, O.; Glodny, S.; Hummers-Pradier, E.; Ledig, T.; Bogdan, Christian (Bundesgesundheitsblatt, Gesundheitsforschung, Gesundheitsschutz, 2016)
EVALuna2:7725

Bacterial coinfection restrains antiviral CD8 T-cell response via LPS-induced inhibitory NK cells - Straub, Tobias; Freudenberg, Marina A.; Schleicher, Ulrike; Bogdan, Christian; Gasteiger, Georg; Pircher, Hanspeter (Nature Communications, 2018)
Infection of specific pathogen-free mice with lymphocytic choriomeningitis virus (LCMV) is a widely used model to study antiviral T-cell immunity. Infections in the real world, however, are often accompanied by coinfections with unrelated pathogens. Here we show that in mice, systemic coinfection with E. coli suppresses the LCMV-specific cytotoxic T-lymphocyte (CTL) response and virus elimination in a NK cell- and TLR2/4-dependent manner. Soluble TLR4 ligand LPS also induces NK cell-mediated negative CTL regulation during LCMV infection. NK cells in LPS-treated mice suppress clonal expansion of LCMV-specific CTLs by a NKG2D- or NCR1-independent but perforin-dependent mechanism. These results suggest a TLR4-mediated immunoregulatory role of NK cells during viral-bacterial coinfections.
EVALuna2:36425

Basophil-derived amphiregulin is essential for UVB irradiation-induced immune suppression - Meulenbroeks, Chantal; Van Weelden, Huib; Schwartz, Christian; Vöhringer, David; Redegeld, Frank A. M.; Rutten, Victor P. M. G.; Willemse, Ton; Sijts, Alice J. A. M.; Zaiss, Dietmar M. W. (Journal of Investigative Dermatology, 2015)
UVB irradiation (290-320 nm) is used to treat skin diseases like psoriasis and atopic dermatitis, and is known to suppress contact hypersensitivity (CHS) reactions in mouse models. Regulatory T cells (Treg cells) have been shown to be responsible for this UVB-induced suppression of CHS. The epidermal growth factor (EGF)-like growth factor amphiregulin (AREG) engages EGFR on Treg cells and, in different disease models, it was shown that mast cell-derived AREG is essential for optimal Treg cell function in vivo. Here we determined whether AREG has a role in UVB-induced, Treg cell-mediated suppression of CHS reactions in the skin. Our data show that AREG is essential for UVB-induced CHS suppression. In contrast to the general assumption, however, mast cells were dispensable for UVB-induced immune suppression, whereas basophil-derived AREG was essential. These data reveal, to our knowledge, a previously unreported function for basophils in the homeostasis of immune responses in the skin. Basophils thus fulfill a dual function: they contribute to the initiation of effective type 2 immune responses and, by enhancing the suppressive capacity of local Treg cell populations, also to local immune regulation in the skin.
EVALuna2:25862

Basophil-mediated protection against gastrointestinal helminths requires IgE-induced cytokine secretion - Schwartz, Christian; Turqueti-Neves, Adriana; Hartmann, Susanne; Yu, Philipp; Nimmerjahn, Falk; Vöhringer, David (Proceedings of the National Academy of Sciences of the United States of America, 2014)
Basophils orchestrate protection against reinfections with gastrointestinal helminths and ticks, but the underlying mechanisms remain elusive. We investigated the role of Fc receptors on basophils, the antibody isotypes IgG1 and IgE, and basophil-derived IL-4/IL-13 during challenge infections with Heligmosomoides polygyrus and Nippostrongylus brasiliensis. Using mixed bone marrow chimeras, we found that activating Fc receptors on basophils were required for protective immunity but not for regulation of basophil homeostasis. Furthermore, rapid worm expulsion was impaired in IgE-deficient but not in IgG1-deficient mice. Basophils promoted the recruitment of other effector cells into the small intestine and induced expression of the antihelminthic proteins resistin-like molecule ? and mucin 5ac. Selective deletion of IL-4/IL-13 in basophils resulted in impaired worm expulsion. Collectively, our results indicate that IgE-mediated activation of basophils and the release of basophil-derived IL-4/IL-13 are critical steps in protective immunity against helminths. Therefore, development of effective vaccines against helminths should consider boosting the IL-4/IgE/basophil axis of the immune system.
EVALuna2:25872

Basophils Are Dispensable for the Control of a Filarial Infection - Hartmann, Wiebke; Linnemann, Lara Christine; Reitz, Martina; Specht, Sabine; Vöhringer, David; Breloer, Minka (ImmunoHorizons, 2018)
Basophils are innate effector cells that contribute to allergic reactions and provide protection against parasites. Using basophil-deficient Mcpt8-cre mice, we have previously shown that these granulocytes contributed to the immune mediated early control of the gastrointestinal helminth Strongyloides ratti in mice. In this study, we analyze the impact of basophils on the immune response and defense against the tissue-dwelling filarial helminth parasite Litomosoides sigmodontis Although basophils and IgE increased at the site of infection, the absence of basophils did not change the outcome of L. sigmodontis infection. Worm burden in the thoracic cavity and microfilaremiae in the peripheral blood were alike in L. sigmodontis-infected Mcpt8-cre mice compared with Mcpt8 wild type littermates during the entire course of infection. Analysis of the cytokine and Ab response to L. sigmodontis revealed no consistent alterations in the absence of basophils. Furthermore, basophil-deficient and -competent mice were protected to the same extent during a secondary infection with L. sigmodontis In summary, our findings suggest that basophils are dispensable for the initiation of the appropriate immune response and host defense against Lsigmodontis infection in mice.
EVALuna2:184197

Basophils are dispensable for the establishment of protective adaptive immunity against primary and challenge infection with the intestinal helminth parasite Strongyloides ratti - Reitz, Martina; Brunn, Marie-Luise; Vöhringer, David; Breloer, Minka (Plos Neglected Tropical Diseases, 2018)
Infections with helminth parasites are controlled by a concerted action of innate and adaptive effector cells in the frame of a type 2 immune response. Basophils are innate effector cells that may also contribute to the initiation and amplification of adaptive immune responses. Here, we use constitutively basophil-deficient Mcpt8-Cre mice to analyze the impact of basophils during initiation and execution of the protective type 2 responses to both, a primary infection and a challenge infection of immune mice with the helminth parasite Strongyloides ratti. Basophil numbers expanded during parasite infection in blood and mesenteric lymph nodes. Basophil deficiency significantly elevated intestinal parasite numbers and fecal release of eggs and larvae during a primary infection. However, basophils were neither required for the initiation of a S. ratti-specific cellular and humoral type 2 immune response nor for the efficient protection against a challenge infection. Production of Th2 cytokines, IgG1 and IgE as well as mast cell activation were not reduced in basophil-deficient Mcpt8-Cre mice compared to basophil-competent Mcpt8-WT littermates. In addition, a challenge infection of immune basophil-deficient and WT mice resulted in a comparable reduction of tissue migrating larvae, parasites in the intestine and fecal release of eggs and L1 compared to mice infected for the first time. We have shown previously that S. ratti infection induced expansion of Foxp3+ regulatory T cells that interfered with efficient parasite expulsion. Here we show that depletion of regulatory T cells reduced intestinal parasite burden also in absence of basophils. Thus basophils were not targeted specifically by S. ratti-mediated immune evasive mechanisms. Our collective data rather suggests that basophils are non-redundant innate effector cells during murine Strongyloides infections that contribute to the early control of intestinal parasite burden.
EVALuna2:36388

Basophils are dispensable for the recovery of gross locomotion after spinal cord hemisection injury - Geurts, Nathalie; Vangansewinkel, Tim; Lemmens, Stefanie; Nelissen, Sofie; Geboes, Lies; Schwartz, Christian; Vöhringer, David; Hendrix, Sven (Journal of Leukocyte Biology, 2015)
Basophils are the smallest population of granulocytes found in the circulation. They have crucial and nonredundant roles in allergic disorders, in protection from parasite infections, in autoimmunity, and in the regulation of type 2 immunity. They share phenotypic and functional properties with mast cells, which exert substantial protective effects after traumatic brain injury and spinal cord injury, although they are considered one of the most proinflammatory cell types in the body. In contrast, the in vivo functions of basophils in central nervous system trauma are still obscure and not well studied. In this study, we show that by comparing spinal cord injury in wild type vs. basophil-deficient Mcpt8Cre transgenic mice, the locomotor recovery is not affected in mice depleted in basophils. In addition, no substantial differences were observed in the lesion size and in the astrocytic and macrophage/microglia reaction between both mouse strains. Hence, despite the multiple properties shared with mast cells, these data show, for the first time, to our knowledge, that basophils are dispensable for the functional recovery process after hemisection injury to the spinal cord in mice.
EVALuna2:25876

Basophils balance healing after myocardial infarction via IL-4/IL-13 - Sicklinger, Florian; Meyer, Ingmar Sören; Li, Xue; Radtke, Daniel; Dicks, Severin; Kornadt, Moritz P.; Mertens, Christina; Meier, Julia K.; Lavine, Kory J.; Zhang, Yunhang; Kuhn, Tim Christian; Terzer, Tobias; et al. (Journal of Clinical Investigation, 2021)
The inflammatory response after myocardial infarction (MI) is a precisely regulated process that greatly affects subsequent remodeling. Here, we show that basophil granulocytes infiltrated infarcted murine hearts, with a peak occurring between days 3 and 7. Antibody-mediated and genetic depletion of basophils deteriorated cardiac function and resulted in enhanced scar thinning after MI. Mechanistically, we found that basophil depletion was associated with a shift from reparative Ly6Clo macrophages toward increased numbers of inflammatory Ly6Chi monocytes in the infarcted myocardium. Restoration of basophils in basophil-deficient mice by adoptive transfer reversed this proinflammatory phenotype. Cellular alterations in the absence of basophils were accompanied by lower cardiac levels of IL-4 and IL-13, two major cytokines secreted by basophils. Mice with basophil-specific IL-4/IL-13 deficiency exhibited a similarly altered myeloid response with an increased fraction of Ly6Chi monocytes and aggravated cardiac function after MI. In contrast, IL-4 induction in basophils via administration of the glycoprotein IPSE/α-1 led to improved post-MI healing. These results in mice were corroborated by the finding that initially low counts of blood basophils in patients with acute MI were associated with a worse cardiac outcome after 1 year, characterized by a larger scar size. In conclusion, we show that basophils promoted tissue repair after MI by increasing cardiac IL-4 and IL-13 levels.
CRIS-Team Scopus Importer:2021-07-16

Basophils: important emerging players in allergic and anti-parasite responses. - Schwartz, Christian; Vöhringer, David (Bioessays, 2011)

Basophils: important emerging players in allergic and anti-parasite responses. - Vöhringer, David; et al. (Bioessays, 2011)
UnivIS-Import:2015-04-14:Pub.2011.med.IKMI.pifto.basoph
Keywords: Allergy; Basophils; Helminth; Th2 cells

Basophils in allergic immune responses. - Vöhringer, David (Current Opinion in Immunology, 2011)
Basophils are rare effector cells of the innate immune system. They are generally associated with type 2 immune responses that develop during helminth infections and allergic reactions. The role of basophils for initiation and execution of allergic immune responses is not well understood. Over the past few years new tools have been generated to study the function of basophils in mouse models. Depending on the experimental systems used conflicting results were obtained with regard to the role of basophils for initiation and execution of immune responses against allergens and helminths. This review highlights the current knowledge about basophil in vivo functions with a focus on the role of basophils for allergic responses like asthma, allergic skin diseases and anaphylaxis. © 2011 Elsevier Ltd.
UnivIS-Import:2015-03-09:Pub.2011.med.IKMI.pifto.basoph_9

Basophils in immune responses against helminths. - Vöhringer, David (Microbes and Infection, 2011)
Basophils are a major source of IL-4 and IL-13, two key cytokines that orchestrate expulsion of gastrointestinal nematodes in different mouse models. Based on recent reports, this review discusses potential roles of basophils and other cells during early and late phases of the immune response against parasitic worms. © 2011 Institut Pasteur.
UnivIS-Import:2015-03-09:Pub.2011.med.IKMI.pifto.basoph_3
Keywords: Basophils; Helminths; IL-4/IL-13; Th2 cells

Basophils in inflammation - Schwartz, Christian; Eberle, Jörg; Vöhringer, David (European Journal of Pharmacology, 2015)
Basophils are functionally closely related to mast cells. Both cell types express the high-affinity IgE receptor (Fc?RI) and rapidly release preformed mediator from intracellular stores upon IgE-mediated activation. However, in contrast to mast cells basophils finish their maturation in the bone marrow and have a lifespan of only 2-3 days. Basophil numbers increase in response to IL-3 or TSLP and migrate into tissues to promote type 2 immune responses. Here we review recent advances regarding the pro- and anti-inflammatory functions of basophils in murine models and human allergic inflammation of the skin, lung and intestine.
EVALuna2:25875

B cell fate mapping reveals their contribution to the memory immune response against helminths - Haase, Paul; Schäfer, Simon; Gerlach, Roman; Winkler, Thomas; Vöhringer, David (Frontiers in Immunology, 2022)
An estimated quarter of the human world population is infected with gastrointestinal helminths causing major socioeconomic problems in endemic countries. A better understanding of humoral immune responses against helminths is urgently needed to develop effective vaccination strategies. Here, we used a fate mapping (FM) approach to mark germinal center (GC) B cells and their developmental fates by induced expression of a fluorescent protein during infection of mice with the helminth Nippostrongylus brasiliensis. We could show that FM+ cells persist weeks after clearance of the primary infection mainly as CD80+CD73+PD-L2+ memory B cells. A secondary infection elicited expansion of helminth-specific memory B cells and plasma cells (PCs). Adoptive transfers and analysis of somatic mutations in immunoglobulin genes further revealed that FM+ B cells rapidly convert to PCs rather than participating again in a GC reaction. These results provide new insights in the population dynamics of the humoral immune response against helminths.
CRIS-Team Scopus Importer:2022-12-16
Keywords: fate mapping; germinal center; helminths; memory responses; plasma cells

B-cell-intrinsic STAT6 signaling controls germinal center formation - Turqueti-Neves, Adriana; Otte, Manuel; Da Costa, Olivia Prazeres; Hoepken, Uta E.; Lipp, Martin; Buch, Thorsten; Vöhringer, David (European Journal of Immunology, 2014)
Infection with helminths and exposure to antigens induce a strong type 2 immune response resulting in the secretion of the cytokines IL-4 and IL-13 by CD4(+) T cells and several innate cell types. IL-4 and IL-13 promote class switch recombination to IgG1 and IgE while their role for germinal center (GC) formation is poorly understood. We found a dramatic reduction in the numbers of GC B cells when investigating different type 2 immune responses in IL-4/IL-13-deficient mice. IL-4/IL-13 from T cells located outside B-cell follicles was sufficient for GC formation. We further revealed that IL-4/IL-13 acts directly on B cells for the formation of a robust GC response. The frequency of apoptotic GC B cells was not altered in the absence of IL-4/IL-13 and proliferation was even enhanced. However, deficiency of signal transducer and activator of transcription 6 signaling in B cells resulted in failure to downregulate the chemotactic receptor Gpr183 (Ebi2) and downregulation of this receptor has been shown to be essential for proper GC B-cell differentiation. Thus, T-cell-derived extrafollicular IL-4/IL-13 and signal transducer and activator of transcription 6-regulated genes in B cells play a critical role for orchestration of the GC response in type 2 immunity.
EVALuna2:25869

B cell repertoire analysis identifies new antigenic domains on glycoprotein B of human cytomegalovirus which are target of neutralizing antibodies - Pötzsch, Sonja; Spindler, Nadja; Wiegers, Anna-Katharina; Fisch, Tanja; Ruecker, Pia; Sticht, Heinrich; Grieb, Nina; Baroti, Tina; Weisel, Florian; Stamminger, Thomas; Martin-Parras, Luis; Mach, Michael; et al. (PLoS Pathogens, 2011)
Human cytomegalovirus (HCMV), a herpesvirus, is a ubiquitously distributed pathogen that causes severe disease in immunosuppressed patients and infected newborns. Efforts are underway to prepare effective subunit vaccines and therapies including antiviral antibodies. However, current vaccine efforts are hampered by the lack of information on protective immune responses against HCMV. Characterizing the B-cell response in healthy infected individuals could aid in the design of optimal vaccines and therapeutic antibodies. To address this problem, we determined, for the first time, the B-cell repertoire against glycoprotein B (gB) of HCMV in different healthy HCMV seropositive individuals in an unbiased fashion. HCMV gB represents a dominant viral antigenic determinant for induction of neutralizing antibodies during infection and is also a component in several experimental HCMV vaccines currently being tested in humans. Our findings have revealed that the vast majority (>90%) of gB-specific antibodies secreted from B-cell clones do not have virus neutralizing activity. Most neutralizing antibodies were found to bind to epitopes not located within the previously characterized antigenic domains (AD) of gB. To map the target structures of these neutralizing antibodies, we generated a 3D model of HCMV gB and used it to identify surface exposed protein domains. Two protein domains were found to be targeted by the majority of neutralizing antibodies. Domain I, located between amino acids (aa) 133-343 of gB and domain II, a discontinuous domain, built from residues 121-132 and 344-438. Analysis of a larger panel of human sera from HCMV seropositive individuals revealed positivity rates of >50% against domain I and >90% against domain II, respectively. In accordance with previous nomenclature the domains were designated AD-4 (Dom II) and AD-5 (Dom I), respectively. Collectively, these data will contribute to optimal vaccine design and development of antibodies effective in passive immunization. © 2011 Pötzsch et al.
EVALuna2:8099

B Cells Producing Type I Interferon Modulate Macrophage Polarization in Tuberculosis - Benard, Alan; Sakwa, Imme; Schierloh, Pablo; Colom, Andre; Mercier, Ingrid; Tailleux, Ludovic; Jouneau, Luc; Boudinot, Pierre; Al-Saati, Talal; Lang, Roland; Rehwinkel, Jan; Loxton, Andre G.; et al. (American Journal of Respiratory and Critical Care Medicine, 2017)
RATIONALE: In addition to their well-known function as antibody-producing cells, B lymphocytes can markedly influence the course of infectious or non-infectious diseases via antibody-independent mechanisms. In tuberculosis, B cells accumulate in lungs, yet their functional contribution to the host response remains poorly understood. OBJECTIVES: To document the role of B cells in tuberculosis in an unbiased manner. METHODS: We generated the transcriptome of B cells isolated from Mycobacterium tuberculosis (Mtb)-infected mice, and validated the identified key pathways using in vitro and in vivo assays. The obtained data were substantiated using B cells from pleural effusion of tuberculosis patients. MEASUREMENTS AND MAIN RESULTS: B cells isolated from Mtb-infected mice displayed a STAT1-centered signature, suggesting a role for interferons in B cell response to infection. B cells stimulated in vitro with Mtb produced type I interferon, via a mechanism involving the innate sensor STING, and antagonized by MyD88 signaling. In vivo, B cells expressed type I interferon in the lungs of Mtb-infected mice and, of clinical relevance, in pleural fluid from patients with tuberculosis. Type I interferon expression by B cells induced an altered polarization of macrophages towards a regulatory/anti-inflammatory profile in vitro. In vivo, increased provision of type I interferon by B cells in a murine model of B cell-restricted Myd88-deficiency correlated with an enhanced accumulation of regulatory/anti-inflammatory macrophages in Mtb infected lungs. CONCLUSION: Type I interferon produced by Mtb-stimulated B cells favors macrophage polarization towards a regulatory/anti-inflammatory phenotype during Mtb infection.
EVALuna2:33729

Beginning to Understand the Role of the Type IV Secretion System Effector Proteins in Coxiella burnetii Pathogenesis - Lührmann, Anja; Newton, Hayley J.; Bonazzi, Matteo (Current Topics in Microbiology and Immunology, 2017)
Coxiella burnetii is the etiological agent of the zoonotic disease Q fever, which manifests in severe outbreaks and is associated with important health and economic burden. Moreover, C. burnetii belongs to the list of class B bioterrorism organisms, as it is an airborne and highly infective pathogen with remarkable resistance to environmental stresses. Detailed study of the host-pathogen interaction during C. burnetii infection has been hampered due to the obligate intracellular nature of this pathogen. However, the development of an axenic culture medium, together with the implementation of bioinformatics tools and high-content screening approaches, have significantly progressed C. burnetii research in the last decade. This has facilitated identification of the Dot/Icm type IV secretion system (T4SS) as an essential virulence factor. T4SS is used to deliver an arsenal of effector proteins into the cytoplasm of the host cell. These effectors mediate the survival of the host cell and the development of very large replicative compartments called Coxiella-containing vacuoles (CCVs). Biogenesis of the CCV relies on T4SS-dependent re-routing of numerous intracellular trafficking pathways to deliver membranes and nutrients that are essential for bacterial replication. This review aims to illustrate the key milestones that have contributed to ascribe C. burnetii as a model organism for the study of host/pathogen interactions as well as presenting an up-to-date description of our knowledge of the cell biology of C. burnetii infections.
EVALuna2:34142

Bile acids and microbiota: Multifaceted and versatile regulators of the liver–gut axis - Grüner, Niklas; Mattner, Jochen (International Journal of Molecular Sciences, 2021)
After their synthesis from cholesterol in hepatic tissues, bile acids (BAs) are secreted into the intestinal lumen. Most BAs are subsequently re-absorbed in the terminal ileum and are trans-ported back for recycling to the liver. Some of them, however, reach the colon and change their physicochemical properties upon modification by gut bacteria, and vice versa, BAs also shape the composition and function of the intestinal microbiota. This mutual interplay of both BAs and gut microbiota regulates many physiological processes, including the lipid, carbohydrate and energy metabolism of the host. Emerging evidence also implies an important role of this enterohepatic BA circuit in shaping mucosal colonization resistance as well as local and distant immune responses, tissue physiology and carcinogenesis. Subsequently, disrupted interactions of gut bacteria and BAs are associated with many disorders as diverse as Clostridioides difficile or Salmonella Typhimurium infection, inflammatory bowel disease, type 1 diabetes, asthma, metabolic syndrome, obesity, Par-kinson’s disease, schizophrenia and epilepsy. As we cannot address all of these interesting under-lying pathophysiologic mechanisms here, we summarize the current knowledge about the physio-logic and pathogenic interplay of local site microbiota and the enterohepatic BA metabolism using a few selected examples of liver and gut diseases.
CRIS-Team Scopus Importer:2021-02-05
Keywords: Bile acids; Enterohepatic recirculation; Host–microbe interactions; Intestinal microbiota; Microbial metabolism

Biomimetic Magnetic Particles for the Removal of Gram-Positive Bacteria and Lipoteichoic Acid. - Friedrich, Bernhard; Eichermüller, Julia; Bogdan, Christian; Cunningham, Sarah; Hackstein, Holger; Strauss, Richard; Alexiou, Christoph; Lyer, Stefan; Tietze, Rainer (Pharmaceutics, 2022)
Gram+ bacteria are very common in clinical medicine and responsible for a large number of infectious diseases. For example, Gram+ bacteria play a major role in causing bloodstream infections and sepsis. Therefore, the detection of Gram+ bacteria is of great importance for the diagnosis and treatment of infectious diseases. Furthermore, these bacteria are often present in biofilms that cover implants. Recent research work has mainly focused on the biologic activity and removal of Gram-negative bacteria or bacterial components such as lipopolysaccharides (LPS). In contrast, the effects of lipoteichoic acid (LTA) have been less well studied so the relevance of their removal from body fluids is possibly underestimated. To address this topic, we evaluated superparamagnetic iron oxide particles (SPION) carrying different peptides derived from the innate immune receptor (GP-340) for their ability to bind and remove Gram+ bacteria and LTA from different media. Our results show that, beyond S. aureus, effective agglutinating and removing of S. pneumoniae was possible. Furthermore, we were able to show for the first time that this was possible with LTA alone and that the magnetic removal of bacteria was also efficient under flow conditions. We also found that this method was able to capture Stapyhylococcus aureus from platelet concentrates, which can help to enhance the sensitivity of microbiological diagnostics, quality control measures, and blood product safety.
EVALuna2:508460

Blockade of the CD47/SIRPα checkpoint axis potentiates the macrophage-mediated antitumor efficacy of tafasitamab. - Biedermann, Alexander; Patra-Kneuer, Maria; Mougiakakos, Dimitrios; Büttner-Herold, Maike; Mangelberger-Eberl, Doris; Berges, Johannes; Kellner, Christian; Altmeyer, Sarah; Bittenbring, Jörg Thomas; Augsberger, Christian; Ilieva-Babinsky, Kristina; Haskamp, Stefan; et al. (Haematologica, 2024)
Macrophages are one of the key mediators of the therapeutic effects exerted by monoclonal antibodies, such as the anti-CD19 antibody tafasitamab, approved in combination with lenalidomide for the treatment of relapsed or refractory diffuse large B-cell lymphoma (DLBCL). However, antibody-dependent cellular phagocytosis (ADCP) in the tumor microenvironment can be counteracted by increased expression of the inhibitory receptor SIRPα on macrophages and its ligand, the immune checkpoint molecule CD47, on tumor cells. The aim of this study was to investigate the impact of the CD47-SIRPα axis on tafasitamab- mediated phagocytosis and explore the potential of anti-CD47 blockade to enhance its antitumor activity. Elevated expression of both SIRPα and CD47 was observed in DLBCL patient-derived lymph node biopsies compared to healthy control lymph nodes. CRISPR-mediated CD47 overexpression affected tafasitamab-mediated ADCP in vitro and increased expression of SIRPα on macrophages correlated with decreased ADCP activity of tafasitamab against DLBCL cell lines. A combination of tafasitamab and an anti-CD47 blocking antibody enhanced ADCP activity of in vitro-generated macrophages. Importantly, tafasitamab-mediated phagocytosis was elevated in combination with CD47 blockade using primary DLBCL cells and patient-derived lymphoma-associated macrophages in an autologous setting. Furthermore, lymphoma cells with low CD19 expression were efficiently eliminated by the combination treatment. Finally, combined treatment of tafasitamab and an anti-CD47 antibody resulted in enhanced tumor volume reduction and survival benefit in lymphoma xenograft mouse models. These findings provide evidence that CD47 blockade can enhance the phagocytic potential of tumor-targeting immunotherapies such as tafasitamab and suggest that there is value in exploring the combination in the clinic.
EVALuna2:569373

Bovine blood derived macrophages are unable to control Coxiella burnetii replication under hypoxic conditions - Mauermeir, Michael; Ölke, Martha; Hayek, Inaya; Schulze-Lührmann, Jan; Dettmer, Katja; Oefner, Peter J.; Berens, Christian; Menge, Christian; Lührmann, Anja (Frontiers in Immunology, 2023)
Background: Coxiella burnetii is a zoonotic pathogen, infecting humans, livestock, pets, birds and ticks. Domestic ruminants such as cattle, sheep, and goats are the main reservoir and major cause of human infection. Infected ruminants are usually asymptomatic, while in humans infection can cause significant disease. Human and bovine macrophages differ in their permissiveness for C. burnetii strains from different host species and of various genotypes and their subsequent host cell response, but the underlying mechanism(s) at the cellular level are unknown. Methods: C. burnetii infected primary human and bovine macrophages under normoxic and hypoxic conditions were analyzed for (i) bacterial replication by CFU counts and immunofluorescence; (ii) immune regulators by westernblot and qRT-PCR; cytokines by ELISA; and metabolites by gas chromatography-mass spectrometry (GC-MS). Results: Here, we confirmed that peripheral blood-derived human macrophages prevent C. burnetii replication under oxygen-limiting conditions. In contrast, oxygen content had no influence on C. burnetii replication in bovine peripheral blood-derived macrophages. In hypoxic infected bovine macrophages, STAT3 is activated, even though HIF1α is stabilized, which otherwise prevents STAT3 activation in human macrophages. In addition, the TNFα mRNA level is higher in hypoxic than normoxic human macrophages, which correlates with increased secretion of TNFα and control of C. burnetii replication. In contrast, oxygen limitation does not impact TNFα mRNA levels in C. burnetii-infected bovine macrophages and secretion of TNFα is blocked. As TNFα is also involved in the control of C. burnetii replication in bovine macrophages, this cytokine is important for cell autonomous control and its absence is partially responsible for the ability of C. burnetii to replicate in hypoxic bovine macrophages. Further unveiling the molecular basis of macrophage-mediated control of C. burnetii replication might be the first step towards the development of host directed intervention measures to mitigate the health burden of this zoonotic agent.
CRIS-Team Scopus Importer:2023-02-24
Keywords: bovine macrophages; citrate; Coxiella burnetii; HIF1α; hypoxia; normoxia; STAT3; TNF

Break on through: The role of innate immunity and barrier defence in atopic dermatitis and psoriasis - Hawerkamp, Heike C.; Caoimhe, Fahy; Fallon, Padraic G.; Schwartz, Christian (Skin Health and Disease, 2022)
The human skin can be affected by a multitude of diseases including inflammatory conditions such as atopic dermatitis and psoriasis. Here, we describe how skin barrier integrity and immunity become dysregulated during these two most common inflammatory skin conditions. We summarise recent advances made in the field of the skin innate immune system and its interaction with adaptive immunity. We review gene variants associated with atopic dermatitis and psoriasis that affect innate immune mechanisms and skin barrier integrity. Finally, we discuss how current and future therapies may affect innate immune responses and skin barrier integrity in a generalized or more targeted approach in order to ameliorate disease in patients.<br

Brucella abortus down-regulates MHC class II by the IL-6-dependent inhibition of CIITA through the downmodulation of IFN regulatory factor-1 (IRF-1) - Velasquez, Lis N.; Milillo, M. Ayelen; Delpino, M. Victoria; Trotta, Aldana; Fernandez, Pablo; Pozner, Roberto G.; Lang, Roland; Balboa, Luciana; Giambartolomei, Guillermo H.; Barrionuevo, Paula (Journal of Leukocyte Biology, 2017)
Brucella abortus is an intracellular pathogen capable of surviving inside of macrophages. The success of B. abortus as a chronic pathogen relies on its ability to orchestrate different strategies to evade the adaptive CD4(+) T cell responses that it elicits. Previously, we demonstrated that B. abortus inhibits the IFN-?-induced surface expression of MHC class II (MHC-II) molecules on human monocytes, and this phenomenon correlated with a reduction in antigen presentation. However, the molecular mechanisms, whereby B. abortus is able to down-regulate the expression of MHC-II, remained to be elucidated. In this study, we demonstrated that B. abortus infection inhibits the IFN-?-induced transcription of MHC-II, transactivator (CIITA) and MHC-II genes. Accordingly, we observed that the synthesis of MHC-II proteins was also diminished. B. abortus was not only able to reduce the expression of mature MHC-II, but it also inhibited the expression of invariant chain (Ii)-associated immature MHC-II molecules. Outer membrane protein 19 (Omp19), a prototypical B. abortus lipoprotein, diminished the expression of MHC-II and CIITA transcripts to the same extent as B. abortus infection. IL-6 contributes to these down-regulatory phenomena. In addition, B. abortus and its lipoproteins, through IL-6 secretion, induced the transcription of the negative regulators of IFN-? signaling, suppressor of cytokine signaling (SOCS)-1 and -3, without interfering with STAT1 activation. Yet, B. abortus lipoproteins via IL-6 inhibit the expression of IFN regulatory factor 1 (IRF-1), a critical regulatory transcription factor for CIITA induction. Overall, these results indicate that B. abortus inhibits the expression of MHC-II molecules at very early points in their synthesis and in this way, may prevent recognition by T cells establishing a chronic infection.
EVALuna2:7719

Butyrophilin 2a2 (Btn2a2) expression on thymic epithelial cells promotes central T cell tolerance and prevents autoimmune disease: Btn2a2 promotes central tolerance - Frech, Michael; Danzer, Heike; Uchil, Pooja; Azizov, Vugar; Schmid, Eva; Schälter, Fabian; Dürholz, Kerstin; Mauro, Daniele; Rauber, Simon; Munoz Becerra, Luis; Taher, Leila; Ciccia, Francesco; et al. (Journal of Autoimmunity, 2023)
Butyrophilins are surface receptors belonging to the immunoglobulin superfamily. While several members of the butyrophilin family have been implicated in the development of unconventional T cells, butyrophilin 2a2 (Btn2a2) has been shown to inhibit conventional T cell activation. Here, we demonstrate that in steady state, the primary source of Btn2a2 are thymic epithelial cells (TEC). Absence of Btn2a2 alters thymic T cell maturation and bypasses central tolerance mechanisms. Furthermore, Btn2a2−/− mice develop spontaneous autoimmunity resembling human primary Sjögren's Syndrome (pSS), including formation of tertiary lymphoid structures (TLS) in target organs. Ligation of Btn2a2 on developing thymocytes is associated with reduced TCR signaling and CD5 levels, while absence of Btn2a2 results in increased TCR signaling and CD5 levels. These results define a novel role for Btn2a2 in promoting central tolerance by modulating TCR signaling strength and indicate a potential mechanism of pSS development.
CRIS-Team Scopus Importer:2023-07-07
Keywords: Autoimmune disease; Autoimmunity; Butyrophilin 2a2 (Btn2a2); Central tolerance; Primary sjögren's syndrome (pSS); Thymic epithelial cells (TEC)

Can Perfusion-Based Brain Tissue Oxygenation MRI Support the Understanding of Cerebral Abscesses In Vivo? - Knott, Michael; Hölter, Philip; Soder, Liam; Schlaffer, Sven-Martin; Hoffmanns, Sophia; Lang, Roland; Dörfler, Arnd; Schmidt, Manuel (Diagnostics, 2023)
Purpose: The clinical condition of a brain abscess is a potentially life-threatening disease. The combination of MRI-based imaging, surgical therapy and microbiological analysis is critical for the treatment and convalescence of the individual patient. The aim of this study was to evaluate brain tissue oxygenation measured with dynamic susceptibility contrast perfusion weighted imaging (DSC-PWI) in patients with brain abscess and its potential benefit for a better understanding of the environment in and around brain abscesses. Methods: Using a local database, 34 patients (with 45 abscesses) with brain abscesses treated between January 2013 and March 2021 were retrospectively included in this study. DSC-PWI imaging and microbiological work-up were key inclusion criteria. These data were analysed regarding a correlation between DSC-PWI and microbiological result by quantifying brain tissue oxygenation in the abscess itself, the abscess capsula and the surrounding oedema and by using six different parameters (CBF, CBV, CMRO2, COV, CTH and OEF). Results: Relative cerebral blood flow (0.335 [0.18–0.613] vs. 0.81 [0.49–1.08], p = 0.015), relative cerebral blood volume (0.44 [0.203–0.72] vs. 0.87 [0.67–1.2], p = 0.018) and regional cerebral metabolic rate for oxygen (0.37 [0.208–0.695] vs. 0.82 [0.55–1.19], p = 0.022) were significantly lower in the oedema around abscesses without microbiological evidence of a specific bacteria in comparison with microbiological positive lesions. Conclusions: The results of this study indicate a relationship between brain tissue oxygenation status in DSC-PWI and microbiological/inflammatory status. These results may help to better understand the in vivo environment of brain abscesses and support future therapeutic decisions.
CRIS-Team Scopus Importer:2023-11-24
Keywords: brain abscess; brain tissue oxygenation; DSC-PWI

Case report: Cutaneous pseudolymphoma caused by a Leishmania infantum infection in a patient treated with anti-TNF antibody for plaque psoriasis - Scholl, Sarah; Schuster, Daniel; Technau-Hafsi, Kristin; Stete, Katarina; Rieg, Siegbert; May, Annette M.; Bogdan, Christian; Schauer, Franziska (Frontiers in Medicine, 2022)
For psoriasis, which affects up to 2% of the population and adalimumab is approved from the age of 4 years. Here, we present a middle-aged Italian man with long-term history of plaque psoriasis and psoriasis arthropathica and adalimumab therapy. He developed ulcers or nodules within the psoriatic plaques, resembling cutaneous infection with Leishmania infantum. TNF and other cytokines such as IL-12 and IFN-γ are central in the early control of the infection. Discontinuation of the anti-TNF-treatment resolved the infection without specific therapy.
CRIS-Team Scopus Importer:2022-12-30
Keywords: adalimumab; anti-TNF therapy; cutaneous leishmaniasis; skin pseudolymphoma; skin ulceration

Case Report: Local Treatment of a Leishmania tropica Infection in a Syrian Child with a Novel Filmogenic Preparation of Pharmaceutical Sodium Chlorite (LeiProtect®) - Debus, Dirk; Genç, Semra; Kurz, Philipp; Holzer, Martin; Bauer, Kurt; Heimke-Brinck, Ralph; Baier, Martin; Sebald, Heidi; Debus, Andrea; Bogdan, Christian; Stahl, Kurt Wilhelm (American Journal of Tropical Medicine and Hygiene, 2022)
Cutaneous leishmaniasis (CL) frequently entails chronic skin lesions that heal only slowly. Until now, the available therapeutic options are very limited. Here, we present a case of a 5½-year-old Syrian refugee with two progressive lower-leg skin ulcers caused by Leishmania tropica. The patient received topical treatment with LeiProtect®, a newly developed, hydroxypropylcellulose-based, filmogenic gel containing nontoxic concentrations of pharmaceutical sodium chlorite. The skin lesions completely healed within 8 weeks and did not relapse during 1 year of follow-up, underlining the efficacy of this novel local therapy of CL.
CRIS-Team Scopus Importer:2022-04-01

CCR3-dependent eosinophil recruitment is regulated by sialyltransferase ST3Gal-IV - Immler, Roland; Nussbaumer, Katrin; Doerner, Axel; El Bounkari, Omar; Huber, Silke; Abisch, Janine; Napoli, Matteo; Schmidt, Sarah; Margraf, Andreas; Pruenster, Monika; Rohwedder, Ina; Lange-Sperandio, Baerbel; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2024)
Eosinophil recruitment is a pathological hallmark of many allergic and helminthic diseases. Here, we investigated chemokine receptor CCR3-induced eosinophil recruitment in sialyltransferase St3gal4-/- mice. We found a marked decrease in eosinophil extravasation into CCL11-stimulated cremaster muscles and into the inflamed peritoneal cavity of St3gal4-/- mice. Ex vivo flow chamber assays uncovered reduced adhesion of St3gal4-/- compared to wild type eosinophils. Using flow cytometry, we show reduced binding of CCL11 to St3gal4-/- eosinophils. Further, we noted reduced binding of CCL11 to its chemokine receptor CCR3 isolated from St3gal4-/- eosinophils. This was accompanied by almost absent CCR3 internalization of CCL11-stimulated St3gal4-/- eosinophils. Applying an ovalbumin-induced allergic airway disease model, we found a dramatic reduction in eosinophil numbers in bronchoalveolar lavage fluid following intratracheal challenge with ovalbumin in St3gal4-deficient mice. Finally, we also investigated tissue-resident eosinophils under homeostatic conditions and found reduced resident eosinophil numbers in the thymus and adipose tissue in the absence of ST3Gal-IV. Taken together, our results demonstrate an important role of ST3Gal-IV in CCR3-induced eosinophil recruitment in vivo rendering this enzyme an attractive target in reducing unwanted eosinophil infiltration in various disorders including allergic diseases.
CRIS-Team Scopus Importer:2024-05-10
Keywords: asthma; chemokines; eosinophil; inflammation; sialylation

CD101 as an indicator molecule for pathological changes at the interface of host-microbiota interactions - Wrage, Marius; Kaltwasser, Johanna; Menge, Sonja; Mattner, Jochen (International Journal of Medical Microbiology, 2021)
Intestinal microbiota signal to local and distant tissues in the body. Thus, they also regulate biochemical, metabolic and immunological processes in the gut and in the pancreas. Vice versa, eating habits or the immune system of the host shape the intraluminal microbiota. Disruptions of these versatile host-microbiota interactions underlie the pathogenesis of complex immune-mediated disorders such as inflammatory bowel disease (IBD) or type 1 diabetes (T1D). Consequently, dysbiosis and increased intestinal permeability associated with both disorders change the biology of underlying tissues, as evidenced, for example, by an altered expression of surface markers such as CD101 on immune cells located at these dynamic host-microbiota interfaces. CD101, a heavily glycosylated member of the immunoglobulin superfamiliy, is predominantly detected on myeloid cells, intraepithelial lymphocytes (IELs) and regulatory T cells (Tregs) in the gut. The expression of CD101 on both myeloid cells and T lymphocytes protects from experimental enterocolitis and T1D. The improved outcome of both diseases is associated with an anti-inflammatory cytokine profile and a reduced expansion of T cells. However, distinct bacteria suppress the expression of CD101 on myeloid cells, similar as does inflammation on T cells. Thus, the reduced CD101 expression in T1D and IBD patients might be a consequence of an altered composition of the intestinal microbiota, enhanced bacterial translocation and a subsequent primining of local and systemic inflammatory immune responses.
CRIS-Team Scopus Importer:2021-04-09
Keywords: CD101; Host-microbe interactions; Immune-mediated disease; Microbiota; Mucosal surfaces

CD101 inhibits the expansion of colitogenic T cells - Schey, Regina; Dornhoff, H.; Baier, J. L. C.; Purtak, M.; Opoka, R.; Koller, A. K.; Atreya, Raja; Rau, Tilman; Daniel, Christoph; Amann, Kerstin Ute; Bogdan, Christian; Mattner, Jochen (Mucosal Immunology, 2016)
CD101 exerts negative-costimulatory effects in vitro, but its function in vivo remains poorly defined. CD101 is abundantly expressed on lymphoid and myeloid cells in intestinal tissues, but absent from naïve splenic T cells. Here, we assessed the impact of CD101 on the course of inflammatory bowel disease (IBD). Using a T-cell transfer model of chronic colitis, we found that in recipients of naïve T cells from CD101(+/+) donors up to 30% of the recovered lymphocytes expressed CD101, correlating with an increased interleukin (IL)-2-mediated FoxP3 expression. Transfer of CD101(-/-) T cells caused more severe colitis and was associated with an expansion of IL-17-producing T cells and an enhanced expression of IL-2R?/? independently of FoxP3. The co-transfer of naïve and regulatory T cells (Treg) protected most effectively from colitis, when both donor and recipient mice expressed CD101. Although the expression of CD101 on T cells was sufficient for Treg-function and the inhibition of T-cell proliferation, sustained IL-10 production required additional CD101 expression by myeloid cells. Finally, in patients with IBD a reduced CD101 expression on peripheral and intestinal monocytes and CD4(+) T cells correlated with enhanced IL-17 production and disease activity. Thus, CD101 deficiency is a novel marker for progressive colitis and potential target for therapeutic intervention.
EVALuna2:2051

Cd101 is a type 1 diabetes susceptibility gene in NOD mice - Mattner, Jochen; Wicker, L. (EUROPEAN JOURNAL OF IMMUNOLOGY, 2019)
CRIS-Team WoS Importer:2019-10-08

CD19 CAR T-Cell Therapy in Autoimmune Disease - A Case Series with Follow-up. - Müller, Fabian; Taubmann, Jule; Bucci, Laura; Wilhelm, Artur; Bergmann, Christina; Völkl, Simon; Aigner, Michael; Rothe, Tobias; Minopoulou, Ioanna; Tur, Carlo; Knitza, Johannes; Kharboutli, Soraya; et al. (New England Journal of Medicine, 2024)
BACKGROUND: Treatment for autoimmune diseases such as systemic lupus erythematosus (SLE), idiopathic inflammatory myositis, and systemic sclerosis often involves long-term immune suppression. Resetting aberrant autoimmunity in these diseases through deep depletion of B cells is a potential strategy for achieving sustained drug-free remission. METHODS: We evaluated 15 patients with severe SLE (8 patients), idiopathic inflammatory myositis (3 patients), or systemic sclerosis (4 patients) who received a single infusion of CD19 chimeric antigen receptor (CAR) T cells after preconditioning with fludarabine and cyclophosphamide. Efficacy up to 2 years after CAR T-cell infusion was assessed by means of Definition of Remission in SLE (DORIS) remission criteria, American College of Rheumatology-European League against Rheumatism (ACR-EULAR) major clinical response, and the score on the European Scleroderma Trials and Research Group (EUSTAR) activity index (with higher scores indicating greater disease activity), among others. Safety variables, including cytokine release syndrome and infections, were recorded. RESULTS: The median follow-up was 15 months (range, 4 to 29). The mean (±SD) duration of B-cell aplasia was 112±47 days. All the patients with SLE had DORIS remission, all the patients with idiopathic inflammatory myositis had an ACR-EULAR major clinical response, and all the patients with systemic sclerosis had a decrease in the score on the EUSTAR activity index. Immunosuppressive therapy was completely stopped in all the patients. Grade 1 cytokine release syndrome occurred in 10 patients. One patient each had grade 2 cytokine release syndrome, grade 1 immune effector cell-associated neurotoxicity syndrome, and pneumonia that resulted in hospitalization. CONCLUSIONS: In this case series, CD19 CAR T-cell transfer appeared to be feasible, safe, and efficacious in three different autoimmune diseases, providing rationale for further controlled clinical trials. (Funded by Deutsche Forschungsgemeinschaft and others.).
EVALuna2:555903

Cd4+ T cells induced by tuberculosis subunit vaccine h1 can improve the hiv-1 env humoral response by intrastructural help - Klessing, Stephan; Temchura, Vladimir; Tannig, Pierre; Peter, Antonia Sophia; Christensen, Dennis; Lang, Roland; Überla, Klaus (Vaccines, 2020)
The induction of a potent and long-lasting, broadly neutralizing antibody response is one of the most promising approaches in HIV-1 vaccination. Recently, we demonstrated that Gagspecific T helper cells induced by DNA priming can enhance and modulate the HIV Env-specific B cell response upon virus-like particle (VLP) boost by intrastructural help (ISH). In order to minimize the induction of potentially harmful HIV specific TH cells, we explored the possibility to harness the heterologous TH cells induced by a recombinant tuberculosis subunit vaccine H1, which contains a fusion protein of Ag85B and ESAT-6 antigens in combination with the liposomal adjuvant CAF01. To provide ISH, immunodominant MHC-II restricted peptides from the H1 vaccine were genetically incorporated into the HIV 1 Gag protein and used for HIV VLP production. ISH effects on Envspecific antibody levels and B cell differentiation were analyzed in mice primed against H1 and boosted with VLPs. In contrast to non-primed mice, a significant increase of Env-specific IgG levels for up to 26 weeks after the last immunization was observed. This increase was largely caused by elevated IgG2b and IgG2c levels in mice that received H1 priming. Additionally, ISH enhanced the frequency of Env-specific long-lived plasma cells in the bone marrow. In this study, we were able to demonstrate that a heterologous prime-boost regimen consisting of the H1 tuberculosis subunit vaccine and T helper epitope modified HIV-1 VLPs resulted in enhanced HIV Env antibody and B cell responses, mediated by intrastructural help.
CRIS-Team Scopus Importer:2020-10-23
Keywords: H1 tuberculosis vaccine; HIV-1 vaccine; IgG isotype modulation; Intrastructural help

CD4 T Helper Cells Instruct Lymphopenia-Induced Memory-Like CD8 T Cells for Control of Acute LCMV Infection - Schmitt, Michaela; Sitte, Selina; Vöhringer, David (Frontiers in Immunology, 2016)
Lymphopenic conditions lead to expansion of memory-like T cells (TML), which develop from naïve T cells by spontaneous proliferation. TML cells are often increased in the elderly population, AIDS patients, and patients recovering from radio- or chemotherapy. At present, it is unclear whether TML cells can efficiently respond to foreign antigen and participate in antiviral immunity. To address this question, we analyzed the immune response during acute low-dose infection with lymphocytic choriomeningitis virus-WE in T cell lymphopenic CD4Cre/R-diphtheria toxin alpha (DTA) mice in which most peripheral T cells show a TML phenotype. On day 8 after infection, the total number of effector T cells and polyfunctional IFN-? and TNF-? producing CD8 T cells were three- to fivefold reduced in CD4Cre/R-DTA mice as compared to controls. Viral clearance and the humoral immune response were severely impaired in CD4Cre/R-DTA mice although CTLs efficiently killed transferred target cells in vivo. Transfer of naïve CD4 T cells but not anti-PD-L1 blockade restored the expansion of antigen-specific polyfunctional CD8 T cells and resulted in lower viral titers. This finding indicates that under lymphopenic conditions endogenous CD4 TML cell lack the capacity to promote expansion of CTLs. However, CD8 TML cells retain sufficient functional plasticity to participate in antiviral immunity in the presence of appropriate help by fully functional CD4 T cells. This capacity might be exploited to develop treatments for improvement of CD8 T cell functions under various clinical settings of lymphopenia.
EVALuna2:25884

CD83 acts as immediate early response gene in activated macrophages and exhibits specific intracellular trafficking properties - Langguth, Pia; Peckert, Katrin; Beck, Philipp; Kuhnt, Christine; Draßner, Christina; Deinzer, Andrea; Steinkasserer, Alexander; Wild, Andreas (Biochemical and Biophysical Research Communications, 2023)
Macrophages (MΦ) are remarkably plastic cells, which assume phenotypes in every shade between a pro-inflammatory classical activation, and anti-inflammatory or resolving activation. Therefore, elucidation of mechanisms involved in shaping MΦ plasticity and function is key to understand their role during immunological balance. The immune-modulating CD83 molecule is expressed on activated immune cells and various tissue resident MΦ, rendering it an interesting candidate for affecting MΦ biology. However, in-depth analyses of the precise kinetics and trafficking of CD83 within pro-inflammatory, LPS activated bone-marrow-derived MΦ have not been performed. In this study, we show that activation with LPS leads to a very fast and strong, but transient increase of CD83 expression on these cells. Its expression peaks within 2 h of stimulation and is thereby faster than the early activation antigen CD69. To trace the CD83 trafficking through MΦs, we employed multiple inhibitors, thereby revealing a de novo synthesis and transport of the protein to the cell surface followed by lysosomal degradation, all within 6 h. Moreover, we found a similar expression kinetic and trafficking in human monocyte derived MΦ. This places CD83 at a very early point of MΦ activation suggesting an important role in decisions regarding the subsequent cellular fate.
CRIS-Team Scopus Importer:2023-02-10
Keywords: CD83; expression; intracellular trafficking; lipopolysaccharide; macrophages

CD83 expressed by macrophages is an important immune checkpoint molecule for the resolution of inflammation - Peckert-Maier, Katrin; Langguth, Pia; Strack, Astrid; Stich, Lena; Mühl-Zürbes, Petra; Kuhnt, Christine; Drassner, Christina; Zinser, Elisabeth; Wrage, Marius; Mattner, Jochen; Steinkasserer, Alexander; Royzman, Dmytro; et al. (Frontiers in Immunology, 2023)
Excessive macrophage (M phi) activation results in chronic inflammatory responses or autoimmune diseases. Therefore, identification of novel immune checkpoints on M phi, which contribute to resolution of inflammation, is crucial for the development of new therapeutic agents. Herein, we identify CD83 as a marker for IL-4 stimulated pro-resolving alternatively activated M phi (AAM). Using a conditional KO mouse (cKO), we show that CD83 is important for the phenotype and function of pro-resolving M phi. CD83-deletion in IL-4 stimulated M phi results in decreased levels of inhibitory receptors, such as CD200R and MSR-1, which correlates with a reduced phagocytic capacity. In addition, CD83-deficient M phi upon IL-4 stimulation, show an altered STAT-6 phosphorylation pattern, which is characterized by reduced pSTAT-6 levels and expression of the target gene Gata3. Concomitantly, functional studies in IL-4 stimulated CD83 KO M phi reveal an increased production of pro-inflammatory mediators, such as TNF-alpha, IL-6, CXCL1 and G-CSF. Furthermore, we show that CD83-deficient M phi have enhanced capacities to stimulate the proliferation of allo-reactive T cells, which was accompanied by reduced frequencies of Tregs. In addition, we show that CD83 expressed by M phi is important to limit the inflammatory phase using a full-thickness excision wound healing model, since inflammatory transcripts (e.g. Cxcl1, Il6) were increased, whilst resolving transcripts (e.g. Ym1, Cd200r, Msr-1) were decreased in wounds at day 3 after wound infliction, which reflects the CD83 resolving function on M phi also in vivo. Consequently, this enhanced inflammatory milieu led to an altered tissue reconstitution after wound infliction. Thus, our data provide evidence that CD83 acts as a gatekeeper for the phenotype and function of pro-resolving M phi.
CRIS-Team WoS Importer:2023-03-17

CD83 orchestrates immunity toward self and non-self in dendritic cells - Wild, Andreas; Krzyzak, Lena; Peckert, Katrin; Stich, Lena; Kuhnt, Christine; Butterhof, Alina; Seitz, Christine; Mattner, Jochen; Grner, Niklas; Gänsbauer, Maximilian; Purtak, Martin; Soulat, Didier; et al. (JCI Insight, 2019)
Dendritic cells (DCs) are crucial to balance protective immunity and autoimmune inflammatory processes. Expression of CD83 is a well-established marker for mature DCs, although its physiological role is still not completely understood. Using a DC-specific CD83-conditional KO (CD83(Delta DC)) mouse, we provide new insights into the function of CD83 within this cell type. Interestingly, CD83-deficient DCs produced drastically increased IL-2 levels and displayed higher expression of the costimulatory molecules CD25 and OX40L, which causes superior induction of antigen-specific T cell responses and compromises Treg suppressive functions. This also directly translates into accelerated immune responses in vivo. Upon Salmonella typhimurium and Listeria monocytogenes infection, CD83(Delta DC) mice cleared both pathogens more efficiently, and CD83-deficient DCs expressed increased IL-12 levels after bacterial encounter. Using the experimental autoimmune encephalomyelitis model, autoimmune inflammation was dramatically aggravated in CD83(Delta DC) mice while resolution of inflammation was strongly reduced. This phenotype was associated with increased cell influx into the CNS accompanied by elevated Th17 cell numbers. Concomitantly, CD83(Delta DC) mice had reduced Treg numbers in peripheral lymphoid organs. In summary, we show that CD83 ablation on DCs results in enhanced immune responses by dysregulating tolerance mechanisms and thereby impairing resolution of inflammation, which also demonstrates high clinical relevance.
CRIS-Team WoS Importer:2019-11-01

C/EBPβ regulates lipid metabolism and Pparg isoform 2 expression in alveolar macrophages - Dörr, Dorothea; Obermayer, Benedikt; Weiner, January Mikolaj; Zimmermann, Karin; Anania, Chiara; Wagner, Lisa Katharina; Lyras, Ekaterini Maria; Sapozhnikova, Valeriia; Lara-Astiaso, David; Prósper, Felipe; Lang, Roland; Lupiáñez, Darío G.; et al. (Science immunology, 2022)
Pulmonary alveolar proteinosis (PAP) is a syndrome characterized by accumulation of surfactant lipoproteins within the lung alveoli. Alveolar macrophages (AMs) are crucial for surfactant clearance, and their differentiation depends on colony-stimulating factor 2 (CSF2), which regulates the establishment of an AM-characteristic gene regulatory network. Here, we report that the transcription factor CCAAT/enhancer binding protein β (C/EBPβ) is essential for the development of the AM identity, as demonstrated by transcriptome and chromatin accessibility analysis. Furthermore, C/EBPβ-deficient AMs showed severe defects in proliferation, phagocytosis, and lipid metabolism, collectively resulting in a PAP-like syndrome. Mechanistically, the long C/EBPβ protein variants LAP* and LAP together with CSF2 signaling induced the expression of Pparg isoform 2 but not Pparg isoform 1, a molecular regulatory mechanism that was also observed in other CSF2-primed macrophages. These results uncover C/EBPβ as a key regulator of AM cell fate and shed light on the molecular networks controlling lipid metabolism in macrophages.
CRIS-Team Scopus Importer:2022-09-30

Cell death induction facilitates egress of Coxiella burnetii from infected host cells at late stages of infection - Schulze-Lührmann, Jan; Liebler-Tenorio, Elisabeth; Felipe-López, Alfonso; Lührmann, Anja (Molecular Microbiology, 2023)
Intracellular bacteria have evolved mechanisms to invade host cells, establish an intracellular niche that allows survival and replication, produce progeny, and exit the host cell after completion of the replication cycle to infect new target cells. Bacteria exit their host cell by (i) initiation of apoptosis, (ii) lytic cell death, and (iii) exocytosis. While bacterial egress is essential for bacterial spreading and, thus, pathogenesis, we currently lack information about egress mechanisms for the obligate intracellular pathogen C. burnetii, the causative agent of the zoonosis Q fever. Here, we demonstrate that C. burnetii inhibits host cell apoptosis early during infection, but induces and/or increases apoptosis at later stages of infection. Only at later stages of infection did we observe C. burnetii egress, which depends on previously established large bacteria-filled vacuoles and a functional intrinsic apoptotic cascade. The released bacteria are not enclosed by a host cell membrane and can infect and replicate in new target cells. In summary, our data argue that C. burnetii egress in a non-synchronous way at late stages of infection. Apoptosis-induction is important for C. burnetii egress, but other pathways most likely contribute.
CRIS-Team Scopus Importer:2023-12-29
Keywords: apoptosis; Coxiella burnetii; egress; Q fever; spreading

Cell type-specific modulation of metabolic, immune-regulatory, and anti-microbial pathways by CD101 - Wrage, Marius; Holland, Tim; Nüse, Björn; Kaltwasser, Johanna; Fröhlich, Jessica; Arnold, Harald; Gießler, Claudia; Flamann, Cindy; Bruns, Heiko; Berges, Johannes; Daniel, Christoph; Hoffmann, Markus; et al. (Mucosal Immunology, 2024)
T lymphocytes and myeloid cells express the immunoglobulin-like glycoprotein cluster of differentiation (CD)101, notably in the gut. Here, we investigated the cell-specific functions of CD101 during dextran sulfate sodium (DSS)-induced colitis and Salmonella enterica Typhimurium infection. Similar to conventional CD101−/− mice, animals with a regulatory T cell-specific Cd101 deletion developed more severe intestinal pathology than littermate controls in both models. While the accumulation of T helper 1 cytokines in a CD101-deficient environment entertained DSS-induced colitis, it impeded the replication of Salmonella as revealed by studying CD101−/− x interferon-g−/− mice. Moreover, CD101-expressing neutrophils were capable to restrain Salmonella infection in vitro and in vivo. Both cell-intrinsic and -extrinsic mechanisms of CD101 contributed to the control of bacterial growth and spreading. The CD101-dependent containment of Salmonella infection required the expression of Irg-1 and Nox2 and the production of itaconate and reactive oxygen species. The level of intestinal microbial antigens in the sera of inflammatory bowel disease patients correlated inversely with the expression of CD101 on myeloid cells, which is in line with the suppression of CD101 seen in mice following DSS application or Salmonella infection. Thus, depending on the experimental or clinical setting, CD101 helps to limit inflammatory insults or bacterial infections due to cell type-specific modulation of metabolic, immune-regulatory, and anti-microbial pathways.
CRIS-Team Scopus Importer:2024-07-19

Characterisation of Roseomonas mucosa isolated from the root canal of an infected tooth - Diesendorf, Nina; Köhler, Stefanie; Geißdörfer, Walter; Grobecker-Karl, Tanja; Karl, Matthias; Burkovski, Andreas (BMC Research Notes, 2017)

Characterization of a discontinuous neutralizing epitope on glycoprotein B of human cytomegalovirus - Spindler, Nadja; Ruecker, Pia; Pötzsch, Sonja; Diestel, Uschi; Sticht, Heinrich; Martin-Parras, Luis; Winkler, Thomas; Mach, Michael (Journal of Virology, 2013)
Human cytomegalovirus (HCMV) is a ubiquitously distributed pathogen that causes severe disease in immunosuppressed patients and newborn infants infected in utero. The viral envelope glycoprotein B (gB) is an attractive molecule for active vaccination and passive immunoprophylaxis and therapy. Using human monoclonal antibodies (MAbs), we have recently identified antigenic region 4 (AD-4) on gB as an important target for neutralizing antibodies. AD-4 is formed by a discontinuous sequence comprising amino acids 121 to 132 and 344 to 438 of gB of HCMV strain AD169. To map epitopes for human antibodies on this protein domain, we used a three-dimensional (3D) model of HCMV gB to identify surface-exposed amino acids on AD-4 and selected juxtaposed residues for alanine scans. A tyrosine (Y) at position 364 and a lysine (K) at position 379 (the YK epitope), which are immediate neighbors on the AD-4 surface, were found to be essential for binding of the human MAbs. Recognition of AD-4 by sera from HCMV-infected individuals also was largely dependent on these two residues, indicating a general importance for the antibody response against AD-4. A panel of AD-4 recombinant viruses harboring mutations at the crucial antibody binding sites was generated. The viruses showed significantly reduced susceptibility to neutralization by AD-4-specific MAbs or polyclonal AD-4-specific antibodies, indicating that the YK epitope is dominant for the AD-4-specific neutralizing antibody response during infection. To our knowledge, this is the first molecular identification of a functional discontinuous epitope on HCMV gB. Induction of antibodies specific for this epitope may be a desirable goal following vaccination with gB.
EVALuna2:8189

Characterization of the Protein Tyrosine Phosphatase LmPRL-1 Secreted by Leishmania major via the Exosome Pathway - Leitherer, Sabine; Clos, Joachim; Liebler-Tenorio, Elisabeth M.; Schleicher, Ulrike; Bogdan, Christian; Soulat, Didier (Infection and Immunity, 2017)
Similar to other intracellular pathogens, Leishmania parasites are known to evade the antimicrobial effector functions of host immune cells. To date, however, only a few virulence factors have been described for Leishmania major, one of the causative agents of cutaneous leishmaniasis. Here, we have characterized the expression and function of an L. major phosphatase, which we termed LmPRL-1. This enzyme shows a strong structural similarity to the human phosphatases of regenerating liver (PRL-1, -2, and -3) that regulate the proliferation, differentiation, and motility of cells. The biochemical characterization of the L. major phosphatase revealed that the enzyme is redox sensitive. When analyzing the subcellular localization of LmPRL-1 in promastigotes, amastigotes, and infected macrophages, we found that the phosphatase was predominantly expressed and secreted by promastigotes via the exosome route. Finally, we observed that ectopic expression of LmPRL-1 in L. major led to an increased number of parasites in macrophages. From these data, we conclude that the L. major phosphatase LmPRL-1 contributes to the intracellular survival of the parasites in macrophages.
EVALuna2:7751

Chronic mycobacterial infection induces an immune suppressive microenvironment altering dendritic cell function - Merga, K. A.; Schleicher, Ulrike; Bogdan, Christian; Weiss, S.; Goethe, R. (2018)
EVALuna2:212766

Chronic Systemic Infection of Mice with Leishmania infantum Leads to Increased Bone Mass - Lai, Chaobo; Heinemann, Jennifer; Schleicher, Ulrike; Schett, Georg; Bogdan, Christian; Bozec, Aline; Soulat, Didier (Journal of Bone and Mineral Research, 2022)
Vector-borne infections of humans with the protozoan parasite Leishmania (L.) infantum can cause a systemic and potentially lethal disease termed visceral leishmaniasis. In the corresponding mouse model, an intravenous infection with L. infantum leads to the persistence of parasites in various organs, including bone marrow (BM). Considering the anatomical proximity between the BM and the cortical bone, we investigated whether a chronic infection with L. infantum affected bone homeostasis. Unexpectedly, chronic infection with L. infantum caused an increase in bone mass in mice. In vivo, an increased number of osteoblasts and osteocytes and a decreased maturation of osteoclasts characterized the phenotype. Confocal laser scanning fluorescence microscopy confirmed the infection of BM macrophages but also revealed the presence of parasites in osteoclasts. In vitro, mature osteoclasts took up L. infantum parasites. However, infection of osteoclast progenitors abolished their differentiation and function. In addition, secretory products of infected BM-derived macrophages inhibited the maturation of osteoclasts. Both in vitro and in vivo, infected macrophages and osteoclasts showed an enhanced expression of the anti-osteoclastogenic chemokine CCL5 (RANTES). Neutralization of CCL5 prevented the inhibition of osteoclast generation seen in the presence of culture supernatants from L. infantum-infected macrophages. Altogether, our study shows that chronic infection with Leishmania increases bone mass by inducing bone formation and impairing osteoclast differentiation and function. (c) 2022 American Society for Bone and Mineral Research (ASBMR).
CRIS-Team WoS Importer:2022-12-02

Chronic vasculitis and polyneuropathy due to infection with Bartonella henselae - Schoerner, Christoph; Harrer, Thomas; et al. (Infection, 2007)
Bartonella henselae, the causative agent of cat scratch disease and bacillary angiomatosis, is associated with an expanding spectrum of diseases. Here, we report on a 40-year-old patient suffering from chronic recurrent painful ulcers of the toes, distal axonal sensomotor polyneuropathy and Raynaud's phenomenon. Biopsy of the sural nerve demonstrated an axonal neuropathy with a neurogenic muscular atrophy. Treatment with high dose corticosteroids had no beneficial effect. A biopsy taken from a recurring ulcer 7 years after the beginning of the disease revealed superficial ulcerated hyperkeratosis with subepithelial proliferation of small vessels compatible with a diagnosis of verruca peruana, however, without detection of microorganism. Serologic analysis revealed an elevated IFT titer of 1:1,024 against B. henselae. Treatment with erythromycin induced healing of the ulcer, remission of the vasculitis and the polyneuropathy, and a decline of the IFT titer. This case illustrates that B. henselae infection should be considered in patients with vasculitis and polyneuropathic syndromes. © 2007 Urban & Vogel.
UnivIS-Import:2015-04-14:Pub.2007.med.IKMI.LHMMIPDR.chroni

Class I myosin Myo1e regulates TLR4-triggered macrophage spreading, chemokine release, and antigen presentation via MHC class II - Wenzel, Jens; Ouderkirk, Jessica L.; Krendel, Mira; Lang, Roland (European Journal of Immunology, 2015)
TLR-mediated recognition of microbial danger induces substantial changes in macrophage migration, adherence, and phagocytosis. Recently, we described the LPS-regulated phosphorylation of many cytoskeleton-associated proteins by phosphoproteomics. The functional role of these cytoskeletal and motor proteins in innate immune cell responses is largely unexplored. Here, we first identified both long-tailed class I myosins Myo1e and Myo1f as important contributors to LPS-triggered macrophage spreading. Mouse bone marrow-derived macrophages and DCs deficient in Myo1e selectively secreted increased amounts of the chemokine CCL2. In addition, the cell surface expression of MHC class II (MHC-II) on both cell types was reduced in the absence of Myo1e. However, transcriptional changes in CCL2 and MHC-II were not observed in the absence of Myo1e, indicating that Myo1e regulates specific intracellular transport processes. The capacity of macrophages and DCs lacking Myo1e to stimulate antigen-specific CD4(+) T-cell proliferation was impaired, consistent with the reduced MHC-II surface protein levels. Surprisingly, in Myo1e-deficient DCs, the proteolytic cleavage of endocytosed antigen was also increased. Together, our results provide evidence for a non-redundant function of the motor protein Myo1e in the regulation of TLR4-controlled, cytoskeleton-associated functional properties of macrophages and DCs, and in induction of a full MHC-II-restricted adaptive immune response.
EVALuna2:7660

Class switch towards non-inflammatory, spike-specific IgG4 antibodies after repeated SARS-CoV-2 mRNA vaccination - Irrgang, Pascal; Gerling, Juliane; Kocher, Katharina; Lapuente, Dennis; Steininger, Philipp; Habenicht, Katharina Marie; Wytopil, Monika; Beileke, Stephanie; Schäfer, Simon; Zhong, Jahn; Ssebyatika, George; Krey, Thomas; et al. (Science immunology, 2022)
RNA vaccines are efficient preventive measures to combat the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic. High levels of neutralizing SARS-CoV-2 antibodies are an important component of vaccine-induced immunity. Shortly after the initial two mRNA vaccine doses, the immunoglobulin G (IgG) response mainly consists of the proinflammatory subclasses IgG1 and IgG3. Here, we report that several months after the second vaccination, SARS-CoV-2–specific antibodies were increasingly composed of noninflammatory IgG4, which were further boosted by a third mRNA vaccination and/or SARS-CoV-2 variant breakthrough infections. IgG4 antibodies among all spike-specific IgG antibodies rose, on average, from 0.04% shortly after the second vaccination to 19.27% late after the third vaccination. This induction of IgG4 antibodies was not observed after homologous or heterologous SARS-CoV-2 vaccination with adenoviral vectors. Single-cell sequencing and flow cytometry revealed substantial frequencies of IgG4-switched B cells within the spike-binding memory B cell population [median of 14.4%; interquartile range (IQR) of 6.7 to 18.1%] compared with the overall memory B cell repertoire (median of 1.3%; IQR of 0.9 to 2.2%) after three immunizations. This class switch was associated with a reduced capacity of the spike-specific antibodies to mediate antibody-dependent cellular phagocytosis and complement deposition. Because Fc-mediated effector functions are critical for antiviral immunity, these findings may have consequences for the choice and timing of vaccination regimens using mRNA vaccines, including future booster immunizations against SARS-CoV-2.<br

Clinical complexity of Leishmania (Viannia) braziliensis infections amongst travelers - Eichner, Saskia; Thoma-Uszynski, Sybille; Herrgott, Ilka; Sebald, Heidi; Debus, Andrea; Tsianakas, Athanasios; Ehrchen, Jan; Harms, Gundel; Simon, Miklos; Sunderkoetter, Cord; Bogdan, Christian (European Journal of Dermatology, 2013)
The protozoan parasite Leishmania (Viannia) braziliensis is one of the main causes of cutaneous and mucocutaneous leishmaniasis in South America. Here, we describe three cases of L. (V.) braziliensis infection which were acquired during travelling in Bolivia, Peru or Paraguay and illustrate the phenotypic heterogeneity and therapeutic complexity of the disease. Two patients presented with unusual clinical manifestations, i.e. with prominent regional lymphadenopathy ("bubonic leishmaniasis") and with simultaneously emerged skin and mucosal lesions, respectively. Both patients insufficiently responded to oral treatment with miltefosine; resolution of the lesions was only achieved after a course of intravenous liposomal amphotericin B. Key words cutaneous leishmaniasis, mucosal leishmaniasis, Leishmania (V.) braziliensis.
CRIS-Team Scopus Importer:2024-02-26
Keywords: cutaneous leishmaniasis; mucosal leishmaniasis; Leishmania (V.) braziliensis

Clinical evaluation of two different (1,3)-ß-d-glucan assays for diagnosis of invasive fungal diseases: A retrospective cohort study - Zubkowicz, Marta; Held, Jürgen; Baier, Michael; Pletz, Mathias W.; Kesselmeier, Miriam; Hagel, Stefan; Bahrs, Christina (Mycoses, 2020)
Background: Early diagnosis of invasive fungal diseases (IFDs) remains a major challenge in routine clinical practice. Objectives: The aim of this retrospective cohort study was to evaluate the diagnostic performance of the fungal biomarker (1,3)-ß-d-glucan (BDG) using the β-Glucan test (GT) and the well-established Fungitell assay® (FA) in real-life clinical practice. Patients/Methods: We included 109 patients with clinical suspicion of IFD who were treated at Jena University Hospital, Germany, between November 2018 and March 2019. The patients were classified according to the latest update of the EORTC/MSG consensus definitions of IFD. The first serum sample of every patient was analysed for BDG using the FA and the GT, respectively. Results: Fifty-six patients (51.4%) had at least one host factor for IFD. In patients with proven (n = 11) or probable IFDs (n = 20), median BDG concentrations were 145.0 pg/ml for the FA and 5.1 pg/ml for the GT, respectively. A positive test result of both BDG assays at manufacturer's cut-offs predicted 89.5%-98.3% of proven or probable IFD, but the sensitivity of both assays was limited: The FA identified 60.7% of IFDs (cut-off: 80 pg/ml). Reducing the GT cut-off value from 11.0 to 4.1 pg/ml increased the detection rate of IFDs from 35.5% to 54.8%. Conclusions: A positive test result of both BDG assays at manufacturer's cut-off was highly predictive for IFD, but except for Pneumocystis jirovecii pneumonia sensitivities were limited. Adjustment of the GT cut-off value equalised sensitivities of GT and FA.
CRIS-Team Scopus Importer:2020-12-04
Keywords: (1; 3)-ß-d-Glucan; Aspergillus; Candida; invasive fungal disease; Pneumocystis

Clinical Manifestation of Cutaneous Leishmaniasis Following a Mechanical Trauma - Busch, Dorothee; Bogdan, Christian; Erfurt-Berge, Cornelia (International Journal of Lower Extremity Wounds, 2020)
Unusual skin ulcers frequently represent a diagnostic challenge. When the most common disease entities such as arterial, venous or diabetic ulcers have been excluded, the question of further differential diagnoses and procedures arises. Other possible causes include chronic inflammatory diseases, neoplasia, self-inflicted wounds, primary infectious diseases and physical/chemical damage to the skin. To narrow down the differential diagnoses, a detailed history of the patient is essential, which also needs to include events further back in time.
CRIS-Team Scopus Importer:2020-11-13
Keywords: delayed diagnosis; leg ulcer; leishmaniasis; trauma

CMV seropositivity is a potential novel risk factor for severe COVID-19 in non-geriatric patients. - Weber, Simone; Kehl, Victoria; Erber, Johanna; Wagner, Karolin I.; Jetzlsperger, Ana Marija; Burrell, Teresa; Schober, Kilian; Schommers, Philipp; Augustin, Max; Crowell, Claudia S.; Gerhard, Markus; Winter, Christof; et al. (PLoS ONE, 2022)
BACKGROUND: COVID-19 has so far affected more than 250 million individuals worldwide, causing more than 5 million deaths. Several risk factors for severe disease have been identified, most of which coincide with advanced age. In younger individuals, severe COVID-19 often occurs in the absence of obvious comorbidities. Guided by the finding of cytomegalovirus (CMV)-specific T cells with some cross-reactivity to SARS-CoV-2 in a COVID-19 intensive care unit (ICU) patient, we decided to investigate whether CMV seropositivity is associated with severe or critical COVID-19. Herpes simplex virus (HSV) serostatus was investigated as control. METHODS: National German COVID-19 bio-sample and data banks were used to retrospectively analyze the CMV and HSV serostatus of patients who experienced mild (n = 101), moderate (n = 130) or severe to critical (n = 80) disease by IgG serology. We then investigated the relationship between disease severity and herpesvirus serostatus via statistical models. RESULTS: Non-geriatric patients (< 60 years) with severe COVID-19 were found to have a very high prevalence of CMV-seropositivity, while CMV status distribution in individuals with mild disease was similar to the prevalence in the German population; interestingly, this was not detectable in older patients. Prediction models support the hypothesis that the CMV serostatus, unlike HSV, might be a strong biomarker in identifying younger individuals with a higher risk of developing severe COVID-19, in particular in absence of other co-morbidities. CONCLUSIONS: We identified 'CMV-seropositivity' as a potential novel risk factor for severe COVID-19 in non-geriatric individuals in the studied cohorts. More mechanistic analyses as well as confirmation of similar findings in cohorts representing the currently most relevant SARS-CoV-2 variants should be performed shortly.
EVALuna2:535689

Combined Clinical, Epidemiological, and Genome-Based Analysis Identified a Nationwide Outbreak of Burkholderia cepacia Complex Infections Caused by Contaminated Mouthwash Solutions - Bender, Jennifer K.; Haller, Sebastian; Pfeifer, Yvonne; Hogardt, Michael; Hunfeld, Klaus-Peter; Thuermer, Andrea; Zanuzdana, Arina; Werner, Markus; Kunz, Bernd; Eisenberger, David; Pfennigwerth, Niels; Kempf, Volkhard A. J.; et al. (Open Forum Infectious Diseases, 2022)
Background In September 2018, Burkholderia cepacia complex (BCC) infections in 3 patients associated with exposure to a mouthwash solution (MWS) were reported to the Robert Koch Institute (RKI). As the product was still on the market and the scale of the outbreak was unclear, a nation-wide investigation was initiated. Methods We aimed to investigate BCC infections/colonizations associated with MWS. Hospitals, laboratories, and public health services were informed that BCC isolates should be sent to the RKI. These isolates were typed by pulsed-field gel electrophoresis (PFGE) and whole-genome sequencing (WGS) including development of an ad hoc core genome MLST (cgMLST) scheme. Results In total, 36 patients from 6 hospitals met the case definition, the last patient in November 2018. Twenty-nine isolates from 26 of these patients were available for typing. WGS analysis revealed 2 distinct cgMLST clusters. Cluster 1 (Burkholderia arboris) contained isolates from patients and MWS obtained from 4 hospitals and isolates provided by the manufacturer. Patient and MWS isolates from another hospital were assigned to cluster 2 (B. cepacia). Conclusions The combined clinical, epidemiological, and microbiological investigation, including whole-genome analysis, allowed for uncovering a supraregional BCC outbreak in health care settings. Strains of B. arboris and B. cepacia were identified as contaminating species of MWS bottles and subsequent colonization and putative infection of patients in several hospitals. Despite a recall of the product by the manufacturer in August 2018, the outbreak lasted until December 2018. Reporting of contaminated medical products and recalls should be optimized to protect patients.
CRIS-Team WoS Importer:2022-04-29
Keywords: Burkholderia arboris; outbreak; clonal transfer; mouthwash solution; medical device

Comment on: “New recommendation on yellow fever booster vaccination in Germany” - Kling, Kerstin; Domingo, Cristina; Bogdan, Christian; Mertens, Thomas; Wolff, Robert; Wiedermann, Ursula (Travel Medicine and Infectious Disease, 2023)
CRIS-Team Scopus Importer:2023-04-14

Comment on "TLR9-dependent activation of dendritic cells by DNA from Leishmania major favors Th1 cell development and the resolution of lesions" - Bogdan, Christian; Schleicher, Ulrike (Journal of Immunology, 2009)
CRIS-Team Scopus Importer:2024-02-26

Comparative Analysis of the Euroimmun CXCL13 Enzyme-Linked Immunosorbent Assay and the ReaScan Lateral Flow Immunoassay for Diagnosis of Lyme Neuroborreliosis - Ziegler, Katharina; Rath, Anca; Schoerner, Christoph; Meyer, Renate; Bertsch, Thomas; Erbguth, Frank; Bogdan, Christian; Steinmann, Jörg; Held, Jürgen (Journal of Clinical Microbiology, 2020)
Diagnosis of Lyme neuroborreliosis (LNB) is challenging, as long as Borrelia-specific intrathecal antibodies are not yet detectable. The chemokine CXCL13 is elevated in the cerebrospinal fluid (CSF) of LNB patients. Here, we compared the performances of the Euroimmun CXCL13 enzyme-linked immunosorbent assay (CXCL13 ELISA) and the ReaScan CXCL13 lateral flow immunoassay (CXCL13 LFA), a rapid point-of-care test, to support the diagnosis of LNB. In a dual-center case-control study, CSF samples from 90 patients (34 with definite LNB, 10 with possible LNB, and 46 with other central nervous system [CNS] diseases [non-LNB group]) were analyzed with the CXCL13 ELISA and the CXCL13 LFA. Classification of patients followed the European Federation of Neurological Societies (EFNS) guidelines on LNB. The CXCL13 ELISA detected elevated CXCL13 levels in all patients with definite LNB (median, 1,409 pg/ml) compared to the non-LNB controls (median, 20.7 pg/ml; P < 0.0001), with a sensitivity of 100% and a specificity of 84.8% (cutoff value, 78.6 pg/ml; area under the receiver operating characteristic [ROC] curve, 0.93). Similarly, the CXCL13 LFA yielded elevated CXCL13 levels in 31 patients with definite LNB (median arbitrary value, 223.5) compared to the non-LNB control patients (median arbitrary value, 0; P < 0.0001) and had a sensitivity and specificity of 91.2% and 93.5%, respectively (cutoff arbitrary value, 22.5; area under the ROC curve, 0.94). The correlation between the CXCL13 levels obtained by ELISA and LFA was strong (Spearman correlation coefficient r = 0.89; P < 0.0001). The CXCL13 ELISA and the CXCL13 LFA are comparable diagnostic tools for the detection of CXCL13 in the CSF of patients with definite LNB. The advantage of the CXCL13 LFA is the shorter time to result.
CRIS-Team Scopus Importer:2020-09-04
Keywords: biomarker; Borrelia burgdorferi; CSF; Lyme disease; meningitis; neuroborreliosis

Comparative Analysis of the Wako β-Glucan Test and the Fungitell Assay for Diagnosis of Candidemia and Pneumocystis jirovecii Pneumonia - Friedrich, Ricarda; Rappold, Elfriede; Bogdan, Christian; Held, Juergen (Journal of Clinical Microbiology, 2018)
(1→3)-β-d-Glucan (BDG) is a biomarker for invasive fungal disease. Until now, all BDG data in the Western Hemisphere were obtained using the Fungitell assay (FA). How it compares to the Wako β-glucan test (GT), which was recently launched in Europe, is largely unknown. We conducted a case-control study to compare the two assays in serum samples from 120 candidemia and 63 Pneumocystis jirovecii pneumonia (PCP) patients. Two hundred patients with bacteremia or negative blood cultures served as candidemia control group. In patients with candidemia the median BDG values of the FA and the GT were 351 and 8.4 pg/ml, respectively. With both assays, the BDG levels in candidemia were significantly higher than those measured in the control group (P < 0.001). The sensitivity, specificity, and positive and negative predictive values for the diagnosis of candidemia were 86.7%, 85.0%, 6.0%, and 99.8% for the FA and 42.5%, 98.0%, 19.0%, and 99.4% for the GT, respectively. In PCP patients the median BDG values of the FA and the GT were 963 and 57.7 pg/ml, respectively. The sensitivities for PCP diagnosis were 100% for the FA and 88.9% for the GT. In practical terms, the GT proved to be robust and applicable for testing single samples, whereas for economic reasons the FA required the samples to be tested in batch. The sensitivity of the FA is superior to that of the GT. However, the GT is a valuable alternative to the FA, especially for patients with suspected PCP and in laboratories with low sample throughput.
EVALuna2:34508

Comparative whole genome analysis of three consecutive Salmonella diarizonae isolates - Gerlach, Roman G.; Walter, Steffi; McClelland, Michael; Schmidt, Christiane; Steglich, Matthias; Prager, Rita; Bender, Jennifer K.; Fuchs, Stephan; Schoerner, Christoph; Rabsch, Wolfgang; Lang, Werner; Jantsch, Jonathan (International Journal of Medical Microbiology, 2017)
Infections of very young children or immunocompromised people with Salmonella of higher subspecies are a well-known phenomenon often associated with contact to cold-blooded animals. We describe the molecular characterization of three S. enterica subsp. diarizonae strains, isolated consecutively over a period of several months from a hospital patient suffering from diarrhea and sepsis with fatal outcome. With the initial isolate the first complete genome sequence of a member of subsp. diarizonae is provided and based on this reference we revealed the genomic differences between the three isolates by use of next-generation sequencing and confirmed by phenotypical tests. Genome comparisons revealed mutations within gpt, hfq and purK in the first isolate as a sign of clonal variation rather than host-directed evolution. Furthermore, our work demonstrates that S. enterica subsp. diarizonae possess, besides a conserved set of known Salmonella Pathogenicity Islands, a variable portfolio of additional genomic islands of unknown function.
EVALuna2:7731

Comparison of 1,3-β-d-glucan with galactomannan in serum and bronchoalveolar fluid for the detection of Aspergillus species in immunosuppressed mechanical ventilated critically ill patients - Lahmer, Tobias; Neuenhahn, Michael; Held, Jürgen; Rasch, Sebastian; Schmid, Roland M.; Huber, Wolfgang (Journal of Critical Care, 2016)
Invasive pulmonary aspergillosis (IPA) is an important cause of morbidity/mortality in immunocompromised critically ill patients. New diagnostic strategies for early detection of IPA include the noninvasive biomarkers 1,3-?-d-glucan (BDG), serum, and bronchoalveolar (BAL) fluid galactomannan (GM). The aim of this study was to compare these markers for early detection of IPA in immunosuppressed critically ill patients.Between December 2014 and December 2015, 49 immunosuppressed patients with respiratory failure were treated at our intensive care unit (ICU). We compared the BDG Fungitell assay with GM Platelia assay in serum and BAL for early detection of IPA. All tests were performed initially after admission at the ICU.In our study with 49 patients, 13 (26%) had probable IPA. These patients had a higher Acute Physiology And Chronic Health Evaluation II score (28 vs 23, P<.001), Sequential Organ Failure Assessment score (16 vs 14, P<.001), more neutropenia (77% vs 30%, P<.001), worse Horowitz Index (99 vs 73 P<.020), a longer ICU stay (26 vs 17 days, P<.044), and a higher mortality rate (77% vs 58%, P<.001) as compared with patients without probable IPA. The used biomarker BDG presented in patients with probable IPA showed significantly higher levels as compared with patients without probable IPA (375 [103-1000 pg/mL; P<.001] vs 64 [30-105 pg/mL; P < .001]). Comparison of BDG with GM showed that positive serum GM could be detected in only 4 (30%), whereas positive BAL GM could be detected in 12 (92%; mean optical density index, 3.7) of 13 probable IPA cases. These results can be expressed as an overall sensitivity of 88% and a specificity of 82% for probable IPA using the BDG Fungitell assay, a sensitivity of 35% and a specificity of 70% using the serum GM Platelia assay, and a sensitivity of 70% and a specificity of 94% using the BAL GM Platelia assay. The negative predictive values of the used tests were 94% for the BDG Fungitell assay, 94% for the serum GM Platelia assay, and 90% for the BAL GM Platelia assay.1,3-?-d-Glucan may be a useful marker for patients under surveillance at risk for IPA. In critically ill patients with immunosuppression, early diagnosis of IPA may be improved by BDG as compared with serum GM. However, diagnostic performance and accuracy increase when BDG is run in parallel with GM from BAL; moreover, the association of the 2 parameters has also the advantage of detecting early and reliable IPA.
EVALuna2:7720

Comparison of parameter-adapted segmentation methods for fluorescence micrographs - Held, Christian; Palmisano, Ralf; Häberle, Lothar; Hensel, Michael; Wittenberg, Thomas (Cytometry Part A, 2011)
Interpreting images from fluorescence microscopy is often a time-consuming task with poor reproducibility. Various image processing routines that can help investigators evaluate the images are therefore useful. The critical aspect for a reliable automatic image analysis system is a robust segmentation algorithm that can perform accurate segmentation for different cell types. In this study, several image segmentation methods were therefore compared and evaluated in order to identify the most appropriate segmentation schemes that are usable with little new parameterization and robustly with different types of fluorescence-stained cells for various biological and biomedical tasks. The study investigated, compared, and enhanced four different methods for segmentation of cultured epithelial cells. The maximum-intensity linking (MIL) method, an improved MIL, a watershed method, and an improved watershed method based on morphological reconstruction were used. Three manually annotated datasets consisting of 261, 817, and 1,333 HeLa or L929 cells were used to compare the different algorithms. The comparisons and evaluations showed that the segmentation performance of methods based on the watershed transform was significantly superior to the performance of the MIL method. The results also indicate that using morphological opening by reconstruction can improve the segmentation of cells stained with a marker that exhibits the dotted surface of cells

Comparison of the transcriptome, lipidome, and c-di-GMP production between BCGΔBCG1419c and BCG, with Mincle- and Myd88-dependent induction of proinflammatory cytokines in murine macrophages - Flores-Valdez, Mario Alberto; Peterson, Eliza J.R.; Aceves-Sánchez, Michel de Jesús; Baliga, Nitin S.; Morita, Yasu S.; Sparks, Ian L.; Saini, Deepak Kumar; Yadav, Rahul; Lang, Roland; Mata-Espinosa, Dulce; León-Contreras, Juan Carlos; Hernández-Pando, Rogelio (Scientific Reports, 2024)
We have previously reported the transcriptomic and lipidomic profile of the first-generation, hygromycin-resistant (HygR) version of the BCGΔBCG1419c vaccine candidate, under biofilm conditions. We recently constructed and characterized the efficacy, safety, whole genome sequence, and proteomic profile of a second-generation version of BCGΔBCG1419c, a strain lacking the BCG1419c gene and devoid of antibiotic markers. Here, we compared the antibiotic-less BCGΔBCG1419c with BCG. We assessed their colonial and ultrastructural morphology, biofilm, c-di-GMP production in vitro, as well as their transcriptomic and lipidomic profiles, including their capacity to activate macrophages via Mincle and Myd88. Our results show that BCGΔBCG1419c colonial and ultrastructural morphology, c-di-GMP, and biofilm production differed from parental BCG, whereas we found no significant changes in its lipidomic profile either in biofilm or planktonic growth conditions. Transcriptomic profiling suggests changes in BCGΔBCG1419c cell wall and showed reduced transcription of some members of the DosR, MtrA, and ArgR regulons. Finally, induction of TNF-α, IL-6 or G-CSF by bone-marrow derived macrophages infected with either BCGΔBCG1419c or BCG required Mincle and Myd88. Our results confirm that some differences already found to occur in HygR BCGΔBCG1419c compared with BCG are maintained in the antibiotic-less version of this vaccine candidate except changes in production of PDIM. Comparison with previous characterizations conducted by OMICs show that some differences observed in BCGΔBCG1419c compared with BCG are maintained whereas others are dependent on the growth condition employed to culture them.
CRIS-Team Scopus Importer:2024-06-14
Keywords: BCG; c-di-GMP; Cytokines; Lipids; RNASeq; Transcriptomic; Tuberculosis

Compartmentalized immune responses and the local microbiota determine mucosal and systemic immunity against SARS-CoV-2 - Buttenschön, Jonas; Vogt, Stefan; Mattner, Jochen (Cellular & Molecular Immunology, 2022)
CRIS-Team WoS Importer:2022-01-14

Concerted activity of IgG1 antibodies and IL-4/IL-25-dependent effector cells trap helminth larvae in the tissues following vaccination with defined secreted antigens, providing sterile immunity to challenge infection - Hewitson, James P.; Filbey, Kara J.; Bieren, Julia Esser-Von; Camberis, Mali; Schwartz, Christian; Murray, Janice; Reynolds, Lisa A.; Blair, Natalie; Robertson, Elaine; Harcus, Yvonne; Boon, Louis; Huang, Stanley Ching-Cheng; et al. (PLoS Pathogens, 2015)
Over 25% of the world's population are infected with helminth parasites, the majority of which colonise the gastrointestinal tract. However, no vaccine is yet available for human use, and mechanisms of protective immunity remain unclear. In the mouse model of Heligmosomoides polygyrus infection, vaccination with excretory-secretory (HES) antigens from adult parasites elicits sterilising immunity. Notably, three purified HES antigens (VAL-1, -2 and -3) are sufficient for effective vaccination. Protection is fully dependent upon specific IgG1 antibodies, but passive transfer confers only partial immunity to infection, indicating that cellular components are also required. Moreover, immune mice show greater cellular infiltration associated with trapping of larvae in the gut wall prior to their maturation. Intra-vital imaging of infected intestinal tissue revealed a four-fold increase in extravasation by LysM+GFP+ myeloid cells in vaccinated mice, and the massing of these cells around immature larvae. Mice deficient in FcR? chain or C3 complement component remain fully immune, suggesting that in the presence of antibodies that directly neutralise parasite molecules, the myeloid compartment may attack larvae more quickly and effectively. Immunity to challenge infection was compromised in IL-4R?- and IL-25-deficient mice, despite levels of specific antibody comparable to immune wild-type controls, while deficiencies in basophils, eosinophils or mast cells or CCR2-dependent inflammatory monocytes did not diminish immunity. Finally, we identify a suite of previously uncharacterised heat-labile vaccine antigens with homologs in human and veterinary parasites that together promote full immunity. Taken together, these data indicate that vaccine-induced immunity to intestinal helminths involves IgG1 antibodies directed against secreted proteins acting in concert with IL-25-dependent Type 2 myeloid effector populations.
EVALuna2:25873

Conditional IL-4/IL-13-deficient mice reveal a critical role of innate immune cells for protective immunity against gastrointestinal helminths - Oeser, Katharina; Schwartz, Christian; Vöhringer, David (Mucosal Immunology, 2015)
Approximately one-third of the world population is infected with gastrointestinal helminths. Studies in mouse models have demonstrated that the cytokines interleukin (IL)-4 and IL-13 are essential for worm expulsion, but the critical cellular source of these cytokines is poorly defined. Here, we compared the immune response to Nippostrongylus brasiliensis in wild-type, T cell-specific IL-4/IL-13-deficient and general IL-4/IL-13-deficient mice. We show that T cell-derived IL-4/IL-13 promoted T helper 2 (Th2) polarization in a paracrine manner, differentiation of alternatively activated macrophages, and tissue recruitment of innate effector cells. However, innate IL-4/IL-13 played the critical role for induction of goblet cell hyperplasia and secretion of effector molecules like Mucin5ac and RELM? in the small intestine. Surprisingly, T cell-specific IL-4/IL-13-deficient and wild-type mice cleared the parasite with comparable efficiency, whereas IL-4/IL-13-deficient mice showed impaired expulsion. These findings demonstrate that IL-4/IL-13 produced by cells of the innate immune system is required and sufficient to initiate effective type 2 immune responses resulting in protective immunity against N. brasiliensis.
EVALuna2:25865

Confocal laser endomicroscopy for in vivo diagnosis of Clostridium difficile associated colitis - a pilot study. - Günther, Claudia; Neumann, Helmut; Vieth, Michael; Mudter, Jonas; Becker, Christoph; Schoerner, Christoph; Atreya, Raja; et al. (PLoS ONE, 2013)
Clostridium difficile infection (CDI) is one of the most dreaded causes of hospital-acquired diarrhea. Main objective was to investigate whether confocal laser endomicroscopy (CLE) has the capability for in vivo diagnosis of C. difficile associated histological changes. Second objective was to prove the presence of intramucosal bacteria using CLE. 80 patients were prospectively included, 10 patients were diagnosed with CDI based on toxigenic culture. To validate the presence of intramucosal bacteria ex vivo, CLE was performed in pure C. difficile culture; additionally fluorescence in situ hybridization (FISH) was performed. Finally, CLE with fluorescence labelled oligonucleotide probe specific for C. difficile was performed ex vivo in order to prove the presence of bacteria. CLE identified CDI-associated histological changes in vivo (sensitivity and accuracy of 88.9% and 96.3%). In addition, intramucosal bacteria were visualized. The presence of these bacteria could be proven by CLE with labeled, specific molecular C. difficile probe and FISH-technique. Based on comparison between CLE and FISH analyses, sensitivity and specificity for the presence of intramucosal bacteria were 100%. CLE has the potential for in vivo diagnosis of CDI associated colitis. In addition, CLE allowed the detection of intramucosal bacteria in vivo. BACKGROUND METHODS RESULTS CONCLUSION

Contact, Collaboration, and Conflict: Signal Integration of Syk-Coupled C-Type Lectin Receptors - Ostrop, Jenny; Lang, Roland (Journal of Immunology, 2017)
Several spleen tyrosine kinase-coupled C-type lectin receptors (CLRs) have emerged as important pattern recognition receptors for infectious danger. Because encounter with microbial pathogens leads to the simultaneous ligation of several CLRs and TLRs, the signals emanating from different pattern recognition receptors have to be integrated to achieve appropriate biological responses. In this review, we briefly summarize current knowledge about ligand recognition and core signaling by Syk-coupled CLRs. We then address mechanisms of synergistic and antagonistic crosstalk between different CLRs and with TLRs. Emerging evidence suggests that signal integration occurs through 1) direct interaction between receptors, 2) regulation of expression levels and localization, and 3) collaborative or conflicting signaling interference. Accordingly, we aim to provide a conceptual framework for the complex and sometimes unexpected outcome of CLR ligation in bacterial and fungal infection.
EVALuna2:7742

Contribution of MINCLE-SYK Signaling to Activation of Primary Human APCs by Mycobacterial Cord Factor and the Novel Adjuvant TDB - Ostrop, Jenny; Jozefowski, Katrin; Zimmermann, Stephanie; Hofmann, Katharina; Strasser, Erwin; Lepenies, Bernd; Lang, Roland (Journal of Immunology, 2015)
Trehalose-6,6-dimycolate (TDM), the mycobacterial cord factor, is an abundant cell wall glycolipid and major virulence factor of Mycobacterium tuberculosis. Its synthetic analog trehalose-6,6-dibehenate (TDB) is a new adjuvant currently in phase I clinical trials. In rodents, the C-type lectin receptors Mincle and Mcl bind TDB/TDM and activate macrophages and dendritic cells (DC) through the Syk-Card9 pathway. However, it is unknown whether these glycolipids activate human innate immune cells through the same mechanism. We performed in vitro analysis of TDB/TDM-stimulated primary human monocytes, macrophages, and DC; determined C-type lectin receptor expression; and tested the contribution of SYK, MINCLE, and MCL by small interfering RNA knockdown and genetic complementation. We observed a robust chemokine and cytokine release in response to TDB or TDM. MCSF-driven macrophages secreted higher levels of IL-8, IL-6, CCL3, CCL4, and CCL2 after stimulation with TDM, whereas DC responded more strongly to TDB and GM-CSF-driven macrophages were equally responsive to TDB and TDM. SYK kinase and the adaptor protein CARD9 were essential for glycolipid-induced IL-8 production. mRNA expression of MINCLE and MCL was high in monocytes and macrophages, with MINCLE and MCL proteins localized intracellularly under resting conditions. Small interfering RNA-mediated MINCLE or MCL knockdown caused on average reduced TDB- or TDM-induced IL-8 production. Conversely, retroviral expression in murine Mincle-deficient DC revealed that human MINCLE, but not MCL, was sufficient to confer responsiveness to TDB/TDM. Our study demonstrates that SYK-CARD9 signaling plays a key role in TDB/TDM-induced activation of innate immune cells in man as in mouse, likely by engagement of MINCLE.
EVALuna2:7676

Controlled human malaria infection with Plasmodium falciparum demonstrates impact of naturally acquired immunity on virulence gene expression - Bachmann, Anna; Bruske, Ellen; Krumkamp, Ralf; Turners, Louise; Wichers, J. Stephan; Petter, Michaela; Held, Jana; Duffy, Michael F.; Sim, B. Kim Lee; Hoffman, Stephen L.; Kremsner, Peter G.; Lell, Bertrand; et al. (PLoS Pathogens, 2019)
The pathogenesis of Plasmodium falciparum malaria is linked to the variant surface antigen PfEMP1, which mediates tethering of infected erythrocytes to the host endothelium and is encoded by approximately 60 var genes per parasite genome. Repeated episodes of malaria infection result in the gradual acquisition of protective antibodies against PfEMP1 variants. The antibody repertoire is believed to provide a selective pressure driving the clonal expansion of parasites expressing unrecognized PfEMP1 variants, however, due to the lack of experimental in vivo models there is only limited experimental evidence in support of this concept. To get insight into the impact of naturally acquired immunity on the expressed var gene repertoire early during infection we performed controlled human malaria infections of 20 adult African volunteers with life-long malaria exposure using aseptic, purified, cryopreserved P. falciparum sporozoites (Sanaria PfSPZ Challenge) and correlated serological data with var gene expression patterns from ex vivo parasites. Among the 10 African volunteers who developed patent infections, individuals with low antibody levels showed a steep rise in parasitemia accompanied by broad activation of multiple, predominantly subtelomeric var genes, similar to what we previously observed in naïve volunteers. In contrast, individuals with intermediate antibody levels developed asymptomatic infections and the ex vivo parasite populations expressed only few var gene variants, indicative of clonal selection. Importantly, in contrast to parasites from naïve volunteers, expression of var genes coding for endothelial protein C receptor (EPCR)-binding PfEMP1 that are associated with severe childhood malaria was rarely detected in semi-immune adult African volunteers. Moreover, we followed var gene expression for up to six parasite replication cycles and demonstrated for the first time in vivo a shift in the dominant var gene variant. In conclusion, our data suggest that P. falciparum activates multiple subtelomeric var genes at the onset of blood stage infection facilitating rapid expansion of parasite clones which express PfEMP1 variants unrecognized by the host's immune system, thus promoting overall parasite survival in the face of host immunity.
CRIS-Team Scopus Importer:2019-08-20

Control of immune cell signaling by the immuno-metabolite itaconate - Lang, Roland; Siddique, Md Nur A Alam (Frontiers in Immunology, 2024)
Immune cell activation triggers signaling cascades leading to transcriptional reprogramming, but also strongly impacts on the cell’s metabolic activity to provide energy and biomolecules for inflammatory and proliferative responses. Macrophages activated by microbial pathogen-associated molecular patterns and cytokines upregulate expression of the enzyme ACOD1 that generates the immune-metabolite itaconate by decarboxylation of the TCA cycle metabolite cis-aconitate. Itaconate has anti-microbial as well as immunomodulatory activities, which makes it attractive as endogenous effector metabolite fighting infection and restraining inflammation. Here, we first summarize the pathways and stimuli inducing ACOD1 expression in macrophages. The focus of the review then lies on the mechanisms by which itaconate, and its synthetic derivatives and endogenous isomers, modulate immune cell signaling and metabolic pathways. Multiple targets have been revealed, from inhibition of enzymes to the post-translational modification of many proteins at cysteine or lysine residues. The modulation of signaling proteins like STING, SYK, JAK1, RIPK3 and KEAP1, transcription regulators (e.g. Tet2, TFEB) and inflammasome components (NLRP3, GSDMD) provides a biochemical basis for the immune-regulatory effects of the ACOD1-itaconate pathway. While the field has intensely studied control of macrophages by itaconate in infection and inflammation models, neutrophils have now entered the scene as producers and cellular targets of itaconate. Furthermore, regulation of adaptive immune responses by endogenous itaconate, as well as by exogenously added itaconate and derivatives, can be mediated by direct and indirect effects on T cells and antigen-presenting cells, respectively. Taken together, research in ACOD1-itaconate to date has revealed its relevance in diverse immune cell signaling pathways, which now provides opportunities for potential therapeutic or preventive manipulation of host defense and inflammation.
CRIS-Team Scopus Importer:2024-03-29
Keywords: ACOD1; IRG1; itaconate; macrophages; metabolism; post-translational modification; signal transduction; transport

Conventional non-woven vs. novel nano FFP2 masks - a competetive study on the filtration performance after various types of conditions - Halamicek, Robin; Wiesmann, Carolin; Kröner, Richard; Bogdan, Christian; Schubert, Dirk W. (Nordic Polymer Days, 2023)
Filtering face piece (FFP) masks, categorized by different filtration efficiency standards, are mandatory to achieve an efficient protection against viruses like the severe acute respirato- ry syndrome coronavirus type 2 (SARS-CoV-2) [1]. They conventionally comprise an electro- statically treated melt blown non-woven layer as the main filtering medium if the standard is FFP2. However, novel nanofibrous masks with the same standard are arising on the market, promising a higher safety alongside a high- er better wearing comfort – but for a higher unit price. This study compared different mask models from both mask types regard- ing their filtration performance after various types of conditions (change of temperature and air humidity, exposure to isopropyl al- cohol (IPA) and an autoclave sterilization) to evaluate the superior FFP2 mask type. Due to the absence of prior electrostatic treatment, the nanofibrous masks did not show a signi- ficant change in filtration efficiency when exposed to IPA, unlike to the melt blown non-woven masks. However, most melt blown type masks maintained a sufficient filtration efficiency after all other treatments and also at the untreated condition – with even better results than the nanofibrous competitors. This applied particulary for the capacity to filter smallest particles/droplets with a size of around 0.1 μm, which is below the range of typical filtering standards but important for the retention of virally contaminated nano- aerosols or unattached viruses [2-4]. Based on their better filtration performance, lower price and potential reusability, it can be concluded that conventional melt blown non-woven masks with an electrostatic treatment are the preferable FFP2 mask type for a protective purpo

Correction to: Diagnostic performance of four SARS-CoV-2 antibody assays in patients with COVID-19 or with bacterial and non-SARS-CoV-2 viral respiratory infections (European Journal of Clinical Microbiology & Infectious Diseases, (2021), 10.1007/s10096-021-04285-4) - Huber, Timo; Steininger, Philipp; Irrgang, Pascal; Korn, Klaus; Tenbusch, Matthias; Diesch, Katharina; Achenbach, Susanne; Kremer, Andreas; Werblow, Marissa; Vetter, Marcel; Bogdan, Christian; Held, Jürgen (European Journal of Clinical Microbiology & Infectious Diseases, 2021)
In the originally published version of the article, captions of Figures 1, 2, 3, 4, and 5 have missing figure denominations. The figures are presented here with correct captions. Layout adjustments are also made to Tables 2-5 for readability. The original article has been corrected. (Figure presented.).
CRIS-Team Scopus Importer:2021-07-30

Corrigendum: Dusp16 Deficiency Causes Congenital Obstructive Hydrocephalus and Brain Overgrowth by Expansion of the Neural Progenitor Pool - Zega, Ksenija; Jovanovic, Vukasin M.; Vitic, Zagorka; Niedzielska, Magdalena; Knaapi, Laura; Jukic, Marin M.; Partanen, Juha; Friedel, Roland H.; Lang, Roland; Brodski, Claude (Frontiers in Molecular Neuroscience, 2018)
[This corrects the article on p. 372 in vol. 10, PMID: 29170629.].
EVALuna2:36431

Corrigendum to: “Resistance to antibacterial therapy in pediatric febrile urinary tract infectionsda single-center analysis” [J Pediatr Urol 16 (2020) 71–79] (Journal of Pediatric Urology (2020) 16(1) (71–79), (S1477513119303389), (10.1016/j.jpurol.2019.10.018)) - Raupach, Thomas; Held, Jürgen; Prokosch, Hans-Ulrich; Rascher, Wolfgang; Zierk, Jakob (Journal of Pediatric Urology, 2022)
In order to fulfil the requirements of the doctoral office of the Friedrich-Alexander-University Erlangan-Nuremberg (FAU), the following updates have been made to the abovementioned article: Affiliation ‘a’ now reads as: Department of Pediatrics and Adolescent Medicine, Friedrich-Alexander-University Erlangen-Nuremberg (FAU), Erlangen, Germany. The following has been added to the Acknowledgements: The present work was performed in fulfilment of the requirements for obtaining the degree “Dr. med. (Doctor medicinae) at the Friedrich-Alexander University Erlangen-Nuremberg (FAU)”.
CRIS-Team Scopus Importer:2024-12-16

Cortactin: A major cellular target of the gastric carcinogen Helicobacter pylori - Sharafutdinov, Irshad; Backert, Steffen; Tegtmeyer, Nicole (Cancers, 2020)
Cortactin is an actin binding protein and actin nucleation promoting factor regulating cytoskeletal rearrangements in nearly all eukaryotic cell types. From this perspective, cortactin poses an attractive target for pathogens to manipulate a given host cell to their own benefit. One of the pathogens following this strategy is Helicobacter pylori, which can cause a variety of gastric diseases and has been shown to be the major risk factor for the onset of gastric cancer. During infection of gastric epithelial cells, H. pylori hijacks the cellular kinase signaling pathways, leading to the disruption of key cell functions. Specifically, by overruling the phosphorylation status of cortactin, H. pylori alternates the activity of molecular interaction partners of this important protein, thereby manipulating the performance of actin-cytoskeletal rearrangements and cell movement. In addition, H. pylori utilizes a unique mechanism to activate focal adhesion kinase, which subsequently prevents host epithelial cells from extensive lifting from the extracellular matrix in order to achieve chronic infection in the human stomach.
CRIS-Team Scopus Importer:2020-02-07
Keywords: Abl; CagA; CagPAI; FAK; Helicobacter pylori; SHP2; Signaling; Src; T4SS; Type IV secretion; Tyrosine kinases

Cortactin promotes effective ags cell scattering by helicobacter pylori caga, but not cellular vacuolization and apoptosis induced by the vacuolating cytotoxin vaca - Sharafutdinov, Irshad; Knorr, Jakob; Soltan Esmaeili, Delara; Backert, Steffen; Tegtmeyer-Backert, Nicole (Pathogens, 2022)
Cortactin is an actin-binding protein and actin-nucleation promoting factor regulating cytoskeletal rearrangements in eukaryotes. Helicobacter pylori is a gastric pathogen that exploits cortactin to its own benefit. During infection of gastric epithelial cells, H. pylori hijacks multiple cellular signaling pathways, leading to the disruption of key cell functions. Two bacterial virulence factors play important roles in this scenario, the vacuolating cytotoxin VacA and the translocated effector protein CagA of the cag type IV secretion system (T4SS). Specifically, by overruling the phosphorylation status of cortactin, H. pylori alternates the activity of molecular interaction partners of this important protein, thereby manipulating the performance of cytoskeletal rearrangements, endosomal trafficking and cell movement. Based on shRNA knockdown and other studies, it was previously reported that VacA utilizes cortactin for its cellular uptake, intracellular travel and induction of apoptosis by a mitochondria-dependent mechanism, while CagA induces cell scattering, motility and elongation. To investigate the role of cortactin in these phenotypes in more detail, we produced a complete knockout mutant of cortactin in the gastric adenocarcinoma cell line AGS by CRISPR-Cas9. These cells were infected with H. pylori wild-type or various isogenic mutant strains. Unexpectedly, cortactin deficiency did not prevent the uptake and formation of VacA-dependent vacuoles, nor the induction of apoptosis by internalized VacA, while the induction of T4SS-and CagA-dependent AGS cell movement and elongation were strongly reduced. Thus, we provide evidence that cortactin is required for the function of internalized CagA, but not VacA.
CRIS-Team Scopus Importer:2022-01-07
Keywords: Annexin V; Apoptosis; CagA; CagE; Caspase-3; Cell scattering; Cortactin; FlaA; H. pylori; T4SS; VacA

Corynebacterium diphteriae invasion-associated protein (DIP1281) is involved in cell surface organization, adhesion and internalization in epithelial cells - Ott, Lisa; Höller, Martina; Gerlach, Roman G.; Hensel, Michael; Rheinlaender, Johannes; Schäffer, Tilman; Burkovski, Andreas (BMC Microbiology, 2010)
Corynebacterium diphtheriae, the causative agent of diphtheria, is well-investigated in respect to toxin production, while little is known about C. diphtheriae factors crucial for colonization of the host. In this study, we investigated the function of surface-associated protein DIP1281, previously annotated as hypothetical invasion-associated protein. Microscopic inspection of DIP1281 mutant strains revealed an increased size of the single cells in combination with an altered less club-like shape and formation of chains of cells rather than the typical V-like division forms or palisades of growing C. diphtheriae cells. Cell viability was not impaired. Immuno-fluorescence microscopy, SDS-PAGE and 2-D PAGE of surface proteins revealed clear differences of wild-type and mutant protein patterns, which were verified by atomic force microscopy. DIP1281 mutant cells were not only altered in shape and surface structure but completely lack the ability to adhere to host cells and consequently invade these. Our data indicate that DIP1281 is predominantly involved in the organization of the outer surface protein layer rather than in the separation of the peptidoglycan cell wall of dividing bacteria. The adhesion- and invasion-negative phenotype of corresponding mutant strains is an effect of rearrangements of the outer surface. BACKGROUND RESULTS CONCLUSIONS
UnivIS-Import:2015-03-09:Pub.2010.nat.dphy.IAP.LAP.coryne

Coxiella burnetii Affects HIF1 alpha Accumulation and HIF1 alpha Target Gene Expression - Hayek, Inaya; Szperlinski, Manuela; Lührmann, Anja (Frontiers in Cellular and Infection Microbiology, 2022)
HIF1 alpha is an important transcription factor regulating not only cellular responses to hypoxia, but also anti-infective defense responses. We recently showed that HIF1 alpha hampers replication of the obligate intracellular pathogen Coxiella burnetii which causes the zoonotic disease Q fever. Prior to development of chronic Q fever, it is assumed that the bacteria enter a persistent state. As HIF1 alpha and/or hypoxia might be involved in the induction of C. burnetii persistence, we analyzed the role of HIF1 alpha and hypoxia in the interaction of macrophages with C. burnetii to understand how the bacteria manipulate HIF1 alpha stability and activity. We demonstrate that a C. burnetii-infection initially induces HIF1 alpha stabilization, which decreases then over the course of an infection. This reduction depends on bacterial viability and a functional type IV secretion system (T4SS). While neither the responsible T4SS effector protein(s) nor the molecular mechanism leading to this partial HIF1 alpha destabilization have been identified, our results demonstrate that C. burnetii influences the expression of HIF1 alpha target genes in multiple ways. Therefore, a C. burnetii infection promotes HIF1 alpha-mediated upregulation of several metabolic target genes; affects apoptosis-regulators towards a more pro-apoptotic signature; and under hypoxic conditions, shifts the ratio of the inflammatory genes analyzed towards a pro-inflammatory profile. Taken together, C. burnetii modulates HIF1 alpha in a still elusive manner and alters the expression of multiple HIF1 alpha target genes.
CRIS-Team WoS Importer:2022-07-08

Coxiella burnetiias a useful tool to investigate bacteria-friendly host cell compartments - Pechstein, Julian; Schulze-Luehrmann, Jan; Lührmann, Anja (International Journal of Medical Microbiology, 2017)
Coxiella burnetii is an obligate intracellular and airborne pathogen which can cause the zoonotic disease Q fever. After inhalation of contaminated aerosols alveolar macrophages are taking up C. burnetii into a phagosome. This phagosome matures to a very large vacuole called the C. burnetii-containing vacuole (CCV). Host endogenous and bacterial driven processes lead to the biogenesis of this unusual compartment, which resembles partially a phagolysosome. However, there are several important differences to the classical phagolysosome, which are crucial for the ability of C. burnetii to replicate intracellularly and depend on a functional type IV secretion system (T4SS). The T4SS delivers effector proteins into the host cell cytoplasm to redirect intracellular processes, leading to the establishment of a microenvironment allowing bacterial replication. This article summarizes the current knowledge of the microenvironment permissive for C. burnetii replication.
EVALuna2:7729

Coxiella burnetii: Ein Übersichtsartikel mit Fokus auf das Infektionsgeschehen in deutschen Schaf- und Ziegenherden - Bauer, Benjamin U.; Runge, Martin; Campe, Amely; Henning, Klaus; Mertens-Scholz, Katja; Boden, Katharina; Sobotta, Katharina; Frangoulidis, Dimitrios; Knittler, Michael R.; Matthiesen, Svea; Berens, Christian; Lührmann, Anja; et al. (Berliner und Münchener Tierärztliche Wochenschrift, 2020)
Q fever is a worldwide zoonosis caused by Coxiella (C.) burnetii. This bacterium is shed in huge amounts with birth products from infected small ruminants. Shedding also occurs via milk, faeces and urine. The main route of infection for humans and animals is via inhalation of contaminated aerosols. Apart from wind, many other meteorological conditions influence pathogen dissemination. Also, Dermacentor spp. and Ixodes ricinus ticks could play a role in transmission. Infections in goats can lead to abortion during the last trimester of pregnancy. In comparison to goats, C. burnetii seems to cause less abortion in sheep. In humans, 40% of infected persons show flu-like symptoms such as fever and headaches. Up to 5% of all infected people can develop chronic Q fever, which often manifests as endocarditis. Since 2000, several human Q fever epidemics occurred in Germany with up to 331 reported human infections. The source of infection was mostly associated with parturition of sheep. As the number of goats has increased in Germany over the last couple of years, Q fever cases connected to this species will probably increase in the future. For the detection of C. burnetii in animals, ELISA and/or PCR are routinely used. With Multiple Loci Variable Number of Tandem Repeats Analysis (MLVA/VNTR) it is possible to genotype isolates. MLVA-Cluster A was detected in samples from small ruminants, Cluster C is associated with cattle. Treatment with oxytetracycline is ineffective for the control of Q fever in animals, whereas the use of an inactivated Phase I whole cell vaccine reduces shedding and therefore the risk of transmission. Many disinfectants are ineffective against C. burnetii because of its high tenacity.
CRIS-Team Scopus Importer:2020-07-31
Keywords: Coxiellosis; Q fever; Small ruminants; Zoonosis

Coxiella burnetii-infected NK cells release infectious bacteria by degranulation - Matthiesen, Svea; Zaeck, Luca; Franzke, Kati; Jahnke, Rico; Fricke, Charlie; Mauermeir, Michael; Finke, Stefan; Lührmann, Anja; Knittler, Michael R. (Infection and Immunity, 2020)
Natural killer (NK) cells are critically involved in the early immune response against various intracellular pathogens, including Coxiella burnetii and Chlamydia psittaci. Chlamydia-infected NK cells functionally mature, induce cellular immunity, and protect themselves by killing the bacteria in secreted granules. Here, we report that infected NK cells do not allow intracellular multiday growth of Coxiella, as is usually observed in other host cell types. C. burnetii-infected NK cells display maturation and gamma interferon (IFN-) secretion, as well as the release of Coxiella-containing lytic granules. Thus, NK cells possess a potent program to restrain and expel different types of invading bacteria via degranulation. Strikingly, though, in contrast to Chlamydia, expulsed Coxiella organisms largely retain their infectivity and, hence, escape the cell-autonomous self-defense mechanism in NK cells.
CRIS-Team Scopus Importer:2020-11-06
Keywords: Cell-autonomous immunity; Chlamydia psittaci; Coxiella burnetii; NK cells

CreER(T2) expression from within the c-Kit gene locus allows efficient inducible gene targeting in and ablation of mast cells - Heger, Klaus; Seidler, Barbara; Vahl, J. Christoph; Schwartz, Christian; Kober, Maike; Klein, Sabine; Vöhringer, David; Saur, Dieter; Schmidt-Supprian, Marc (European Journal of Immunology, 2014)
Mast cells are abundantly situated at contact sites between the body and its environment, such as the skin and, especially during certain immune responses, at mucosal surfaces. They mediate allergic reactions and degrade toxins as well as venoms. However, their roles during innate and adaptive immune responses remain controversial and it is likely that major functions remain to be discovered. Recent developments in mast cell-specific conditional gene targeting in the mouse promise to enhance our understanding of these fascinating cells. To complete the genetic toolbox to study mast cell development, homeostasis and function, it is imperative to inducibly manipulate their gene expression. Here, we report the generation of a novel knock-in mouse line expressing a tamoxifen-inducible version of the Cre recombinase from within the endogenous c-Kit locus. We demonstrate highly efficient and specific inducible expression of a fluorescent reporter protein in mast cells both in vivo and in vitro. Furthermore, induction of diphtheria toxin A expression allowed selective and efficient ablation of mast cells at various anatomical locations, while other hematopoietic cells remain unaffected. This novel mouse strain will hence be very valuable to study mast cell homeostasis and how specific genes influence their functions in physiology and pathology.
EVALuna2:25867

CRISPR-Cas9, the new kid on the block of fungal molecular biology - Krappmann, Sven (Medical Mycology, 2017)
Research on fungal pathogens with the aim to identify virulence determinants strictly relies on the generation of defined, recombinant strains, a task that is executed by means of a sophisticated molecular biology toolbox. Recent developments in fungal genome engineering have opened a new frontier by implementing the CRISPR-Cas9 technology, based on expression of the Cas9 endonuclease that is loaded by a single guiding RNA (sgRNA) molecule to target a defined site in the recipient genome. This novel approach has been adapted successfully to engineer fungal genomes, among them the one of the human-pathogenic mould Aspergillus fumigatus Implementation of the required components was achieved by various means that differ with respect to expression of the Cas9 enzyme and sgRNA delivery. Validation of CRISPR-Cas9-mediated mutagenesis could be executed by targeting selected candidate genes of A. fumigatus to provide a promising perspective for screening and multiplexing approaches to scrutinize the virulome of this opportunistic fungal pathogen in a comprehensive manner, such as by analyzing genetic polymorphisms or the function of gene families.
EVALuna2:7747

Current research and unmet needs in allergy and immunology in Germany: report presented by the DGfI and DGAKI task force Allergy & Immunology - Albrecht, Melanie; Schaub, Bianca; Gilles, Stefanie; Koehl, Jorg; Altrichter, Sabine; Vöhringer, David; Spillner, Edzard; Ehlers, Marc; Joensson, Friederike; Loser, Karin; Mayer, Johannes U.; Roesner, Lennart M.; et al. (European Journal of Immunology, 2022)
CRIS-Team WoS Importer:2022-06-17

Cutting edge: Mincle is essential for recognition and adjuvanticity of the mycobacterial cord factor and its synthetic analog trehalose-dibehenate. - Schoenen, Hanne; Bodendorfer, Barbara; Hitchens, Kelly; Manzanero, Silvia; Werninghaus, Kerstin; Nimmerjahn, Falk; Agger, Else Marie; Stenger, Steffen; Andersen, Peter; Ruland, Juergen; Brown, Gordon D.; Wells, Christine; et al. (Journal of Immunology, 2010)
The mycobacterial cord factor trehalose-6,6-dimycolate (TDM) and its synthetic analog trehalose-6,6-dibehenate (TDB) are potent adjuvants for Th1/Th17 vaccination that activate Syk-Card9 signaling in APCs. In this study, we have further investigated the molecular mechanism of innate immune activation by TDM and TDB. The Syk-coupling adapter protein FcRgamma was essential for macrophage activation and Th17 adjuvanticity. The FcRgamma-associated C-type lectin receptor Mincle was expressed in macrophages and upregulated by TDM and TDB. Recombinant Mincle-Fc fusion protein specifically bound to the glycolipids. Genetic ablation of Mincle abolished TDM/TDB-induced macrophage activation and induction of T cell immune responses to a tuberculosis subunit vaccine. Macrophages lacking Mincle or FcRgamma were impaired in the inflammatory response to Mycobacterium bovis bacillus Calmette-Guérin. These results establish that Mincle is a key receptor for the mycobacterial cord factor and controls the Th1/Th17 adjuvanticity of TDM and TDB.
UnivIS-Import:2015-03-09:Pub.2010.med.IKMI.LHMMIPDR.cuttin

Cutting edge: TNF is essential for mycobacteria-induced MINCLE expression, macrophage activation, and Th17 adjuvanticity - Schick, Judith; Schäfer, Johanna; Alexander, Christian; Dichtl, Stefanie; Murray, Peter J.; Christensen, Dennis; Sorg, Ursula; Pfeffer, Klaus; Schleicher, Ulrike; Lang, Roland (Journal of Immunology, 2020)
TNF blockade is a successful treatment for human autoimmune disorders like rheumatoid arthritis and inflammatory bowel disease yet increases susceptibility to tuberculosis and other infections. The C-type lectin receptors (CLR) MINCLE, MCL, and DECTIN-2 are expressed on myeloid cells and sense mycobacterial cell wall glycolipids. In this study, we show that TNF is sufficient to upregulate MINCLE, MCL, and DECTIN-2 in macrophages. TNF signaling through TNFR1 p55 was required for upregulation of these CLR and for cytokine secretion in macrophages stimulated with the MINCLE ligand trehalose-6,6-dibehenate or infected with Mycobacterium bovis bacillus Calmette-Guérin. The Th17 response to immunization with the MINCLE dependent adjuvant trehalose-6,6-dibehenate was specifically abrogated in TNF-deficient mice and strongly attenuated by TNF blockade with etanercept. Together, interference with production or signaling of TNF antagonized the expression of DECTIN-2 family CLR, thwarting vaccine responses and possibly increasing infection risk.
CRIS-Team Scopus Importer:2020-07-31

Cytokine-dependent regulation of dendritic cell differentiation in the splenic microenvironment - Globisch, Theresa; Steiner, Nancy; Fuelle, Lorenz; Lukacs-Kornek, Veronika; Degrandi, Daniel; Dresing, Philipp; Alferink, Judith; Lang, Roland; Pfeffer, Klaus; Beyer, Marc; Weighardt, Heike; Kurts, Christian; et al. (European Journal of Immunology, 2014)
The DC-derived chemokine CCL17, a ligand of CCR4, has been shown to promote various inflammatory diseases such as atopic dermatitis, atherosclerosis, and inflammatory bowel disease. Under steady-state conditions, and even after systemic stimulation with LPS, CCL17 is not expressed in resident splenic DCs as opposed to CD8?(-) CD11b(+) LN DCs, which produce large amounts of CCL17 in particular after maturation. Upon systemic NKT cell activation through ?-galactosylceramide stimulation however, CCL17 can be upregulated in both CD8?(-) and CD8?(+) splenic DC subsets and enhances cross-presentation of exogenous antigens. Based on genome-wide expression profiling, we now show that splenic CD11b(+) DCs are susceptible to IFN-?-mediated suppression of CCL17, whereas LN CD11b(+) CCL17(+) DCs downregulate the IFN-?R and are much less responsive to IFN-?. Under inflammatory conditions, particularly in the absence of IFN-? signaling in IFN-?RKO mice, CCL17 expression is strongly induced in a major proportion of splenic DCs by the action of GM-CSF in concert with IL-4. Our findings demonstrate that the local cytokine milieu and differential cytokine responsiveness of DC subsets regulate lymphoid organ specific immune responses at the level of chemokine expression.
EVALuna2:7641

Cytokine-Mediated Regulation of ARG1 in Macrophages and Its Impact on the Control of Salmonella enterica Serovar Typhimurium Infection - Brigo, Natascha; Pfeifhofer-Obermair, Christa; Tymoszuk, Piotr; Demetz, Egon; Engl, Sabine; Barros-Pinkelnig, Marina; Dichtl, Stefanie; Fischer, Christine; Valente De Souza, Lara; Petzer, Verena; Von Raffay, Laura; Hilbe, Richard; et al. (Cells, 2021)
Arginase 1 (ARG1) is a cytosolic enzyme that cleaves L-arginine, the substrate of inducible nitric oxide synthase (iNOS), and thereby impairs the control of various intracellular pathogens. Herein, we investigated the role of ARG1 during infection with Salmonella enterica serovar Typhimurium (S.tm). To study the impact of ARG1 on Salmonella infections in vitro, bone marrow-derived macrophages (BMDM) from C57BL/6N wild-type, ARG1-deficient Tie2Cre(+/-)ARG1(fl/fl) and NRAMP(G169) C57BL/6N mice were infected with S.tm. In wild-type BMDM, ARG1 was induced by S.tm and further upregulated by the addition of interleukin (IL)-4, whereas interferon-gamma had an inhibitory effect. Deletion of ARG1 did not result in a reduction in bacterial numbers. In vivo, Arg1 mRNA was upregulated in the spleen, but not in the liver of C57BL/6N mice following intraperitoneal S.tm infection. The genetic deletion of ARG1 (Tie2Cre(+/-)ARG1(fl/fl)) or its pharmacological inhibition with CB-1158 neither affected the numbers of S.tm in spleen, liver and blood nor the expression of host response genes such as iNOS, IL-6 or tumour necrosis factor (TNF). Furthermore, ARG1 was dispensable for pathogen control irrespective of the presence or absence of the phagolysosomal natural resistance-associated macrophage protein 1 (NRAMP1). Thus, unlike the detrimental function of ARG1 seen during infections with other intraphagosomal microorganisms, ARG1 did not support bacterial survival in systemic salmonellosis, indicating differential roles of arginine metabolism for host immune response and microbe persistence depending on the type of pathogen.
CRIS-Team WoS Importer:2021-08-06

DC subset–specific induction of T cell responses upon antigen uptake via Fcγ receptors in vivo - Lehmann, Christian; Baranska, Anna; Heidkamp, Gordon Frederik; Heger, Lukas; Neubert, Kirsten; Lühr, Jennifer; Hoffmann, Alana; Reimer, Katharina; Brückner, Christin; Beck, Simone; Seeling, Michaela; Kießling, Melissa; et al. (Journal of Experimental Medicine, 2017)
Dendritic cells (DCs) are efficient antigen-presenting cells equipped with various cell surface receptors for the direct or indirect recognition of pathogenic microorganisms. Interestingly, not much is known about the specific expression pattern and function of the individual activating and inhibitory Fcγ receptors (FcγRs) on splenic DC subsets in vivo and how they contribute to the initiation of T cell responses. By targeting antigens to select activating and the inhibitory FcγR in vivo, we show that antigen uptake under steady-state conditions results in a short-term expansion of antigen-specific T cells, whereas under inflammatory conditions especially, the activating FcγRIV is able to induce superior CD4+ and CD8+ T cell responses. Of note, this effect was independent of FcγR intrinsic activating signaling pathways. Moreover, despite the expression of FcγRIV on both conventional splenic DC subsets, the induction of CD8+ T cell responses was largely dependent on CD11c+CD8+ DCs, whereas CD11c+CD8− DCs were critical for priming CD4+ T cell responses.<br
Keywords: Infectious disease and host defense; Innate immunity and inflammation; Tolerance

Deficiency of the microprocessor component DGCR8 impairs macrophage growth and unleashes IFN-dependent gene expression in response to mycobacteria - Killy, Barbara; Bodendorfer, B.; Pracht, Katharina; Jäck, Hans-Martin; Lang, Roland (EUROPEAN JOURNAL OF IMMUNOLOGY, 2019)
CRIS-Team WoS Importer:2019-10-08

Defining metaniches in the oral cavity according to their microbial composition and cytokine profile - Seidel, Corinna Lesley; Gerlach, Roman; Wiedemann, Patrick; Weider, Matthias; Rodrian, Gabriele; Hader, Michael; Frey, Benjamin; Gaipl, Udo; Bozec, Aline; Cieplik, Fabian; Kirschneck, Christian; Bogdan, Christian; et al. (International Journal of Molecular Sciences, 2020)
The human oral microbiota consists of over 700 widespread taxa colonizing the oral cavity in several anatomically diverse oral niches. Lately, sequencing of the 16S rRNA genes has become an acknowledged, culture-independent method to characterize the oral microbiota. However, only a small amount of data are available concerning microbial differences between oral niches in periodontal health and disease. In the context of periodontitis, the cytokine expression in the gingival crevicular fluid has been studied in detail, whereas little is known about the cytokine profile in hard and soft tissue biofilms. In order to characterize oral niches in periodontal health, the oral microbiota and cytokine pattern were analyzed at seven different sites (plaque (P), gingival crevicular fluid (GCF), saliva (S), tongue (T), hard palate (HP), cheek (C) and sublingual area (U)) of 20 young adults using next-generation sequencing and multiplex immunoassays. Site-specific microbial compositions were detected, which clustered into three distinct metaniches (“P-GCF”, “S-T-HP” and “C-U”) and were associated with niche-/metaniche-specific cytokine profiles. Our findings allow the definition of distinct metaniches according to their microbial composition, partly reflected by their cytokine profile, and provide new insights into microenvironmental similarities between anatomical diverse oral niches.
CRIS-Team Scopus Importer:2020-11-20
Keywords: Cytokine profile; Metaniches; Multiplex immunoassay; Next-generation sequencing; Oral biofilms and fluids; Oral microbiota; Oral niches

Defying Death - How Coxiella burnetii Copes with Intentional Host Cell Suicide - Cordsmeier, Arne; Wagner, Nicole; Lührmann, Anja; Berens, Christian (The Yale Journal of Biology and Medicine, 2019)
The obligate intracellular pathogen Coxiella burnetii is the causative agent of the worldwide zoonotic disease Q fever. This Gram-negative bacterium infects macrophages where it establishes a replicative niche in an acidic and phagolysosome-like vacuole. Establishing and maintaining the niche requires a functional type IV secretion system (T4SS dagger) which translocates multiple effector proteins into the host cell. These effector proteins act by manipulating diverse cellular processes allowing the bacterium to establish an infection and complete its complex biphasic developmental cycle. The lengthy nature of this life cycle suggests that C. burnetii has to successfully deal with cellular defense processes. Cell death is one mechanism infected cells frequently utilize to control or to at least minimize the impact of an infection. To date, four effector proteins have been identified in C. burnetii, which interfere with the induction of cell death. Three, AnkG, CaeA, and CaeB, affect intrinsic apoptosis, CaeA additionally extrinsic apoptosis. The proteins target different steps of the apoptotic pathway and are not conserved among isolates suggesting redundancy as an important feature of cell death inhibition. The fourth effector protein, IcaA, interferes with the non-canonical pathway of pyroptosis, an important inflammatory cell death pathway for controlling infectious disease. Autophagy is relevant for the C. burnetii life-cycle, but to which extent autophagic cell death is a factor in bacterial survival and proliferation is still not clear. To convincingly understand how bacterial manipulation of autophagy affects cell death either directly or indirectly will require further experiments. Collectively, C. burnetii modulates the extrinsic and intrinsic apoptotic pathways and non-canonical pyroptosis to inhibit host cell death, thereby providing a stable, intracellular niche for the course of the pathogen's infectious cycle.
CRIS-Team WoS Importer:2020-01-07

Dendritic Cells Are Dispensable for T Cell Priming and Control of Acute Lymphocytic Choriomeningitis Virus Infection - Hilpert, Cornelia; Sitte, Selina; Matthies, Alexander Oliver; Vöhringer, David (Journal of Immunology, 2016)
Dendritic cells (DCs) are considered to be the major APCs with potent activity for priming of naive CD4 and CD8 T cells. However, T cell priming can also be achieved by other APCs including macrophages, B cells, or even nonhematopoietic cell types. Systemic low-dose infection of mice with lymphocytic choriomeningitis virus (LCMV) results in massive expansion of virus-specific CD4 and CD8 T cells. To determine the role of DCs as APCs and source of type I IFNs in this infection model, we used ?DC mice in which DCs are constitutively ablated because of expression of the diphtheria toxin ? subunit within developing DCs. ?DC mice showed lower serum concentrations of IFN-? and IL-12p40, but normal IFN-? levels during the first days postinfection. No differences were found for proliferation of transferred TCR-transgenic cells during the early phase of infection, suggesting that T cell priming occurred with the same efficiency in wild-type and ?DC mice. Expansion and cytokine expression of endogenous LCMV-specific T cells was comparable between wild-type and ?DC mice during primary infection and upon rechallenge of memory mice. In both strains of infected mice the viral load was reduced below the limit of detection with the same kinetic. Further, germinal center formation and LCMV-specific Ab responses were not impaired in ?DC mice. This indicates that DCs are dispensable as APCs for protective immunity against LCMV infectio
EVALuna2:25882

Dendritic Cells Control Regulatory T Cell Function Required for Maintenance of Intestinal Tissue Homeostasis - Hilpert, Cornelia; Sitte, Selina; Arnold, Harald; Lehmann, Christian; Dudziak, Diana; Mattner, Jochen; Vöhringer, David (Journal of Immunology, 2019)
Dendritic cells (DCs) together with regulatory T cells (Tregs) are essential mediators of immune homeostasis. Disruption of function or frequency of either cell type can lead to fatal autoimmunity. We previously described that mice constitutively lacking DCs (∆DC) develop autoimmunity characterized by reduced body weight, autoantibodies, and pronounced intestinal inflammation. In this study, we show that lack of DCs leads to an altered gene expression profile in peripheral but not thymic Tregs with increased expression of inhibitory receptors. The suppressive function of Tregs from ΔDC mice was impaired in T cell cocultures. In a model of transfer colitis, Tregs from ∆DC mice were only functional in the presence of DCs in recipient mice. Lack of MHC class II on DCs also resulted in upregulation of inhibitory receptors on Tregs, reduced body weight, and elevated serum IgA levels. Further analysis of the IgA response revealed an expansion of IgA+ germinal center B cells and plasma cells in mesenteric lymph nodes and more IgA-coated commensal bacteria in feces of ∆DC mice. Thus, we show a critical role for DCs to establish intestinal homeostasis by regulating Treg function for prevention of spontaneous inflammation.
CRIS-Team Scopus Importer:2019-11-29

Detailed β-(1→3)-D-glucan and mannan antigen kinetics in patients with candidemia - Träger, Johannes; Dräger, Sarah; Mihai, Sidonia; Cipa, Franziska; Grawitz, Andrea Busse; Epting, Thomas; Meyer, Renate; Rappold, Elfriede; Held, Jürgen (Journal of Clinical Microbiology, 2023)
Fungal antigens such as β-(1→3)-D-glucan (BDG) or mannan (Mn) are useful for detection of candidemia. However, detailed data on serum levels before diagnosis and during treatment are scarce. We conducted a prospective study at two German tertiary care centers for 36 months. Sera from adult patients with candidemia were tested for BDG (Fungitell assay) and Mn (Platelia Candida Ag-Plus assay). For each patient, the clinical course and biomarker kinetics were closely followed and compared. 1,243 sera from 131 candidemia episodes and 15 relapses were tested. In 35% of episodes, empirical therapy included an antifungal drug. Before blood culture sampling, BDG and Mn levels were elevated in 62.4% and 30.8% of patients, respectively. Sensitivity at blood culture sampling was 78.6% (BDG) and 35.1% (Mn). BDG levels of non-survivors were significantly higher than those of survivors. During follow-up, a therapeutic response was associated with decreasing BDG and Mn levels in 84.3% or 70.5% of episodes, respectively. A median increase of 513 pg BDG/mL and 390 pg Mn/mL indicated a relapse of candidemia with a sensitivity of 80% or 46.7%, respectively. In 72.9% and 46.8% of patients, increasing BDG or Mn levels were associated with a fatal outcome. Prior to discharge, BDG and Mn levels had dropped or normalized in 65.7% or 82.1% of patients, respectively. Summarising, in patients with candidemia, biomarker positivity usually precedes culture positivity. Relapses are mostly accompanied by secondary biomarker increases. Rising concentrations of BDG and Mn predict lethality, whereas decreasing levels suggest a favorable outcome in the majority of patients.
CRIS-Team Scopus Importer:2023-12-08
Keywords: biomarker; Candida; Fungitell; glucan; mannan; Platelia; sepsis

Detection and virulence potential of a phospholipase D-negative Corynebacterium ulcerans from a concurrent diphtheria and infectious mononucleosis case - Simpson-Lourêdo, Liliane; Silva, Cecília M.F.; Hacker, Elena; Souza, Nadjla F.; Santana, Milena M.; Antunes, Camila A.; Nagao, Prescilla E.; Hirata, Raphael; Burkovski, Andreas; Villas Bôas, Maria Helena S.; Mattos-Guaraldi, Ana Luíza (Antonie Van Leeuwenhoek International Journal of General and Molecular Microbiology, 2019)
Diphtheria by Corynebacterium ulcerans is increasingly occurring in children, adolescents and adults. In addition to diphtheria toxin (DT), phospholipase D (PLD) is considered a virulence factor of C. ulcerans. In the present study, a first case of concurrent diphtheria by a PLD-negative C. ulcerans and infectious mononucleosis (IM) was verified. Clinical and microbiological profiles and binding properties to human Fibrinogen (Fbg), Fibronectin (Fn) and type I collagen (col I) biotinylated proteins and virulence to Caenorhabditis elegans were investigated for C. ulcerans strain 2590 (clinical isolate) and two control strains, including PLD-positive BR-AD22 wild type and PLD-negative ELHA-1 PLD mutant strains. MALDI-TOF assays and a multiplex PCR of genes coding for potentially toxigenic corynebacteria identified strain 2590 as non-DT producing. Interestingly, strain 2590 did not express PLD activity in the CAMP test although the presence of the pld gene was verified. PLD-negative 2590 and a PLD-positive 210932 strains showed similar affinity to Fbg, Fn and type I collagen. C. elegans were able to escape from C. ulcerans strains, independent of PLD and DT production. Higher mortality of nematodes was verified for PLD-negative strains. Additional studies concerning multifactorial virulence potential of C. ulcerans, including environmental conditions remain necessary.
CRIS-Team Scopus Importer:2019-06-18
Keywords: Co-infection; Corynebacterium ulcerans; Diphtheria; Infectious mononucleosis; Virulence factors; Zoonosis

Determinants of the interaction of Aspergillus fumigatus and eosinophils in the context of allergic bronchopulmonary aspergillosis - Adam, Jasmin; Schrüfer, Sebastian; Westermann, Stefanie; Vöhringer, David; Krappmann, Sven (MYCOSES, 2022)
CRIS-Team WoS Importer:2022-09-23

Determining Coreceptor Expression and Function in Murine ILC2 Through Flow Cytometry Characterization and Coculture Techniques - Schwartz, Christian; Fallon, Padraic G. (Methods in Molecular Biology, 2020)
Group 2 innate lymphoid cells are important innate effectors and regulators of adaptive immunity in response to parasitic infections and allergic inflammation. Their low frequency in vivo during steady state condition may complicate research on the cells. During type 2 biased immune responses they are activated, increase in frequency and release cytokines as well as regulate T cell functions through direct interactions including MHC class II–T cell receptor interactions. Importantly, coreceptors significantly influence the ILC2-T cell cross talk and shape the adaptive immune response. Here, we provide an experimental framework to study the function of coreceptors expressed on tissue ILC2. In brief, we describe flow cytometric analysis of the coreceptor of interest, the isolation and culture of mouse pulmonary ILC2 and splenic T cells, as well as approaches to manipulate their coculture. Finally, downstream readout options are outlined.
CRIS-Team Scopus Importer:2020-03-24
Keywords: Coculture; Cytokines; ILC2; Innate immunity; MHC2; Regulation; Stimulation; T helper cells; Transcription factors; Type 2 immune response

Development of prevalence and incidence of non-tuberculous mycobacteria in German laboratories from 2016 to 2020 - Corbett, Caroline; Finger, Philipp; Heiß-Neumann, Marion; Bohnert, Juergen; Eder, Ines B.; Eisele, Melanie; Friesen, Inna; Kaasch, Achim J.; Kehrmann, Jan; Lang, Roland; Rödel, Jürgen; Roessler, Susann; et al. (Emerging Microbes & Infections, 2023)
Numbers of non-tuberculous mycobacteria (NTM) pulmonary diseases (PD) have been repeatedly reported as increasing over the last decades, particularly in Europe. Sound epidemiological data are however missing for most European regions. This study calculated prevalence and incidence of NTM recovered from patients’ lungs in Germany, the largest Central European country, over a five-year period. It furthermore determined regional particularities of NTM species and results from susceptibility testing. 22 German NTM laboratories provided their mycobacteriological diagnostic data of 11,430 NTM isolates recovered from 5998 pulmonary patients representing 30% of all notified NTM-PD cases of Germany from 2016 to 2020. NTM incidence and prevalence were calculated for every study year. The presented epidemiological indicators are particularly reliant as TB surveillance data were used as a reference and TB notification reaches almost 100% in Germany. Laboratory incidence and prevalence of NTM recovered from respiratory samples ranged from 4.5–4.9 and from 5.3–5.8/100,000 for the population of Germany, respectively, and did not change over the five-year study period. Prevalence and incidence were stable also when stratifying for facultative pathogenic NTM, M. avium/intracellulare complex (MAIC), and M. abscessus/chelonae complex (MABSC). The proportion of NTM with drug susceptibility testing (DST) increased from 27.3% (2016) to 43.8% (2020). The unchanging laboratory NTM prevalence/incidence in Germany represents a “ceiling” of possible NTM-PD notification when diagnostic strategies do not change in the coming years. A notable increase in NTM-DST may indicate better notification of NTM-PD and/or awareness of new clinical guidelines but still remains below clinical needs.
CRIS-Team Scopus Importer:2024-12-16
Keywords: drug susceptibility; incidence; Non-tuberculous mycobacteria; NTM-pulmonary disease; prevalence

DGCR8 deficiency impairs macrophage growth and unleashes the interferon response to mycobacteria - Killy, Barbara; Bodendorfer, Barbara; Mages, Jörg; Ritter, Kristina; Schreiber, Jonathan; Hölscher, Christoph; Pracht, Katharina; Ekici, Arif Bülent; Jäck, Hans-Martin; Lang, Roland (Life Science Alliance, 2021)
The mycobacterial cell wall glycolipid trehalose-6,6-dimycolate (TDM) activates macrophages through the C-type lectin receptor MINCLE. Regulation of innate immune cells relies on miRNAs, which may be exploited by mycobacteria to survive and replicate in macrophages. Here, we have used macrophages deficient in the microprocessor component DGCR8 to investigate the impact of miRNA on the response to TDM. Deletion of DGCR8 in bone marrow progenitors reduced macrophage yield, but did not block macrophage differentiation. DGCR8-deficient macrophages showed reduced constitutive and TDM-inducible miRNA expression. RNAseq analysis revealed that they accumulated primary miRNA transcripts and displayed a modest type I IFN signature at baseline. Stimulation with TDM in the absence of DGCR8 induced overshooting expression of IFNβ and IFN-induced genes, which was blocked by antibodies to type I IFN. In contrast, signaling and transcriptional responses to recombinant IFNβ were unaltered. Infection with live Mycobacterium bovis Bacille Calmette-Guerin replicated the enhanced IFN response. Together, our results reveal an essential role for DGCR8 in curbing IFNβ expression macrophage reprogramming by mycobacteria.
CRIS-Team Scopus Importer:2021-04-16

Diagnosis and therapy of cutaneous and mucocutaneous Leishmaniasis in Germany - Boecken, Gerhard; Sunderkötter, Cord; Bogdan, Christian; Weitzel, Thomas; Fischer, Marcellus; Müller, Andreas; Löbermann, Micha; Anders, Gerlind; Von Stebut, Esther; Schunk, Mirjam; Burchard, Gerd; Grobusch, Martin; et al. (Journal der Deutschen Dermatologischen Gesellschaft, 2011)
The incidence of cutaneous and mucocutaneous Leishmaniasis (CL/MCL) is increasing globally, also in Germany, although the cases are imported and still low in number. The current evidence for the different therapies has many limitations due to lack of sufficient studies on the different Leishmania species with differing virulence. So far there is no international gold standard for the optimal management. The aim of the German joint working group on Leishmaniasis, formed by the societies of Tropical Medicine (DTG), Chemotherapy (PEG) and Dermatology (DDG), was to establish a guideline for the diagnosis and treatment of CL and MCL in Germany, based on evidence (Medline search yielded 400 articles) and, where lacking, on consensus of the experts. As the clinical features do not necessarily reflect the involved Leishmania species and, as different parasite species and even geographically distinct strains of the same species may require different treatments or varying dosagesor durations of therapy, the guidelines suggest for Germany to identify the underlying parasite prior to treatment. Because of relevant differences in prognosis and ensuing therapy species should be identified in i) New World CL/MCL (NWCL/ MCL) to distinguish between L. mexicana-complex and subgenus Viannia, ii) in suspected infections with L. mexicana-complex to distinguish from L. amazonensis, and iii) in Old World CL (OWCL) to distinguish between L. infantum and L. major, L. tropica, or L. aethiopica. A state-of-the-art diagnostic algorithm is presented. For recommendations on localized and systemic drug treatment and physical procedures, data from the accessible literature were adjusted according to the involved parasite species and a clinical differentiation into uncomplicated or complex lesions. Systemic therapy was strictly recommended for i) complex lesions (e. g. > 3 infected lesions, infections in functionally or cosmetically critical areas such as face or hands, presence of lymphangitis), ii) lesions refractory to therapy, iii) NWCL by the subgenus Viannia or by L. amazonensis, iv) in MCL and v) in recalcitrant, or disseminating or diffuse cutaneous courses. In e. g. infection with L. major it encompasses miltefosine, fluconazole and ketoconazole, while antimony or allopurinol were here considered second choice. Local therapy was considered appropriate for i) uncomplicated lesions of OWCL, ii) L. mexicana-complex and iii) pregnant women. In e. g. infection with L. major it encompasses perilesional antimony, combined with cryotherapy, paromomycin 15 %/in methylbenzethoniumchlorid 12 % and thermotherapy. The group also stated that there is an urgent need for improving the design and the way of publishing of clinical trials in leishmaniasis. © 2011 The Authors.
CRIS-Team Scopus Importer:2024-02-26
Keywords: clinical disease; cutaneous; diagnosis; epidemiology; guideline; leishmaniasis; mucocutaneous; treatment

Diagnostic performance of (1→3)-β-d-glucan alone and in combination with aspergillus pcr and galactomannan in serum of pediatric patients after allogeneic hematopoietic stem cell transplantation - Springer, Jan; Held, Jürgen; Mengoli, Carlo; Schlegel, Paul Gerhardt; Gamon, Florian; Traeger, Johannes; Kurzai, Oliver; Einsele, Hermann; Loeffler, Juergen; Eyrich, Matthias (Journal of Fungi, 2021)
Data on biomarker-assisted diagnosis of invasive aspergillosis (IA) in pediatric patients is scarce. Therefore, we conducted a cohort study over two years including 404 serum specimens of 26 pediatric patients after allogeneic hematopoietic stem cell transplantation (alloSCT). Sera were tested prospectively twice weekly for Aspergillus-specific DNA, galactomannan (GM), and retrospectively for (1→3)-β-D-glucan (BDG). Three probable IA and two possible invasive fungal disease (IFD) cases were identified using the European Organization for Research and Treatment of Cancer and the Mycoses Study Group (EORTC/MSGERC) 2019 consensus definitions. Sensitivity and specificity for diagnosis of probable IA and possible IFD was 80% (95% confidential interval (CI): 28–99%) and 55% (95% CI: 32–77%) for BDG, 40% (95% CI: 5–85%) and 100% (95% CI: 83–100%) for GM, and 60% (95% CI: 15–95%) and 95% (95% CI: 75–100%) for Aspergillus-specific real-time PCR. However, sensitivities have to be interpreted with great caution due to the limited number of IA cases. Interestingly, the low specificity of BDG was largely caused by false-positive BDG results that clustered around the date of alloSCT. The following strategies were able to increase BDG specificity: two consecutive positive BDG tests for diagnosis (specificity 80% (95% CI: 56–94%)); using an optimized cutoff value of 306 pg/mL (specificity 90% (95% CI: 68–99%)) and testing BDG only after the acute posttransplant phase. In summary, BDG can help to diagnose IA in pediatric alloSCT recipients. However, due to the poor specificity either an increased cutoff value should be utilized or BDG results should be confirmed by an alternative Aspergillus assay.
CRIS-Team Scopus Importer:2021-04-16
Keywords: Aspergillus; Beta-D-glucan; Galactomannan; Pediatric; Real-time PCR

Diagnostic performance of four SARS-CoV-2 antibody assays in patients with COVID-19 or with bacterial and non-SARS-CoV-2 viral respiratory infections - Huber, Timo; Steininger, Philipp; Irrgang, Pascal; Korn, Klaus; Tenbusch, Matthias; Diesch, Katharina; Achenbach, Susanne; Kremer, Andreas; Werblow, Marissa; Vetter, Marcel; Bogdan, Christian; Held, Jürgen (European Journal of Clinical Microbiology & Infectious Diseases, 2021)
SARS-CoV-2 antibody assays are used for epidemiological studies and for the assessment of vaccine responses in highly vulnerable patients. So far, data on cross-reactivity of SARS-CoV-2 antibody assays is limited. Here, we compared four enzyme-linked immunosorbent assays (ELISAs; Vircell SARS-CoV-2 IgM/IgA and IgG, Euroimmun SARS-CoV-2 IgA and IgG) for detection of anti-SARS-CoV-2 antibodies in 207 patients with COVID-19, 178 patients with serological evidence of different bacterial infections, 107 patients with confirmed viral respiratory disease, and 80 controls from the pre-COVID-19 era. In COVID-19 patients, the assays showed highest sensitivity in week 3 (Vircell-IgM/A and Euroimmun-IgA: 78.9% each) and after week 7 (Vircell-IgG: 97.9%; Euroimmun-IgG: 92.1%). The antibody indices were higher in patients with fatal disease. In general, IgM/IgA assays had only limited or no benefit over IgG assays. In patients with non-SARS-CoV-2 respiratory infections, IgG assays were more specific than IgM/IgA assays, and bacterial infections were associated with more false-positive results than viral infections. The specificities in bacterial and viral infections were 68.0 and 81.3% (Vircell-IgM/IgA), 84.8 and 96.3% (Euroimmun-IgA), 97.8 and 86.0% (Vircell-IgG), and 97.8 and 99.1% (Euroimmun-IgG), respectively. Sera from patients positive for antibodies against Mycoplasma pneumoniae, Chlamydia psittaci, and Legionella pneumophila yielded particularly high rates of unspecific false-positive results in the IgM/IgA assays, which was revealed by applying a highly specific flow-cytometric assay using HEK 293 T cells expressing the SARS-CoV-2 spike protein. Positive results obtained with anti-SARS-CoV-2 IgM/IgA ELISAs require careful interpretation, especially if there is evidence for prior bacterial respiratory infections.
CRIS-Team Scopus Importer:2021-06-18
Keywords: Antibody; Bacterial infections; Coronavirus; COVID-19; Euroimmun; SARS-CoV-2; Vircell

Diagnostic performance of the novel Fungitell STAT assay in comparison to the classical Fungitell assay and the Fujifilm Wako beta-glucan test in patients with invasive fungal disease - Kuepper, C.; Forster, J.; Traeger, J.; Meyer, R.; Cipa, Franziska; Mihai, Sidonia; Meintker, Lisa; Werblow, M.; Kurzai, O.; Held, Jürgen (MYCOSES, 2021)
CRIS-Team WoS Importer:2021-10-08

Diagnostic Value of Vaginal Discharge, Wet Mount and Vaginal pH - An Update on the Basics of Gynecologic Infectiology - Frobenius, Wolfgang; Bogdan, Christian (Geburtshilfe und Frauenheilkunde, 2015)
The majority of uncomplicated vulvovaginal complaints (e.g. bacterial vaginosis, vulvovaginal candidiasis, trichomoniasis) can be detected with uncomplicated basic infectiological tests and can usually be treated effectively without requiring further diagnostic procedures. Tests include measurement of vaginal pH, preparation and assessment of wet mount slides prepared from vaginal or cervical discharge, and the correct clinical and microbiological classification of findings. In Germany, at least in recent years, this has not been sufficiently taught or practiced. As new regulations on specialist gynecologic training in Germany are currently being drawn up, this overview provides basic information on gynecologic infectiology and summarizes clinically relevant aspects of recent microbiological findings on the physiology and pathology of vaginal flora. The clinical signs and symptoms of aerobic vaginitis, the pathogenesis of which is still not completely understood, are also reviewed. Finally, the symptoms, indications and risk factors for pelvic inflammatory disease (PID) are presented. In contrast to the above-listed infections, PID requires immediate culture of the pathogen from samples (e.g. obtained by laparoscopy) with microbiological diagnostic procedures carried out by specialist laboratories. A schematic summary of all pathologies discussed here is presented.
EVALuna2:7681

Differential control of Mincle-dependent cord factor recognition and macrophage responses by the transcription factors C/EBP? and HIF1? - Schoenen, Hanne Gunda; Huber, Alexandra; Sonda, Nada; Zimmermann, Stephanie; Jantsch, Jonathan; Lepenies, Bernd; Bronte, Vincenzo; Lang, Roland (Journal of Immunology, 2014)
Trehalose-6,6-dimycolate (TDM), the mycobacterial cord factor, and its synthetic analog Trehalose-6,6-dibehenate (TDB) bind to the C-type lectin receptors macrophage-inducible C-type lectin (Mincle) and Mcl to activate macrophages. Genetically, the transcriptional response to TDB/TDM has been defined to require FcR?-Syk-Card9 signaling. However, TDB/TDM-triggered kinase activation has not been studied well, and it is largely unknown which transcriptional regulators bring about inflammatory gene expression. In this article, we report that TDB/TDM caused only weak Syk-phosphorylation in resting macrophages, consistent with low basal Mincle expression. However, LPS-priming caused MYD88-dependent upregulation of Mincle, resulting in enhanced TDB/TDM-induced kinase activation and more rapid inflammatory gene expression. TLR-induced Mincle expression partially circumvented the requirement for Mcl in the response to TDB/TDM. To dissect transcriptional responses to TDB/TDM, we mined microarray data and identified early growth response (Egr) family transcription factors as direct Mincle target genes, whereas upregulation of Cebpb and Hif1a required new protein synthesis. Macrophages and dendritic cells lacking C/EBP? showed nearly complete abrogation of TDB/TDM responsiveness, but also failed to upregulate Mincle. Retroviral rescue of Mincle expression in Cebpb-deficient cells restored induction of Egr1, but not of G-CSF. This pattern of C/EBP? dependence was also observed after stimulation with the Dectin-1 ligand Curdlan. Inducible expression of hypoxia-inducible factor 1? (HIF1?) also required C/EBP?. In turn, HIF1? was not required for Mincle expression, kinase activation, and Egr1 or Csf3 expression, but critically contributed to NO production. Taken together, we identify C/EBP? as central hub in Mincle expression and inflammatory gene induction, whereas HIF1? controls Nos2 expression. C/EBP? also connects TLR signals to cord factor responsiveness through MYD88-dependent upregulation of Mincle.
EVALuna2:7659

Differential Lipid Recognition by Mouse versus Human CD300f, Inhibiting Passive Cutaneous Anaphylaxis, Depends on a Single Amino Acid Substitution in its Immunoglobulin-Like Domain - Izawa, Kumi; Kaitani, Ayako; Ando, Tomoaki; Maehara, Akie; Nagamine, Masakazu; Yamada, Hiromichi; Ando, Taiki; Ide, Takuma; Matsuzawa, Moe; Okamoto, Yoko; Yin, Enzhi; Fukase, Saaya; et al. (Journal of Investigative Dermatology, 2019)
CRIS-Team Scopus Importer:2019-11-12

Differentiation and tissue-adaptation of type-2 innate lymphoid cells during helminth infection - Lian, M.; Zeis, P.; Fan, X.; Symowski, Cornelia; Gentek, R.; Bajenoff, M.; Rudensky, A. Y.; Vöhringer, David; Kastenmueller, W.; Gruen, D.; Gasteiger, G. (EUROPEAN JOURNAL OF IMMUNOLOGY, 2019)
CRIS-Team WoS Importer:2019-10-08

Direct Visualization of Fungal Burden in Filamentous Fungus-Infected Silkworms - Yu, Yidong; Wolf, Ann-Katrin; Thusek, Sina; Heinekamp, Thorsten; Bromley, Michael; Krappmann, Sven; Terpitz, Ulrich; Voigt, Kerstin; Brakhage, Axel A.; Beilhack, Andreas (Journal of Fungi, 2021)
Invasive fungal infections (IFIs) are difficult to diagnose and to treat and, despite several available antifungal drugs, cause high mortality rates. In the past decades, the incidence of IFIs has continuously increased. More recently, SARS-CoV-2-associated lethal IFIs have been reported worldwide in critically ill patients. Combating IFIs requires a more profound understanding of fungal pathogenicity to facilitate the development of novel antifungal strategies. Animal models are indispensable for studying fungal infections and to develop new antifungals. However, using mammalian animal models faces various hurdles including ethical issues and high costs, which makes large-scale infection experiments extremely challenging. To overcome these limitations, we optimized an invertebrate model and introduced a simple calcofluor white (CW) staining protocol to macroscopically and microscopically monitor disease progression in silkworms (Bombyx mori) infected with the human pathogenic filamentous fungi Aspergillus fumigatus and Lichtheimia corymbifera. This advanced silkworm A. fumigatus infection model could validate knockout mutants with either attenuated, strongly attenuated or unchanged virulence. Finally, CW staining allowed us to efficiently visualize antifungal treatment outcomes in infected silkworms. Conclusively, we here present a powerful animal model combined with a straightforward staining protocol to expedite large-scale in vivo research of fungal pathogenicity and to investigate novel antifungal candidates.
CRIS-Team WoS Importer:2021-03-12

Discovery of a monoclonal, high-affinity CD8+ T-cell clone following natural hepatitis C virus infection - Cai, Curtis; Keoshkerian, Elizabeth; Wing, Kristof; Samir, Jerome; Effenberger, Manuel; Schober, Kilian; Bull, Rowena A.; Lloyd, Andrew R.; Busch, Dirk H.; Luciani, Fabio (Immunology and Cell Biology, 2024)
CD8+ T cells recognizing their cognate antigen are typically recruited as a polyclonal population consisting of multiple clonotypes with varying T-cell receptor (TCR) affinity to the target peptide–major histocompatibility complex (pMHC) complex. Advances in single-cell sequencing have increased accessibility toward identifying TCRs with matched antigens. Here we present the discovery of a monoclonal CD8+ T-cell population with specificity for a hepatitis C virus (HCV)–derived human leukocyte antigen (HLA) class I epitope (HLA-B*07:02 GPRLGVRAT) which was isolated directly ex vivo from an individual with an episode of acutely resolved HCV infection. This population was absent before infection and underwent expansion and stable maintenance for at least 2 years after infection as measured by HLA-multimer staining. Furthermore, the monoclonal clonotype was characterized by an unusually long dissociation time (half-life = 794 s and koff = 5.73 × 10−4) for its target antigen when compared with previously published results. A comparison with related populations of HCV-specific populations derived from the same individual and a second individual suggested that high-affinity TCR–pMHC interactions may be inherent to epitope identity and shape the phenotype of responses which has implications for rational TCR selection and design in the age of personalized immunotherapies.
CRIS-Team Scopus Importer:2024-06-21
Keywords: affinity; CD8; monoclonal expansion; T-cell receptor; T-cell response dynamics

Disrupting ceramide-CD300f interaction prevents septic peritonitis by stimulating neutrophil recruitment - Izawa, Kumi; Maehara, Akie; Isobe, Masamichi; Yasuda, Yuka; Urai, Makoto; Hoshino, Yasutaka; Ueno, Keigo; Matsukawa, Toshihiro; Takahashi, Mariko; Kaitani, Ayako; Shiba, Emiko; Takamori, Ayako; et al. (Scientific Reports, 2017)
Sepsis is a serious clinical problem. Negative regulation of innate immunity is associated with sepsis progression, but the underlying mechanisms remains unclear. Here we show that the receptor CD300f promotes disease progression in sepsis. CD300f (-/-) mice were protected from death after cecal ligation and puncture (CLP), a murine model of septic peritonitis. CD300f was highly expressed in mast cells and recruited neutrophils in the peritoneal cavity. Analysis of mice (e.g., mast cell-deficient mice) receiving transplants of wild-type or CD300f (-/-) mast cells or neutrophils indicated that CD300f deficiency did not influence intrinsic migratory abilities of neutrophils, but enhanced neutrophil chemoattractant production (from mast cells and neutrophils) in the peritoneal cavity of CLP-operated mice, leading to robust accumulation of neutrophils which efficiently eliminated Escherichia coli. Ceramide-CD300f interaction suppressed the release of neutrophil chemoattractants from Escherichia coli-stimulated mast cells and neutrophils. Administration of the reagents that disrupted the ceramide-CD300f interaction prevented CLP-induced sepsis by stimulating neutrophil recruitment, whereas that of ceramide-containing vesicles aggravated sepsis. Extracellular concentrations of ceramides increased in the peritoneal cavity after CLP, suggesting a possible role of extracellular ceramides, CD300f ligands, in the negative-feedback suppression of innate immune responses. Thus, CD300f is an attractive target for the treatment of sepsis.
EVALuna2:25887

Dissecting the gene expression, localization, membrane topology, and function of the plasmodium falciparum STEVOR protein family - Wichers, J. Stephan; Scholz, Judith A.M.; Strauss, Jan; Witt, Susanne; Lill, Andrés; Ehnold, Laura Isabell; Neupert, Niklas; Liffner, Benjamin; Lühken, Renke; Petter, Michaela; Lorenzen, Stephan; Wilson, Danny W.; et al. (Mbio, 2019)
During its intraerythrocytic development, the malaria parasite Plasmodium falciparum exposes variant surface antigens (VSAs) on infected erythrocytes to establish and maintain an infection. One family of small VSAs is the polymorphic STEVOR proteins, which are marked for export to the host cell surface through their PEXEL signal peptide. Interestingly, some STEVORs have also been reported to localize to the parasite plasma membrane and apical organelles, pointing toward a putative function in host cell egress or invasion. Using deep RNA sequencing analysis, we characterized P. falciparum stevor gene expression across the intraerythrocytic development cycle, including free merozoites, in detail and used the resulting stevor expression profiles for hierarchical clustering. We found that most stevor genes show biphasic expression oscillation, with maximum expression during trophozoite stages and a second peak in late schizonts. We selected four STEVOR variants, confirmed the expected export of these proteins to the host cell membrane, and tracked them to a secondary location, either to the parasite plasma membrane or the secretory organelles of merozoites in late schizont stages. We investigated the function of a particular STEVOR that showed rhoptry localization and demonstrated its role at the parasite-host interface during host cell invasion by specific antisera and targeted gene disruption. Experimentally determined membrane topology of this STEVOR revealed a single transmembrane domain exposing the semiconserved as well as variable protein regions to the cell surface. IMPORTANCE Malaria claims about half a million lives each year. Plasmodium falciparum, the causative agent of the most severe form of the disease, uses proteins that are translocated to the surface of infected erythrocytes for immune evasion. To circumvent the detection of these gene products by the immune system, the parasite evolved a complex strategy that includes gene duplications and elaborate sequence polymorphism. STEVORs are one family of these variant surface antigens and are encoded by about 40 genes. Using deep RNA sequencing of blood-stage parasites, including free merozoites, we first established stevor expression of the cultured isolate and compared it with published transcriptomes. We reveal a biphasic expression of most stevor genes and confirm this for individual STEVORs at the protein level. The membrane topology of a rhoptry-associated variant was experimentally elucidated and linked to host cell invasion, underlining the importance of this multi-functional protein family for parasite proliferation.
CRIS-Team Scopus Importer:2019-08-16
Keywords: Host cell invasion; Malaria; Variant surface antigens

DISSECTING THE INTERPLAY OF TCR AVIDITY OF NAIVE CD8+T CELLS AND TCR RECRUITMENT AFTER ANTIGEN EXPOSURE BY ENGINEERING POLYCLONAL REPERTOIRES - Straub, A.; Grassmann, S.; Jarosch, S.; Muller, T.; Wagner, K.; Hammel, M.; Buchholz, V.; Schober, Kilian; Busch, D. (HUMAN GENE THERAPY, 2022)
CRIS-Team WoS Importer:2022-10-21

Disseminated coccidioidomycosis: Monitoring of serologic markers for treatment response - Wilmes, Dunja; Schui, Daniela; Held, Jürgen; Ackermann, Sina; Geipel, Udo; Emrich, Kai; Winkelmann, Ernst Joachim; Rickerts, Volker (Medical Mycology Case Reports, 2020)
We describe a patient with a disseminated coccidioidomycosis. Biomarkers in serum during itraconazole therapy showed a rapid clearing of Coccidioides DNA as detected by PCR. Coccidioides antibody detection by lateral flow assay became negative after one year and decreased from 1:64 to 1:8 in the complement fixation test after two years. The (1 → 3)-ß-D-glucan levels normalised after two years without increase after cessation of antifungal therapy. Biomarkers in serum may guide treatment decisions in disseminated coccidioidomycosis.
CRIS-Team Scopus Importer:2020-06-16
Keywords: Coccidioides qPCR; Coccidioidomycosis; Endemic mycosis; Osteomyelitis; travel Related diseases

Distinct gut microbial signature and altered short chain fatty acid metabolism at disease onset in a rat preclinical model of superimposed preeclampsia - Alhasan, Moumen M.; Landa, María S.; García, Silvia I.; Gerlach, Roman; Harb, Hani; Fahlbusch, Fabian B.; Conrad, Melanie L.; Barrientos, Gabriela (Scientific Reports, 2024)
Chronic hypertension is an increasingly prevalent condition that constitutes a risk factor for superimposed preeclampsia during pregnancy. In this study, we assessed the gut microbiome in a rat model of superimposed preeclampsia to characterize the microbial signature associated with defective placentation processes identified at the preclinical disease stage. The blood pressure profile, renal function parameters and fetal phenotype were evaluated in pregnant Stroke-prone Spontaneously Hypertensive Rats (SHRSP) and their normotensive controls. On gestation day (GD)14, feces were collected and gut microbiome composition and short-chain fatty acid concentrations were determined by 16S rRNA sequencing and gas chromatography respectively. At disease onset on GD14, the fecal gut microbiome of SHRSP showed a lower alpha diversity and significant differences in beta diversity when compared with control animals. In the feces, Prevotella, Bifidobacterium, Parasutterella and Roseburia were enriched in SHRSP pregnancies compared to controls, showing a strong correlation with clinical parameters. Bacteria from the families Ruminococcaceae, Oscillospiraceae and the genera Blautia and Faecalibacterium were depleted. Considering short-chain fatty acids, acetate, propionate and valerate were increased in the SHRSP model, showing a strong positive correlation with the relative abundance of enriched taxa. We show that on GD14, at the asymptomatic SPE onset stage, pregnant SHRSP display a distinct gut microbiome signature and altered short chain fatty acid metabolism compared to control animals.
CRIS-Team Scopus Importer:2025-02-04

Divergent effects of itaconate isomers on Coxiella burnetii growth in macrophages and in axenic culture - Siddique, Md Nur A Alam; Kellermeier, Fabian; Ölke, Martha; Zhao, Mingming; Büssow, Konrad; Oefner, Peter J.; Lührmann, Anja; Dettmer, Katja; Lang, Roland (Frontiers in Immunology, 2024)
Aconitate decarboxylase-1 (ACOD1) is expressed by activated macrophages and generates itaconate that exerts anti-microbial and immunoregulatory effects. ACOD1-itaconate is essential for macrophage-mediated control of the intracellular pathogen Coxiella (C.) burnetii, which causes Q fever. Two isomers of itaconate, mesaconate and citraconate, have overlapping yet distinct activity on macrophage metabolism and inflammatory gene expression. Here, we found that all three isomers inhibited the growth of C. burnetii in axenic culture in ACCM-2 medium. However, only itaconate reduced C. burnetii replication efficiently in Acod1-/- macrophages. In contrast, addition of citraconate strongly increased C. burnetii replication in Acod1+/- macrophages, whereas mesaconate weakly enhanced bacterial burden in Acod1-/- macrophages. Analysis of intracellular isomers showed that exogenous citraconate and mesaconate inhibited the generation of itaconate by infected Acod1+/- macrophages. Uptake of added isomers into Acod1-/- macrophages was increased after infection for itaconate and mesaconate, but not for citraconate. Mesaconate, but not citraconate, competed with itaconate for uptake into macrophages. Taken together, inhibition of itaconate generation by macrophages and interference with the uptake of extracellular itaconate could be identified as potential mechanisms behind the divergent effects of citraconate and mesaconate on C. burnetii replication in macrophages or in axenic culture.
CRIS-Team Scopus Importer:2024-08-30
Keywords: ACOD1; citraconate; infection; IRG1; itaconate; mesaconate; transport; uptake

DNA methylation profiling identifies TBKBP1 as potent amplifier of cytotoxic activity in CMV-specific human CD8+ T cells - Yu, Zheng; Sasidharan-Nair, Varun; Buchta, Thalea; Bonifacius, Agnes; Khan, Fawad; Pietzsch, Beate; Ahmadi, Hosein; Beckstette, Michael; Niemz, Jana; Hilgendorf, Philipp; Mausberg, Philip; Keller, Andreas; et al. (PLoS Pathogens, 2024)
Epigenetic mechanisms stabilize gene expression patterns during CD8+ T cell differentiation. Although adoptive transfer of virus-specific T cells is clinically applied to reduce the risk of virus infection or reactivation in immunocompromised individuals, the DNA methylation pattern of virus-specific CD8+ T cells is largely unknown. Hence, we here performed whole-genome bisulfite sequencing of cytomegalovirus-specific human CD8+ T cells and found that they display a unique DNA methylation pattern consisting of 79 differentially methylated regions (DMRs) when compared to memory CD8+ T cells. Among the top demethylated DMRs in cytomegalovirus-specific CD8+ T cells was TBKBP1, coding for TBK-binding protein 1 that can interact with TANK-binding kinase 1 (TBK1) and mediate pro-inflammatory responses in innate immune cells downstream of intracellular virus sensing. Since TBKBP1 has not yet been reported in T cells, we aimed to unravel its role in virus-specific CD8+ T cells. TBKBP1 demethylation in terminal effector CD8+ T cells correlated with higher TBKBP1 expression at both mRNA and protein level, independent of alternative splicing of TBKBP1 transcripts. Notably, the distinct DNA methylation patterns in CD8+ T cell subsets was stable upon long-term in vitro culture. TBKBP1 overexpression resulted in enhanced TBK1 phosphorylation upon stimulation of CD8+ T cells and significantly improved their virus neutralization capacity. Collectively, our data demonstrate that TBKBP1 modulates virus-specific CD8+ T cell responses and could be exploited as therapeutic target to improve adoptive T cell therapies.
CRIS-Team Scopus Importer:2024-10-11

Dominant immune tolerance in the intestinal tract imposed by RelB-dependent migratory dendritic cells regulates protective type 2 immunity - Geiselhöringer, Anna Lena; Kolland, Daphne; Patt, Arisha Johanna; Hammann, Linda; Köhler, Amelie; Kreft, Luisa; Wichmann, Nina; Hils, Miriam; Ruedl, Christiane; Riemann, Marc; Biedermann, Tilo; Anz, David; et al. (Nature Communications, 2024)
Dendritic cells (DCs) are crucial for initiating protective immune responses and have also been implicated in the generation and regulation of Foxp3+ regulatory T cells (Treg cells). Here, we show that in the lamina propria of the small intestine, the alternative NF-κB family member RelB is necessary for the differentiation of cryptopatch and isolated lymphoid follicle-associated DCs (CIA-DCs). Moreover, single-cell RNA sequencing reveals a RelB-dependent signature in migratory DCs in mesenteric lymph nodes favoring DC-Treg cell interaction including elevated expression and release of the chemokine CCL22 from RelB-deficient conventional DCs (cDCs). In line with the key role of CCL22 to facilitate DC-Treg cell interaction, RelB-deficient DCs have a selective advantage to interact with Treg cells in an antigen-specific manner. In addition, DC-specific RelB knockout animals show increased total Foxp3+ Treg cell numbers irrespective of inflammatory status. Consequently, DC-specific RelB knockout animals fail to mount protective Th2-dominated immune responses in the intestine after infection with Heligmosomoides polygyrus bakeri. Thus, RelB expression in cDCs acts as a rheostat to establish a tolerogenic set point that is maintained even during strong type 2 immune conditions and thereby is a key regulator of intestinal homeostasis.
CRIS-Team Scopus Importer:2024-11-08

Dual role of the mycobacterial cord factor TDM in cross-regulation of macrophage responses to IFN gamma - Killy, Barbara; Huber, Angelika; Ekici, Arif Bülent; Wirtz, Stefan; Dalpke, A.; Lang, Roland (2017)
EVALuna2:33888

Dual Specificity Phosphatases: From Molecular Mechanisms to Biological Function - Pulido, Rafael; Lang, Roland (International Journal of Molecular Sciences, 2019)
Dual specificity phosphatases (DUSPs) constitute a heterogeneous group of enzymes, relevant in human disease, which belong to the class I Cys-based group of protein tyrosine phosphatase (PTP) gene superfamily [...].
CRIS-Team Scopus Importer:2019-09-20

Dual-Specificity Phosphatases in Immunity and Infection: An Update - Lang, Roland; Raffi, Faizal A.M. (International Journal of Molecular Sciences, 2019)
Kinase activation and phosphorylation cascades are key to initiate immune cell activation in response to recognition of antigen and sensing of microbial danger. However, for balanced and controlled immune responses, the intensity and duration of phospho-signaling has to be regulated. The dual-specificity phosphatase (DUSP) gene family has many members that are differentially expressed in resting and activated immune cells. Here, we review the progress made in the field of DUSP gene function in regulation of the immune system during the last decade. Studies in knockout mice have confirmed the essential functions of several DUSP-MAPK phosphatases (DUSP-MKP) in controlling inflammatory and anti-microbial immune responses and support the concept that individual DUSP-MKP shape and determine the outcome of innate immune responses due to context-dependent expression and selective inhibition of different mitogen-activated protein kinases (MAPK). In addition to the canonical DUSP-MKP, several small-size atypical DUSP proteins regulate immune cells and are therefore also reviewed here. Unexpected and complex findings in DUSP knockout mice pose new questions regarding cell type-specific and redundant functions. Another emerging question concerns the interaction of DUSP-MKP with non-MAPK binding partners and substrate proteins. Finally, the pharmacological targeting of DUSPs is desirable to modulate immune and inflammatory responses.
CRIS-Team Scopus Importer:2019-06-21
Keywords: atypical DUSP; cytokines; inflammation; macrophage; MAPK phosphatase; T cell

Duration of Protection After Vaccination Against Yellow Fever-Systematic Review and Meta-analysis - Kling, Kerstin; Domingo, Cristina; Bogdan, Christian; Duffy, Steven; Harder, Thomas; Howick, Jeremy; Kleijnen, Jos; Mcdermott, Kevin; Wichmann, Ole; Wilder-Smith, Annelies; Wolff, Robert (Clinical Infectious Diseases, 2022)
The duration of protection after a single dose of yellow fever vaccine is a matter of debate. To summarize the current knowledge, we performed a systematic literature review and meta-analysis. Studies on the duration of protection after 1 and >= 2 vaccine doses were reviewed. Data were stratified by time since vaccination. In our meta-analysis, we used random-effects models. We identified 36 studies from 20 countries, comprising more than 17 000 participants aged 6 months to 85 years. Among healthy adults and children, pooled seroprotection rates after single vaccination dose were close to 100% by 3 months and remained high in adults for 5 to 10 years. In children vaccinated before age 2 years, the seroprotection rate was 52% within 5 years after primary vaccination. For immunodeficient persons, data indicate relevant waning. The extent of waning of seroprotection after yellow fever vaccination depends on age and immune status at primary vaccination.
CRIS-Team WoS Importer:2022-08-19

Durch Biofilm bakteriell besiedelte Implantate bedingen Wundheilungsstörungen - Beier, Justus; Bogdan, Christian; Schmitz, Markus; Schubert, Dirk W.; Schultz, Gregory; Horch, Raymund E. (Chirurgische Allgemeine - Zeitung für Klinik und Praxis, 2013)

Dusp16 Deficiency Causes Congenital Obstructive Hydrocephalus and Brain Overgrowth by Expansion of the Neural Progenitor Pool - Zega, Ksenija; Jovanovic, Vukasin M.; Vitic, Zagorka; Niedzielska, Magdalena; Knaapi, Laura; Jukic, Marin M.; Partanen, Juha; Friedel, Roland F.; Lang, Roland; Brodski, Claude (Frontiers in Molecular Neuroscience, 2017)
Hydrocephalus can occur in children alone or in combination with other neurodevelopmental disorders that are often associated with brain overgrowth. Despite the severity of these disorders, the molecular and cellular mechanisms underlying these pathologies and their comorbidity are poorly understood. Here, we studied the consequences of genetically inactivating in mice dual-specificity phosphatase 16 (Dusp16), which is known to negatively regulate mitogen-activated protein kinases (MAPKs) and which has never previously been implicated in brain development and disorders. Mouse mutants lacking a functionalDusp16gene (Dusp16-/-) developed fully-penetrant congenital obstructive hydrocephalus together with brain overgrowth. The midbrain aqueduct inDusp16-/-mutants was obstructed during mid-gestation by an expansion of neural progenitors, and during later gestational stages by neurons resulting in a blockage of cerebrospinal fluid (CSF) outflow. In contrast, the roof plate and ependymal cells developed normally. We identified a delayed cell cycle exit of neural progenitors inDusp16-/-mutants as a cause of progenitor overproliferation during mid-gestation. At later gestational stages, this expanded neural progenitor pool generated an increased number of neurons associated with enlarged brain volume. Taken together, we found thatDusp16plays a critical role in neurogenesis by balancing neural progenitor cell proliferation and neural differentiation. Moreover our results suggest that a lack of functionalDusp16could play a central role in the molecular mechanisms linking brain overgrowth and hydrocephalus.
EVALuna2:33301

Dynamics of humoral and cellular immune responses after homologous and heterologous SARS-CoV-2 vaccination with ChAdOx1 nCoV-19 and BNT162b2 - Vogel, Emanuel; Kocher, Katharina; Priller, Alina; Cheng, Cho Chin; Steininger, Philipp; Liao, Bo Hung; Körber, Nina; Willmann, Annika; Irrgang, Pascal; Held, Jürgen; Moosmann, Carolin; Schmidt, Viviane; et al. (EBioMedicine, 2022)
Background: Vaccines are an important means to overcome the SARS-CoV-2 pandemic. They induce specific antibody and T-cell responses but it remains open how well vaccine-induced immunity is preserved over time following homologous and heterologous immunization regimens. Here, we compared the dynamics of humoral and cellular immune responses up to 180 days after homologous or heterologous vaccination with either ChAdOx1-nCoV-19 (ChAd) or BNT162b2 (BNT) or both. Methods: Various tests were used to determine the humoral and cellular immune response. To quantify the antibody levels, we used the surrogate neutralization (sVNT) assay from YHLO, which we augmented with pseudo- and real virus neutralization tests (pVNT and rVNT). Antibody avidity was measured by a modified ELISA. To determine cellular reactivity, we used an IFN-γ Elispot, IFN-γ/IL Flurospot, and intracellular cytokine staining. Findings: Antibody responses significantly waned after vaccination, irrespective of the regimen. The capacity to neutralize SARS-CoV-2 – including variants of concern such as Delta or Omicron – was superior after heterologous compared to homologous BNT vaccination, both of which resulted in longer-lasting humoral immunity than homologous ChAd immunization. All vaccination regimens induced stable, polyfunctional T-cell responses. Interpretation: These findings demonstrate that heterologous vaccination with ChAd and BNT is a potent alternative to induce humoral and cellular immune protection in comparison to the homologous vaccination regimens. Funding: The study was funded by the German Centre for Infection Research (DZIF), the European Union's “Horizon 2020 Research and Innovation Programme" under grant agreement No. 101037867 (VACCELERATE), the “Bayerisches Staatsministerium für Wissenschaft und Kunst” for the CoVaKo-2021 and the For-COVID projects and the Helmholtz Association via the collaborative research program “CoViPa”. Further support was obtained from the Federal Ministry of Education and Science (BMBF) through the “Netzwerk Universitätsmedizin”, project “B-Fast” and “Cov-Immune”. KS is supported by the German Federal Ministry of Education and Research (BMBF, 01KI2013) and the Else Kröner-Stiftung (2020_EKEA.127).
CRIS-Team Scopus Importer:2022-10-21
Keywords: antibody avidity; BNT162b2; ChAdOx1-nCoV-19; COVID-19; Heterologous vaccination; long-term; maintenance; SARS-CoV-2; T cell immunity; vaccine

Dysregulated skin barrier function in Tmem79 mutant mice promotes IL-17A-dependent spontaneous skin and lung inflammation - Saunders, Sean P.; Floudas, Achilleas; Moran, Tara; Byrne, Ciara M.; Rooney, Michael D.; Fahy, Caoimhe M.R.; Geoghegan, Joan A.; Iwakura, Yoichiro; Fallon, Padraic G.; Schwartz, Christian (Allergy, 2020)
Background: Atopic dermatitis (AD) is associated with a dysregulation of the skin barrier and may predispose to the development of secondary allergic conditions, such as asthma. Tmem79ma/ma mice harbor a mutation in the gene encoding Transmembrane Protein 79 (or Mattrin), which has previously been associated with AD. As a result of the Tmem79 gene mutation, these mice have a defective skin barrier and develop spontaneous skin inflammation. In this study, Tmem79ma/ma mice were assessed for the underlying immunological response in the development of spontaneous skin and lung inflammation. Methods: Development of spontaneous skin and lung inflammation in Tmem79ma/ma mice was analyzed. We further investigated susceptibility to cutaneous Staphylococcus aureus infection. Tmem79ma/ma were crossed to IL-17A-deficient mice to address the contribution of IL-17A to spontaneous skin and lung disease. Results: Tmem79ma/ma mice developed IL-17A-dependent spontaneous AD-like inflammation and were refractory to S aureus infection. Mutant mice progressed to airway inflammation subsequent to the occurrence of dermatitis. The progression from skin to lung disease is dependent on adaptive immunity and is facilitated by cutaneous expansion of Th17 and TCRγδ T cells. Conclusion: Mice lacking Tmem79/Mattrin expression have a defective skin barrier. In adulthood, these mice develop dermatitis with secondary progression to lung inflammation. The development of skin and lung inflammation is IL-17A-dependent and mediated by TCRγδ T cells.
CRIS-Team Scopus Importer:2020-07-31
Keywords: cutaneous inflammation; interleukin-17A; lung inflammation; skin barrier; Tmem79

Early and late genome-wide gastric epithelial transcriptome response during infection with the human carcinogen Helicobacter pylori - Sharafutdinov, Irshad; Ekici, Arif Bülent; Vieth, Michael; Backert, Steffen; Linz, Bodo (Cell Insight, 2022)
Infection of the stomach by Helicobacter pylori is a major risk factor for the development of gastric cancer. Colonization of the gastric epithelium leads to the activation of multiple disease-related signaling pathways. Serine protease HtrA represents an important secreted virulence factor that mediates cleavage of cellular junctions. However, its potential role in nuclear responses is unknown. Here, we performed a genome-wide RNA-seq analysis of polarized gastric epithelial cells infected by wild-type (wt) and ΔhtrA mutant bacteria. Fluorescence microscopy showed that H. pylori wt, but not ΔhtrA bacteria, preferably localized at cellular junctions. Our results pinpointed early (2 h) and late (6 h) transcriptional responses, with most differentially expressed genes at 6 h post infection. The transcriptomes revealed HtrA-dependent targeting of genes associated with inflammation and apoptosis (e.g. IL8, ZFP36, TNF). Accordingly, infection with the ΔhtrA mutant induced increased apoptosis rates in host cells, which was associated with reduced H. pylori CagA expression. In contrast, transcription of various carcinogenesis-associated genes (e.g. DKK1, DOCK8) was affected by H. pylori independent of HtrA. These findings suggest that H. pylori disturbs previously unknown molecular pathways in an HtrA-dependent and HtrA-independent manner, and provide valuable new insights of this significant pathogen in humans and thus potential targets for better controlling the risk of malignant transformation.<br
Keywords: Helicobacter; Cancer; RNA-seq; HtrA; Apoptosis; Inflammation

Early CCR6 expression on B cells modulates germinal centre kinetics and efficient antibody responses - Reimer, Dorothea; Lee, Adrian Y. S.; Bannan, Jennifer; Fromm, Phillip; Kara, Ervin E.; Comerford, Iain; Mccoll, Shaun; Wiede, Florian; Mielenz, Dirk; Körner, Heinrich (Immunology and Cell Biology, 2017)
The CC-chemokine receptor 6 (CCR6) can be detected on naive and activated B cells. Counterintuitively, its absence accelerates the appearance of germinal centres (GCs) and increases the production of low-affinity antibodies. The detailed mechanism of CCR6 function during the humoral response has remained elusive, but previously we identified a distinct CCR6high B-cell population in vivo early after antigenic challenge. In this study, we defined this population specifically as early, activated pre-GC B cells. In accordance, we show that CCR6 is upregulated rapidly within hours on the protein or mRNA level after activation in vitro. In addition, only activated B cells migrated specifically towards CCL20, the specific ligand for CCR6. Lack of CCR6 increased the dark zone/light zone ratio of GC and led to decreased antigen-specific IgG1 and IgG2a antibody generation in a B-cell intrinsic manner in mixed bone marrow chimeras. In contrast, antigen-specific IgM responses were normal. Hence, CCR6 negatively regulates entry of activated, antigen-specific pre-GC B cells into the GC reaction.
EVALuna2:36045

Editorial: Lectins and Their Ligands in Shaping Immune Responses - Lepenies, Bernd; Lang, Roland (Frontiers in Immunology, 2019)
CRIS-Team Scopus Importer:2019-11-05
Keywords: C-type lectins; dendritic cells; galectins; glycoimmunology; immunomodulation; lectins; myeloid cells; siglecs

Editorial: Sulphur Metabolism of Fungi - Implications for Virulence and Opportunities for Therapy - Amich, Jorge; Krappmann, Sven; Bachhawat, Anand Kumar (Frontiers in Microbiology, 2020)
CRIS-Team Scopus Importer:2020-11-06
Keywords: fungal primary metabolism; implications for virulence; opportunities for therapy; pathogenic fungi; sulfur metabolism of fungi

Effectiveness, immunogenicity and safety of 23-valent pneumococcal polysaccharide vaccine revaccinations in the elderly: a systematic review - Remschmidt, Cornelius; Harder, Thomas; Wichmann, Ole; Bogdan, Christian; Falkenhorst, Gerhard (BMC Infectious Diseases, 2016)
In many industrialized countries routine vaccination with the 23-valent pneumococcal polysaccharide vaccine (PPSV-23) is recommended to prevent pneumococcal disease in the elderly. However, vaccine-induced immunity wanes after a few years, and there are controversies around revaccination with PPSV-23. Here, we systematically assessed the effectiveness and safety of PPSV-23 revaccination.We conducted a systematic literature review in MEDLINE, EMBASE, and Cochrane Central Register of Controlled Trials from inception to June 2015. We included all study types that compared effectiveness, immunogenicity and/or safety of PPSV-23 as a primary vs. a revaccination dose in persons aged 50 years and older. With respect to immunogenicity, we calculated the ratio of geometric mean antibody concentrations and opsonophagocytic indexes at identical time-points after primary and revaccination. Additionally, we compared rates and severity of adverse events (AEs) after primary and revaccination.We included 14 observational studies. 10 studies had a prospective design and analysed data on (i) the same individuals after a first and a second dose of PPSV-23 given 1 to 10 years later (n = 5) or (ii) two groups consisting of participants receiving PPSV-23 who were either vaccine-naïve or had received a first PPSV-23 dose 3 to 13 years earlier (n = 5). Three studies used electronic data bases to compare AEs after primary vs. revaccination doses of PPSV-23 after 1 to 10 years and one study had a cross-sectional design. Number of participants in the non-register-based and register-based studies ranged from 29 to 1414 and 360 to 316,000, respectively. 11 out of 14 included studies were at high risk of bias, three studies had an unclear risk of bias. None of the studies reported data on clinical effectiveness. Immunogenicity studies revealed that during the first two months antibody levels tended to be lower after revaccination as compared to primary vaccination. Thereafter, no obvious differences in antibody levels were observed. Compared to primary vaccination, revaccination was associated with an increased risk of local and systemic AEs, which, however, were usually mild and self-limiting. The risk and severity of AEs appeared to decrease with longer intervals between primary and revaccination.Data comparing the effectiveness of primary vs. revaccination with PPSV-23 are still lacking, because there are no studies with clinical endpoints. Data from observational studies indicates that revaccination with PPSV-23 is likely to induce long-term antibody levels that are comparable to those after primary vaccination. Given the high disease burden and the waning of vaccine-induced immunity, revaccination with PPSV-23 could be considered in the elderly. The increased risk of local and systemic AEs can likely be mitigated when giving revaccination at least five years after the primary dose. Adequately powered randomized controlled trials using clinical endpoints are urgently needed.
EVALuna2:7724

Effectiveness of the 23-Valent Pneumococcal Polysaccharide Vaccine (PPV23) against Pneumococcal Disease in the Elderly: Systematic Review and Meta-Analysis - Falkenhorst, Gerhard; Remschmidt, Cornelius; Harder, Thomas; Hummers-Pradier, Eva; Wichmann, Ole; Bogdan, Christian (PLoS ONE, 2017)
Routine vaccination of elderly people against pneumococcal diseases is recommended in many countries. National guidelines differ, recommending either the 23-valent polysaccharide vaccine (PPV23), the 13-valent conjugate vaccine (PCV13) or both. Considering the ongoing debate on the effectiveness of PPV23, we performed a systematic literature review and meta-analysis of the vaccine efficacy/effectiveness (VE) of PPV23 against invasive pneumococcal disease (IPD) and pneumococcal pneumonia in adults aged >=60 years living in industrialized countries.We searched for pertinent clinical trials and observational studies in databases MEDLINE, EMBASE, Cochrane Central Register of Controlled Trials, and Cochrane Database of Systematic Reviews. We assessed the risk of bias of individual studies using the Cochrane Risk of Bias tool for randomized controlled trials and the Newcastle-Ottawa Scale for observational studies. We rated the overall quality of the evidence by GRADE criteria. We performed meta-analyses of studies grouped by outcome and study design using random-effects models. We applied a sensitivity analysis excluding studies with high risk of bias.We identified 17 eligible studies. Pooled VE against IPD (by any serotype) was 73% (95%CI: 10-92%) in four clinical trials, 45% (95%CI: 15-65%) in three cohort studies, and 59% (95%CI: 35-74%) in three case-control studies. After excluding studies with high risk of bias, pooled VE against pneumococcal pneumonia (by any serotype) was 64% (95%CI: 35-80%) in two clinical trials and 48% (95%CI: 25-63%) in two cohort studies. Higher VE estimates in trials (follow-up 2.5 years) than in observational studies (follow-up 5 years) may indicate waning protection. Unlike previous meta-analyses, we excluded two trials with high risk of bias regarding the outcome pneumococcal pneumonia, because diagnosis was based on serologic methods with insufficient specificity.Our meta-analysis revealed significant VE of PPV23 against both IPD and pneumococcal pneumonia by any serotype in the elderly, comparable to the efficacy of PCV13 against vaccine-serotype disease in a recent clinical trial in elderly people. Due to its broader serotype coverage and the decrease of PCV13 serotypes among adults resulting from routine infant immunization with PCV13, PPV23 continues to play an important role for protecting adults against IPD and pneumococcal pneumonia.
EVALuna2:7727

Effective Priming of Herpes Simplex Virus-Specific CD8+T CellsIn VivoDoes Not Require Infected Dendritic Cells - Whitney, Paul G.; Makhlouf, Christina; Macleod, Beth; Ma, Joel Z.; Gressier, Elise; Greyer, Marie; Hochheiser, Katharina; Bachem, Annabell; Zaid, Ali; Vöhringer, David; Heath, William R.; Wagle, Mayura V.; et al. (Journal of Virology, 2018)
Resolution of virus infections depends on the priming of virus-specific CD8+T cells by dendritic cells (DC). While this process requires major histocompatibility complex (MHC) class I-restricted antigen presentation by DC, the relative contribution to CD8+T cell priming by infected DC is less clear. We have addressed this question in the context of a peripheral infection with herpes simplex virus 1 (HSV). Assessing the endogenous, polyclonal HSV-specific CD8+T cell response, we found that effectivein vivoT cell priming depended on the presence of DC subsets specialized in cross-presentation, while Langerhans cells and plasmacytoid DC were dispensable. Utilizing a novel mouse model that allows for thein vivoelimination of infected DC, we also demonstratedin vivothat this requirement for cross-presenting DC was not related to their infection but instead reflected their capacity to cross-present HSV-derived antigen. Taking the results together, this study shows that infected DC are not required for effective CD8+T cell priming during a peripheral virus infection.IMPORTANCEThe ability of some DC to present viral antigen to CD8+T cells without being infected is thought to enable the host to induce killer T cells even when viruses evade or kill infected DC. However, direct experimentalin vivoproof for this notion has remained elusive. The work described in this study characterizes the role that different DC play in the induction of virus-specific killer T cell responses and, critically, introduces a novel mouse model that allows for the selective elimination of infected DCin vivoOur finding that HSV-specific CD8+T cells can be fully primed in the absence of DC infection shows that cross-presentation by DC is indeed sufficient for effective CD8+T cell priming during a peripheral virus infection.
EVALuna2:33417

Electroporation of siRNA into Mouse Bone Marrow-Derived Macrophages and Dendritic Cells - Siegert, Isabel; Schatz, Valentin; Prechtel, Alexander T.; Steinkasserer, Alexander; Bogdan, Christian; Jantsch, Jonathan (Methods in Molecular Biology, 2014)
Dendritic cells (DC) and macrophages (M?) play a pivotal role in antimicrobial defense, in the regulation of immune responses, and in maintaining tissue homeostasis. The analysis of DC and M? function relies on primary cells albeit these cells are known to be difficult to transfect. This makes the use of small interfering RNA (siRNA) for targeted manipulation of gene expression by RNA interference difficult. In the following chapter, we provide a detailed protocol for the successful transfer of siRNA via electroporation into a defined population of mouse bone marrow-derived M? or DC that does not cause toxicity to the myeloid cells or nonspecific alterations of their biological functions. Factors that influence the transfection and knockdown rate will be highlighted.
EVALuna2:7575

Elimination of bacterial contaminations by treatment of water with boron-doped diamond electrodes - Schorr, Bastian; Ghanem, Hanadi; Rosiwal, Stefan; Geißdörfer, Walter; Burkovski, Andreas (World Journal of Microbiology & Biotechnology, 2019)
Boron-doped diamond electrodes can be used to generate reactive oxygen species directly at the electrode’s surface. This property was used in this study for in-situ electrochemical oxidation to eliminate different bacteria, i.e. Escherichia coli, Pseudomonas fluorescens and Pseudomonas aeruginosa, as well as Bacillus subtilis spores from water samples. Application of low voltages in the rage from 4 to 10 V and short incubation times in the range of minutes allowed a complete disinfection of water contaminated with enterobacteria and freshwater microbes including nosocomial pathogens as well as a significant reduction of spores. A pilot reactor was constructed, which allowed to decrease microbial contamination of sewage plant effluent drastically.
Keywords: Reactive oxygen species; Sewage treatment plant; Drinking water; Potable water; Water purification

Emergence of novel ST1299 vanA lineages as possible cause for the striking rise of vancomycin resistance among invasive strains of Enterococcus faecium at a German university hospital - Valenza, Giuseppe; Eisenberger, David; Voigtländer, Sven; Alsalameh, Rayya; Gerlach, Roman; Koch, Sonja; Kunz, Bernd; Held, Jürgen; Bogdan, Christian (Microbiology Spectrum, 2023)
IMPORTANCE: The proportion of VREfm among all Enterococcus faecium isolated from blood cultures in German hospitals has increased in the period 2015-2020 from 11.9% to 22.3% with a country-wide spread of the clonal lineage ST117/CT71 vanB. In this study, we provided useful information about the genetic diversity of invasive strains of E. faecium. Moreover, our findings confirm the nosocomial spread of novel ST1299 vanA lineages, which recently had a rapid expansion in Austria and the south-eastern part of Germany.
CRIS-Team Scopus Importer:2023-12-29
Keywords: bloodstream Infection; core genome multilocus sequence typing; Enterococcus faecium; ST1299 vanA; vancomycin resistance

Enhancing automated micrograph-based evaluation of LPS-stimulated macrophage spreading - Held, Christian; Wenzel, Jens; Wiesmann, Veit; Palmisano, Ralf; Lang, Roland; Wittenberg, Thomas (Cytometry Part A, 2013)
To evaluate macrophage spreading in immunofluorescence images of macrophages for surface protein CD11b and nuclear counterstaining with DAPI, it is necessary to measure the size of the macrophages at different time points after stimulation. Manual evaluation of fluorescent micrographs is usually a time-consuming and error-prone task, with poor reproducibility. Automatic image analysis methods can be used to improve the results. The quality of the analysis with these methods mainly depends on the quality of the image segmentation. A segmentation and quantification scheme based on shading correction, k-means clustering, and fast marching level sets has been developed for the purpose. An initial application of this approach showed that separating touching and overlapping cells in particular suffers severely in the inevitably blurred conditions, leading to partly erroneous measurements of macrophage spreading. An alternative method of segmentation in fluorescent micrographs was therefore investigated and evaluated in this study. The proposed approach uses a methodology that separates foreground objects from background objects on the basis of Boykov's graph cuts. In this process, a rough estimation of background pixels is used for background seeds. To identify foreground seeds, a difference of Gaussian band pass filter based workflow is developed. Information on foreground and background seeds is then used for a gradient magnitude based graph cut resulting in a robust figure-ground separation method. In addition, a fast marching level set approach is used in the post-processing step, which makes it possible to split touching cells by incorporating information about the cell nuclei. An evaluation based on a total of 553 manually labeled macrophages depicted in 21 micrographs showed that the proposed method significantly improves segmentation and splitting performance for fluorescent micrographs of LPS-stimulated macrophages and reduces the rate of error in automated analysis of macrophage spreading in comparison with alternative methods. © 2013 International Society for Advancement of Cytometry.
UnivIS-Import:2015-04-14:Pub.2013.tech.IMMD.IMMD9.enhanc
Keywords: Fluorescence Microscopy; Image Processing; Computer Assisted Microscopy

Enzymatic lipid oxidation by eosinophils propagates coagulation, hemostasis, and thrombotic disease. - Uderhardt, Stefan; Ackermann, Jochen A.; Fillep, Tobias; Hammond, Victoria J.; Willeit, Johann; Santer, Peter; Mayr, Manuel; Biburger, Markus; Miller, Meike; Zellner, Katie R.; Stark, Konstantin; Zarbock, Alexander; et al. (Journal of Experimental Medicine, 2017)
Blood coagulation is essential for physiological hemostasis but simultaneously contributes to thrombotic disease. However, molecular and cellular events controlling initiation and propagation of coagulation are still incompletely understood. In this study, we demonstrate an unexpected role of eosinophils during plasmatic coagulation, hemostasis, and thrombosis. Using a large-scale epidemiological approach, we identified eosinophil cationic protein as an independent and predictive risk factor for thrombotic events in humans. Concurrent experiments showed that eosinophils contributed to intravascular thrombosis by exhibiting a strong endogenous thrombin-generation capacity that relied on the enzymatic generation and active provision of a procoagulant phospholipid surface enriched in 12/15-lipoxygenase-derived hydroxyeicosatetraenoic acid-phosphatidylethanolamines. Our findings reveal a previously unrecognized role of eosinophils and enzymatic lipid oxidation as regulatory elements that facilitate both hemostasis and thrombosis in response to vascular injury, thus identifying promising new targets for the treatment of thrombotic disease.

Eosinophil extracellular vesicles and DNA traps in allergic inflammation - Weihrauch, Tobias; Melo, Rossana C.N.; Vöhringer, David; Vöhringer, David; Weller, Peter F.; Raap, Ulrike (Frontiers in Allergy, 2024)
Eosinophil granulocytes, a specialized subset of white blood cells, have traditionally been associated with allergic responses and parasitic infections. However, recent research has unveiled their versatile roles in immune regulation beyond these classical functions. This review highlights the emerging field of eosinophil biology, with a particular focus on their release of extracellular vesicles (EVs) and extracellular DNA traps (EETs). It further explores potential implications of eosinophil-derived EVs and EETs for immune responses during inflammatory diseases. The release of EVs/EETs from eosinophils, which also affects the eosinophils themselves, may influence both local and systemic immune reactions, affecting the pathophysiology of conditions such as airway inflammation, chronic rhinosinusitis and atopic dermatitis.
CRIS-Team Scopus Importer:2024-09-06
Keywords: EETosis; eosinophil activation; eosinophilic diseases; extracellular vesicles; inflammation; sombrero vesicles

Eosinophil homing to the bone marrow - Vöhringer, David (Blood, 2020)
CRIS-Team Scopus Importer:2020-12-11

Eosinophils as modulators of host defense during parasitic, fungal, bacterial, and viral infections - Gazzinelli-Guimaraes, Pedro H.; Jones, Shelby M.; Vöhringer, David; Mayer-Barber, Katrin D.; Samarasinghe, Amali E. (Journal of Leukocyte Biology, 2024)
Eosinophils, traditionally associated as central innate effector cells with type 2 immunity during allergic and helminth parasitic diseases, have recently been revealed to have important roles in tissue homeostasis as well as host defense in a broader variety of infectious diseases. In a dedicated session at the 2023 biennial conference of the International Eosinophil Society titled “Eosinophils in Host Defense,” the multifaceted roles eosinophils play against diverse pathogens, ranging from parasites to fungi, bacteria, and viruses, were presented. In this review, the session speakers offer a comprehensive summary of recent discoveries across pathogen classes, positioning eosinophils as pivotal leukocytes in both host defense and pathology. By unraveling the intricacies of eosinophil engagement in host resistance, this exploration may provide valuable insights not only to understand specific underpinnings of eosinophil functions related to each class of pathogens but also to develop novel therapeutics effective against a broad spectrum of infectious diseases.
CRIS-Team Scopus Importer:2025-02-04
Keywords: Aspergillus; eosinophilia; helminth parasites; immune response; influenza; pathogens; vaccine-associated enhanced disease

Eosinophils, but Not Type 2 Innate Lymphoid Cells, Are the Predominant Source of Interleukin 4 during the Innate Phase of Leishmania major Infection - Sasse, Carolin; Barinberg, David; Obermeyer, Stephanie; Debus, Andrea; Schleicher, Ulrike; Bogdan, Christian (Pathogens, 2022)
Interleukin (IL)-4 plays a central role in the initiation of a type 2 T helper cell (Th2) response, which leads to non-healing and progressive infections with the protozoan parasite Leishmania (L.) major. Here, we tested the hypothesis that type 2 innate lymphoid cells (ILC2), which promote the development of Th2 cells, form an important source of IL-4 early after intradermal or subcutaneous L. major infection. Lineage-marker negative CD90.2(+)CD127(+)PD1(-) ILC2 were readily detectable in the ear or foot skin, but hardly in the draining lymph nodes of both naive and L. major-infected self-healing C57BL/6 and non-healing BALB/c mice and made up approximately 20% to 30% of all CD45(+)SiglecF(-) cells. Dermal ILC2 of C57BL/6 mice expressed the inducible T cell-costimulator (ICOS, CD278), whereas BALB/C ILC2 were positive for the stem cell antigen (Sca)-1. Within the first 5 days of infection, the absolute numbers of ILC2 did not significantly change in the dermis, which is in line with the unaltered expression of cytokines activating (IL-18, IL-25, IL-33, TSLP) or inhibiting ILC2 (IL-27, IFN-gamma). At day 5 to 6 post infection, we observed an upregulation of IL-4, but not of IL-5, IL-10 or IL-13 mRNA. Using IL-4-reporter (4get) mice, we found that the production of IL-4 by C57BL/6 or BALB/c mice was largely restricted to CD45(+)FSiglecF(+) cells of high granularity, i.e., eosinophils. From these data, we conclude that eosinophils, but not ILC2, are a major innate source of IL-4 at the skin site of L. major infection.
CRIS-Team WoS Importer:2022-09-09

Eosinophils Mediate Basophil-Dependent Allergic Skin Inflammation in Mice - Eberle, Jörg; Radtke, Daniel; Nimmerjahn, Falk; Vöhringer, David (Journal of Investigative Dermatology, 2019)
The mechanisms leading to allergic skin inflammation, such as atopic dermatitis or urticaria, are poorly defined. Here we used a mouse model for IgE-dependent chronic allergic inflammation to study the role of basophils and eosinophils for induction of pathology. FcεRI expression in basophils was required for the ear swelling response, and basophils promoted the expression of eosinophil-recruiting chemokines in the ear. The ear swelling response could be prevented by prior infection of mice with helminths in an IgE-dependent manner. Impaired skin eosinophilia and reduced ear swelling was further observed in IL-4/IL-13–deficient and STAT6-deficient mice. In addition, eosinophil-deficient ΔdblGATA mice showed only weak ear swelling response, which could be enhanced by eosinophil transfer. This suggests that IgE-activated basophils orchestrate the recruitment of eosinophils by secretion of IL-4/IL-13, which leads to STAT6-dependent expression of CCL24 from endothelial cells and extravasation of eosinophils into the ear pinna. Eosinophils are then the critical effector cells that cause pathology. Therefore, combined therapeutic approaches that block basophil activation and reduce eosinophil numbers could be efficient strategies to improve treatment of chronic allergic disorders of the skin.
CRIS-Team Scopus Importer:2019-07-02

Eosinophil-specific deletion of I?B? in mice reveals a critical role of NF-?B-induced Bcl-xL for inhibition of apoptosis - Schwartz, Christian; Willebrand, Ralf; Huber, Silke; Rupec, Rudolf A.; Wu, Davina; Locksley, Richard; Vöhringer, David (Blood, 2015)
Eosinophils are associated with type 2 immune responses to allergens and helminths. They release various proinflammatory mediators and toxic proteins on activation and are therefore considered proinflammatory effector cells. Eosinophilia is promoted by the cytokines interleukin (IL)-3, IL-5, and granulocyte macrophage-colony-stimulating factor (GM-CSF) and can result from enhanced de novo production or reduced apoptosis. In this study, we show that only IL-5 induces differentiation of eosinophils from bone marrow precursors, whereas IL-5, GM-CSF, and to a lesser extent IL-3 promote survival of mature eosinophils. The receptors for these cytokines use the common ? chain, which serves as the main signaling unit linked to signal transducer and activator of transcription 5, p38 mitogen-activated protein kinase, and nuclear factor (NF)-?B pathways. Inhibition of NF-?B induced apoptosis of in vitro cultured eosinophils. Selective deletion of I?B? in vivo resulted in enhanced expression of Bcl-xL and reduced apoptosis during helminth infection. Retroviral overexpression of Bcl-xL promoted survival, whereas pharmacologic inhibition of Bcl-xL in murine or human eosinophils induced rapid apoptosis. These results suggest that therapeutic strategies targeting Bcl-xL in eosinophils could improve health conditions in allergic inflammatory diseases.
EVALuna2:25866

Eosinophils preserve bone homeostasis by inhibiting excessive osteoclast formation and activity via eosinophil peroxidase. - Andreev, Darja; Kachler, Katerina; Liu, Mengdan; Chen, Zhu; Krishnacoumar, Brenda; Ringer, Mark; Frey, Silke; Krönke, Gerhard; Vöhringer, David; Schett, Georg; Bozec, Aline (Nature Communications, 2024)
Eosinophils are involved in tissue homeostasis. Herein, we unveiled eosinophils as important regulators of bone homeostasis. Eosinophils are localized in proximity to bone-resorbing osteoclasts in the bone marrow. The absence of eosinophils in ΔdblGATA mice results in lower bone mass under steady-state conditions and amplified bone loss upon sex hormone deprivation and inflammatory arthritis. Conversely, increased numbers of eosinophils in IL-5 transgenic mice enhance bone mass under steady-state conditions and protect from hormone- and inflammation- mediated bone loss. Eosinophils strongly inhibit the differentiation and demineralization activity of osteoclasts and lead to profound changes in the transcriptional profile of osteoclasts. This osteoclast-suppressive effect of eosinophils is based on the release of eosinophil peroxidase causing impaired reactive oxygen species and mitogen-activated protein kinase induction in osteoclast precursors. In humans, the number and the activity of eosinophils correlates with bone mass in healthy participants and rheumatoid arthritis patients. Taken together, experimental and human data indicate a regulatory function of eosinophils on bone.
EVALuna2:554518

Epidermal Growth Factor Receptor Expression Licenses Type-2 Helper T Cells to Function in a T Cell Receptor-Independent Fashion. - Minutti, Carlos M.; Drube, Sebastian; Blair, Natalie; Schwartz, Christian; Mccrae, Jame C.; Mckenzie, Andrew N.; Kamradt, Thomas; Mokry, Michal; Coffer, Paul J.; Sibilia, Maria; Sijts, Alice J.; Fallon, Padraic G.; et al. (Immunity, 2017)
Gastro-intestinal helminth infections trigger the release of interleukin-33 (IL-33), which induces type-2 helper T cells (Th2 cells) at the site of infection to produce IL-13, thereby contributing to host resistance in a T cell receptor (TCR)-independent manner. Here, we show that, as a prerequisite for IL-33-induced IL-13 secretion, Th2 cells required the expression of the epidermal growth factor receptor (EGFR) and of its ligand, amphiregulin, for the formation of a signaling complex between T1/ST2 (the IL-33R) and EGFR. This shared signaling complex allowed IL-33 to induce the EGFR-mediated activation of the MAP-kinase signaling pathway and consequently the expression of IL-13. Lack of EGFR expression on T cells abrogated IL-13 expression in infected tissues and impaired host resistance. EGFR expression on Th2 cells was TCR-signaling dependent, and therefore, our data reveal a mechanism by which antigen presentation controls the innate effector function of Th2 cells at the site of inflammation.
Keywords: gastro-intestinal helminth infections; type-2 helper T cells; interleukin-13; interleukin-33; TCR-independent IL-13 secretion; cytokine signaling

Epithelial OPA1 links mitochondrial fusion to inflammatory bowel disease - Bao, Lili; Yu, Yidong; Gonzalez Acera, Miguel; Patankar, Jay; Gießl, Andreas; Sturm, Gregor; Kühl, Anja A.; Atreya, Raja; Erkert, Lena; Gamez-Belmonte, Reyes; Krug, Susanne M.; Schmid, Benjamin; et al. (Science Translational Medicine, 2025)
Dysregulation at the intestinal epithelial barrier is a driver of inflammatory bowel disease (IBD). However, the molecular mechanisms of barrier failure are not well understood. Here, we demonstrate dysregulated mitochondrial fusion in intestinal epithelial cells (IECs) of patients with IBD and show that impaired fusion is sufficient to drive chronic intestinal inflammation. We found reduced expression of mitochondrial fusion–related genes, such as the dynamin-related guanosine triphosphatase (GTPase) optic atrophy 1 (OPA1), and fragmented mitochondrial networks in crypt IECs of patients with IBD. Mice with Opa1 deficiency in the gut epithelium (Opa1i∆IEC) spontaneously developed chronic intestinal inflammation with mucosal ulcerations and immune cell infiltration. Intestinal inflammation in Opa1i∆IEC mice was driven by microbial translocation and associated with epithelial progenitor cell death and gut barrier dysfunction. Opa1-deficient epithelial cells and human organoids exposed to a pharmacological OPA1 inhibitor showed disruption of the mitochondrial network with mitochondrial fragmentation and changes in mitochondrial size, ultrastructure, and function, resembling changes observed in patient samples. Pharmacological inhibition of the GTPase dynamin-1–like protein in organoids derived from Opa1i∆IEC mice partially reverted this phenotype. Together, our data demonstrate a role for epithelial OPA1 in regulating intestinal immune homeostasis and epithelial barrier function. Our data provide a mechanistic explanation for the observed mitochondrial dysfunction in IBD and identify mitochondrial fusion as a potential therapeutic target in this disease.
CRIS-Team Scopus Importer:2025-01-31

Erfolgreiche Therapie der kutanen Leishmaniose mit simulierter Tageslicht-photodynamischer Therapie - Hobelsberger, Sarah; Krauss, Marie-Paloma; Bogdan, Christian; Aschoff, Roland (Hautarzt, 2021)
A 5-year-old Syrian boy , presented with a complex cutaneous leishmaniasis (CL) of the right ankle caused by Leishmania (L.) tropica. The patient received photodynamic therapy (PDT; 6 cycles with application of 5‑aminolevulinic acid and foil occlusion for 3 h). Due to pain during exposure to red light, exposure was continued with simulated daylight (sDL-PDT). The lesion healed with an atrophic scar. Due to fewer side effects and less pain, sDL-PDT seems to be a good therapeutic strategy for CL caused by L. tropica.
CRIS-Team Scopus Importer:2021-07-16
Keywords: 5‑Aminolevulinic acid; Child; Foil occlusion; Leishmania tropica; Simulated daylight photodynamic therapy

ERK activation and autophagy impairment are central mediators of irinotecan-induced steatohepatitis - Mahli, Abdo; Saugspier, Michael; Koch, Andreas; Sommer, Judith; Dietrich, Peter; Lee, Seren; Thasler, Reinhard; Schulze-Luehrmann, Jan; Lührmann, Anja; Thasler, Wolfgang Erwin; Müller, Martina; Boßerhoff, Anja Katrin; et al. (Gut, 2017)
Preoperative chemotherapy with irinotecan is associated with the development of steatohepatitis, which increases the risk of perioperative morbidity and mortality for liver surgery. The molecular mechanisms of this chemotherapeutic complication are widely unknown.Mechanisms of irinotecan-induced steatohepatitis were studied in primary human hepatocytes in vitro, in mice treated with irinotecan and in liver specimens from irinotecan-treated compared with control patients.Irinotecan dose-dependently induced lipid accumulation and pro-inflammatory gene expression in hepatocytes. This was accompanied by an impairment of mitochondrial function with reduced expression of carnitine palmitoyltransferase I and an induction of acyl-coenzyme A oxidase-1 (ACOX1), oxidative stress and extracellular signal-regulated kinase (ERK) activation. ERK inhibition prevented irinotecan-induced pro-inflammatory gene expression but had only a slight effect on lipid accumulation. However, irinotecan also induced an impairment of the autophagic flux mediated by alkalisation of lysosomal pH. Re-acidification of lysosomal pH abolished irinotecan-induced autophagy impairment and lipid accumulation. Also in mice, irinotecan treatment induced hepatic ACOX1 expression, ERK phosphorylation and inflammation, as well as impairment of autophagy and significant steatosis. Furthermore, irinotecan-treated patients revealed higher hepatic ERK activity, expression of pro-inflammatory genes and markers indicative for a shift to peroxisomal fatty acid oxidation and an impaired autophagic flux. Pretreatment with the multityrosine kinase inhibitor sorafenib did not affect autophagy impairment and steatosis but significantly reduced ERK phosphorylation and inflammatory response in irinotecan-treated hepatocytes and murine livers.Irinotecan induces hepatic steatosis via autophagy impairment and inflammation via ERK activation. Sorafenib appears as a novel therapeutic option for the prevention and treatment of irinotecan-induced inflammation.
EVALuna2:4748

Erratum to "Incidence of invasive pneumococcal disease in 5-15 year old children with and without comorbidities in Germany after the introduction of PCV13: Implications for vaccinating children with comorbidities" [Vaccine 33 (2015) 6617-6621], DOI: 10.1016/j.vaccine.2015.10.102 - Weinberger, Raphael; Falkenhorst, Gerhard; Bogdan, Christian; van der Linden, Mark; Imöhl, Matthias; von Kries, Rüdiger (Vaccine, 2016)
CRIS-Team Scopus Importer:2024-02-26

Erratum to: Pneumokokkenimpfung im Säuglings- und im Kleinkindalter: Epidemiologische und immunologische Basis der pädiatrischen Pneumokokkenimpfung (Monatsschrift Kinderheilkunde, (2024), 10.1007/s00112-024-01940-w) - Vygen-Bonnet, Sabine; Schlaberg, Johanna; Kremer-Flach, Katrin; Perriat, Delphine; Bogdan, Christian (Monatsschrift Kinderheilkunde, 2024)
Dieser Artikel enthielt ursprünglich den Satz „Für PCV20 ist nur ein modifiziertes 3 + 1 Schema (Impfung im Alter von 2, 4, 6 und 11 Monaten) zugelassen.“ Korrekt ist: „Für PCV20 ist nur ein 3 + 1 Schema zugelassen.“ Der Originalbeitrag wurde korrigiert.
CRIS-Team Scopus Importer:2024-04-12

Erratum zu: Impfen bei Immundefizienz: Anwendungshinweise zu den von der Ständigen Impfkommission empfohlenen Impfungen.(II) Impfen bei 1. Primären Immundefekterkrankungen und 2. HIV-Infektion (Bundesgesundheitsblatt - Gesundheitsforschung - Gesundheitsschutz, (2018), 61, 8, (1034-1051), 10.1007/s00103-018-2761-8) - Ehl, Stephan; Bogdan, Christian; Niehues, Tim; Burchard, Gerd; Baumann, Ulrich; Hecht, Jane; Koch, Judith; Liese, Johannes G.; Neubert, Jennifer; Wiese-Posselt, Miriam; Zepp, Fred (Bundesgesundheitsblatt, Gesundheitsforschung, Gesundheitsschutz, 2019)
CRIS-Team Scopus Importer:2019-05-28

Evaluating the Use of Neonatal Colonization Screening for Empiric Antibiotic Therapy of Sepsis and Pneumonia - Bär, Alisa; Schmitt-Grohé, Sabina; Held, Jürgen; Lubig, Julia; Hanslik, Gregor; Fahlbusch, Fabian; Reutter, Heiko Martin; Wölfle, Joachim; van der Donk, Adriana; Schleier, Maria; Hepp, Tobias; Morhart, Patrick (Antibiotics, 2023)
(1) Background: Since 2013, weekly screening for multidrug-resistant Gram-negative (MDRGN) bacteria has been performed in German neonatal intensive care units (NICU). National guidelines recommend considering these colonization analyses for antibiotic treatment regimens. Our retrospective single center study provides insight into the clinical dichotomy of bacterial colonization and infection rates in neonates. (2) Methods: We analyzed microbiological data of neonates admitted to our tertiary level NICU over nine years. Colonization with MDRGN/Serratia marcescens (SERMA) was compared to microbiological findings in sepsis and pneumonia. (3) Results: We analyzed 917 blood and 1799 tracheal aspirate samples. After applying criteria from the Nosocomial Infection Surveillance for Neonates (NEO-KISS), we included 52 and 55 cases of sepsis and pneumonia, respectively; 19.2% of sepsis patients and 34.5% of pneumonia patients had a prior colonization with MDRGN bacteria or SERMA. In these patients, sepsis was not attributable to MDRGN bacteria yet one SERMA, while in pneumonias, ten MDRGN bacteria and one SERMA were identified. We identified late-onset pneumonia and cesarean section as risk factors for MDRGN/SERMA acquisition. (4) Conclusions: Colonization screening is a useful tool for hygiene surveillance. However, our data suggest that consideration of colonization with MDRGN/SERMA might promote extensive use of last resort antibiotics in neonates.
CRIS-Team Scopus Importer:2023-03-10
Keywords: colonization; MDR; MDRGN; multidrug-resistant bacteria; multidrug-resistant Gram-negative bacteria; neonatal infection; neonates; pneumonia; screening; sepsis

Evaluation of INSTAND e.V.'s external quality assessment for Cryptococcus antigen testing autumn 2016-spring 2021 - Wilmes, D.; Heckmann, D.; Ehrhard, I.; Schaumburg, F.; Dichtl, K.; Schoerner, Christoph; Mccormick-Smith, I.; Rickerts, V. (MYCOSES, 2021)
CRIS-Team WoS Importer:2021-10-08

Evaluation of the amplex eazyplex loop-mediated isothermal amplification assay for rapid diagnosis of pneumocystis jirovecii pneumonia - Huber, Timo; Serr, Annerose; Geißdörfer, Walter; Hess, Christina; Lynker-Assmus, Christian; Von Loewenich, Friederike D.; Bogdan, Christian; Held, Jürgen (Journal of Clinical Microbiology, 2020)
Quantitative PCR (qPCR) assays are the gold standard for diagnosis of Pneumocystis jirovecii pneumonia (PCP). However, they are laborious and require skilled personnel. Therefore, execution outside regular working hours of the molecular biology laboratory is limited. The eazyplex P. jirovecii assay (PJA) uses loopmediated isothermal amplification for detection of P. jirovecii. It is performed directly with respiratory specimens, without the need for special skills, and delivers a result within 3 to 25 min. The goal of our study was to compare the performance of the eazyplex PJA with that of established P. jirovecii qPCR assays. All archived bronchoalveolar lavage fluid (BALF) samples that had previously tested positive for P. jirovecii by qPCR assay and 50 control samples (retrospective part), as well as all BALF samples received for P. jirovecii analysis over a period of 4 months (prospective part), were tested. Forty-nine patients with proven PCP and 126 patients without PCP were included. The sensitivity and specificity of the eazyplex PJA (95.7% and 96.5%, respectively) were comparable to those for three different P. jirovecii qPCR assays. The detection limit of the eazyplex PJA was analogous to 103 copies of the major surface glycoprotein gene per 25 μl of BALF, corresponding to 10 to 20 P. jirovecii cells. The eazyplex PJA reliably discriminated patients with PCP from patients with P. jirovecii colonization. It delivered a positive result within a mean of 9 min 38 s and required a hands-on time of 2 min 45 s. In summary, the eazyplex PJA showed identical performance for the diagnosis of PCP, compared to qPCR assays. However, in terms of time to result, practicability, and robustness, the eazyplex PJA is clearly superior and allows for around-the-clock molecular testing.
CRIS-Team Scopus Importer:2020-12-11
Keywords: AIDS; BALF; HIV; LAMP; NAT; PCP; PCR; Pneumocystis carinii; Point-of-care

Evaluation of the Loop-Mediated Isothermal Amplification Assay (LAMP) Eazyplex® Pneumocystis jirovecii - Scharmann, Ulrike; Kirchhoff, Lisa; Buer, Jan; Schuler, Franziska; Serr, Annerose; Rößler, Susann; Held, Jürgen; Szumlanski, Tobias; Steinmann, Joerg; Rath, Peter Michael (Journal of Fungi, 2025)
A commercially available loop-mediated isothermal amplification assay (LAMP) for the detection of Pneumocystis jirovecii (P. jirovecii) has been evaluated for the diagnosis of Pneumocystis pneumonia (PcP) in critically ill patients. Altogether, 109 lower respiratory tract specimens from 95 patients with a positive P. jirovecii test in routine diagnostics were collected from five distinct university hospitals in Germany. All samples were tested with a qPCR and eazyplex® LAMP assay. qPCR was set as the gold standard and was evaluated beforehand with samples from 100 patients categorized to have proven, probable, and possible PcP according to the EORTC/MSGERC guidelines. The sensitivity, specificity, and positive and negative predictive value (PPV and NPV) of the LAMP were assessed. Sensitivity was 68%, specificity was 86%, and PPV and NPV were 99% and 16%, respectively. All patients with proven PcP were positive in the LAMP. There was a weak correlation between the time to positivity and the fungal load (squared Pearson correlation coefficient (r2) = 0.5653). A positive result in the LAMP indicates a PcP. Because of the low sensitivity, negative results do not rule out an infection and should be clarified with further molecular methods. The LAMP should be used in patients in whom a PcP is expected, not for screening only.
CRIS-Team Scopus Importer:2025-05-09
Keywords: fungal infection; LAMP; molecular diagnostic; Pneumocystis jirovecii; pulmonary infection; qPCR

Exogenous TNFR2 activation protects from acute GvHD via host T reg cell expansion - Chopra, Martin; Biehl, Marlene; Steinfatt, Tim; Brandl, Andreas; Kums, Juliane; Amich, Jorge; Vaeth, Martin; Kuen, Janina; Holtappels, Rafaela; Podlech, Juergen; Mottok, Anja; Kraus, Sabrina; et al. (Journal of Experimental Medicine, 2016)
Donor CD4(+)Foxp3(+) regulatory T cells (T reg cells) suppress graft-versus-host disease (GvHD) after allogeneic hematopoietic stem cell transplantation (HCT [allo-HCT]). Current clinical study protocols rely on the ex vivo expansion of donor T reg cells and their infusion in high numbers. In this study, we present a novel strategy for inhibiting GvHD that is based on the in vivo expansion of recipient T reg cells before allo-HCT, exploiting the crucial role of tumor necrosis factor receptor 2 (TNFR2) in T reg cell biology. Expanding radiation-resistant host T reg cells in recipient mice using a mouse TNFR2-selective agonist before allo-HCT significantly prolonged survival and reduced GvHD severity in a TNFR2- and T reg cell-dependent manner. The beneficial effects of transplanted T cells against leukemia cells and infectious pathogens remained unaffected. A corresponding human TNFR2-specific agonist expanded human T reg cells in vitro. These observations indicate the potential of our strategy to protect allo-HCT patients from acute GvHD by expanding T reg cells via selective TNFR2 activation in vivo.
EVALuna2:7721

Experimental Cutaneous Leishmaniasis: Mouse Models for Resolution of Inflammation Versus Chronicity of Disease - Bogdan, Christian; Debus, Andrea; Sebald, Heidi; Rai, Baplu; Schäfer, Johanna; Obermeyer, Stephanie; Schleicher, Ulrike (Leishmania, 2019)
Experimental cutaneous leishmaniasis of mice is a valuable model to study the immune response to the protozoan pathogen Leishmania and to define mechanisms of parasite control and resolution of inflammation as well as of parasite evasion and chronicity of disease. In addition, over many years Leishmania-infected mice have been successfully used to analyze the function of newly discovered immune cell types, transcription factors, cytokines, and effector mechanisms in vivo. In this chapter we present detailed protocols for the culture, propagation, and inoculation of Leishmania promastigotes, the monitoring of the course of cutaneous infection, the determination of the tissue parasite burden and for the phenotyping of the ensuing immune response. The focus lies on the L. major mouse model, but an overview on other established models of murine cutaneous leishmaniasis is also provided.
CRIS-Team Scopus Importer:2019-05-02
Keywords: Cutaneous leishmaniasis; Leishmania major; Mouse models

Exploration of Sulfur Assimilation of Aspergillus fumigatus Reveals Biosynthesis of Sulfur-Containing Amino Acids as a Virulence Determinant - Amich, Jorge; Duemig, Michaela; O'Keeffe, Grainne; Binder, Jasmin; Doyle, Sean; Beilhack, Andreas; Krappmann, Sven (Infection and Immunity, 2016)
Fungal infections are of major relevance due to the increased numbers of immunocompromised patients, frequently delayed diagnosis, and limited therapeutics. To date, the growth and nutritional requirements of fungi during infection, which are relevant for invasion of the host, are poorly understood. This is particularly true for invasive pulmonary aspergillosis, as so far, sources of (macro)elements that are exploited during infection have been identified to only a limited extent. Here, we have investigated sulfur (S) utilization by the human-pathogenic mold Aspergillus fumigatus during invasive growth. Our data reveal that inorganic S compounds or taurine is unlikely to serve as an S source during invasive pulmonary aspergillosis since a sulfate transporter mutant strain and a sulfite reductase mutant strain are fully virulent. In contrast, the S-containing amino acid cysteine is limiting for fungal growth, as proven by the reduced virulence of a cysteine auxotroph. Moreover, phenotypic characterization of this strain further revealed the robustness of the subordinate glutathione redox system. Interestingly, we demonstrate that methionine synthase is essential for A. fumigatus virulence, defining the biosynthetic route of this proteinogenic amino acid as a potential antifungal target. In conclusion, we provide novel insights into the nutritional requirements ofA. fumigatus during pathogenesis, a prerequisite to understanding and fighting infection.
EVALuna2:7707

Exploring the interrelationship between the skin microbiome and skin volatiles: A pilot study - Härtl, Tobias; Owsienko, Diana; Schwinn, Leo; Hirsch, Cathrin; Eskofier, Björn; Lang, Roland; Wirtz, Stefan; Loos, Helene (Frontiers in Ecology and Evolution, 2023)
Unravelling the interplay between a human’s microbiome and physiology is a relevant task for understanding the principles underlying human health and disease. With regard to human chemical communication, it is of interest to elucidate the role of the microbiome in shaping or generating volatiles emitted from the human body. In this study, we characterized the microbiome and volatile organic compounds (VOCs) sampled from the neck and axilla of ten participants (five male, five female) on two sampling days, by applying different methodological approaches. Volatiles emitted from the respective skin site were collected for 20 min using textile sampling material and analyzed on two analytical columns with varying polarity of the stationary phase. Microbiome samples were analyzed by a culture approach coupled with MALDI-TOF-MS analysis and a 16S ribosomal RNA gene (16S RNA) sequencing approach. Statistical and advanced data analysis methods revealed that classification of body sites was possible by using VOC and microbiome data sets. Higher classification accuracy was achieved by combination of both data pools. Cutibacterium, Staphylococcus, Micrococcus, Streptococcus, Lawsonella, Anaerococcus, and Corynebacterium species were found to contribute to classification of the body sites by the microbiome. Alkanes, esters, ethers, ketones, aldehydes and cyclic structures were used by the classifier when VOC data were considered. The interdisciplinary methodological platform developed here will enable further investigations of skin microbiome and skin VOCs alterations in physiological and pathological conditions.
CRIS-Team Scopus Importer:2023-02-17
Keywords: axilla; body odor; chemical communication; gas chromatography–mass spectrometry; multi-omic analyses; neck

Expression of HIF1α in intestinal epithelium restricts arthritis inflammation by inhibiting RIPK3-induced cell death machinery - Lyu, Pang; Wen, Jinming; Zhang, Wenshuo; Liu, Ning; Stolzer, Iris; Gießl, Andreas; Jia, Yewei; Mauro, Daniele; Zhang, Fulin; Ciccia, Francesco; Soulat, Didier; Günther, Claudia; et al. (Annals of the Rheumatic Diseases, 2024)
Objectives: To investigate the mechanism by which intestinal epithelial cell (IEC) death induces arthritis. Methods: IEC death was assessed by staining for necroptosis and apoptosis markers and fluorescence in situ hybridisation at different time points during collagen-induced arthritis (CIA). During the development of CIA, messenger RNA (mRNA) sequencing was performed, followed by Gene Ontology enrichment analysis of differentially expressed genes. Mice deficient for hypoxia-inducible factor 1α (Hif1a) in IECs (Hif1aΔIEC) were generated and induced for arthritis. mRNA sequencing, chromatin immunoprecipitated (ChIP) DNA sequencing and ChIP-qualitative PCR were performed on IECs from Hif1aΔIEC mice and littermate controls. Effects of HIF1α stabilisation by inhibition of prolyl hydroxylase domain-containing enzymes and treatment with the inhibitor of receptor-interacting protein kinase-3 (RIPK3) were tested in intestinal organoids and in CIA. Results: IEC underwent apoptotic and necroptotic cell death at the onset of arthritis, leading to impaired gut barrier function. HIF1α was identified as one of the most upregulated genes in IECs during the onset of arthritis. Deletion of Hif1a in IEC enhanced IEC necroptosis, triggered intestinal inflammation and exacerbated arthritis. HIF1α was found to be a key transcriptional repressor for the necroptosis-inducing factor RIPK3. Enhanced RIPK3 expression, indicating necroptosis, was also found in the intestinal epithelium of patients with new-onset rheumatoid arthritis. Therapeutic stabilisation of HIF1α as well as small-molecule-based RIPK3 inhibition rescued intestinal necroptosis in vitro and in vivo and suppressed the development of arthritis. Conclusion: Our results identify IEC necroptosis as a critical link between the gut and the development of arthritis.
CRIS-Team Scopus Importer:2024-04-05
Keywords: Arthritis; Experimental; Arthritis; Rheumatoid; Immune System Diseases; Inflammation

Ex vivo metabolic profiling of physiological human T cell responses - Schuster, Ev-Marie; Frischholz, Sina; Schuelein, C.; Alsalameh, R.; Esse, Jan; Bogdan, Christian; Held, Jürgen; Schober, Kilian (EUROPEAN JOURNAL OF IMMUNOLOGY, 2022)
CRIS-Team WoS Importer:2023-02-17

Faecal microbiota transplantation-A clinical view - Mattner, Jochen; Schmidt, F.; Siegmund, B. (International Journal of Medical Microbiology, 2016)
Faecal microbiota transplantation has gained increasing attention over the last decade as various phenotypes could be transferred from a donor to a recipient in different animal models. Clinically, however, the sole indication with evidence from a randomized placebo controlled trial is refractory Clostridium difficile infection. Despite revealing successful clinical outcomes, questions concerning regulatory affairs, the identification of the best donor, the optimal mixture of the transplant as well as the preferred route of administration remain to be clarified even for this indication. Initiated by the idea that alterations in the composition of the intestinal microbiota are associated with intestinal inflammation in inflammatory bowel disease, several studies investigated whether faecal microbiota transplantation would be an equally suitable approach for these devastating disorders. Indeed, the available data indicate changes in the microbiota composition following faecal microbial transplantation depending on the degree of intestinal inflammation. Furthermore, first data even provide evidence that the transplantation of an "optimized" microbiota induces clinical remission in ulcerative colitis. However, despite these intriguing results it needs to be considered that not only "a cure of inflammation", but also risk factors and phenotypes including obesity can be transferred via faecal microbiota transplantation. Thus, a deeper understanding of the impact of a distinct microbiota composition is required before "designing" the optimal faecal microbiota transplant.
EVALuna2:7702

Fatal Leishmaniasis in the Absence of TNF Despite a Strong Th1 Response - Fromm, Phillip D.; Kling, Jessica C.; Remke, Annika; Bogdan, Christian; Koerner, Heinrich (Frontiers in Microbiology, 2015)
Induction of inducible nitric oxide synthase in mononuclear phagocytes by IFN-? and innate tumor necrosis factor (TNF) provide the basis for an effective immune response to the intracellular parasite Leishmania (L.) major. In previous experiments, we observed a fatal visceral form of leishmaniasis in L. major-infected C57BL/6 TNF(-/-) mice. To further delineate the protective function of TNF and its receptor requirements, we comparatively assessed L. major-infected C57BL/6 mice that were either deficient for membrane and soluble TNF (Tnf (-) (/) (-)), for soluble TNF alone (memTnf(?/?) ), or the TNF receptors type 1 (Tnfr1 (-) (/) (-)) or type 2 (Tnfr2 (-) (/) (-)). We detected locally and systemically increased levels of the cytokine IFN-? in the absence of the TNF-TNFR1-signaling pathway. An analysis of transcription factors and cytokines revealed that activated Tnf (-) (/) (-) CD4(+) T cells displayed a highly active Th1 phenotype with a strong usage of the T cell receptor V?5.1/2. From these data we conclude that the fatal outcome of L. major infection in Tnf (-) (/) (-) mice does not result from a skewed or deficient Th1 differentiation.
EVALuna2:7701

Fatal Mycotic Aneurysm of the Basilar Artery Caused by Aspergillus fumigatus in a Patient with Pituitary Adenoma and Meningitis - Winterholler, Martin; Coras, Roland; Geißdörfer, Walter; Rammensee, Rudolf; Gölitz, Philipp; Bogdan, Christian; Lang, Roland (Frontiers in Medicine, 2017)
Fungal infections of the central nervous system (CNS) frequently occur in immunosuppressed patients. Here, we describe the case of an immunocompetent 64-year-old man who presented with diplopia, right-sided hemiparesis, and a mild headache after cleaning and replacing nesting boxes of wild birds during the preceding months. Lumbar puncture revealed pleocytosis, elevated protein, and lactate levels in the cerebrospinal fluid (CSF). Initial imaging showed ischemia in the left thalamus and an enlargement of the sellar region. Antibiotic treatment and corticosteroids led to an initial improvement but was followed by rapid deterioration. Antibiotic treatment was modified and antifungal therapy was added. Eighteen days after admission, the patient died from a subarachnoid hemorrhage resulting from the rupture of a fusiform aneurysm of the basilar artery. Microbiological culture of CSF was negative, but a positive galactomannan assay suggested fungal infection which was corroborated by detection of Aspergillus fumigatus DNA in pan-fungal PCR and sequencing. The presence of septated hyphae in the wall of the basilar artery confirmed the diagnosis of a mycotic aneurysm caused by hyphomycetal infection. In addition, brain autopsy revealed the presence of an invasive adrenocorticotrophic hormone-producing pituitary adenoma with arrosion of the sellar bone. This process and its invasiveness likely facilitated the spread of the fungal pathogen from the sphenoid sinus to the dura mater and finally led to cerebral angioinvasion. Our case demonstrates the challenge to timely diagnose and effectively treat aspergillosis as a cause of CNS infection also in apparently immunocompetent patients. The potential of assays detecting fungal antigens and of PCR to facilitate a timely diagnosis is discussed.
EVALuna2:7760

Ferritin-Mediated Iron Sequestration Stabilizes Hypoxia-Inducible Factor-1α upon LPS Activation in the Presence of Ample Oxygen. - Siegert, Isabel; Schödel, Johannes; Nairz, Manfred; Schatz, Valentin; Dettmer, Katja; Dick, Christopher; Kalucka, Joanna; Franke, Kristin; Ehrenschwender, Martin; Schley, Gunnar; Beneke, Angelika; Sutter, Jörg; et al. (Cell Reports, 2015)
Both hypoxic and inflammatory conditions activate transcription factors such as hypoxia-inducible factor (HIF)-1α and nuclear factor (NF)-κB, which play a crucial role in adaptive responses to these challenges. In dendritic cells (DC), lipopolysaccharide (LPS)-induced HIF1α accumulation requires NF-κB signaling and promotes inflammatory DC function. The mechanisms that drive LPS-induced HIF1α accumulation under normoxia are unclear. Here, we demonstrate that LPS inhibits prolyl hydroxylase domain enzyme (PHD) activity and thereby blocks HIF1α degradation. Of note, LPS-induced PHD inhibition was neither due to cosubstrate depletion (oxygen or α-ketoglutarate) nor due to increased levels of reactive oxygen species, fumarate, and succinate. Instead, LPS inhibited PHD activity through NF-κB-mediated induction of the iron storage protein ferritin and subsequent decrease of intracellular available iron, a critical cofactor of PHD. Thus, hypoxia and LPS both induce HIF1α accumulation via PHD inhibition but deploy distinct molecular mechanisms (lack of cosubstrate oxygen versus deprivation of co-factor iron).

First assessment for the presence of phlebotomine vectors in bavaria, southern germany, by combined distribution modeling and field surveys - Haeberlein, Simone; Fischer, Dominik; Thomas, Stephanie Margarete; Schleicher, Ulrike; Beierkuhnlein, Carl; Bogdan, Christian (PLoS ONE, 2013)
Leishmaniasis is caused by protozoa of the genus Leishmania and transmitted by sand flies from mammalian reservoirs to humans. In recent years, a northward spread of L. infantum from highly endemic Mediterranean countries into previously non-endemic Central European areas has been suspected based on presumed sporadic cases of autochthonous leishmaniasis. Here, we investigated whether sand flies are prevalent in Bavaria in Southern Germany, a federal state in which autochthonous cases have previously been reported. Considering the present and future climatic conditions, we determined whether Bavaria is suitable for five sand fly species with assumed spreading tendencies towards Central Europe: Phlebotomus ariasi , P. neglectus , P. perfiliewi and P. perniciosus that are known vectors for Leishmania in Europe, and P. mascittii, a suspected but not proven vector. Within Bavaria we defined sampling regions based on their climatic suitability and their spatial distance to the sites of the autochthonous cases and/or to areas of reported sand fly detection in states adjacent to Bavaria. At 155 locations in 7 sampling regions, CDC light traps were placed during 38 nights in the summers of 2009 and 2010, resulting in 202 trap-nights. All traps were negative for sand flies. The results suggest that Bavaria is not yet endemic for sand flies, but do not exclude the possibility of sporadic cases of autochthonous human or zoonotic Leishmania infections. This study, which combined methodological approaches from different disciplines, serves as reference for future surveys and risk analyses of sand flies and leishmaniasis in so far non-endemic areas of Europe. © 2013 Simone Haeberlein.
CRIS-Team Scopus Importer:2024-02-26

First report of the new emerging global clone ST1193 among clinical isolates of extended-spectrum beta-lactamase (ESBL)-producing Escherichia coli from Germany - Valenza, Giuseppe; Werner, Markus; Eisenberger, David; Nickel, Silke; Lehner-Reindl, Verena; Hoeller, Christiane; Bogdan, Christian (Journal of Global Antimicrobial Resistance, 2019)
Objectives: Sequence type 1193 (ST1193) is a new emerging global clone of Escherichia coli. The main goal of this study was to determine the prevalence and molecular characteristics of ST1193 among clinical isolates of extended-spectrum beta-lactamase (ESBL)-producing E. coli from University Hospital of Erlangen, Germany.
CRIS-Team WoS Importer:2019-07-09

First two years of data curation by the German national candidemia surveillance network: New insights into epidemiology and resistance - Aldejohann, A. M.; Wallstabe, J.; Reinhardt, M.; Martin, R.; Elias, J.; Mattwich, C.; Hamprecht, A.; Held, Jürgen; Hess, C.; Hogardt, M.; Vorbeck, L.; Rath, P. M.; et al. (MYCOSES, 2022)
CRIS-Team WoS Importer:2022-09-23

Flagellin hypervariable region determines symbiotic properties of commensal Escherichia coli strains - Steimle, Alex; Menz, Sarah; Bender, Annika; Ball, Brianna; Weber, Alexander N. R.; Hagemann, Thomas; Lange, Anna; Maerz, Jan K.; Peruse, Raphael; Michaelis, Lena; Schaefer, Andrea; Yao, Hans; et al. (Plos Biology, 2019)
Escherichia coli represents a classical intestinal gram-negative commensal. Despite this commensalism, different E. coli strains can mediate disparate immunogenic properties in a given host. Symbiotic E. coli strains such as E. coli Nissle 1917 (EcN) are attributed beneficial properties, e.g., promotion of intestinal homeostasis. Therefore, we aimed to identify molecular features derived from symbiotic bacteria that might help to develop innovative therapeutic alternatives for the treatment of intestinal immune disorders. This study was performed using the dextran sodium sulphate (DSS)-induced colitis mouse model, which is routinely used to evaluate potential therapeutics for the treatment of Inflammatory Bowel Diseases (IBDs). We focused on the analysis of flagellin structures of different E. coli strains. EcN flagellin was found to harbor a substantially longer hypervariable region (HVR) compared to other commensal E. coli strains, and this longer HVR mediated symbiotic properties through stronger activation of Toll-like receptor (TLR)5, thereby resulting in interleukin (IL)-22-mediated protection of mice against DSS-induced colitis. Furthermore, using bone-marrow-chimeric mice (BMCM), CD11c+ cells of the colonic lamina propria (LP) were identified as the main mediators of these flagellin-induced symbiotic effects. We propose flagellin from symbiotic E. coli strains as a potential therapeutic to restore intestinal immune homeostasis, e.g., for the treatment of IBD patients.
CRIS-Team WoS Importer:2019-07-19

Flow cytometry as a new complementary tool to study Coxiella burnetii in cell cultures - Rebbig, Annica; Matthiesen, Svea; Lührmann, Anja; Knittler, Michael R. (Journal of Microbiological Methods, 2018)
Flow cytometry enables the analysis of cells by labeling them with fluorescent probes. We describe a novel flow cytometric approach permitting reliable analysis of Coxiella (C.) burnetii-infected cells. The method quantifies infection-forming units (IFUs) in a dose-dependent manner and allows for the specific detection of infection/replication-competent coxiella in cell cultures.
EVALuna2:36416

Flt3L controls the number of innate lymphoid cells in fetal and adult mice - Barenwaldt, A.; Von Burg, N.; Kreuzaler, M.; Sitte, S.; Horvath, E.; Peter, A.; Vöhringer, David; Rolink, A.; Finke, D. (2016)
EVALuna2:33425

Flt3 Ligand Regulates the Development of Innate Lymphoid Cells in Fetal and Adult Mice - Baerenwaldt, Anne; Von Burg, Nicole; Kreuzaler, Matthias; Sitte, Selina; Horvath, Edit; Peter, Annick; Vöhringer, David; Rolink, Antonius G.; Finke, Daniela (Journal of Immunology, 2016)
Flt3 ligand (Flt3L) promotes survival of lymphoid progenitors in the bone marrow and differentiation of dendritic cells (DCs), but its role in regulating innate lymphoid cells (ILCs) during fetal and adult life is not understood. By using Flt3L knockout and transgenic mice, we demonstrate that Flt3L controls ILC numbers by regulating the pool of ?4?7(-) and ?4?7(+) lymphoid tissue inducer cell progenitors in the fetal liver and common lymphoid progenitors in the bone marrow. Deletion of flt3l severely reduced the number of fetal liver progenitors and lymphoid tissue inducer cells in the neonatal intestine, resulting in impaired development of Peyer's patches. In the adult intestine, NK cells and group 2 and 3 ILCs were severely reduced. This effect occurred independently of DCs as ILC numbers were normal in mice in which DCs were constitutively deleted. Finally, we could show that administration of Flt3L increased the number of NKp46(-) group 3 ILCs in wild-type and even in Il7(-/-) mice, which generally have reduced numbers of ILCs. Taken together, Flt3L significantly contributes to ILC and Peyer's patches development by targeting lymphoid progenitor cells during fetal and adult life.
EVALuna2:7713

Follicular Conjunctivitis due to Chlamydia felis-Case Report, Review of the Literature and Improved Molecular Diagnostics - Wons, Juliana; Meiller, Ralph; Bergua, Antonio; Bogdan, Christian; Geißdörfer, Walter (Frontiers in Medicine, 2017)
A 29-year-old woman presented with unilateral, chronic follicular conjunctivitis since 6 weeks. While the conjunctival swab taken from the patient's eye was negative in a Chlamydia (C.) trachomatis-specific PCR, C. felis was identified as etiological agent using a pan-Chlamydia TaqMan-PCR followed by sequence analysis. A pet kitten of the patient was found to be the source of infection, as its conjunctival and pharyngeal swabs were also positive for C. felis. The patient was successfully treated with systemic doxycycline. This report, which presents one of the few documented cases of human C. felis infection, illustrates that standard PCR tests are designed to detect the most frequently seen species of a bacterial genus but might fail to be reactive with less common species. We developed a modified pan-Chlamydia/C. felis duplex TaqMan-PCR assay that detects C. felis without the need of subsequent sequencing. The role of chlamydiae-specific serum antibody titers for the diagnosis of follicular conjunctivitis is discussed.
EVALuna2:7759

Foxp1 controls mature B cell survival and the development of follicular and B-1 B cells - Patzelt, Thomas; Keppler, Selina J.; Gorka, Oliver; Thoene, Silvia; Wartewig, Tim; Reth, Michael; Foerster, Irmgard; Lang, Roland; Buchner, Maike; Ruland, Juergen (Proceedings of the National Academy of Sciences of the United States of America, 2018)
The transcription factor Foxp1 is critical for early B cell development. Despite frequent deregulation of Foxp1 in B cell lymphoma, the physiological functions of Foxp1 in mature B cells remain unknown. Here, we used conditional gene targeting in the B cell lineage and report that Foxp1 disruption in developing and mature B cells results in reduced numbers and frequencies of follicular and B-1 B cells and in impaired antibody production upon T cell-independent immunization in vivo. Moreover, Foxp1-deficient B cells are impaired in survival even though they exhibit an increased capacity to proliferate. Transcriptional analysis identified defective expression of the prosurvival Bcl-2 family gene Bcl2l1 encoding Bcl-xl in Foxp1-deficient B cells, and we identified Foxp1 binding in the regulatory region of Bcl2l1 Transgenic overexpression of Bcl2 rescued the survival defect in Foxp1-deficient mature B cells in vivo and restored peripheral B cell numbers. Thus, our results identify Foxp1 as a physiological regulator of mature B cell survival mediated in part via the control of Bcl-xl expression and imply that this pathway might contribute to the pathogenic function of aberrant Foxp1 expression in lymphoma.
EVALuna2:36430

FRA-1 TRANSCRIPTION FACTOR EXPRESSION IN MACROPHAGES FOSTER INFLAMMATION DURING RHEUMATOID ARTHRITIS DEVELOPMENT - Hannemann, Nicole; Schnelzer, Anne; Jordan, Jutta; Eberhardt, Martin; Schleicher, Ulrike; Hueber, Axel; Reid, Stephen; Sonnewald, Sophia; Bäuerle, Tobias; Vera, Julio; Bogdan, Christian; Schett, Georg; et al. (2017)
EVALuna2:13497

Friend or Foe? The Ambiguous Role of Innate Lymphoid Cells in Cancer Development - Mattner, Jochen; Wirtz, Stefan (Trends in Immunology, 2017)
The development of immunotherapies represents a major advance towards the effective eradication of malignant tumors. So far, therapeutic approaches have largely focused on T lymphocytes, but the innate arm of the immune system might be similarly important. Innate lymphoid cells (ILCs) are rapidly-responding cells that are functionally analogous to diverse T cell subsets. In recent years these cells have attracted enormous attention owing to their pleiotropic effects in early host defense to infection and organ pathologies. ILCs might also represent promising targets in the context of cancer therapy because they are an innate immune cell population endowed with potent immunomodulatory properties. In this review we discuss the impact of the three ILC subsets and the signature cytokines they release on cancer development and tumor growth.
EVALuna2:7741

Functional impact of reverse signalling via PD-L1 in ILC2 during type 2 immune responses - Bailer, Moritz; Deinzer, Andrea; Schmidt, Viviane; Schwartz, Christian (EUROPEAN JOURNAL OF IMMUNOLOGY, 2022)
CRIS-Team WoS Importer:2023-01-27

Functionality of antigen-specific T cell receptor repertoires after SARS-CoV-2 vaccination - Kocher, Katharina; Drost, F.; Schuelein, C.; Moosmann, Carolin; D'Ippolito, E.; Busch, D. H.; Bogdan, Christian; Tenbusch, Matthias; Schubert, B.; Schober, Kilian (EUROPEAN JOURNAL OF IMMUNOLOGY, 2022)
CRIS-Team WoS Importer:2023-01-27

Function of Macrophage and Parasite Phosphatases in Leishmaniasis - Soulat, Didier; Bogdan, Christian (Frontiers in Immunology, 2017)
The kinetoplastid protozoan parasites belonging to the genusLeishmaniaare the causative agents of different clinical forms of leishmaniasis, a vector-borne infectious disease with worldwide prevalence. The protective host immune response againstLeishmaniaparasites relies on myeloid cells such as dendritic cells and macrophages in which upon stimulation by cytokines (e.g., interferon-γ) a complex network of signaling pathways is switched on leading to strong antimicrobial activities directed against the intracellular parasite stage. The regulation of these pathways classically depends on post-translational modifications of proteins, with phosphorylation events playing a cardinal role.Leishmaniaparasites deactivate their phagocytic host cells by inducing specific mammalian phosphatases that are capable to impede signaling. On the other hand, there is now also evidence thatLeishmaniaspp. themselves express phosphatases that might target host cell molecules and thereby facilitate the intracellular survival of the parasite. This review will present an overview on the modulation of host phosphatases byLeishmaniaparasites as well as on the known families ofLeishmaniaphosphatases and their possible function as virulence factors. A more detailed understanding of the role of phosphatases inLeishmania-host cell interactions might open new avenues for the treatment of non-healing, progressive forms of leishmaniasis.
EVALuna2:33306

Gaps in Vaccine Coverage and Adverse Effects of Vaccines - An Overview - Bogdan, Christian (Deutsche Medizinische Wochenschrift, 2019)
The success of vaccination programs is jeopardized by gaps in vaccine coverage of the target population. These are frequently due to a lack of awareness, but also result from misconceptions of adverse effects of vaccines. Subject of this article are the current vaccination rates of children, adolescents and adults as well as of medical personnel in Germany, the reporting and surveillance system for adverse effects of vaccines, the magnitude of registered permanent vaccine-induced damages and the possible immunological mechanisms underlying vaccine-triggered autoimmune diseases.
CRIS-Team WoS Importer:2019-03-06

Generation, culture and flow-cytometric characterization of primary mouse macrophages - Schleicher, Ulrike; Bogdan, Christian (Macrophages and Dendritic Cells: Methods and Protocols, 2009)
Macrophages are not only host cells for many pathogens, but also fulfill several key functions in the innate and adaptive immune response, including the release of pro- and anti-inflammatory cytokines, the generation of organic and inorganic autacoids, the phagocytosis and killing of intracellular microorganisms or tumor cells, and the degradation and presentation of antigens. Several of these functions are shared by other immune cells, including dendritic cells, granulocytes, NK cells, and/or T lymphocytes. Thus, the analysis of macrophage functions in vitro using primary mouse cell populations requires standardized methods for the generation and culture of macrophages that guarantee high cell purity as well as the absence of stimulatory microbial contaminants. This chapter presents methodology to achieve these aims. © 2009 Humana Press, a part of Springer Science+Business Media, LLC.
CRIS-Team Scopus Importer:2024-02-26
Keywords: Bone marrow-derived macrophages; Cell sorting; Cytokines; Flow cytometry; Interferon-gamma; Macrophages; Peritoneal exudate macrophages; Resident peritoneal macrophages; Teflon bags

Genetic and functional data identifying Cd101 as a type 1 diabetes (T1D) susceptibility gene in nonobese diabetic (NOD) mice - Mattner, Jochen; Mohammed, Javid P.; Fusakio, Michael E.; Giessler, Claudia; Hackstein, Carl Philipp; Opoka, Robert; Wrage, Marius; Schey, Regina; Clark, Jan; Fraser, Heather I.; Rainbow, Daniel B.; Wicker, Linda S. (PLoS Genetics, 2019)
Type 1 diabetes (T1D) is a chronic multi-factorial disorder characterized by the immune-mediated destruction of insulin-producing pancreatic beta cells. Variations at a large number of genes influence susceptibility to spontaneous autoimmune T1D in non-obese diabetic (NOD) mice, one of the most frequently studied animal models for human disease. The genetic analysis of these mice allowed the identification of many insulin-dependent diabetes (Idd) loci and candidate genes, one of them being Cd101. CD101 is a heavily glycosylated transmembrane molecule which exhibits negative-costimulatory functions and promotes regulatory T (Treg) function. It is abundantly expressed on subsets of lymphoid and myeloid cells, particularly within the gastrointestinal tract. We have recently reported that the genotype-dependent expression of CD101 correlates with a decreased susceptibility to T1D in NOD.B6 Idd10 congenic mice compared to parental NOD controls. Here we show that the knockout of CD101 within the introgressed B6-derived Idd10 region increased T1D frequency to that of the NOD strain. This loss of protection from T1D was paralleled by decreased Gr1-expressing myeloid cells and FoxP3+ Tregs and an enhanced accumulation of CD4-positive over CD8-positive T lymphocytes in pancreatic tissues. As compared to CD101+/+ NOD.B6 Idd10 donors, adoptive T cell transfers from CD101-/- NOD.B6 Idd10 mice increased T1D frequency in lymphopenic NOD scid and NOD.B6 Idd10 scid recipients. Increased T1D frequency correlated with a more rapid expansion of the transferred CD101-/- T cells and a lower proportion of recipient Gr1-expressing myeloid cells in the pancreatic lymph nodes. Fewer of the Gr1+ cells in the recipients receiving CD101-/- T cells expressed CD101 and the cells had lower levels of IL-10 and TGF-β mRNA. Thus, our results connect the Cd101 haplotype-dependent protection from T1D to an anti-diabetogenic function of CD101-expressing Tregs and Gr1-positive myeloid cells and confirm the identity of Cd101 as Idd10.
CRIS-Team Scopus Importer:2019-07-09

Genetic surgery in fungi: employing site-specific recombinases for genome manipulation - Krappmann, Sven (Applied Microbiology and Biotechnology, 2014)
Site-specific recombination mediates the rearrangement of nucleic acids by the virtue of an recombinase acting on specific recognition sequences. Recombining activities belong either to the tyrosine- or serine-type group, based on the presence of specific residues in the catalytic centre, which can be further subdivided into families due to additional criteria. The most prominent systems are the ? phage integrase acting on att sites; the Cre recombinase from bacteriophage P1 with its loxP attachment sites; the FLP/FTR system of fungal origin, where it is required for 2-?m plasmid replication/amplification in yeast; and the prokaryotic ?-recombinase that recombines six sites specifically in cis. Each of these has been exploited in fungal hosts of biotechnological, medical or general relevance, mainly for cloning projects, approaches of gene targeting, genome modification or screening purposes. With their precise and defined mode of action are site-specific recombination systems eminently suited for genetic tasks in fungi, like they are executed in functional studies at high throughput or modern approaches of synthetic biology.
EVALuna2:7574

GENE-TRANSFER METHODOLOGY AFFECTS CHIMERIC ANTIGEN RECEPTOR EXPRESSION AND REGULATION IN T-CELLS, AND DETERMINES ANTITUMOR POTENCY IN THE CONTEXT OF HIGH VS. LOW TARGET ANTIGEN DENSITY - Gehrke, L.; Verbruggen, C.; Nerreter, T.; Schober, Kilian; Busch, D.; Einsele, H.; Sauer, M.; Hudecek, M.; Weber, J. (HUMAN GENE THERAPY, 2022)
CRIS-Team WoS Importer:2022-10-21

Gene Trap Mice Reveal an Essential Function of Dual Specificity Phosphatase Dusp16/MKP-7 in Perinatal Survival and Regulation of Toll-like Receptor (TLR)-induced Cytokine Production - Niedzielska, Magdalena; Bodendorfer, Barbara; Muench, Sandra; Eichner, Alexander; Derigs, Marcus; Da Costa, Olivia; Schweizer, Astrid; Neff, Frauke; Nitschke, Lars; Sparwasser, Tim; Keyse, Stephen M.; Lang, Roland (Journal of Biological Chemistry, 2014)
MAPK activity is negatively regulated by members of the dual specificity phosphatase (Dusp) family, which differ in expression, substrate specificity, and subcellular localization. Here, we investigated the function of Dusp16/MKP-7 in the innate immune system. The Dusp16 isoforms A1 and B1 were inducibly expressed in macrophages and dendritic cells following Toll-like receptor stimulation. A gene trap approach was used to generate Dusp16-deficient mice. Homozygous Dusp16tp/tp mice developed without gross abnormalities but died perinatally. Fetal liver cells from Dusp16tp/tp embryos efficiently reconstituted the lymphoid and myeloid compartments with Dusp16-deficient hematopoietic cells. However, GM-CSF-induced proliferation of bone marrow progenitors in vitro was impaired in the absence of Dusp16. In vivo challenge with Escherichia coli LPS triggered higher production of IL-12p40 in mice with a Dusp16-deficient immune system. In vitro, Dusp16-deficient macrophages, but not dendritic cells, selectively overexpressed a subset of TLR-induced genes, including the cytokine IL-12. Dusp16-deficient fibroblasts showed enhanced activation of p38 and JNK MAPKs. In macrophages, pharmacological inhibition and siRNA knockdown of JNK1/2 normalized IL-12p40 secretion. Production of IL-10 and its inhibitory effect on IL-12 production were unaltered in Dusp16tp/tp macrophages. Altogether, the Dusp16 gene trap mouse model identifies an essential role in perinatal survival and reveals selective control of differentiation and cytokine production of myeloid cells by the MAPK phosphatase Dusp16.
EVALuna2:7642

Geographical sequence variation in the Leishmania major virulence factor P46 - Bifeld, Eugenia; Chrobak, Mareike; Zander, Dorothea; Schleicher, Ulrike; Schoenian, Gabriele; Clos, Joachim (Infection Genetics and Evolution, 2015)
Cutaneous leishmaniasis as caused by Leishmania major is a zoonotic infection with wide epidemiological impact. The L. major P46 virulence gene was shown to boost the parasite's virulence and extends its range of experimental hosts. Here we show that P46 is subject to significant geographical sequence variations that may reflect the adaption to different reservoir hosts. This view is supported by the results of passage experiments using P46 variants in different experimental hosts. Conversely, loss of P46 expression leads to attenuation both in vitro and in BALB/c mice. Although part of the L. major exosomal protein payload, P46 is not required for exosome-mediated immune modulation.
EVALuna2:7640

Granulocyte development, tissue recruitment, and function during allergic inflammation - Radtke, Daniel; Vöhringer, David (European Journal of Immunology, 2023)
Granulocytes provide a fast innate response to pathogens and allergens. In allergy and anti-helminth immunity, epithelial cells of damaged barriers release alarmins like IL-25, IL-33, and thymic stromal lymphopoietin (TSLP) but also chemokines like CXCL1 or CCL11 to promote cell recruitment and inflammation. In addition, mast cells positioned at barrier tissue sites also quickly release mediators upon specifically sensing antigens through IgE bound to FcεR1 on their surface. Released mediators induce the recruitment of different granulocytes in a timely ordered manner. First, neutrophils extravasate from the blood vasculature to the side of alarmin release and promote a potent inflammatory response. Alarmins and activated mast cells further promote activation of ILC2s and recruitment of basophils and eosinophils, which inhibit neutrophil recruitment and enhance tissue type 2 immunity. In addition to their potent pro-inflammatory effector functions, granulocytes can also contribute to termination and resolution of inflammation. Here, we summarize the development and tissue recruitment of granulocyte subsets, and describe general effector functions and aspects of their increasingly appreciated role in limiting tissue damage. We further discuss targeting approaches for therapeutic interventions in allergic disorders.
CRIS-Team Scopus Importer:2023-04-21
Keywords: Allergy; Basophils; Eosinophils; Granulocytes; Neutrophils

Group 2 innate lymphoid cells are a non-redundant source of interleukin-5 required for development and function of murine B1 cells - Troch, Karoline F.; Jakob, Manuel O.; Forster, Patrycja M.; Jarick, Katja J.; Schreiber, Jonathan; Preusser, Alexandra; Guerra, Gabriela M.; Durek, Pawel; Tizian, Caroline; Sterczyk, Nele; Helfrich, Sofia; Duerr, Claudia U.; et al. (Nature Communications, 2024)
Tissue-resident immune cells, such as innate lymphoid cells, mediate protective or detrimental immune responses at barrier surfaces. Upon activation by stromal or epithelial cell-derived alarmins, group 2 innate lymphoid cells (ILC2s) are a rapid source of type 2 cytokines, such as IL-5. However, due to the overlap in effector functions, it remains unresolved whether ILC2s are an essential component of the type 2 response or whether their function can be compensated by other cells, such as T cells. Here we show a non-redundant role of ILC2s in supporting the development and function of B1 cells. We demonstrate that B1 cells fail to develop properly in the absence of ILC2s and identify the IL-33 receptor on ILC2s as an essential cell-intrinsic regulator of IL-5 production. Further, conditional deletion of Il5 in ILC2s results in defective B1 cell development and immunoglobulin production. Consequently, B1 cells with phosphatidylcholine specific B cell receptor rearrangements are diminished in ILC2-deficient mice. Thus, our data establish an essential function of ILC2s in supporting B1 cells and antibody production at barrier surfaces.
CRIS-Team Scopus Importer:2025-02-04

Group 2 Innate Lymphoid Cells (ILC2) Suppress Beneficial Type 1 Immune Responses During Pulmonary Cryptococcosis - Kindermann, Markus; Knipfer, Lisa; Obermeyer, Stephanie; Müller, Uwe; Alber, Gottfried; Bogdan, Christian; Schleicher, Ulrike; Neurath, Markus; Wirtz, Stefan (Frontiers in Immunology, 2020)
Cryptococcus neoformans is an opportunistic fungal pathogen preferentially causing disease in immunocompromised individuals such as organ-transplant-recipients, patients receiving immunosuppressive medications or, in particular, individuals suffering from HIV infection. Numerous studies clearly indicated that the control of C. neoformans infections is strongly dependent on a prototypic type 1 immune response and classical macrophage activation, whereas type 2-biased immunity and alternative activation of macrophages has been rather implicated in disease progression and detrimental outcomes. However, little is known about regulatory pathways modulating and balancing immune responses during early phases of pulmonary cryptococcosis. Here, we analyzed the role of group 2 innate lymphoid cells (ILC2s) for the control of C. neoformans infection. Using an intranasal infection model with a highly virulent C. neoformans strain, we found that ILC2 numbers were strongly increased in C. neoformans-infected lungs along with induction of a type 2 response. Mice lacking ILC2s due to conditional deficiency of the transcription factor RAR-related orphan receptor alpha (Rora) displayed a massive downregulation of features of type 2 immunity as reflected by reduced levels of the type 2 signature cytokines IL-4, IL-5, and IL-13 at 14 days post-infection. Moreover, ILC2 deficiency was accompanied with increased type 1 immunity and classical macrophage activation, while the pulmonary numbers of eosinophils and alternatively activated macrophages were reduced in these mice. Importantly, this shift in pulmonary macrophage polarization in ILC2-deficient mice correlated with improved fungal control and prolonged survival of infected mice. Conversely, adoptive transfer of ILC2s was associated with a type 2 bias associated with less efficient anti-fungal immunity in lungs of recipient mice. Collectively, our date indicate a non-redundant role of ILC2 in orchestrating myeloid anti-cryptococcal immune responses toward a disease exacerbating phenotype.
CRIS-Team Scopus Importer:2020-03-10
Keywords: fungi (Candida; Cryptococcus); ILC2; innate immunity; lung infection; type 2 immune response

Guidelines for the use of flow cytometry and cell sorting in immunological studies - Cossarizza, Andrea; Chang, Hyun-Dong; Radbruch, Andreas; Akdis, Mubeccel; Andrae, Immanuel; Annunziato, Francesco; Bacher, Petra; Barnaba, Vincenzo; Battistini, Luca; Bauer, Wolfgang M.; Baumgart, Sabine; Becher, Burkhard; et al. (European Journal of Immunology, 2017)
EVALuna2:13453

Guidelines for the use of flow cytometry and cell sorting in immunological studies (second edition) - Cossarizza, Andrea; Acs, Andreas; Adam, Dieter; Adam-Klages, Sabine; Agace, William W.; Aghaeepour, Nima; Akdis, Mübeccel; Allez, Matthieu; Almeida, Larissa Nogueira; Alvisi, Giorgia; Anderson, Graham; Andrä, Immanuel; et al. (European Journal of Immunology, 2019)
These guidelines are a consensus work of a considerable number of members of the immunology and flow cytometry community. They provide the theory and key practical aspects of flow cytometry enabling immunologists to avoid the common errors that often undermine immunological data. Notably, there are comprehensive sections of all major immune cell types with helpful Tables detailing phenotypes in murine and human cells. The latest flow cytometry techniques and applications are also described, featuring examples of the data that can be generated and, importantly, how the data can be analysed. Furthermore, there are sections detailing tips, tricks and pitfalls to avoid, all written and peer-reviewed by leading experts in the field, making this an essential research companion.
CRIS-Team Scopus Importer:2019-10-29

Gut Pathobiont–Derived Outer Membrane Vesicles Drive Liver Inflammation and Fibrosis in Primary Sclerosing Cholangitis–Associated Inflammatory Bowel Disease - Dorner, Heidrun; Stolzer, Iris; Mattner, Jochen; Kaminski, Sophie; Leistl, Sofia; Edrich, Lisa-Maria; Schwendner, Raphael; Hobauer, Julia; Sebald, Adrian Thomas Erwin; Leikam, Stefanie; Gonzalez Acera, Miguel; Düll, Miriam; et al. (Gastroenterology, 2024)
Background & Aims: Primary sclerosing cholangitis (PSC), often associated with inflammatory bowel disease (IBD), presents a multifactorial etiology involving genetic, immunologic, and environmental factors. Gut dysbiosis and bacterial translocation have been implicated in PSC-IBD, yet the precise mechanisms underlying their pathogenesis remain elusive. Here, we describe the role of gut pathobionts in promoting liver inflammation and fibrosis due to the release of bacterial outer membrane vesicles (OMVs). Methods: Preclinical mouse models in addition to ductal organoids were used to acquire mechanistic data. A proof-of-concept study including serum and liver biopsies of a patient cohort of PSC (n = 22), PSC-IBD (n = 45), and control individuals (n = 27) was performed to detect OMVs in the systemic circulation and liver. Results: In both preclinical model systems and in patients with PSC-IBD, the translocation of OMVs to the liver correlated with enhanced bacterial sensing and accumulation of the NLRP3 inflammasome. Using ductal organoids, we were able to precisely attribute the pro-inflammatory and pro-fibrogenic properties of OMVs to signaling pathways dependent on Toll-like receptor 4 and NLRP3–gasdermin-D. The immunostimulatory potential of OMVs could be confirmed in macrophages and hepatic stellate cells. Furthermore, when we administered gut pathobiont–derived OMVs to Mdr2–/– mice, we observed a significant enhancement in liver inflammation and fibrosis. In a translational approach, we substantiated the presence of OMVs in the systemic circulation and hepatic regions of severe fibrosis using a PSC-IBD patient cohort. Conclusions: This study demonstrates the contribution of gut pathobionts in releasing OMVs that traverse the mucosal barrier and, thus, promote liver inflammation and fibrosis in PSC-IBD. OMVs might represent a critical new environmental factor that interacts with other disease factors to cause inflammation and thus define potential new targets for fibrosis therapy.
CRIS-Team Scopus Importer:2024-09-27
Keywords: Bacterial Extracellular Vesicle; Hepatic Inflammation; Inflammasome; PSC-IBD

Harnessing naturally occurring mutations for T-cell therapy: a potential new avenue to enhance treatment efficacy - Hiltensperger, Michael; Ruland, Jürgen; Schober, Kilian (Signal Transduction and Targeted Therapy, 2024)
CRIS-Team Scopus Importer:2024-05-10

Hätten Sie an eine viszerale Leishmaniasis gedacht? - Hof, Herbert; Binder, Rudolf; Märkl, Krystyna; Zhelegu, Valdete; Gabat, Stefanie; Eickel, Vera; Miller, Bernhart; Geißdörfer, Walter; Christian, Bogdan (MMW Fortschritte der Medizin, 2019)
CRIS-Team Scopus Importer:2019-12-24
Keywords: bone marrow puncture; hepatosplenomegaly; Leishmania; liposomal amphotericin B; lymphadenopathy

Heat-killed Mycobacterium tuberculosis prime-boost vaccination induces myeloid-derived suppressor cells with spleen dendritic cell killing capability - Ribechini, Eliana; Eckert, Ina; Beilhack, Andreas; Du Plessis, Nelita; Walzl, Gerhard; Schleicher, Ulrike; Ritter, Uwe; Lutz, Manfred B. (JCI Insight, 2019)
Tuberculosis patients and mice infected with live Mycobacterium tuberculosis accumulate high numbers of myeloid-derived suppressor cells (MDSCs), Here, we hypothesized that dead M. tuberculosis vaccines also may induce MDSCs that could impair the efficacy of vaccination. We found that repeated injections of M. tuberculosis vaccines (heat-killed M. tuberculosis in incomplete Freund's adjuvant, such as Montanide) but not single or control vaccines without M. tuberculosis strongly expanded CD11b(+) myeloid cells in the spleen, leading to T cell suppression of proliferation and killing ex vivo. Dead M. tuberculosis vaccination induced the generation of CD11b(+)Ly6C(hi)CD115(+) iNDS/Nos2(+) monocytic MDSCs (M-MDSCs) upon application of inflammatory or microbial activation signals. In vivo these M-M DSCs were positioned strategically in the splenic bridging channels and then positioned in the white pulp areas. Notably, within 6-24 hours, in a Nos2-dependent fashion, they produced ND to rapidly kill conventional and plasmacytoid DCs while, surprisingly, sparing T cells in vivo. Thus, we demonstrate that M. tuberculosis vaccine induced M-MDSCs do not directly suppress effector T cells in vivo but, instead, indirectly by killing DCs. Collectively, we demonstrate that M. tuberculosis booster vaccines induce M-MDSCs in the spleen that can be activated to kill DCs. Our data suggest that formation of MDSCs by M. tuberculosis vaccines should be investigated also in clinical trials.
CRIS-Team WoS Importer:2019-07-26

Helminth Modulation of Lung Inflammation. - Schwartz, Christian; Hams, Emily; Fallon, Padraic G. (Trends in Parasitology, 2018)
Parasitic helminths must establish chronic infections to complete their life cycle and therefore are potent modulators of multiple facets of host physiology. Parasitic helminths have coevolved with humans to become arguably master selectors of our immune system, whereby they have impacted on the selection of genes with beneficial mutations for both host and parasite. While helminth infections of humans are a significant health burden, studies have shown that helminths or helminth products can alter susceptibility to unrelated infectious or inflammatory diseases. This has generated interest in the use of helminth infections or molecules as therapeutics. In this review, we focus on the impact of helminth infections on pulmonary immunity, especially with regard to homeostatic lung function, pulmonary viral and bacterial (co)infections, and asthma.

Hemophagocytic lymphohistiocytosis in imported pediatric visceral leishmaniasis in a nonendemic area - Bode, Sebastian F. N.; Bogdan, Christian; Beutel, Karin; Behnisch, Wolfgang; Greiner, Jeanette; Henning, Stephan; Jorch, Norbert; Jankofsky, Martin; Jakob, Marcus; Schmid, Irene; Veelken, Norbert; Vraetz, Thomas; et al. (Journal of Pediatrics, 2014)
To describe characteristics of visceral leishmaniasis-associated hemophagocytic lymphohistiocytosis (HLH) with focus on diagnostic clues and pitfalls, including the frequency of central nervous system (CNS) involvement, and to determine the efficacy of liposomal amphotericin B (L-AmB).We retrospectively analyzed clinical and laboratory features, diagnostic procedures, and treatment of 13 patients with HLH with imported visceral leishmaniasis, reported to the German HLH reference center (1999-2012).The spectrum of presentations was indistinguishable from patients with hereditary HLH or with acquired HLH because of infections with other pathogens. In 8 patients, disease onset occurred before the age of 2 years, coinciding with the typical age of manifestation of primary HLH. Two patients had mild nonspecific CNS findings. Misleading antiviral IgM (n = 6) and autoantibodies (n = 2) led to inaccurate interpretation of the etiology of HLH, sometimes with inappropriate therapeutic consequences. False negative results for Leishmania were obtained by initial bone marrow microscopy in 6/13, serology in 1/12, bone marrow culture in 2/5, and polymerase chain reaction of peripheral blood in 1/3 patients, and all bone marrow samples tested were Leishmania-positive by polymerase chain reaction (n = 7). L-AmB was administered to 12 patients, 5 of whom had no prior HLH-directed immunosuppressive therapy; sodium stibogluconate was administered to 1 patient. Persistent remission was achieved in 11 cases. Two patients required repeated or prolonged L-AmB therapy.Awareness of diagnostic pitfalls may save patients from unnecessary toxic treatment. CNS involvement is rare. L-AmB shows efficacy in visceral leishmaniasis-associated HLH.
EVALuna2:7654

Heterologous prime–boost vaccination with ChAdOx1 nCoV-19 and BNT162b2 - Tenbusch, Matthias; Schumacher, Sofie; Vogel, Emanuel; Priller, Alina; Held, Jürgen; Steininger, Philipp; Beileke, Stephanie; Irrgang, Pascal; Brockhoff, Ronja; Salmanton-García, Jon; Tinnefeld, Kathrin; Mijocevic, Hrvoje; et al. (Lancet Infectious Diseases, 2021)
CRIS-Team Scopus Importer:2021-09-10

HIF1A and NFAT5 coordinate Na+-boosted antibacterial defense via enhanced autophagy and autolysosomal targeting - Neubert, Patrick; Weichselbaum, Andrea; Reitinger, Carmen; Schatz, Valentin; Schröder, Agnes; Ferdinand, John R.; Simon, Michaela; Bär, Anna Lorena; Brochhausen, Christoph; Gerlach, Roman G.; Tomiuk, Stefan; Hammer, Karin; et al. (Autophagy, 2019)
Infection and inflammation are able to induce diet-independent Na + -accumulation without commensurate water retention in afflicted tissues, which favors the pro-inflammatory activation of mouse macrophages and augments their antibacterial and antiparasitic activity. While Na + -boosted host defense against the protozoan parasite Leishmania major is mediated by increased expression of the leishmanicidal NOS2 (nitric oxide synthase 2, inducible), the molecular mechanisms underpinning this enhanced antibacterial defense of mouse macrophages with high Na + (HS) exposure are unknown. Here, we provide evidence that HS-increased antibacterial activity against E. coli was neither dependent on NOS2 nor on the phagocyte oxidase. In contrast, HS-augmented antibacterial defense hinged on HIF1A (hypoxia inducible factor 1, alpha subunit)-dependent increased autophagy, and NFAT5 (nuclear factor of activated T cells 5)-dependent targeting of intracellular E. coli to acidic autolysosomal compartments. Overall, these findings suggest that the autolysosomal compartment is a novel target of Na + -modulated cell autonomous innate immunity. Abbreviations: ACT: actins; AKT: AKT serine/threonine kinase 1; ATG2A: autophagy related 2A; ATG4C: autophagy related 4C, cysteine peptidase; ATG7: autophagy related 7; ATG12: autophagy related 12; BECN1: beclin 1; BMDM: bone marrow-derived macrophages; BNIP3: BCL2/adenovirus E1B interacting protein 3; CFU: colony forming units; CM-H 2 DCFDA: 5-(and-6)-chloromethyl-2′,7′-dichlorodihydrofluorescein diacetate, acetyl ester; CTSB: cathepsin B; CYBB: cytochrome b-245 beta chain; DAPI: 4,6-diamidino-2-phenylindole; DMOG: dimethyloxallyl glycine; DPI: diphenyleneiodonium chloride; E. coli: Escherichia coli; FDR: false discovery rate; GFP: green fluorescent protein; GSEA: gene set enrichment analysis; GO: gene ontology; HIF1A: hypoxia inducible factor 1, alpha subunit; HUGO: human genome organization; HS: high salt (+ 40 mM of NaCl to standard cell culture conditions); HSP90: heat shock 90 kDa proteins; LDH: lactate dehydrogenase; LPS: lipopolysaccharide; Lyz2/LysM: lysozyme 2; NFAT5/TonEBP: nuclear factor of activated T cells 5; MΦ: macrophages; MAP1LC3/LC3: microtubule associated protein 1 light chain 3; MFI: mean fluorescence intensity; MIC: minimum inhibitory concentration; MOI: multiplicity of infection; MTOR: mechanistic target of rapamycin kinase; NaCl: sodium chloride; NES: normalized enrichment score; n.s.: not significant; NO: nitric oxide; NOS2/iNOS: nitric oxide synthase 2, inducible; NS: normal salt; PCR: polymerase chain reaction; PGK1: phosphoglycerate kinase 1; PHOX: phagocyte oxidase; RFP: red fluorescent protein; RNA: ribonucleic acid; ROS: reactive oxygen species; sCFP3A: super cyan fluorescent protein 3A; SBFI: sodium-binding benzofuran isophthalate; SLC2A1/GLUT1: solute carrier family 2 (facilitated glucose transporter), member 1; SQSTM1/p62: sequestosome 1; ULK1: unc-51 like kinase 1; v-ATPase: vacuolar-type H + -ATPase; WT: wild type.
CRIS-Team Scopus Importer:2019-05-02
Keywords: Autophagy; cell-autonomous immunity; E. coli; macrophage; salt; sodium

High-fat-diet-associated intestinal microbiota exacerbates psoriasis-like inflammation by enhancing systemic γδ T cell IL-17 production - Sonomoto, Koshiro; Song, Rui; Eriksson, Daniel; Hahn, Anne Maria; Meng, Xianyi; Lyu, Pang; Cao, Shan; Liu, Ning; Taudte, Verena; Wirtz, Stefan; Tanaka, Yoshiya; Winkler, Thomas; et al. (Cell Reports, 2023)
Although it is known that psoriasis is strongly associated with obesity, the mechanistic connection between diet and skin lesions is not well established. Herein, we showed that only dietary fat, not carbohydrates or proteins, exacerbates psoriatic disease. Enhanced psoriatic skin inflammation was associated with changes in the intestinal mucus layer and microbiota composition by high-fat diet (HFD). Change of intestinal microbiota by vancomycin treatment effectively blocked activation of psoriatic skin inflammation by HFD, inhibited the systemic interleukin-17 (IL-17) response, and led to increased mucophilic bacterial species such as Akkermansia muciniphila. By using IL-17 reporter mice, we could show that HFD facilitates IL-17-mediated γδ T cell response in the spleen. Notably, oral gavage with live or heat-killed A. muciniphila effectively inhibited HFD-induced enhancement of psoriatic disease. In conclusion, HFD exacerbates psoriatic skin inflammation through changing the mucus barrier and the intestine microbial composition, which leads to an enhanced systemic IL-17 response.
CRIS-Team Scopus Importer:2023-07-28
Keywords: CP: Immunology; CP: Microbiology; high-fat diet; psoriasis; γδT cell

High frequency of Tropheryma whipplei in culture-negative endocarditis - Geißdörfer, Walter; Moos, Verena; Moter, Annette; Loddenkemper, Christoph; Jansen, Andreas; Tandler, Rene; Morguet, Andreas J.; Fenollar, Florence; Raoult, Didier; Bogdan, Christian; Schneider, Thomas (Journal of Clinical Microbiology, 2012)
"Classical" Whipple's disease (cWD) is caused by Tropheryma whipplei and is characterized by arthropathy, weight loss, and diarrhea. T. whipplei infectious endocarditis (TWIE) is rarely reported, either in the context of cWD or as isolated TWIE without signs of systemic infection. The frequency of TWIE is unknown, and systematic studies are lacking. Here, we performed an observational cohort study on the incidence of T. whipplei infection in explanted heart valves in two German university centers. Cardiac valves from 1,135 patients were analyzed for bacterial infection using conventional culture techniques, PCR amplification of the bacterial 16S rRNA gene, and subsequent sequencing. T. whipplei-positive heart valves were confirmed by specific PCR, fluorescence in situ hybridization, immunohistochemistry, histological examination, and culture for T. whipplei. Bacterial endocarditis was diagnosed in 255 patients, with streptococci, staphylococci, and enterococci being the main pathogens. T. whipplei was the fourth most frequent pathogen, found in 16 (6.3%) cases, and clearly outnumbered Bartonella quintana, Coxiella burnetii, and members of the HACEK group (Haemophilus species, Actinobacillus actinomycetemcomitans, Cardiobacterium hominis, Eikenella corrodens, and Kingella kingae). In this cohort, T. whipplei was the most commonly found pathogen associated with culture-negative infective endocarditis. Copyright © 2012, American Society for Microbiology. All Rights Reserved.
CRIS-Team Scopus Importer:2024-02-26

High prevalence of the recently identified clonal lineage ST1299/CT3109 vanA among vancomycin-resistant Enterococcus faecium strains isolated from municipal wastewater - Valenza, Giuseppe; Eisenberger, David; Esse, Jan; Held, Jürgen; Lehner-Reindl, Verena; Plaumann, Peter Louis; Ziegler, Tobias; Knauer, Max; Bogdan, Christian; Dudler, Patrick (mSphere, 2024)
Previously, we demonstrated that the majority of vancomycin-resistant Enterococcus faecium (VREfm) strains from in-patients of the University Hospital Erlangen, Germany, belonged to only three clonal lineages, namely ST117/CT71 vanB and two novel ST1299 vanA lineages classified as CT3109 and CT1903. The goal of the current study was (i) to investigate whether VREfm is also detectable in wastewater of the city of Erlangen, (ii) to identify their molecular features, and (iii) to clarify whether VREfm could arise from the community of the city of Erlangen or can be (directly) connected to nosocomial infections in the hospital setting. From April to May 2023, a total of 244 VREfm strains from raw wastewater of the city of Erlangen were analyzed by core genome multilocus sequence typing (cgMLST). Moreover, 20 of them were further investigated for single nucleotide polymorphisms (SNPs). The molecular characterization of the wastewater VREfm strains revealed a high prevalence (27.9%) of the recently identified clonal lineage ST1299/CT3109 vanA, which is mainly characterized by the presence of the tetracycline-resistance determinant tet(M) and the virulence genes pilA and prpA. The SNPs analysis revealed the presence of two major clusters, namely cluster I (≤65 SNPs), which included well-known hospital-adapted vanB clonal lineages such as ST117/CT71 and ST80/CT1065 and cluster II (≤70 SNPs), which were mainly characterized by the lineage ST1299/CT3109 vanA. Based on the concomitant resistance to vancomycin and tetracycline, we propose that ST1299/CT3109 vanA primarily originated and spread outside of hospital settings.IMPORTANCEThis study provides a detailed genomic analysis of vancomycin-resistant Enterococcus faecium (VREfm) strains isolated from municipal wastewater with a particular focus on clonal lineages, antimicrobial resistance, and the presence of virulence genes. The high wastewater prevalence of the recently identified clonal lineage ST1299/CT3109 vanA, which has been previously detected in hospitals, suggests an enormous potential for future spread in Germany.
CRIS-Team Scopus Importer:2024-10-04
Keywords: core genome multilocus sequence typing; Enterococcus faecium; single nucleotide polymorphisms; ST117/CT71; ST1299/CT3109; vancomycin-resistance; wastewater

High salt reduces the activation of IL-4- and IL-13-stimulated macrophages - Binger, Katrina J.; Gebhardt, Matthias; Heinig, Matthias; Rintisch, Carola; Schröder, Agnes; Neuhofer, Wolfgang; Hilgers, Karl Friedrich; Manzel, Arndt; Schwartz, Christian; Kleinewietfeld, Markus; Voelkl, Jakob; Schatz, Valentin; et al. (Journal of Clinical Investigation, 2015)
A high intake of dietary salt (NaCl) has been implicated in the development of hypertension, chronic inflammation, and autoimmune diseases. We have recently shown that salt has a proinflammatory effect and boosts the activation of Th17 cells and the activation of classical, LPS-induced macrophages (M1). Here, we examined how the activation of alternative (M2) macrophages is affected by salt. In stark contrast to Th17 cells and M1 macrophages, high salt blunted the alternative activation of BM-derived mouse macrophages stimulated with IL-4 and IL-13, M(IL-4+IL-13) macrophages. Salt-induced reduction of M(IL-4+IL-13) activation was not associated with increased polarization toward a proinflammatory M1 phenotype. In vitro, high salt decreased the ability of M(IL-4+IL-13) macrophages to suppress effector T cell proliferation. Moreover, mice fed a high salt diet exhibited reduced M2 activation following chitin injection and delayed wound healing compared with control animals. We further identified a high salt-induced reduction in glycolysis and mitochondrial metabolic output, coupled with blunted AKT and mTOR signaling, which indicates a mechanism by which NaCl inhibits full M2 macrophage activation. Collectively, this study provides evidence that high salt reduces noninflammatory innate immune cell activation and may thus lead to an overall imbalance in immune homeostasis.
EVALuna2:3819

Histone modifications associated with gene expression and genome accessibility are dynamically enriched at Plasmodium falciparum regulatory sequences - Tang, Jingyi; Chisholm, Scott A.; Yeoh, Lee M.; Gilson, Paul R.; Papenfuss, Anthony T.; Day, Karen P.; Petter, Michaela; Duffy, Michael F. (Epigenetics & Chromatin, 2020)
Background: The malaria parasite Plasmodium falciparum has an unusually euchromatic genome with poorly conserved positioning of nucleosomes in intergenic sequences and poorly understood mechanisms of gene regulation. Variant histones and histone modifications determine nucleosome stability and recruit trans factors, but their combinatorial contribution to gene regulation is unclear. Results: Here, we show that the histone H3 acetylations H3K18ac and H3K27ac and the variant histone Pf H2A.Z are enriched together at regulatory sites upstream of genes. H3K18ac and H3K27ac together dynamically mark regulatory regions of genes expressed during the asexual life cycle. In contrast, H3K4me1 is depleted in intergenic sequence and dynamically depleted upstream of expressed genes. The temporal pattern of H3K27ac and H3K18ac enrichment indicates that they accumulate during S phase and mitosis and are retained at regulatory sequences until at least G1 phase and after cessation of expression of the cognate genes. We integrated our ChIPseq data with existing datasets to show that in schizont stages H3K18ac, H3K27ac and Pf H2A.Z colocalise with the transcription factor PfAP2-I and the bromodomain protein PfBDP1 and are enriched at stably positioned nucleosomes within regions of exposed DNA at active transcriptional start sites. Using transient transfections we showed that sequences enriched with colocalised H3K18ac, H3K27ac and Pf H2A.Z possess promoter activity in schizont stages, but no enhancer-like activity. Conclusions: The dynamic H3 acetylations define P. falciparum regulatory sequences and contribute to gene activation. These findings expand the knowledge of the chromatin landscape that regulates gene expression in P. falciparum.
CRIS-Team Scopus Importer:2020-12-04
Keywords: Gene regulation; Histone modifications; Plasmodium falciparum

HLA reduction of human T cells facilitates generation of immunologically multicompatible cellular products - Winterhalter, Pascal M.; Warmuth, Linda; Hilgendorf, Philipp; Schütz, Julius M.; Dötsch, Sarah; Tonn, Torsten; Cicin-Sain, Luka; Busch, Dirk H.; Schober, Kilian (Blood Advances, 2024)
Adoptive cellular therapies have shown enormous potential but are complicated by personalization. Because of HLA mismatch, rejection of transferred T cells frequently occurs, compromising the T-cell graft’s functionality. This obstacle has led to the development of HLA knock-out (KO) T cells as universal donor cells. Whether such editing directly affects T-cell functionality remains poorly understood. In addition, HLA KO T cells are susceptible to missing self-recognition through natural killer (NK) cells and lack of canonical HLA class I expression may represent a safety hazard. Engineering of noncanonical HLA molecules could counteract NK-cell recognition, but further complicates the generation of cell products. Here, we show that HLA KO does not alter T-cell functionality in vitro and in vivo. Although HLA KO abrogates allogeneic T-cell responses, it elicits NK-cell recognition. To circumvent this problem, we demonstrate that selective editing of individual HLA class I molecules in primary human T cells is possible. Such HLA reduction not only inhibits T-cell alloreactivity and NK-cell recognition simultaneously, but also preserves the T-cell graft’s canonical HLA class I expression. In the presence of allogeneic T cells and NK cells, T cells with remaining expression of a single, matched HLA class I allele show improved functionality in vivo in comparison with conventional allogeneic T cells. Since reduction to only a few, most frequent HLA haplotypes would already be compatible with large shares of patient populations, this approach significantly extends the toolbox to generate broadly applicable cellular products.
CRIS-Team Scopus Importer:2024-07-19

Homologous COVID-19 BNT162b2 mRNA Vaccination at a German Tertiary Care University Hospital: A Survey-Based Analysis of Reactogenicity, Safety, and Inability to Work among Healthcare Workers - Niekrens, Valentin; Esse, Jan; Held, Jürgen; Knobloch, Carina; Steininger, Philipp; Kunz, Bernd; Seggewies, Christof; Bogdan, Christian (Vaccines, 2022)
At the start of the SARS-CoV-2 pandemic, healthcare workers had an increased risk of acquiring coronavirus disease (COVID)-19. As tertiary care hospitals are critical for the treatment of severely ill patients, the University Hospital Erlangen offered BNT162b2 mRNA vaccination against COVID-19 to all employees when the vaccine became available in Germany. Here, we performed a survey to assess the age- and sex-dependent reactogenicity and safety of BNT162b2 in a real-life setting with a special emphasis on the rate of vaccine-related incapacity to work amongst the employees. All vaccinated employees were invited to participate in the survey and received access to an electronic questionnaire between 31 March and 14 June 2021, which allowed them to report local and systemic adverse effects after the first or second vaccine dose. A total of 2372 employees completed the survey. After both the first and second dose, women had a higher risk than men for vaccine-related systemic side effects (odds ratio (OR) 1.48 (1.24-1.77) and 1.49 (1.23-1.81), respectively) and for inability to work (OR 1.63 (1.14-2.34) and 1.85 (1.52-2.25), respectively). Compared to employees >= 56 years of age, younger vaccinated participants had a higher risk of systemic reactions after the first (OR 1.35 (1.07-1.70)) and second vaccination (OR 2.08 (1.64-2.63)) and were more often unable to work after dose 2 (OR 2.20 (1.67-2.88)). We also recorded four anaphylactic reactions and received two reports of severe adverse effects indicative of vaccine complications. After the first and second vaccination, 7.9% and 34.7% of the survey participants, respectively, were temporarily unable to work, which added up to 1700 days of sick leave in this cohort. These real-life data extend previous results on the reactogenicity and safety of BNT162b2. Loss of working time due to vaccine-related adverse effects was substantial, but was outweighed by the potential benefit of prevented cases of COVID-19.
CRIS-Team WoS Importer:2022-06-10

Host-parasite interactions - Körner, Heinrich; Hu, Shanshan; Bogdan, Christian (Springer-Verlag Wien, 2016)
Ontogeny and differentiation of cells of the monocyte/macrophage lineage are currently subjects of intense research. The concept of the macrophage as “simple” phagocytic cell has undergone profound changes. It has now been established that this myeloid lineage of cells is phenotypically and functionally much more diverse and exerts a much wider influence on the immune response than previously thought. How have these new findings changed our perception of the role of monocytes and macrophages in parasitic diseases? There is now strong evidence that macrophages fulfill organ-specific differential functions, exert activating as well as inhibitory effects on the adaptive immune response, and exist in a whole range of different activation statuses which show a high degree of plasticity. In the present chapter, we will not only review the pertinent literature on these new developments but also bring it into relation to the anti-infectious immune response, focusing on four parasitic diseases (trypanosomiasis, toxoplasmosis, malaria, and leishmaniasis) as examples.
CRIS-Team Scopus Importer:2024-02-26

How to invade a susceptible host: cellular aspects of aspergillosis - Krappmann, Sven (Current Opinion in Microbiology, 2016)
Diseases caused by Aspergillus spp. and in particular A. fumigatus are manifold and affect individuals suffering from immune dysfunctions, among them immunocompromised ones. The determinants of whether the encounter of a susceptible host with infectious propagules of this filamentous saprobe results in infection have been characterized to a limited extent. Several cellular characteristics of A. fumigatus that have evolved in its natural environment contribute to its virulence, among them general traits as well as particular ones that affect interaction with the mammalian host. Among the latter, conidial constituents, cell wall components, secreted proteins as well as extrolites shape the tight interaction of A. fumigatus with the host milieu and also contribute to evasion from immune surveillance.
EVALuna2:7748

Human dendritic cell subsets display distinct interactions with the pathogenic mould Aspergillus fumigatus - Lother, Jasmin; Breitschopf, Tanja; Krappmann, Sven; Morton, C. Oliver; Bouzani, Maria; Kurzai, Oliver; Gunzer, Matthias; Hasenberg, Mike; Einsele, Hermann; Loeffler, Juergen (International Journal of Medical Microbiology, 2014)
The mould Aspergillus fumigatus is primarily an opportunistic pathogen of immunocompromised patients. Once fungal spores have been inhaled they encounter cells of the innate immune system, which include dendritic cells (DCs). DCs are the key antigen-presenting cells of the immune system and distinct subtypes, which differ in terms of origin, morphology and function. This study has systematically compared the interactions between A. fumigatus and myeloid DCs (mDCs), plasmacytoid DCs (pDCs) and monocyte-derived DCs (moDCs). Analyses were performed by time-lapse video microscopy, scanning electron microscopy, plating assays, flow cytometry, 25-plex ELISA and transwell assays. The three subsets of DCs displayed distinct responses to the fungus with mDCs and moDCs showing the greatest similarities. mDCs and moDCs both produced rough convolutions and occasionally phagocytic cups upon exposure to A. fumigatus whereas pDCs maintained a smooth appearance. Both mDCs and moDCs phagocytosed conidia and germ tubes, while pDCs did not phagocytose any fungi. Analysis of cytokine release and maturation markers revealed specific differences in pro- and anti-inflammatory patterns between the different DC subsets. These distinct characteristics between the DC subsets highlight their differences and suggest specific roles of moDCs, mDCs and pDCs during their interaction with A. fumigatus in vivo.
EVALuna2:7661

Human skin dendritic cell fate is differentially regulated by the monocyte identity factor Kruppel-like factor 4 during steady state and inflammation - Jurkin, Jennifer; Krump, Corinna; Koeffel, Rene; Fieber, Christina; Schuster, Christopher; Brunner, Patrick M.; Borek, Izabela; Eisenwort, Gregor; Lim, Clarice; Mages, Joerg; Lang, Roland; Bauer, Wolfgang; et al. (Journal of Allergy and Clinical Immunology, 2017)
Langerhans cell (LC) networks play key roles in immunity and tolerance at body surfaces. LCs are established prenatally and can be replenished from blood monocytes. Unlike skin-resident dermal DCs (dDCs)/interstitial-type DCs and inflammatory dendritic epidermal cells appearing in dermatitis/eczema lesions, LCs lack key monocyte-affiliated markers. Inversely, LCs express various epithelial genes critical for their long-term peripheral tissue residency.Dendritic cells (DCs) are functionally involved in inflammatory diseases; however, the mechanisms remained poorly understood.In vitro differentiation models of human DCs, gene profiling, gene transduction, and immunohistology were used to identify molecules involved in DC subset specification.Here we identified the monocyte/macrophage lineage identity transcription factor Kruppel-like factor 4 (KLF4) to be inhibited during LC differentiation from human blood monocytes. Conversely, KLF4 is maintained or induced during dermal DC and monocyte-derived dendritic cell/inflammatory dendritic epidermal cell differentiation. We showed that in monocytic cells KLF4 has to be repressed to allow their differentiation into LCs. Moreover, respective KLF4 levels in DC subsets positively correlate with proinflammatory characteristics. We identified epithelial Notch signaling to repress KLF4 in monocytes undergoing LC commitment. Loss of KLF4 in monocytes transcriptionally derepresses Runt-related transcription factor 3 in response to TGF-?1, thereby allowing LC differentiation marked by a low cytokine expression profile.Monocyte differentiation into LCs depends on activation of Notch signaling and the concomitant loss of KLF4.
EVALuna2:7718

Hypoxia-inducible factor-1α causes renal cyst expansion through calcium-activated chloride secretion - Willam, Carsten; Eckhardt, Kai-Uwe; Buchholz, Björn; Schley, Gunnar; Faria, Diana; Kroening, Sven; Willam, Carsten; Schreiber, Rainer; Klanke, Bernd; Burzlaff, Nicolai; Jantsch, Jonathan; Kunzelmann, Karl; et al. (Journal of the American Society of Nephrology, 2014)
Polycystic kidney diseases are characterized by numerous bilateral renal cysts that continuously enlarge and, through compression of intact nephrons, lead to a decline in kidney function over time. We previously showed that cyst enlargement is accompanied by regional hypoxia, which results in the stabilization of hypoxia-inducible transcription factor-1α (HIF-1α) in the cyst epithelium. Here we demonstrate a correlation between cyst size and the expression of the HIF-1α-target gene, glucose transporter 1, and report that HIF-1α promotes renal cyst growth in two in vitro cyst models - principal-like MDCK cells (plMDCKs) within a collagen matrix and cultured embryonic mouse kidneys stimulated with forskolin. In both models, augmenting HIF-1α levels with the prolyl hydroxylase inhibitor 2-(1-chloro-4- hydroxyisoquinoline-3-carboxamido) acetate enhanced cyst growth. In addition, inhibition of HIF-1α degradation through tubule-specific knockdown of the von Hippel-Lindau tumor suppressor increased cyst size in the embryonic kidney cyst model. In contrast, inhibition of HIF-1α by chetomin and knockdown of HIF-1α both decreased cyst growth in these models. Consistent with previous reports, plMDCK cyst enlargement was driven largely by transepithelial chloride secretion, which consists, in part, of a calcium-activated chloride conductance. plMDCKs deficient for HIF-1α almost completely lacked calcium-activated chloride secretion. We conclude that regional hypoxia in renal cysts contributes to cyst growth, primarily due to HIF-1α-dependent calcium-activated chloride secretion. These findings identify the HIF system as a novel target for inhibition of cyst growth. Copyright © 2014 by the American Society of Nephrology.

Hypoxia in Leishmania major skin lesions impairs the NO-dependent leishmanicidal activity of macrophages - Mahnke, Alexander; Meier, Robert J.; Schatz, Valentin; Hofmann, Julian; Castiglione, Kirstin; Schleicher, Ulrike; Wolfbeis, Otto S.; Bogdan, Christian; Jantsch, Jonathan (Journal of Investigative Dermatology, 2014)
Cure of infections with Leishmania major is critically dependent on the ability of macrophages to induce the type 2 nitic oxide (NO) synthase (NOS2) that produces high levels of NO in the presence of ample oxygen. Therefore, we analyzed the oxygen levels found in leishmanial skin lesions and their effect on the NOS2-dependent leishmanicidal activity of macrophages (M?). When L. major skin lesions of self-healing C57BL/6 mice reached their maximum size, the infected tissue displayed low oxygen levels (pO2 21 Torr). M? activated under these oxygen tensions failed to produce sufficient amounts of NO to clear L. major. Nos2-deficient and hypoxic wild-type macrophages displayed a similar phenotype. Killing was restored when M? were reoxygenated or exposed to a NO donor. The resolution of the lesion in C57BL/6 mice was paralleled by an increase of lesional pO2. When mice were kept under normobaric hypoxia, this caused a persistent suppression of the lesional pO2 and a concurrent increase of the parasite load. In Nos2-deficient mice, there was no effect of atmospheric hypoxia. Low oxygen levels found at leishmanial skin lesions impaired the NOS2-dependent leishmanicidal activity of M?. Hence, tissue oxygenation represents an underestimated local milieu factor that participates in the persistence of Leishmania.
EVALuna2:7645

I?B kinase 2 is essential for IgE-induced mast cell de novo cytokine production but not for degranulation - Peschke, Katrin; Weitzmann, Anke; Heger, Klaus; Behrendt, Rayk; Schubert, Nadja; Scholten, Julia; Vöhringer, David; Hartmann, Karin; Dudeck, Anne; Schmidt-Supprian, Marc; Roers, Axel (Cell Reports, 2014)
The immunoglobulin E (IgE)-mediated mast cell (MC) response is central to the pathogenesis of type I allergy and asthma. I?B kinase 2 (IKK2) was reported to couple IgE-induced signals to MC degranulation by phosphorylating the SNARE protein SNAP23. We investigated MC responses in mice with MC-specific inactivation of IKK2 or NF-?B essential modulator (NEMO), or animals with MC-specific expression of a mutant, constitutively active IKK2. We show that the IgE-induced late-phase cytokine response is reduced in mice lacking IKK2 or NEMO in MCs. However, anaphylactic in vivo responses of these animals are not different from those of control mice, and in vitro IKK2-deficient MCs readily phosphorylate SNAP23 and degranulate similarly to control cells in response to allergen or calcium ionophore. Constitutive overactivation of the NF-?B pathway has only slight effects on allergen-triggered MC responses. Thus, IKK2 is dispensable for MC degranulation, and the important question how IgE-induced signals trigger MC vesicle fusion remains open.
EVALuna2:25863

Identification and characterization of T-cell receptors with therapeutic potential showing conserved specificity against all SARS-CoV 2 strains - Reimann, Hannah; Moosmann, Carolin; Schober, Kilian; Lang, Vanessa; Verhagen, Johan; Zeun, Julia; Mackensen, Andreas; Kremer, Anita; Völkl, Simon; Aigner, Michael (Immunobiology, 2023)
Introduction: Treatment of severe COVID-19 disease can be challenging in immunocompromized patients due to newly emerging virus variants of concern (VOC) escaping the humoral response. Thus, T cells recognizing to date unmutated epitopes are not only relevant for patients’ immune responses against VOC, but might also serve as a therapeutic option for patients with severe COVID-19 disease in the future, e.g. following allogenic stem cell transplantation. Methods: To this purpose, the activation, cytokine profile and specificity of T-cell clones against unmutated and omicron Spike (S)-protein was analyzed, HLA restriction was determined and most promising T-cell receptor (TCR) was introduced into allogeneic T cells via CRISPR/Cas9-mediated orthotopic TCR replacement. Finally, T-cell responses of engineered T cells was determined and durability of the TCR replacement measured. Perspective: SARS-CoV-2 specific engineered T cells recognizing a genomically stable region of the S-protein of all SARS-CoV 2 variants were successfully generated. Such transgenic T cells exhibit favorable effector functions and provide a treatment option of immunocompromised COVID-19 patients.
CRIS-Team Scopus Importer:2023-08-11
Keywords: Orthotopic TCR replacement; SARS-CoV-2; T-cell engineering; T-cell therapy

Identification of Aspergillus fumigatus Surface Components That Mediate Interaction of Conidia and Hyphae With Human Platelets - Rambach, Guenter; Blum, Gerhard; Latge, Jean-Paul; Fontaine, Thierry; Heinekamp, Thorsten; Hagleitner, Magdalena; Jeckstroem, Hanna; Weigel, Guenter; Wuertinger, Philipp; Pfaller, Kristian; Krappmann, Sven; Loeffler, Juergen; et al. (Journal of Infectious Diseases, 2015)
Platelets were recently identified as a part of innate immunity. They are activated by contact with Aspergillus fumigatus; putative consequences include antifungal defense but also thrombosis, excessive inflammation, and thrombocytopenia. We aimed to identify those fungal surface structures that mediate interaction with platelets.Human platelets were incubated with Aspergillus conidia and hyphae, isolated wall components, or fungal surface mutants. Interaction was visualized microscopically; activation was quantified by flow cytometry of specific markers.The capacity of A. fumigatus conidia to activate platelets is at least partly due to melanin, because this effect can be mimicked with "melanin ghosts"; a mutant lacking melanin showed reduced platelet stimulating potency. In contrast, conidial hydrophobin masks relevant structures, because an A. fumigatus mutant lacking the hydrophobin protein induced stronger platelet activation than wild-type conidia. A. fumigatus hyphae also contain surface structures that interact with platelets. Wall proteins, galactomannan, chitin, and ?-glucan are not the relevant hyphal components; instead, the recently identified fungal polysaccharide galactosaminogalactan potently triggered platelet activation.Conidial melanin and hydrophobin as well as hyphal galactosaminogalactan represent important pathogenicity factors that modulate platelet activity and thus might influence immune responses, inflammation, and thrombosis in infected patients.
EVALuna2:7693

Identification of murine basophils by flow cytometry and histology - Schwartz, Christian; Vöhringer, David (Methods in Molecular Biology, 2014)
Here we describe how murine basophils can be detected in vivo by flow cytometry and immunofluorescence staining. Basophils constitute a homogeneous population of CD4(-)CD19(-)CD49b(+)IgE(+) cells in flow cytometric analysis. When IgE levels are low one can also use anti-Fc?RI or anti-CD200R3 antibodies instead of anti-IgE. For immunofluorescence staining we use an anti-Mcpt8 antibody since Mcpt8 is a specific marker for murine basophils. We describe how to prepare the tissue to cut cryo-sections and how to perform the staining using a tyramide-based amplification kit.
EVALuna2:25874

Identification of Murine Basophils by Flow Cytometry and Histology. - Schwartz, Christian; Vöhringer, David (Methods in Molecular Biology, 2020)
Here, we describe how murine basophils can be detected in vivo by flow cytometry and immunofluorescence staining. Basophils constitute a homogeneous population of CD4-CD19-CD49b+IgE+ cells in flow cytometric analysis. When IgE levels are low, one can also use anti-FcεRI or anti-CD200R3 antibodies instead of anti-IgE. For immunofluorescence staining, we use an anti-Mcpt8 antibody since Mcpt8 is a specific marker for murine basophils. We describe how to prepare the tissue to cut cryo-sections and how to perform the staining using a tyramide-based amplification kit.
EVALuna2:419002

Identification of Novel STAT6-Regulated Proteins in Mouse B Cells by Comparative Transcriptome and Proteome Analysis - Mokada Gopal, Lavanya; Boeser, Alexander; Lehmann, Christian; Drepper, Friedel; Dudziak, Diana; Warscheid, Bettina; Vöhringer, David (Journal of Immunology, 2017)
The transcription factor STAT6 plays a key role in mediating signaling downstream of the receptors for IL-4 and IL-13. In B cells, STAT6 is required for class switch recombination to IgE and for germinal center formation during type 2 immune responses directed against allergens or helminths. In this study, we compared the transcriptomes and proteomes of primary mouse B cells from wild-type and STAT6-deficient mice cultured for 4 d in the presence or absence of IL-4. Microarray analysis revealed that 214 mRNAs were upregulated and 149 were downregulated >3-fold by IL-4 in a STAT6-dependent manner. Across all samples, 5000 proteins were identified by label-free quantitative liquid chromatography/mass spectrometry. A total of 149 proteins was found to be differentially expressed >3-fold between IL-4-stimulated wild-type and STAT6(-/-) B cells (75 upregulated and 74 downregulated). Comparative analysis of the proteome and transcriptome revealed that expression of these proteins was mainly regulated at the transcriptional level, which argues against a major role for posttranscriptional mechanisms that modulate the STAT6-dependent proteome. Nine proteins were selected for confirmation by flow cytometry or Western blot. We show that CD30, CD79b, SLP-76, DEC205, IL-5R?, STAT5, and Thy1 are induced by IL-4 in a STAT6-dependent manner. In contrast, Syk and Fc receptor-like 1 were downregulated. This dataset provides a framework for further functional analysis of newly identified IL-4-regulated proteins in B cells that may contribute to germinal center formation and IgE switching in type 2 immunity.
EVALuna2:25886

IgG subclass and vaccination stimulus determine changes in antigen specific antibody glycosylation in mice - Kao, Daniela; Lux, Anja; Schaffert, Anja; Lang, Roland; Altmann, Friedrich; Nimmerjahn, Falk (European Journal of Immunology, 2017)
Immunoglobulin G (IgG) glycosylation can modulate antibody effector functions. Depending on the precise composition of the sugar moiety attached to individual IgG glycovariants either pro- or anti-inflammatory effector pathways can be initiated via differential binding to type I or type II Fc-receptors. However, an in depth understanding of how individual IgG subclasses are glycosylated during the steady state and how their glycosylation pattern changes during vaccination is missing. To monitor IgG subclass glycosylation during the steady state and upon vaccination of mice with different T-cell dependent and independent antigens, tryptic digests of serum, and antigen-specific IgG preparations were analyzed by reversed phase-liquid chromatography-mass spectrometry. We show that there is a remarkable difference with respect to how individual IgG subclasses are glycosylated during the steady state. More importantly, upon T-cell dependent and independent vaccinations, individual antigen-specific IgG subclasses reacted differently with respect to changes in individual glycoforms, suggesting that the IgG subclass itself is a major determinant of restricting or allowing alterations in specific IgG glycovariants.
EVALuna2:7735

IKK? Promotes Intestinal Tumorigenesis by Limiting Recruitment of M1-like Polarized Myeloid Cells - Goektuna, Serkan I.; Canli, Ozge; Bollrath, Julia; Fingerle, Alexander A.; Horst, David; Diamanti, Michaela A.; Pallangyo, Charles; Bennecke, Moritz; Nebelsiek, Tim; Mankan, Arun K.; Lang, Roland; Artis, David; et al. (Cell Reports, 2014)
The recruitment of immune cells into solid tumors is an essential prerequisite of tumor development. Depending on the prevailing polarization profile of these infiltrating leucocytes, tumorigenesis is either promoted or blocked. Here, we identify I?B kinase ? (IKK?) as a central regulator of a tumoricidal microenvironment during intestinal carcinogenesis. Mice deficient in IKK? kinase activity are largely protected from intestinal tumor development that is dependent on the enhanced recruitment of interferon ? (IFN?)-expressing M1-like myeloid cells. In IKK? mutant mice, M1-like polarization is not controlled in a cell-autonomous manner but, rather, depends on the interplay of both IKK? mutant tumor epithelia and immune cells. Because therapies aiming at the tumor microenvironment rather than directly at the mutated cancer cell may circumvent resistance development, we suggest IKK? as a promising target for colorectal cancer (CRC) therapy.
EVALuna2:7655

IL-17 Receptor A Maintains and Protects the Skin Barrier To Prevent Allergic Skin Inflammation. - Floudas, Achilleas; Saunders, Sean P.; Moran, Tara; Schwartz, Christian; Hams, Emily; Fitzgerald, Denise C.; Johnston, James A.; Ogg, Graham S.; Mckenzie, Andrew N.; Walsh, Patrick T.; Fallon, Padraic G. (Journal of Immunology, 2017)
mice was dependent on TSLP, but not the other alarmins IL-25 and IL-33. The associated skin inflammation was mediated by IL-5-expressing pathogenic effector Th2 cells and was independent of TCRγδ T cells and IL-22. An absence of IL-17RA in nonhematopoietic cells, but not in the hematopoietic cells, was required for the development of spontaneous skin inflammation. Skin microbiome dysbiosis developed in the absence of IL-17RA, with antibiotic intervention resulting in significant amelioration of skin inflammation and reductions in skin-infiltrating pathogenic effector Th2 cells and TSLP. This study describes a previously unappreciated protective role for IL-17RA signaling in regulation of the skin barrier and maintenance of skin immune homeostasis.

IL-1α reversibly inhibits skeletal muscle ryanodine receptor a novel mechanism for critical illness myopathy? - Edwards, Joshua N.; Weber, Cornelia; Liu, Ilon; Reischl, Barbara; Most, Patrick; Wirth-Hücking, Anette; Yi, Bing; Friedrich, Oliver; Voelkers, Mirko; Buttgereit, Andreas; Lang, Roland; Lee, Aven; et al. (American journal of respiratory cell and molecular biology, 2014)
Critical illness myopathies in patients with sepsis or sustained mechanical ventilation prolong intensive care treatment and threaten both patients and health budgets; no specific therapy is available. Underlying pathophysiological mechanisms are still patchy. We characterized IL-1α action on muscle performance in "skinned" muscle fibers using force transducers and confocal Ca fluorescence microscopy for force/Ca transients and Ca sparks. Association of IL-1α with sarcoplasmic reticulum (SR) release channel, ryanodine receptor (RyR) 1, was investigated with coimmunoprecipitation and confocal immunofluorescence colocalization. Membrane integrity was studied in single, intact fibers challenged with IL-1α. IL-1α reversibly stabilized Mg inhibition of Ca release. Low Mg-induced force and Ca transients were reversibly abolished by IL-1a. At normal Mg , IL-1α reversibly increased caffeine-induced force and Ca transients. IL-1α reduced SR Ca leak via RyR1, as judged by (1) increased SR Ca retention, (2) increased IL-1α force transients being reproduced by 25 μM tetracaine, and (3) reduced Ca spark frequencies by IL-1a or tetracaine. Coimmunoprecipitation confirmed RyR1/IL-1 association. RyR1/IL-1 immunofluorescence patterns perfectly colocalized. Long-term, 8-hour IL-1α challenge of intact muscle fibers compromised membrane integrity in approximately 50% of fibers, and confirmed intracellular IL-1α deposition. IL-1α exerts a novel, specific, and reversible interaction mechanism with the skeletal muscle RyR1 macromolecular release complex without the need to act via its membrane IL-1 receptor, as IL-1R membrane expression levels were not detectable in Western blots or immunostaining of single fibers. We present a potential explanation of how the inflammatory mediator, IL-1α, may contribute to muscle weakness in critical illness. Copyright © 2014 by the American Thoracic Society.
Keywords: Critical illness myopathy; Cytokines; IL-1; Ryanodine receptor 1

IL-25 and type 2 innate lymphoid cells induce pulmonary fibrosis - Hams, Emily; Armstrong, Michelle E.; Barlow, Jillian L.; Saunders, Sean P.; Schwartz, Christian; Cooke, Gordon; Fahy, Ruairi J.; Crotty, Thomas B.; Hirani, Nikhil; Flynn, Robin J.; Vöhringer, David; Mckenzie, Andrew N. J.; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2014)
Disease conditions associated with pulmonary fibrosis are progressive and have a poor long-term prognosis with irreversible changes in airway architecture leading to marked morbidity and mortalities. Using murine models we demonstrate a role for interleukin (IL)-25 in the generation of pulmonary fibrosis. Mechanistically, we identify IL-13 release from type 2 innate lymphoid cells (ILC2) as sufficient to drive collagen deposition in the lungs of challenged mice and suggest this as a potential mechanism through which IL-25 is acting. Additionally, we demonstrate that in human idiopathic pulmonary fibrosis there is increased pulmonary expression of IL-25 and also observe a population ILC2 in the lungs of idiopathic pulmonary fibrosis patients. Collectively, we present an innate mechanism for the generation of pulmonary fibrosis, via IL-25 and ILC2, that occurs independently of T-cell-mediated antigen-specific immune responses. These results suggest the potential of therapeutically targeting IL-25 and ILC2 for the treatment of human fibrotic diseases.
EVALuna2:25861

IL-27 Induced by Select Candida spp. via TLR7/NOD2 Signaling and IFN-β Production Inhibits Fungal Clearance - Patin, Emmanuel C.; Jones, Adam V.; Thompson, Aiysha; Clement, Mathew; Liao, Chia-Te; Griffiths, James S.; Wallace, Leah E.; Bryant, Clare E.; Lang, Roland; Rosenstiel, Philip; Humphreys, Ian R.; Taylor, Philip R.; et al. (Journal of Immunology, 2016)
Candida spp. elicit cytokine production downstream of various pathogen recognition receptors, including C-type lectin-like receptors, TLRs, and nucleotide oligomerization domain (NOD)-like receptors. IL-12 family members IL-12p70 and IL-23 are important for host immunity against Candida spp. In this article, we show that IL-27, another IL-12 family member, is produced by myeloid cells in response to selected Candida spp. We demonstrate a novel mechanism for Candida parapsilosis-mediated induction of IL-27 in a TLR7-, MyD88-, and NOD2-dependent manner. Our data revealed that IFN-? is induced by C. parapsilosis, which in turn signals through the IFN-?/? receptor and STAT1/2 to induce IL-27. Moreover, IL-27R (WSX-1)-deficient mice systemically infected with C. parapsilosis displayed enhanced pathogen clearance compared with wild-type mice. This was associated with increased levels of proinflammatory cytokines in the serum and increased IFN-? and IL-17 responses in the spleens of IL-27R-deficient mice. Thus, our data define a novel link between C. parapsilosis, TLR7, NOD2, IFN-?, and IL-27, and we have identified an important role for IL-27 in the immune response against C. parapsilosis Overall, these findings demonstrate an important mechanism for the suppression of protective immune responses during infection with C. parapsilosis, which has potential relevance for infections with other fungal pathogens.
EVALuna2:7705

IL-27 suppresses type 2 immune responses in vivo via direct effects on group 2 innate lymphoid cells - Mchedlidze, T.; Kindermann, M.; Neves, A. T.; Vöhringer, David; Neurath, Markus; Wirtz, Stefan (Mucosal Immunology, 2016)
Group 2 innate lymphoid cells (ILC2) were recently characterized by their ability to produce significant amounts of type-2 signature cytokines and drive central beneficial and pathological features of type-2 immune responses. Although factors such as IL-33 and IL-25 were shown to have ILC2 activating capacity, it is not well understood, how ILC2 responses are regulated in vivo. Here we provide compelling evidence that IL-27-signalling directly inhibits ILC2 responses and reveal a novel mechanism for negative regulation of the innate arm of type-2 immunity. We demonstrate that IL-27-deficiency is linked to increased mucosal presence of ILC2 in a model of inflammatory lung disease. Moreover, IL-27-treatment inhibited ILC2 proliferation and cytokine production and significantly reduced their accumulation in vivo. During helminth infection, regulation of ILC2 by IL-27 directly impacted anti-parasitic immunity. Thus, therapeutic modulation of the IL-27/IL-27R axis may be relevant in a number of inflammatory conditions associated with dysregulated type-2 responses.
EVALuna2:2062

IL-33-Induced Cytokine Secretion and Survival of Mouse Eosinophils Is Promoted by Autocrine GM-CSF - Willebrand, Ralf; Vöhringer, David (PLoS ONE, 2016)
Eosinophils are major effector cells during allergic responses and helminth infections. Recent studies further highlight eosinophils as important players in many other biological processes. Therefore it is important to understand how these cells can be modulated in terms of survival and effector function. In the present study we investigated how eosinophils respond to the alarmin IL-33. We show that IL-33 promotes eosinophil survival in a ST2- and MyD88-dependent manner. IL-33-mediated protection from apoptosis was dependent on autocrine GM-CSF release. In addition, GM-CSF increased the IL-33-induced secretion of IL-4 and IL-13 from eosinophils. Unexpectedly, this effect was further enhanced by cross-linking of Siglec-F, a proposed inhibitory and apopotosis-inducing receptor on eosinophils. Co-culture experiments with eosinophils and macrophages revealed that the IL-33-induced release of IL-4 and IL-13 from eosinophils was required for differentiation of alternatively activated macrophages (AAMs). The differentiation of AAMs could be further increased in the presence of GM-CSF. These results indicate that cross-talk between Siglec-F and the receptors for IL-33, LPS and GM-CSF plays an important role for efficient secretion of IL-4 and IL-13. Deciphering the molecular details of this cross-talk could lead to the development of new therapeutic option to treat eosinophil-associated diseases.
EVALuna2:25883

IL-33-induced metabolic reprogramming controls the differentiation of alternatively activated macrophages and the resolution of inflammation - Faas, Maria; Ipseiz, Natacha; Ackermann, Jochen; Culemann, Stephan; Grüneboom, Anika; Schröder, Fenja; Rothe, Tobias; Scholtysek, Carina; Eberhardt, Martin; Böttcher, Martin; Kirchner, Philipp; Stoll, Cornelia; et al. (Immunity, 2021)
Alternatively activated macrophages (AAMs) contribute to the resolution of inflammation and tissue repair. However, molecular pathways that govern their differentiation have remained incompletely understood. Here, we show that uncoupling protein-2-mediated mitochondrial reprogramming and the transcription factor GATA3 specifically controlled the differentiation of pro-resolving AAMs in response to the alarmin IL-33. In macrophages, IL-33 sequentially triggered early expression of pro-inflammatory genes and subsequent differentiation into AAMs. Global analysis of underlying signaling events revealed that IL-33 induced a rapid metabolic rewiring of macrophages that involved uncoupling of the respiratory chain and increased production of the metabolite itaconate, which subsequently triggered a GATA3-mediated AAM polarization. Conditional deletion of GATA3 in mononuclear phagocytes accordingly abrogated IL-33-induced differentiation of AAMs and tissue repair upon muscle injury. Our data thus identify an IL-4-independent and GATA3-dependent pathway in mononuclear phagocytes that results from mitochondrial rewiring and controls macrophage plasticity and the resolution of inflammation.
CRIS-Team Scopus Importer:2021-11-19
Keywords: alternatively activated macrophage; GATA3; interleukin-33; itaconate; mitochondrial rewiring; resolution of inlammation; UCP2; uncoupling

IL-33/ST2 immune responses to respiratory bacteria in pediatric asthma - Hentschke, Isabell; Graser, Anna; Melichar, Volker O.; Kiefer, Alexander; Zimmermann, Theodor; Kross, Bettina; Haag, Patricia; Xepapadaki, Paraskevi; Papadopoulos, Nikolaos G.; Bogdan, Christian; Finotto, Susetta (Scientific Reports, 2017)
Here we investigated the relationship between local bacterial colonization and anti-bacterial immune responses in pre-school asthmatic and control children within the EU-wide study PreDicta. In this cohort of pre-school asthmatic children, nasopharyngeal colonization with Gram-negative bacteria such as Haemophilus influenzae and Moraxella catarrhalis was found to be associated with the highest interferon beta (IFN?) and IL-33 levels in the nasal pharyngeal fluids (NPF). IL33R-ST2 was found induced in the blood of asthmatic children with additional Gram + bacteria in the nasopharynx (Gr+/-). Furthermore, asthmatic children had more episodes of infection that required antibiotic therapy than the control group. Treatment with antibiotics associated with reduced ST2 in blood cells of both asthmatic and control children and reduced IL-33 levels in the airways of asthmatic children. In the absence of Staphylococcus (S.) aureus in NPF, antibiotic therapy associated with decreased IL-33 levels in the NPF and lower ST2 values in the blood of control children but not of asthmatic children. These data suggest that, in asthmatic children, Gram- bacteria, which persist after antibiotic therapy, contributes to IL-33 locally and associated with Gr + bacteria colonization in the airways, inhibited IFN-? and in the absence of Staphylococcus (S.) aureus, induced ST2 bearing cells in their blood.
EVALuna2:7728

IL-3 orchestrates ulcerative colitis pathogenesis by controlling the development and the recruitment of splenic reservoir neutrophils - Benard, Alan; Mittelstädt, Anke; Klösch, Bettina; Glanz, Karolina; Müller, Jan; Schoen, Janina; Nüse, Björn; Brunner, Maximilian; Naschberger, Elisabeth; Stürzl, Michael; Mattner, Jochen; Munoz, Luis Enrique; et al. (Cell Reports, 2023)
Inflammatory bowel diseases (IBDs) are a global health issue with an increasing incidence. Although the pathogenesis of IBDs has been investigated intensively, the etiology of IBDs remains enigmatic. Here, we report that interleukin-3 (Il-3)-deficient mice are more susceptible and exhibit increased intestinal inflammation during the early stage of experimental colitis. IL-3 is locally expressed in the colon by cells harboring a mesenchymal stem cell phenotype and protects by promoting the early recruitment of splenic neutrophils with high microbicidal capability into the colon. Mechanistically, IL-3-dependent neutrophil recruitment involves CCL5+ PD-1high LAG-3high T cells, STAT5, and CCL20 and is sustained by extramedullary splenic hematopoiesis. During acute colitis, Il-3−/− show, however, increased resistance to the disease as well as reduced intestinal inflammation. Altogether, this study deepens our understanding of IBD pathogenesis, identifies IL-3 as an orchestrator of intestinal inflammation, and reveals the spleen as an emergency reservoir for neutrophils during colonic inflammation.
CRIS-Team Scopus Importer:2023-06-23
Keywords: CCL5; colitis; CP: Immunology; interleukin-3; neutrophils; spleen

IL-4 and helminth infection downregulate MINCLE-dependent macrophage response to mycobacteria and Th17 adjuvanticity - Schick, Judith; Altunay, Meltem; Lacorcia, Matthew; Marschner, Nathalie; Westermann, Stefanie; Schluckebier, Julia; Schubart, Christoph; Bodendorfer, Barbara; Christensen, Dennis; Alexander, Christian; Wirtz, Stefan; Vöhringer, David; et al. (eLife, 2023)
The myeloid C-type lectin receptor (CLR) MINCLE senses the mycobacterial cell wall component trehalose-6,6'-dimycolate (TDM). Recently, we found that IL-4 downregulates MINCLE expression in macrophages. IL-4 is a hallmark cytokine in helminth infections, which appear to increase the risk for mycobacterial infection and active tuberculosis. Here, we investigated functional consequences of IL-4 and helminth infection on MINCLE-driven macrophage activation and Th1/Th17 adjuvanticity. IL-4 inhibited MINCLE and cytokine induction after macrophage infection with Mycobacterium bovis bacille Calmette-Guerin (BCG). Infection of mice with BCG upregulated MINCLE on myeloid cells, which was inhibited by IL-4 plasmid injection and by infection with the nematode Nippostrongylus brasiliensis in monocytes. To determine the impact of helminth infection on MINCLE-dependent immune responses, we vaccinated mice with a recombinant protein together with the MINCLE ligand trehalose-6,6-dibehenate (TDB) as adjuvant. Concurrent infection with N. brasiliensis or with Schistosoma mansoni promoted T cell-derived IL-4 production and suppressed Th1/Th17 differentiation in the spleen. In contrast, helminth infection did not reduce Th1/Th17 induction by TDB in draining peripheral lymph nodes, where IL-4 levels were unaltered. Upon use of the TLR4-dependent adjuvant G3D6A, N. brasiliensis infection impaired selectively the induction of splenic antigen-specific Th1 but not of Th17 cells. Inhibition of MINCLE-dependent Th1/Th17 responses in mice infected with N. brasiliensis was dependent on IL-4/IL-13. Thus, helminth infection attenuated the Th17 response to MINCLE-dependent immunization in an organ- and adjuvant-specific manner via the Th2 cytokines IL-4/IL-13. Taken together, our results demonstrate downregulation of MINCLE expression on monocytes and macrophages by IL-4 as a possible mechanism of thwarted Th17 vaccination responses by underlying helminth infection.
CRIS-Team Scopus Importer:2023-02-17
Keywords: C-type lectin receptors; co-infection; immunology; infectious disease; inflammation; microbiology; mouse; mycobacterial cord factor; Nippostrongylus brasiliensis; Schistosoma mansoni; Th cell differentiation

IL-4/IL-13-producing ILC2s are required for timely control of intestinal helminth infection in mice - Varela, Filipa; Symowski, Cornelia; Pollock, Jonathan; Wirtz, Stefan; Vöhringer, David (European Journal of Immunology, 2022)
Infection of mice with Nippostrongylus brasiliensis (Nb) serves as a model for human hookworm infection affecting about 600 million people world-wide. Expulsion of Nb from the intestine requires IL-13-mediated mucus secretion from goblet cells and activation of smooth muscles cells. Type 2 innate lymphoid cells (ILC2s) are a major cellular source of IL-13 but it remains unclear whether IL-13 secretion from ILC2s is required for Nb expulsion. Here, we compared the immune response to Nb infection in mixed bone marrow chimeras with wild-type or IL-4/IL-13-deficient ILC2s. ILC2-derived IL-4/IL-13 was required for recruitment of eosinophils to the lung but had no influence of systemic eosinophil levels. In the small intestine, goblet cell hyperplasia and tuft cell accumulation was largely dependent on IL-4/IL-13 secretion from ILC2s. This further translated to higher eggs counts and impaired worm expulsion in mice with IL-4/IL-13-deficient ILC2s. Overall, we demonstrate that ILC2s constitute a non-redundant source of IL-4/IL-13 required for protective immunity against primary Nb infection.
CRIS-Team Scopus Importer:2022-10-14
Keywords: bone marrow chimeras; eosinophils; IL-4/IL-13; ILC2; intestinal helminth infection

ILC2s regulate adaptive Th2 cell functions via PD-L1 checkpoint control. - Schwartz, Christian; Khan, Adnan R.; Floudas, Achilleas; Saunders, Sean P.; Hams, Emily; Rodewald, Hans-Reimer; Mckenzie, Andrew N. J.; Fallon, Padraic G. (Journal of Experimental Medicine, 2017)
Our results identify a novel PD-L1-controlled mechanism for type 2 polarization, with ILC2s mediating an innate checkpoint to control adaptive T helper responses, which has important implications for the treatment of type 2 inflammation.

Images in clinical tropical medicine rhinophyma-like cutaneous leishmaniasis due to leishmania aethiopica treated successfully with liposomal Amphotericin B - Kirchberger, Michael Constantin; Schliep, Stefan; Bogdan, Christian (American Journal of Tropical Medicine and Hygiene, 2019)
CRIS-Team Scopus Importer:2019-05-02

Immune cells control skin lymphatic electrolyte homeostasis and blood pressure - Wiig, Helge; Schröder, Agnes; Neuhofer, Wolfgang; Jantsch, Jonathan; Kopp, Christoph; Karlsen, Tine V.; Boschmann, Michael; Goss, Jennifer; Bry, Maija; Rakova, Natalia; Dahlmann, Anke; Brenner, Sven; et al. (Journal of Clinical Investigation, 2013)
The skin interstitium sequesters excess Na+ and Cl- in salt-sensitive hypertension. Mononuclear phagocyte system (MPS) cells are recruited to the skin, sense the hypertonic electrolyte accumulation in skin, and activate the tonicity-responsive enhancer-binding protein (TONEBP, also known as NFAT5) to initiate expression and secretion of VEGFC, which enhances electrolyte clearance via cutaneous lymph vessels and increases eNOS expression in blood vessels. It is unclear whether this local MPS response to osmotic stress is important to systemic blood pressure control. Herein, we show that deletion of TonEBP in mouse MPS cells prevents the VEGFC response to a high-salt diet (HSD) and increases blood pressure. Additionally, an antibody that blocks the lymph-endothelial VEGFC receptor, VEGFR3, selectively inhibited MPS-driven increases in cutaneous lymphatic capillary density, led to skin Cl- accumulation, and induced salt-sensitive hypertension. Mice overexpressing soluble VEGFR3 in epidermal keratinocytes exhibited hypoplastic cutaneous lymph capillaries and increased Na+, Cl-, and water retention in skin and salt-sensitive hypertension. Further, we found that HSD elevated skin osmolality above plasma levels. These results suggest that the skin contains a hypertonic interstitial fluid compartment in which MPS cells exert homeostatic and blood pressure-regulatory control by local organization of interstitial electrolyte clearance via TONEBP and VEGFC/VEGFR3-mediated modification of cutaneous lymphatic capillary function.
EVALuna2:7617

Immune responses to tumor-unrelated antigens might predict adverse effects in patients treated with anti-PD-1 immunotherapy - Nuse, Bjorn; Holland, Tim; Mattner, Jochen (Cellular & Molecular Immunology, 2022)
CRIS-Team WoS Importer:2022-12-02

Immunogenicity and diagnostic potential of synthetic antigenic cell surface glycans of leishmania - Anish, Chakkumkal; Martin, Christopher E.; Wahlbrink, Annette; Bogdan, Christian; Ntais, Pantelis; Antoniou, Maria; Seeberger, Peter H. (ACS Chemical Biology, 2013)
Detection and quantification of pathogen-derived antigenic structures is a key method for the initial diagnosis and follow-up of various infectious diseases. Complex parasitic diseases such as leishmaniasis require highly sensitive and specific tests prior to treatment with potentially toxic drugs. To investigate the diagnostic potential of cell surface glycans found on Leishmania parasites, we identified diagnostically relevant glycan epitopes and used synthetic glycan microarrays to screen sera from infected humans and dogs. On the basis of the screening results, we selected a tetrasaccharide to generate anti-glycan antibodies. The corresponding tetrasaccharide-carrier protein conjugate was immunogenic in mice, and sera obtained from immunized mice specifically detected the Leishmania parasite. These results demonstrate how synthetic glycan arrays, in combination with immunological methods, help to identify promising carbohydrate antigens for pathogen detection. © 2013 American Chemical Society.
CRIS-Team Scopus Importer:2024-02-26

Immunologie und klinische Wirksamkeit der Pneumokokken-Impfung im Alter - Bogdan, Christian; Falkenhorst, G. (Internistische Praxis, 2018)
Streptococcus pneumoniae is a frequent cause of local and systemic infections in humans. The polysaccharide capsule, of which so far 97 different serotypes have been described, is its most important virulence factor. Elderly people show an increased susceptibility to pneumococcal infections, even in the absence of additional risk factors. In Germany two different pneumococcal vaccines are available for prophylaxis: the 13-valent polysaccharideprotein- conjugate vaccine (PCV13) and the 23-valent polysaccharide vaccine (PPSV23). Today, following the widespread use of PCV13 in infants and small children, only 30 % of invasive pneumococcal disease (IPD) episodes in elderly people (>60 yrs) are caused by pneumococcal serotypes contained in the PCV13 vaccine, whereas roughly 70 % of the IPD cases are due to serotypes covered by the PPSV23 vaccine. As in immunocompetent adults and elderly people both vaccines showed a comparable efficacy against pneumococcal disease with vaccine serotypes, the Standing Committee on Vaccination in Germany (STIKO) recommends the use of PPSV23 as the standard anti-pneumococcal vaccine in people >60 yrs of age. In the presence of certain underlying diseases the sole application of PPSV23 or the sequential vaccination with PCV13 followed by PPSV23 after a minimum of 2 (better 6-12) months is indicated. This review will discuss the principal immunological differences between both vaccines and the considerations that led to the recommendation by the STIKO.
CRIS-Team Scopus Importer:2024-02-26
Keywords: 13-valent pneumococcal conjugate vaccine; 23-valent pneumococcal polysaccharide vaccine; Indications for vaccination; Standing Committee on Vaccination (STIKO); Streptococcus pneumoniae (pneumococci)

Immunomodulation and Immune Escape Strategies of Gastrointestinal Helminths and Schistosomes - Wiedemann, Marie; Vöhringer, David (Frontiers in Immunology, 2020)
Parasitic worms (helminths) developed various immunoregulatory mechanisms to counteract the immune system of their host. The increasing identification and characterization of helminth-derived factors with strong immune modulatory activity provides novel insights into immune escape strategies of helminths. Such factors might be good targets to enhance anti-helminthic immune responses. In addition, immunosuppressive helminth-derived factors could be useful to develop new therapeutic strategies for treatment of chronic inflammatory conditions. This review will take an in depth look at the effects of immunomodulatory molecules produced by different helminths with a focus on schistosomes and mouse models of hookworm infections.
CRIS-Team Scopus Importer:2020-10-23
Keywords: Helminths; immunomodulation; nematode; parasites; schistosomes; trematode; type 2 immunity

ImmunoPET/MR imaging allows specific detection of Aspergillus fumigatus lung infection in vivo - Rolle, Anna-Maria; Hasenberg, Mike; Thornton, Christopher R.; Solouk-Saran, Djamschid; Maenn, Linda; Weski, Juliane; Maurer, Andreas; Fischer, Eliane; Spycher, Philipp R.; Schibli, Roger; Boschetti, Frederic; Stegemann-Koniszewski, Sabine; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2016)
Invasive pulmonary aspergillosis (IPA) is a life-threatening lung disease caused by the fungus Aspergillus fumigatus, and is a leading cause of invasive fungal infection-related mortality and morbidity in patients with hematological malignancies and bone marrow transplants. We developed and tested a novel probe for noninvasive detection of A. fumigatus lung infection based on antibody-guided positron emission tomography and magnetic resonance (immunoPET/MR) imaging. Administration of a [(64)Cu]DOTA-labeled A. fumigatus-specific monoclonal antibody (mAb), JF5, to neutrophil-depleted A. fumigatus-infected mice allowed specific localization of lung infection when combined with PET. Optical imaging with a fluorochrome-labeled version of the mAb showed colocalization with invasive hyphae. The mAb-based newly developed PET tracer [(64)Cu]DOTA-JF5 distinguished IPA from bacterial lung infections and, in contrast to [(18)F]FDG-PET, discriminated IPA from a general increase in metabolic activity associated with lung inflammation. To our knowledge, this is the first time that antibody-guided in vivo imaging has been used for noninvasive diagnosis of a fungal lung disease (IPA) of humans, an approach with enormous potential for diagnosis of infectious diseases and with potential for clinical translation.
EVALuna2:7708

Impact of Microbes on the Pathogenesis of Primary Biliary Cirrhosis (PBC) and Primary Sclerosing Cholangitis (PSC) - Mattner, Jochen (International Journal of Molecular Sciences, 2016)
Primary biliary cirrhosis (PBC) and primary sclerosing cholangitis (PSC) represent the major clinical entities of chronic cholestatic liver diseases. Both disorders are characterized by portal inflammation and slowly progress to obliterative fibrosis and eventually liver cirrhosis. Although immune-pathogenic mechanisms have been implicated in the pathogenesis of PBC and PSC, neither disorder is considered to be a classical autoimmune disease, as PSC and PBC patients do not respond to immune-suppressants. Furthermore, the decreased bile flow resulting from the immune-mediated tissue assault and the subsequent accumulation of toxic bile products in PBC and PSC not only perpetuates biliary epithelial damage, but also alters the composition of the intestinal and biliary microbiota and its mutual interactions with the host. Consistent with the close association of PSC and inflammatory bowel disease (IBD), the polyclonal hyper IgM response in PBC and (auto-)antibodies which cross-react to microbial antigens in both diseases, an expansion of individual microbes leads to shifts in the composition of the intestinal or biliary microbiota and a subsequent altered integrity of epithelial layers, promoting microbial translocation. These changes have been implicated in the pathogenesis of both devastating disorders. Thus, we will discuss here these recent findings in the context of novel and alternative therapeutic options.
EVALuna:33884

Impairing fluoride export of Aspergillus fumigatus mitigates its voriconazole resistance - Binder, Jasmin; Held, Jürgen; Krappmann, Sven (International Journal of Antimicrobial Agents, 2019)
Fungi have evolved specific export activities to balance intracellular levels of the toxic ion fluoride, while the first-line antimycotic voriconazole contains fluorine. This study aimed to explore whether impaired fluoride export might result in altered susceptibilities of the human pathogenic mould Aspergillus fumigatus towards this antifungal compound. Functional characterization of the putative fluoride exporter in A. fumigatus was performed in the context of azole resistance by generating deletion strains that were assessed for their resistance against fluoride and voriconazole. The FexA fluoride exporter of A. fumigatus appears to be expressed constitutively, and targeting its encoding gene results in significantly increased sensitivity towards this halide. Impaired fluoride export correlates with increased susceptibility of an azole-resistant fexAΔ strain. These results demonstrate that the fexA-encoded gene product is the major fluoride export activity of A. fumigatus, and that voriconazole serves as a source of fluoride. However, these data do not support the application of voriconazole based on fluoride toxicity.
CRIS-Team Scopus Importer:2019-05-03
Keywords: Aspergillosis; Azole resistance; FEX

Impfempfehlungen der Ständigen Impfkommission (STIKO): Impfungen bei Immundefizienz und Impfung gegen COVID-19 - Bogdan, Christian (Hautarzt, 2021)
Background: The working methods of the Standing Committee on Vaccination (STIKO) and its recommendations are only partially known by medical professionals and the public. Objectives: Methodology of the standard operating procedure of the STIKO, annual vaccination recommendations, normal vaccination reaction versus vaccination side effects, instructions for vaccination in case of immunodeficiency, and recommendation for COVID-19 vaccination are presented. Materials and methods: Presentation of the path to a vaccination recommendation, differences between recommendations and instructions for action, key statements on vaccination in immunodeficiency, and summary of the data situation on COVID-19 mRNA vaccination. Results: The STIKO works purely on an evidence-based basis by systematically evaluating the existing preclinical and clinical studies results for a vaccine using the GRADE method. Only vaccination complications and vaccination injuries are notifiable. Immunodeficient patients can receive inactivated vaccines at any time, but generally not live vaccines. Based on current knowledge, the COVID-19 mRNA vaccination can be described as safe and effective. Conclusions: The STIKO vaccination recommendations are considered as the medical standard. The published current instructions for vaccination of immunodeficient patients and the recently published recommendation for COVID-19 vaccination, together with their scientific backgrounds and reasons, represent a valuable basis for medical action in the field of vaccination against infectious diseases.
CRIS-Team Scopus Importer:2021-02-05
Keywords: Adverse effects of vaccines; mRNA vaccine; Normal vaccine response; Vaccine complication; Vaccine injury

Impfen bei Immundefizienz : Anwendungshinweise zu den von der Ständigen Impfkommission empfohlenen Impfungen(I) Grundlagenpapier - Niehues, Tim; Bogdan, Christian; Hecht, Jane; Mertens, Thomas; Wiese-Posselt, Miriam; Zepp, Fred (Bundesgesundheitsblatt, Gesundheitsforschung, Gesundheitsschutz, 2017)
EVALuna2:7758

Impfen bei Immundefizienz: Anwendungshinweise zu den von der Ständigen Impfkommission empfohlenen Impfungen. (III) Impfen bei hämatologischen und onkologischen Erkrankungen (antineoplastische Therapie, Stammzelltransplantation), Organtransplantation und Asplenie - Laws, Hans-Juergen; Baumann, Ulrich; Bogdan, Christian; Burchard, Gerd; Christopeit, Maximilian; Hecht, Jane; Heininger, Ulrich; Hilgendorf, Inken; Kern, Winfried; Kling, Kerstin; Kobbe, Guido; Kuelper, Wiebe; et al. (Bundesgesundheitsblatt, Gesundheitsforschung, Gesundheitsschutz, 2020)
CRIS-Team Scopus Importer:2020-05-15

Impfen bei Immundefizienz : Anwendungshinweise zu den von der Ständigen Impfkommission empfohlenen Impfungen. (IV) Impfen bei Autoimmunkrankheiten, bei anderen chronisch-entzündlichen Erkrankungen und unter immunmodulatorischer Therapie - Wagner, Norbert; Assmus, Frauke; Arendt, Gabriele; Baum, Erika; Baumann, Ulrich; Bogdan, Christian; Burchard, Gerd; Foell, Dirk; Garbe, Edeltraut; Hecht, Jane; Mueller-Ladner, Ulf; Niehues, Tim; et al. (Bundesgesundheitsblatt, Gesundheitsforschung, Gesundheitsschutz, 2019)
CRIS-Team Scopus Importer:2019-05-02

Importance of cortactin for efficient epithelial NF-kappa B activation by Helicobacter pylori, Salmonella enterica and Pseudomonas aeruginosa, but not Campylobacter spp. - Tegtmeyer-Backert, Nicole; Soltan Esmaeili, Delara; Sharafutdinov, Irshad; Knorr, Jakob; Naumann, Michael; Alter, Thomas; Backert, Steffen (European Journal of Microbiology and Immunology, 2021)
Transcription factors of the nuclear factor kappa-light-chain-enhancer of activated B cells (NF-kappa B) family control important signaling pathways in the regulation of the host innate immune system. Various bacterial pathogens in the human gastrointestinal tract induce NF-kappa B activity and provoke pro-inflammatory signaling events in infected epithelial cells. NF-kappa B activation requires the phosphorylation-dependent proteolysis of inhibitor of kappa B (I kappa B) molecules including the NF-kappa B precursors through ubiquitin-mediated proteolysis. The canonical NF-kappa B pathway merges on I kappa B kinases (IKKs), which are required for signal transduction. Using CRISPR-Cas9 technology, secreted embryonic alkaline phosphatase (SEAP) reporter assays and cytokine enzyme-linked immunosorbent assay (ELISA), we demonstrate that the actin-binding protein cortactin is involved in NF-kappa B activation and subsequent interleukin-8 (IL-8) production upon infection by Helicobacter pylori, Salmonella enterica and Pseudomonas aeruginosa. Our data indicate that cortactin is needed to efficiently activate the c-Sarcoma (Src) kinase, which can positively stimulate NF-kappa B during infection. In contrast, cortactin is not involved in activation of NF-kappa B and IL-8 expression upon infection with Campylobacter species C. jejuni, C. coli or C. consisus, suggesting that Campylobacter species pluralis (spp.) induce a different signaling pathway upstream of cortactin to trigger the innate immune response.
CRIS-Team WoS Importer:2022-02-25
Keywords: ADP-heptose; NF-ĸB; Helicobacter pylori; T4SS; cortactin; Src; interleukin-8; inflammation

Inception of early-life allergen-induced airway hyperresponsiveness is reliant on IL-13+CD4+ T cells - Saglani, Sejal; Gregory, Lisa G.; Manghera, Avneet K.; Branchett, William J.; Uwadiae, Faith; Entwistle, Lewis J.; Oliver, R. A.; Vasiliou, Jessica E.; Sherburn, Rebekah; Lui, Stephen; Puttur, F.; Vöhringer, David; et al. (Science immunology, 2018)
Airway hyperresponsiveness (AHR) is a critical feature of wheezing and asthma in children, but the initiating immune mechanisms remain unconfirmed. We demonstrate that both recombinant interleukin-33 (rIL-33) and allergen [house dust mite (HDM) or Alternaria alternata] exposure from day 3 of life resulted in significantly increased pulmonary IL-13+CD4+ T cells, which were indispensable for the development of AHR. In contrast, adult mice had a predominance of pulmonary LinnegCD45+CD90+IL-13+ type 2 innate lymphoid cells (ILC2s) after administration of rIL-33. HDM exposure of neonatal IL-33 knockout (KO) mice still resulted in AHR. However, neonatal CD4creIL-13 KO mice (lacking IL-13+CD4+ T cells) exposed to allergen from day 3 of life were protected from AHR despite persistent pulmonary eosinophilia, elevated IL-33 levels, and IL-13+ ILCs. Moreover, neonatal mice were protected from AHR when inhaled Acinetobacter lwoffii (an environmental bacterial isolate found in cattle farms, which is known to protect from childhood asthma) was administered concurrent with HDM. A. lwoffii blocked the expansion of pulmonary IL-13+CD4+ T cells, whereas IL-13+ ILCs and IL-33 remained elevated. Administration of A. lwoffii mirrored the findings from the CD4creIL-13 KO mice, providing a translational approach for disease protection in early life. These data demonstrate that IL-13+CD4+ T cells, rather than IL-13+ ILCs or IL-33, are critical for inception of allergic AHR in early life.
EVALuna2:36389

Incidence of invasive pneumococcal disease in 5-15 year old children with and without comorbidities in Germany after the introduction of PCV13: Implications for vaccinating children with comorbidities - Weinberger, Raphael; Falkenhorst, Gerhard; Bogdan, Christian; Van Der Linden, Mark; Imoehl, Matthias; Von Kries, Rildiger (Vaccine, 2015)
To describe the burden of suffering from IPD in children aged 5-15 years with and without comorbidities up to 5 years after the introduction of PCV13 in Germany and to identify the potential benefit for PCV13 and PPV23 vaccination.The surveillance of IPD for children <16 years was based on two independently reporting sources: active surveillance in pediatric hospitals and a laboratory-based sentinel surveillance system.IPD with cultural detection of pneumococci at a physiologically sterile site in children from 2010 to 2014 in Germany. Incidence was estimated by capture-recapture analysis with stratification by absence/presence of comorbidities. Coverage of the observed serotypes by different vaccines was assessed.142 (Capture recapture-corrected: 437) cases were reported: 72.5% were healthy children and 27.5% had a comorbidity. The incidence of IPD related to children with comorbidities was 0.2 per 100,000. One third of these cases had serotypes not included in either vaccine. The remaining cases might benefit from pneumococcal vaccination but one third of all cases was not vaccinated. The additional potential benefit of PPV23 compared to PCV13 with respect to coverage was 10%.The incidence of IPD in children with comorbidities in Germany is low. Pneumococcal vaccination uptake in children with comorbidities should be increased, although only about two-thirds of the cases might be preventable by presently available vaccines.
EVALuna2:7678

Incidence of invasive pneumococcal disease in 5-15 year old children with and without comorbidities in Germany after the introduction of PCV13: Implications for vaccinating children with comorbidities (vol 33, pg 6617, 2015) - Weinberger, Raphael; Falkenhorst, Gerhard; Bogdan, Christian; Van Der Linden, Mark; Imoehl, Matthias; Von Kries, Ruediger (Vaccine, 2016)
EVALuna2:33312

Increased zinc levels facilitate phenotypic detection of ceftazidime-avibactam resistance in metallo-β-lactamase-producing Gram-negative bacteria - Simon, Michaela; Gerlach, Roman; Pfeifer, Yvonne; Pfennigwerth, Niels; Gatermann, Sören G.; Schröder, Agnes; Hiergeist, Andreas; Hamprecht, Axel; Rügamer, Tamara; Gessner, André; Jantsch, Jonathan (Frontiers in Microbiology, 2022)
Ceftazidime-avibactam is one of the last resort antimicrobial agents for the treatment of carbapenem-resistant, Gram-negative bacteria. Metallo-β-lactamase-producing bacteria are considered to be ceftazidime-avibactam resistant. Here, we evaluated a semi-automated antimicrobial susceptibility testing system regarding its capability to detect phenotypic ceftazidime-avibactam resistance in 176 carbapenem-resistant, metallo-β-lactamase-producing Enterobacterales and Pseudomonas aeruginosa isolates. Nine clinical isolates displayed ceftazidime-avibactam susceptibility in the semi-automated system and six of these isolates were susceptible by broth microdilution, too. In all nine isolates, metallo-β-lactamase-mediated hydrolytic activity was demonstrated with the EDTA-modified carbapenemase inactivation method. As zinc is known to be an important co-factor for metallo-β-lactamase activity, test media of the semi-automated antimicrobial susceptibility testing system and broth microdilution were supplemented with zinc. Thereby, the detection of phenotypic resistance was improved in the semi-automated system and in broth microdilution. Currently, ceftazidime-avibactam is not approved as treatment option for infections by metallo-β-lactamase-producing, Gram-negative bacteria. In infections caused by carbapenem-resistant Gram-negatives, we therefore recommend to rule out the presence of metallo-β-lactamases with additional methods before initiating ceftazidime-avibactam treatment.
CRIS-Team Scopus Importer:2022-12-16
Keywords: antimicrobial susceptibility testing; ceftazidime-avibactam; Enterobacterales; metallo-β-lactamases; Micronaut; Phoenix; Pseudomonas aeruginosa; zinc

Induction of Aspergillus fumigatus zinc cluster transcription factor OdrA/Mdu2 provides combined cellular responses for oxidative stress protection and multiple antifungal drug resistance - Sasse, Christoph; Bastakis, Emmanouil; Bakti, Fruzsina; Höfer, Annalena M.; Zangl, Isabella; Schüller, Christoph; Köhler, Anna M.; Gerke, Jennifer; Krappmann, Sven; Finkernagel, Florian; Harting, Rebekka; Strauss, Joseph; et al. (mBio, 2023)
Zinc cluster transcription factors (Zcfs) encoding zcf genes are exclusive for fungi and required for multiple cellular processes including metabolism and development. Genome-wide screening of 228 zinc cluster transcription factor encoding genes by overexpression in Aspergillus fumigatus revealed 11 genes which provided increased tolerance to the broadly applied azole voriconazole or to the polyene amphotericin B or to both. These include four oxidative stress and drug resistance genes (odrA-D) genes encoding factors, which provide broad cellular stress protection. Thereby, the corresponding fungal OdrA/Mdu2- and AtrR/OdrD-dependent genetic networks are interconnected. OdrA/Mdu2 activates atrR/odrD transcription by direct binding to the promoter, whereas AtrR/OdrD functions as repressor of odrA/mdu2 expression. odrA/ mdu2 overexpression provides combined resistance to amphotericin B, voriconazole, itraconazole, and reactive oxygen species generated by menadione. OdrA/Mdu2-mediated itraconazole resistance is evoked by direct regulation of the transporter encoding gene mdr1. Oxidative stress-inducing substances like amphotericin B and menadione promote OdrA/Mdu2 accumulation in the nucleus to regulate stress response genes like mdr1 and the putative glutathione-S-transferase encoding gene gstD. The expression levels and external stress conditions fostering nuclear accumulation of OdrA/Mdu2 determine the regulation of the target genes. Hence, OdrA/Mdu2 provides a combined adaptation strategy for survival in nature or within a potential host, where this fungus represents the most common agent for human mold pneumonia worldwide. The OdrA/ Mdu2 controlled genetic network highlights the tight connection between oxidative stress response and antifungal drug adaption to secure A. fumigatus survival in various hostile environments. IMPORTANCE An overexpression screen of 228 zinc cluster transcription factor encoding genes of A. fumigatus revealed 11 genes conferring increased tolerance to antifungal drugs. Out of these, four oxidative stress and drug tolerance transcription factor encoding odr genes increased tolerance to oxidative stress and antifungal drugs when overexpressed. This supports a correlation between oxidative stress response and antifungal drug tolerance in A. fumigatus. OdrA/Mdu2 is required for the cross-tolerance between azoles, polyenes, and oxidative stress and activates genes for detoxification. Under oxidative stress conditions or when overexpressed, OdrA/Mdu2 accumulates in the nucleus and activates detoxifying genes by direct binding at their promoters, as we describe with the mdr1 gene encoding an itraconazole specific efflux pump. Finally, this work gives new insights about drug and stress resistance in the opportunistic pathogenic fungus A. fumigatus.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Aspergillus fumigatus; atrR; drug tolerance; mdr1; OdrA/Mdu2; oxidative stress; zinc cluster transcription factors

Induction of proliferation and pro-inflammatory cytokine production in rheumatoid arthritis peripheral blood mononuclear cells by a 65 KDa chondrocyte membrane-specific, constitutive target autoantigen (CH65) - Alsalameh, Rayya J.; Casey, Rachael C.; Mollenhauer, Jürgen; Kalden, Joachim; Burmester, Gerd R.; Alsalameh, Saifeddin M. (International Journal of Rheumatic Diseases, 2013)
To analyze proliferation and pro-inflammatory cytokine production of peripheral blood mononuclear cells (PBMC) from rheumatoid arthritis (RA) patients following stimulation with a purified chondrocyte membrane-associated autoantigen (CH65).CH65 was highly purified from bovine chondrocyte membranes by solubilization and ion exchange chromatography. PBMC of RA patients (n = 37; 28 seropositive, nine seronegative) and non-arthritic donors (n = 20) were isolated by ficoll centrifugation and used in cell proliferation assays. The levels of interleukin (IL)-1, tumo necrosis factor (TNF) and IL-6 produced after stimulation with CH65 were determined by enzyme-linked immunosorbent assay (ELISA). Statistical analysis was performed using Mann-Whitney U-test and Spearman rank test and the software SPSS 13.0(TM) (SPSS Inc.; Chicago, IL, USA).Peripheral blood mononuclear cells exhibited a strong proliferative response to purified CH65 in approximately 50% of the RA patients (seropositive > seronegative), with a maximum reactivity at 0.15 or 0.30 ?g/mL culture medium. In contrast, PBMC from normal donors did not show a proliferative response to CH65 at any dose. The proliferative response in RA patients peaked at days 7-9 and returned to control levels at day 13, indicating an antigen-driven process. CH65-stimulated RA PBMC produced moderate to high amounts of IL-1, TNF and IL-6. This was comparable to the response after exposure to isolated whole chondrocyte membranes or purified collagen type II.These results demonstrate a significant cellular immune response to CH65 protein in RA patients. Given the high similarity between bovine and human CH65, the results suggest a pathogenetic involvement of this molecule as a cartilage-specific potential target autoantigen in RA.
EVALuna2:7644

INDUCTION OF TH2 CELLS AND EOSINOPHIL BY INFECTION WITH NIPPOSTRONGYLUS BRASILIENSIS PROTECTS AGAINST RHEUMATOID ARTHRITIS - Chen, Zhu; Oeser, Katharina; Baum, Wolfgang; Vöhringer, David; Schett, Georg; Bozec, Aline (2014)
EVALuna2:13204

Infections with the tick-borne bacterium "Candidatus Neoehrlichia mikurensis" mimic noninfectious conditions in patients with B cell malignancies or autoimmune diseases - Grankvist, Anna; Andersson, Per-Ola; Mattsson, Mattias; Sender, Monica; Vaht, Krista; Hoper, Linnea; Sakiniene, Egidija; Trysberg, Estelle; Stenson, Martin; Fehr, Jan; Pekova, Sona; Bogdan, Christian; et al. (Clinical Infectious Diseases, 2014)
Candidatus Neoehrlichia mikurensis is a newly discovered noncultivatable bacterium spread among ticks and rodents in Europe and Asia that can infect humans, particularly immunocompromised patients.We compiled clinical and laboratory data from 11 patients with hematological malignances or autoimmune diseases who were diagnosed with Candidatus N. mikurensis infection in Europe 2010-2013. Both published (6) and unpublished cases (5) were included.The patients had a median age of 67, were mostly male (8/11), and resided in Sweden, Switzerland, Germany, and the Czech Republic. All but one had ongoing or recent immune suppressive treatment and a majority were splenectomized (8/11). Less than half of them recalled tick exposure. The most frequent symptoms were fever (11/11), localized pain afflicting muscles and/or joints (8/11), vascular and thromboembolic events (6/11), that is, deep vein thrombosis (4), transitory ischemic attacks (2), pulmonary embolism (1), and arterial aneurysm (1). Typical laboratory findings were elevated C-reactive protein, leukocytosis with neutrophilia, and anemia. Median time from onset of symptoms to correct diagnosis was 2 months. In at least 4 cases, the condition was interpreted to be due to the underlying disease, and immunosuppressive therapy was scheduled. All patients recovered completely when doxycycline was administered.Candidatus N. mikurensis is an emerging tick-borne pathogen that may give rise to a systemic inflammatory syndrome in persons with hematologic or autoimmune diseases that could be mistaken for recurrence of the underlying disease and/or unrelated arteriosclerotic vascular events. Awareness of this new pathogen is warranted among rheumatologists, hematologists, oncologists, and infectious disease specialists.
EVALuna2:7651

Inflammation-induced IgE promotes epithelial hyperplasia and tumour growth - Hayes, Mark David; Ward, Sophie; Crawford, Greg; Seoane, Rocio Castro; Jackson, William David; Kipling, David; Vöhringer, David; Dunn-Walters, Deborah; Strid, Jessica (eLife, 2020)
IgE is the least abundant circulating antibody class but is constitutively present in healthy tissues bound to resident cells via its high-affinity receptor, FcεRI. The physiological role of endogenous IgE antibodies is unclear but it has been suggested that they provide host protection against a variety of noxious environmental substances and parasitic infections at epithelial barrier surfaces. Here we show, in mice, that skin inflammation enhances levels of IgE antibodies that have natural specificities and a repertoire, VDJ rearrangements and CDRH3 characteristics similar to those of IgE antibodies in healthy tissue. IgE-bearing basophils are recruited to inflamed skin via CXCL12 and thymic stromal lymphopoietin (TSLP)/IL-3-dependent upregulation of CXCR4. In the inflamed skin, IgE/FcεRI-signalling in basophils promotes epithelial cell growth and differentiation, partly through histamine engagement of H1R and H4R. Furthermore, this IgE response strongly drives tumour outgrowth of epithelial cells harbouring oncogenic mutation. These findings indicate that natural IgE antibodies support skin barrier defences, but that during chronic tissue inflammation this role may be subverted to promote tumour growth.
CRIS-Team Scopus Importer:2020-01-21
Keywords: basophils; cancer; cancer biology; epithelial cells; IgE; immunology; inflammation; mouse; skin

Inflammatory Properties and Adjuvant Potential of Synthetic Glycolipids Homologous to Mycolate Esters of the Cell Wall of Mycobacterium tuberculosis - Tima, Hermann Giresse; Al Dulayymi, Juma'A Raheem; Denis, Olivier; Lehebel, Pauline; Baols, Klarah Sherzad; Mohammed, Mohsin Omar; L'Homme, Laurent; Sahb, Mohaned Mohammed; Potemberg, Georges; Legrand, Sylvie; Lang, Roland; Beyaert, Rudi; et al. (Journal of Innate Immunity, 2017)
The cell wall of mycobacteria is characterised by glycolipids composed of different classes of mycolic acids (MAs; alpha-, keto-, and methoxy-) and sugars (trehalose, glucose, and arabinose). Studies using mutant Mtb strains have shown that the structure of MAs influences the inflammatory potential of these glycolipids. As mutant Mtb strains possess a complex mixture of glycolipids, we analysed the inflammatory potential of single classes of mycolate esters of the Mtb cell wall using 38 different synthetic analogues. Our results show that synthetic trehalose dimycolate (TDM) and trehalose, glucose, and arabinose monomycolates (TMM, GMM, and AraMM) activate bone marrow-derived dendritic cells in terms of the production of pro-inflammatory cytokines (IL-6 and TNF-?) and reactive oxygen species, upregulation of costimulatory molecules, and activation of NLRP3 inflammasome by a mechanism dependent on Mincle. These findings demonstrate that Mincle receptor can also recognise pentose esters and seem to contradict the hypothesis that production of GMM is an escape mechanism used by pathogenic mycobacteria to avoid recognition by the innate immune system. Finally, our experiments indicate that TMM and GMM, as well as TDM, can promote Th1 and Th17 responses in mice in an OVA immunisation model, and that further analysis of their potential as novel adjuvants for subunit vaccines is warranted.
EVALuna2:7739

Influence of different treatment conditions on the filtration performance of conventional electret melt blown non-woven and novel nano FFP2 masks - Halamicek, Robin; Wiesmann, Carolin; Kröner, Richard; Eber, Matthias; Bogdan, Christian; Schubert, Dirk W. (PLoS ONE, 2023)
To allow an efficient protection against viruses like the severe acute respiratory syndrome coronavirus type 2 (SARS-CoV-2), it is important to avoid their spreading by using filtering face pieces (FFP), which are categorized by different standards according to their filtration efficiency. In this study, we subjected six brands of FFP2 standard masks to three different conditions and subsequently analysed them for their filtration performance to evaluate potentials for reusability. The conditions comprised changes of temperature and air humidity, an exposure to isopropyl alcohol (IPA) and an autoclave sterilization. While four of six masks consisted of electrostatically treated melt blown non-wovens, two masks were fabricated using a nanofibrous multilayer system. Due to the absence of prior electrostatic treatment, the nano-masks did not show a significant change in filtration efficiency when discharged by IPA, unlike the melt blown nonwoven masks showing a significant decrease of filtration efficiency down to around 50% at a particle size of 0.3 μm. However, most melt blown masks maintained a sufficient filtration efficiency after all other treatments with even better results than the nanofibrous masks. This was particularly the case for the capacity to filter smallest particles/droplets with a size of around 0.1 μm, which is below the range of typical filtering standards and important for the retention of virally contaminated nano-aerosols or unattached viruses. After temperature/humidity variation and autoclave sterilization, melt blown masks were able to retain a filtration efficiency up to over 90% at 0.1 μm contrary to nano-masks showing a decrease down to around 70%. Based on their better filtration performance, lower price and potential reusability, we conclude that electret melt blown masks are the preferable type of FFP2 masks.
CRIS-Team Scopus Importer:2023-09-29

Influence of Platelet-rich Plasma on the immune response of human monocyte-derived dendritic cells and macrophages stimulated with Aspergillus fumigatus - Czakai, Kristin; Dittrich, Marcus; Kaltdorf, Martin; Mueller, Tobias; Krappmann, Sven; Schedler, Anette; Bonin, Michael; Duehring, Sybille; Schuster, Stefan; Speth, Cornelia; Rambach, Guenter; Einsele, Hermann; et al. (International Journal of Medical Microbiology, 2017)
Dendritic cells (DCs) and macrophages (M?) are critical for protection against pathogenic fungi including Aspergillus fumigatus. To analyze the role of platelets in the innate immune response, human DCs and M?s were challenged with A. fumigatus in presence or absence of human platelet rich plasma (PRP). Gene expression analyses and functional investigations were performed. A systems biological approach was used for initial modelling of the DC - A. fumigatus interaction. DCs in a quiescent state together with different corresponding activation states were validated using gene expression data from DCs and M? stimulated with A. fumigatus. To characterize the influence of platelets on the immune response of DCs and M? to A. fumigatus, we experimentally quantified their cytokine secretion, phagocytic capacity, maturation, and metabolic activity with or without platelets. PRP in combination with A. fumigatus treatment resulted in the highest expression of the maturation markers CD80, CD83 and CD86 in DCs. Furthermore, PRP enhanced the capacity of macrophages and DCs to phagocytose A. fumigatus conidia. In parallel, PRP in combination with the innate immune cells significantly reduced the metabolic activity of the fungus. Interestingly, A. fumigatus and PRP stimulated M? showed a significantly reduced gene expression and secretion of IL6 while PRP only reduced the IL-6 secretion of A. fumigatus stimulated DCs. The in silico systems biological model correlated well with these experimental data. Different modules centrally involved in DC function became clearly apparent, including DC maturation, cytokine response and apoptosis pathways. Taken together, the ability of PRP to suppress IL-6 release of human DCs might prevent local excessive inflammatory hemorrhage, tissue infarction and necrosis in the human lung.
EVALuna2:7746

Influence of probiotics on the periodontium, the oral microbiota and the immune response during orthodontic treatment in adolescent and adult patients (ProMB Trial): study protocol for a prospective, double-blind, controlled, randomized clinical trial - Seidel, Corinna Lesley; Gerlach, Roman; Weider, Matthias; Woelfel, Theresa; Schwarz, Vincent; Stroebel, Armin; Schmetzer, Helga; Bogdan, Christian; Gölz, Lina (BMC Oral Health, 2022)
Background Orthodontic treatment with fixed appliances is often necessary to correct malocclusions in adolescence or adulthood. However, oral hygiene is complicated by appliances, and prior studies indicate that they may trigger oral inflammation and dysbiosis of the oral microbiota, especially during the first 3 months after insertion, and, thus, may present a risk for inflammatory oral diseases. In recent periodontal therapeutic studies, probiotics have been applied to improve clinical parameters and reduce local inflammation. However, limited knowledge exists concerning the effects of probiotics in orthodontics. Therefore, the aim of our study is to evaluate the impact of probiotics during orthodontic treatment. Methods This study is a monocentric, randomized, double blind, controlled clinical study to investigate the effectiveness of daily adjuvant use of Limosilactobacillus reuteri (Prodentis (R)-lozenges, DSM 17938, ATCC PTA 5289) versus control lozenges during the first three months of orthodontic treatment with fixed appliances. Following power analysis, a total of 34 adolescent patients (age 12-17) and 34 adult patients (18 years and older) undergoing orthodontic treatment at the University Hospital Erlangen will be assigned into 2 parallel groups using a randomization plan for each age group. The primary outcome measure is the change of the gingival index after 4 weeks. Secondary outcomes include the probing pocket depth, the modified plaque index, the composition of the oral microbiota, the local cytokine expression and-only for adults-serum cytokine levels and the frequencies of cells of the innate and adaptive immune system in peripheral blood. Discussion Preventive strategies in everyday orthodontic practice include oral hygiene instructions and regular dental cleaning. Innovative methods, like adjuvant use of oral probiotics, are missing. The aim of this study is to analyse, whether probiotics can improve clinical parameters, reduce inflammation and prevent dysbiosis of the oral microbiota during orthodontic treatment. If successful, this study will provide the basis for a new strategy of prophylaxis of oral dysbiosis-related diseases during treatment with fixed appliances.
CRIS-Team WoS Importer:2022-05-13
Keywords: Probiotics; Lactobacillus reuteri; Limosilactobacillus reuteri; Oral microbiota; Cytokines; Inflammation; Orthodontic treatment; Oral health; Prevention; Study protocol

Inhibited Arginase-1 Expression by Fra-1 in Myeloid Cells Enhance Rheumatoid Arthritis Inflammation - Hannemann, Nicole; Schnelzer, A.; Jordan, J.; Eberhardt, Martin; Schleicher, Ulrike; Uebe, Steffen; Ekici, Arif Bülent; Reid, Stephen; Sonnewald, Sophia; Bäuerle, Tobias; Bogdan, Christian; Vera, Julio; et al. (2017)
EVALuna2:33310

INHIBITION OF ARGINASE-1 EXPRESSION BY THE TRANSCRIPTION FACTOR FRA-1 IN MACROPHAGES EXACERBATES RHEUMATOID ARTHRITIS INFLAMMATION - Hannemann, Nicole; Cao, Shan; Schnelzer, A.; Jordan, J.; Eberhardt, Martin; Schleicher, Ulrike; Uebe, Steffen; Ekici, Arif Bülent; Rech, Jürgen; Bäuerle, Tobias; Bogdan, Christian; Vera, Julio; et al. (ANNALS OF THE RHEUMATIC DISEASES, 2019)
CRIS-Team WoS Importer:2019-05-17

Inhibition of Hedgehog Acyltransferase Alleviates the Profibrotic Effects of Transforming Growth Factor beta in Systemic Sclerosis - Liang, Ruifang; Kagwiria, Rosebeth; Dees, Clara; Zhang, Yun; Distler, Oliver; Schett, Georg; Distler, Jörg (2017)
EVALuna2:33436

Innate immune system favors emergency monopoiesis at the expense of DC-differentiation to control systemic bacterial infection in mice - Pasquevich, Karina A.; Bieber, Kristin; Guenter, Manina; Grauer, Matthias; Poetz, Oliver; Schleicher, Ulrike; Biedermann, Tilo; Beer-Hammer, Sandra; Buehring, Hans-Joerg; Rammensee, Hans-Georg; Zender, Lars; Autenrieth, Ingo B.; et al. (European Journal of Immunology, 2015)
DCs are professional APCs playing a crucial role in the initiation of T-cell responses to combat infection. However, systemic bacterial infection with various pathogens leads to DC-depletion in humans and mice. The mechanisms of pathogen-induced DC-depletion remain poorly understood. Previously, we showed that mice infected with Yersinia enterocolitica (Ye) had impaired de novo DC-development, one reason for DC-depletion. Here, we extend these studies to gain insight into the molecular mechanisms of DC-depletion and the impact of different bacteria on DC-development. We show that the number of bone marrow (BM) hematopoietic progenitors committed to the DC lineage is reduced following systemic infection with different Gram-positive and Gram-negative bacteria. This is associated with a TLR4- and IFN-?-signaling dependent increase of committed monocyte progenitors in the BM and mature monocytes in the spleen upon Ye-infection. Adoptive transfer experiments revealed that infection-induced monopoiesis occurs at the expense of DC-development. Our data provide evidence for a general response of hematopoietic progenitors upon systemic bacterial infections to enhance monocyte production, thereby increasing the availability of innate immune cells for pathogen control, whereas impaired DC-development leads to DC-depletion, possibly driving transient immunosuppression in bacterial sepsis.
EVALuna2:7688

Innate PD-L1 limits T cell-mediated adipose tissue inflammation and ameliorates diet-induced obesity - Schwartz, Christian; Schmidt, Viviane; Deinzer, Andrea; Hawerkamp, H. C.; Hams, E.; Bayerlein, Jasmin; Roeger, O.; Bailer, Moritz; Krautz, Christian; El Gendy, Amr; Elshafei, Moustafa; Heneghan, H. M.; et al. (EUROPEAN JOURNAL OF IMMUNOLOGY, 2022)
CRIS-Team WoS Importer:2023-01-27

Innate PD-L1 limits T cell-mediated adipose tissue inflammation and ameliorates diet-induced obesity - Schwartz, Christian; Schmidt, Viviane; Deinzer, Andrea; Hawerkamp, Heike C.; Hams, Emily; Bayerlein, Jasmin; Roeger, Ole; Bailer, Moritz; Krautz, Christian; Elgendy, Amr; Elshafei, Moustafa; Heneghan, Helen M.; et al. (Science Translational Medicine, 2022)
Obesity has become a major health problem in the industrialized world. Immune regulation plays an important role in adipose tissue homeostasis; however, the initial events that shift the balance from a noninflammatory homeostatic environment toward inflammation leading to obesity are poorly understood. Here, we report a role for the costimulatory molecule programmed death-ligand 1 (PD-L1) in the limitation of diet-induced obesity. Functional ablation of PD-L1 on dendritic cells (DCs) using conditional knockout mice increased weight gain and metabolic syndrome during diet-induced obesity, whereas PD-L1 expression on type 2 innate lymphoid cells (ILC2s), T cells, and macrophages was dispensable for obesity control. Using in vitro cocultures, DCs interacted with T cells and ILC2s via the PD-L1:PD-1 axis to inhibit T helper type 1 proliferation and promote type 2 polarization, respectively. A role for PD-L1 in adipose tissue regulation was also shown in humans, with a positive correlation between PD-L1 expression in visceral fat of people with obesity and elevated body weight. Thus, we define a mechanism of adipose tissue homeostasis controlled by the expression of PD-L1 by DCs, which may be a clinically relevant finding with regard to immune-related adverse events during immune checkpoint inhibitor therapy.
CRIS-Team Scopus Importer:2022-03-25

Innate PD-L1 limits T cell mediated adipose tissue inflammation - Schwartz, Christian; Schmidt, Viviane; Deinzer, Andrea; Hawerkamp, Heike C.; Hams, Emily; Bayerlein, Jasmin; Roeger, Ole; Bailer, Moritz; Krautz, Christian; El Gendy, Amr; Elshafei, Moustafa; Hogan, Andrew E.; et al. (EUROPEAN JOURNAL OF IMMUNOLOGY, 2022)
Obesity has become a major health problem in the industrialized world. Immune regulation plays an important role in adipose tissue homeostasis; however, the initial events that shift the balance from a noninflammatory homeostatic environment toward inflammation leading to obesity are poorly understood. Here, we report a role for the costimulatory molecule programmed death-ligand 1 (PD-L1) in the limitation of diet-induced obesity. Functional ablation of PD-L1 on dendritic cells (DCs) using conditional knockout mice increased weight gain and metabolic syndrome during diet-induced obesity, whereas PD-L1 expression on type 2 innate lymphoid cells (ILC2s), T cells, and macrophages was dispensable for obesity control. Using in vitro cocultures, DCs interacted with T cells and ILC2s via the PD-L1:PD-1 axis to inhibit T helper type 1 proliferation and promote type 2 polarization, respectively. A role for PD-L1 in adipose tissue regulation was also shown in humans, with a positive correlation between PD-L1 expression in visceral fat of people with obesity and elevated body weight. Thus, we define a mechanism of adipose tissue homeostasis controlled by the expression of PD-L1 by DCs, which may be a clinically relevant finding with regard to immune-related adverse events during immune checkpoint inhibitor therapy.<br
CRIS-Team WoS Importer:2022-03-11

In Search for Methods to Support Electronic Patient Recruitment in a Multi-ICU Clinical Trial - Diesch, Katharina; Held, Jürgen; Kraus, Stefan; Kunze, Ulrich; Kraska, Detlef; Prokosch, Hans-Ulrich (German Medical Data Sciences: Shaping Change – Creative Solutions for Innovative Medicine, 2019)
Antimycotics are substances to treat fungal infections, a frequent cause of death on intensive care units. It is of great importance to administer such drugs only to patients who actually need them, since the unnecessary application leads to the selection of multiresistent fungi, making future therapy more difficult, and represents a significant financial burden for the health care system. Within the scope of a prospective study, which analyses the premature discontinuation of the administration of unnecessary antifungal drugs, two software platforms for recruitment support were implemented and compared at the University Hospital Erlangen. Besides technical aspects, such as the necessary development time and query runtimes, their usability and user friendliness for the clinical users were compared. We found that the practical identification of patient cohorts is possible both with a full featured business intelligence application and with a low effort approach based on language constructs of the Arden Syntax. Furthermore, this pilot evaluation led to important insights related to the clinical documentation context and data quality issues. A comprehensive analysis of the clinical environment and documentation context is essential for the final decision on the tool to be used.
CRIS-Team Scopus Importer:2019-09-24
Keywords: Antimycotics; Arden Syntax; Clinical Research; Clinical Trial Support; Patient Cohort Identification; Secondary Use

In Situ Maturation and Tissue Adaptation of Type 2 Innate Lymphoid Cell Progenitors - Zeis, Patrice; Lian, Mi; Fan, Xiying; Herman, Josip S.; Hernandez, Daniela C.; Gentek, Rebecca; Elias, Shlomo; Symowski, Cornelia; Knoepper, Konrad; Peltokangas, Nina; Friedrich, Christin; Doucet-Ladeveze, Remi; et al. (Immunity, 2020)
To investigate how innate lymphoid cells (ILCs) are locally maintained, Zeis et al. generated a single-cell atlas of lung ILCs and tracked Il18r1+ progenitor and effector ILC2s. Their work identifies tissue-resident and circulating ILC progenitors and highlights in situ differentiation and tissue adaptation as a mechanism of ILC renewal and phenotypic diversification.
CRIS-Team Scopus Importer:2020-10-23
Keywords: bone marrow; ILC2; ILCP; immune system development; Innate lymphoid cells (ILC); Nippostrongylus Brasiliensis; progenitors; single cell atlas; single-cell RNA-seq; tissue immunity

Integrative bioinformatic analyses of global transcriptome data decipher novel molecular insights into cardiac anti-fibrotic therapies - Fuchs, Maximilian; Kreutzer, Fabian Philipp; Kapsner, Lorenz; Mitzka, Saskia; Just, Annette; Perbellini, Filippo; Terracciano, Cesare M.; Xiao, Ke; Geffers, Robert; Bogdan, Christian; Prokosch, Hans-Ulrich; Fiedler, Jan; et al. (International Journal of Molecular Sciences, 2020)
Integrative bioinformatics is an emerging field in the big data era, offering a steadily increasing number of algorithms and analysis tools. However, for researchers in experimental life sciences it is often difficult to follow and properly apply the bioinformatical methods in order to unravel the complexity and systemic effects of omics data. Here, we present an integrative bioinformatics pipeline to decipher crucial biological insights from global transcriptome profiling data to validate innovative therapeutics. It is available as a web application for an interactive and simplified analysis without the need for programming skills or deep bioinformatics backgroundThe approach was applied to an ex vivo cardiac model treated with natural anti-fibrotic compounds and we obtained new mechanistic insights into their anti-fibrotic action and molecular interplay with miRNAs in cardiac fibrosis. Several gene pathways associated with proliferation, extracellular matrix processes and wound healing were altered, and we could identify micro (mi) RNA-21-5p and miRNA-223-3p as key molecular components related to the anti-fibrotic treatment. Importantlyour pipeline is not restricted to a specific cell type or disease and can be broadly applied to better understand the unprecedented level of complexity in big data research.
CRIS-Team Scopus Importer:2020-07-17
Keywords: Algorithm; Big data; Cardiac fibrosis; Integrative bioinformatics; MiRNAs; Natural compounds; Transcriptomics; Web application

Interactions between Innate Lymphoid Cells and Cells of the Innate and Adaptive Immune System - Symowski, Cornelia; Vöhringer, David (Frontiers in Immunology, 2017)
Type 2 innate lymphoid cells (ILC2s) are a major source of cytokines, which are also produced by Th2 cells and several cell types of the innate immune system. Work over the past few years indicates that ILC2s play a central role in regulating type 2 immune responses against allergens and helminths. ILC2s can interact with a variety of cells types of the innate and adaptive immune system by cell-cell contacts or by communicationviasoluble factors. In this review, we provide an overview about recent advances in our understanding how ILC2s orchestrate type 2 immune responses with focus on direct interactions between ILC2s and other cells of the immune system.
EVALuna2:33422

Intercellular nanotube-mediated mitochondrial transfer enhances T cell metabolic fitness and antitumor efficacy - Baldwin, Jeremy G.; Heuser-Loy, Christoph; Saha, Tanmoy; Schelker, Roland; Slavkovic-Lukic, Dragana; Strieder, Nicholas; Hernandez-Lopez, Inmaculada; Rana, Nisha; Barden, Markus; Mastrogiovanni, Fabio; Martín-Santos, Azucena; Raimondi, Andrea; et al. (Cell, 2024)
Mitochondrial loss and dysfunction drive T cell exhaustion, representing major barriers to successful T cell-based immunotherapies. Here, we describe an innovative platform to supply exogenous mitochondria to T cells, overcoming these limitations. We found that bone marrow stromal cells establish nanotubular connections with T cells and leverage these intercellular highways to transplant stromal cell mitochondria into CD8+ T cells. Optimal mitochondrial transfer required Talin 2 on both donor and recipient cells. CD8+ T cells with donated mitochondria displayed enhanced mitochondrial respiration and spare respiratory capacity. When transferred into tumor-bearing hosts, these supercharged T cells expanded more robustly, infiltrated the tumor more efficiently, and exhibited fewer signs of exhaustion compared with T cells that did not take up mitochondria. As a result, mitochondria-boosted CD8+ T cells mediated superior antitumor responses, prolonging animal survival. These findings establish intercellular mitochondrial transfer as a prototype of organelle medicine, opening avenues to next-generation cell therapies.
CRIS-Team Scopus Importer:2024-11-08
Keywords: bone marrow stromal cells; cancer immunotherapy; CAR T therapy; CD8; immune metabolism; mitochondrial transfer; nanotubes; Talin 2; TCR-T therapy; TIL therapy

Interdisciplinary studies on Coxiella burnetii: From molecular to cellular, to host, to one health research - Bauer, Benjamin U.; Knittler, Michael R.; Andrack, Jennifer; Berens, Christian; Campe, Amely; Christiansen, Bahne; Fasemore, Akinyemi M.; Fischer, Silke F.; Ganter, Martin; Körner, Sophia; Makert, Gustavo R.; Matthiesen, Svea; et al. (International Journal of Medical Microbiology, 2023)
The Q-GAPS (Q fever GermAn interdisciplinary Program for reSearch) consortium was launched in 2017 as a German consortium of more than 20 scientists with exceptional expertise, competence, and substantial knowledge in the field of the Q fever pathogen Coxiella (C.) burnetii. C. burnetii exemplifies as a zoonotic pathogen the challenges of zoonotic disease control and prophylaxis in human, animal, and environmental settings in a One Health approach. An interdisciplinary approach to studying the pathogen is essential to address unresolved questions about the epidemiology, immunology, pathogenesis, surveillance, and control of C. burnetii. In more than five years, Q-GAPS has provided new insights into pathogenicity and interaction with host defense mechanisms. The consortium has also investigated vaccine efficacy and application in animal reservoirs and identified expanded phenotypic and genotypic characteristics of C. burnetii and their epidemiological significance. In addition, conceptual principles for controlling, surveilling, and preventing zoonotic Q fever infections were developed and prepared for specific target groups. All findings have been continuously integrated into a Web-based, interactive, freely accessible knowledge and information platform (www.q-gaps.de), which also contains Q fever guidelines to support public health institutions in controlling and preventing Q fever. In this review, we will summarize our results and show an example of how an interdisciplinary consortium provides knowledge and better tools to control a zoonotic pathogen at the national level.
CRIS-Team Scopus Importer:2023-12-15
Keywords: Immune subversion/defense; Molecular epidemiology; One Health; Q fever; Ruminants; Virulence factors; Zoonosis

Interdisciplinary symposium on challenges and opportunities for vaccines: A comprehensive approach of current and future vaccine strategies to improve vaccine effectiveness in complex chronic infectious contexts - Siebner, Alex S.; Habib, Marrium; Osmani, Vanesa; Adegnika, Ayola Akim; Bogdan, Christian; Breloer, Minka; Elliott, Alison; Fathi, Anahita; Hendrickx, Greet; Nono, Justin Komguep; Lang, Roland; Mayer, Johannes U.; et al. (Vaccine: X, 2025)
Vaccination is a key public health intervention, but vaccine immunogenicity, efficacy, and effectiveness vary geographically. These variations are not yet fully understood but are likely influenced by factors such as chronic infections, environmental and genetic differences, social and behavioral factors, and operational challenges, particularly in low- and middle-income countries (LMICs). To address these issues, the “International Symposium on Global Challenges and Opportunities for Vaccines” was held in Kloster Bernried, Germany, bringing together international scientists and stakeholders. Key discussions included: (1) Compromised vaccine immunogenicity due to helminth infections, (2) new vaccine approaches in vaccine development, (3) new frontiers in therapeutic vaccination, (4) challenges of vaccine trials, especially in low-resource settings, and (5) conceptualizing vaccine confidence in low and high resource contexts. The symposium highlighted the challenges of conducting vaccine trials in LMICs, such as participant follow-up, logistics, resources, and building trust. The main recommendation was to improve future vaccine trial designs through a comprehensive, interdisciplinary approach, including tools to evaluate vaccine immunogenicity, efficacy, and effectiveness.
CRIS-Team Scopus Importer:2025-03-14

Interleukin-13 and its receptor are synaptic proteins involved in plasticity and neuroprotection - Li, Shun; olde Heuvel, Florian; Rehman, Rida; Aousji, Oumayma; Froehlich, Albrecht; Li, Zhenghui; Jark, Rebecca; Zhang, Wanhong; Conquest, Alison; Woelfle, Sarah; Schoen, Michael; O´Meara, Caitlin C.; et al. (Nature Communications, 2023)
Immune system molecules are expressed by neurons, yet their functions are often unknown. We have identified IL-13 and its receptor IL-13Ra1 as neuronal, synaptic proteins in mouse, rat, and human brains, whose engagement upregulates the phosphorylation of NMDAR and AMPAR subunits and, in turn, increases synaptic activity and CREB-mediated transcription. We demonstrate that increased IL-13 is a hallmark of traumatic brain injury (TBI) in male mice as well as in two distinct cohorts of human patients. We also provide evidence that IL-13 upregulation protects neurons from excitotoxic death. We show IL-13 upregulation occurring in several cohorts of human brain samples and in cerebrospinal fluid (CSF). Thus, IL-13 is a physiological modulator of synaptic physiology of neuronal origin, with implications for the establishment of synaptic plasticity and the survival of neurons under injury conditions. Furthermore, we suggest that the neuroprotection afforded through the upregulation of IL-13 represents an entry point for interventions in the pathophysiology of TBI.
CRIS-Team Scopus Importer:2023-01-27

Interleukin-33-activated basophils promote asthma by regulating Th2 cell entry into lung tissue - Schuijs, Martijn J.; Brenis Gomez, Claudia M.; Bick, Fabian; Van Moorleghem, Justine; Vanheerswynghels, Manon; van Loo, Geert; Beyaert, Rudi; Vöhringer, David; Locksley, Richard M.; Hammad, Hamida; Lambrecht, Bart N. (Journal of Experimental Medicine, 2024)
Asthma is characterized by lung eosinophilia, remodeling, and mucus plugging, controlled by adaptive Th2 effector cells secreting IL-4, IL-5, and IL-13. Inhaled house dust mite (HDM) causes the release of barrier epithelial cytokines that activate various innate immune cells like DCs and basophils that can promote Th2 adaptive immunity directly or indirectly. Here, we show that basophils play a crucial role in the development of type 2 immunity and eosinophilic inflammation, mucus production, and bronchial hyperreactivity in response to HDM inhalation in C57Bl/6 mice. Interestingly, conditional depletion of basophils during sensitization did not reduce Th2 priming or asthma inception, whereas depletion during allergen challenge did. During the challenge of sensitized mice, basophil-intrinsic IL-33/ST2 signaling, and not FcεRI engagement, promoted basophil IL-4 production and subsequent Th2 cell recruitment to the lungs via vascular integrin expression. Basophil-intrinsic loss of the ubiquitin modifying molecule Tnfaip3, involved in dampening IL-33 signaling, enhanced key asthma features. Thus, IL-33-activated basophils are gatekeepers that boost allergic airway inflammation by controlling Th2 tissue entry.
CRIS-Team Scopus Importer:2024-10-04

Interleukin 33: an innate alarm for adaptive responses beyond Th2 immunity-emerging roles in obesity, intestinal inflammation, and cancer. - Schwartz, Christian; O'Grady, Katie; Lavelle, Ed C.; Fallon, Padraic G. (European Journal of Immunology, 2016)
Interleukin (IL)-33, a member of the IL-1 family, was originally described in 2005 as a potent initiator of type 2 immunity found during allergic inflammation and parasitic infections. IL-33 has been shown to play important and potent roles bridging innate and adaptive immunity in the regulation of tissue homeostasis, injury, and repair. Recent discoveries have extended the range of functions for IL-33 beyond type 2 conditions and its role as an alarmin at barrier sites, with emerging central roles for IL-33 in T-cell regulation, obesity, viral and tumor immunity. Here, we review the recent advances on how IL-33 activity is regulated, its immunomodulatory properties on innate and adaptive cells, and the newly discovered roles of IL-33 in obesity, intestinal inflammation, and tumorigenesis.

Intestinal eosinophils: characterization of elusive granulocytes as anti-bacterial and immunomodulatory effector cells in colitis - Holland, Tim; Mattner, Jochen (Signal Transduction and Targeted Therapy, 2023)
CRIS-Team Scopus Importer:2023-09-08

Intestinal epithelial Gasdermin C is induced by IL-4R/STAT6 signaling but is dispensable for gut immune homeostasis - Gámez Belmonte, Maria de los Reyes; Wagner, Yara; Mahapatro, Mousumi; Wang, Ru; Erkert, Lena; Gonzalez Acera, Miguel; Cineus, Roodline; Hainbuch, Saskia; Patankar, Jay; Vöhringer, David; Hegazy, Ahmed N.; Neurath, Markus; et al. (Scientific Reports, 2024)
Gasdermin C is one of the least studied members of the gasdermin family of proteins, known for their critical involvement in pyroptosis and host defense. Furthermore, evidence for the role of Gasdermin C in the intestine is scarce and partly controversial. Here, we tested the functional role of Gasdermin C in intestinal homeostasis, inflammation and tumorigenesis. : We studied Gasdermin C in response to cytokines in intestinal organoids. We evaluated epithelial differentiation, cell death and immune infiltration under steady state conditions in a new mouse line deficient in Gasdermin C. The role of Gasdermin C was analyzed in acute colitis, infection and colitis-associated cancer. Gasdemin C is highly expressed in the intestinal epithelium and strongly induced by the type 2 cytokines IL-4 and IL-13 in a STAT6-dependent manner. Gasdermin C-deficient mice show no changes in tissue architecture and epithelial homeostasis. Epithelial organoids deficient in Gasdermin C develop normally and show no alterations in proliferation or cell death. No changes were found in models of acute colitis, type 2 intestinal infection and colitis-associated cancer. Gasdermin C genes are upregulated by type 2 immunity, yet appear dispensable for the development of intestinal inflammation, infection and colitis-associated cancer.
CRIS-Team Scopus Importer:2024-11-15
Keywords: Gasdermin; Gut pathology; Intestinal homeostasis

Intestinal helminth co-infection and associated factors among pulmonary tuberculosis patients in Africa and Asia: a systematic review and meta-analysis - Zenebe, Yohannes; Habtamu, Meseret; Abebe, Markos; Tulu, Begna; Atnafu, Abay; Mekonnen, Daniel; Lang, Roland; Munshea, Abaineh (BMC Infectious Diseases, 2023)
Introduction: Tuberculosis (TB) and intestinal helminths have huge public health importance, and they are geographically overlapped. Data about the burden of intestinal helminth and TB co-infection in these areas are fragmented. In this systematic review and meta-analysis we compile the current literatures and generate pooled prevalence. We also identity factors associated with intestinal helminth co-infection among TB patients. Methods: Original articles published in English language up to March 23, 2022 were systematically searched from electronic database (PubMed/Medline, Scopus, Science Direct, Google Scholars and HINARI). The search was done using medical subject heading terms and keywords. Identified articles were exported into the EndNote library. The identified articles were screened using PRISMA flow diagram. Then the methodological quality of included articles was evaluated and rated using the modified version of Newcastle–Ottawa Scale. Data were extracted using Microsoft Excel. Sensitivity analysis and Egger regression test were used for the assessment of heterogeneity and publication bias. Finally the results are presented with a meta-analysis of pooled estimates, forest plots, and tables. The quantitative data were analyzed using Stata version 14. Results: From a total of 5457 searched articles, 22 eligible articles were included in the review. The pooled prevalence of helminth co-infection among TB cases was 29.69% (95%CI: 21.10, 38.29). TB patients were found to more frequently harbor one or more intestinal helminths than TB negative individuals (OR = 1.72 (95%CI: 1.20, 2.48)). Among the reported helminths, Schistosoma mansoni and Strongyloides stercoralis had the highest pooled prevalence among TB cases. However, unlike other individual helminths, only Strongyloides stercoralis (OR = 2.67 (95% CI, 1.20–6.76)) had significant association with TB cases compared to TB negatives. BMI was significantly associated with intestinal helminth co-infection among TB patients (OR = 2.75 (95%CI: 1.19, 6.38)). Conclusions: Patients with TB have been shown to harbor co-infection with one or more intestinal helminths with considerable proportions when compared with TB-negative individuals. The higher prevalence of helminth infection in TB cases might indicate that co-infection promotes active TB disease. Thus, routine intestinal helminth screening and assessment of their nutritional status is suggested for TB patients.
CRIS-Team Scopus Importer:2023-11-10
Keywords: Africa; Asia; Co-infection; Intestinal helminths; Pooled prevalence; Tuberculosis

Intestinal Helminth Infections and Their Association with QuantiFERON-TB Gold Plus Test Performance in an Endemic Setting, Northwest Ethiopia - Zenebe, Yohannes; Abebe, Markos; Munshea, Abaineh; Yismaw, Gizachew; Zewde, Meaza; Alemayehu, Mekdelawit; Lang, Roland; Habtamu, Meseret (Infection and Drug Resistance, 2024)
Background: Timely detection and treatment of latent TB infection (LTBI) is part of WHO’s strategy against tuberculosis (TB). Helminth infections can modulate immune responses, potentially impacting the performance of interferon-gamma release assays (IGRAs) such as the QuantiFERON-TB Gold Plus (QFT-Plus). This study evaluated the association between helminth infections and QFT-Plus results among participants from a TB-endemic region. Methods: A cross-sectional study was conducted from October 2022 to March 2023 in Bahir Dar, Ethiopia. Stool samples of 314 potential participants were examined for helminths using wet mount and Kato-Katz techniques. LTBI was assessed by QFT-Plus from a total of 100 gender-matched helminth-positive and-negative participants. The association between helminth infection status, egg count, and QFT-Plus positivity was analyzed, and p values <0.05 were considered significant. Results: Overall, 53 of 314 screened participants were infected with helminths (16.9%), with A. lumbricoides (47.2%) and hookworm (30.2%) as most prevalent species. The overall QFT-Plus positivity rate was 30.0%, with similar rates observed between helminth-positive and helminth-negative participants. Although QFT-Plus positivity was slightly lower in hookworm carriers (25%) compared to those with A. lumbricoides (32%), a higher-than-median hookworm egg burden was significantly associated with reduced QFT-Plus positivity (P = 0.029). QFT-Plus positivity was significantly higher among male participants than females (P = 0.032). Conclusion: While overall helminth infection status did not significantly affect QFT-Plus positivity, higher hookworm burden was associated with reduced QFT-Plus reactivity. These findings suggest that the type of helminth and infection intensity, rather than its mere presence, may influence IGRA performance. Further studies with larger sample sizes are warranted to understand the species-specific effect of helminth infection on immune modulation of the host.
CRIS-Team Scopus Importer:2024-11-08
Keywords: Ethiopia; intestinal helminths; LTBI; MTB; QFT-Plus

Intestinal tumorigenesis initiated by dedifferentiation and acquisition of stem-cell-like properties - Schwitalla, Sarah; Fingerle, Alexander A.; Cammareri, Patrizia; Nebelsiek, Tim; Goektuna, Serkan I.; Ziegler, Paul K.; Canli, Ozge; Heijmans, Jarom; Huels, David J.; Moreaux, Guenievre; Rupec, Rudolf A.; Gerhard, Markus; et al. (Cell, 2013)
Cell-type plasticity within a tumor has recently been suggested to cause a bidirectional conversion between tumor-initiating stem cells and nonstem cells triggered by an inflammatory stroma. NF-κB represents a key transcription factor within the inflammatory tumor microenvironment. However, NF-κB's function in tumor-initiating cells has not been examined yet. Using a genetic model of intestinal epithelial cell (IEC)-restricted constitutive Wnt-activation, which comprises the most common event in the initiation of colon cancer, we demonstrate that NF-κB modulates Wnt signaling and show that IEC-specific ablation of RelA/p65 retards crypt stem cell expansion. In contrast, elevated NF-κB signaling enhances Wnt activation and induces dedifferentiation of nonstem cells that acquire tumor-initiating capacity. Thus, our data support the concept of bidirectional conversion and highlight the importance of inflammatory signaling for dedifferentiation and generation of tumor-initiating cells in vivo.
EVALuna2:7625

Intracellular compartments of pathogens: Highways to hell or stairways to heaven? - Haas, Albert; Hensel, Michael; Lührmann, Anja; Rudel, Thomas; Saftig, Paul; Schaible, Ulrich E. (International Journal of Medical Microbiology, 2017)
EVALuna2:36417

Involvement of interleukin-18 in the pathogenesis of human eosinophilic esophagitis - Niranjan, Rituraj; Rajavelu, Priya; Ventateshaiah, Sathisha Upparahalli; Shukla, Jai Shankar; Zaidi, Asifa; Mariswamy, Siddesha Jalahalli; Mattner, Jochen; Fortgang, Liana; Kowalczyk, Monika; Balart, Luis; Shukla, Anshi; Mishra, Anil (Clinical Immunology, 2015)
IL-18 is induced in food allergy and EoE is food allergen-induced disease. Therefore, we tested the hypothesis whether IL-18 is involved in food allergen-induced EoE pathogenesis. Accordingly, we examined normal SPT+ and SPT- EoE patient blood and biopsy samples for IL-18, IL-18R?, ICAM and VCAM expression. Herein, we show increased IL-18 level is highly significant in food allergen SPT+ compared to SPT- EoE patients. We also report that IL-18R?+ cells and mRNA levels are induced in the esophageal biopsies of EoE patients and blood IL-18 levels correlate with esophageal eosinophilia (P<0.01). Additionally, we report that the levels of esophageal eosinophil and mast cells correlate with ICAM expression in human EoE. Mechanistically, we show that IL-18 in vitro stimulates iNKT cells and endothelial cells and induce eosinophil active cytokines IL-5 and IL-13. We provide the evidence that IL-18 is critical cytokine involved in activation of iNKT cells and ICAM in promoting human EoE.
EVALuna2:7684

Iron Regulator Hepcidin Impairs Macrophage-Dependent Cardiac Repair After Injury - Zlatanova, Ivana; Pinto, Cristina; Bonnin, Philippe; Mathieu, Jacques R. R.; Bakker, Wineke; Vilar, Jose; Lemitre, Mathilde; Vöhringer, David; Vaulont, Sophie; Peyssonnaux, Carole; Silvestre, Jean-Sébastien (Circulation, 2019)
BACKGROUND: Defective systemic and local iron metabolism correlates with cardiac disorders. Hepcidin, a master iron sensor, actively tunes iron trafficking. We hypothesized that hepcidin could play a key role to locally regulate cardiac homeostasis following acute myocardial infarction (AMI). METHODS: Cardiac repair was analyzed in mice harboring specific cardiomyocyte or myeloid cell deficiency of hepcidin and challenged with AMI. RESULTS: We found that the expression of hepcidin was elevated after AMI and the specific deletion of hepcidin in cardiomyocytes failed to improve cardiac repair and function. However, transplantation of bone marrow derived cells from hepcidin deficient mice ( Hamp-/-) or from mice with specific deletion of hepcidin in myeloid cells (LysMCRE/+/ Hampf/f) improved cardiac function. This effect was associated with a robust reduction in the infarct size and tissue fibrosis in addition to favoring cardiomyocyte renewal. Macrophages lacking hepcidin promoted cardiomyocyte proliferation in a prototypic model of apical resection-induced cardiac regeneration in neonatal mice. IL-6 increased hepcidin levels in inflammatory macrophages. Hepcidin deficiency enhanced the number of CD45+/CD11b+/F4/80+/CD64+/MHCIILow/CCR2+ inflammatory macrophages and fostered STAT3 phosphorylation, an instrumental step in the release of IL-4 and IL-13. The combined genetic suppression of hepcidin and IL-4/IL-13 in macrophages failed to improve cardiac function in both adult and neonatal injured hearts. CONCLUSIONS: Hepcidin refrains macrophage-induced cardiac repair and regeneration through modulation of IL-4/IL-13 pathways.
EVALuna2:36405

Ischaemic stroke and Clostridium septicum sepsis and meningitis in a patient with occult colon carcinoma - a case report and review of the literature - Macha, Kosmas; Giede-Jeppe, Antje; Lücking, Hannes; Coras, Roland; Huttner, Hagen; Held, Jürgen (BMC Neurology, 2016)
Clostridium septicum is a rare cause of meningitis and brain abscess in children and adults. Gas production by the pathogen can lead to pneumocephalus and the overall mortality rate of Clostridium septicum CNS infection is as high as 74%. The most common entry site of the pathogen is the gastrointestinal tract.We describe a 74-year-old man who presented with a left-sided cerebral infarction in the middle cerebral artery territory. In addition the patient showed signs of Systemic Inflammatory Response Syndrome and Disseminated Intravascular Coagulation. Examination of blood cultures and cerebrospinal fluid led to the diagnosis of sepsis and meningitis caused by Clostridium septicum. Despite appropriate antibiotic therapy the condition of the patient deteriorated rapidly and he died on day 2 after admission. Autopsy revealed a previously unknown adenocarcinoma of the colon ascendens as entry site of the pathogen.Clostridium septicum should be considered as potential pathogen in patients with sepsis and meningitis. Gram stain morphology in conjunction with severe sepsis can rapidly point into the direction of this pathogen. CNS infections manifest either as meningoencephalitis/cerebritis or as brain abscess. Entry site of the pathogen is almost uniquely the gastrointestinal tract. In adults more than 50% suffer from colorectal carcinoma, therefore survivors of Clostridium septicum infections should be examined for underlying occult colorectal malignancy.
EVALuna2:7346

Is COVID-19-associated pulmonary aspergillosis (CAPA) a myth? Frequency of Aspergillus detection from respiratory samples in intensive care unit patients with and without COVID-19 - Kuemmig, T.; Esse, Jan; Herbst, Larissa; Castellanos, I.; Strauss, Richard; Geißdörfer, Walter; Mihai, Sidonia; Rakova, Natalia; Cipa, Franziska; Pflaum, D.; Werblow, M.; Lang, Anne-Katharina; et al. (MYCOSES, 2021)
CRIS-Team WoS Importer:2021-10-08

Itaconate mediates control of Coxiella burnetii infection in murine macrophages - Siddique, Md Nur A Alam; Kohl, Lisa; Berger, Raffaela; Schulze-Lührmann, Jan; Lührmann, Anja; Wilde, Katja Dettmer; Lang, Roland (EUROPEAN JOURNAL OF IMMUNOLOGY, 2021)
CRIS-Team WoS Importer:2022-03-11

Kutane Leishmaniasis als Reisedermatose. Klinik, Diagnostik und Therapie - Von Stebut, E.; Schleicher, Ulrike; Bogdan, Christian (Hautarzt, 2012)
Leishmaniasis is a disease with worldwide increasing incidence, which in Germany is almost exclusively observed in patients who have travelled to classical endemic regions such as the Mediterranean basin. Cause of the disease is an infection with protozoan parasites of the genus Leishmania, which are transmitted by sand flies and replicate intracellularly within mammalian hosts. Depending on the inoculated parasite (sub-) species and the immune status of the host, a local cutaneous, diffuse cutaneous, mucocutaneous or visceral form of leishmaniasis will develop. Cutaneous leishmaniasis, which frequently appears only weeks after the bite of a sand fly, starts with the formation of a papule, which subsequently can turn into a skin ulcer. The latter may heal spontaneously after months leaving behind a scar or persist as chronic, non-healing cutaneous leishmaniasis. If cutaneous leishmaniasis is suspected, a sterile skin biopsy followed by appropriate diagnostic measures in a specialized laboratory to identify the pathogen should be performed. For the decision on the type of therapy, several clinical parameters (e.g. number and localization of lesions, immune status) and, most importantly, the underlying parasite (sub-) species need to be considered. Therapy can consist of a variety of topical measures or systemic drug treatment. A modern and safe vaccine does not yet exist. © 2012 Springer-Verlag.
CRIS-Team Scopus Importer:2024-02-26
Keywords: Cutaneous leishmaniasis; Leishmaniasis; Mucocutaneous leishmaniasis; Oriental sore; Therapy

LAMP proteins account for the maturation delay during the establishment of the Coxiella burnetii-containing vacuole - Schulze-Luehrmann, Jan; Eckart, Rita A.; Oelke, Martha; Saftig, Paul; Liebler-Tenorio, Elisabeth; Lührmann, Anja (Cellular Microbiology, 2016)
The obligate intracellular pathogen Coxiella burnetii replicates in a large phagolysosomal-like vacuole. Currently, both host and bacterial factors required for creating this replicative parasitophorous C. burnetii-containing vacuole (PV) are poorly defined. Here, we assessed the contributions of the most abundant proteins of the lysosomal membrane, LAMP-1 and LAMP-2, to the establishment and maintenance of the PV. Whereas these proteins were not critical for uptake of C. burnetii, they influenced the intracellular replication of C. burnetii. In LAMP-1/2 double-deficient fibroblasts as well as in LAMP-1/2 knock-down cells, C. burnetii establishes a significantly smaller, yet faster maturing vacuole, which harboured more bacteria. The accelerated maturation of PVs in LAMP double-deficient fibroblasts, which was partially or fully reversed by ectopic expression of LAMP-1 or LAMP-2, respectively, was characterized by an increased fusion rate with endosomes, lysosomes and bead-containing phagosomes, but not by different fusion kinetics with autophagy vesicles. These findings establish that LAMP proteins are critical for the maturation delay of PVs. Unexpectedly, neither the creation of the spacious vacuole nor the delay in maturation was found to be prerequisites for the intracellular replication of C. burnetii.
EVALuna2:7697

L-arginine as a novel target for clinical intervention in inflammatory bowel disease - Nüse, Björn; Mattner, Jochen (Exploration of Immunology, 2021)
Arginase-1 (Arg1) and the inducible nitric oxide synthase 2 (NOS2) compete for the common substrate L-arginine, semi-essential amino acid, and central intestinal metabolite. Both enzymes exhibit various, sometimes opposing effects on immune responses, tissue regeneration, or microbial growth and replication. In sub-mucosal tissues of patients suffering from inflammatory bowel disease (IBD), similar as in experimental colitis, the expression and activity of both enzymes, Arg1 and NOS2 are more prominent than in respective controls. Accordingly, the metabolism of L-arginine is altered in IBD patients. Thus, L-arginine represents a promising medical target for clinical intervention in these devastating diseases. Previous studies primarily focused on the host side of L-arginine metabolism. Initial reports using Arg1 inhibitors generated conflicting results in murine colitis models. Subsequently, only the generation of conditional Arg1 knockout mice allowed reliable functional analyses of Arg1 and the L-arginine metabolism in the immune system. Utilizing cell-specific conditional Arg1 knockouts, we have recently reported that Arg1, surprisingly, hampered the resolution of experimental colitis due to the restriction of the intraluminal availability of L-arginine. Reduced levels of L-arginine restrained the compositional diversity of the intestinal microbiota and subsequently the mutual metabolism between the microbiota and the host. Thus, the intraluminal microbiota represents a potential therapeutic target for L-arginine metabolism aside from host-dependent L-arginine consumption.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Arginase-1; colitis; gut microbiota; inflammatory bowel disease; intestinal metabolism; L-arginine

L-arginine metabolism as pivotal interface of mutual host–microbe interactions in the gut - Nüse, Björn; Holland, Tim; Rauh, Manfred; Gerlach, Roman; Mattner, Jochen (Gut Microbes, 2023)
L-arginine (L-arg) is a versatile amino acid and a central intestinal metabolite in mammalian and microbial organisms. Thus, L-arg participates as precursor of multiple metabolic pathways in the regulation of cell division and growth. It also serves as a source of carbon, nitrogen, and energy or as a substrate for protein synthesis. Consequently, L-arg can simultaneously modify mammalian immune functions, intraluminal metabolism, intestinal microbiota, and microbial pathogenesis. While dietary intake, protein turnover or de novo synthesis usually supply L-arg in sufficient amounts, the expression of several key enzymes of L-arg metabolism can change rapidly and dramatically following inflammation, sepsis, or injury. Consequently, the availability of L-arg can be restricted due to increased catabolism, transforming L-arg into an essential amino acid. Here, we review the enzymatic pathways of L-arg metabolism in microbial and mammalian cells and their role in immune function, intraluminal metabolism, colonization resistance, and microbial pathogenesis in the gut.
CRIS-Team Scopus Importer:2023-07-21
Keywords: colonization resistance; dietary L-arg supplementation; host–microbe interaction; intestinal microbiota; L-arginine (L-arg); microbial pathogenesis; mucosal immune function; mutual metabolic pathways; virulence factor

L-Arginine metabolism inhibits arthritis and inflammatory bone loss - Cao, Shan; Li, Yixuan; Song, Rui; Meng, Xianyi; Fuchs, Maximilian; Liang, Chunguang; Kachler, Katerina; Meng, Xinyu; Wen, Jinming; Schlötzer-Schrehardt, Ursula; Taudte, Verena; Geßner, Arne; et al. (Annals of the Rheumatic Diseases, 2023)
Objectives: To investigate the effect of the L-Arginine metabolism on arthritis and inflammation-mediated bone loss. Methods: L-Arginine was applied to three arthritis models (collagen-induced arthritis, serum-induced arthritis and human TNF transgenic mice). Inflammation was assessed clinically and histologically, while bone changes were quantified by μCT and histomorphometry. In vitro, effects of L-Arginine on osteoclast differentiation were analysed by RNA-seq and mass spectrometry (MS). Seahorse, Single Cell ENergetIc metabolism by profilIng Translation inHibition and transmission electron microscopy were used for detecting metabolic changes in osteoclasts. Moreover, arginine-Associated metabolites were measured in the serum of rheumatoid arthritis (RA) and pre-RA patients. Results: L-Arginine inhibited arthritis and bone loss in all three models and directly blocked TNFα-induced murine and human osteoclastogenesis. RNA-seq and MS analyses indicated that L-Arginine switched glycolysis to oxidative phosphorylation in inflammatory osteoclasts leading to increased ATP production, purine metabolism and elevated inosine and hypoxanthine levels. Adenosine deaminase inhibitors blocking inosine and hypoxanthine production abolished the inhibition of L-Arginine on osteoclastogenesis in vitro and in vivo. Altered arginine levels were also found in RA and pre-RA patients. Conclusion: Our study demonstrated that L-Arginine ameliorates arthritis and bone erosion through metabolic reprogramming and perturbation of purine metabolism in osteoclasts.
CRIS-Team Scopus Importer:2023-11-24
Keywords: Arthritis; Inflammation; Osteoporosis

L-ARGININE REPROGRAMS OSTEOCLAST PURINE METABOLISM AMELIORATING BONE LOSS IN RHEUMATOID ARTHRITIS - Cao, Shan; Song, Rui; Meng, Xianyi; Kachler, Katerina; Fuchs, Maximilian; Meng, X.; Li, Y.; Taudte, Verena; Kunz, Meik; Schlötzer-Schrehardt, Ursula; Schleicher, Ulrike; Chen, X.; et al. (ANNALS OF THE RHEUMATIC DISEASES, 2022)
CRIS-Team WoS Importer:2022-11-04

Late-Onset Aspergillus Fumigatus Infection of an Aortic Stent Graft in an Immunocompetent Patient - Ballazhi, Fatos; Weyand, Michael; Lang, Werner; Schoerner, Christoph; Seitz, Tatjana (Thoracic and Cardiovascular Surgeon Reports, 2015)
Aspergillus fumigatus as a clinical entity is difficult to diagnose. We present a case, which could facilitate diagnosis and management of the aforementioned disease. A 60-year-old man with stent graft implantation in the descending aorta (6 years ago) presented with fever, night sweats, and weight loss over 5 months. Leukocytosis and elevated C-reactive protein were constantly spiking. Blood cultures were negative. Notably, the serum immunoglobulin E (IgE) level was strongly elevated (> 1,000 U/mL). Anamnestically, the patient suffered from a mild form of atopic dermatitis and bronchial asthma. The pulmonary status showed no abnormalities in the computed tomography image. Nonetheless, a chest scan revealed a suspected abscess around the stent graft of the descending aorta. Extra-anatomic ascending to descending aortic bypass (Gelsoft 22 mm, Vascutek, Juchinnan, Scotland, United Kingdom) was performed. Intraoperative samples revealed A. fumigatus. These findings were confirmed by polymerase chain reaction analysis. Infection by A. fumigatus represents a diagnostic challenge because blood cultures are usually negative, but expeditious treatment is required to prevent occurrence of irreversible complications. A late graft infection, possibly caused by A. fumigatus should be suspected in patients with implanted grafts, who suffer from unexplained, blood culture-negative fever that does not respond to antibiotics and who have a history of dermatitis or bronchial asthma with elevated IgE antibodies.
EVALuna2:7685

Latest perspectives on macrophages in bone homeostasis - Bozec, Aline; Soulat, Didier (Pflügers Archiv: European Journal of Physiology, 2017)
Knowledge about macrophages residing in the bone, also known as osteal macrophages or osteomacs, is still limited. A hallmark of this peculiar myeloid population is the expression of macrophage markers distinct from the markers found on osteoclast surface. In bone, osteomacs are in contact with osteoblasts, where they are involved in regulating bone homeostasis. However, additional macrophage subtypes already present in the bone marrow or recruited from the blood circulation could have further functions, which could be all important for the maintenance of the bone architecture and its associated functions. Indeed, bone marrow macrophages have been found to eliminate apoptotic cells, particularly apoptotic osteoblasts through a process named efferocytosis. This phagocytic process plays an essential role in bone tissue homeostasis and new bone formation. In addition, bone marrow macrophages can influence the hematopoietic stem cell (HSC) niches. They contribute to the regulation of the HSC progenitor cell maintenance, mobilization, and function. To do so, macrophages secrete cytokines in steady state or during stress conditions. These cytokines influence hematopoiesis either by a direct effect on HSCs or through the control of stromal cells that are essential for the HSC niches. Interestingly, the similarities between the niches for HSCs and the niche for metastatic tumor cells support the possibility that bone-resident macrophages could control the homing of tumor cells and their proliferation within the bone. In general, macrophage role during metastatic processes is well described; however, their direct involvement in bone metastasis is a rising research area. In this review, we will highlight the macrophage functions in the skeleton, in the maintenance of the HCS niches, and their importance in bone metastasis.
EVALuna2:7749

Launch of a national candidemia surveillance network in Germany - Aldejohann, A. M.; Reinhardt, M.; Martin, R.; Walther, G.; Elias, J.; Haas, A.; Hamprecht, A.; Held, Jürgen; Hess, C.; Hogardt, M.; Rath, P. M.; Rothe, K.; et al. (MYCOSES, 2021)
CRIS-Team WoS Importer:2021-10-08

LDHA-Associated Lactic Acid Production Blunts Tumor Immunosurveillance by T and NK Cells - Brand, Almut; Singer, Katrin; Koehl, Gudrun E.; Kolitzus, Marlene; Schoenhammer, Gabriele; Thiel, Annette; Matos, Carina; Bruss, Christina; Klobuch, Sebastian; Peter, Katrin; Kastenberger, Michael; Bogdan, Christian; et al. (Cell Metabolism, 2016)
Elevated lactate dehydrogenase A (LDHA) expression is associated with poor outcome in tumor patients. Here we show that LDHA-associated lactic acid accumulation in melanomas inhibits tumor surveillance by T and NK cells. In immunocompetent C57BL/6 mice, tumors with reduced lactic acid production (Ldha(low)) developed significantly slower than control tumors and showed increased infiltration with IFN-?-producing T and NK cells. However, in Rag2(-/-)?c(-/-) mice, lacking lymphocytes and NK cells, and in Ifng(-/-) mice, Ldha(low) and control cells formed tumors at similar rates. Pathophysiological concentrations of lactic acid prevented upregulation of nuclear factor of activated T cells (NFAT) in T and NK cells, resulting in diminished IFN-? production. Database analyses revealed negative correlations between LDHA expression and T cell activation markers in human melanoma patients. Our results demonstrate that lactic acid is a potent inhibitor of function and survival of T and NK cells leading to tumor immune escape.
EVALuna2:7715

Leukoreduction system chambers are an efficient, valid, and economic source of functional monocyte-derived dendritic cells and lymphocytes - Pfeiffer, Isabell A.; Zinser, Elisabeth; Strasser, Erwin; Stein, Marcello F.; Dörrie, Jan; Schaft, Niels; Steinkasserer, Alexander; Knippertz, Ilka (Immunobiology, 2013)
The demand for human monocyte-derived dendritic cells (moDCs), as well as for primary human B and T lymphocytes for immunological research purposes has been increased in recent years. Classically, these monocytes are isolated from blood, leukapheresis products or buffy coats of healthy donors by plastic adherence of peripheral blood mononuclear cells (PBMCs), followed by stimulation with granulocyte macrophage colony-stimulating factor (GM-CSF) and interleukin (IL)-4, while lymphocytes are usually isolated from the non-adherent fraction (NAF) by magnetic cell sorting. However, donor-blood is a limited resource and not every blood bank offers leukapheresis products or buffy coats for laboratory use. Additionally, a leukapheresis is very expensive and also the generation/isolation of cells is time- and cost-intensive. To overcome some of these obstacles, we evaluated if low-cost leukoreduction system chambers (LRSCs), which arise after routine donor plateletpheresis procedures, and are usually discarded, would be an alternative and appropriate source of PBMCs to generate moDCs and to isolate lymphocytes. By analyzing the number and phenotype of immature and mature dendritic cells (DCs), as well as of B and T lymphocytes derived from LRSCs, we found all cells to be of high quantity and quality. Further investigations on DCs comprising transwell migration assays, allogeneic mixed lymphocyte reactions (MLR), cytokine secretion assays, and cytotoxic T cell induction assays revealed high migratory, as well as stimulatory capacity of these cells. In addition, DCs and T cells were efficiently electroporated with mRNA and showed characteristic cytokine production after co-culture, demonstrating LRSCs as an efficient, valid, and economic source for generation of moDCs and lymphocytes for research purposes. © 2013 Elsevier GmbH.
CRIS-Team Scopus Importer:2021-10-01
Keywords: B cell; Leukoreduction system chamber; Monocyte-derived dendritic cell; Peripheral blood mononuclear cell; T cell

Lightning up the worm: How to probe fungal virulence in an alternative mini-host by bioluminescence - Krappmann, Sven (Virulence, 2015)
EVALuna2:7689

Limitation of TCA Cycle Intermediates Represents an Oxygen-Independent Nutritional Antibacterial Effector Mechanism of Macrophages - Hayek, Inaya; Fischer, Fabian; Schulze-Luehrmann, Jan; Dettmer, Katja; Sobotta, Katharina; Schatz, Valentin; Kohl, Lisa; Boden, Katharina; Lang, Roland; Oefner, Peter J.; Wirtz, Stefan; Jantsch, Jonathan; et al. (Cell Reports, 2019)
In hypoxic and inflamed tissues, oxygen (O-2)-dependent antimicrobial defenses are impaired due to a shortage of O-2. To gain insight into the mechanisms that control bacterial infection under hypoxic conditions, we infected macrophages with the obligate intracellular pathogen Coxiella burnetii, the causative agent of Q fever. Our experiments revealed that hypoxia impeded C. burnetii replication in a hypoxia-inducible factor (HIF) 1 alpha-dependent manner. Mechanistically, under hypoxia, HIF1 alpha impaired the activity of STAT3, which in turn reduced the intracellular level of TCA cycle intermediates, including citrate, and impeded C. burnetii replication in macrophages. However, bacterial viability was maintained, allowing the persistence of C. burnetii, which is a prerequisite for the development of chronic Q fever. This knowledge will open future research avenues on the pathogenesis of chronic Q fever. In addition, the regulation of TCA cycle metabolites by HIF1 alpha represents a previously unappreciated mechanism of host defense against intracellular pathogens.
CRIS-Team WoS Importer:2019-04-09

Listeria monocytogenes: No Spreading without NO - Bogdan, Christian (Immunity, 2012)
In infectious disease immunology, inducible nitric oxide (NO) synthase-derived NO is believed to function primarily as an antimicrobial and immunoregulatory molecule. In this issue of Immunity, Cole et al. (2012) show that NO helps the intracellular bacteria Listeria monocytogenes to spread. © 2012 Elsevier Inc.
CRIS-Team Scopus Importer:2024-02-26

Live Cell Imaging Reveals Novel Functions of Salmonella enterica SPI2-T3SS Effector Proteins in Remodeling of the Host Cell Endosomal System - Rajashekar, Roopa; Liebl, David; Chikkaballi, Deepak; Liss, Viktoria; Hensel, Michael (PLoS ONE, 2014)
Intracellular Salmonella enterica induce a massive remodeling of the endosomal system in infected host cells. One dramatic consequence of this interference is the induction of various extensive tubular aggregations of membrane vesicles, and tubules positive for late endosomal/lysosomal markers are referred to as Salmonella-induced filaments or SIF. SIF are highly dynamic in nature with extension and collapse velocities of 0.4-0.5 µm x sec-1. The induction of SIF depends on the function of the Salmonella Pathogenicity Island 2 (SPI2) encoded type III secretion system (T3SS) and a subset of effector proteins. In this study, we applied live cell imaging and electron microscopy to analyze the role of individual effector proteins in SIF morphology and dynamic properties of SIF. SIF in cells infected with sifB, sseJ, sseK1, sseK2, sseI, sseL, sspH1, sspH2, slrP, steC, gogB or pipB mutant strains showed a morphology and dynamics comparable to SIF induced by WT Salmonella. SIF were absent in cells infected with the sifA-deficient strain and live cell analyses allowed tracking of the loss of the SCV membrane of intracellular sifA Salmonella. In contrast to analyses in fixed cells, in living host cells SIF induced by sseF- or sseG-deficient strains were not discontinuous, but rather continuous and thinner in diameter. A very dramatic phenotype was observed for the pipB2-deficient strain that induced very bulky, non-dynamic aggregations of membrane vesicles. Our study underlines the requirement of the study of Salmonella-host interaction in living systems and reveals new phenotypes due to the intracellular activities of Salmonella.
EVALuna2:7668

Locally renewing resident synovial macrophages provide a protective barrier for the joint - Culemann, Stephan; Grüneboom, Anika; Nicolás-Ávila, José Ángel; Weidner, Daniela; Lämmle, Katrin Franziska; Rothe, Tobias; Quintana, Juan A.; Kirchner, Philipp; Krljanac, Branislav; Eberhardt, Martin; Ferrazzi, Fulvia; Kretzschmar, Elke; et al. (Nature, 2019)
Macrophages are considered to contribute to chronic inflammatory diseases such as rheumatoid arthritis1. However, both the exact origin and the role of macrophages in inflammatory joint disease remain unclear. Here we use fate-mapping approaches in conjunction with three-dimensional light-sheet fluorescence microscopy and single-cell RNA sequencing to perform a comprehensive spatiotemporal analysis of the composition, origin and differentiation of subsets of macrophages within healthy and inflamed joints, and study the roles of these macrophages during arthritis. We find that dynamic membrane-like structures, consisting of a distinct population of CX3CR1+ tissue-resident macrophages, form an internal immunological barrier at the synovial lining and physically seclude the joint. These barrier-forming macrophages display features that are otherwise typical of epithelial cells, and maintain their numbers through a pool of locally proliferating CX3CR1− mononuclear cells that are embedded into the synovial tissue. Unlike recruited monocyte-derived macrophages, which actively contribute to joint inflammation, these epithelial-like CX3CR1+ lining macrophages restrict the inflammatory reaction by providing a tight-junction-mediated shield for intra-articular structures. Our data reveal an unexpected functional diversification among synovial macrophages and have important implications for the general role of macrophages in health and disease.
CRIS-Team Scopus Importer:2019-08-16

Loss of the Periplasmic Chaperone Skp and Mutations in the Efflux Pump AcrAB-TolC Play a Role in Acquired Resistance to Antimicrobial Peptides in Salmonella typhimurium - Kapach, Gal; Nuri, Reut; Schmidt, Christiane; Danin, Adi; Ferrera, Shir; Savidor, Alon; Gerlach, Roman; Shai, Yechiel (Frontiers in Microbiology, 2020)
Bacterial resistance to antibiotics is a major concern worldwide, leading to an extensive search for alternative drugs. Promising candidates are antimicrobial peptides (AMPs), innate immunity molecules, shown to be highly efficient against multidrug resistant bacteria. Therefore, it is essential to study bacterial resistance mechanisms against them. For that purpose, we used experimental evolution, and isolated a Salmonella enterica serovar typhimurium-resistant line to the AMP 4DK5L7. This AMP displayed promising features including widespread activity against Gram-negative bacteria and protection from proteolytic degradation. However, the resistance that evolved in the isolated strain was particularly high. Whole genome sequencing revealed that five spontaneous mutations had evolved. Of these, three are novel in the context of acquired AMP resistance. Two mutations are related to the AcrAB-TolC multidrug efflux pump. One occurred in AcrB, the substrate-binding domain of the system, and the second in RamR, a transcriptional regulator of the system. Together, the mutations increased the minimal inhibitory concentration (MIC) by twofold toward this AMP. Moreover, the mutation in AcrB induced hypersusceptibility toward ampicillin and colistin. The last mutation occurred in Skp, a periplasmic chaperone that participates in the biogenesis of outer membrane proteins (OMPs). This mutation increased the MIC by twofold to 4DK5L7 and by fourfold to another AMP, seg5D. Proteomic analysis revealed that the mutation abolished Skp expression, reduced OMP abundance, and increased DegP levels. DegP, a protease that was reported to have an additional chaperone activity, escorts OMPs through the periplasm along with Skp, but is also associated with AMP resistance. In conclusion, our data demonstrate that both loss of Skp and manipulation of the AcrAB-TolC system are alternative strategies of AMP acquired resistance in Salmonella typhimurium and might represent a common mechanism in other Gram-negative bacteria.
CRIS-Team Scopus Importer:2020-04-14
Keywords: AcrAB-TolC; antimicrobial peptide (AMPs); bacterial resistance; efflux pump; periplasm; ramR; Skp

LOWERING THE BINDING STRENGTH OF ANTI-CD19 CAR-T CELLS CAN REDUCE TOXICITY BUT AT THE COST OF IN VIVO ANTI-TUMOR EFFICACY - Doetsch, S.; Warmuth, L.; D'Ippolito, E.; Honold, B.; Trebo, M.; Manlik, W.; Graml, F.; Stengl, A.; Schuetz, J.; Schober, Kilian; Schmidt, G.; Wanisch, A.; et al. (HUMAN GENE THERAPY, 2022)
CRIS-Team WoS Importer:2022-10-21

LPS structure and PhoQ activity are important for Salmonella Typhimurium virulence in the Galleria mellonella infection model [corrected]. - Bender, Jennifer; Wille, Thorsten; Blank, Katrin; Lange, Anna; Gerlach, Roman (PLoS ONE, 2013)
The larvae of the wax moth, Galleria mellonella, have been used experimentally to host a range of bacterial and fungal pathogens. In this study we evaluated the suitability of G. mellonella as an alternative animal model of Salmonella infection. Using a range of inoculum doses we established that the LD₅₀ of SalmonellaTyphimurium strain NCTC 12023 was 3.6 × 10³ bacteria per larva. Further, a set of isogenic mutant strains depleted of known virulence factors was tested to identify determinants essential for S. Typhimurium pathogenesis. Mutants depleted of one or both of the type III secretion systems encoded by Salmonella Pathogenicity Islands 1 and 2 showed no virulence defect. In contrast, we observed reduced pathogenic potential of a phoQ mutant indicating an important role for the PhoPQ two-component signal transduction system. Lipopolysaccharide (LPS) structure was also shown to influence Salmonella virulence in G. mellonella. A waaL(rfaL) mutant, which lacks the entire O-antigen (OAg), was virtually avirulent, while a wzz(ST)/wzz(fepE) double mutant expressing only a very short OAg was highly attenuated for virulence. Furthermore, shortly after infection both LPS mutant strains showed decreased replication when compared to the wild type in a flow cytometry-based competitive index assay. In this study we successfully established a G. mellonella model of S. Typhimurium infection. By identifying PhoQ and LPS OAg length as key determinants of virulence in the wax moth larvae we proved that there is an overlap between this and other animal model systems, thus confirming that the G. mellonella infection model is suitable for assessing aspects of Salmonella virulence function.

Macrophage-derived nitric oxide initiates T-cell diapedesis and tumor rejection - Sektioglu, Ibrahim M.; Carretero, Rafael; Bender, Noemi; Bogdan, Christian; Garbi, Natalio; Umansky, Viktor; Umansky, Ludmila; Urban, Katharina; Von Knebel-Doeberitz, Magnus; Somasundaram, Veena; Wink, David; Beckhove, Philipp; et al. (OncoImmunology, 2016)
In tumor biology, nitric oxide (NO) is generally regarded as an immunosuppressive molecule that impedes T-cell functions and activation of endothelial cells. Contrasting with this view, we here describe a critical role for NO derived from inducible nitric oxide (iNOS)-expressing tumor macrophages in T-cell infiltration and tumor rejection as shown by iNOS gene deletion, inhibition of iNOS, or NO donors. Specifically, macrophage-derived NO was found to induce on tumor vessels adhesion molecules that were required for T-cell extravasation. Experiments with human endothelial cells revealed a bimodal dose-dependent effect of NO. High doses of NO donors were indeed suppressive but lower, more physiological concentrations, induced adhesion molecules in an NFkB-dependent pathway and preferentially activated transcription of genes involved in lymphocyte diapedesis. iNOS(+) macrophages in tumors appear to generate precisely the amount of NO that promotes endothelial activation and T-cell infiltration. These results will be valuable for the development of strategies designed to overcome the paucity of T-cell infiltration into tumors that is a major obstacle in clinical cancer immunotherapy.
EVALuna2:7726

Macrophage phosphoproteome analysis reveals MINCLE-dependent and -independent mycobacterial cord factor signaling - Hansen, M.; Peltier, J.; Killy, B.; Trost, M.; Lang, Roland (EUROPEAN JOURNAL OF IMMUNOLOGY, 2019)
CRIS-Team WoS Importer:2019-10-08

Macrophage phosphoproteome analysis reveals MINCLE-dependent and-independent mycobacterial cord factor signaling - Hansen, Madlen; Peltier, Julian; Killy, Barbara; Amin, Bushra; Bodendorfer, Barbara; HäRtlova, Anetta; Uebel, Sebastian; Bosmann, Markus; Hofmann, Jörg; Büttner, Christian; Ekici, Arif Bülent; Kuttke, Mario; et al. (Molecular & Cellular Proteomics, 2019)
Immune sensing of Mycobacterium tuberculosis relies on recognition by macrophages. Mycobacterial cord factor, trehalose-6,6-dimycolate (TDM), is the most abundant cell wall glycolipid and binds to the C-type lectin receptor (CLR) MINCLE. To explore the kinase signaling linking the TDM-MINCLE interaction to gene expression, we employed quantitative phosphoproteome analysis. TDM caused upregulation of 6.7% and suppressed 3.8% of the 14,000 phospho-sites identified on 3727 proteins. MINCLE-dependent phosphorylation was observed for canonical players of CLR signaling (e.g. PLC, PKC), and was enriched for PKC and GSK3 kinase motifs. MINCLE-dependent activation of the PI3K-AKT-GSK3 pathway contributed to inflammatory gene expression and required the PI3K regulatory subunit p85. Unexpectedly, a substantial fraction of TDM-induced phosphorylation was MINCLE-independent, a finding paralleled by transcriptome data. Bioinformatics analysis of both data sets concurred in the requirement for MINCLE for innate immune response pathways and processes. In contrast, MINCLE-independent phosphorylation and transcriptome responses were linked to cell cycle regulation. Collectively, our global analyses show substantial reprogramming of macrophages by TDM and reveal a dichotomy of MINCLE-dependent and-independent signaling linked to distinct biological responses.
CRIS-Team Scopus Importer:2019-05-02

Macrophages as host, effector and immunoregulatory cells in leishmaniasis: Impact of tissue micro-environment and metabolism - Bogdan, Christian (Cytokine: X, 2020)
Leishmania are protozoan parasites that predominantly reside in myeloid cells within their mammalian hosts. Monocytes and macrophages play a central role in the pathogenesis of all forms of leishmaniasis, including cutaneous and visceral leishmaniasis. The present review will highlight the diverse roles of macrophages in leishmaniasis as initial replicative niche, antimicrobial effectors, immunoregulators and as safe hideaway for parasites persisting after clinical cure. These multiplex activities are either ascribed to defined subpopulations of macrophages (e.g., Ly6ChighCCR2+ inflammatory monocytes/monocyte-derived dendritic cells) or result from different activation statuses of tissue macrophages (e.g., macrophages carrying markers of of classical [M1] or alternative activation [M2]). The latter are shaped by immune- and stromal cell-derived cytokines (e.g., IFN-γ, IL-4, IL-10, TGF-β), micro milieu factors (e.g., hypoxia, tonicity, amino acid availability), host cell-derived enzymes, secretory products and metabolites (e.g., heme oxygenase-1, arginase 1, indoleamine 2,3-dioxygenase, NOS2/NO, NOX2/ROS, lipids) as well as by parasite products (e.g., leishmanolysin/gp63, lipophosphoglycan). Exciting avenues of current research address the transcriptional, epigenetic and translational reprogramming of macrophages in a Leishmania species- and tissue context-dependent manner.
CRIS-Team Scopus Importer:2020-12-25
Keywords: Arginase; Hypoxia; Interferon-α/β; Interferon-γ; Leishmaniasis; Macrophages; Metabolism; Nitric oxide; Phagocyte NADPH oxidase; Tonicity

Macrophages inhibit Coxiella burnetii by the ACOD1-itaconate pathway for containment of Q fever - Kohl, Lisa; Siddique, Md Nur A Alam; Bodendorfer, Barbara; Berger, Raffaela; Preikschat, Annica; Daniel, Christoph; Ölke, Martha; Liebler-Tenorio, Elisabeth; Schulze-Lührmann, Jan; Mauermeir, Michael; Yang, Kai-Ting; Hayek, Inaya; et al. (Embo Molecular Medicine, 2022)
Infection with the intracellular bacterium Coxiella (C.) burnetii can cause chronic Q fever with severe complications and limited treatment options. Here, we identify the enzyme cis-aconitate decarboxylase 1 (ACOD1 or IRG1) and its product itaconate as protective host immune pathway in Q fever. Infection of mice with C. burnetii induced expression of several anti-microbial candidate genes, including Acod1. In macrophages, Acod1 was essential for restricting C. burnetii replication, while other antimicrobial pathways were dispensable. Intratracheal or intraperitoneal infection of Acod1−/− mice caused increased C. burnetii burden, weight loss and stronger inflammatory gene expression. Exogenously added itaconate restored pathogen control in Acod1−/− mouse macrophages and blocked replication in human macrophages. In axenic cultures, itaconate directly inhibited growth of C. burnetii. Finally, treatment of infected Acod1−/− mice with itaconate efficiently reduced the tissue pathogen load. Thus, ACOD1-derived itaconate is a key factor in the macrophage-mediated defense against C. burnetii and may be exploited for novel therapeutic approaches in chronic Q fever.
CRIS-Team Scopus Importer:2022-12-16
Keywords: Cis-aconitate decarboxylase 1; Coxiella burnetii; Immune responsive gene 1; immunometabolism; itaconate

Magnetic Removal of Candida albicans Using Salivary Peptide-Functionalized SPIONs - Friedrich, Bernhard; Tietze, Rainer; Dümig, Michaela; Sover, Alexandru; Boca, Marius Andrei; Schreiber, Eveline; Band, Julia; Janko, Christina; Krappmann, Sven; Alexiou, Christoph; Lyer, Stefan (International Journal of Nanomedicine, 2023)
Purpose: Magnetic separation of microbes can be an effective tool for pathogen identification and diagnostic applications to reduce the time needed for sample preparation. After peptide functionalization of superparamagnetic iron oxide nanoparticles (SPIONs) with an appropriate interface, they can be used for the separation of sepsis-associated yeasts like Candida albicans. Due to their magnetic properties, the magnetic extraction of the particles in the presence of an external magnetic field ensures the accumulation of the targeted yeast. Materials and Methods: In this study, we used SPIONs coated with 3-aminopropyltriethoxysilane (APTES) and functionalized with a peptide originating from GP340 (SPION-APTES-Pep). For the first time, we investigate whether this system is suitable for the separation and enrichment of Candida albicans, we investigated its physicochemical properties and by thermogravimetric analysis we determined the amount of peptide on the SPIONs. Further, the toxicological profile was evaluated by recording cell cycle and DNA degradation. The separation efficiency was investigated using Candida albicans in different experimental settings, and regrowth experiments were carried out to show the use of SPION-APTES-Pep as a sample preparation method for the identification of fungal infections. Conclusion: SPION-APTES-Pep can magnetically remove more than 80% of the microorganism and with a high selective host-pathogen distinction Candida albicans from water-based media and about 55% in blood after 8 minutes processing without compromising effects on the cell cycle of human blood cells. Moreover, the separated fungal cells could be regrown without any restrictions.
CRIS-Team Scopus Importer:2023-07-07
Keywords: Candida albicans; fungal sepsis; GP340; microbiological identification; SPIONs

Management of chronic osteomyelitis of the tibia with life-threatening complications under negative pressure wound therapy and isolation of Helcococcus kunzii - Stanger, Katrin M.; Albert, Frauke; Kneser, Ulrich; Bogdan, Christian; Horch, Raymund E. (International Wound Journal, 2015)
We report the case of an 86-year-old man with severe wound infection originating from a chronic crural ulcer of the lower limb, which under negative pressure wound therapy led to excessive tissue necrosis and perforation of the anterior tibial artery. A swab taken 10 and 7 days preoperatively was positive for Helcococcus kunzii. H. kunzii has been described as a potentially pathogenic organism. The questions whether the negative pressure wound therapy itself caused the bleeding or the negative pressure wound therapy, which generates an anaerobic atmosphere, has triggered the growth and invasion of the facultative anaerobic bacterium H. kunzii and owing to the infection the artery perforated or whether the bacteria has no influence at all remain currently unanswered. After surgical debridement the signs of infection were completely eliminated, and a free musculocutaneous flap led to rapid healing of the wound. Following which H. kunzii was no longer detectable.
EVALuna2:7649

Manipulation of microvillar proteins during Salmonella enterica invasion results in brush border effacement and actin remodeling - Felipe-Lopez, Alfonso; Hansmeier, Nicole; Danzer, Claudia Agnes; Hensel, Michael (Frontiers in Cellular and Infection Microbiology, 2023)
Enterocyte invasion by the gastrointestinal pathogen Salmonella enterica is accompanied by loss of brush border and massive remodeling of the actin cytoskeleton, leading to microvilli effacement and formation of membrane ruffles. These manipulations are mediated by effector proteins translocated by the Salmonella Pathogenicity Island 1-encoded type III secretion system (SPI1-T3SS). To unravel the mechanisms of microvilli effacement and contribution of SPI1-T3SS effector proteins, the dynamics of host-pathogen interactions was analyzed using live cell imaging (LCI) of polarized epithelial cells (PEC) expressing LifeAct-GFP. PEC were infected with S. enterica wild-type and mutant strains with defined defects in SPI1-T3SS effector proteins, and pharmacological inhibition of actin assembly were applied. We identified that microvilli effacement involves two distinct mechanisms: i) F-actin depolymerization mediated by villin and ii), the consumption of cytoplasmic G-actin by formation of membrane ruffles. By analyzing the contribution of individual SPI1-T3SS effector proteins, we demonstrate that SopE dominantly triggers microvilli effacement and formation of membrane ruffles. Furthermore, SopE via Rac1 indirectly manipulates villin, which culminates in F-actin depolymerization. Collectively, these results indicate that SopE has dual functions during F-actin remodeling in PEC. While SopE-Rac1 triggers F-actin polymerization and ruffle formation, activation of PLCγ and villin by SopE depolymerizes F-actin in PEC. These results demonstrate the key role of SopE in destruction of the intestinal barrier during intestinal infection by Salmonella.
CRIS-Team Scopus Importer:2023-03-31
Keywords: brush border; cell invasion; F-actin dynamics; polarized epithelial cell; type III secretion system

Mast cells have no impact on cutaneous leishmaniasis severity and related Th2 differentiation in resistant and susceptible mice - Paul, Christoph; Wolff, Svenja; Zapf, Thea; Raifer, Hartmann; Feyerabend, Thorsten B.; Bollig, Nadine; Camara, Baerbel; Trier, Claudia; Schleicher, Ulrike; Rodewald, Hans-Reimer; Lohoff, Michael (European Journal of Immunology, 2016)
The genus leishmania comprises different protozoan parasites which are causative agents of muco-cutaneous and systemic, potentially lethal diseases. After infection with the species Leishmania major, resistant mice expand Th1 cells which stimulate macrophages for Leishmania destruction. In contrast, susceptible mice generate Th2 cells which deactivate macrophages, leading to systemic spread of the pathogens. Th-cell differentiation is determined within the first days, and Th2 cell differentiation requires IL-4, whereby the initial IL-4 source is often unknown. Mast cells are potential sources of IL-4, and hence their role in murine leishmaniasis has previously been studied in mast cell-deficient Kit mutant mice, although these mice display immunological phenotypes beyond mast cell deficiency. We therefore readdressed this question by infecting Kit-independent mast cell-deficient mice that are Th1 (C57BL/6 Cpa(Cre) ) or Th2 (BALB/c Cpa(Cre) ) prone with L. major. Using different parasite doses and intra- or subcutaneous infection routes, the results demonstrate no role of mast cells on lesion size development, parasite load, immune cell phenotypes expanding in draining lymph nodes, and cytokine production during murine cutaneous leishmaniasis. Thus, other cell types such as ILCs or T cells have to be considered as primary source of Th2-driving IL-4.
EVALuna2:7687

Mast cells link immune sensing to antigen-avoidance behaviour - Plum, Thomas; Binzberger, Rebecca; Thiele, Robin; Shang, Fuwei; Postrach, Daniel; Fung, Candice; Fortea, Marina; Stakenborg, Nathalie; Wang, Zheng; Tappe-Theodor, Anke; Poth, Tanja; MacLaren, Duncan A.A.; et al. (Nature, 2023)
The physiological functions of mast cells remain largely an enigma. In the context of barrier damage, mast cells are integrated in type 2 immunity and, together with immunoglobulin E (IgE), promote allergic diseases. Allergic symptoms may, however, facilitate expulsion of allergens, toxins and parasites and trigger future antigen avoidance1–3. Here, we show that antigen-specific avoidance behaviour in inbred mice4,5 is critically dependent on mast cells; hence, we identify the immunological sensor cell linking antigen recognition to avoidance behaviour. Avoidance prevented antigen-driven adaptive, innate and mucosal immune activation and inflammation in the stomach and small intestine. Avoidance was IgE dependent, promoted by Th2 cytokines in the immunization phase and by IgE in the execution phase. Mucosal mast cells lining the stomach and small intestine rapidly sensed antigen ingestion. We interrogated potential signalling routes between mast cells and the brain using mutant mice, pharmacological inhibition, neural activity recordings and vagotomy. Inhibition of leukotriene synthesis impaired avoidance, but overall no single pathway interruption completely abrogated avoidance, indicating complex regulation. Collectively, the stage for antigen avoidance is set when adaptive immunity equips mast cells with IgE as a telltale of past immune responses. On subsequent antigen ingestion, mast cells signal termination of antigen intake. Prevention of immunopathology-causing, continuous and futile responses against per se innocuous antigens or of repeated ingestion of toxins through mast-cell-mediated antigen-avoidance behaviour may be an important arm of immunity.
CRIS-Team Scopus Importer:2023-07-21

Mating-type factor-specific regulation of the fumagillin/pseurotin secondary metabolite supercluster in Aspergillus fumigatus - Yu, Yidong; Blachowicz, Adriana; Will, Christine; Szewczyk, Edyta; Glenn, Steven; Gensberger-Reigl, Sabrina; Nowrousian, Minou; Wang, Clay C. C.; Krappmann, Sven (Molecular Microbiology, 2018)
In the human pathogenic mold Aspergillus fumigatus, sexual identity is determined by the mating-type idiomorphs MAT1-1 and MAT1-2 residing at the MAT locus. Upon crossing of compatible partners, a heterothallic mating is executed to eventually form cleistothecia that contain recombinant ascospores. Given that the MAT1 gene products are DNA binding master regulators that govern this complex developmental process, we monitored the MAT1-driven transcriptomes of A. fumigatus by conditional overexpression of either MAT1 gene followed by RNA-seq analyses. Numerous genes related to the process of mating were found to be under transcriptional control, such as pheromone production and recognition. Substantial differences between the MAT1-1- and MAT1-2-driven transcriptomes could be detected by functional categorization of differentially expressed genes. Moreover, a significant and distinct impact on expression of genetic clusters of secondary metabolism became apparent, which could be verified on the product level. Unexpectedly, specific cross-regulation of the fumagillin/pseurotin supercluster was evident, thereby uncoupling its co-regulatory characteristic. These insights imply a tight interconnection of sexual development accompanied by ascosporogenesis with secondary metabolite production of a pathogenic fungus and impose evolutionary constraints that link these two fundamental aspects of the fungal lifestyle.
EVALuna2:36418

Measurement of TLR-induced macrophage spreading by automated image analysis: Differential role of Myd88 and MAPK in early and late responses - Wenzel, Jens; Held, Christian; Palmisano, Ralf; Teufel, S.; David, Jean Pierre; Wittenberg, Thomas; Lang, Roland (Frontiers in Physiology, 2011)
Sensing of infectious danger by toll-like receptors (TLRs) on macrophages causes not only a reprogramming of the transcriptome but also changes in the cytoskeleton important for cell spreading and motility. Since manual determination of cell contact areas from fluo-, rescence micrographs is very time-consuming and prone to bias, we have developed and tested algorithms for automated measurement of macrophage spreading. The two-step method combines identification of cells by nuclear staining with DAPI and cell surface staining of the integrin CD11b. Automated image analysis correlated very well with manual annotation in resting macrophages and early after stimulation, whereas at later time points the automated cell segmentation algorithm and manual annotation showed slightly larger variation. The method was applied to investigate the impact of genetic or pharmacological inhibition of known TLR signaling components. Deficiency in the adapter protein Myd88 strongly reduced spreading activity at the late time points, but had no impact early after LPS-stimulation. A similar effect was observed upon pharmacological inhibition of MEK1, the kinase activating the mitogen-activated protein kinases (MAPK) ERK1/2, indicating that ERK1/2 mediates Myd88-dependent macrophages spreading. In contrast, macrophages lacking the MAPK p38 were impaired in the initial spreading response but responded normally 8-24 h after stimulation. The dichotomy of p38 and ERK1/2 MAPK effects on early and late macrophage spreading raises the question which of the respective substrate proteins mediate(s) cytoskeletal remodeling and spreading. The automated measurement of cell spreading described here increases the objectivity and greatly reduces the time required for such investigations and is therefore expected to facilitate larger throughput analysis of macrophage spreading, e.g., in siRNA knockdown screens. © 2011 Wenzel, Held, Palmisano, Teufel, David, Wittenberg and Lang.

Mechanisms controlling bacterial infection in myeloid cells under hypoxic conditions - Hayek, Inaya; Schatz, Valentin; Bogdan, Christian; Jantsch, Jonathan; Lührmann, Anja (Cellular and Molecular Life Sciences, 2020)
Various factors of the tissue microenvironment such as the oxygen concentration influence the host–pathogen interaction. During the past decade, hypoxia-driven signaling via hypoxia-inducible factors (HIF) has emerged as an important factor that affects both the pathogen and the host. In this chapter, we will review the current knowledge of this complex interplay, with a particular emphasis given to the impact of hypoxia and HIF on the inflammatory and antimicrobial activity of myeloid cells, the bacterial responses to hypoxia and the containment of bacterial infections under oxygen-limited conditions. We will also summarize how low oxygen concentrations influence the metabolism of neutrophils, macrophages and dendritic cells. Finally, we will discuss the consequences of hypoxia and HIFα activation for the invading pathogen, with a focus on Pseudomonas aeruginosa, Mycobacterium tuberculosis, Coxiella burnetii, Salmonella enterica and Staphylococcus aureus. This includes a description of the mechanisms and microbial factors, which the pathogens use to sense and react to hypoxic conditions.
CRIS-Team Scopus Importer:2020-11-06
Keywords: Bacteria; Dendritic cells; HIF1α; Hypoxia; Infection; Macrophages; Metabolism; Neutrophils

Mechanisms of autoimmune liver disease - Baier, Julia; Mattner, Jochen (Discovery medicine, 2014)
The immune system of the liver is characterized by a predominant innate component. Several innate immune cell populations have been implicated in the pathogenesis of immune-mediated hepatic diseases, which are frequently associated with systemic symptoms or with co-morbidities affecting other organ systems. Thus, next to tissue-specific factors, general tolerance mechanisms are affected in devastating hepatic disorders like primary sclerosing cholangitis (PSC), autoimmune hepatitis (AIH), or primary biliary cirrhosis (PBC). The innate immune cell populations abundantly detected within the liver and endowed with potent immunomodulatory capacities include innate lymphoid cells (ILCs) and natural killer T (NKT) cells. While both ILCs and NKT cells can be activated by different cytokines and/or chemokines, NKT cells also respond to (glyco-) lipid antigens engaging their canonical, semi-invariant TCR. Once activated, ILCs and NKT cells release copious amounts of Th1, Th2, and/or Th17 cytokines that shape subsequent innate and adaptive immune responses. Those immunomodulatory features as well as the recently described antigen-presenting capacity of ILCs and/or the bi-directional functional role of NKT cells might not only underlie the pathogenic mechanisms in the respective disorders, but also provide promising targets for clinical intervention. We will discuss these novel aspects as well as the role of alarmin-like cytokines such as IL-33 in the context of ILC and NKT cell activation and the consequences for the induction and progress of hepatic tissue damage and fibrosis.
EVALuna2:7662

Mechanisms of Innate Lymphoid Cell and Natural Killer T Cell Activation during Mucosal Inflammation - Nau, David; Altmayer, Nora; Mattner, Jochen (Journal of Immunology Research, 2014)
Mucosal surfaces in the airways and the gastrointestinal tract are critical for the interactions of the host with its environment. Due to their abundance at mucosal tissue sites and their powerful immunomodulatory capacities, the role of innate lymphoid cells (ILCs) and natural killer T (NKT) cells in the maintenance of mucosal tolerance has recently moved into the focus of attention. While NKT cells as well as ILCs utilize distinct transcription factors for their development and lineage diversification, both cell populations can be further divided into three polarized subpopulations reflecting the distinction into Th1, Th2, and Th17 cells in the adaptive immune system. While bystander activation through cytokines mediates the induction of ILC and NKT cell responses, NKT cells become activated also through the engagement of their canonical T cell receptors (TCRs) by (glyco)lipid antigens (cognate recognition) presented by the atypical MHC I like molecule CD1d on antigen presenting cells (APCs). As both innate lymphocyte populations influence inflammatory responses due to the explosive release of copious amounts of different cytokines, they might represent interesting targets for clinical intervention. Thus, we will provide an outlook on pathways that might be interesting to evaluate in this context.
EVALuna2:7650

Medical Student Self-Assessment of Knowledge About Vaccinations and the Quality of Vaccination Training - Roberts, Kimberly; Streng, Andrea; Göttler, David; Hartmann, Katrin; Peter-Kern, Martina; Roggendorf, Hedwig; Bogdan, Christian; Jilg, Wolfgang; Plentz, Annelie; Hübner, Johannes; Schober, Tilmann; Liese, Johannes (Deutsches Ärzteblatt international, 2022)
CRIS-Team Scopus Importer:2022-12-02

M-EndoL: MRSA in der Versorgung am Lebensende - Untersuchung der Auswirkungen von MRSA- (oder andere multiresistente Keim-) Kolonisation oder Infektion auf Patienten am Lebensende, deren Angehörige, Teammitglieder und Einrichtungen - Ostgathe, Christoph; Lang, Frieder; Bogdan, Christian; Sieber, Cornel; Schöffski, Oliver; Stiel, Stephanie; Heckel, Maria; Tiedtke, Johanna; Sturm, Alexander; Adelhardt, Thomas (Zeitschrift für Palliativmedizin, 2014)

Meningitis and intracranial abscess due to Mycoplasma pneumoniae in a B cell-depleted patient with multiple sclerosis - Madžar, Dominik; Nickel, Florian; Rothhammer, Veit; Gölitz, Philipp; Geißdörfer, Walter; Dumke, Roger; Lang, Roland (European Journal of Clinical Microbiology & Infectious Diseases, 2024)
Mycoplasma pneumoniae, a frequent respiratory pathogen, can cause neurological disease manifestations. We here present a case of M. pneumoniae as cause of meningitis and occurrence of an intracranial abscess as a complication of mastoiditis with septic cerebral venous sinus thrombosis in a patient with multiple sclerosis on anti-CD20 therapy.
CRIS-Team Scopus Importer:2024-09-20
Keywords: Abscess; Anti-CD20 antibody; Complication; Mastoiditis; Multiple sclerosis; Mycoplasma pneumoniae; Ocrelizumab; Rituximab; Septic cerebral venous sinus thrombosis

Meningokokken-Meningitis - Esse, Jan; Träger, Johannes; Bogdan, Christian (TumorDiagnostik & Therapie, 2024)
CRIS-Team Scopus Importer:2024-05-24

Metaplastic epithelial cells: origination from stem cells and promotion of intestinal inflammation - Holland, Tim; Mattner, Jochen (Signal Transduction and Targeted Therapy, 2025)
CRIS-Team Scopus Importer:2025-03-21

Microbiologic diagnostics and pathogen spectrum in infective endocarditis of surgically treated patients: a five-year, retrospective, monocentric study - Ziegler, Renate; Arnold, Hendrik; Bertram, Ralph; Geißdörfer, Walter; Pauschinger, Matthias; Fischlein, Theodor; Pollari, Francesco; Steinmann, Joerg (Infection, 2023)
PurposeThe spectrum of causative organisms in infective endocarditis (IE) has changed significantly in the last decades. Reliable pathogen detection is crucial for appropriate antimicrobial therapy for IE. The aim of the study was to evaluate the diagnostic value of microbiological methods for detecting the causative microorganism of IE and to analyze the spectrum of pathogens.MethodsA total of 224 cases (211 unique patients, some with multiple surgeries) were included into this retrospective study. Patients were diagnosed with IE according to the modified Duke criteria from January 2016 to July 2021 and underwent heart valve surgery in a tertiary hospital. Pathogen detection was performed by blood culture, microbiological culture and 16S rDNA PCR of explanted heart valve material.ResultsA causative pathogen of IE was detected in 95.5% (n = 214) of cases. Blood cultures were positive in 83.3%, while a pathogen in the examined heart valve samples was identified in 32.6% by culture and in 88.2% by 16S rDNA PCR. A microorganism was identified by 16S rDNA PCR in 61.1% of blood culture negative cases but only in 19.4% by heart valve culture. The most common pathogens were Staphylococcus aureus (27%), viridans group streptococci (20%), enterococci (19%) and coagulase-negative staphylococci (CoNS 8%). Cutibacterium acnes (7%) was detected in prosthetic valve IE cases only.ConclusionBlood culture as a comparatively non-invasive and straightforward technique remains an important and reliable method for initial detection of the causative organism in IE. Diagnostic stewardship programs should broadly emphasize proper collection of blood cultures, particularly sampling prior to any antibiotic treatment. Additionally, molecular testing using 16S rDNA tissue PCR can be used with culture techniques to increase the diagnostic yield, especially in the case of a negative blood culture.
CRIS-Team WoS Importer:2023-04-28

Mild hyperthermia enhances human monocyte-derived dendritic cell functions and offers potential for applications in vaccination strategies - Knippertz, Ilka; Stein, Marcello F.; Dörrie, Jan; Schaft, Niels; Mueller, Ina; Deinzer, Anja; Steinkasserer, Alexander; Nettelbeck, Dirk. M. (International Journal of Hyperthermia, 2011)
Dendritic cell (DC)-based immunotherapy has been shown to be a promising strategy for anti-cancer therapy. Nevertheless, only a low overall clinical response rate has been observed in vaccinated patients with advanced cancer and therefore methods to improve DC immuno-stimulatory functions are currently under intense investigation. In this respect, we exposed human monocyte-derived DCs to a physiological temperature stress of 40°C for up to 24 h followed by analysis for (i) expression of different heat shock proteins, (ii) survival, (iii) cell surface maturation markers, (iv) cytokine secretion, and (v) migratory capacity. Furthermore, we examined the ability of heat-shocked DCs to prime nave CD8 + T cells after loading with MelanA peptide, by transfection with MelanA RNA, or by transduction with MelanA by an adenovirus vector. The results clearly indicate that in comparison to control DCs, which remained at 37°C, heat-treated cells revealed no differences concerning the survival rate or their migratory capacity. However, DCs exposed to thermal stress showed a time-dependent enhanced expression of the immune-chaperone heat shock protein 70A and both an up-regulation of co-stimulatory molecules such as CD80, CD83, and CD86 and of the inflammatory cytokine TNF-α. Moreover, these cells had a markedly improved capacity to prime autologous nave CD8 + T cells in vitro in an antigen-specific manner, independent of the method of antigen-loading. Thus, our strategy of heat treatment of DCs offers a promising means to improve DC functions during immune activation which, as a physical method, facilitates straight-forward applications in clinical DC vaccination protocols. © 2011 Informa UK Ltd All rights reserved: reproduction in whole or part not permitted.
CRIS-Team Scopus Importer:2021-10-01
Keywords: Cytotoxic T lymphocytes; Dendritic cells; Hsp70; Hyperthermia; Immunotherapy

Mincle-mediated anti-inflammatory IL-10 response counter-regulates IL-12 in vitro - Patin, Emmanuel C.; Willcocks, Sam; Orr, Selinda; Ward, Theresa H.; Lang, Roland; Schaible, Ulrich E. (Innate Immunity, 2016)
The role of macrophage-inducible C-type lectin (Mincle) in anti-inflammatory responses has not yet been fully characterized. Herein, we show that engagement of Mincle by trehalose-dimycolate or mycobacteria promotes IL-10 production in macrophages, which causes down-regulation of IL-12p40 secretion. Thus, Mincle mediates both pro- as well as anti-inflammatory responses.
EVALuna2:7704

Modulation of host cell apoptotic pathways by intracellular pathogens - Friedrich, Anja; Pechstein, Julian; Berens, Christian; Lührmann, Anja (Current Opinion in Microbiology, 2017)
Nearly all steps of the host cell apoptotic cascade can be subverted by intracellular microorganisms. Some pathogens modulate early steps and interfere with sensing of extracellular signals, cellular stress or signal transduction; others target Bcl-2 proteins, caspases, or inhibitor of apoptosis proteins (IAPs). In many cases the exact molecular mechanisms leading to interference with the host cell apoptotic cascade are still unknown. However, there are some examples where bacterial factors that modulate host cell death have been identified. In this review we will summarize recent findings on how intracellular pathogens or their secreted proteins alter the intrinsic and/or extrinsic host cell apoptotic pathways.
EVALuna2:7732

Modulation of host cell metabolism by T4SS-encoding intracellular pathogens - Hayek, Inaya; Berens, Christian; Lührmann, Anja (Current Opinion in Microbiology, 2019)
Intracellular bacterial pathogens intimately interact with the infected host cell to prevent elimination and to ensure survival. One group of intracellular pathogens, including Coxiella burnetii, Legionella pneumophila, Brucella spp., Anaplasma phagocytophilum, and Ehrlichia chaffeensis, utilizes a type IV secretion system (T4SS) that injects effectors to modulate host cell signalling, vesicular trafficking, autophagy, cell death and transcription to ensure survival [1]. So far, little emphasis has been directed towards understanding how these bacteria manipulate host cell metabolism. This manipulation is not only important for gaining access to nutrients, but also for regulating specific virulence programs [2,3]. Here, we will summarize recent progress made in characterizing the manipulation of host cell metabolism by C. burnetii and other intracellular pathogens utilizing a T4SS.
CRIS-Team Scopus Importer:2019-06-25

Modulation of the humoral immune response by constitutively active STAT6 expression in murine B cells - Haase, Paul; Mokada Gopal, Lavanya; Radtke, Daniel; Vöhringer, David (European Journal of Immunology, 2019)
The transcription factor STAT6 regulates gene expression in response to IL-4 and IL-13. To further investigate how activated STAT6 modulates B cells development and function in vivo, we characterized mice that express a constitutively active version specifically in B cells. CD19Cre_STAT6vt mice show spontaneous phosphorylation and nuclear translocation of STAT6 in B cells. About 80 genes were more than twofold up- or downregulated in splenic B cells from CD19Cre_STAT6vt as compared to control mice. B cell development, tissue localization, and populations of follicular and marginal zone B cells, B1 B cells, GC B cells, and plasma cells (PCs) appeared to be normal. However, the number of IgE(+) and IgG1(+) GC B cells and PCs as well as serum IgE and IgG1 levels were increased in CD19Cre_STAT6vt mice. Infection with Lymphocytic choriomeningitis virus associated with high levels of TNF and IFN-gamma did not prevent the development of a significantly increased IgE and IgG1 response against the virus in CD19Cre_STAT6vt mice. These results suggest that prolonged STAT6 activation during chronic allergic inflammation may result in IgE responses during subsequent viral or bacterial infection that could further stimulate mast cell activation even in the absence of the initial allergic response.
CRIS-Team WoS Importer:2019-12-27

Molecular Assessment of Staphylococcus Aureus Strains in STAT3 Hyper-IgE Syndrome Patients - Schwierzeck, Vera; Effner, Renate; Abel, Felicitas; Reiger, Matthias; Notheis, Gundula; Held, Jürgen; Simon, Valeska; Dintner, Sebastian; Hoffmann, Reinhard; Hagl, Beate; Huebner, Johannes; Mellmann, Alexander; et al. (Journal of Clinical Immunology, 2022)
Hyper-IgE syndromes (HIES) are a group of inborn errors of immunity (IEI) caused by monogenic defects such as in the gene STAT3 (STAT3-HIES). Patients suffering from HIES show an increased susceptibility to Staphylococcus aureus (S. aureus) including skin abscesses and pulmonary infections. To assess if the underlying immune defect of STAT3-HIES patients influences the resistance patterns, pathogenicity factors or strain types of S. aureus. We characterized eleven S. aureus strains isolated from STAT3-HIES patients (n = 4) by whole genome sequencing (WGS) to determine presence of resistance and virulence genes. Additionally, we used multi-locus sequence typing (MLST) and protein A (spa) typing to classify these isolates. Bacterial isolates collected from this cohort of STAT3-HIES patients were identified as common spa types in Germany. Only one of the isolates was classified as methicillin-resistant S. aureus (MRSA). For one STAT3 patient WGS illustrated that infection and colonization occurred with different S. aureus isolates rather than one particular clone. The identified S. aureus carriage profile on a molecular level suggests that S. aureus strain type in STAT3-HIES patients is determined by local epidemiology rather than the underlying immune defect highlighting the importance of microbiological assessment prior to antibiotic treatment.
CRIS-Team WoS Importer:2022-06-17

Molecular diagnosis of polymicrobial brain abscesses with 16S-rDNA-based next-generation sequencing - Stebner, Alexander; Enßer, Armin; Geißdörfer, Walter; Bozhkov, Yavor; Lang, Roland (Clinical Microbiology and Infection, 2020)
Objectives: Brain abscesses lead to high mortality despite antibiotic and surgical treatment. Identification of causative bacteria is important to guide antibiotic therapy, but culture-based methods and molecular diagnostics by Sanger sequencing of 16S PCR products are hampered by antibiotic treatment and the often polymicrobial nature of brain abscesses. We have applied 16S-rRNA-based next-generation sequencing (NGS) for metagenomic analysis of intracranial abscess (brain and epidural) and meningitis samples. Methods: Seventy-nine samples from 54 patients with intracranial abscesses or meningitis were included. DNA was subjected to 16S PCR. Amplicons were analysed with the Illumina MiSeq system, sequence reads were blasted versus the NCBI 16S bacterial database and analysed using MEGAN software. Results were compared to those of gram-staining, culture and Sanger sequencing. Results: The NGS workflow was successful for 51 intracranial abscesses (46 brain and five epidural) and nine meningitis samples. Inclusion of (mono)bacterial meningitis samples allowed us to establish a cut-off criterion for the exclusion of contaminating sequences. In total 86 bacterial taxa were identified in brain abscesses by NGS, with Streptococcus intermedius and Fusobacterium nucleatum as most prevalent species; Propionibacterium and Staphylococcus spp. were associated with epidural abscesses. NGS identified two or more bacterial taxa in 31/51 intracranial abscesses, revealing the polymicrobial nature of these infections and allowing the discrimination of up to 16 bacterial taxa per sample. Conclusion: These results extend earlier studies showing that NGS methods expand the spectrum of bacteria detected in brain abscesses and demonstrate that the MiSeq platform is suitable for metagenomic diagnostics of this severe infection.
CRIS-Team Scopus Importer:2020-04-28
Keywords: 16S rDNA; Brain abscess; Metagenome; Next-generation sequencing; Polymicrobial infection

Molecular diagnosis of skin infections using paraffin-embedded tissue - review and interdisciplinary consensus - Sunderkoetter, Cord; Becker, Karsten; Kutzner, Heinz; Meyer, Thomas; Bloedorn-Schlicht, Norbert; Reischl, Udo; Nenoff, Pietro; Geissdoerfer, Walter; Graeser, Yvonne; Herrmann, Mathias; Kuehn, Joachim; Bogdan, Christian (Journal der Deutschen Dermatologischen Gesellschaft, 2018)
Nucleic acid amplification techniques (NATs), such as PCR, are highly sensitive and specific methods that have become valuable supplements to culture and serology in the diagnosis of infectious disorders. However, especially when using formalin-fixed and paraffin-embedded tissue, these techniques are associated with both false-negative and false-positive results, a pitfall that is frequently misjudged. Representatives of the German Society of Hygiene and Microbiology (DGHM) and the German Society of Dermatology (DDG) therefore set out to develop a consensus - in the form of a review article - on the appropriate indications for NATs using paraffin-embedded tissue, its contraindications, and the key points to be considered in the pre- and post-analytical phase. Given that fresh, naive tissue is preferably to be used in the workup of a suspected infection, PCR analysis on paraffin sections represents an exception. The latter may be considered if an infection is suspected at a later point in time and fresh tissue has not been preserved or can no longer be obtained. Potential indications include confirmation of histologically suspected infections with Leishmania spp., Bartonella spp., Rickettsia spp., or in case of ecthyma contagiosum. Infections with, for example, mycobacteria or RNA viruses, on the other hand, are not considered useful indications for NATs using paraffin sections. In order to avoid misinterpretation of test results, it is essential that laboratory reports on NATs using paraffin-embedded tissue contain information on the indication/diagnostic circumstances, the required and chosen pre-analytical steps, the limitations of the method, and on diagnostic alternatives.
EVALuna2:33303

Molecular typing and in vitro resistance of Cryptococcus neoformans clinical isolates obtained in Germany between 2011 and 2017 - Selb, Regina; Fuchs, Vidmante; Graf, Barbara; Hamprecht, Axel; Hogardt, Michael; Sedlacek, Ludwig; Schwarz, R.; Idelevich, Evgeny A.; Becker, Sören L.; Held, Jürgen; Küpper-Tetzel, Claus P.; McCormick-Smith, Ilka; et al. (International Journal of Medical Microbiology, 2019)
Cryptococcosis is a fungal infection of the central nervous system predominantly caused by Cryptococcus neoformans in immunocompromised patients. In several countries worldwide, up to 50% of isolates show in vitro resistance to clinically used antifungals including fluconazole. No prospective data on susceptibility to antifungal drugs are available for Germany. In this study, we characterised all C. neoformans isolates collected from individual patients’ samples at the German reference laboratory for cryptococcosis 2011 and 2017 (n = 133) by multi-locus sequence typing and phenotypic drug susceptibility testing. We identified serotype A/genotype VNI isolates belonging to clonal complexes previously described from Europe, Africa, Asia and South America as the most prevalent agents of cryptococcosis in Germany. Overall, we observed minimal inhibitory concentrations (MICs) above the epidemiological cut-offs (ECVs) in 1.6% of isolates regarding fluconazole and 2.3% of isolates regarding 5-flucytosine. Here, two C. neoformans var. grubii isolates displayed decreased drug susceptibility to fluconazole, one of them additionally to 5-flucytosine. We also found 5-flucytosine MICs above the ECV for two C. neoformans var. neoformans isolates. We identified a novel mutation in the ERG11 gene which might be associated with the elevated fluconazole MIC in one of the isolates. The clinical importance of the detected in vitro resistance is documented by patient histories showing relapsed infection or primary fatal disease. Of note, sertraline demonstrated antifungal activity comparable to previous reports. Systematic collection of susceptibility data in combination with molecular typing of C. neoformans is important to comprehensively assess the spread of isolates and to understand their drug resistance patterns.
CRIS-Team Scopus Importer:2019-08-30
Keywords: Cryptococcosis; Cryptococcus neoformans; Fluconazole; Flucytosine; Fungal drug resistance; MLST

Monocyte-Derived signals activate human natural Killer cells in response to Leishmania Parasites - Messlinger, Helena; Sebald, Heidi; Heger, Lukas; Dudziak, Diana; Bogdan, Christian; Schleicher, Ulrike (Frontiers in Immunology, 2018)
Activated natural killer (NK) cells release interferon (IFN)-gamma, which is crucial for the control of intracellular pathogens such as Leishmania. In contrast to experimental murine leishmaniasis, the human NK cell response to Leishmania is still poorly characterized. Here, we investigated the interaction of human blood NK cells with promastigotes of different Leishmania species (Leishmania major, Leishmania mexicana, Leishmania infantum, and Leishmania donovani). When peripheral blood mononuclear cells or purified NK cells and monocytes (all derived from healthy blood donors from Germany without a history of leishmaniasis) were exposed to promastigotes, NK cells showed increased surface expression of the activation marker CD69. The extent of this effect varied depending on the Leishmania species; differences between dermotropic and viscerotropic L. infantum strains were not observed. Upregulation of CD69 required direct contact between monocytes and Leishmania and was partly inhibitable by anti-interleukin (IL)-18. Unexpectedly, IL-18 was undetectable in most of the supernatants (SNs) of monocyte/parasite cocultures. Confocal fluorescence microscopy of non-permeabilized cells revealed that Leishmania-infected monocytes trans-presented IL-18 to NK cells. Native, but not heat-treated SNs of monocyte/Leishmania cocultures also induced CD69 on NK cells, indicating the involvement of a soluble heat-labile factor other than IL-18. A role for the NK cell-activating cytokines IL-1 beta, IL-2, IL-12, IL-15, IL-21, and IFN-alpha/beta was excluded. The increase of CD69 was not paralleled by NK cell IFN-gamma production or enhanced cytotoxicity. However, prior exposure of NK cells to Leishmania parasites synergistically increased their IFN-gamma release in response to IL-12, which was dependent on endogenous IL-18. CD1c(+) dendritic cells were identified as possible source of Leishmania-induced IL-12. Finally, we observed that direct contact between Leishmania and NK cells reduced the expression of CD56 mRNA and protein on NK cells. We conclude that Leishmania activate NK cells via trans-presentation of IL-18 by monocytes and by a monocyte-derived soluble factor. IL-12 is needed to elicit the IFN-gamma-response of NK cells, which is likely to be an important component of the innate control of the parasite.
EVALuna2:33305

Monocytes Elicit a Neutrophil-Independent Th1/Th17 Response Upon Immunization With a Mincle-Dependent Glycolipid Adjuvant - Desel, Christiane; Murray, Peter J.; Lehmann, Christian; Heger, Lukas; Christensen, Dennis; Andersen, Peter; Mack, Matthias; Dudziak, Diana; Lang, Roland (Frontiers in Immunology, 2022)
Successful subunit vaccination with recombinant proteins requires adjuvants. The glycolipid trehalose-dibehenate (TDB), a synthetic analog of the mycobacterial cord factor, potently induces Th1 and Th17 immune responses and is a candidate adjuvant for human immunization. TDB binds to the C-type lectin receptor Mincle and triggers Syk-Card9-dependent APC activation. In addition, interleukin (IL)-1 receptor/MyD88-dependent signaling is required for TDB adjuvanticity. The role of different innate immune cell types in adjuvant-stimulated Th1/Th17 responses is not well characterized. We investigated cell recruitment to the site of injection (SOI) and to the draining lymph nodes (dLNs) after immunization with the TDB containing adjuvant CAF01 in a protein-based vaccine. Recruitment of monocytes and neutrophils to the SOI and the dramatic increase in lymph node cellularity was partially dependent on both Mincle and MyD88. Despite their large numbers at the SOI, neutrophils were dispensable for the induction of Th1/Th17 responses. In contrast, CCR2-dependent monocyte recruitment was essential for the induction of Th1/Th17 cells. Transport of adjuvant to the dLN did not require Mincle, MyD88, or CCR2. Together, adjuvanticity conferred by monocytes can be separated at the cellular level from potential tissue damage by neutrophils.
CRIS-Team WoS Importer:2022-06-03

Mouth-nose masks impair the visual field of healthy eyes - Weber, Albert; Hohberger, Bettina; Bergua, Antonio (PLoS ONE, 2021)
Background Mouth-nose masks have been requested to prevent the transmission of severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2). The aim of the present study was to investigate, if wearing a mouth-nose mask impairs the visual field function in normals. Methods Thirty eyes of 30 subjects were recruited for the present study. White-on-white perimetry (OCTOPUS 900; 90o) was done and sensitivity was analysed in 14 defined test points (P1-P14, inferior visual field) under 3 different test conditions while the subjects were wearing a mouth-nose mask: (I) 1.5 cm under the lower eyelid, nose clip not used (position1.5cm_no_clip); (II) 1.5 cm under the lower eyelid, nose clip correctly positioned (position1.5cm_with_clip); (III) 0.5 cm under the lower eyelid, nose clip correctly positioned (position0.5cm_with_clip). All data were compared to sensitivity without wearing a mouth-nose mask (reference). Mean Δ was calculated, being the difference between the results of each test condition and reference, respectively. Results Sensitivity was significantly different between position1.5cm_no_clip and reference at 10 test points (p<0.05). Sensitivity at test point P7 was significantly different between position1.5cm_with_clip and position0.5cm_with_clip compared to reference (p<0.001), respectively. Mean Δ increased while wearing a mask at P7: position1.5cm_with_clip (-8.3 dB ± 7.3 dB) < position0.5cm_with_clip (-11.3 dB ± 9.5 dB) < position1.5cm_no_clip (-20.1 dB ± 7.6 dB). Conclusion Visual field function was observed to be significantly impaired in the inferior-nasal sector while persons were wearing a mouth-nose mask, especially when the nose clip was not correctly used.
CRIS-Team Scopus Importer:2021-05-28

Mucocutaneous Leishmaniasis due to Leishmania infantum Infection - Linse, Kai Philipp; Bogdan, Christian; Haenssle, Holger A.; Toberer, Ferdinand (Acta Dermato-Venereologica, 2022)
CRIS-Team Scopus Importer:2022-08-05

MUCOSAL IMMUNOLOGY. The microbiota regulates type 2 immunity through ROR?t? T cells - Ohnmacht, Caspar; Park, Joo-Hong; Cording, Sascha; Wing, James B.; Atarashi, Koji; Obata, Yuuki; Gaboriau-Routhiau, Valerie; Marques, Rute; Dulauroy, Sophie; Fedoseeva, Maria; Busslinger, Meinrad; Cerf-Bensussan, Nadine; et al. (Science, 2015)
Changes to the symbiotic microbiota early in life, or the absence of it, can lead to exacerbated type 2 immunity and allergic inflammations. Although it is unclear how the microbiota regulates type 2 immunity, it is a strong inducer of proinflammatory T helper 17 (T(H)17) cells and regulatory T cells (T(regs)) in the intestine. Here, we report that microbiota-induced T(regs) express the nuclear hormone receptor ROR?t and differentiate along a pathway that also leads to T(H)17 cells. In the absence of ROR?t(+) T(regs), T(H)2-driven defense against helminths is more efficient, whereas T(H)2-associated pathology is exacerbated. Thus, the microbiota regulates type 2 responses through the induction of type 3 ROR?t(+) T(regs) and T(H)17 cells and acts as a key factor in balancing immune responses at mucosal surfaces.
EVALuna2:25870

Mucosal mast cells are indispensable for the timely termination of Strongyloides ratti infection - Reitz, M.; Brunn, M-L; Rodewald, H-R; Feyerabend, T. B.; Roers, A.; Dudeck, A.; Vöhringer, David; Joesson, F.; Kuel, A. A.; Breloer, Minka (Mucosal Immunology, 2016)
Mast cells and basophils are innate immune cells with overlapping functions that contribute to anti-helminth immunity. Mast cell function during helminth infection was previously studied using mast cell-deficient Kit-mutant mice that display additional mast cell-unrelated immune deficiencies. Here, we use mice that lack basophils or mucosal and connective tissue mast cells in a Kit-independent manner to re-evaluate the impact of each cell type during helminth infection. Neither mast cells nor basophils participated in the immune response to tissue-migrating Strongyloides ratti third-stage larvae, but both cell types contributed to the early expulsion of parasitic adults from the intestine. The termination of S. ratti infection required the presence of mucosal mast cells: Cpa3(Cre) mice, which lack mucosal and connective tissue mast cells, remained infected for more than 150 days. Mcpt5(Cre) R-DTA mice, which lack connective tissue mast cells only, and basophil-deficient Mcpt8(Cre) mice terminated the infection after 1 month with wild-type kinetics despite their initial increase in intestinal parasite burden. Because Cpa3(Cre) mice showed intact Th2 polarization and efficiently developed protective immunity after vaccination, we hypothesize that mucosal mast cells are non-redundant terminal effector cells in the intestinal epithelium that execute anti-helminth immunity but do not orchestrate it.Mucosal Immunology advance online publication, 6 July 2016; doi:10.1038/mi.2016.56.
EVALuna2:25879

Multidrug-resistant bacterial microorganisms (MDRO) in end-of-life care: development of recommendations for hospitalized patients using a mixed-methods approach - Heckel, Maria; Stiel, Stephanie; Herbst, Franziska A.; Tiedtke, Johanna; Sturm, Alexander; Adelhardt, Thomas; Bogdan, Christian; Sieber, Cornel; Schöffski, Oliver; Lang, Frieder; Ostgathe, Christoph (Supportive Care in Cancer, 2018)
Purpose Palliative care professionals are frequently confronted with patients colonized or infected with MDRO. One major challenge is how to balance necessary isolation measures and social inclusion as one of the main principles of palliative and end-of-life care. To date, MDRO-specific policies and protocols vary widely between institutions. Aim: provide empirical recommendations on how to deal with hospitalized MDRO patients in end-of-life care.Methods Recommendations were developed based on (i) initial results of face-to-face interviews and focus groups, (ii) impartial experts' comments and consensus on the draft via online survey and (iii) a face-to-face meeting with consortium members to finalize recommendations. Findings of 158 interviews and six focus groups (39 participants) with patients, family caregivers, staff members and institutional stakeholders contributed to the recommendations. The assessments of 17 experts were considered.Results In total, 21 recommendations were approved. The recommended strategy in dealing with MDRO at the end of life allows case-based application of protection and isolation measures. MDRO diagnostics and therapy involve screening at admission. The recommendations suggest consideration of required accommodation facilities, provided material as well as staff and time resources. The recommendations further highlight the importance of providing for strategies enabling the patient's social inclusion and provision of verbal and written information about MDRO for patients and family caregivers, transparent medical documentation, and staff member training.Conclusion The recommendations summarize the perspectives of individuals and groups affected by MDRO at the end of life and provide practical guidance for clinical routine. Further dissemination and implementation requirements are discussed and should contain the evaluation of the knowledge, views, worries, and anxieties of the target groups.
Keywords: Palliative care; Terminal care; Drug resistance; Multiple; Practice guideline; Methicillin-resistant Staphylococcus aureus; Empirical research

Multilocus Sequence Analysis of Clinical "Candidatus Neoehrlichia mikurensis" Strains from Europe - Grankvist, Anna; Moore, Edward R. B.; Stadler, Liselott Svensson; Pekova, Sona; Bogdan, Christian; Geißdörfer, Walter; Grip-Linden, Jenny; Brandstrom, Kenny; Marsal, Jan; Andreasson, Kristofer; Lewerin, Catharina; Welinder-Olsson, Christina; et al. (Journal of Clinical Microbiology, 2015)
"Candidatus Neoehrlichia mikurensis" is the tick-borne agent of neoehrlichiosis, an infectious disease that primarily affects immunocompromised patients. So far, the genetic variability of "Ca. Neoehrlichia" has been studied only by comparing 16S rRNA genes and groEL operon sequences. We describe the development and use of a multilocus sequence analysis (MLSA) protocol to characterize the genetic diversity of clinical "Ca. Neoehrlichia" strains in Europe and their relatedness to other species within the Anaplasmataceae family. Six genes were selected: ftsZ, clpB, gatB, lipA, groEL, and 16S rRNA. Each MLSA locus was amplified by real-time PCR, and the PCR products were sequenced. Phylogenetic trees of MLSA locus relatedness were constructed from aligned sequences. Blood samples from 12 patients with confirmed "Ca. Neoehrlichia" infection from Sweden (n = 9), the Czech Republic (n = 2), and Germany (n = 1) were analyzed with the MLSA protocol. Three of the Swedish strains exhibited identical lipA sequences, while the lipA sequences of the strains from the other nine patients were identical to each other. One of the Czech strains had one differing nucleotide in the clpB sequence from the sequences of the other 11 strains. All 12 strains had identical sequences for the genes 16S rRNA, ftsZ, gatB, and groEL. According to the MLSA, among the Anaplasmataceae, "Ca. Neoehrlichia" is most closely related to Ehrlichia ruminantium, less so to Anaplasma phagocytophilum, and least to Wolbachia endosymbionts. To conclude, three sequence types of infectious "Ca. Neoehrlichia" were identified: one in the west of Sweden, one in the Czech Republic, and one spread throughout Europe.
EVALuna2:7679

Murine eosinophil development and allergic lung eosinophilia are largely dependent on the signaling adaptor GRB2 - Willebrand, Ralf; Dietschmann, Axel; Nitschke, Lars; Krappmann, Sven; Vöhringer, David (European Journal of Immunology, 2018)
Eosinophils are innate effector cells associated with allergic inflammation. Their development and survival is largely dependent on IL-5 and the common beta chain (βc ) of the IL-5 receptor that serves as docking site for several proteins that mediate down-stream signaling cascades including JAK/STAT, PI3 kinase, NFκB, and RAS-MAP kinase pathways. The relative contribution of these signaling pathways for eosinophil development and homeostasis in vivo are poorly understood. Here, we investigated the role of GRB2, an adaptor protein that binds to βc and other proteins and elicits the RAS-MAP kinase pathway. By using GRB2 inhibitors and inducible deletion of the Grb2 gene in mouse eosinophils we demonstrate that GRB2 plays a critical role for development of eosinophils from bone marrow precursors. Furthermore, Aspergillus fumigatus-induced allergic lung eosinophilia was significantly reduced in mice with induced genetic deletion of Grb2. Our results indicate that GRB2 is important for eosinophil development in steady-state conditions and during allergic inflammation. Based on these findings pharmacologic GRB2 inhibitors may have the potential to dampen tissue eosinophilia in various eosinophil-associated diseases.
EVALuna2:36387

Mutant characterization and in vivo conditional repression identify aromatic amino acid biosynthesis to be essential for Aspergillus fumigatus virulence - Sasse, Anna; Hamer, Stefanie N.; Amich, Jorge; Binder, Jasmin; Krappmann, Sven (Virulence, 2016)
Pathogenicity of the saprobe Aspergillus fumigatus strictly depends on nutrient acquisition during infection, as fungal growth determines colonisation and invasion of a susceptible host. Primary metabolism has to be considered as a valid target for antimycotic therapy, based on the fact that several fungal anabolic pathways are not conserved in higher eukaryotes. To test whether fungal proliferation during invasive aspergillosis relies on endogenous biosynthesis of aromatic amino acids, defined auxotrophic mutants of A. fumigatus were generated and assessed for their infectious capacities in neutropenic mice and found to be strongly attenuated in virulence. Moreover, essentiality of the complete biosynthetic pathway could be demonstrated, corroborated by conditional gene expression in infected animals and inhibitor studies. This brief report not only validates the aromatic amino acid biosynthesis pathway of A. fumigatus to be a promising antifungal target but furthermore demonstrates feasibility of conditional gene expression in a murine infection model of aspergillosis.
EVALuna2:7691

Mycobacterial Cord Factor Reprograms the Macrophage Response to IFN-γ towards Enhanced Inflammation yet Impaired Antigen Presentation and Expression of GBP1 - Huber, Alexandra; Killy, Barbara; Grummel, Nadine; Bodendorfer, Barbara; Paul, Sushmita; Wiesmann, Veit; Naschberger, Elisabeth; Zimmer, Jana; Wirtz, Stefan; Schleicher, Ulrike; Vera, Julio; Ekici, Arif Bülent; et al. (Journal of Immunology, 2020)
Mycobacteria survive in macrophages despite triggering pattern recognition receptors and T cell-derived IFN-γ production. Mycobacterial cord factor trehalose-6,6-dimycolate (TDM) binds the C-type lectin receptor MINCLE and induces inflammatory gene expression. However, the impact of TDM on IFN-γ-induced macrophage activation is not known. In this study, we have investigated the cross-regulation of the mouse macrophage transcriptome by IFN-γ and by TDM or its synthetic analogue trehalose-6,6-dibehenate (TDB). As expected, IFN-γ induced genes involved in Ag presentation and antimicrobial defense. Transcriptional programs induced by TDM and TDB were highly similar but clearly distinct from the response to IFN-γ. The glycolipids enhanced expression of a subset of IFN-γ-induced genes associated with inflammation. In contrast, TDM/TDB exerted delayed inhibition of IFN-γ-induced genes, including pattern recognition receptors, MHC class II genes, and IFN-γ-induced GTPases, with antimicrobial function. TDM downregulated MHC class II cell surface expression and impaired T cell activation by peptide-pulsed macrophages. Inhibition of the IFN-γ-induced GTPase GBP1 occurred at the level of transcription by a partially MINCLE-dependent mechanism that may target IRF1 activity. Although activation of STAT1 was unaltered, deletion of Socs1 relieved inhibition of GBP1 expression by TDM. Nonnuclear Socs1 was sufficient for inhibition, suggesting a noncanonical, cytoplasmic mechanism. Taken together, unbiased analysis of transcriptional reprogramming revealed a significant degree of negative regulation of IFN-γ-induced Ag presentation and antimicrobial gene expression by the mycobacterial cord factor that may contribute to mycobacterial persistence.
CRIS-Team Scopus Importer:2020-09-18

Myd88-deficiency impairs clearance of Coxiella burnetii Nine Mile Phase II: a new mouse model of Q-fever resolution and chronicity - Kohl, Lisa (EUROPEAN JOURNAL OF IMMUNOLOGY, 2019)
CRIS-Team WoS Importer:2019-10-08

MyD88 Is Required for Efficient Control of Coxiella burnetii Infection and Dissemination - Kohl, Lisa; Hayek, Inaya; Daniel, Christoph; Schulze-Luehrmann, Jan; Bodendorfer, Barbara; Lührmann, Anja; Lang, Roland (Frontiers in Immunology, 2019)
The intracellular pathogen Coxiella (C.) burnetii causes Q fever, a usually self-limiting respiratory infection that becomes chronic and severe in some patients. Innate immune recognition of C. burnetii and its role in the decision between resolution and chronicity is not understood well. However, TLR2 is important for the response to C. burnetii in mice, and genetic polymorphisms in Myd88 have been associated with chronic Q fever in humans. Here, we have employed MyD88-deficient mice in infection models with the attenuated C. burnetii Nine Mile phase II strain (NMII). Myd88(-/-) macrophages failed to restrict the growth of NMII in vitro, and to upregulate production of the cytokines TNF, IL-6, and IL-10. Following intraperitoneal infection, NMII bacterial burden was significantly higher on day 5 and 20 in organs of Myd88(-/-) mice. After infection via the natural route by intratracheal injection, a higher bacterial load in the lung and increased dissemination of NMII to other organs was observed in MyD88-deficient mice. While wild-type mice essentially cleared NMII on day 27 after intratracheal infection, it was still readily detectable on day 42 in multiple organs in the absence of MyD88. Despite the elevated bacterial load, Myd88(-/-) mice had less granulomatous inflammation and expressed significantly lower levels of chemoattractants, inflammatory cytokines, and of several IFN gamma-induced genes relevant for control of intracellular pathogens. Together, our results show that MyD88-dependent signaling is essential for early control of C. burnetii replication and to prevent systemic spreading. The continued presence of NMII in the organs of Myd88(-/-) mice constitutes a new mouse model to study determinants of chronicity and resolution in Q fever.
CRIS-Team WoS Importer:2019-02-21

Myeloid Cell-Derived HIF-1? Promotes Control of Leishmania major - Schatz, Valentin; Strussmann, Yannic; Mahnke, Alexander; Schley, Gunnar; Waldner, Maximilian; Ritter, Uwe; Wild, Jens; Willam, Carsten; Dehne, Nathalie; Brune, Bernhard; Mcniff, Jennifer M.; Colegio, Oscar R.; et al. (Journal of Immunology, 2016)
Hypoxia-inducible factor-1? (HIF-1?), which accumulates in mammalian host organisms during infection, supports the defense against microbial pathogens. However, whether and to what extent HIF-1? expressed by myeloid cells contributes to the innate immune response against Leishmania major parasites is unknown. We observed that Leishmania-infected humans and L. major-infected C57BL/6 mice exhibited substantial amounts of HIF-1? in acute cutaneous lesions. In vitro, HIF-1? was required for leishmanicidal activity and high-level NO production by IFN-?/LPS-activated macrophages. Mice deficient for HIF-1? in their myeloid cell compartment had a more severe clinical course of infection and increased parasite burden in the skin lesions compared with wild-type controls. These findings were paralleled by reduced expression of type 2 NO synthase by lesional CD11b(+) cells. Together, these data illustrate that HIF-1? is required for optimal innate leishmanicidal immune responses and, thereby, contributes to the cure of cutaneous leishmaniasis.
EVALuna2:2181

Myeloid cells and the microenvironment, microorganisms and metabolism - Bogdan, Christian; Steinkasserer, Alexander (Immunobiology, 2015)
EVALuna2:7673

Nasal carriage of methicillin-resistant Staphylococcus aureus (MRSA) at a palliative care unit: A prospective single service analysis - Heckel, Maria; Geißdörfer, Walter; Herbst, Franziska A.; Stiel, Stephanie; Ostgathe, Christoph; Bogdan, Christian (PLoS ONE, 2017)
BACKGROUND: The emergence of multidrug-resistant bacterial microorganisms is a particular challenge for the health care systems. Little is known about the occurrence of methicillin-resistant Staphylococcus aureus (MRSA) and multidrug-resistant Gram-negative bacteria (MDRGNB) in patients of palliative care units (PCU). AIM: The primary aim of this study was to determine the carriage of MRSA among patients of a PCU at a German University Hospital and to assess whether the positive cases would have been detected by a risk-factor-based screening-approach. DESIGN: Between February 2014 and January 2015 patients from our PCU were tested for MRSA carriage within 48 hours following admission irrespective of pre-existing risk factors. In addition, risk factors for MRSA colonization were assessed. Samples from the nostrils and, if applicable, from pre-existing wounds were analysed by standardized culture-based laboratory techniques for the presence of MRSA and of other bacteria and fungi. Results from swabs taken prior to admission were also recorded if available. RESULTS: 297 out of 317 patients (93.7%) fulfilled one or more MRSA screening criteria. Swabs from 299 patients were tested. The detection rate was 2.1% for MRSA. All MRSA cases would have been detected by a risk-factor-based screening-approach. Considering the detected cases and the results from swabs taken prior to admission, 4.1% of the patients (n = 13) were diagnosed with MRSA and 4.1% with MDRGNB (n = 13), including two patients with MRSA and MDRGNB (0.6%). The rate of MRSA carriage in PCU patients (4.1%) was elevated compared to the rate seen in the general cohort of patients admitted to our University Hospital (2.7%). CONCLUSIONS: PCU patients have an increased risk to carry MRSA compared to other hospitalized patients. Although a risk factor-based screening is likely to detect all MRSA carriers amongst PCU patients, we rather recommend a universal screening to avoid the extra effort to identify the few risk factor-negative patients (<7%). As we did not perform a systematic MDRGNB screening, further studies are needed to determine the true prevalence of MDRGNB amongst PCU patients.
EVALuna2:33307

Natural killer cells in experimental and human leishmaniasis. - Bogdan, Christian (Frontiers in Cellular and Infection Microbiology, 2012)
Infections with parasites of the genus Leishmania lead to a rapid, but transient activation of natural killer (NK) cells. In mice activation of NK cells requires a toll-like-receptor 9-dependent stimulation of dendritic cells (DC) which is followed by the production of IL-12. Although NK cells appear to be non-essential for the ultimate control of cutaneous and visceral leishmaniasis (VL) and can exhibit immunosuppressive functions, they form an important source of interferon (IFN)-γ, which elicits antileishmanial activity in macrophages and helps to pave a protective T helper cell response. In contrast, the cytotoxic activity of NK cells is dispensable, because Leishmania-infected myeloid cells are largely resistant to NK-mediated lysis. In human cutaneous and VL, the functional importance of NK cells is suggested by reports that demonstrate (1) a direct activation or inhibition of NK cells by Leishmania promastigotes, (2) the suppression of NK cell numbers or activity during chronic, non-healing infections, and (3) the recovery of NK cell activity following treatment. This review aims to provide an integrated view on the migration, activation, inhibition, function, and therapeutic modulation of NK cells in experimental and human leishmaniasis.
CRIS-Team Scopus Importer:2024-02-26

Natural killer T (NKT) cells in autoimmune hepatitis - Mattner, Jochen (Current Opinion in Immunology, 2013)

Neuerungen in den aktuellen STIKO-Empfehlungen 2018/2019 - Bogdan, Christian (Pädiatrische Praxis, 2019)
The latest recommendations of the German Standing Committee on Vaccination (STIKO), which have been in force since August 23, 2018, include the following major amendments: • Universal use of a quadrivalent influenza vaccine, which in addition to the two influenza A virus types (H1N1, H3N2) contains two influenza B lines. • Routine human papilloma virus vaccination for all children at the age of 9 to 14. • Simultaneous active and passive immunization against tetanus also in patients with minor or clean wounds if immunity to tetanus is not existing or documented.
CRIS-Team Scopus Importer:2021-04-20

Neutrophil breaching of the blood vessel pericyte layer during diapedesis requires mast cell-derived IL-17A - Joulia, Regis; Guerrero-Fonseca, Idaira Maria; Girbl, Tamara; Coates, Jonathon A.; Stein, Monja; Vazquez-Martinez, Laura; Lynam, Eleanor; Whiteford, James; Schnoor, Michael; Vöhringer, David; Roers, Axel; Nourshargh, Sussan; et al. (Nature Communications, 2022)
Neutrophil diapedesis is an immediate step following infections and injury and is driven by complex interactions between leukocytes and various components of the blood vessel wall. Here, we show that perivascular mast cells (MC) are key regulators of neutrophil behaviour within the sub-endothelial space of inflamed venules. Using confocal intravital microscopy, we observe directed abluminal neutrophil motility along pericyte processes towards perivascular MCs, a response that created neutrophil extravasation hotspots. Conversely, MC-deficiency and pharmacological or genetic blockade of IL-17A leads to impaired neutrophil sub-endothelial migration and breaching of the pericyte layer. Mechanistically, identifying MCs as a significant cellular source of IL-17A, we establish that MC-derived IL-17A regulates the enrichment of key effector molecules ICAM-1 and CXCL1 in nearby pericytes. Collectively, we identify a novel MC-IL-17A-pericyte axis as modulator of the final steps of neutrophil diapedesis, with potential translational implications for inflammatory disorders driven by increased neutrophil diapedesis.
CRIS-Team Scopus Importer:2022-12-02

Nitric oxide-mediated regulation of ferroportin-1 controls macrophage iron homeostasis and immune function in Salmonella infection - Nairz, Manfred; Schleicher, Ulrike; Schroll, Andrea; Sonnweber, Thomas; Theurl, Igor; Ludwiczek, Susanne; Talasz, Heribert; Brandacher, Gerald; Moser, Patrizia L.; Muckenthaler, Martina U.; Fang, Ferric C.; Bogdan, Christian; et al. (Journal of Experimental Medicine, 2013)
Nitric oxide (NO) generated by inducible NO synthase 2 (NOS2) affects cellular iron homeostasis, but the underlying molecular mechanisms and implications for NOS2-dependent pathogen control are incompletely understood. In this study, we found that NO up-regulated the expression of ferroportin-1 (Fpn1), the major cellular iron exporter, in mouse and human cells. Nos2-/- macrophages displayed increased iron content due to reduced Fpn1 expression and allowed for an enhanced iron acquisition by the intracellular bacterium Salmonella typhimurium. Nos2 gene disruption or inhibition of NOS2 activity led to an accumulation of iron in the spleen and splenic macrophages. Lack of NO formation resulted in impaired nuclear factor erythroid 2-related factor-2 (Nrf2) expression, resulting in reduced Fpn1 transcription and diminished cellular iron egress. After infection of Nos2-/- macrophages or mice with S. typhimurium, the increased iron accumulation was paralleled by a reduced cytokine (TNF, IL-12, and IFN-γ) expression and impaired pathogen control, all of which were restored upon administration of the iron chelator deferasirox or hyperexpression of Fpn1 or Nrf2. Thus, the accumulation of iron in Nos2-/- macrophages counteracts a proinflammatory host immune response, and the protective effect of NO appears to partially result from its ability to prevent iron overload in macrophages. ©2013 Nairz et al.
CRIS-Team Scopus Importer:2024-02-26

Nitric oxide synthase in innate and adaptive immunity: an update - Bogdan, Christian (Trends in Immunology, 2015)
Thirty years after the discovery of its production by activated macrophages, our appreciation of the diverse roles of nitric oxide (NO) continues to grow. Recent findings have not only expanded our understanding of the mechanisms controlling the expression of NO synthases (NOS) in innate and adaptive immune cells, but have also revealed new functions and modes of action of NO in the control and escape of infectious pathogens, in T and B cell differentiation, and in tumor defense. I discuss these findings, in the context of a comprehensive overview of the various sources and multiple reaction partners of NO, and of the regulation of NOS2 by micromilieu factors, antisense RNAs, and 'unexpected' cytokines.
EVALuna2:7675

NKT Cells Contribute to the Control of Microbial Infections - Vogt, Sabine; Mattner, Jochen (Frontiers in Cellular and Infection Microbiology, 2021)
Innate (-like) T lymphocytes such as natural killer T (NKT) cells play a pivotal role in the recognition of microbial infections and their subsequent elimination. They frequently localize to potential sites of pathogen entry at which they survey extracellular and intracellular tissue spaces for microbial antigens. Engagement of their T cell receptors (TCRs) induces an explosive release of different cytokines and chemokines, which often pre-exist as constitutively expressed gene transcripts in NKT cells and underlie their poised effector state. Thus, NKT cells regulate immune cell migration and activation and subsequently, bridge innate and adaptive immune responses. In contrast to conventional T cells, which react to peptide antigens, NKT cells recognize lipids presented by the MHC class I like CD1d molecule on antigen presenting cells (APCs). Furthermore, each NKT cell TCR can recognize various antigen specificities, whereas a conventional T lymphocyte TCR reacts mostly only to one single antigen. These lipid antigens are either intermediates of the intracellular APC`s-own metabolism or originate from the cell wall of different bacteria, fungi or protozoan parasites. The best-characterized subset, the type 1 NKT cell subset expresses a semi-invariant TCR. In contrast, the TCR repertoire of type 2 NKT cells is diverse. Furthermore, NKT cells express a panoply of inhibitory and activating NK cell receptors (NKRs) that contribute to their primarily TCR-mediated rapid, innate like immune activation and even allow an adaption of their immune response in an adoptive like manner. Dueto their primary localization at host-environment interfaces, NKT cells are one of the first immune cells that interact with signals from different microbial pathogens. Vice versa, the mutual exchange with local commensal microbiota shapes also the biology of NKT cells, predominantly in the gastrointestinal tract. Following infection, two main signals drive the activation of NKT cells: first, cognate activation upon TCR ligation by microbial or endogenous lipid antigens; and second, bystander activation due to cytokines. Here we will discuss the role of NKT cells in the control of different microbial infections comparing pathogens expressing lipid ligands in their cell walls to infectious agents inducing endogenous lipid antigen presentation by APCs.
CRIS-Team WoS Importer:2021-10-22

NLRP3 Inhibition Leads to Impaired Mucosal Fibroblast Function in Patients with Inflammatory Bowel Diseases - Weber, Simone; Sitte, Selina; Vögele, Anna-Lena; Sologub, Ludmilla; Wilfer, Angelika; Rath, Timo; Nägel, Andreas; Zundler, Sebastian; Franchi, Luigi; Opipari, Anthony W.; Sonnewald, Sophia; Reid, Stephen; et al. (Journal of Crohns & Colitis, 2023)
Background and Aims: Inflammatory bowel diseases (IBD) are characterized by mucosal inflammation and sequential fibrosis formation, but the exact role of the hyperactive NLRP3 inflammasome in these processes is unclear. Thus, we studied the expression and function of the NLRP3 inflammasome in the context of inflammation and fibrosis in IBD. Methods: We analysed intestinal NLRP3 expression in mucosal immune cells and fibroblasts from IBD patients and NLRP3-associated gene expression via single-cell RNA sequencing and microarray analyses. Furthermore, cytokine secretion of NLRP3 inhibitor treated blood and mucosal cells, as well as proliferation, collagen production, and cell death of NLRP3 inhibitor treated intestinal fibroblasts from IBD patients were studied. Results: We found increased NLRP3 expression in the inflamed mucosa of IBD patients and NLRP3 inhibition led to reduced IL-1β and IL-18 production in blood cells and diminished the bioactive form of mucosal IL-1β. Single cell analysis identified overlapping expression patterns of NLRP3 and IL-1β in classically activated intestinal macrophages and we also detected NLRP3 expression in CD163+ macrophages. In addition, NLRP3 expression was also found in intestinal fibroblasts from IBD patients. Inhibition of NLRP3 led to reduced proliferation of intestinal fibroblasts, which was associated with a marked decrease in production of collagen type I and type VI in IBD patients. Moreover, NLRP3 inhibition in intestinal fibroblasts induced autophagy, a cellular process involved in collagen degradation. Conclusions: In the presented study, we demonstrate that inhibiting NLRP3 might pave the way for novel therapeutic approaches in IBD, especially to prevent the severe complication of intestinal fibrosis formation.
CRIS-Team Scopus Importer:2023-11-17
Keywords: fibroblasts; fibrosis; IL-18; IL-1β; Inflammatory bowel diseases; mucosal immune system; NLRP3 inflammasome; small molecule inhibitor

No Role for Mast Cells in Obesity-Related Metabolic Dysregulation - Chmelar, Jindrich; Chatzigeorgiou, Antonios; Chung, Kyoung-Jin; Prucnal, Marta; Vöhringer, David; Roers, Axel; Chavakis, Triantafyllos (Frontiers in Immunology, 2016)
Obesity-related adipose tissue (AT) inflammation that promotes metabolic dysregulation is associated with increased AT mast cell numbers. Mast cells are potent inducers of inflammatory responses and could potentially contribute to obesity-induced AT inflammation and metabolic dysregulation. Conflicting findings were reported on obesity-related metabolic dysfunction in mast cell-deficient mice, thus creating a controversy that has not been resolved to date. Whereas traditional Kit hypomorphic mast cell-deficient strains featured reduced diet-induced obesity and diabetes, a Kit-independent model of mast cell deficiency, Cpa3(Cre/+) mice, displayed no alterations in obesity and insulin sensitivity. Herein, we analyzed diet-induced obesity in Mcpt5-Cre R-DTA mice, in which the lack of mast cells is caused by a principle different from mast cell deficiency in Cpa3(Cre/+) mice or Kit mutations. We observed no difference between mast cell-deficient and -proficient mice in diet-induced obesity with regards to weight gain, glucose tolerance, insulin resistance, metabolic parameters, hepatic steatosis, and AT or liver inflammation. We conclude that mast cells play no essential role in obesity and related pathologies.
EVALuna2:25885

Novel GM-CSF signals via IFN-γR/IRF-1 and AKT/mTOR license monocytes for suppressor function - Ribechini, Eliana; Hutchinson, James A.; Hergovits, Sabine; Heuer, Marion; Lucas, Jorg; Schleicher, Ulrike; Garrote, Ana-Laura Jordan; Potter, Sarah J.; Riquelme, Paloma; Brackmann, Heike; Muller, Nora; Raifer, Hartmann; et al. (Blood Advances, 2017)
Granulocyte-macrophage colony-stimulating factor (GM-CSF) controls proliferation and survival of myeloid cells including monocytes. Here, we describe a time-dependent licensing process driven by GM-CSF in murine Ly6Chigh and human CD14+ monocytes that disables their inflammatory functions and promotes their conversion into suppressor cells. This 2-step licensing of monocytes requires activation of the AKT/mTOR/mTORC1 signaling cascade by GM-CSF followed by signaling through the interferon-γ receptor (IFN-γR)/interferon regulatory factor-1 (IRF-1) pathway. Only licensing-dependent adaptations in Toll-like receptor/inflammasome, IFN-γR, and phosphatidylinositol 3-kinase/AKT/mTOR signaling lead to stabilized expression of inducible nitric oxide synthase by mouse and indoleamine 2,3-dioxygenase (IDO) by human monocytes, which accounts for their suppressor activity. This study suggests various myeloid cells with characteristics similar to those described for monocytic myeloid-derived suppressor cells, Mreg, or suppressor macrophages may arise from licensed monocytes. Markers of GM-CSF-driven monocyte licensing, including p-Akt, p-mTOR, and p-S6, distinguish inflammatory monocytes from potentially suppressive monocytes in peripheral blood of patients with high-grade glioma.
EVALuna2:36433

Novel plasmids in multidrug-resistant Shigella flexneri serotypes from Pakistan - Nisa, Iqbal; Driessen, Arnold; Nijland, Jeroen; Rahman, Hazir; Mattner, Jochen; Qasim, Muhammad (Archives of Microbiology, 2023)
Shigellosis is the main cause of food and waterborne diarrhea and is an emerging threat to human health. The current study characterized the indigenous multidrug-resistant Shigella flexneri serotypes for their plasmid profiles and genetic diversity, to characterize the plasmid evolutionary patterns and distribution. In total, 199 identified S. flexneri isolates belonging to six different serotypes were analyzed for plasmid profiling, followed by an analysis of whole genome sequencing. All isolates of S. flexneri resistant to antibiotics harbored multiple copies of plasmids with sizes ranging from 1.25 kbp to 9.4 kbp. These isolates were clustered into 22 distinct plasmid patterns, labeled as p1-p22. Among these, p1 (24%) and p10 (13%) were the predominant plasmid profiles. All S. flexneri strains were grouped into 12 clades with a 75% similarity level. Also, a significant association was observed among the plasmid patterns, p23 and p17 with the drug-resistant patterns AMC, SXT, C (19.5%) and OFX, AMC, NA, CIP (13.5%), respectively. Moreover, the most widespread plasmid patterns p4, p10, and p1 showed a significant association with the serotypes 1b (29.16%), 2b (36%), and 7a (100%), respectively. After plasmid sequence assembly and annotation analysis, a variety of small plasmids that vary in size from 973 to 6200 bp were discovered. Many of these plasmids displayed high homology and coverage with plasmids from non-S. flexneri. Several novel plasmids of small size were discovered in multidrug-resistant S. flexneri. The data also showed that plasmid profile analysis is more consistent than antibiotic susceptibility pattern analysis for identifying epidemic strains of S. flexneri isolated in Pakistan.
CRIS-Team Scopus Importer:2023-04-21
Keywords: Multidrug-resistant Shigella flexneri; Pakistan; Plasmids; Whole genome sequencing

Nuclear trafficking of the anti-apoptotic Coxiella burnetii effector protein AnkG requires binding to p32 and Importin-alpha 1 - Schäfer, Walter; Eckart, Rita; Schmid, Benedikt; Cagkoeylue, Hasret; Hof, Kerstin; Muller, Yves; Amin, Bushra; Lührmann, Anja (Cellular Microbiology, 2017)
The obligate intracellular bacterium Coxiella burnetii causes the zoonotic disease Q-fever. Coxiella pathogenesis depends on a functional type IV secretion system (T4SS). The T4SS effector AnkG inhibits pathogen-induced host cell apoptosis, which is believed to be important for the establishment of a persistent infection. However, the mode of action of AnkG is not fully understood. We have previously demonstrated that binding of AnkG to p32 is crucial for migration of AnkG into the nucleus and that nuclear localization of AnkG is essential for its antiapoptotic activity. Here, we compared the activity of AnkG from the C. burnetii strains Nine Mile and Dugway. Although there is only a single amino acid exchange at residue 11, we observed a difference in anti-apoptotic activity and nuclear migration. Mutation of amino acid 11 to glutamic acid, threonine or valine results in AnkG mutants that had lost the anti-apoptotic activity and the ability to migrate into the nucleus. We identified Importin-a1 to bind to AnkG, but not to the mutants and concluded that binding of AnkG to p32 and Importin-a1 is essential for migration into the nucleus. Also during Coxiella infection binding of AnkG to p32 and Importin-a1 is crucial for nuclear localization of AnkG.
EVALuna2:7733

Nuclear trafficking of the anti-apoptotic Coxiella burnetii effector protein AnkG requires binding to p32 and Importin-α1 - Schäfer, Walter; Eckart, Rita; Schmid, Benedikt; Cagköylü, Hasret; Hof, Kerstin; Muller, Yves; Amin, Bushra; Lührmann, Anja (Cellular Microbiology, 2016)
The obligate intracellular bacterium Coxiella burnetii causes the zoonotic disease Q-fever. Coxiella pathogenesis depends on a functional type IV secretion system (T4SS). The T4SS effector AnkG inhibits pathogen-induced host cell apoptosis, which is believed to be important for the establishment of a persistent infection. However, the mode of action of AnkG is not fully understood. We have previously demonstrated that binding of AnkG to p32 is crucial for migration of AnkG into the nucleus and that nuclear localization of AnkG is essential for its anti-apoptotic activity. Here, we compared the activity of AnkG from the C. burnetii strains Nine Mile and Dugway. Although there is only a single amino acid exchange at residue 11, we observed a difference in anti-apoptotic activity and nuclear migration. Mutation of amino acid 11 to glutamic acid, threonine or valine results in AnkG mutants that had lost the anti-apoptotic activity and the ability to migrate into the nucleus. We identified Importin-α1 to bind to AnkG, but not to the mutants and concluded that binding of AnkG to p32 and Importin-α1 is essential for migration into the nucleus. Also during Coxiella infection binding of AnkG to p32 and Importin-α1 is crucial for nuclear localization of AnkG.
EVALuna2:7709

Obesity impairs pulmonary type 2 immunity during helminth infection - Deinzer, Andrea; Schmidt, Viviane; Schwartz, Christian (EUROPEAN JOURNAL OF IMMUNOLOGY, 2022)
CRIS-Team WoS Importer:2023-01-27

Obesity-Mediated Immune Modulation: One Step Forward, (Th)2 Steps Back - Schmidt, Viviane; Hogan, Andrew E.; Fallon, Padraic G.; Schwartz, Christian (Frontiers in Immunology, 2022)
Over the past decades, the relationship between the immune system and metabolism has become a major research focus. In this arena of immunometabolism the capacity of adipose tissue to secrete immunomodulatory molecules, including adipokines, within the underlying low-grade inflammation during obesity brought attention to the impact obesity has on the immune system. Adipokines, such as leptin and adiponectin, influence T cell differentiation into different T helper subsets and their activation during immune responses. Furthermore, within the cellular milieu of adipose tissue nutrient availability regulates differentiation and activation of T cells and changes in cellular metabolic pathways. Upon activation, T cells shift from oxidative phosphorylation to oxidative glycolysis, while the differential signaling of the kinase mammalian target of rapamycin (mTOR) and the nuclear receptor PPAR gamma, amongst others, drive the subsequent T cell differentiation. While the mechanisms leading to a shift from the typical type 2-dominated milieu in lean people to a Th1-biased pro-inflammatory environment during obesity are the subject of extensive research, insights on its impact on peripheral Th2-dominated immune responses become more evident. In this review, we will summarize recent findings of how Th2 cells are metabolically regulated during obesity and malnutrition, and how these states affect local and systemic Th2-biased immune responses.
CRIS-Team WoS Importer:2022-07-29

Obituary Prof. Victoria Kolb-Bachofen - Foerstermann, Ulrich; Bogdan, Christian; Pfeilschifter, Josef M.; Mayer, Bernd M. (Nitric Oxide-Biology and Chemistry, 2014)
EVALuna2:7658

Of mice and men: Interaction of Corynebacterium diphtheriae strains with murine and human phagocytes - Weerasekera, Dulanthi; Fastner, Tamara Antonia; Lang, Roland; Burkovski, Andreas; Ott, Lisa (Virulence, 2019)
Seven non-toxigenic C. diphtheriae strains and one toxigenic strain were analyzed with regard to their interaction with murine macrophages (BMM) and human THP-1 macrophage-like cells. Proliferation assays with BMM and THP-1 revealed similar intracellular CFUs for C. diphtheriae strains independent of the host cell. Strain ISS4060 showed highest intracellular CFUs, while the toxigenic DSM43989 was almost not detectable. This result was confirmed by TLR 9 reporter assays, showing a low signal for DSM43989, indicating that the bacteria are not endocytosed. In contrast, the non-pathogenic C. glutamicum showed almost no intracellular CFUs independent of the host cell, but was recognized by TLR9, indicating that the bacteria were degraded immediately after endocytosis. In terms of G-CSF and IL-6 production, no significant differences between BMM and THP-1 were observed. G-CSF production was considerably higher than IL-6 for all C. diphtheriae strains and the C. glutamicum did not induce high cytokine secretion in general. Furthermore, all corynebacteria investigated in this study were able to induce NFκB signaling but only viable C. diphtheriae strains were able to cause host cell damage, whereas C. glutamicum did not. The absence of Mincle resulted in reduced G-CSF production, while no influence on the uptake of the bacteria was observed. In contrast, when MyD88 was absent, both the uptake of the bacteria and cytokine production were blocked. Consequently, phagocytosis only occurs when the TLR/MyD88 pathway is functional, which was also supported by showing that all corynebacteria used in this study interact with human TLR2.
CRIS-Team Scopus Importer:2019-06-04
Keywords: Cytotoxicity; inflammation; interleukins; macrophages; NFκB; TLRs

On the lineage of Aspergillus fumigatus isolates in common laboratory use - Bertuzzi, Margherita; van Rhijn, Norman; Krappmann, Sven; Bowyer, Paul; Bromley, Michael J.; Bignell, Elaine M. (Medical Mycology, 2021)
The origin of isolates routinely used by the community of Aspergillus fumigatus researchers is periodically a matter of intense discussion at our centre, as the construction of recombinant isolates have sometimes followed convoluted routes, the documentation describing their lineages is fragmented, and the nomenclature is confusing. As an aide memoir, not least for our own benefit, we submit the following account and tabulated list of strains (Table 1) in an effort to collate all of the relevant information in a single, easily accessible document. To maximise the accuracy of this record we have consulted widely amongst the community of Medical Mycologists using these strains. All the strains described are currently available from one of these organisations, namely the Fungal Genetics Stock Centre (FGSC), FungiDB, Ensembl Fungi and The National Collection of Pathogenic Fungi (NCPF) at Public Health England. Display items from this manuscript are also featured on FungiDB. LAY ABSTRACT: We present a concise overview on the definition, origin and unique genetic makeup of the Aspergillus fumigatus isolates routinely in use by the fungal research community, to aid researchers to describe past and new strains and the experimental differences observed more accurately.
CRIS-Team Scopus Importer:2021-01-22
Keywords: Aspergillus fumigatus; isolate; lineage; strain

Opposing functions of thymic stromal lymphopoietin-responsive basophils and dendritic cells in a mouse model of atopic dermatitis - Schwartz, Christian; Eberle, Jörg; Hoyler, Thomas; Diefenbach, Andreas; Lechmann, Matthias; Vöhringer, David (Journal of Allergy and Clinical Immunology, 2016)
EVALuna2:25878

Orofacial clefts alter early life oral microbiome maturation towards higher levels of potentially pathogenic species: A prospective observational study - Seidel, Corinna Lesley; Strobel, Karin; Weider, Matthias; Tschaftari, Marco; Unertl, Christoph; Willershausen, Ines; Weber, Manuel; Hörning, André; Morhart, Patrick; Schneider, Michael; Beckmann, Matthias; Bogdan, Christian; et al. (Journal of Oral Microbiology, 2023)
Orofacial clefts (OFC) present different phenotypes with a postnatal challenge for oral microbiota development. In order to investigate the impact of OFC on oral microbiota, smear samples from 15 neonates with OFC and 17 neonates without OFC were collected from two oral niches (tongue, cheek) at two time points, i.e. after birth (T0: Ø3d OFC group; Ø2d control group) and 4–5 weeks later (T1: Ø32d OFC group; Ø31d control group). Subsequently, the samples were analyzed using next-generation sequencing. We detected a significant increase of alpha diversity and anaerobic and Gram-negative species from T0 to T1 in both groups. Further, we found that at T1 OFC neonates presented a significantly lower alpha diversity (lowest values for high cleft severity) and significantly higher levels of Enterobacteriaceae (Citrobacter, Enterobacter, Escherichia-Shigella, Klebsiella), Enterococcus, Bifidobacterium, Corynebacterium, Lactocaseibacillus, Staphylococcus, Acinetobacter and Lawsonella compared to controls. Notably, neonates with unilateral and bilateral cleft lip and palate (UCLP/BCLP) presented similarities in beta diversity and a mixture with skin microbiota. However, significant differences were seen in neonates with cleft palate only compared to UCLP/BCLP with higher levels of anaerobic species. Our findings revealed an influence of OFC as well as cleft phenotype and severity on postnatal oral microbiota maturation.
CRIS-Team Scopus Importer:2023-01-20
Keywords: early life dysbiosis; microbiome maturation; neonates; oral microbiome; Orofacial clefts

Orthotopic T-cell receptor replacement in primary human T cells using CRISPR-Cas9-mediated homology-directed repair. - Moosmann, Carolin; Müller, Thomas R.; Busch, Dirk H.; Schober, Kilian (STAR Protocols, 2022)
Adoptive T cell therapy using T-cell receptor (TCR)-engineered T cells allows to redirect T cell specificity and to target any antigen of interest. Here, we apply advanced genetic engineering using clustered regularly interspaced short palindromic repeats (CRISPR)-associated protein 9 (Cas9) for simultaneous editing of TCR α- and β-chains in primary human T cells. Together with non-virally delivered template DNA, this CRISPR-Cas9-system allows for elimination of the endogenous TCR and orthotopic placement of TCR α- and β-chains. For complete details on the use and execution of this protocol, please refer to Schober et al. (2019) and Müller et al. (2021).

ORTHOTOPIC T CELL RECEPTOR REPLACEMENT NEXT - GENERATION ENGINEERING OF T CELLS FOR THERAPY - Schober, Kilian (HUMAN GENE THERAPY, 2022)
CRIS-Team WoS Importer:2022-10-21

Osteocyte necrosis triggers osteoclast-mediated bone loss through macrophage-inducible C-type lectin - Andreev, Darja; Liu, Mengdan; Weidner, Daniela; Kachler, Katerina; Faas, Maria; Grüneboom, Anika; Schlötzer-Schrehardt, Ursula; Munoz, Luis Enrique; Steffen, Ulrike; Grötsch, Bettina; Killy, Barbara; Krönke, Gerhard; et al. (Journal of Clinical Investigation, 2020)
Although the control of bone-resorbing osteoclasts through osteocyte-derived RANKL is well defined, little is known about the regulation of osteoclasts by osteocyte death. Indeed, several skeletal diseases, such as bone fracture, osteonecrosis, and inflammation are characterized by excessive osteocyte death. Herein we show that osteoclasts sense damageassociated molecular patterns (DAMPs) released by necrotic osteocytes via macrophage-inducible C-type lectin (Mincle), which induced their differentiation and triggered bone loss. Osteoclasts showed robust Mincle expression upon exposure to necrotic osteocytes in vitro and in vivo. RNA sequencing and metabolic analyses demonstrated that Mincle activation triggers osteoclastogenesis via ITAM-based calcium signaling pathways, skewing osteoclast metabolism toward oxidative phosphorylation. Deletion of Mincle in vivo effectively blocked the activation of osteoclasts after induction of osteocyte death, improved fracture repair, and attenuated inflammation-mediated bone loss. Furthermore, in patients with osteonecrosis, Mincle was highly expressed at skeletal sites of osteocyte death and correlated with strong osteoclastic activity. Taken together, these data point to what we believe is a novel DAMP-mediated process that allows osteoclast activation and bone loss in the context of osteocyte death.
CRIS-Team Scopus Importer:2020-10-16

Otubain 2 promotes muramyl dipeptide-mediated anti-colitogenic effects due to de-ubiquitination of receptor interaction protein 2 - Mattner, Jochen (Clinical and Translational Discovery, 2024)
CRIS-Team Scopus Importer:2024-11-01

Overwhelming Postsplenectomy Infection: A Prospective Multicenter Cohort Study - Theilacker, Christian; Ludewig, Katrin; Serr, Annerose; Schimpf, Julia; Held, Jürgen; Boegelein, Martin; Bahr, Viola; Rusch, Stephan; Pohl, Annette; Kogelmann, Klaus; Frieseke, Sigrun; Bogdanski, Ralph; et al. (Clinical Infectious Diseases, 2016)
Recent population-based cohort studies have questioned the role of pneumococci as the most frequent pathogen causing severe infection in patients after splenectomy. The aim of the study was to define the causative pathogens and clinical presentation of patients with overwhelming postsplenectomy infection (OPSI).In a prospective cohort study in 173 German intensive care units, we searched for patients with and without asplenia and community-acquired severe sepsis/septic shock. Clinical and laboratory variables and survival of patients were assessed.Fifty-two patients with severe sepsis or septic shock with asplenia and 52 without asplenia were included. OPSI patients more often had a history of malignancy (38% vs 17%; P = .016) and had a lower body mass index (24 kg/m(2) vs 28 kg/m(2); P = .004). Streptococcus pneumoniae was detected more frequently in OPSI patients (42% vs 12% without asplenia; P < .001) and more frequently manifested as bloodstream infection (31% vs 6%; P = .002). Gram-negative infection was similar in both groups (12% vs 19%; P = .157). Pneumococcal vaccine coverage of OPSI patients was low overall (42% vs 8% among patients without asplenia; P < .001). Purpura fulminans was a frequent complication, developing in 19% of OPSI patients vs 5% of patients without asplenia (P = .038). The interval between splenectomy and OPSI was 6 years (range, 1 month-50 years). On multivariable Poisson regression, asplenia was the only predictive variable independently associated with pneumococcal sepsis (adjusted relative risk, 2.53 [95% confidence interval, 1.06-6.08]).Pneumococcal infections remain the most important cause of severe sepsis and septic shock following splenectomy.
EVALuna2:7698

Pathogenic fungi regulate immunity by inducing neutrophilic myeloid-derived suppressor cells - Rieber, Nikolaus; Singh, Anurag; Oez, Hasan; Carevic, Melanie; Bouzani, Maria; Amich, Jorge; Ost, Michael; Ye, Zhiyong; Ballbach, Marlene; Schaefer, Iris; Mezger, Markus; Klimosch, Sascha N.; et al. (Cell Host & Microbe, 2015)
Despite continuous contact with fungi, immunocompetent individuals rarely develop pro-inflammatory antifungal immune responses. The underlying tolerogenic mechanisms are incompletely understood. Using both mouse models and human patients, we show that infection with the human pathogenic fungi Aspergillus fumigatus and Candida albicans induces a distinct subset of neutrophilic myeloid-derived suppressor cells (MDSCs), which functionally suppress T and NK cell responses. Mechanistically, pathogenic fungi induce neutrophilic MDSCs through the pattern recognition receptor Dectin-1 and its downstream adaptor protein CARD9. Fungal MDSC induction is further dependent on pathways downstream of Dectin-1 signaling, notably reactive oxygen species (ROS) generation as well as caspase-8 activity and interleukin-1 (IL-1) production. Additionally, exogenous IL-1? induces MDSCs to comparable levels observed during C. albicans infection. Adoptive transfer and survival experiments show that MDSCs are protective during invasive C. albicans infection, but not A. fumigatus infection. These studies define an innate immune mechanism by which pathogenic fungi regulate host defense.
EVALuna2:7690

Patients' views on the impact of multi-drug-resistant bacterial microorganisms (MDRO) in end-of-life care - A qualitative study using principles of Grounded Theory. - Sturm, Alexander; Ostgathe, Christoph; Stiel, Stephanie; Heckel, Maria; Herbst, Franziska A.; Adelhardt, Thomas; Schöffski, Oliver; Bogdan, Christian; Tiedtke, Johanna; Lang, Frieder; Sieber, Cornel (SPRINGER, 2018)

Persistence of the IgE repertoire in birch pollen allergy - Otte, Manuel; Mahler, Vera; Kerpes, Andrea; Pabst, Oliver; Vöhringer, David (Journal of Allergy and Clinical Immunology, 2016)
EVALuna2:19587

Perturbations of mucosal homeostasis through interactions of intestinal microbes with myeloid cells - Schey, Regina; Danzer, Claudia Agnes; Mattner, Jochen (Immunobiology, 2015)
Mucosal surfaces represent the largest areas of interactions of the host with its environment. Subsequently, the mucosal immune system has evolved complex strategies to maintain the integrity of the host by inducing protective immune responses against pathogenic and tolerance against dietary and commensal microbial antigens within the broad range of molecules the intestinal epithelium is exposed to. Among many other specialized cell subsets, myeloid cell populations - due to their strategic location in the subepithelial lamina propria - are the first ones to scavenge and process these intestinal antigens and to send consecutive signals to other immune and non-immune cell subsets. Thus, myeloid cell populations represent attractive targets for clinical intervention in chronic inflammatory bowel diseases (IBDs) such as ulcerative colitis (UC) and Crohn's disease (CD) as they initiate and modulate inflammatory or regulatory immune response and shape the intestinal T cell pool. Here, we discuss the interactions of the intestinal microbiota with dendritic cell and macrophage populations and review in this context the literature on four promising candidate molecules that are critical for the induction and maintenance of intestinal homeostasis on the one hand, but also for the initiation and propagation of chronic intestinal inflammation on the other.
EVALuna2:7664

PGAM5-MAVS interaction regulates TBK1/ IRF3 dependent antiviral responses - Yu, Yidong; Zielinska, Marta; Li, Wei; Bernkopf, Dominic; Heilingloh, Christiane; Neurath, Markus; Becker, Christoph (Scientific Reports, 2020)
Viral infections trigger host innate immune responses, characterized by the production of type-I interferons (IFN) including IFNβ. IFNβ induces cellular antiviral defense mechanisms and thereby contributes to pathogen clearance. Accumulating evidence suggests that mitochondria constitute a crucial platform for the induction of antiviral immunity. Here we demonstrate that the mitochondrial protein phosphoglycerate mutase family member 5 (PGAM5) is important for the antiviral cellular response. Following challenge of HeLa cells with the dsRNA-analog poly(I:C), PGAM5 oligomers and high levels of PGAM5 were found in mitochondrial aggregates. Using immunoprecipitation, a direct interaction of PGAM5 with the mitochondrial antiviral-signaling protein (MAVS) was demonstrated. In addition, PGAM5 deficient cells showed diminished expression of IFNβ and IFNβ target genes as compared to WT cells. Moreover, PGAM5 deficient mouse embryonic fibroblasts (MEFs) exhibited decreased phosphorylation levels of IRF3 and TBK1 when challenged with poly(I:C) intracellularly. Finally, PGAM5 deficient MEFs, upon infection with vesicular stomatitis virus (VSV), revealed diminished IFNβ expression and increased VSV replication. Collectively, our study highlights PGAM5 as an important regulator for IFNβ production mediated via the TBK1/IRF3 signaling pathway in response to viral infection.
CRIS-Team Scopus Importer:2020-06-02

Phosphatidylinositol 3-Kinase (PI3K) Orchestrates Aspergillus fumigatus-Induced Eosinophil Activation Independently of Canonical Toll-Like Receptor (TLR)/C-Type-Lectin Receptor (CLR) Signaling - Dietschmann, Axel; Schrüfer, Sebastian; Westermann, Stefanie; Henkel, Fiona; Castiglione, Kirstin; Willebrand, Ralf; Adam, Jasmin; Ruland, Jurgen; Lang, Roland; Sheppard, Donald C.; Esser-Von-Bieren, Julia; Radtke, Daniel; et al. (Mbio, 2022)
Eosinophilia is associated with various persisting inflammatory diseases and often coincides with chronic fungal infections or fungal allergy as in the case of allergic bronchopulmonary aspergillosis (ABPA). Here, we show that intranasal administration of live Aspergillus fumigatus conidia causes fatal lung damage in eosinophilic interleukin-5 (IL-5)-transgenic mice. To further investigate the activation of eosinophils by A. fumigatus, we established a coculture system of mouse bone marrow-derived eosinophils (BMDE) with different A. fumigatus morphotypes and analyzed the secretion of cytokines, chemokines, and eicosanoids. A. fumigatus-stimulated BMDE upregulated expression of CD11b and downregulated CD62L and CCR3. They further secreted several proinflammatory mediators, including IL-4, IL-13, IL-18, macrophage inflammatory protein-1 alpha (MIP-1 alpha)/CC chemokine ligand 3 (CCL3), MIP-1 beta/CCL4, and thromboxane. This effect required direct interaction and adherence between eosinophils and A. fumigatus, as A. fumigatus culture supernatants or A. fumigatus mutant strains with impaired adhesion elicited a rather poor eosinophil response. Unexpectedly, canonical Toll-like receptor (TLR) or C-type-lectin receptor (CLR) signaling was largely dispensable, as the absence of MYD88, TRIF, or caspase recruitment domain-containing protein 9 (CARD9) resulted in only minor alterations. However, transcriptome analysis indicated a role for the PI3K-AKT-mTOR pathway in A. fumigatus-induced eosinophil activation. Correspondingly, we could show that phosphatidylinositol 3-kinase (PI3K) inhibitors successfully prevent A. fumigatus-induced eosinophil activation. The PI3K pathway in eosinophils may therefore serve as a potential drug target to interfere with undesired eosinophil activation in fungus-elicited eosinophilic disorders. IMPORTANCE Allergic bronchopulmonary aspergillosis (ABPA) is caused by the fungus Aspergillus fumigatus, afflicts about five million patients globally, and is still a noncurable disease. ABPA is associated with pronounced lung eosinophilia. Activated eosinophils enhance the inflammatory response not only by degranulation of toxic proteins but also by secretion of small effector molecules. Receptors and signaling pathways involved in activation of eosinophils by A. fumigatus are currently unknown. Here, we show that A. fumigatus-elicited activation of eosinophils requires direct cell-cell contact and results in modulation of cell surface markers and rapid secretion of cytokines, chemokines, and lipid mediators. Unexpectedly, this activation occurred independently of canonical Toll-like receptor or C-type lectin receptor signaling. However, transcriptome analysis indicated a role for the PI3K-AKT-mTOR pathway, and PI3K inhibitors successfully prevented A. fumigatus-induced eosinophil activation. The PI3K pathway may therefore serve as a potential drug target to interfere with undesired eosinophil activation in fungus-elicited eosinophilic disorders.
CRIS-Team WoS Importer:2022-06-24

Photo Quiz: Mysterious Objects in a Pleural Biopsy Sample from a Patient with Recurrent Pleural Empyema - Held, Jürgen; Graeber, Kai; Leubner-Metzger, Gerhard; Kunkel, Tim; Theilacker, Christian; Kramme, Stefanie; Schmitt-Graeff, Annette (Journal of Clinical Microbiology, 2015)
EVALuna2:7699

Phylogenomic characterisation of a novel corynebacterial species pathogenic to animals - Möller, Jens; Musella, Luca; Melnikov, Vyacheslav; Geißdörfer, Walter; Burkovski, Andreas; Sangal, Vartul (Antonie Van Leeuwenhoek International Journal of General and Molecular Microbiology, 2020)
The genus Corynebacterium includes species of biotechnological, medical and veterinary importance. An atypical C. ulcerans strain, W25, was recently isolated from a case of necrotizing lymphadenitis in a wild boar. In this study, we have analysed the genome sequence of this strain and compared the phenotypic and virulence properties with other corynebacterial pathogens. Phylogenomic analyses revealed that strain W25 belongs to a novel species along with PO100/5 and KL1196. The latter strains were isolated from a pig and a roe deer, respectively; hence, this species appears to be associated to animals. The isolate W25 is likely a non-toxigenic tox gene bearing strain and may have compromised abilities to adhere to pharyngeal and laryngeal epithelial cells due to potential loss of the gene functions in spaBC and spaDEF pilus gene clusters. A number of corynebacterial virulence genes are present including pld encoding phospholipase D. Therefore, this strain may be able to cause severe invasive infections in animals and zoonotic infections in humans.
CRIS-Team Scopus Importer:2020-06-16
Keywords: Corynebacterium ulcerans; Diphtheria; Non-toxigenic; NTTB; Toxigenic; Virulence; Zoonotic

Physiology and pathology of eosinophils: Recent developments: Summary of the Focus Workshop Organized by DGAKI - Renz, Harald; Bachert, Claus; Berek, Claudia; Hamelmann, Eckard; Levi-Schaffer, Francesca; Raap, Ulrike; Simon, Hans Uwe; Ploetz, Sabine; Taube, Christian; Valent, Peter; Vöhringer, David; Werfel, Thomas; et al. (Scandinavian Journal of Immunology, 2021)
Over the last century, eosinophils have been regarded ambiguously either as ‘friends’ or ‘foes’. Recent developments have greatly enhanced our understanding of the role and function of eosinophils in health and disease. Pathogenic eosinophilic inflammation can lead to severe diseases in various organs, such as the gastrointestinal tract, airways, heart and skin. In a 2-day focus workshop of the German Society for Allergology and Clinical Immunology (DGAKI), the state of the art was discussed and practical recommendations for diagnosis and treatment of eosinophilic diseases, with a particular focus on new biologics, such as anti-interleukin 5 and anti-interleukin 5R, were derived.
CRIS-Team Scopus Importer:2021-03-19
Keywords: anti-interleukin 5; DNAzyme against GATA3; eosinophil; eosinophil diseases; hypereosinophilic syndrome

PI3K signaling orchestrates eosinophil activation against Aspergillus fumigatus independently of canonical TLR/CLR signaling - Dietschmann, Axel; Schrüfer, Sebastian; Westermann, Stefanie; Henkel, F.; Castiglione, Kathrin; Willebrand, Ralf; Ruland, J.; Lang, Roland; Esser-Von-Bieren, J.; Radtke, Daniel; Krappmann, Sven; Vöhringer, David (MYCOSES, 2021)
CRIS-Team WoS Importer:2021-10-08

Pilot Study on the Use of a Laser-Structured Double Diamond Electrode (DDE) for Biofilm Removal from Dental Implant Surfaces - Koch, Maximilian; Burkovski, Andreas; Zulla, Manuel; Rosiwal, Stefan; Geissdorfer, Walter; Dittmar, Roman; Grobecker-Karl, Tanja (Journal of Clinical Medicine, 2020)
No proper treatment option for peri-implantitis exists yet. Based on previous studies showing the in vitro effectiveness of electrochemical disinfection using boron-doped diamond electrodes, novel double diamond electrodes (DDE) were tested here. Using a ceramic carrier and a laser structuring process, a clinically applicable electrode array was manufactured. Roughened metal discs (n = 24) made from Ti-Zr alloy were exposed to the oral cavities of six volunteers for 24 h in order to generate biofilm. Then, biofilm removal was carried out either using plastic curettes and chlorhexidine digluconate or electrochemical disinfection. In addition, dental implants were contaminated with ex vivo multispecies biofilm and disinfected using DDE treatment. Bacterial growth and the formation of biofilm polymer were determined as outcome measures. Chemo-mechanical treatment could not eliminate bacteria from roughened surfaces, while in most cases, a massive reduction of bacteria and biofilm polymer was observed following DDE treatment. Electrochemical disinfection was charge- and time-dependent and could also not reach complete disinfection in all instances. Implant threads had no negative effect on DDE treatment. Bacteria exhibit varying resistance to electrochemical disinfection with Bacillus subtilis, Neisseria sp., Rothia mucilaginosa, Staphylococcus haemolyticus, and Streptococcus mitis surviving 5 min of DDE application at 6 V. Electrochemical disinfection is promising but requires further optimization with respect to charge quantity and application time in order to achieve disinfection without harming host tissue.
CRIS-Team WoS Importer:2020-11-06

Pivotal Role of Intestinal Microbiota and Intraluminal Metabolites for the Maintenance of Gut-Bone Physiology - Grüner, Niklas; Ortlepp, Anna Lisa; Mattner, Jochen (International Journal of Molecular Sciences, 2023)
Intestinal microbiota, and their mutual interactions with host tissues, are pivotal for the maintenance of organ physiology. Indeed, intraluminal signals influence adjacent and even distal tissues. Consequently, disruptions in the composition or functions of microbiota and subsequent altered host-microbiota interactions disturb the homeostasis of multiple organ systems, including the bone. Thus, gut microbiota can influence bone mass and physiology, as well as postnatal skeletal evolution. Alterations in nutrient or electrolyte absorption, metabolism, or immune functions, due to the translocation of microbial antigens or metabolites across intestinal barriers, affect bone tissues, as well. Intestinal microbiota can directly and indirectly alter bone density and bone remodeling. Intestinal dysbiosis and a subsequently disturbed gut-bone axis are characteristic for patients with inflammatory bowel disease (IBD) who suffer from various intestinal symptoms and multiple bone-related complications, such as arthritis or osteoporosis. Immune cells affecting the joints are presumably even primed in the gut. Furthermore, intestinal dysbiosis impairs hormone metabolism and electrolyte balance. On the other hand, less is known about the impact of bone metabolism on gut physiology. In this review, we summarized current knowledge of gut microbiota, metabolites and microbiota-primed immune cells in IBD and bone-related complications.
CRIS-Team Scopus Importer:2023-04-07
Keywords: arthritis; cell trafficking; cytokines; gut–bone axis; hormone and electrolyte metabolism; inflammatory bowel disease; intestinal dysbiosis; intestinal microbiota; osteoporosis; spondyloarthropathy

Plasmodium falciparum gametocytes display global chromatin remodelling during sexual differentiation - Jeninga, Myriam; Tang, Jingyi; Selvarajah, Shamista A.; Maier, Alexander G.; Duffy, Michael F.; Petter, Michaela (BMC Biology, 2023)
Background: The protozoan malaria parasite Plasmodium falciparum has a complex life cycle during which it needs to differentiate into multiple morphologically distinct life forms. A key process for transmission of the disease is the development of male and female gametocytes in the human blood, yet the mechanisms determining sexual dimorphism in these haploid, genetically identical sexual precursor cells remain largely unknown. To understand the epigenetic program underlying the differentiation of male and female gametocytes, we separated the two sexual forms by flow cytometry and performed RNAseq as well as comprehensive ChIPseq profiling of several histone variants and modifications. Results: We show that in female gametocytes the chromatin landscape is globally remodelled with respect to genome-wide patterns and combinatorial usage of histone variants and histone modifications. We identified sex specific differences in heterochromatin distribution, implicating exported proteins and ncRNAs in sex determination. Specifically in female gametocytes, the histone variants H2A.Z/H2B.Z were highly enriched in H3K9me3-associated heterochromatin. H3K27ac occupancy correlated with stage-specific gene expression, but in contrast to asexual parasites this was unlinked to H3K4me3 co-occupancy at promoters in female gametocytes. Conclusions: Collectively, we defined novel combinatorial chromatin states differentially organising the genome in gametocytes and asexual parasites and unravelled fundamental, sex-specific differences in the epigenetic code. Our chromatin maps represent an important resource for future understanding of the mechanisms driving sexual differentiation in P. falciparum.
CRIS-Team Scopus Importer:2023-04-28
Keywords: Epigenome; Gametocytogenesis; Histone variants; Malaria; Plasmodium falciparum; Transcriptome

Pleural Resident Macrophages and Pleural IRA B Cells Promote Efficient Immunity Against Pneumonia by Inducing Early Pleural Space Inflammation - Benard, Alan; Podolska, Malgorzata; Czubayko, Franziska; Kutschick, Isabella; Klösch, Bettina; Jacobsen, Anne; Naschberger, Elisabeth; Brunner, Maximilian; Krautz, Christian; Trufa, Denis; Sirbu, Horia; Lang, Roland; et al. (Frontiers in Immunology, 2022)
Airway infection is a major cause of mortality worldwide. The identification of new mechanisms aiding in effective host immune response is therefore required. Here, we show that the specific depletion of the pleural immune cell compartment during bacterial pneumonia resulted in a reduced pulmonary immune response and increased mortality in mice. Bacterial airway infection provoked early pleural space (PS) inflammation characterized by innate response activator (IRA) B cell development and pleural large resident macrophage (LRM) necroptosis, the repopulation of LRMs being driven by cellular proliferation in situ. Necroptotic LRMs amplified PS inflammation by stimulating pleural Mincle-expressing macrophages whereas IRA B cells contributed partially to GM-CSF-induced PS inflammation. Upon pulmonary infection, the induction of PS inflammation resulted in reduced bacterial burden whereas the specific depletion of pleural resident macrophages led to increased mortality and bacterial burden and reduced pulmonary immunity. Moreover, mice in which B cells were unable to produce GM-CSF exhibited reduced CD103+ dendritic cells and reduced CD4+ T cell numbers in the draining lymph node. Altogether, our results describe a previously unrecognized mechanism of pleural space inflammation necessary for effective protection against bacterial airway infection.
CRIS-Team Scopus Importer:2022-05-13
Keywords: bacterial airway infection; IRA B cells; mincle; necroptosis; pleural resident macrophages; pleural space

Pneumococcal vaccination (2): Plea for the recommendations of the Standing Committee on Vaccination (STIKO) Plädoyer für STIKO-Empfehlungen - Falkenhorst, Gerhard; Leidel, Jan; Bogdan, Christian (Deutsches Ärzteblatt international, 2017)
CRIS-Team Scopus Importer:2024-02-26

Pneumokokkenimpfung im Säuglings- und im Kleinkindalter: Epidemiologische und immunologische Basis der pädiatrischen Pneumokokkenimpfung - Vygen-Bonnet, Sabine; Schlaberg, Johanna; Kremer-Flach, Katrin; Perriat, Delphine; Bogdan, Christian (Monatsschrift Kinderheilkunde, 2024)
Streptococcus pneumoniae causes various childhood diseases. Invasive pneumococcal diseases (IPD) are rare. They mainly affect infants and toddlers and can have a severe or fatal course. Pneumococcal vaccines are the most effective form of prevention. This article provides an overview of the current epidemiological situation of IPD in childhood in Germany, the available vaccines and the immunological basis of pediatric pneumococcal vaccination. Data from the German Paediatric Surveillance Unit (GPSU) on IPD in children and adolescents under 16 years of age were analyzed. In addition, published data on the serotype distribution, the safety and effectiveness of pneumococcal conjugate vaccines (PCV) and vaccination coverage in Germany are presented. The pneumococcal immune defence and the mode of action of conjugate vaccines as well as the current recommendations of the Standing Committee on Vaccination (STIKO) at the Robert Koch Institute and aspects of its implementation are explained. As the main disease burden of IPD is in infancy, the STIKO recommends early pneumococcal vaccination for all infants as well as for children and adolescents with certain underlying diseases. Nevertheless, in Germany currently around 25% of all children up to their 2nd birthday are not or not fully immunized against pneumococci.
CRIS-Team Scopus Importer:2024-03-22
Keywords: Conjugate vaccine; Infants; Invasive pneumococcal disease; Meningitis; pneumococcal; Sepsis

Practicability of hygienic wrapping of touchscreen operated mobile devices in a clinical setting - Hammon, Matthias; Kunz, Hans Bernd; Dinzl, Veronika; Kammerer, Ferdinand J.; Schwab, Siegfried; Bogdan, Christian; Uder, Michael; Schlechtweg, Philipp (PLoS ONE, 2014)
To prove effectiveness of wrapping tablet computers in order to reduce microbiological contamination and to evaluate whether a plastic bag-covered tablet leads to impaired user satisfaction or touchscreen functionality.Within a period of 11 days 115 patients were provided with a tablet computer while waiting for their magnetic resonance imaging examination. Every day the contamination of the surface of the tablet was determined before the first and after the final use. Before the device was handed over to a patient, it was enclosed in a customized single-use plastic bag, which was analyzed for bacterial contamination after each use. A questionnaire was applied to determine whether the plastic bag impairs the user satisfaction and the functionality of the touchscreen.Following the use by patients the outside of the plastic bags was found to be contaminated with various bacteria (657.5 ± 368.5 colony forming units/day); some of them were potentially pathogenic. In contrast, the plastic bag covered surface of the tablet was significantly less contaminated (1.7 ± 1.9 colony forming units/day). Likewise, unused plastic bags did not show any contamination. 11% of the patients reported problems with the functionality of the touchscreen. These patients admitted that they had never used a tablet or a smartphone before.Tablets get severely contaminated during usage in a clinical setting. Wrapping with a customized single-use plastic bag significantly reduces microbiological contamination of the device, protects patients from the acquisition of potentially pathogenic bacteria and hardly impairs the user satisfaction and the functionality of the touchscreen.
EVALuna2:7657

Precision size and refractive index analysis of weakly scattering nanoparticles in polydispersions - Kashkanova, Anna D.; Blessing, Martin; Gemeinhardt, Andre; Soulat, Didier; Sandoghdar, Vahid (Nature Methods, 2022)
Characterization of the size and material properties of particles in liquid suspensions is in very high demand, for example, in the analysis of colloidal samples or of bodily fluids such as urine or blood plasma. However, existing methods are limited in their ability to decipher the constituents of realistic samples. Here we introduce iNTA as a new method that combines interferometric detection of scattering with nanoparticle tracking analysis to reach unprecedented sensitivity and precision in determining the size and refractive index distributions of nanoparticles in suspensions. After benchmarking iNTA with samples of colloidal gold, we present its remarkable ability to resolve the constituents of various multicomponent and polydisperse samples of known origin. Furthermore, we showcase the method by elucidating the refractive index and size distributions of extracellular vesicles from Leishmania parasites and human urine. The current performance of iNTA already enables advances in several important applications, but we also discuss possible improvements.
CRIS-Team Scopus Importer:2022-05-20

Predicting T cell receptor functionality against mutant epitopes - Drost, Felix; Dorigatti, Emilio; Straub, Adrian; Hilgendorf, Philipp; Wagner, Karolin I.; Heyer, Kersten; López Montes, Marta; Bischl, Bernd; Busch, Dirk H.; Schober, Kilian; Schubert, Benjamin (Cell Genomics, 2024)
Cancer cells and pathogens can evade T cell receptors (TCRs) via mutations in immunogenic epitopes. TCR cross-reactivity (i.e., recognition of multiple epitopes with sequence similarities) can counteract such escape but may cause severe side effects in cell-based immunotherapies through targeting self-antigens. To predict the effect of epitope point mutations on T cell functionality, we here present the random forest-based model Predicting T Cell Epitope-Specific Activation against Mutant Versions (P-TEAM). P-TEAM was trained and tested on three datasets with TCR responses to single-amino-acid mutations of the model epitope SIINFEKL, the tumor neo-epitope VPSVWRSSL, and the human cytomegalovirus antigen NLVPMVATV, totaling 9,690 unique TCR-epitope interactions. P-TEAM was able to accurately classify T cell reactivities and quantitatively predict T cell functionalities for unobserved single-point mutations and unseen TCRs. Overall, P-TEAM provides an effective computational tool to study T cell responses against mutated epitopes.
CRIS-Team Scopus Importer:2024-09-13
Keywords: active learning; cross-reactivity; deep mutational scan; epitope; machine learning; mutation; T cell receptor; TCR-epitope prediction

Presence of Infected Gr-1intCD11bhiCD11cint Monocytic Myeloid Derived Suppressor Cells Subverts T Cell Response and Is Associated With Impaired Dendritic Cell Function in Mycobacterium avium-Infected Mice - Abdissa, Ketema; Nerlich, Andreas; Beineke, Andreas; Ruangkiattikul, Nanthapon; Pawar, Vinay; Heise, Ulrike; Janze, Nina; Falk, Christine; Bruder, Dunja; Schleicher, Ulrike; Bogdan, Christian; Weiss, Siegfried; et al. (Frontiers in Immunology, 2018)
Myeloid-derived suppressor cells (MDSC) are immature myeloid cells with immunomodulatory function. To study the mechanism by which MDSC affect antimicrobial immunity, we infected mice with two M. avium strains of differential virulence, highly virulent Mycobacterium avium subsp. avium strain 25291 (MAA) and low virulent Mycobacterium avium subsp. hominissuis strain 104 (MAH). Intraperitoneal infection with MAA, but not MAH, caused severe disease and massive splenic infiltration of monocytic MDSC (M-MDSC; Gr-1intCD11bhiCD11cint) expressing inducible NO synthase (Nos2) and bearing high numbers of mycobacteria. Depletion experiments demonstrated that M-MDSC were essential for disease progression. NO production by M-MDSC influenced antigen-uptake and processing by dendritic cells and proliferation of CD4+ T cells. M-MDSC were also induced in MAA-infected mice lacking Nos2. In these mice CD4+ T cell expansion and control of infection were restored. However, T cell inhibition was only partially relieved and arginase (Arg) 1-expressing M-MDSC were accumulated. Likewise, inhibition of Arg1 also partially rescued T cell proliferation. Thus, mycobacterial virulence results in the induction of M-MDSC that block the T cell response in a Nos2- and Arg1-dependent manner.
EVALuna2:36424

Primary cutaneous cryptococcosis in an eight-year-old immunocompetent child: how to treat? - Lenz, D.; Held, Jürgen; Goerke, S.; Wagner, Dirk; Tintelnot, K.; Henneke, P.; Hufnagel, M. (Klinische Pädiatrie, 2015)
Here we report on a case of primary cryptococcal skin infection in an immunocompetent 8-year-old boy. The infection first manifested itself as a subcutaneous abscess around the proximal joint of his right thumb after a minor injury from contact with a thorny shrub. After surgical incision and drainage was performed, Cryptococcus neoformans var. neoformans was the only pathogen cultured from the lesion. An agglutination test for the capsular antigen in serum displayed negative results and the immunological work-up revealed no underlying immunodeficiency. A "watch and wait" strategy - one without systemic antifungal treatment - was adopted and this resulted in uneventful healing. In summary, primary cryptococcal skin infections in immunocompetent hosts may be managed successfully by surgical treatment in combination with careful clinical follow-up. This approach may help avoid unnecessary antimicrobial treatments.
EVALuna2:7712

Prior flavivirus immunity skews the yellow fever vaccine response to cross-reactive antibodies with potential to enhance dengue virus infection - Santos-Peral, Antonio; Luppa, Fabian; Goresch, Sebastian; Nikolova, Elena; Zaucha, Magdalena; Lehmann, Lisa; Dahlstroem, Frank; Karimzadeh, Hadi; Thorn-Seshold, Julia; Winheim, Elena; Schuster, Ev-Marie; Dobler, Gerhard; et al. (Nature Communications, 2024)
The yellow fever 17D vaccine (YF17D) is highly effective but is frequently administered to individuals with pre-existing cross-reactive immunity, potentially impacting their immune responses. Here, we investigate the impact of pre-existing flavivirus immunity induced by the tick-borne encephalitis virus (TBEV) vaccine on the response to YF17D vaccination in 250 individuals up to 28 days post-vaccination (pv) and 22 individuals sampled one-year pv. Our findings indicate that previous TBEV vaccination does not affect the early IgM-driven neutralizing response to YF17D. However, pre-vaccination sera enhance YF17D virus infection in vitro via antibody-dependent enhancement (ADE). Following YF17D vaccination, TBEV-pre-vaccinated individuals develop high amounts of cross-reactive IgG antibodies with poor neutralizing capacity. In contrast, TBEV-unvaccinated individuals elicit a non-cross-reacting neutralizing response. Using YF17D envelope protein mutants displaying different epitopes, we identify quaternary dimeric epitopes as the primary target of neutralizing antibodies. Additionally, TBEV-pre-vaccination skews the IgG response towards the pan-flavivirus fusion loop epitope (FLE), capable of mediating ADE of dengue and Zika virus infections in vitro. Together, we propose that YF17D vaccination conceals the FLE in individuals without prior flavivirus exposure but favors a cross-reactive IgG response in TBEV-pre-vaccinated recipients directed to the FLE with potential to enhance dengue virus infection.
CRIS-Team Scopus Importer:2024-03-08

Processing and secretion of guanylate binding protein-1 depend on inflammatory caspase activity - Naschberger, Elisabeth; Geissdorfer, Walter; Bogdan, Christian; Tripal, Philipp; Kremmer, Elisabeth; Stürzl, Michael; Britzen-Laurent, Nathalie (Journal of Cellular and Molecular Medicine, 2017)
Human guanylate binding protein-1 (GBP-1) belongs to the family of large GTPases. The expression of GBP-1 is inducible by inflammatory cytokines, and the protein is involved in inflammatory processes and host defence against cellular pathogens. GBP-1 is the first GTPase which was described to be secreted by eukaryotic cells. Here, we report that precipitation of GBP-1 with GMP-agarose from cell culture supernatants co-purified a 47-kD fragment of GBP-1 (p47-GBP-1) in addition to the 67-kD full-length form. MALDI-TOF sequencing revealed that p47-GBP-1 corresponds to the C-terminal helical part of GBP-1 and lacks most of the globular GTPase domain. In silico analyses of protease target sites, together with cleavage experiments in vitro and in vivo, showed that p67-GBP-1 is cleaved by the inflammatory caspases 1 and 5, leading to the formation of p47-GBP-1. Furthermore, the secretion of p47-GBP-1 was found to occur via a non-classical secretion pathway and to be dependent on caspase-1 activity but independent of inflammasome activation. Finally, we showed that p47-GBP-1 represents the predominant form of secreted GBP-1, both in cell culture supernatants and, in vivo, in the cerebrospinal fluid of patients with bacterial meningitis, indicating that it may represent the biologically active form of extracellular GBP-1. These findings confirm the involvement of caspase-1 in non-classical secretion mechanisms and open novel perspectives for the extracellular function of secreted GBP-1.
EVALuna2:7752

Proliferation-independent GM-CSF and M-CSF signals control monocyte conversion into monocytic myeloid-derived suppressor cells - Ribechini, E.; Hutchinson, J. A.; Hergovits, S.; Heuer, M.; Lucas, J.; Schleicher, Ulrike; Garrote, A. L. Jordan; Potter, S. J.; Riquelme, P.; Brackmann, H.; Mueller, N.; Raifer, H.; et al. (2017)
EVALuna2:33309

Protection against RNA-induced liver damage by myeloid cells requires type I interferon and IL-1 receptor antagonist in mice - Conrad, Elea; Resch, Theresa K.; Gogesch, Patricia; Kalinke, Ulrich; Bechmann, Ingo; Bogdan, Christian; Waibler, Zoe (Hepatology, 2014)
Cell types and mechanisms involved in type I interferon (IFN)-mediated anti-inflammatory effects are poorly understood. Upon injection of artificial double-stranded RNA (poly(I:C)), we observed severe liver damage in type I IFN-receptor (IFNAR) chain 1-deficient mice, but not in wild-type (WT) controls. Studying mice with conditional IFNAR ablations revealed that IFNAR triggering of myeloid cells is essential to protect mice from poly(I:C)-induced liver damage. Accordingly, in poly(I:C)-treated WT, but not IFNAR-deficient mice, monocytic myeloid-derived suppressor cells (MDSCs) were recruited to the liver. Comparing WT and IFNAR-deficient mice with animals deficient for the IFNAR on myeloid cells only revealed a direct IFNAR-dependent production of the anti-inflammatory cytokine interleukin-1 receptor antagonist (IL-1RA) that could be assigned to liver-infiltrating cells. Upon poly(I:C) treatment, IFNAR-deficient mice displayed both a severe lack of IL-1RA production and an increased production of proinflammatory IL-1?, indicating a severely imbalanced cytokine milieu in the liver in absence of a functional type I IFN system. Depletion of IL-1? or treatment with recombinant IL-1RA both rescued IFNAR-deficient mice from poly(I:C)-induced liver damage, directly linking the deregulated IL-1? and IL-1RA production to liver pathology. Conclusion: Type I IFN signaling protects from severe liver damage by recruitment of monocytic MDSCs and maintaining a balance between IL-1? and IL-1RA production.
EVALuna2:7653

Protein secretion systems and adhesins: the molecular armory of Gram-negative pathogens. - Gerlach, Roman; Hensel, Michael (International Journal of Medical Microbiology, 2007)
Protein secretion is a basic cellular function found in organisms of all kingdoms of life. Gram-negative bacteria have evolved a remarkable number of pathways for the transport of proteins across the cell envelope. The secretion systems fulfill general cellular functions but are also essential for pathogenic bacteria during the interaction with eukaryotic host cells. Secretion systems range from relatively simple structures such as type I secretion systems composed of three subunits that only secrete one substrate protein to complex machines such as type III and IV secretion systems composed of more than 20 subunits that can translocate large sets of effector proteins into eukaryotic target cells. In this review, the main structural and functional features of secretion systems are described. One subgroup of substrate proteins of secretion systems are protein adhesins. Despite the conserved function in binding to host cell ligands or to abiotic surfaces, the assembly of the various bacterial adhesins is highly divergent. Here we give an overview on the recent understanding of the assembly of fimbrial and non-fimbrial adhesins and the role of type I, III and V secretion systems and specialized branches of the general secretion pathway in their biogenesis.

Proteome Analysis Reveals the Conidial Surface Protein CcpA Essential for Virulence of the Pathogenic Fungus Aspergillus fumigatus - Voltersen, Vera; Blango, Matthew G.; Herrmann, Sahra; Schmidt, Franziska; Heinekamp, Thorsten; Strassburger, Maria; Krueger, Thomas; Bacher, Petra; Lother, Jasmin; Weiss, Esther; Huenniger, Kerstin; Liu, Hong; et al. (Mbio, 2018)
Aspergillus fumigatus is a common airborne fungal pathogen of humans and a significant source of mortality in immunocompromised individuals. Here, we provide the most extensive cell wall proteome profiling to date of A. fumigatus resting conidia, the fungal morphotype pertinent to first contact with the host. Using liquid chromatography-tandem mass spectrometry (LC-MS/MS), we identified proteins within the conidial cell wall by hydrogen-fluoride (HF)-pyridine extraction and proteins exposed on the surface using a trypsin-shaving approach. One protein, designated conidial cell wall protein A (CcpA), was identified by both methods and was found to be nearly as abundant as hydrophobic rodlet layer-forming protein RodA. CcpA, an amphiphilic protein, like RodA, peaks in expression during sporulation on resting conidia. Despite high cell wall abundance, the cell surface structure of ΔccpA resting conidia appeared normal. However, trypsin shaving of ΔccpA conidia revealed novel surface-exposed proteins not detected on conidia of the wild-type strain. Interestingly, the presence of swollen ΔccpA conidia led to higher activation of neutrophils and dendritic cells than was seen with wild-type conidia and caused significantly less damage to epithelial cells in vitro In addition, virulence was highly attenuated when cortisone-treated, immunosuppressed mice were infected with ΔccpA conidia. CcpA-specific memory T cell responses were detectable in healthy human donors naturally exposed to A. fumigatus conidia, suggesting a role for CcpA as a structural protein impacting conidial immunogenicity rather than possessing a protein-intrinsic immunosuppressive effect. Together, these data suggest that CcpA serves as a conidial stealth protein by altering the conidial surface structure to minimize innate immune recognition.IMPORTANCE The mammalian immune system relies on recognition of pathogen surface antigens for targeting and clearance. In the absence of immune evasion strategies, pathogen clearance is rapid. In the case of Aspergillus fumigatus, the successful fungus must avoid phagocytosis in the lung to establish invasive infection. In healthy individuals, fungal spores are cleared by immune cells; however, in immunocompromised patients, clearance mechanisms are impaired. Here, using proteome analyses, we identified CcpA as an important fungal spore protein involved in pathogenesis. A. fumigatus lacking CcpA was more susceptible to immune recognition and prompt eradication and, consequently, exhibited drastically attenuated virulence. In infection studies, CcpA was required for virulence in infected immunocompromised mice, suggesting that it could be used as a possible immunotherapeutic or diagnostic target in the future. In summary, our report adds a protein to the list of those known to be critical to the complex fungal spore surface environment and, more importantly, identifies a protein important for conidial immunogenicity during infection.
EVALuna2:36419

Proteomics of diphtheria toxoid vaccines reveals multiple proteins that are immunogenic and may contribute to protection of humans against Corynebacterium diphtheriae - Möller, Jens; Kraner, Max; Sonnewald, Uwe; Sangal, Vartul; Tittlbach, Hannes; Winkler, Julia; Winkler, Thomas; Melnikov, Vyacheslav; Lang, Roland; Sing, Andreas; Mattos-Guaraldi, Ana Luiza; Burkovski, Andreas (Vaccine, 2019)
Introduced for mass immunization in the 1920s, vaccines against diphtheria are among the oldest and safest vaccines known. The basic principle of their production is the inactivation of purified diphtheria toxin by formaldehyde cross-linking, which converts the potentially fatal toxin in a completely harmless protein aggregate, which is still immunogenic. Since in addition to diphtheria toxin also other proteins may be secreted by Corynebacterium diphtheriae during cultivation, we assumed that diphtheria toxoid might not be the only component present in the vaccine. To address this question, we established a protocol to reverse formaldehyde cross-linking and carried out mass spectrometric analyses. Different secreted, membrane-associated and cytoplasmic proteins of C. diphtheriae were detected in several vaccine preparations from across the world. Based on these results, bioinformatics and Western blot analyses were applied to characterize if these proteins are immunogenic and may therefore support protection against C. diphtheriae. In frame of this study, we could show that the C. diphtheriae toxoid vaccines induce antibodies against different C. diphtheriae proteins and against diphtheria toxin secreted by Corynebacterium ulcerans, an emerging pathogen which is outnumbering C. diphtheriae as cause of diphtheria-like illness in Western Europe.
CRIS-Team Scopus Importer:2019-05-09
Keywords: Corynebacteria; Corynebacterium ulcerans; Exoproteome; Mass spectrometry; Proteomics; Secretome; Vaccination

Pseudomonas aeruginosa-Derived Volatile Sulfur Compounds Promote Distal Aspergillus fumigatus Growth and a Synergistic Pathogen-Pathogen Interaction That Increases Pathogenicity in Co-infection - Scott, Jennifer; Sueiro-Olivares, Monica; Ahmed, Wadar; Heddergott, Christoph; Zhao, Can; Thomas, Riba; Bromley, Michael; Latge, Jean-Paul; Krappmann, Sven; Fowler, Stephen; Bignell, Elaine; Amich, Jorge (Frontiers in Microbiology, 2019)
Pathogen-pathogen interactions in polymicrobial infections are known to directly impact, often to worsen, disease outcomes. For example, co-infection with Pseudomonas aeruginosa and Aspergillus fumigatus, respectively the most common bacterial and fungal pathogens isolated from cystic fibrosis (CF) airways, leads to a worsened prognosis. Recent studies of in vitro microbial cross-talk demonstrated that P. aeruginosa-derived volatile sulfur compounds (VSCs) can promote A. fumigatus growth in vitro. However, the mechanistic basis of such cross-talk and its physiological relevance during co-infection remains unknown. In this study we combine genetic approaches and GC-MS-mediated volatile analysis to show that A. fumigatus assimilates VSCs via cysteine (CysB)- or homocysteine (CysD)-synthase. This process is essential for utilization of VSCs as sulfur sources, since P. aeruginosa-derived VSCs trigger growth of A. fumigatus wild-type, but not of a 1cysB1cysD mutant, on sulfur-limiting media. P. aeruginosa produces VSCs when infecting Galleria mellonella and co-infection with A. fumigatus in this model results in a synergistic increase in mortality and of fungal and bacterial burdens. Interestingly, the increment in mortality is much greater with the A. fumigatus wild-type than with the 1cysB1cysD mutant. Therefore, A. fumigatus' ability to assimilate P. aeruginosa derived VSCs significantly triggers a synergistic association that increases the pathobiology of infection. Finally, we show that P. aeruginosa can promote fungal growth when growing on substrates that resemble the lung environment, which suggests that this volatile based synergism is likely to occur during co-infection of the human respiratory airways.
CRIS-Team WoS Importer:2019-11-01

Q-GAPS - Q Fever - German Interdisciplinary Program for reSearch. The Q Fever Information and Research Network - Dimitrios, Frangoulidis; Martin, Ganter; Martin, Runge; Amely, Campe; Katja, Mertens-Scholz; Michael, Knittler; Christian, Berens; Lührmann, Anja; Silke, Fischer (GESUNDHEITSWESEN, 2022)
CRIS-Team WoS Importer:2022-06-03

Rahmen – zwischen innen und aussen: Beiträge zur Theorie und Geschichte - Möseneder, Karl; Körner, Heinrich (Reimer, 2010)

Rapid Healing of Cutaneous Leishmaniasis by High-Frequency Electrocauterization and Hydrogel Wound Care with or without DAC N-055: A Randomized Controlled Phase IIa Trial in Kabul - Jebran, Ahmad Fawad; Schleicher, Ulrike; Steiner, Reto; Wentker, Pia; Mahfuz, Farouq; Stahl, Hans-Christian; Amin, Faquir Mohammad; Bogdan, Christian; Stahl, Kurt-Wilhelm (Plos Neglected Tropical Diseases, 2014)
Anthroponotic cutaneous leishmaniasis (CL) due to Leishmania (L.) tropica infection is a chronic, frequently disfiguring skin disease with limited therapeutic options. In endemic countries healing of ulcerative lesions is often delayed by bacterial and/or fungal infections. Here, we studied a novel therapeutic concept to prevent superinfections, accelerate wound closure, and improve the cosmetic outcome of ACL.From 2004 to 2008 we performed a two-armed, randomized, double-blinded, phase IIa trial in Kabul, Afghanistan, with patients suffering from L. tropica CL. The skin lesions were treated with bipolar high-frequency electrocauterization (EC) followed by daily moist-wound-treatment (MWT) with polyacrylate hydrogel with (group I) or without (group II) pharmaceutical sodium chlorite (DAC N-055). Patients below age 5, with facial lesions, pregnancy, or serious comorbidities were excluded. The primary, photodocumented outcome was the time needed for complete lesion epithelialization. Biopsies for parasitological and (immuno)histopathological analyses were taken prior to EC (1(st)), after wound closure (2(nd)) and after 6 months (3(rd)). The mean duration for complete wound closure was short and indifferent in group I (59 patients, 43.1 d) and II (54 patients, 42 d; p = 0.83). In patients with Leishmania-positive 2(nd) biopsies DAC N-055 caused a more rapid wound epithelialization (37.2 d vs. 58.3 d; p = 0.08). Superinfections occurred in both groups at the same rate (8.8%). Except for one patient, reulcerations (10.2% in group I, 18.5% in group II; p = 0.158) were confined to cases with persistent high parasite loads after healing. In vitro, DAC N-055 showed a leishmanicidal effect on pro- and amastigotes.Compared to previous results with intralesional antimony injections, the EC plus MWT protocol led to more rapid wound closure. The tentatively lower rate of relapses and the acceleration of wound closure in a subgroup of patients with parasite persistence warrant future studies on the activity of DAC N-055.ClinicalTrails.gov NCT00947362.
EVALuna2:7647

Rapid phenotypic antimicrobial susceptibility testing of Gram-negative rods directly from positive blood cultures using the novel Q-linea ASTar system - Esse, Jan; Träger, Johannes; Valenza, Giuseppe; Bogdan, Christian; Held, Jürgen (Journal of Clinical Microbiology, 2023)
Adequate and timely antibiotic therapy is crucial for the treatment of sepsis. Innovative systems, like the Q-linea ASTar, have been developed to perform rapid antimicrobial susceptibility testing (AST) directly from positive blood cultures (BCs). We conducted a prospective study to evaluate ASTar under real-life conditions with a focus on time-to-result and impact on antimicrobial therapy. Over 2 months, all positive BCs that showed Gram-negative rods upon microscopy were tested with the ASTar and our standard procedure (VITEK 2 from short-term culture). Additionally, we included multidrug-resistant Gram-negative bacteria from our archive. Both methods were compared to broth microdilution. In total, 78 bacterial strains (51 prospective and 27 archived) were tested. ASTar covered 94% of the species encountered. The categorical and essential agreement was 95.6% and 90.7%, respectively. ASTar caused 2.4% minor, 2.0% major, and 2.4% very major errors. The categorical agreement was similar to standard procedure. The average time between BC sampling and the availability of the antibiogram for the attending physician was 28 h 49 min for ASTar and 44 h 18 min for standard procedure. ASTar correctly identified all patients who required an escalation of antimicrobial therapy and 75% of those who were eligible for de-escalation. In conclusion, ASTar provided reliable AST results and significantly shortened the time to obtain an antibiogram. However, the percentage of patients that will profit from ASTar in a low-resistance setting is limited, and it is currently unclear if a change of therapy 29 h after BC sampling will have a significant impact on the patient’s prognosis.
CRIS-Team Scopus Importer:2023-12-08
Keywords: AST; blood stream infection; RAST; scum plate method; sepsis; VITEK

Ratiometric luminescence 2D in vivo imaging and monitoring of mouse skin oxygenation - Hofmann, Julian; Meier, Robert J.; Mahnke, Alexander; Schatz, Valentin; Brackmann, Florian; Trollmann, Regina; Bogdan, Christian; Liebsch, Gregor; Wang, Xu Dong; Wolfbeis, Otto S.; Jantsch, Jonathan (Methods and Applications in Fluorescence, 2013)
Tissue oxygenation plays a critical role in the pathogenesis of various diseases, but non-invasive, robust and user-friendly methods for its measurement in vivo still need to be established. Here, we are presenting an in vivo oxygen-detection system that uses ratiometric luminescence imaging (RLI) as a readout scheme to determine the skin oxygen tension of mouse hind footpads via side-by-side comparison with more established techniques including luminescence-lifetime imaging using planar sensor films and the polarographic electrode as the gold standard. We also demonstrate that this technology allows the detection of changes in mouse skin tissue oxygenation induced by subjecting mice to systemic hypoxia. The data demonstrate oxygen imaging based on RLI to be a most useful tool for reliably and easily analyzing and monitoring skin tissue oxygenation in vivo. This technology will advance our understanding of local regulation of skin tissue oxygenation in various disease conditions.
CRIS-Team Scopus Importer:2024-02-26

Rational clinical use of near-patient analytical systems for molecular detection of infectious agents - Luppa, Peter B.; Rabenau, Holger F.; GÃssler, Norbert; Huzly, Daniela; Nauck, Matthias; Reischl, Udo; Schoerner, Christoph; Zeichhardt, Heinz (Journal of Laboratory Medicine, 2021)
Tests for diagnosing infectious diseases (ID-POCT) play a special role among the available point-of-care testing (POCT) methods. A systematic literature search was performed in PubMed. Based on this literature review and our own experience, aspects associated with using molecular biological methods in the diagnostic amplification of pathogen DNA/RNA (nucleic acid testing = NAT) and/or signal amplification were discussed in an interdisciplinary manner. This resulted in the following recommendations for the near-patient use of NAT methods. Due to the current rise in the use of near-patient NAT testing (e.g., using disposable cartridges), recommendations are made for their implementation and appropriate clinical use in the hospital setting. Particular emphasis is placed on the analytical quality of the results. Furthermore, internal best-practice rules and selection criteria are proposed to ensure rapid diagnosis. Equally important are a medically valid interpretation of results and compliance with hygiene requirements. These recommendations emphasize that near-patient NAT should always be procured in conjunction with a (preferably) multidisciplinary institution responsible for POCT and knowledge of the test specifications and risks, as well as quality assurance need to be in place before they are carried out. These recommendations are intended to improve patient safety and to avoid economically questionable expenditures.
CRIS-Team Scopus Importer:2021-05-07
Keywords: infectious agents; nucleic acid testing; POCT

Reactogenicity correlates only weakly with humoral immunogenicity after COVID-19 vaccination with BNT162b2 mRNA (Comirnaty®) - Held, Jürgen; Esse, Jan; Tascilar, Koray; Steininger, Philipp; Schober, Kilian; Irrgang, Pascal; Alsalameh, Rayya; Tenbusch, Matthias; Seggewies, Christof; Bogdan, Christian (Vaccines, 2021)
mRNA vaccines against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), such as BNT162b2 (Comirnaty®), have proven to be highly immunogenic and efficient but also show marked reactogenicity, leading to adverse effects (AEs). Here, we analyzed whether the severity of AEs predicts the antibody response against the SARS-CoV-2 spike protein. Healthcare workers without prior SARS-CoV-2 infection, who received a prime-boost vaccination with BNT162b2, completed a standardized electronic questionnaire on the duration and severity of AEs. Serum specimens were collected two to four weeks after the boost vaccination and tested with the COVID-19 ELISA IgG (Vircell-IgG), the LIAISON® SARS-CoV-2 S1/S2 IgG CLIA (DiaSorin-IgG) and the iFlash-2019-nCoV NAb surrogate neutralization assay (Yhlo-NAb). A penalized linear regression model fitted by machine learning was used to correlate AEs with antibody levels. Eighty subjects were enrolled in the study. Systemic, but not local, AEs occurred more frequently after the boost vaccination. Elevated SARS-CoV-2 IgG antibody levels were measured in 92.5% of subjects with Vircell-IgG and in all subjects with DiaSorin-IgG and Yhlo-NAb. Gender, age and BMI showed no association with the antibody levels or with the AEs. The linear regression model identified headache, malaise and nausea as AEs with the greatest variable importance for higher antibody levels (Vircell-IgG and DiaSorin-IgG). However, the model performance for predicting antibody levels from AEs was very low for Vircell-IgG (squared correlation coefficient r2 = 0.04) and DiaSorin-IgG (r2 = 0.06). AEs did not predict the surrogate neutralization (Yhlo-NAb) results. In conclusion, AEs correlate only weakly with the SARS-CoV-2 spike protein antibody levels after COVID-19 vaccination with BNT162b2 mRNA.
CRIS-Team Scopus Importer:2021-10-22
Keywords: Adverse effects; Adverse reactions; Antibody; BioNTech; Machine learning; MRNA vaccine; Pfizer; SARS-CoV-2; Side effects

Recent advances in understanding basophil functionsin vivo - Vöhringer, David (F1000Research, 2017)
Basophils are mainly known as pro-inflammatory effector cells associated with allergy and helminth infections. Although they were identified over 130 years ago, theirin vivofunctions are still poorly understood. New insights into basophil development and function have been gained by the development of various transgenic mouse lines and staining techniques to detect and purify these cells from different organs. Several studies over the past few years have identified unexpected functions for basophils, including immunomodulatory properties and interactions with other immune cells. Here, I summarize and discuss the main findings.
EVALuna2:33474

Recognition of candida albicans and role of innate type 17 immunity in oral candidiasis - Pavlova, Anna; Sharafutdinov, Irshad (Microorganisms, 2020)
Candida albicans is an opportunistic pathogenic fungus considered to be a common member of the human microflora. Similar to some other opportunistic microbes, C. albicans can invade and benefit from its host when the immune status of that host is weakened. Most often this happens to immunocompromised individuals, leading to the infection of oral and vaginal mucosae or the systemic spread of the pathogen throughout the entire body. Oropharyngeal candidiasis (OPC) occurs in up to 90 percent of patients with acquired immunodeficiency syndrome (AIDS), making it the most frequent opportunistic infection for this group. Upon first signs of fungal invasion, a range of host signaling activates in order to eliminate the threat. Epithelial and myeloid type cells detect C. albicans mainly through receptor tyrosine kinases and pattern-recognition receptors. This review provides an overview of downstream signaling resulting in an adequate immune response through the activation of various transcription factors. The study discusses recent advances in research of the interleukin-17 (IL-17) producing innate cells, including natural T helper 17 (nTh17) cells, γδ T cells, invariant natural killer T (iNKT) cells and type 3 innate lymphoid cells (ILC3) that are involved in response to oral C. albicans infections.
CRIS-Team Scopus Importer:2020-09-18
Keywords: Candida albicans; IL-17; ILC3; INKT; Innate immunity; Natural Th17 cells; Receptor tyrosine kinase; γδ T cells

Recombinant protein production and purification of SiiD, SiiE and SiiF - Components of the SPI4-encoded type I secretion system from Salmonella Typhimurium - Klingl, Stefan; Kordes, Sina; Schmid, Benedikt; Gerlach, Roman; Hensel, Michael; Muller, Yves (Protein Expression and Purification, 2020)
In humans, Salmonella enterica infections are responsible for a plethora of medical conditions. These include intestinal inflammation and typhoid fever. The initial contact between Salmonella and polarized epithelial cells is established by the SPI4-encoded type I secretion system (T1SS), which secretes SiiE, a giant non-fimbrial adhesin. We have recombinantly produced various domains of this T1SS from Salmonella enterica serovar Typhimurium in Escherichia coli for further experimental characterization. We purified three variants of SiiD, the periplasmic adapter protein spanning the space between the inner and outer membrane, two variants of the SiiE N-terminal region and the N-terminal domain of the SiiF ATP-binding cassette (ABC) transporter. In all three proteins, at least one variant yielded high amounts of pure soluble protein. Secondary structure content and cooperative unfolding were investigated by circular dichroism (CD) spectroscopy. Secondary structure contents were in good agreement with estimates derived from SiiD and SiiF homology models or, in case of the SiiE N-terminal region, a secondary structure prediction. For one SiiD variant, protein crystals could be obtained that diffracted X-rays to approximately 4 Å resolution.
CRIS-Team Scopus Importer:2020-04-17
Keywords: Protein expression; Purification; Salmonella; Type I secretion system (T1SS)

Recruitment of highly cytotoxic CD8+ T cell receptors in mild SARS-CoV-2 infection - Wagner, Karolin I.; Mateyka, Laura M.; Jarosch, Sebastian; Grass, Vincent; Weber, Simone; Schober, Kilian; Hammel, Monika; Burrell, Teresa; Kalali, Behnam; Poppert, Holger; Beyer, Henriette; Schambeck, Sophia; et al. (Cell Reports, 2021)
Keywords: CD8+ T cells; cytotoxic T cells; mild COVID-19; SARS-CoV-2 infection; TCR identification; scRNA sequencing; T cell immunity; T cell receptor; TCR engineering

Regulation of eosinophil development and survival - Willebrand, Ralf; Vöhringer, David (Current Opinion in Hematology, 2017)
Eosinophils are a subset of granulocytes generally associated with type 2 immune responses. They can contribute to protection against helminths but also mediate pro-inflammatory functions during allergic immune responses. Only recently, eosinophils were also found to exert many other functions such as regulation of glucose and fat metabolism, thermogenesis, survival of plasma cells, and antitumor activity. The mechanisms that control eosinophil development and survival are only partially understood.Here we review new findings regarding the role of cell-extrinsic and cell-intrinsic factors for eosinophilopoiesis and eosinophil homeostasis. Several reports provide new insights in the regulation of eosinophil development by transcription factors, miRNAs and epigenetic modifications. Danger signals like lipopolysaccharide or alarmins can activate eosinophils but also prolong their lifespan. We further reflect on the observations that eosinophil development is tightly controlled by the unfolded protein stress response and formation of cytoplasmic granules.Eosinophils emerge as important regulators of diverse biological processes. Their differentiation and survival is tightly regulated by factors that are still poorly understood. Newly identified pathways involved in eosinophilopoiesis and eosinophil homeostasis may lead to development of new therapeutic options for treatment of eosinophil-associated diseases.
EVALuna2:25881

Regulation of Lymphocytes by Nitric Oxide - Bogdan, Christian (Humana Press Inc., 2011)
Shortly after the identification of nitric oxide (NO) as a product of macrophages, it was discovered that NO generated by inducible NO synthase (iNOS) inhibits the proliferation of T lymphocytes. Since then, it has become clear that iNOS activity also regulates the development, differentiation, and/or function of various types of T cells and B cells and also affects NK cells. The three key mechanisms underlying the iNOS-dependent immunoregulation are (a) the modulation of signaling processes by NO, (b) the depletion of arginine, and (c) the alteration of accessory cell functions. This chapter highlights important principles of iNOS-dependent immunoregulation of lymphocytes and also reviews more recent evidence for an effect of endothelial or neuronal NO synthase in lymphocytes.
CRIS-Team Scopus Importer:2024-02-26
Keywords: Arginase; B lymphocytes; Endothelial nitric oxide synthase; Inducible nitric oxide synthase; Myeloid (-derived) suppressor cells; Natural killer cells; Neuronal nitric oxide synthase; Nitric oxide; T lymphocytes

Regulation of the humoral type 2 immune response against allergens and helminths - Haase, Paul; Vöhringer, David (European Journal of Immunology, 2020)
The type 2 immune response is associated with helminth infections and allergic inflammation where antibody production of the IgG1 and IgE isotypes can elicit protective or proinflammatory functions. Studies over the past few years revealed important new insights regarding the regulatory mechanisms orchestrating the humoral type 2 immune response. This includes investigations on B-cell extrinsic signals, such IL-4 and IL-21, derived from different T-helper cell subsets or discovery of new follicular helper T cells with regulatory or IgE-promoting activities. In addition, studies on B-cell intrinsic factors required for germinal center formation and class switch recombination, including the transcription factors STAT3, STAT6, and BCL-6, led to a better understanding of these processes in type 2 immune responses. Here, we review the current understanding of mechanisms controlling humoral type 2 immunity in vivo including the generation of IgE-producing plasma cells and the memory IgE response.
CRIS-Team WoS Importer:2021-01-15

Regulation of type 2 immune responses by components of the innate and adaptive immune system - Vöhringer, David (2017)
EVALuna2:33421

Relevance of inducible nitric oxide synthase for immune control of Mycobacterium avium subspecies paratuberculosis infection in mice - Abdissa, Ketema; Ruangkiattikul, Nanthapon; Ahrend, Wiebke; Nerlich, Andreas; Beineke, Andreas; Laarmann, Kristin; Janze, Nina; Lobermeyer, Ulrike; Suwandi, Abdulhadi; Falk, Christine; Schleicher, Ulrike; Weiss, Siegfried; et al. (Virulence, 2020)
Mycobacterium avium subspecies paratuberculosis (MAP) causes Johne's disease (JD), an incurable chronic intestinal bowel disease in ruminants. JD occurs worldwide and causes enormous economic burden in dairy industry. Research on JD pathobiology is hampered by its complexity which cannot completely be mimicked by small animal models. As a model the mouse allows dissecting some pathogenicity features of MAP. However, for unknown reasons MAP exhibits reduced growth in granulomas of infected mice compared to other Mycobacterium avium subspecies. Here, we characterized immune reactions of MAP-infected C57BL/6 mice. After infection, mice appeared fully immunocompetent. A strong antigen-specific T cell response was elicited indicated by IFN gamma production of splenic T cells re-stimulated with MAP antigens. Function of splenic dendritic cells and proliferation of adoptively transferred antigen-specific CD4(+) T cells was unaltered. Isolated splenic myeloid cells from infected mice revealed that MAP resides in CD11b(+) macrophages. Importantly, sorted CD11b(+)CD11c(-) cells expressed high level of type 2 nitric oxide synthase (NOS2) but only low levels of pro- and anti-inflammatory cytokines. Correspondingly, MAP-infected MAC2 expressing myeloid cells in spleen and liver granuloma displayed strong expression of NOS2. In livers of infected Nos2(-/-)mice higher bacterial loads, more granuloma and larger areas of tissue damage were observed 5 weeks post infection compared to wild type mice. In vitro, MAP was sensitive to NO released by a NO-donor. Thus, a strong T cell response and concomitant NOS2/NO activity appears to control MAP infection, but allows development of chronicity and pathogen persistence. A similar mechanism might explain persistence of MAP in ruminants.
CRIS-Team WoS Importer:2020-05-29

Relevant Aspects on cutaneous Leishmaniasis in Mallorca - Burmann, Sven-Niklas; Sunderkoetter, Cord; Boeer-Auer, Almut; Oellig, Frank; Fischer, Marcellus; Bogdan, Christian; Michalowitz, Alena-Lioba; Kreuter, Alexander (Journal der Deutschen Dermatologischen Gesellschaft, 2022)
CRIS-Team WoS Importer:2022-05-13

Relevante Aspekte zur kutanen Leishmaniose auf Mallorca - Burmann, Sven Niklas; Sunderkötter, Cord; Böer-Auer, Almut; Oellig, Frank; Fischer, Marcellus; Bogdan, Christian; Michalowitz, Alena Lioba; Kreuter, Alexander (Journal der Deutschen Dermatologischen Gesellschaft, 2022)
CRIS-Team Scopus Importer:2022-04-29

RELMα-expressing macrophages protect against fatal lung damage and reduce parasite burden during helminth infection - Krljanac, Branislav; Schubart, Christoph; Naumann, Ronald; Wirtz, Stefan; Culemann, Stephan; Krönke, Gerhard; Vöhringer, David (Science immunology, 2019)
Alternatively activated macrophages (AAMs) can contribute to wound healing, regulation of glucose and fat metabolism, resolution of inflammation, and protective immunity against helminths. Their differentiation, tissue distribution, and effector functions are incompletely understood. Murine AAMs express high levels of resistin-like molecule (RELM) α, an effector protein with potent immunomodulatory functions. To visualize RELMα+ macrophages (MΦs) in vivo and evaluate their role in defense against helminths, we generated RELMα reporter/deleter mice. Infection with the helminth Nippostrongylus brasiliensis induced expansion of RELMα+ lung interstitial but not alveolar MΦs in a STAT6-dependent manner. RELMα+ MΦs were required for prevention of fatal lung damage during primary infection. Furthermore, protective immunity was lost upon specific deletion of RELMα+ MΦs during secondary infection. Thus, RELMα reporter/deleter mice reveal compartmentalization of AAMs in different tissues and demonstrate their critical role in resolution of severe lung inflammation and protection against migrating helminths.
CRIS-Team Scopus Importer:2019-06-18

Renal leishmaniasis as unusual cause of nephrotic syndrome in an HIV patient - Amann, Kerstin Ute; Bogdan, Christian; Harrer, Thomas; Rech, Jürgen (Journal of the American Society of Nephrology, 2012)
Renal involvement is a rare complication in HIV-1-infected patients leading to various pathologies and clinical symptoms. In addition to the classic HIV-1-associated nephropathy with collapsing-type focal segmental glomerulosclerosis and characteristic tubulocystic changes, which is more common in Afro-American than in Caucasian HIV-1 patients, immune complex GNs such as membranous GN and membranoproliferative GN are particularly common renal manifestations. Besides HIV-1 itself, a number of opportunistic infections may cause renal disease in HIV-1-infected patients. In this study, we report an unusual case of HIV-1 infection with a severe renal manifestation of systemic leishmaniasis that developed years after repeated visits to Mediterranean countries. The case presents several remarkable clinical, pathologic, and therapeutic aspects that may be important for daily clinical practice. Copyright © 2012 by the American Society of Nephrology.
CRIS-Team Scopus Importer:2021-02-03

Reorganization of the endosomal system in Salmonella-infected cells: the ultrastructure of Salmonella-induced tubular compartments - Krieger, Viktoria; Liebl, David; Zhang, Yuying; Rajashekar, Roopa; Chlanda, Petr; Giesker, Katrin; Chikkaballi, Deepak; Hensel, Michael (PLoS Pathogens, 2014)
During the intracellular life of Salmonella enterica, a unique membrane-bound compartment termed Salmonella-containing vacuole, or SCV, is formed. By means of translocated effector proteins, intracellular Salmonella also induce the formation of extensive, highly dynamic membrane tubules termed Salmonella-induced filaments or SIF. Here we report the first detailed ultrastructural analyses of the SCV and SIF by electron microscopy (EM), EM tomography and live cell correlative light and electron microscopy (CLEM). We found that a subset of SIF is composed of double membranes that enclose portions of host cell cytosol and cytoskeletal filaments within its inner lumen. Despite some morphological similarities, we found that the formation of SIF double membranes is independent from autophagy and requires the function of the effector proteins SseF and SseG. The lumen of SIF network is accessible to various types of endocytosed material and our CLEM analysis of double membrane SIF demonstrated that fluid phase markers accumulate only between the inner and outer membrane of these structures, a space continual with endosomal lumen. Our work reveals how manipulation of the endosomal membrane system by an intracellular pathogen results in a unique tubular membrane compartmentalization of the host cell, generating a shielded niche permissive for intracellular proliferation of Salmonella.
EVALuna2:7670

Reply to Martin and Dauby - Kling, Kerstin; Domingo, Cristina; Bogdan, Christian; Wilder-Smith, Annelies; Harder, Thomas (Clinical Infectious Diseases, 2022)
CRIS-Team WoS Importer:2023-01-06

Reply to Raoult - Wenneras, Christine; Bloemberg, Guido; Bogdan, Christian (Clinical Infectious Diseases, 2014)
EVALuna2:7652

Resistance to antibacterial therapy in pediatric febrile urinary tract infections—a single-center analysis - Raupach, Thomas; Held, Jürgen; Prokosch, Hans-Ulrich; Rascher, Wolfgang; Zierk, Jakob (Journal of Pediatric Urology, 2019)
Background: Febrile urinary tract infections (UTIs) are common serious bacterial infections in childhood and require early diagnosis and antibacterial therapy. However, considerable uncertainty exists regarding the optimal antibacterial agent for primary treatment of pediatric UTIs. Additionally, patterns of susceptibility and resistance change over time and microbiological in vitro resistance is not necessarily associated with treatment failure. Here, we analyzed uropathogens, their resistance patterns, and response to antibacterial treatment in children with acute pyelonephritis. Methods: We used billing codes (international classification of diseases) to identify all inpatients aged 0–18 years with febrile UTIs in a German university tertiary care center from 2009 until 2018. Microbial results were retrieved from the laboratory information system for all children, and treatment regimen and treatment response were analyzed in a subgroup of children. Results: We identified 907 children with acute pyelonephritis; in 590 cases (65%) an uropathogen was detected. Escherichia coli (60.8%), Enterococcus faecalis (13.2%), Klebsiella pneumoniae (7.0%), Proteus spp. (5.2%), and Pseudomonas aeruginosa (4.2%) were the most common pathogens. 353 of 436 E. coli isolates (81.0%) were susceptible or intermediate to aminopenicillin/β-lactamase-inhibitor (BLI) combinations. We examined 52 cases where E. coli was resistant to initial therapy with aminopenicillin/BLI combinations: Therapy was changed in 35 cases (67%) and left unchanged in 17 cases (33%), and we found no significant differences in C-reactive protein and leucocyte count in blood and urine between both groups after 3 days. Conclusions: We present the spectrum of uropathogens and susceptibility test results in pediatric UTIs in a tertiary care center. Our findings suggest a satisfactory response to first-line therapy with aminopenicillin/BLI combinations.
CRIS-Team Scopus Importer:2019-12-03
Keywords: Antibiotic susceptibility/resistance; Escherichia coli; Febrile urinary tract infections; Pediatrics

Resolution and chronicity of Q-fever in the mouse model: Myd88-deficiency and overexpression of IL-10 impairs clearance of Coxiella burnetii Nine Mile Phase II - Kohl, Lisa; Lührmann, Anja; Lang, Roland (2017)
EVALuna2:33413

Resolution of Cutaneous Leishmaniasis and Persistence of Leishmania major in the Absence of Arginase 1 - Paduch, Katrin; Debus, Andrea; Rai, Baplu; Schleicher, Ulrike; Bogdan, Christian (Journal of Immunology, 2019)
Arginase (Arg) 1 is expressed by hematopoietic (e.g., macrophages) and nonhematopoietic cells (e.g., endothelial cells) and converts L-arginine into ornithine and urea. The enzyme is implicated in tissue repair but also antagonizes the production of NO by type 2 NO synthase in myeloid cells and thereby impedes the control of intracellular parasites such as Leishmania major. In this study, we tested whether Arg1 is required for spontaneous healing of acute cutaneous leishmaniasis in C57BL/6 mice and for lifelong parasite persistence in draining lymph nodes (dLNs) of healed mice. In vitro, bone marrow-derived macrophages and lymphoid endothelial cells readily expressed Arg1 in response to IL-4 and/or IL-13, whereas skin or dLN fibroblasts failed to do so, even during hypoxia. In vivo, Arg1 was found in skin lesions and, to a much lower extent, also in dLNs of acutely infected C57BL/6 mice but became undetectable at both sites after healing. Deletion of Arg1 in hematopoietic and endothelial cells using Tie2Cre(+/-) Arg1(fl/fl) C57BL/6 mice abolished the expression of Arg1 in skin lesions and dLNs but did not affect development and resolution of skin lesions, parasite burden, NO production, or host cell tropism of L. major during the acute or persistent phase of infection. Similar to wild-type controls, parasites persisting in Arg1-deficient mice favored NO synthase 2-negative areas and mainly resided in myeloid cells and fibroblasts. We conclude that Arg1 expression by hematopoietic and endothelial cells is completely dispensable for clinical resolution of cutaneous leishmaniasis and for long-term persistence of L. major.
CRIS-Team WoS Importer:2019-03-06

Retinoic Acid-Related Orphan Receptor α Is Required for Generation of Th2 Cells in Type 2 Pulmonary Inflammation - Roberts, Joseph; Chevalier, Anne; Hawerkamp, Heike C.; Yeow, Aoife; Matarazzo, Laura; Schwartz, Christian; Hams, Emily; Fallon, Padraic G. (Journal of Immunology, 2023)
The transcription factor retinoic acid-related orphan receptor α (RORα) is important in regulating several physiological functions, such as cellular development, circadian rhythm, metabolism, and immunity. In two in vivo animal models of type 2 lung inflammation, Nippostrongylus brasiliensis infection and house dust mite (HDM) sensitization, we show a role for Rora in Th2 cellular development during pulmonary inflammation. N. brasiliensis infection and HDM challenge induced an increase in frequency of Rora-expressing GATA3+CD4 T cells in the lung. Using staggerer mice, which have a ubiquitous deletion of functional RORα, we generated bone marrow chimera mice, and we observed a delayed worm expulsion and reduced frequency in the expansion of Th2 cells and innate lymphoid type 2 cells (ILC2s) in the lungs after N. brasiliensis infection. ILC2-deficient mouse (Rorafl/flIl7raCre) also had delayed worm expulsion with associated reduced frequency of Th2 cells and ILC2s in the lungs after N. brasiliensis infection. To further define the role for Rora-expressing Th2 cells, we used a CD4-specific Rora-deficient mouse (Rorafl/flCD4Cre), with significantly reduced frequency of lung Th2 cells, but not ILC2, after N. brasiliensis infection and HDM challenge. Interestingly, despite the reduction in pulmonary Th2 cells in Rorafl/flCD4Cre mice, this did not impact the expulsion of N. brasiliensis after primary and secondary infection, or the generation of lung inflammation after HDM challenge. This study demonstrates a role for RORα in Th2 cellular development during pulmonary inflammation that could be relevant to the range of inflammatory diseases in which RORα is implicated.
CRIS-Team Scopus Importer:2023-08-18

Retnla-Cre mice - a novel M2-reporter mouse model - Krljanac, B.; Vöhringer, David; Koch, Christoph (2017)
EVALuna2:33420

Review: Impact of Helminth Infection on Antimycobacterial Immunity-A Focus on the Macrophage - Lang, Roland; Schick, Judith (Frontiers in Immunology, 2017)
Successful immune control ofMycobacterium tuberculosis(MTB) requires robust CD4+T cell responses, with IFNγs as the key cytokine promoting killing of intracellular mycobacteria by macrophages. By contrast, helminth infections typically direct the immune system toward a type 2 response, characterized by high levels of the cytokines IL-4 and IL-10, which can antagonize IFNγ production and its biological effects. In many countries with high burden of tuberculosis, helminth infections are endemic and have been associated with increased risk to develop tuberculosis or to inhibit vaccination-induced immunity. Mechanistically, regulation of the antimycobacterial immune response by helminths has been mostly been attributed to the T cell compartment. Here, we review the current status of the literature on the impact of helminths on vaccine-induced and natural immunity to MTB with a focus on the alterations enforced on the capacity of macrophages to function as sensors of mycobacteria and effector cells to control their replication.
EVALuna2:33299

Rhinophyma-Like Cutaneous Leishmaniasis due to Leishmania aethiopica Treated Successfully with Liposomal Amphotericin B - Kirchberger, Michael Constantin; Schliep, Stefan; Bogdan, Christian (American Journal of Tropical Medicine and Hygiene, 2019)
CRIS-Team WoS Importer:2019-03-20

RNAseq analysis of Aspergillus fumigatus in blood reveals a just wait and see resting stage behavior - Irmer, Henriette; Tarazona, Sonia; Sasse, Christoph; Olbermann, Patrick; Loeffler, Jurgen; Krappmann, Sven; Conesa, Ana; Braus, Gerhard H. (BMC Genomics, 2015)
Invasive aspergillosis is started after germination of Aspergillus fumigatus conidia that are inhaled by susceptible individuals. Fungal hyphae can grow in the lung through the epithelial tissue and disseminate hematogenously to invade into other organs. Low fungaemia indicates that fungal elements do not reside in the bloodstream for long.We analyzed whether blood represents a hostile environment to which the physiology of A. fumigatus has to adapt. An in vitro model of A. fumigatus infection was established by incubating mycelium in blood. Our model allowed to discern the changes of the gene expression profile of A. fumigatus at various stages of the infection. The majority of described virulence factors that are connected to pulmonary infections appeared not to be activated during the blood phase. Three active processes were identified that presumably help the fungus to survive the blood environment in an advanced phase of the infection: iron homeostasis, secondary metabolism, and the formation of detoxifying enzymes.We propose that A. fumigatus is hardly able to propagate in blood. After an early stage of sensing the environment, virtually all uptake mechanisms and energy-consuming metabolic pathways are shut-down. The fungus appears to adapt by trans-differentiation into a resting mycelial stage. This might reflect the harsh conditions in blood where A. fumigatus cannot take up sufficient nutrients to establish self-defense mechanisms combined with significant growth.
EVALuna2:7692

Role of basophils in protective immunity to parasitic infections - Eberle, Jörg; Vöhringer, David (Seminars in Immunopathology, 2016)
Basophils have been recognized as important players for protective immunity against a variety of different endo- and ectoparasites. Although basophils represent a relatively rare and short-lived cell type, they produce large quantities of effector molecules including histamine, cytokines, chemokines, and lipid mediators which promote type 2 immune responses. Basophils can be activated either directly by parasite-derived factors or indirectly by recognition of parasite-derived antigens via IgE bound to its high-affinity receptor Fc?RI on the cell surface. Many parasitic infections cause expansion and tissue recruitment of basophils, but the role of basophils for protective immunity remains poorly understood. The development of basophil-deficient mouse models over the past few years makes it possible to study their contributions in various infections. We review here the current knowledge regarding the role of basophils for protective or immunomodulatory functions of basophils mainly during infections of mice with protozoan parasites, helminths, and ectoparasites.
EVALuna2:25880

Role of STAT6-regulated genes in macrophages and intestinal epithelial cells in host immunity against helminths - Westermann, Stefanie; Schubart, Christoph; Vöhringer, David (EUROPEAN JOURNAL OF IMMUNOLOGY, 2022)
CRIS-Team WoS Importer:2023-01-27

Role of the ceramide-CD300f interaction in gram-negative bacterial skin infections - Maehara, Akie; Kaitani, Ayako; Izawa, Kumi; Shiba, Emiko; Nagamine, Masakazu; Takamori, Ayako; Isobe, Masamichi; Uchida, Shino; Uchida, Koichiro; Ando, Tomoaki; Maeda, Keiko; Nakano, Nobuhiro; et al. (Journal of Investigative Dermatology, 2017)
EVALuna2:33473

S1-Leitlinie Diagnostik und Therapie der kutanen und mukokutanen Leishmaniasis in Deutschland - Boecken, Gerhard; Weitzel, Thomas; Sunderkötter, Cord; Fischer, Marcellus; Von Stebut-Boschitz, Esther; Bogdan, Christian; Pietras, Mathias; Anders, Gerlind; Harms-Zwingenberger, Gundel; Burchard, Gerd; Bialek, Ralf; Lippert, Ute; et al. (Journal der Deutschen Dermatologischen Gesellschaft, 2009)
CRIS-Team Scopus Importer:2024-02-26

Safety and effectiveness of acellular pertussis vaccination during pregnancy: a systematic review - Vygen-Bonnet, Sabine; Hellenbrand, Wiebke; Garbe, Edeltraut; von Kries, Rüdiger; Bogdan, Christian; Heininger, Ulrich; Röbl-Mathieu, Marianne; Harder, Thomas (BMC Infectious Diseases, 2020)
BACKGROUND: Infants < 3 months of age are at highest risk for developing severe complications after pertussis. The majority of pregnant women has low concentrations of pertussis-specific antibodies and thus newborns are insufficiently protected by maternally transferred antibodies. Acellular pertussis vaccination during pregnancy was recently implemented in various countries. Here, we assessed the evidence for safety and effectiveness of pertussis vaccination during pregnancy. METHODS: We searched Medline, Embase, and ClinicalTrials.gov from January 1st 2010 to January 10th 2019. We assessed risk of bias (ROB) using the Cochrane ROB tool and ROBINS-I. We evaluated the quality of evidence using the GRADE approach. RESULTS: We identified 1273 articles and included 22 studies (14 for safety; 8 for effectiveness), comprising 1.4 million pregnant women in safety studies and 855,546 mother-infant-pairs in effectiveness studies. No significant differences between vaccinated and unvaccinated women and their infants were observed for safety outcomes with the exception of fever and chorioamnionitis. Compared to no vaccination, three studies showed a significantly increased relative risk for the presence of the ICD-9 code for chorioamnionitis in electronic patient data after pertussis vaccination. However, no study reported an increased risk for clinical sequelae of chorioamnionitis after vaccination during pregnancy, such as preterm birth or neonatal intensive care unit admission. Vaccine effectiveness against pertussis in infants of immunized mothers ranged from 69 to 91% for pertussis prevention, from 91 to 94% for prevention of hospitalization and was 95% for prevention of death due to pertussis. Risk of bias was serious to critical for safety outcomes and moderate to serious for effectiveness outcomes. GRADE evidence quality was moderate to very low, depending on outcome. CONCLUSION: Although an increased risk for a diagnosis of fever and chorioamnionitis was detected in pregnant women after pertussis vaccination, there was no association with a higher frequency of clinically relevant sequelae. Vaccine effectiveness for prevention of infant pertussis, hospitalization and death is high. Pertussis vaccination during pregnancy has an overall positive benefit-risk ratio. In view of the overall quality of available evidence ongoing surveillance of chorioamnionitis and its potential sequelae is recommended when pertussis vaccination in pregnancy is implemented. TRIAL REGISTRATION: PROSPERO CRD42018087814, CRD42018090357.
CRIS-Team Scopus Importer:2020-02-21
Keywords: Acellular pertussis vaccine; Chorioamnionitis; Pertussis; Pregnancy; Tdap

Salmonella enterica invasion of polarized epithelial cells is a highly cooperative effort - Lorkowski, Martin; Felipe-Lopez, Alfonso; Danzer, Claudia Agnes; Hansmeier, Nicole; Hensel, Michael (Infection and Immunity, 2014)
The invasion of polarized epithelial cells by Salmonella enterica requires the cooperative activity of the Salmonella pathogenicity island 1 (SPI1)-encoded type III secretion system (T3SS) and the SPI4-encoded adhesin SiiE. The invasion of polarized cells is more efficient than that of nonpolarized cells, and we observed the formation of clusters of bacteria on infected cells. Here we demonstrate that the invasion of polarized cells is a highly cooperative activity. Using a novel live-cell imaging approach, we visualized the cooperative entry of multiple bacteria into ruffles induced on the apical surfaces of polarized cells. The induction of membrane ruffles by activity of Salmonella enables otherwise noninvasive mutant strains to enter polarized host cells. Bacterial motility and chemotaxis were of lower importance for cooperativity in polarized-cell invasion. We propose that cooperative invasion is a key factor for the very efficient entry into polarized cells and a factor contributing to epithelial damage and intestinal inflammation.
EVALuna2:7669

Salmonella pathogenicity islands in host specificity, host pathogen-interactions and antibiotics resistance of Salmonella enterica. - Gerlach, Roman; Hensel, Michael (Berliner und Münchener Tierärztliche Wochenschrift, 2007)
Salmonella enterica is a pathogen highly successful in causing a variety of gastrointestinal and systemic diseases in animals and humans. While some serovars of S. enterica are able to infect a broad range of host organisms, other serovars are highly restricted to specific host species. The colonization of hosts by S. enterica depends on the function of a large number of virulence determinants. The molecular analyses of virulence genes demonstrated that most of these loci are clustered within Salmonella Pathogenicity Islands (SPI). SPI1 and SPI2 each encode type III secretion systems (T355) that confer main virulence traits of S. enterica, i.e. invasion, enteropathogenesis and intracellular survival and proliferation. Further SPI encode factors that contribute to intracellular survival, different types of adhesins, or effector proteins of the SPI1-T3SS or SPI2-T3SS. The availability of genome sequences of several serovars of S. enterica also revealed serovar-specific SPI. In this review, the main characteristics of the currently known SPI are summarized with focus on their roles in various animal hosts and putative functions in human infections.

Salt-dependent chemotaxis of macrophages - Mueller, Silke; Quast, Thomas; Schröder, Agnes; Hucke, Stephanie; Klotz, Luisa; Jantsch, Jonathan; Gerzer, Rupert; Hemmersbach, Ruth; Kolanus, Waldemar (PLoS ONE, 2013)
Besides their role in immune system host defense, there is growing evidence that macrophages may also be important regulators of salt homeostasis and blood pressure by a TonEBP-VEGF-C dependent buffering mechanism. As macrophages are known to accumulate in the skin of rats fed under high salt diet conditions and are pivotal for removal of high salt storage, the question arose how macrophages sense sites of high sodium storage. Interestingly, we observed that macrophage-like RAW264.7 cells, murine bone marrow-derived macrophages and peritoneal macrophages recognize NaCl hypertonicity as a chemotactic stimulus and migrate in the direction of excess salt concentration by using an in vitro transwell migration assay. While RAW264.7 cells migrated toward NaCl in a dose-dependent fashion, no migratory response toward isotonic or hypotonic media controls, or other osmo-active agents, e.g. urea or mannitol, could be detected. Interestingly, we could not establish a specific role of the osmoprotective transcription factor TonEBP in regulating salt-dependent chemotaxis, since the specific migration of bone marrow-derived macrophages following RNAi of TonEBP toward NaCl was not altered. Although the underlying mechanism remains unidentified, these data point to a thus far unappreciated role for NaCl-dependent chemotaxis of macrophages in the clearance of excess salt, and suggest the existence of novel NaCl sensor/effector circuits, which are independent of the TonEBP system.
EVALuna2:7634

Salvage therapy with Sodium chlorosum (formerly DAC N-055) for cases of refractory lupoid cutaneous leishmaniasis: Results from a compassionate use study with 0.09% Sodium chlorosum in amphiphilic basic cream - Molkara, Sara; Poursoltani, Elaheh; Stahl, Kurt Wilhelm; Maleki, Masoud; Khamesipour, Ali; Bogdan, Christian; Salehi, Maryam; Goyonlo, Vahid Mashayekhi (BMC Infectious Diseases, 2019)
Background: Lupoid cutaneous leishmaniasis (LCL) is known as a rare but serious complication of anthroponotic cutaneous leishmaniasis (ACL) resistant to conventional treatments. Sodium chlorosum, a pro-oxidative preparation of pharmaceutical sodium chlorite (NaClO2), has been successfully used for the treatment of Old World cutaneous leishmaniasis lesions (OWCL) and of some LCL cases in Afghanistan. This clinical trial study aimed to evaluate the effect of a last resort therapy with topical 0.09% sodium chlorosum on LCL in Iran. Methods: Twenty Iranian patients (12 women and 8 men) with LCL refractory to treatment were included in this salvage study. A magistral preparation of sodium chlorosum (10 mM NaClO2 in amphiphilic basic cream) was applied twice daily to the lesions for 6 weeks and continued up to 12 weeks in patients who showed a clinical response within the first 6 weeks. Responders were followed up for a maximum of 1 year. Lesions were photographed during weekly visits. Disappearance of erythema and indurated lesions were rated as complete clinical response. Results: Patients with a mean age of 28.6 (±24.3) and with an ACL proven lesion history of 3.8 (±1.4) years were treated for an average of 7.9 (±1.8) weeks. At the end of the treatment period (12th week), a complete response was observed in 9 of 20 patients (45%). During the one-year follow-up period, LCL lesions recurred in 4 of these 9 patients (with one patient showing only a tiny lesion) and one case lost to follow up whereas the other four remained completely lesion-free. Mild temporary side-effects such as erythema and itching were seen in 4 of 20 patients (20%). Conclusions: Topical sodium chlorosum showed promising therapeutic results and can be considered as safe, painless, and relatively effective treatment for LCL, an ethical prerequisite for a two-armed controlled trial. Trial registration: This study was registered in Iranian registry of clinical trials on 2019-02-02 with registration number IRCT20190114042356N1.
CRIS-Team Scopus Importer:2019-12-10
Keywords: Lupoid cutaneous leishmaniasis; Sodium chlorosum (formerly DAC N-055); Treatment

Scalable reporter assays to analyze the regulation of stx2 expression in shiga toxin-producing enteropathogens - Koeppel, Martin B.; Glaser, Jana; Baumgartner, Tobias; Spriewald, Stefanie; Gerlach, Roman; Armansperg, Benedikt von; Leong, John M.; Stecher, Bärbel (Toxins, 2021)
Stx2 is the major virulence factor of EHEC and is associated with an increased risk for HUS in infected patients. The conditions influencing its expression in the intestinal tract are largely unknown. For optimal management and treatment of infected patients, the identification of environmental conditions modulating Stx2 levels in the human gut is of central importance. In this study, we established a set of chromosomal stx2 reporter assays. One system is based on superfolder GFP (sfGFP) using a T7 polymerase/T7 promoter-based amplification loop. This reporter can be used to analyze stx2 expression at the single-cell level using FACSs and fluorescence microscopy. The other system is based on the cytosolic release of the Gaussia princeps luciferase (gluc). This latter reporter proves to be a highly sensitive and scalable reporter assay that can be used to quantify reporter protein in the culture supernatant. We envision that this new set of reporter tools will be highly useful to comprehensively analyze the influence of environmental and host factors, including drugs, small metabolites and the microbiota, on Stx2 release and thereby serve the identification of risk factors and new therapies in Stx-mediated pathologies.
CRIS-Team Scopus Importer:2021-08-20
Keywords: E. coli; EHEC; Hemolytic–uremic syndrome; HUS; HUSEC; STEC

Scarless deletion of up to seven methyl-accepting chemotaxis genes with an optimized method highlights key function of CheM in Salmonella Typhimurium. - Hoffmann, Stefanie; Schmidt, Christiane; Walter, Steffi; Gerlach, Roman; et al. (PLoS ONE, 2017)
Site-directed scarless mutagenesis is an essential tool of modern pathogenesis research. We describe an optimized two-step protocol for genome editing in Salmonella enterica serovar Typhimurium to enable multiple sequential mutagenesis steps in a single strain. The system is based on the λ Red recombinase-catalyzed integration of a selectable antibiotics resistance marker followed by replacement of this cassette. Markerless mutants are selected by expressing the meganuclease I-SceI which induces double-strand breaks in bacteria still harboring the resistance locus. Our new dual-functional plasmid pWRG730 allows for heat-inducible expression of the λ Red recombinase and tet-inducible production of I-SceI. Methyl-accepting chemotaxis proteins (MCP) are transmembrane chemoreceptors for a vast set of environmental signals including amino acids, sugars, ions and oxygen. Based on the sensory input of MCPs, chemotaxis is a key component for Salmonella virulence. To determine the contribution of individual MCPs we sequentially deleted seven MCP genes. The individual mutations were validated by PCR and genetic integrity of the final seven MCP mutant WRG279 was confirmed by whole genome sequencing. The successive MCP mutants were functionally tested in a HeLa cell infection model which revealed increased invasion rates for non-chemotactic mutants and strains lacking the MCP CheM (Tar). The phenotype of WRG279 was reversed with plasmid-based expression of CheM. The complemented WRG279 mutant showed also partially restored chemotaxis in swarming assays on semi-solid agar. Our optimized scarless deletion protocol enables efficient and precise manipulation of the Salmonella genome. As demonstrated with whole genome sequencing, multiple subsequent mutagenesis steps can be realized without the introduction of unwanted mutations. The sequential deletion of seven MCP genes revealed a significant role of CheM for the interaction of S. Typhimurium with host cells which might give new insights into mechanisms of Salmonella host cell sensing.

Scavenging of bacteria or bacterial products by magnetic particles functionalized with a broad-spectrum pathogen recognition receptor motif offers diagnostic and therapeutic applications - Friedrich, Bernhard; Lyer, Stefan; Janko, Christina; Unterweger, Harald; Brox, Regine; Cunningham, Sarah; Dutz, Silvio; Taccardi, Nicola; Bikker, Floris J.; Hurle, Katrin; Sebald, Heidi; Lenz, Malte; et al. (Acta Biomaterialia, 2022)
Sepsis is a dysregulated host response of severe bloodstream infections, and given its frequency of occurrence and high mortality rate, therapeutic improvements are imperative. A reliable biomimetic strategy for the targeting and separation of bacterial pathogens in bloodstream infections involves the use of the broad-spectrum binding motif of human GP-340, a pattern-recognition receptor of the scavenger receptor cysteine rich (SRCR) superfamily that is expressed on epithelial surfaces but not found in blood. Here we show that these peptides, when conjugated to superparamagnetic iron oxide nanoparticles (SPIONs), can separate various bacterial endotoxins and intact microbes (E. coli, S. aureus, P. aeruginosa and S. marcescens) with high efficiency, especially at low and thus clinically relevant concentrations. This is accompanied by a subsequent strong depletion in cytokine release (TNF, IL-6, IL-1β, Il-10 and IFN-γ), which could have a direct therapeutic impact since escalating immune responses complicates severe bloodstream infections and sepsis courses. SPIONs are coated with aminoalkylsilane and capture peptides are orthogonally ligated to this surface. The particles behave fully cyto- and hemocompatible and do not interfere with host structures. Thus, this approach additionally aims to dramatically reduce diagnostic times for patients with suspected bloodstream infections and accelerate targeted antibiotic therapy. Statement of significance: Sepsis is often associated with excessive release of cytokines. This aspect and slow diagnostic procedures are the major therapeutic obstacles. The use of magnetic particles conjugated with small peptides derived from the binding motif of a broad-spectrum mucosal pathogen recognition protein GP-340 provides a highly efficient scavenging platform. These peptides are not found in blood and therefore are not subject to inhibitory mechanisms like in other concepts (mannose binding lectine, aptamers, antibodies). In this work, data are shown on the broad bacterial binding spectrum, highly efficient toxin depletion, which directly reduces the release of cytokines. Host cells are not affected and antibiotics not adsorbed. The particle bound microbes can be recultured without restriction and thus be used directly for diagnostics.
CRIS-Team Scopus Importer:2022-03-11
Keywords: GP-340; Magnetic nanoparticles; Pathogen binding; Sepsis; SRCR domain

Schistosoma "Eggs-Iting" the Host: Granuloma Formation and Egg Excretion. - Schwartz, Christian; Fallon, Padraic G. (Frontiers in Immunology, 2018)
eggs laid in vasculature must usurp immunity to induce regulated inflammation, to facilitate extravasation through the intestinal wall and to be expelled in the feces. We highlight the roles of immune cell populations, stromal factors, and egg secretions in the process of egg excretion to provide a comprehensive overview of the current state of knowledge regarding a vastly unexplored mechanism.

Schistosoma mansoni Worm Infection Regulates the Intestinal Microbiota and Susceptibility to Colitis. - Floudas, Achilleas; Aviello, Gabriella; Schwartz, Christian; Jeffery, Ian B.; O'Toole, Paul W.; Fallon, Padraic G. (Infection and Immunity, 2019)
worm infection modulates the host's immune system and suppresses bystander colitis while limiting dysbiosis of the host's intestinal microbiome during infection.

Selective ablation of thymic and peripheral Foxp3+ regulatory T cell development - Yilmazer, Acelya; Zevla, Dimitra Maria; Malmkvist, Rikke; Rodríguez, Carlos Alejandro Bello; Undurraga, Pablo; Kirgin, Emre; Boernert, Marie; Vöhringer, David; Kershaw, Olivia; Schlenner, Susan; Kretschmer, Karsten (Frontiers in Immunology, 2023)
Foxp3+ regulatory T (Treg) cells of thymic (tTreg) and peripheral (pTreg) developmental origin are thought to synergistically act to ensure immune homeostasis, with self-reactive tTreg cells primarily constraining autoimmune responses. Here we exploited a Foxp3-dependent reporter with thymus-specific GFP/Cre activity to selectively ablate either tTreg (ΔtTreg) or pTreg (ΔpTreg) cell development, while sparing the respective sister populations. We found that, in contrast to the tTreg cell behavior in ΔpTreg mice, pTreg cells acquired a highly activated suppressor phenotype and replenished the Treg cell pool of ΔtTreg mice on a non-autoimmune C57BL/6 background. Despite the absence of tTreg cells, pTreg cells prevented early mortality and fatal autoimmunity commonly observed in Foxp3-deficient models of complete Treg cell deficiency, and largely maintained immune tolerance even as the ΔtTreg mice aged. However, only two generations of backcrossing to the autoimmune-prone non-obese diabetic (NOD) background were sufficient to cause severe disease lethality associated with different, partially overlapping patterns of organ-specific autoimmunity. This included a particularly severe form of autoimmune diabetes characterized by an early onset and abrogation of the sex bias usually observed in the NOD mouse model of human type 1 diabetes. Genetic association studies further allowed us to define a small set of autoimmune risk loci sufficient to promote β cell autoimmunity, including genes known to impinge on Treg cell biology. Overall, these studies show an unexpectedly high functional adaptability of pTreg cells, emphasizing their important role as mediators of bystander effects to ensure self-tolerance.
CRIS-Team Scopus Importer:2024-12-16
Keywords: autoimmunity; diabetes; Foxp3; immune tolerance; pTreg; scurfy; T cell development; tTreg

Selective expression of constitutively activated STAT6 in intestinal epithelial cells promotes differentiation of secretory cells and protection against helminths - Schubart, Christoph; Krljanac, Branislav; Otte, Manuel; Symowski, Cornelia; Martini, Eva; Günther, Claudia; Becker, Christoph; Daniel, Christoph; Vöhringer, David (Mucosal Immunology, 2018)
Intestinal epithelial cells (IECs) constitute an important barrier between host and pathogen. Immune mechanisms that provide protection against gastrointestinal helminths often require IL-4Rα-induced activation of STAT6-regulated genes in IECs. However, it is not known whether STAT6 activation in IECs enhances protective immunity against helminths. Furthermore, the regulation of proliferation and differentiation processes of the intestinal epithelium by IEC-intrinsic STAT6 signaling remains unclear. To address these questions, we generated mice with specific expression of a constitutively active version of STAT6 in IECs. These VillinCre_STAT6vt mice show accumulation of secretory IECs, increased proliferation of IECs and lengthening of the small intestine. They rapidly expelled Nippostrongylus brasiliensis worms even in the absence of T cells. Furthermore, primary infection with Heligmosomoides polygyrus resulted in larval trapping in the submucosa and the fecundity of adult worms was severely impaired. Our results reveal an important IEC-intrinsic role of STAT6-regulated genes for intestinal homeostasis and protective immunity against helminths.
EVALuna2:35396

Selective Expression of the MAPK Phosphatase Dusp9/MKP-4 in Mouse Plasmacytoid Dendritic Cells and Regulation of IFN-? Production - Niedzielska, Magdalena; Mohamed Raffi, Faizal Ali; Tel, Jurjen; Muench, Sandra; Jozefowski, Katrin; Alati, Nour; Lahl, Katharina; Mages, Joerg; Billmeier, Ulrike; Schiemann, Matthias; Appelt, Uwe K.; Wirtz, Stefan; et al. (Journal of Immunology, 2015)
Plasmacytoid dendritic cells (pDCs) efficiently produce large amounts of type I IFN in response to TLR7 and TLR9 ligands, whereas conventional DCs (cDCs) predominantly secrete high levels of the cytokines IL-10 and IL-12. The molecular basis underlying this distinct phenotype is not well understood. In this study, we identified the MAPK phosphatase Dusp9/MKP-4 by transcriptome analysis as selectively expressed in pDCs, but not cDCs. We confirmed the constitutive expression of Dusp9 at the protein level in pDCs generated in vitro by culture with Flt3 ligand and ex vivo in sorted splenic pDCs. Dusp9 expression was low in B220(-) bone marrow precursors and was upregulated during pDC differentiation, concomitant with established pDC markers. Higher expression of Dusp9 in pDCs correlated with impaired phosphorylation of the MAPK ERK1/2 upon TLR9 stimulation. Notably, Dusp9 was not expressed at detectable levels in human pDCs, although these displayed similarly impaired activation of ERK1/2 MAPK compared with cDCs. Enforced retroviral expression of Dusp9 in mouse GM-CSF-induced cDCs increased the expression of TLR9-induced IL-12p40 and IFN-?, but not of IL-10. Conditional deletion of Dusp9 in pDCs was effectively achieved in Dusp9(flox/flox); CD11c-Cre mice at the mRNA and protein levels. However, the lack of Dusp9 in pDC did not restore ERK1/2 activation after TLR9 stimulation and only weakly affected IFN-? and IL-12p40 production. Taken together, our results suggest that expression of Dusp9 is sufficient to impair ERK1/2 activation and enhance IFN-? expression. However, despite selective expression in pDCs, Dusp9 is not essential for high-level IFN-? production by these cells.
EVALuna2:2008

Self-reactivity of CD8 T-cell clones determines their differentiation status rather than their responsiveness in infections - Paprckova, Darina; Niederlova, Veronika; Moudra, Alena; Drobek, Ales; Pribikova, Michaela; Janusova, Sarka; Schober, Kilian; Neuwirth, Ales; Michalik, Juraj; Huranova, Martina; Horkova, Veronika; Cesnekova, Michaela; et al. (Frontiers in Immunology, 2022)
Mature T cells are selected for recognizing self-antigens with low to intermediate affinity in the thymus. Recently, the relative differences in self-reactivity among individual T-cell clones were appreciated as important factors regulating their fate and immune response, but the role of self-reactivity in T-cell biology is incompletely understood. We addressed the role of self-reactivity in T-cell diversity by generating an atlas of mouse peripheral CD8+ T cells, which revealed two unconventional populations of antigen-inexperienced T cells. In the next step, we examined the steady-state phenotype of monoclonal T cells with various levels of self-reactivity. Highly self-reactive clones preferentially differentiate into antigen-inexperienced memory-like cells, but do not form a population expressing type I interferon-induced genes, showing that these two subsets have unrelated origins. The functional comparison of naïve monoclonal CD8+ T cells specific to the identical model antigen did not show any correlation between the level of self-reactivity and the magnitude of the immune response.
CRIS-Team Scopus Importer:2022-11-04
Keywords: antigen-inexperienced memory-like CD8 T cells; interferon response; self-reactivity; T cell; T-cell diversity

Serum (1→3)-β-D-glucan and galactomannan levels in patients with cystic fibrosis: a retrospective cohort study - Traeger, Johannes; Melichar, Volker Otto; Meyer, Renate; Rauh, Manfred; Bogdan, Christian; Held, Jürgen (BMC Pulmonary Medicine, 2018)
BACKGROUND: Aspergillus fumigatus is frequently encountered in sputum samples of patients with cystic fibrosis (CF), which traditionally has been interpreted as saprophytic airway colonization. However, this mere bystander role has been challenged by recent data. There is now evidence that Aspergillus fumigatus accelerates the decline of pulmonary function. (1→3)-β-D-glucan (BDG) and galactomannan (GM) are highly sensitive fungal biomarkers that are used to diagnose invasive fungal disease. However, their diagnostic value in CF patients is largely unknown. METHODS: We conducted a retrospective cohort study on 104 CF patients to determine whether serum BDG and GM levels correlate with parameters such as Aspergillus-positive sputum cultures and lung function. RESULTS: Aspergillus fumigatus was persistently detected in 22 of the 104 CF patients (21%). Mean serum BDG and GM levels in the Aspergillus-positive patients were significantly higher than in those without persistent Aspergillus detection (89 versus 40 pg/ml [p = 0.022] and 0.30 versus 0.15 ODI [p = 0.013], respectively). 27 and 7 patients had elevated BDG (≥ 60 pg/ml) or GM levels (> 0.5 ODI), respectivly. BDG and GM levels showed a significant correlation (p = 0.004). Patients with increased serum concentrations of BDG were more frequently Aspergillus-positive (40.7 versus 14.3%, p = 0.004) and had a significantly lower forced expiratory volume in one second (FEV1) than patients with a normal BDG (61.6 versus 77.1%, p = 0.007). In the multivariate analysis, BDG but not GM or the growth of A. fumigatus, proved to be an independent predictor for the FEV1. CONCLUSIONS: CF patients with persistent Aspergillus detection have elevated BDG and GM levels which ranged between healthy and invasively infected patients. Serum BDG may be superior to GM and fungal culture in predicting an impaired lung function in CF patients.
EVALuna2:35821

Serum antigen tests for the diagnosis of invasive aspergillosis: a retrospective comparison of five Aspergillus antigen assays and one beta-D-glucan assay - Schub, Thilo; Klugherz, Isabel; Wagener, Johannes; Prattes, Juergen; Hoenigl, Martin; Suerbaum, Sebastian; Held, Jürgen; Dichtl, Karl (Journal of Clinical Microbiology, 2024)
Invasive aspergillosis (IA) is a life-threatening infection. Early and specific diagnosis is pivotal to ensure adequate therapy. Antigen testing from blood is a widespread and convenient diagnostic approach. Various tests for the detection of Aspergillus antigen as well as for the panfungal antigen β-1,3-D-glucan (BDG) are available, for which comprehensive comparisons are still lacking. Blood samples of 82 proven/probable (11/71) IA patients and 52 controls were tested using two enzyme-linked immunosorbent assays (ELISAs) (Bio-Rad and Euroimmun), one chemiluminescent immunoassay (CLIA) (Vircell), one BDG assay (Fujifilm Wako), and two point of care (PoC) assays (Immy sōna and OLM). PoC assays were evaluated visually and used automated read out systems. Of the 82 IA patients, 37 had received solid organ transplantation (SOT) and 25 hematopoietic stem cell transplant (HSCT). Sensitivities and specificities for the eight test systems ranged from 27% to 71% and from 64% to 100%. Estimating a 10% prevalence of IA, test performance would have resulted in positive and negative predictive values of 14%−100% and 91%−95%. Areas under the curve (AUCs) for all tests except GM were below 0.7. When the cut-off values for quantitative tests were normalized to a specificity close to 95%, sensitivities ranged from 14% to 40%. The use of automated read out systems for the PoC assays had a significant impact. Combining different tests did not result in better test strategies. Sensitivity of Aspergillus antigen testing from single serum samples is low. Due to specificity issues, the majority of tests is not suited for screening purposes. The different assays can meet different needs in different diagnostic settings.
CRIS-Team Scopus Importer:2025-02-04
Keywords: 3-D-glucan; antigen; Aspergillus; beta-1; galactomannan; glucan; invasive aspergillosis; serum

Severe Acute Respiratory Syndrome Coronavirus 2 Attachment Receptor Angiotensin-Converting Enzyme 2 Is Decreased in Crohn's Disease and Regulated By Microbial and Inflammatory Signaling - Patankar, Jay Vasant; Lehmann, Malte; Kühl, Anja A.; Atreya, Raja; Becker, Christoph; Gonzalez-Acera, Miguel; Schmitt, Heike; Gamez-Belmonte, Reyes; Mahapatro, Mousumi; Diemand, Leonard; Hartmann, Leonie; Mascia, Fabrizio; et al. (Gastroenterology, 2021)
CRIS-Team Scopus Importer:2021-02-12

Shigella Outer Membrane Vesicles as Promising Targets for Vaccination - Qasim, Muhammad; Wrage, Marius; Nüse, Björn; Mattner, Jochen (International Journal of Molecular Sciences, 2022)
The clinical symptoms of shigellosis, a gastrointestinal infection caused by Shigella spp. range from watery diarrhea to fulminant dysentery. Endemic infections, particularly among children in developing countries, represent the majority of clinical cases. The situation is aggravated due to the high mortality rate of shigellosis, the rapid dissemination of multi-resistant Shigella strains and the induction of only serotype-specific immunity. Thus, infection prevention due to vaccination, encompassing as many of the circulating serotypes as possible, has become a topic of interest. However, vaccines have turned out to be ineffective so far. Outer membrane vesicles (OMVs) are promising novel targets for vaccination. OMVs are constitutively secreted by Gram-negative bacteria including Shigella during growth. They are composed of soluble luminal portions and an insoluble membrane and can contain toxins, bioactive periplasmic and cytoplasmic (lipo-) proteins, (phospho-) lipids, nucleic acids and/or lipopolysaccharides. Thus, OMVs play an important role in bacterial cell– cell communication, growth, survival and pathogenesis. Furthermore, they modulate the secretion and transport of biomolecules, the stress response, antibiotic resistance and immune responses of the host. Thus, OMVs serve as novel secretion machinery. Here, we discuss the current literature and highlight the properties of OMVs as potent vaccine candidates because of their immunomodulatory, antigenic and adjuvant properties.
CRIS-Team Scopus Importer:2022-01-28
Keywords: Outer membrane vesicles (OMVs); Shigella; Vaccination

Siglec-F Promotes IL-33-Induced Cytokine Release from Bone Marrow-Derived Eosinophils Independently of the ITIM and ITIM-like Motif Phosphorylation - Westermann, Stefanie; Dietschmann, Axel; Doehler, Daniela; Castiglione, Kirstin; Bochner, Bruce S.; Vöhringer, David; Radtke, Daniel (Journal of Immunology, 2022)
Eosinophils are potent innate effector cells associated mainly with type 2 immune responses elicited by helminths and allergens. Their activity needs to be tightly controlled to prevent severe inflammation and tissue damage. Eosinophil degranulation and secretion of inflammatory effector molecules, including cytokines, chemokines, and lipid mediators, can be regulated by activating and inhibitory receptors on the cell surface. In this study, we investigated the modulation of proliferation, apoptosis, gene expression, and cytokine/chemokine secretion from IL-33-activated Mus musculus eosinophils on cross-linking of the transmembrane receptor Sialic acid-binding Ig-like lectin F (Siglec-F). Siglec-F contains an ITIM plus an ITIM-like motif in its intracellular tail and is mainly regarded as an inhibitory and apoptosis-inducing receptor. In vitro costimulation of bone marrow-derived eosinophils with anti-Siglec-F and IL-33 compared with treatment with either alone led to enhanced STAT6 phosphorylation, stronger induction of hypoxia/glycolysis-related proinflammatory genes, and elevated secretion of type 2 cytokines (IL-4, IL-13) and chemokines (CCL3, CCL4) with only minor effects on proliferation and apoptosis. Using a competitive mixed bone marrow chimera approach with wild-type and Siglec-F-deficient eosinophils, we observed no evidence for Siglec-F-regulated inhibition of Aspergillus fumigates-elicited lung eosinophilia. Truncation of the Siglec-F cytoplasmic tail, but not mutation of the ITIM and ITIM-like motifs, ablated the effect of enhanced cytokine/chemokine secretion. This provides evidence for an ITIM phosphorylation-independent signaling pathway from the cytoplasmic tail of the Siglec-F receptor that enhances effector molecule release from activated eosinophils.
CRIS-Team WoS Importer:2022-03-04

Signaling events driving Aspergillus fumigatus-induced eosinophil activation - Adam, Jasmin; Graf, Lisa-Marie; Westermann, Stefanie; Vöhringer, David; Krappmann, Sven (International Journal of Medical Microbiology, 2025)
Allergic bronchopulmonary aspergillosis is an incurable disease caused by the environmental mold Aspergillus fumigatus. This hypersensitivity pneumonia is characterized by an inflammatory type 2 immune response, accompanied by influx of eosinophils into the lung. To investigate the mode of action of eosinophils and the signaling events triggered by A. fumigatus, we used an in vitro coculture system of murine bone marrow-derived eosinophils confronted with conidia. Using small-molecule inhibitors, we identified signaling modules of eosinophils in the course of A. fumigatus confrontation. Eosinophils reduced fungal metabolic activity, but inhibition of relevant signaling modules did not affect this phenomenon upon eosinophil confrontation. A. fumigatus-induced secretion of Th2 cytokines and chemokines by eosinophils engaged proto-oncogene tyrosine-protein kinase Src, phosphatidylinositol 3-kinase, p38 mitogen-activated protein kinase as well as calcium cations and to some extent serine/threonine-protein kinase Akt and protein arginine deiminase 4. Src and PI3K kinases were also involved in A. fumigatus-mediated ROS production and regulation of eosinophils surface receptors. Especially Src and PI3K inhibitors prevented A. fumigatus-induced eosinophil activation. Taken together, identification of signaling cascades of eosinophils during their interaction with A. fumigatus provides relevant insights into the host-pathogen interaction in the context of ABPA to yield therapeutic perspectives.
CRIS-Team Scopus Importer:2025-02-17
Keywords: Allergic bronchopulmonary aspergillosis; Allergic lung inflammation; Granulocytes; PI3K; Src

Signatures of recent activation identify a circulating T cell compartment containing tumor-specific antigen receptors with high avidity - Purcarea, A.; Jarosch, S.; Barton, J.; Grassmann, S.; Pachmayr, L.; D'Ippolito, E.; Hammel, M.; Hochholzer, A.; Wagner, K. I.; Van Den Berg, J. H.; Buchholz, V. R.; Haanen, J. B. A. G.; et al. (EUROPEAN JOURNAL OF IMMUNOLOGY, 2022)
CRIS-Team WoS Importer:2023-01-27

SiiA and SiiB are novel type I secretion system subunits controlling SPI4-mediated adhesion of Salmonella enterica - Wille, Thorsten; Wagner, Carolin; Mittelstädt, Wilrun; Blank, Kathrin; Sommer, Erik; Malengo, Gabriele; Döhler, Daniela; Lange, Anna; Sourjik, Viktor; Hensel, Michael; Gerlach, Roman G. (Cellular Microbiology, 2014)
The giant non-fimbrial adhesin SiiE is essential to establish intimate contact between Salmonella enterica and the apical surface of polarized epithelial cells. SiiE is secreted by a type I secretion system (T1SS) encoded by Salmonella Pathogenicity Island 4 (SPI4). We identified SiiA and SiiB as two regulatory proteins encoded by SPI4. Mutant strains in siiA or siiB still secrete SiiE, but are highly reduced in adhesion to, and invasion of polarized cells. SiiA and SiiB are inner membrane proteins with one and three transmembrane (TM) helices respectively. TM2 and TM3 of SiiB are similar to members of the ExbB/TolQ family, while the TM of SiiA is similar to MotB and a conserved aspartate residue in this TM is essential for SPI4-encoded T1SS function. Co-immunoprecipitation, bacterial two-hybrid and FRET demonstrate homo- and heterotypic protein interactions for SiiA and SiiB. SiiB, but not SiiA also interacts with the SPI4-T1SS ATPase SiiF. The integrity of the Walker A box in SiiF was required for SiiB-SiiF interactionand SiiF dimer formation. Based on these data, we describe SiiA and SiiB as new, exclusively virulence-associated members of the Mot/Exb/Tol family of membrane proteins. Both proteins are involved in a novel mechanism of controlling SPI4-T1SS-dependent adhesion, most likely by formation of a proton-conducting channe
EVALuna2:7667

Slp-76 is a critical determinant of NK-cell mediated recognition of missing-self targets - Lampe, Kristin; Endale, Mehari; Cashman, Siobhan; Fang, Hao; Mattner, Jochen; Hildeman, David; Hoebe, Kasper (European Journal of Immunology, 2015)
Absence of MHC class I expression is an important mechanism by which NK cells recognize a variety of target cells, yet the pathways underlying "missing-self" recognition, including the involvement of activating receptors, remain poorly understood. Using ethyl-N-nitrosourea mutagenesis in mice, we identified a germline mutant, designated Ace, with a marked defect in NK cell mediated recognition and elimination of "missing-self" targets. The causative mutation was linked to chromosome 11 and identified as a missense mutation (Thr428Ile) in the SH2 domain of Slp-76-a critical adapter molecule downstream of ITAM-containing surface receptors. The Slp-76 Ace mutation behaved as a hypomorphic allele-while no major defects were observed in conventional T-cell development/function, a marked defect in NK cell mediated elimination of ?2-microglobulin (?2M) deficient target cells was observed. Further studies revealed Slp-76 to control NK-cell receptor expression and maturation; however, activation of Slp-76(ace/ace) NK cells through ITAM-containing NK-cell receptors or allogeneic/tumor target cells appeared largely unaffected. Imagestream analysis of the NK-?2M(-/-) target cell synapse revealed a specific defect in actin recruitment to the conjugate synapse in Slp-76(ace/ace) NK cells. Overall these studies establish Slp-76 as a critical determinant of NK-cell development and NK cell mediated elimination of missing-self target cells in mice.
EVALuna2:7683

SMYD2 Inhibition Downregulates TMPRSS2 and Decreases SARS-CoV-2 Infection in Human Intestinal and Airway Epithelial Cells - Yu, Yidong; Herrmann, Alexandra; Thonn, Veronika; Cordsmeier, Arne; Neurath, Markus; Enßer, Armin; Becker, Christoph (Cells, 2022)
The COVID-19 pandemic caused by SARS-CoV-2 has lasted for more than two years. Despite the presence of very effective vaccines, the number of virus variants that escape neutralizing antibodies is growing. Thus, there is still a need for effective antiviral treatments that target virus replication independently of the circulating variant. Here, we show for the first time that deficiency or pharmacological inhibition of the cellular lysine-methyltransferase SMYD2 decreases TMPRSS2 expression on both mRNA and protein levels. SARS-CoV-2 uses TMPRSS2 for priming its spike protein to infect target cells. Treatment of cultured cells with the SMYD2 inhibitors AZ505 or BAY598 significantly inhibited viral replication. In contrast, treatment of Vero E6 cells, which do not express detectable amounts of TMPRSS2, had no effect on SARS-CoV-2 infection. Moreover, by generating a recombinant reporter virus that expresses the spike protein of the Delta variant of SARS-CoV-2, we demonstrate that BAY598 exhibits similar antiviral activity against this variant of concern. In summary, SMYD2 inhibition downregulates TMPRSS2 and blocks viral replication. Targeting cellular SMYD2 represents a promising tool to curtail SARS-CoV-2 infection.
CRIS-Team Scopus Importer:2022-04-29
Keywords: antiviral treatment; AZ505; BAY598; COVID-19; SARS-CoV-2; SMYD2; TMPRSS2

SMYD2 targets RIPK1 and restricts TNF-induced apoptosis and necroptosis to support colon tumor growth - Yu, Yidong; Thonn, Veronika; Patankar, Jay; Thoma, Oana-Maria; Waldner, Maximilian; Zielinska, Marta; Bao, Lili; Gonzalez Acera, Miguel; Wallmueller, Stefan; Engel, Felix; Stürzl, Michael; Neurath, Markus; et al. (Cell Death & Disease, 2022)
SMYD2 is a histone methyltransferase, which methylates both histone H3K4 as well as a number of non-histone proteins. Dysregulation of SMYD2 has been associated with several diseases including cancer. In the present study, we investigated whether and how SMYD2 might contribute to colorectal cancer. Increased expression levels of SMYD2 were detected in human and murine colon tumor tissues compared to tumor-free tissues. SMYD2 deficiency in colonic tumor cells strongly decreased tumor growth in two independent experimental cancer models. On a molecular level, SMYD2 deficiency sensitized colonic tumor cells to TNF-induced apoptosis and necroptosis without affecting cell proliferation. Moreover, we found that SMYD2 targeted RIPK1 and inhibited the phosphorylation of RIPK1. Finally, in a translational approach, pharmacological inhibition of SMYD2 attenuated colonic tumor growth. Collectively, our data show that SMYD2 is crucial for colon tumor growth and inhibits TNF-induced apoptosis and necroptosis.
CRIS-Team WoS Importer:2022-01-21

Sodium chloride in the tumor microenvironment enhances T cell metabolic fitness and cytotoxicity - Soll, Dominik; Chu, Chang Feng; Sun, Shan; Lutz, Veronika; Arunkumar, Mahima; Gachechiladze, Mariam; Schäuble, Sascha; Alissa-Alkhalaf, Maha; Nguyen, Trang; Khalil, Michelle Amirah; Garcia-Ribelles, Ignacio; Mueller, Michael; et al. (Nature Immunology, 2024)
The efficacy of antitumor immunity is associated with the metabolic state of cytotoxic T cells, which is sensitive to the tumor microenvironment. Whether ionic signals affect adaptive antitumor immune responses is unclear. In the present study, we show that there is an enrichment of sodium in solid tumors from patients with breast cancer. Sodium chloride (NaCl) enhances the activation state and effector functions of human CD8+ T cells, which is associated with enhanced metabolic fitness. These NaCl-induced effects translate into increased tumor cell killing in vitro and in vivo. Mechanistically, NaCl-induced changes in CD8+ T cells are linked to sodium-induced upregulation of Na+/K+-ATPase activity, followed by membrane hyperpolarization, which magnifies the electromotive force for T cell receptor (TCR)-induced calcium influx and downstream TCR signaling. We therefore propose that NaCl is a positive regulator of acute antitumor immunity that might be modulated for ex vivo conditioning of therapeutic T cells, such as CAR T cells.
CRIS-Team Scopus Importer:2024-09-06

SOP - Dealing with multidrug-resistant pathogens on the palliative care unit - Ostgathe, Christoph; Stachura, Peter; Hofmann, Sonja; Van Oorschot, Birgitt; Oechsle, Karin; Bogdan, Christian; Kunz, Hans Bernd; Foertsch, Baerbel; Klein, Carsten (Onkologe, 2017)
EVALuna2:33311

SOP - Handling of multidrug-resistant Pathogens in the Palliative Care Unit - Ostgathe, Christoph; Stachura, Peter; Hofmann, Sonja; Van Oorschot, Birgitt; Oechsle, Karin; Bogdan, Christian; Kunz, Hans Bernd; Foertsch, Baerbel; Klein, Carsten (Onkologe, 2018)
EVALuna2:36423

SOP - Management of multiresistent Pathogens in the Palliative Care Unit - Ostgathe, Christoph; Stachura, Peter; Heckel, Maria; Brunner, Sarah; Gahr, Susanne; Hofmann, Sonja; Van Oorschot, Birgitt; Oechsle, Karin; Bogdan, Christian; Kunz, Bernd; Foertsch, Baerbel; Klein, Carsten (Die Onkologie, 2022)
Infobox 1 SOP aus der Reihe „SOPs zur palliativen Versorgung von Patienten im Netzwerk der deutschen Comprehensive Cancer Center“, erstellt von der AG Palliativmedizin der von der Deutschen Krebshilfe geförderten Comprehensive Cancer Center (CCC
CRIS-Team WoS Importer:2022-10-07

SOP – Umgang mit multiresistenten Erregern auf der Palliativstation - Ostgathe, Christoph; Stachura, Peter; Hofmann, Sonja; van Oorschot, Birgitt; Oechsle, Karin; Bogdan, Christian; Kunz, Bernd; Förtsch, Bärbel; Klein, Carsten (Onkologe, 2017)
CRIS-Team Scopus Importer:2024-02-26

SPIONs functionalized with small peptides for binding of lipopolysaccharide, a pathophysiologically relevant microbial product. - Karawacka, Weronika; Janko, Christina; Unterweger, Harald; Mühlberger, Marina; Lyer, Stefan; Taccardi, Nicola; Mokhir, Andriy; Jira, Wolfgang; Peukert, Wolfgang; Boccaccini, Aldo R.; Kolot, Mikhail; Strauss, Richard; et al. (Colloids and Surfaces B-Biointerfaces, 2018)
Systemic inflammation such as sepsis represents an acute life-threatening condition, to which often no timely remedy can be found. A promising strategy may be to functionalize magnetic nanoparticles with specific peptides, derived from the binding motives of agglutinating salivary proteins, that allow immobilization of pathogens. In this work, superparamagnetic iron oxide nanoparticles with stable polycondensed aminoalkylsilane layer were developed, to which the heterobifunctional linkers N-succinimidyl 3-(2-pyridyldithio)-propanoate (SDPD) and N-succinimidyl bromoacetate (SBA) were bound. These linkers were further chemoselectively reacted with the thiol group of singularly present cysteines of selected peptides. The resulting functional nanoparticles underwent a detailed physicochemical characterization. The biocompatibility of the primarily coated aminoalkylsilane particles was also investigated. To test the pathogen-binding efficacy of the particles, the lipopolysaccharide-immobilization capacity of the peptide-coated particles was compared with free peptides. Here, one particle-bound peptide species succeeded in capturing 90% of the toxin, whereas the degree of immobilization of the toxin with a system that varied in the sequence of the peptide dropped to 35%. With these promising results, we hope to develop extracorporeal magnetic clearance systems for removing pathogens from the human body in order to accelerate diagnosis and alleviate acute disease conditions such as sepsis.

Spontaneous atopic dermatitis in mice with a defective skin barrier is independent of ILC2 and mediated by IL-1β - Schwartz, Christian; Moran, Tara; Saunders, Sean P.; Kaszlikowska, Agnieszka; Floudas, Achilleas; Bom, Joana; Nunez, Gabriel; Iwakura, Yoichiro; O’Neill, Luke; Irvine, Alan D.; McKenzie, Andrew N.J.; Ogg, Graham; et al. (Allergy, 2019)
Background: Atopic dermatitis (AD) is one of the most common skin diseases with a multifactorial etiology. Mutations leading to loss of skin barrier function are associated with the development of AD with group 2 innate lymphoid cells (ILC2) promoting acute skin inflammation. Filaggrin-mutant (Flg ft/ft ) mice develop spontaneous skin inflammation accompanied by an increase in skin ILC2 numbers, IL-1β production, and other cytokines recapitulating human AD. Here, we investigated the role of ILC2, effector cytokines, inflammasome activation, and mast cell function on the development of chronic AD-like inflammation in mice. Methods: Mice with a frameshift mutation in the filaggrin gene develop spontaneous dermatitis. Flg ft/ft mice were crossed to cell- or cytokine-deficient mouse strains, or bred under germ-free conditions. Skin inflammation was scored, and microbiome composition was analyzed. Skin protein expression was measured by multiplex immunoassay. Infiltrating cells were analyzed by flow cytometry. Results: Wild-type and Flg ft/ft mice significantly differ in their microbiome composition. Furthermore, mutant mice do not develop skin inflammation under germ-free conditions. ILC2 deficiency did not ameliorate chronic dermatitis in Flg ft/ft mice, which was also independent of IL-4, IL-5, IL-9, IL-13, IL-17A, and IL-22. Inflammation was independent of NLRP3 inflammasome activation but required IL-1β and IL-1R1-signaling. Mechanistically, IL-1β promoted hyperactivation of IL-1R1-expressing mast cells. Treatment with anti-IL-1β-antibody alleviated dermatitis exacerbation, while antibiotic intervention ameliorated dermatitis in neonatal mice but not in adults with established inflammation. Conclusions: In summary, we identified a critical role for the microbiome and IL-1β mediating chronic inflammation in mice with an impaired skin barrier.
CRIS-Team Scopus Importer:2019-05-17
Keywords: atopic dermatitis; filaggrin; IL-1β; innate lymphoid cells; microbiome

STAT1 coordinates intestinal epithelial cell death during gastrointestinal infection upstream of Caspase-8 - Stolzer, Iris; Schickedanz, Laura; Chiriac, Mircea T.; López-Posadas, Rocío; Grassl, Guntram A.; Mattner, Jochen; Wirtz, Stefan; Neurath, Markus; Günther, Claudia; Winner, Beate (Mucosal Immunology, 2021)
Intestinal homeostasis and the maintenance of the intestinal epithelial barrier are essential components of host defense during gastrointestinal Salmonella Typhimurium infection. Both require a strict regulation of cell death. However, the molecular pathways regulating epithelial cell death have not been completely understood. Here, we elucidated the contribution of central mechanisms of regulated cell death and upstream regulatory components during gastrointestinal infection. Mice lacking Caspase-8 in the intestinal epithelium are highly sensitive towards bacterial induced enteritis and intestinal inflammation, resulting in an enhanced lethality of these mice. This phenotype was associated with an increased STAT1 activation during Salmonella infection. Cell death, barrier breakdown and systemic infection were abrogated by an additional deletion of STAT1 in Casp8ΔIEC mice. In the absence of epithelial STAT1, loss of epithelial cells was abolished which was accompanied by a reduced Caspase-8 activation. Mechanistically, we demonstrate that epithelial STAT1 acts upstream of Caspase-8-dependent as well as -independent cell death and thus might play a major role at the crossroad of several central cell death pathways in the intestinal epithelium. In summary, we uncovered that transcriptional control of STAT1 is an essential host response mechanism that is required for the maintenance of intestinal barrier function and host survival.
CRIS-Team Scopus Importer:2021-09-17

STAT6-dependent deletion and trans-differentiation of alveolar macrophages during allergic airway inflammation - Ruhl, Andreas; Dietschmann, Axel; Murray, P. J.; Vöhringer, David (EUROPEAN JOURNAL OF IMMUNOLOGY, 2022)
CRIS-Team WoS Importer:2023-01-27

Stat6-Dependent Inhibition of Mincle Expression in Mouse and Human Antigen-Presenting Cells by the Th2 Cytokine IL-4 - Hupfer, Thomas; Schick, Judith; Jozefowski, Katrin; Vöhringer, David; Ostrop, Jenny; Lang, Roland (Frontiers in Immunology, 2016)
The C-type lectin receptors (CLRs) Mincle, Mcl, and Dectin-2 bind mycobacterial and fungal cell wall glycolipids and carbohydrates. Recently, we described that expression of these CLR is downregulated during differentiation of human monocytes to dendritic cells (DC) in the presence of GM-CSF and IL-4. Here, we demonstrate that the Th2 cytokine IL-4 specifically inhibits expression of Mincle, Mcl, and Dectin-2 in human antigen-presenting cells (APC). This inhibitory effect of IL-4 was observed across species, as murine macrophages and DC treated with IL-4 also downregulated these receptors. IL-4 blocked upregulation of Mincle and Mcl mRNA expression and cell surface protein by murine macrophages in response to the Mincle ligand Trehalose-6,6-dibehenate (TDB), whereas the TLR4 ligand LPS overcame inhibition by IL-4. Functionally, downregulation of Mincle expression by IL-4 was accompanied by reduced cytokine production upon stimulation with TDB. These inhibitory effects of IL-4 were dependent on the transcription factor Stat6. Together, our results show that the key Th2 cytokine IL-4 exerts a negative effect on the expression of Mincle and other Dectin-2 cluster CLR in mouse and human macrophages and DC, which may render these sentinel cells less vigilant for sensing mycobacterial and fungal ligands.
EVALuna2:7723

STAT6-induced production of mucus and resistin-like molecules in lung Club cells does not protect against helminth or influenza A virus infection - Ruhl, Andreas; Vieira Antao, Ana Isabel; Dietschmann, Axel; Radtke, Daniel; Tenbusch, Matthias; Vöhringer, David (European Journal of Immunology, 2023)
Airway epithelial cells contribute to a variety of lung diseases including allergic asthma, where IL-4 and IL-13 promote activation of the transcription factor STAT6. This leads to goblet cell hyperplasia and the secretion of effector molecules by epithelial cells. However, the specific effect of activated STAT6 in lung epithelial cells is only partially understood. Here, we created a mouse strain to selectively investigate the role of constitutively active STAT6 in Club cells, a subpopulation of airway epithelial cells. CCSP-Cre_STAT6vt mice and bronchiolar organoids derived from these show an enhanced expression of the chitinase-like protein Chil4 (Ym2) and resistin-like molecules (Relm-α, -β, -γ). In addition, goblet cells of these mice spontaneously secrete mucus into the bronchi. However, the activated epithelium resulted neither in impaired lung function nor conferred a protective effect against the migrating helminth Nippostrongylus brasiliensis. Moreover, CCSP-Cre_STAT6vt mice showed similar allergic airway inflammation induced by live conidia of the fungus Aspergillus fumigatus and similar recovery after influenza A virus infection compared to control mice. Together these results highlight that STAT6 signaling in Club cells induces the secretion of Relm proteins and mucus without impairing lung function, but this is not sufficient to confer protection against helminth or viral infections.
CRIS-Team Scopus Importer:2023-11-03
Keywords: Aspergillus fumigatus; Club cell; Influenza a virus; Mucus; Nippostrongylus brasilienis; Relm-α; STAT6

Strain-specific differences in pili formation and the interaction of Corynebacterium diphtheriae with host cells - Ott, Lisa; Höller, Martina; Rheinlaender, Johannes; Schäffer, Tilman; Hensel, Michael; Burkovski, Andreas (BMC Microbiology, 2010)
Background: Corynebacterium diphtheriae, the causative agent of diphtheria, is well-investigated in respect to toxin production, while little is known about C. diphtheriae factors crucial for colonization of the host. In this study, we investigated strain-specific differences in adhesion, invasion and intracellular survival and analyzed formation of pili in different isolates. Results: Adhesion of different C. diphtheriae strains to epithelial cells and invasion of these cells are not strictly coupled processes. Using ultrastructure analyses by atomic force microscopy, significant differences in macromolecular surface structures were found between the investigated C. diphtheriae strains in respect to number and length of pili. Interestingly, adhesion and pili formation are not coupled processes and also no correlation between invasion and pili formation was found. Using RNA hybridization and Western blotting experiments, strain-specific pili expression patterns were observed. None of the studied C. diphtheriae strains had a dramatic detrimental effect on host cell viability as indicated by measurements of transepithelial resistance of Detroit 562 cell monolayers and fluorescence microscopy, leading to the assumption that C. diphtheriae strains might use epithelial cells as an environmental niche supplying protection against antibodies and macrophages. Conclusions: The results obtained suggest that it is necessary to investigate various isolates on a molecular level to understand and to predict the colonization process of different C. diphtheriae strains. © 2010 Ott et al; licensee BioMed Central Ltd.
UnivIS-Import:2015-03-09:Pub.2010.nat.dphy.IAP.LAP.strain

Striking inflammation from both sides: Manganese(II) pentaazamacrocyclic SOD mimics act also as nitric oxide dismutases: A single-cell study - Filipovic, Milos; Koh, Alaric C.W.; Arbault, Stephane; Niketic, Vesna; Debus, Andrea; Schleicher, Ulrike; Bogdan, Christian; Guille, Manon; Lemaitre, Fréderic; Amatore, Christian; Ivanovic-Burmazovic, Ivana (Angewandte Chemie International Edition, 2010)
[Figure Presented] macrophage Removing cytotoxics: A Mn- pentaazamacrocycle removes NO; Cy and their ONOO product as shown by real-time amperometry at single cells (see picture). This is the first compound able to completely abolish the cytotoxic effects of reactive oxygen (ROS) and reactive nitrogen species (RNS) in inflammation. © 2010 Wlley-VCH Verlag GmbH & Co. KGaA.

Structural and functional characterization of SiiA, an auxiliary protein from the SPI4-encoded type 1 secretion system from Salmonella enterica - Kirchweger, Peter; Weiler, Sigrid; Egerer-Sieber, Claudia; Blasl, Anna-Theresa; Hoffmann, Stefanie; Schmidt, Christiane; Sander, Nathalie; Merker, Dorothee; Gerlach, Roman; Hensel, Michael; Muller, Yves (Molecular Microbiology, 2019)
Salmonella invasion is mediated by a concerted action of the Salmonella pathogenicity island 4 (SPI4)-encoded type one secretion system (T1SS) and the SPI1-encoded type three secretion system (T3SS-1). The SPI4-encoded T1SS consists of five proteins (SiiABCDF) and secretes the giant adhesin SiiE. Here, we investigated structure-function relationships in SiiA, a non-canonical T1SS subunit. We show that SiiA consists of a membrane domain, an intrinsically disordered periplasmic linker region and a folded globular periplasmic domain (SiiA-PD). The crystal structure of SiiA-PD displays homology to that of MotB and other peptidoglycan (PG)-binding domains. SiiA-PD binds PG in vitro, albeit at an acidic pH, only. Mutation of Arg162 impedes PG binding of SiiA and reduces Salmonella invasion efficacy. SiiA forms a complex with SiiB at the inner membrane (IM), and the observed SiiA-MotB homology is paralleled by a predicted SiiB-MotA homology. We show that, similar to MotAB, SiiAB translocates protons across the IM. Mutating Asp13 in SiiA impairs proton translocation. Overall, SiiA shares numerous properties with MotB. However, MotAB uses the proton motif force (PMF) to energize the bacterial flagellum, it remains to be shown how usage of the PMF by SiiAB assists T1SS function and Salmonella invasion.
CRIS-Team WoS Importer:2019-10-04

Structural and functional dissection reveals distinct roles of Ca2+-binding sites in the giant adhesin SiiE of Salmonella enterica - Peters, Britta; Stein, Johanna; Klingl, Stefan; Sander, Nathalie; Sandmann, Achim; Taccardi, Nicola; Sticht, Heinrich; Gerlach, Roman; Muller, Yves; Hensel, Michael (PLoS Pathogens, 2017)

Structural insight into the giant Ca²?-binding adhesin SiiE: implications for the adhesion of Salmonella enterica to polarized epithelial cells - Grießl, Martin; Schmid, Benedikt; Kaßler, Kristin; Braunsmann, Christoph; Ritter, Regina; Barlag, Britta; Stierhof, York-Dieter; Sturm, Karina U.; Danzer, Claudia Agnes; Wagner, Carolin; Schaeffer, Tilman E.; Sticht, Heinrich; et al. (Structure, 2013)
SiiE from Salmonella enterica is a giant 5,559-residue-long nonfimbrial adhesin that is secreted by a type 1 secretion system (T1SS) and initiates bacterial adhesion to polarized host cells. Structural insight has been gained into the 53 bacterial Ig-like (BIg) domains of SiiE, which account for 94% of the entire SiiE sequence. The crystal structure of a fragment comprising BIg domains 50 to 52 of SiiE reveals the BIg domain architecture and highlights two types of SiiE-specific Ca²?-binding sites. Sequence homology considerations suggest that full-length SiiE interacts with more than 100 Ca²? ions. Molecular dynamics simulations and single-molecule imaging indicate that Ca²? binding confers SiiE with a rigid 200 nm rod-like habitus that is required to reach out beyond the Salmonella lipopolysaccharide layer and to promote adhesion to host cells. The crystal structure suggests plausible routes for the establishment of the initial contact between Salmonella and host cells.
EVALuna2:7643

Studying Coxiella burnetii Type IV Substrates in the Yeast Saccharomyces cerevisiae: Focus on Subcellular Localization and Protein Aggregation - Rodriguez-Escudero, Maria; Cid, Victor J.; Molina, Maria; Schulze-Luehrmann, Jan; Lührmann, Anja; Rodriguez-Escudero, Isabel (PLoS ONE, 2016)
Coxiella burnetii is a Gram-negative obligate parasitic bacterium that causes the disease Q-fever in humans. To establish its intracellular niche, it utilizes the Icm/Dot type IVB secretion system (T4BSS) to inject protein effectors into the host cell cytoplasm. The host targets of most cognate and candidate T4BSS-translocated effectors remain obscure. We used the yeast Saccharomyces cerevisiae as a model to express and study six C. burnetii effectors, namely AnkA, AnkB, AnkF, CBU0077, CaeA and CaeB, in search for clues about their role in C. burnetii virulence. When ectopically expressed in HeLa cells, these effectors displayed distinct subcellular localizations. Accordingly, GFP fusions of these proteins produced in yeast also decorated distinct compartments, and most of them altered cell growth. CaeA was ubiquitinated both in yeast and mammalian cells and, in S. cerevisiae, accumulated at juxtanuclear quality-control compartments (JUNQs) and insoluble protein deposits (IPODs), characteristic of aggregative or misfolded proteins. AnkA, which was not ubiquitinated, accumulated exclusively at the IPOD. CaeA, but not AnkA or the other effectors, caused oxidative damage in yeast. We discuss that CaeA and AnkA behavior in yeast may rather reflect misfolding than recognition of conserved targets in the heterologous system. In contrast, CBU0077 accumulated at vacuolar membranes and abnormal ER extensions, suggesting that it interferes with vesicular traffic, whereas AnkB associated with the yeast nucleolus. Both effectors shared common localization features in HeLa and yeast cells. Our results support the idea that C. burnetii T4BSS effectors manipulate multiple host cell targets, which can be conserved in higher and lower eukaryotic cells. However, the behavior of CaeA and AnkA prompt us to conclude that heterologous protein aggregation and proteostatic stress can be a limitation to be considered when using the yeast model to assess the function of bacterial effectors.
EVALuna2:7710

Subversion of a family of antimicrobial proteins by Salmonella enterica - Gerlach, Roman; Wittmann, Irene; Heinrich, Lena; Pinkenburg, Olaf; Meyer, Torben; Elpers, Laura; Schmidt, Christiane; Hensel, Michael; Schnare, Markus (Frontiers in Cellular and Infection Microbiology, 2024)
Salmonella enterica is a food-borne pathogen able to cause a wide spectrum of diseases ranging from mild gastroenteritis to systemic infections. During almost all stages of the infection process Salmonella is likely to be exposed to a wide variety of host-derived antimicrobial peptides (AMPs). AMPs are important components of the innate immune response which integrate within the bacterial membrane, thus forming pores which lead ultimately to bacterial killing. In contrast to other AMPs Bactericidal/Permeability-increasing Protein (BPI) displayed only weak bacteriostatic or bactericidal effects towards Salmonella enterica sv. Typhimurium (STM) cultures. Surprisingly, we found that sub-antimicrobial concentrations of BPI fold-containing (BPIF) superfamily members mediated adhesion of STM depending on pre-formed type 1 fimbriae. BPIF proteins directly bind to type 1 fimbriae through mannose-containing oligosaccharide modifications. Fimbriae decorated with BPIF proteins exhibit extended binding specificity, allowing for bacterial adhesion on a greater variety of abiotic and biotic surfaces likely promoting host colonization. Further, fimbriae significantly contributed to the resistance against BPI, probably through sequestration of the AMP before membrane interaction. In conclusion, functional subversion of innate immune proteins of the BPIF family through binding to fimbriae promotes Salmonella virulence by survival of host defense and promotion of host colonization.
CRIS-Team Scopus Importer:2024-03-29
Keywords: adhesion; antimicrobial proteins and peptides; antimicrobial resistance; bactericidal permeability increasing protein; Salmonella Typhimurium; type 1 fimbriae

Successful eradication of newly acquired MRSA in six of seven patients with cystic fibrosis applying a short-term local and systemic antibiotic scheme - Kiefer, Alexander; Bogdan, Christian; Melichar, Volker O. (BMC Pulmonary Medicine, 2018)
BACKGROUND: In individuals with cystic fibrosis (CF), colonization with methicillin-resistant Staphylococcus aureus (MRSA) was reported to be associated with a deterioration of pulmonary disease as reflected by an accelerated decline in lung function. Thus, an early eradication of MRSA could be beneficial in these patients. Here, we report on an intensified MRSA eradication protocol. METHODS: Since 2012 a protocol for the eradication of newly acquired MRSA has been used in our CF Clinic, combining oral rifampicin and fusidic acid, inhaled vancomycin, nasal mupirocin, local antiseptic treatment and hygienic directives all of which are applied for only 7 days during an inpatient hospital stay. RESULTS: Since 2012 seven patients (3 male, 4 female; age range 4 to 30 years) newly acquired MRSA. In 6 of the 7 patients (86%) successful eradication of MRSA was achieved upon first treatment using the protocol described above. In one patient a second course of treatment was performed which, however, also failed to eliminate the colonizing MRSA. CONCLUSIONS: Our protocol led to an eradication rate of 86%. The impact of each individual component of the protocol remains to be determined.
EVALuna2:33304

Success of Helicobacter pylori Guideline-based Treatment of Newly Diagnosed and Previously Treated Patients During 2007–2021 in Edmonton, Alberta - Krahn, Thomas; Buttenschön, Jonas; D’Souza, Pernilla; Girgis, Safwat; Thiesen, Aducio; Rennie, Robert; Turnbull, Lee Ann; van Zanten, Sander Veldhuyzen (Journal of the Canadian Association of Gastroenterology, 2024)
Background: Updated 2016 Helicobacter pylori consensus guidelines recommend treatment for 14 days with concomitant therapy (proton-pump inhibitor (PPI)-amoxicillin-metronidazole-clarithromycin (PAMC) or bismuth-based quadruple therapy (PPI-bismuth-metronidazole-tetracycline, PBMT)) as first line, PBMT or PPI-amoxicillin-levofloxacin (PAL) as second or third line, and PPI-amoxicillin-rifabutin (PAR) as fourth line for 10 days. Objectives: This was a retrospective cohort study to describe and compare the efficacy of anti-Helicobacter treatment regimens over the periods 2007–2015 and 2016–2021 as well as antibiotic resistance. Methods: A modified intention-to-treat (mITT) analysis was used to analyze the success rate of therapies. mITT includes all patients who were prescribed H. pylori treatment and had at least one follow-up test-of-cure. This included patients who could not complete treatment or were non-adherent with treatment. Risk factors for treatment failures were analyzed by univariate and multivariate logistic regression. Resistance testing was done in a small subset of patients. Results: H. pylori-positive patients who received treatment in Edmonton, Alberta were included in a mITT analysis: 334/387(86%) from 2007 to 2015 and 193/199 (97%) from 2016 to 2021. During 2016–2021, 78% (150/193) of patients underwent cumulative guideline-based treatment with a successful cure in 80% (120/150) of patients. In those who were newly diagnosed, the cure rate was 88% (52/59) versus those with previous treatment failure 75% (68/91) (P < 0.05, risk difference [RD] 14%, 95% confidence interval [CI] 1.7–26.3%). The most effective first-line regimens were PAMC for 14 days (87% [45/52]) in 2016–2021 and sequential therapy in 2007–2015 (83% [66/80]) (P = 0.535, RD 4%, 95% CI −8.5–16.5%). When other treatments failed, success with PAR was 50% (2/4) from 2007 to 2015 and 57% (21/37) from 2016 to 2021. Recent (2016–2021) resistance rates to clarithromycin and metronidazole are high at 78% (50/64) and 56% (29/52), respectively. From 2007 to 2015, clarithromycin and metronidazole resistance rates were 80% (36/45) and 83% (38/46), respectively. Levofloxacin resistance increased significantly from 2007–2015 to 2016–2021 (28% [13/46] to 61% [35/57], P < 0.05, RD 33%, 95% CI 11.6–54.4%). Conclusions: Algorithmic treatment with PAMC first line followed by PBMT, PAL, and PAR cures H. pylori in 88% of newly diagnosed patients. PAR therapy shows suboptimal cure rates (50–57% success) but can be considered as third instead of fourth line given increasing levofloxacin resistance rates. Antibiotic resistance in H. pylori is common to clarithromycin, metronidazole, and levofloxacin and frequently accounts for treatment failures.
CRIS-Team Scopus Importer:2024-10-11
Keywords: antibiotic resistance; Helicobacter pylori

Suppressor of Cytokine Signaling 3 in Macrophages Prevents Exacerbated Interleukin-6-Dependent Arginase-1 Activity and Early Permissiveness to Experimental Tuberculosis - Schmok, Erik; Dar, Mahin Abad; Behrends, Jochen; Erdmann, Hanna; Rueckerl, Dominik; Endermann, Tanja; Heitmann, Lisa; Hessmann, Manuela; Yoshimura, Akihiko; Rose-John, Stefan; Scheller, Juergen; Schaible, Ulrich Emil; et al. (Frontiers in Immunology, 2017)
Suppressor of cytokine signaling 3 (SOCS3) is a feedback inhibitor of interleukin (IL)-6 signaling in macrophages. In the absence of this molecule, macrophages become extremely prone to an IL-6-dependent expression of arginase-1 (Arg1) and nitric oxide synthase (NOS)2, the prototype markers for alternative or classical macrophage activation, respectively. Because both enzymes are antipodean macrophage effector molecules inMycobacterium tuberculosis(Mtb) infection, we assessed the relevance of SOCS3 for macrophage activation during experimental tuberculosis using macrophage-specific SOCS3-deficient (LysMcreSOCS3loxP/loxP) mice. Aerosol infection of LysMcreSOCS3loxP/loxPmice resulted in remarkably higher bacterial loads in infected lungs and exacerbated pulmonary inflammation. This increased susceptibility toMtbinfection was accompanied by enhanced levels of both classical and alternative macrophage activation. However, high Arg1 expression preceded the increased induction of NOS2 and at early time points of infection mycobacteria were mostly found in cells positive for Arg1. This sequential activation of Arg1 and NOS2 expression in LysMcreSOCS3loxP/loxPmice appears to favor the initial replication ofMtbparticularly in Arg1-positive cells. Neutralization of IL-6 inMtb-infected LysMcreSOCS3loxP/loxPmice reduced arginase activity and restored control of mycobacterial replication in LysMcreSOCS3loxP/loxPmice. Our data reveal an unexpected role of SOCS3 during experimental TB: macrophage SOCS3 restrains early expression of Arg1 and helps limitMtbreplication in resident lung macrophages, thereby limiting the growth of mycobacteria. Together, SOCS3 keeps IL-6-dependent divergent macrophage responses such asNos2andArg1expression under control and safeguard protective macrophage effector mechanisms.
EVALuna2:33300

Swiprosin-1/EFhd2 limits germinal center responses and humoral type 2 immunity - Brachs, Sebastian; Turqueti-Neves, Adriana; Stein, Merle; Reimer, Dorothea; Brachvogel, Bent; Boesl, Michael; Winkler, Thomas; Vöhringer, David; Jäck, Hans-Martin; Mielenz, Dirk (European Journal of Immunology, 2014)
Activated B cells are selected for in germinal centers by regulation of their apoptosis. The Ca2+ -binding cytoskeletal adaptor protein Swiprosin-1/EFhd2 (EFhd2) can promote apoptosis in activated B cells. We therefore hypothesized that EFhd2 might limit humoral immunity by repressing both the germinal center reaction and the expected enhancement of immune responses in the absence of EFhd2. Here, we established EFhd2(-/-) mice on a C57BL/6 background, which revealed normal B- and T-cell development, basal Ab levels, and T-cell independent type 1, and T-cell independent type 2 responses. However, T cell-dependent immunization with sheep red blood cells and infection with the helminth Nippostrongylus brasiliensis (N.b) increased production of antibodies of multiple isotypes, as well as germinal center formation in EFhd2(-/-) mice. In addition, serum IgE levels and numbers of IgE+ plasma cells were strongly increased in EFhd2(-/-) mice, both after primary as well as after secondary N.b infection. Finally, mixed bone marrow chimeras unraveled an EFhd2-dependent B cell-intrinsic contribution to increased IgE plasma cell numbers in N.b-infected mice. Hence, we established a role for EFhd2 as a negative regulator of germinal center-dependent humoral type 2 immunity, with implications for the generation of IgE.
EVALuna2:13618

Synthesis of dihydrooxazole analogues derived from linezolid - Schoerner, Christoph; Gmeiner, Peter; Einsiedel, Jürgen (Tetrahedron, 2003)
Starting from (S)-serine, the linezolid analogue 3 with dihydrooxazole partial structure was synthesized and pharmacologically investigated. With the help of MEP comparisons structural requirements for antibacterial activity were evaluated. © 2003 Elsevier Science Ltd. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2003.med.IKMI.LHMMIPDR.synthe
Keywords: Antibiotics; Dihydrooxazoles; Serine

Synthetic Lipoteichoic Acid Glycans Are Potential Vaccine Candidates to Protect from Clostridium difficile Infections - Broecker, Felix; Martin, Christopher E.; Wegner, Erik; Mattner, Jochen; Baek, Ju Yuel; Pereira, Claney L.; Anish, Chakkumkal; Seeberger, Peter H. (Cell Chemical Biology, 2016)
Infections with Clostridium difficile increasingly cause morbidity and mortality worldwide. Bacterial surface glycans including lipoteichoic acid (LTA) were identified as auspicious vaccine antigens to prevent colonization. Here, we report on the potential of synthetic LTA glycans as vaccine candidates. We identified LTA-specific antibodies in the blood of C. difficile patients. Therefore, we evaluated the immunogenicity of a semi-synthetic LTA-CRM197 glycoconjugate. The conjugate elicited LTA-specific antibodies in mice that recognized natural LTA epitopes on the surface of C. difficile bacteria and inhibited intestinal colonization of C. difficile in mice in vivo. Our findings underscore the promise of synthetic LTA glycans as C. difficile vaccine candidates.
EVALuna2:7716

Synthetic Oligosaccharide-Based Vaccines Protect Mice from Clostridioides difficile Infections - Broecker, Felix; Wegner, Erik; Seco, Bruna M.S.; Kaplonek, Paulina; Bräutigam, Maria; Enßer, Armin; Pfister, Frederick; Daniel, Christoph; Martin, Christopher E.; Mattner, Jochen; Seeberger, Peter H. (ACS Chemical Biology, 2019)
Infections with Clostridioides difficile (formerly Clostridium difficile) have increased in incidence, morbidity, and mortality over the past decade. Preventing infections is becoming increasingly important, as frontline antibiotics become less effective and frequently induce recurrence by disrupting intestinal microbiota. The clinically most advanced vaccine approaches prevent symptoms once C. difficile infection is established by inducing immunity to secreted clostridial cytotoxins. However, they do not inhibit bacterial colonization and thereby favor asymptomatic carriage. Synthetic oligosaccharides resembling the C. difficile surface glycans PS-I, PS-II, and PS-III are immunogenic and serve as basis for colonization-preventing vaccines. Here, we demonstrate that glycoconjugate vaccine candidates based on synthetic oligosaccharides protected mice from infections with two different C. difficile strains. Four synthetic antigens, ranging in size from disaccharides to hexasaccharides, were conjugated to CRM197, which is a carrier protein used in commercial vaccines. The vaccine candidates induced glycan-specific antibodies in mice and substantially limited C. difficile colonization and colitis after experimental infection. The glycoconjugates ameliorated intestinal pathology more substantially than a toxin-targeting vaccine. Colonization of the gut by C. difficile was selectively inhibited while intestinal microbiota remained preserved. Passive transfer experiments with anti-PS-I serum revealed that protection is mediated by specific antiglycan antibodies; however, cell-mediated immunity likely also contributed to protection in vivo. Thus, glycoconjugate vaccines against C. difficile are a complementary approach to toxin-targeting strategies and are advancing through preclinical work.
CRIS-Team Scopus Importer:2019-12-03

Synthetic oligosaccharide-based vaccines protect mice from Clostridium difficile infections - Mattner, Jochen; Enßer, Armin; Seeberger, P. (EUROPEAN JOURNAL OF IMMUNOLOGY, 2019)
CRIS-Team WoS Importer:2019-10-08

Targeted Second-Line Treatment - Jantsch, Jonathan; Bogdan, Christian (Deutsches Ärzteblatt, 2010)
CRIS-Team Scopus Importer:2024-02-26

T cell-derived IL-4/IL-13 protects mice against fatal Schistosoma mansoni infection independently of basophils - Schwartz, Christian; Oeser, Katharina; Da Costa, Clarissa Prazeres; Layland, Laura E.; Vöhringer, David (Journal of Immunology, 2014)
Schistosomiasis is a severe and chronic disease caused by the parasitic trematode Schistosoma mansoni after deposition of eggs in the liver and intestines. The immune response to S. mansoni eggs is characterized by increased Th2 cells, eosinophilia, and high serum IgE levels. Granulomas are formed around the eggs to protect the organs against tissue damage caused by toxic products that are secreted from the eggs. Egg-derived components have further been shown to activate the IgE-mediated release of IL-4 and IL-13 from basophils, suggesting that basophils could be involved in protection against a fatal course of infection. Using T cell-specific IL-4/IL-13-deficient mice and basophil-deficient Mcpt8Cre mice, we determined the contribution of Th2 cells and basophils for protective immunity against S. mansoni egg-induced pathology during the patent stage of infection. Our results demonstrate that T cell-derived IL-4/IL-13 was essential for granuloma formation, IgE production, basophilia, differentiation of alternatively activated macrophages, and protection against fatal infection. Although basophils were recruited into liver granulomas, they appeared to be dispensable as a source of IL-4/IL-13 both for differentiation of Th2 cells and for prevention of weight loss and mortality.
EVALuna2:25868

T cells are the critical source of IL-4/IL-13 in a mouse model of allergic asthma - Oeser, Katharina; Maxeiner, J.; Symowski, Cornelia; Stassen, M.; Vöhringer, David (Allergy, 2015)
IL-4 and IL-13 play a crucial role during allergic asthma. Both cytokines can be produced by T cells and a variety of cell types of the innate immune system. The relative contribution of T-cell-derived vs innate IL-4/IL-13 for allergic inflammation and airway hyperreactivity remains unclear.We compared the severity of OVA/alum-induced allergic lung inflammation in WT BALB/c mice to mice that lack expression of IL-4/IL-13 only in T cells (4-13Tko) or in all cell types (4-13ko).T-cell-derived IL-4/IL-13 was required for IgG1 and IgE production, recruitment of eosinophils and basophils to the lung, goblet cell hyperplasia, expression of Muc5ac, Clca3, and RELM?, differentiation of alternatively activated macrophages, and airway hyperreactivity. Interestingly, ILC2 recruitment to the lung occurred independently of T-cell-derived IL-4/IL-13 but was diminished in the absence of IL-4/IL-13 from all cell types. Thus, the number of IL-4/IL-13-competent ILC2s did not correlate with the severity of lung pathology.Th2 cells appear to be the critical IL-4/IL-13-expressing cell type for the induction of allergic airway inflammation and airway hyperreactivity. The translational perspective of our results indicates that inhibition or reprogramming of Th2 cells may be very effective for the treatment of allergic asthma.
EVALuna2:25864

TCR/CD3-based synthetic antigen receptors (TCC) convey superior antigen sensitivity combined with high fidelity of activation - Mühlgrabner, Vanessa; Peters, Timo; Velasco Cárdenas, Rubí M.H.; Salzer, Benjamin; Göhring, Janett; Plach, Angelika; Höhrhan, Maria; Perez, Iago Doel; Reis Goncalves, Vasco Dos; Farfán, Jesús Siller; Lehner, Manfred; Stockinger, Hannes; et al. (Science Advances, 2024)
Low antigen sensitivity and a gradual loss of effector functions limit the clinical applicability of chimeric antigen receptor (CAR)–modified T cells and call for alternative antigen receptor designs for effective T cell–based cancer immunotherapy. Here, we applied advanced microscopy to demonstrate that TCR/CD3-based synthetic constructs (TCC) outperform second-generation CAR formats with regard to conveyed antigen sensitivities by up to a thousandfold. TCC-based antigen recognition occurred without adverse nonspecific signaling, which is typically observed in CAR–T cells, and did not depend—unlike sensitized peptide/MHC detection by conventional T cells—on CD4 or CD8 coreceptor engagement. TCC-endowed signaling properties may prove critical when targeting antigens in low abundance and aiming for a durable anticancer response.
CRIS-Team Scopus Importer:2024-09-20

Tet-on, or Tet-off, that is the question: Advanced conditional gene expression in Aspergillus - Wanka, Franziska; Cairns, Timothy; Boecker, Simon; Berens, Christian; Happel, Anna; Zheng, Xiaomei; Sun, Jibin; Krappmann, Sven; Meyer, Vera (Fungal Genetics and Biology, 2015)
In Aspergillus, controlled gene expression is often achieved using the reverse tetracycline-controlled transactivator (rtTA) dependent Tet-on system, whereby transcription is activated in a titratable manner by addition of the tetracycline derivative doxycycline. The complementary Tet-off system utilises the tetracycline-controlled transactivator (tTA) component to quantitatively reduce gene expression. In this study, we utilised a synthetic biological approach to engineer highly optimised Tet-off conditional expression systems in Aspergillus niger and Aspergillus fumigatus. Steps for delivery of these tools include utilising codon optimised cassette components, testing several promoters for improved genetic stability and validating two modified luciferase reporters for highly accurate measurements of gene expression. The Tet-off cassettes developed in this study enable facile and quantitative functional analysis, as validated by Tet-off analysis of genes involved in chitin synthesis and cell wall polarity in A. niger, and para-aminobenzoic acid synthesis in A. fumigatus. We also used a racA(G18V) dominant allele to demonstrate that Tet-off in A. niger enables gene over-expression and downregulation in a single isolate. Additionally, we used the improved luciferase reporters to show that the Tet-off cassette in A. niger enables quantification of gene oscillations. In order to demonstrate that synthetic biological approaches developed here are broadly applicable to engineering transcriptional circuits in filamentous fungi, we used our strategy for improving cassette stability by promoter replacement in the A. niger Tet-on system, which resulted in a modified Tet-on cassette with higher stability in recipient genomes.
EVALuna2:7694

Th2 and eosinophil responses ameliorate arthritis and inflammatory bone loss - Andreev, Darja; Chen, Zhu; Oeser, Katharina; Krljanac, B.; Hueber, Axel; Kleyer, Arnd; Weigmann, Benno; Vöhringer, David; Schett, Georg; Bozec, Aline (2017)
EVALuna2:33419

Th2 and eosinophil responses suppress inflammatory arthritis - Chen, Zhu; Andreev, Darja; Oeser, Katharina; Krljanac, Branislav; Hueber, Axel; Kleyer, Arnd; Vöhringer, David; Schett, Georg; Bozec, Aline (Nature Communications, 2016)
Th2-eosinophil immune responses are well known for mediating host defence against helminths. Herein we describe a function of Th2-eosinophil responses in counteracting the development of arthritis. In two independent models of arthritis, Nippostrongylus brasiliensis infection leads to Th2 and eosinophil accumulation in the joints associated with robust inhibition of arthritis and protection from bone loss. Mechanistically, this protective effect is dependent on IL-4/IL-13-induced STAT6 pathway. Furthermore, we show that eosinophils play a central role in the modulation of arthritis probably through the increase of anti-inflammatory macrophages into arthritic joints. The presence of these pathways in human disease is confirmed by detection of GATA3-positive cells and eosinophils in the joints of rheumatoid arthritis patients. Taken together, these results demonstrate that eosinophils and helminth-induced activation of the Th2 pathway axis effectively mitigate the course of inflammatory arthritis.
EVALuna2:13286

Th2 cell-derived IL-4/IL-13 promote ILC2 accumulation in the lung by ILC2-intrinsic STAT6 signaling in mice - Symowski, Cornelia; Vöhringer, David (European Journal of Immunology, 2019)
Infection of mice with the gastrointestinal helminth Nippostrongylus brasiliensis elicits profound local proliferation and accumulation of type 2 innate lymphoid cells (ILC2s) in the lung. The regulation of ILC2 proliferation and accumulation in the lung is poorly understood. Using T cell-specific IL-4/IL-13-deficient mice, we demonstrate that IL-4/IL-13 secretion from Th2 cells promotes proliferation and expansion of the ILC2 population in the lung of N. brasiliensis-infected mice. Competitive mixed BM chimeras containing normal and STAT6-deficient ILC2s further indicated that ILC2s have to respond directly to IL-4/IL-13 for this effect while STAT6 is not required for IL-13 production in ILC2s. In addition, expression of a constitutively active form of STAT6 in ILC2s was sufficient to promote their proliferation in uninfected mice. The expression of MHC class II in ILC2s appeared to be enhanced by STAT6 signaling supporting the concept that Th2 cells and ILC2s can communicate in an antigen-dependent manner resulting in a Th2-regulated accumulation of ILC2s in the lung during an acute type 2 immune response. Based on our observations, targeting the STAT6 pathway in ILC2s could help to develop new treatments to dampen ILC2 proliferation in the lung and thereby ameliorate ILC2-mediated allergic inflammation.
CRIS-Team Scopus Importer:2019-06-21
Keywords: Allergy; Asthma; Helminths; ILC2 homeostasis; Type 2 immunity

Th2 cells promote eosinophil-independent pathology in a murine model of allergic bronchopulmonary aspergillosis - Dietschmann, Axel; Schruefer, Sebastian; Krappmann, Sven; Vöhringer, David (European Journal of Immunology, 2020)
Repeated inhalation of airborne conidia derived from the fungus Aspergillus fumigatus (Af) can lead to a severe eosinophil-dominated inflammatory condition of the lung termed allergic bronchopulmonary aspergillosis (ABPA). ABPA affects about 5 million individuals worldwide and the mechanisms regulating lung pathology in ABPA are poorly understood. Here, we used a mouse model of ABPA to investigate the role of eosinophils and T cell-derived IL-4/IL-13 for induction of allergic lung inflammation. Selective deletion of IL-4/IL-13 in T cells blunted the Af-induced lung eosinophilia and further resulted in lower expression of STAT6-regulated chemokines and effector proteins such as Arginase 1, Relm-α, Relm-β, and Muc5a/c. Eosinophil-deficient ΔdblGata mice showed lower IL-4 expression in the lung and the number of Th2 cells in the lung parenchyma was reduced. However, expression of the goblet cell markers Clca1 and Muc5a/c, abundance of mucin-positive cells, as well as weight gain of lungs were comparable between Af-challenged ΔdblGata and WT mice. Based on these results, we conclude that T cell-derived IL-4/IL-13 is essential for Af-induced lung eosinophilia and inflammation while eosinophils may play a more subtle immunomodulatory role and should not simply be regarded as pro-inflammatory effector cells in ABPA.
CRIS-Team Scopus Importer:2020-03-20
Keywords: allergy; Aspergillus fumigatus; eosinophils; IL-4/IL-13; lung inflammation

Th2-dependent disappearance and phenotypic conversion of mouse alveolar macrophages - Dietschmann, Axel; Ruhl, Andreas; Murray, Peter J.; Günther, Claudia; Becker, Christoph; Fallon, Padraic; Vöhringer, David (European Journal of Immunology, 2023)
Alveolar macrophages (alvMs) play an important role for maintenance of lung function by constant removal of cellular debris in the alveolar space. They further contribute to defense against microbial or viral infections and limit tissue damage during acute lung injury. alvMs arise from embryonic progenitor cells, seed the alveoli before birth, and have life-long self-renewing capacity. However, recruited monocytes may also help to restore the alvM population after depletion caused by toxins or influenza virus infection. At present, the population dynamics and cellular plasticity of alvMs during allergic lung inflammation is poorly defined. To address this point, we used a mouse model of Aspergillus fumigatus-induced allergic lung inflammation and observed that Th2-derived IL-4 and IL-13 caused almost complete disappearance of alvMs. This effect required STAT6 expression in alvMs and also occurred in various other settings of type 2 immunity-mediated lung inflammation or administration of IL-4 complexes to the lung. In addition, Th2 cells promoted conversion of alvMs to alternatively activated macrophages and multinucleated giant cells. Given the well-established role of alvMs for maintenance of lung function, this process may have implications for resolution of inflammation and tissue homeostasis in allergic asthma.
CRIS-Team Scopus Importer:2023-11-03
Keywords: Allergic asthma; Alternatively activated macrophages; Alveolar macrophages; Aspergillus; Multinucleated giant cells; STAT6

Th2-dependent STAT6-regulated genes in intestinal epithelial cells mediate larval trapping during secondary Heligmosomoides polygyrus bakeri infection - Westermann, Stefanie; Schubart, Christoph; Dietschmann, Axel; Castiglione, Kirstin; Radtke, Daniel; Vöhringer, David (PLoS Pathogens, 2023)
Gastrointestinal helminths are a major health threat worldwide. Alternatively activated macrophages (AAMs) have been shown to contribute to host protection during secondary helminth infections. AAMs express effector molecules that depend on activation of the IL-4- or IL-13-induced transcription factor signal transducer and activator of transcription 6 (STAT6). However, the specific role of STAT6-regulated genes like Arginase-1 (Arg1) from AAMs or STAT6-regulated genes in other cell types for host protection remains unclear. To address this point, we generated mice expressing STAT6 only in macrophages (Mac-STAT6 mouse). In the model of Heligmosomoides polygyrus bakeri (Hpb) infection, Mac-STAT6 mice could not trap larvae in the submucosa of the small intestine after secondary infection. Further, mice lacking Arg1 in hematopoietic and endothelial cells were still protected from secondary Hpb infection. On the other hand, specific deletion of IL-4/IL-13 in T cells blunted AAM polarization, activation of intestinal epithelial cells (IECs) and protective immunity. Deletion of IL-4Rα on IEC also caused loss of larval trapping while AAM polarization remained intact. These results show that Th2-dependent and STAT6-regulated genes in IECs are required and AAMs are not sufficient for protection against secondary Hpb infection by mechanisms that remain to be investigated.
CRIS-Team Scopus Importer:2023-04-28

Th2 single-cell heterogeneity and clonal distribution at distant sites in helminth-infected mice - Radtke, Daniel; Thuma, Natalie; Schülein, Christine; Kirchner, Philipp; Ekici, Arif Bülent; Schober, Kilian; Vöhringer, David (eLife, 2022)
Th2 cells provide effector functions in type 2 immune responses to helminths and allergens. Despite knowledge about molecular mechanisms of Th2 cell differentiation, there is little information on Th2 cell heterogeneity and clonal distribution between organs. To address this, we performed combined single-cell transcriptome and T-cell receptor (TCR) clonotype analysis on murine Th2 cells in mesenteric lymph nodes (MLNs) and lung after infection with Nippostrongylus brasiliensis (Nb) as a human hookworm infection model. We find organ-specific expression profiles, but also populations with conserved migration or effector/resident memory signatures that unexpectedly cluster with potentially regulatory Il10(pos)Foxp3(neg) cells. A substantial MLN subpopulation with an interferon response signature suggests a role for interferon signaling in Th2 differentiation or diversification. Further RNA-inferred developmental directions indicate proliferation as a hub for differentiation decisions. Although the TCR repertoire is highly heterogeneous, we identified expanded clones and CDR3 motifs. Clonal relatedness between distant organs confirmed effective exchange of Th2 effector cells, although locally expanded clones dominated the response. We further cloned an Nb-specific TCR from an expanded clone in the lung effector cluster and describe surface markers that distinguish transcriptionally defined clusters. These results provide insights in Th2 cell subset diversity and clonal relatedness in distant organs.
CRIS-Team WoS Importer:2022-09-02

The anti-apoptotic Coxiella burnetii effector protein AnkG is a strain specific virulence factor - Schäfer, Walter; Schmidt, Tamara; Cordsmeier, Arne; Borges, Vítor; Beare, Paul A.; Pechstein, Julian; Schulze-Luehrmann, Jan; Holzinger, Jonas; Wagner, Nicole; Berens, Christian; Heydel, Carsten; Gomes, João Paulo; et al. (Scientific Reports, 2020)
The ability to inhibit host cell apoptosis is important for the intracellular replication of the obligate intracellular pathogen Coxiella burnetii, as it allows the completion of the lengthy bacterial replication cycle. Effector proteins injected into the host cell by the C. burnetii type IVB secretion system (T4BSS) are required for the inhibition of host cell apoptosis. AnkG is one of these anti-apoptotic effector proteins. The inhibitory effect of AnkG requires its nuclear localization, which depends on p32-dependent intracellular trafficking and importin-α1-mediated nuclear entry of AnkG. Here, we compared the sequences of ankG from 37 C. burnetii isolates and classified them in three groups based on the predicted protein size. The comparison of the three different groups allowed us to identify the first 28 amino acids as essential and sufficient for the anti-apoptotic activity of AnkG. Importantly, only the full-length protein from the first group is a bona fide effector protein injected into host cells during infection and has anti-apoptotic activity. Finally, using the Galleria mellonella infection model, we observed that AnkG from the first group has the ability to attenuate pathology during in vivo infection, as it allows survival of the larvae despite bacterial replication.
CRIS-Team Scopus Importer:2020-10-02

The Aspergillus galactomannan Ag VIRCLIA® Monotest and the sõna Aspergillus galactomannan lateral flow assay show comparable performance for the diagnosis of invasive aspergillosis - Küpper, Corinna; Erb, Timothy Moritz; Träger, Johannes; Meintker, Lisa; Valenza, Giuseppe; Bogdan, Christian; Held, Jürgen (Mycoses, 2024)
Background: Rapid galactomannan tests, such as the sõna Aspergillus GM Lateral Flow Assay (GM-LFA) and the Aspergillus Galactomannan Ag VIRCLIA® Monotest (GM-Monotest), which are suitable for the analysis of single samples, have the potential to accelerate diagnosis of invasive aspergillosis (IA). Objectives: To compare the performance of the GM-Monotest and the GM-LFA for the diagnosis of IA. Patients/Methods: Two patient cohorts were analysed: adults who had received an allogeneic haematopoietic stem-cell transplant (alloHSCT-cohort) and patients with proven/probable IA from a 5-year period (cross-sectional IA-cohort). In the alloHSCT-cohort, weekly serum samples were tested, whereas in the cross-sectional IA-cohort sera and bronchoalveolar lavage fluids were analysed. The diagnostic performance was calculated using two definitions for positivity: (1) a single positive GM result and (2) at least two positive GM results from consecutive samples. IA classification followed EORTC/MSG 2019. Results: The alloHSCT-cohort included 101 patients. Four had proven/probable IA, 26 possible IA and 71 no IA. The specificity for one positive serum and two consecutively positive sera was 88.7% and 100% (GM-Monotest) and 85.9% and 98.6% (GM-LFA). Comparison of ROC curves in the alloHSCT-cohort showed no significant difference. The cross-sectional IA-cohort included 59 patients with proven/probable IA. The sensitivity for one positive sample and two consecutively positive samples was 83.1% and 55.1% (GM-Monotest) and 86.4% and 71.4% (GM-LFA). Conclusions: Both assays showed comparable diagnostic performance with a higher sensitivity for the GM-LFA if two consecutive positive samples were required for positivity. However, due to poor reproducibility, positive GM-LFA results should always be confirmed.
CRIS-Team Scopus Importer:2024-08-16
Keywords: antigen; invasive fungal disease; invasive fungal infection; Platelia; POCT; point-of-care test

The B-cell antigen receptor of IgE-switched plasma cells regulates memory IgE responses - Schmitt, Michaela; Lutz, Johannes; Haase, Paul; Bösl, Michael R.; Wienands, Jürgen; Engels, Niklas; Vöhringer, David (Journal of Allergy and Clinical Immunology, 2020)
Background: Allergic inflammation is driven by IgE-producing plasma cells (PCs), which are required for IgE-mediated activation of mast cells and basophils. Repeated antigen encounter elicits a memory IgE response with elevated serum IgE titers and accumulation of IgE-producing PCs. However, the cellular compartment and molecular signals that underlie the immunologic memory of IgE responses remain unclear. Objective: With this study we aimed at clarifying whether inactivation of the cytoplasmic immunoglobulin tail tyrosine (ITT) motif in transmembrane IgE (mIgE) impairs the memory IgE response in mice. Methods: We generated mice with an inactivated mIgE-ITT motif and analyzed serum IgE levels as well as the generation of IgE-producing germinal center B cells and PCs subsequent to primary and secondary infection with helminths. In vitro cultures were used to study the mIgE-ITT–controlled expression of mIgE on the surface of PCs. Systemic mast cell activation was determined by serum Mcpt1 ELISA in response to ovalbumin challenge. Results: mIgE-ITT–mutant mice showed an impaired memory IgE response subsequent to helminth infection. Furthermore, sensitization and challenge of mIgE-ITT–mutant mice with ovalbumin resulted in diminished serum IgE titers and reduced mast cell activation. The mIgE-ITT motif was required for optimal cell surface expression of mIgE B-cell antigen receptors but not for intracellular IgE expression in PCs. Conclusion: These results indicate that the mIgE B-cell antigen receptor plays a critical role in establishing or maintaining the population of IgE-producing PCs during memory IgE responses.
CRIS-Team Scopus Importer:2020-04-14
Keywords: Allergy; B-cell receptor; helminths; IgE; plasma cells

The Brief Case: Cutaneous Sporotrichosis in an Immunocompetent Patient after Travel to Peru - Wolff, Dorit; Feldt, Torsten; Reifenberger, Julia; Sebald, Heidi; Bogdan, Christian (Journal of Clinical Microbiology, 2018)
EVALuna2:36422

The bulk of the hematopoietic stem cell population is dispensable for murine steady-state and stress hematopoiesis - Schoedel, Kristina B.; Morcos, Mina N. F.; Zerjatke, Thomas; Roeder, Ingo; Grinenko, Tatyana; Vöhringer, David; Goethert, Joachim R.; Waskow, Claudia; Roers, Axel; Gerbaulet, Alexander (Blood, 2016)
Long term repopulating (LT-) hematopoietic stem cells (HSCs) are the most undifferentiated cells at the top of the hematopoietic hierarchy. The regulation of HSC pool size and its contribution to hematopoiesis are incompletely understood. We depleted hematopoietic stem and progenitor cells (HSPCs) in adult mice in situ and found that LT-HSCs recovered from initially very low levels (< 1%) to below 10% of normal numbers but not more, while progenitor cells substantially recovered shortly after depletion. In spite of the persistent and massive reduction of LT-HSCs, steady-state hematopoiesis was unaffected and residual HSCs remained quiescent. Hematopoietic stress, although reported to recruit quiescent HSCs into cycle, was well tolerated by HSPC-depleted mice and did not induce expansion of the small LT-HSC compartment. Only upon 5-Fluorouracil treatment, HSPC-depleted bone marrow was compromised in re-constituting hematopoiesis, demonstrating that HSCs and early progenitors are crucial to compensate myeloablation. Hence, a contracted HSC compartment cannot recover in situ to its original size and normal steady-state blood cell generation is sustained with less than 10% of normal LT-HSC numbers without increased contribution of the few residual cells.
EVALuna2:25877

The CD83 molecule expressed by dendritic cells is a checkpoint to regulate resolution of inflammation as well as homeostasis within periphery and CNS - Wild, Andreas; Krzyzak, Lena; Mattner, Jochen; Winkler, Thomas; Nitschke, Lars; Steinkasserer, Alexander (2018)
EVALuna2:36214

The chemical class of quinazoline compounds provides a core structure for the design of anticytomegaloviral kinase inhibitors - Hutterer, Corina; Hamilton, S.; Steingruber, Mirjam; Zeitträger, Isabel; Bahsi, Hanife; Thuma, Natalie; Naing, Z.; Oerfi, Z.; Oerfi, L.; Socher, Eileen; Sticht, Heinrich; Rawlinson, W.; et al. (Antiviral Research, 2016)
HCMV is a member of the family Herpesviridae and represents a worldwide distributed pathogen with seropositivity rates in the adult population ranging between 40% and 90%. Notably, HCMV infection is a serious, sometimes life-threatening medical problem for newborns and immunosuppressed individuals, including transplant recipients and patients under antitumoral chemotherapy. Current standard therapy with valganciclovir has the disadvantage of inducing drug-resistant virus mutants and toxicity-related side effects. Our analysis stresses the earlier finding that kinase inhibitors of the quinazoline class exert an antiviral response by targeting the viral protein kinase pUL97 without inducing resistance. Therefore, quinazolines have been used as a core structure to gain insight in the mode of inhibitor-kinase interaction. Here, we demonstrate that (i) the novel quinazolines Vi7392 and Vi7453 are highly active against HCMV laboratory and clinically relevant strains including maribavir- and ganciclovir-resistant variants, (ii) antiviral activity is not cell-type specific and was also detected in a placental explant tissue model using a genetically intact HCMV strain (iii) the viral kinase pUL97 represents a target of the anticytomegaloviral activity of these compounds, (iv) induction of pUL97-conferring drug resistance was not detectable under single-step selection, thus differed from the induction of ganciclovir resistance, and (v) pUL97 drug docking simulations enabled detailed insights into specific drug-target binding properties providing a promising basis for the design of optimized kinase inhibitors. These novel findings may open new prospects for the future medical use of quinazoline drug candidates and the use of drug-target dynamic simulations for rational design of antivirals.
Keywords: Antiviral drug target; Homology model of pUL97; Human cytomegalovirus; pUL97 drug docking simulation; Quinazoline compounds; Viral kinase pUL97

The Coxiella burnetii effector protein CaeB modulates endoplasmatic reticulum (ER) stress signalling and is required for efficient replication in Galleria mellonella - Friedrich, Anja; Beare, Paul A.; Schulze-Luehrmann, Jan; Cordsmeier, Arne; Pazen, Tobias; Sonnewald, Sophia; Lührmann, Anja (Cellular Microbiology, 2021)
The obligate intracellular pathogen Coxiella burnetii is the causative agent of the zoonosis Q fever. C. burnetii infection can have severe outcomes due to the development of chronic infection. To establish and maintain an infection, C. burnetii depends on a functional type IVB secretion system (T4BSS) and, thus, on the translocation of effector proteins into the host cell. Here, we showed that the C. burnetii T4BSS effector protein CaeB targets the conserved endoplasmatic reticulum (ER) stress sensor IRE1 during ER stress in mammalian and plant cells. CaeB-induced upregulation of IRE1 RNase activity was essential for CaeB-mediated inhibition of ER stress-induced cell death. Our data reveal a novel role for CaeB in ER stress signalling modulation and demonstrate that CaeB is involved in pathogenicity in vivo. Furthermore, we provide evidence that C. burnetii infection leads to modulation of the ER stress sensors IRE1 and PERK, but not ATF6 during ER stress. While the upregulation of the RNase activity of IRE1 during ER stress depends on CaeB, modulation of PERK is CaeB independent, suggesting that C. burnetii encodes several factors influencing ER stress during infection.
CRIS-Team WoS Importer:2021-02-12

The Coxiella burnetii T4SS Effector AnkF Is Important for Intracellular Replication - Pechstein, Julian; Schulze-Luehrmann, Jan; Bisle, Stephanie; Cantet, Franck; Beare, Paul A.; Olke, Martha; Bonazzi, Matteo; Berens, Christian; Lührmann, Anja (Frontiers in Cellular and Infection Microbiology, 2020)
Coxiella burnetii is an obligate intracellular pathogen and the causative agent of the zoonotic disease Q fever. Following uptake by alveolar macrophages, the pathogen replicates in an acidic phagolysosomal vacuole, the C. burnetii-containing vacuole (CCV). Effector proteins translocated into the host cell by the type IV secretion system (T4SS) are important for the establishment of the CCV. Here we focus on the effector protein AnkF and its role in establishing the CCV. The C. burnetii AnkF knock out mutant invades host cells as efficiently as wild-type C. burnetii, but this mutant is hampered in its ability to replicate intracellularly, indicating that AnkF might be involved in the development of a replicative CCV. To unravel the underlying reason(s), we searched for AnkF interactors in host cells and identified vimentin through a yeast two-hybrid approach. While AnkF does not alter vimentin expression at the mRNA or protein levels, the presence of AnkF results in structural reorganization and vesicular co-localization with recombinant vimentin. Ectopically expressed AnkF partially accumulates around the established CCV and endogenous vimentin is recruited to the CCV in a time-dependent manner, suggesting that AnkF might attract vimentin to the CCV. However, knocking-down endogenous vimentin does not affect intracellular replication of C. burnetii. Other cytoskeletal components are recruited to the CCV and might compensate for the lack of vimentin. Taken together, AnkF is essential for the establishment of the replicative CCV, however, its mode of action is still elusive.
CRIS-Team WoS Importer:2020-12-11

The Coxiella burnetii T4SS effector protein AnkG hijacks the 7SK small nuclear ribonucleoprotein complex for reprogramming host cell transcription - Cordsmeier, Arne; Rinkel, Sven; Jeninga, Myriam; Schulze-Lührmann, Jan; Oelke, Martha; Schmid, Benedikt; Hasler, Daniele; Meister, Gunter; Haecker, Georg; Petter, Michaela; Beare, Paul A.; Lührmann, Anja (PLoS Pathogens, 2022)
Inhibition of host cell apoptosis is crucial for survival and replication of several intracellular bacterial pathogens. To interfere with apoptotic pathways, some pathogens use specialized secretion systems to inject bacterial effector proteins into the host cell cytosol. One of these pathogens is the obligate intracellular bacterium Coxiella burnetii, the etiological agent of the zoonotic disease Q fever. In this study, we analyzed the molecular activity of the anti-apoptotic T4SS effector protein AnkG (CBU0781) to understand how C. burnetii manipulates host cell viability. We demonstrate by co- and RNA-immunoprecipitation that AnkG binds to the host cell DExD box RNA helicase 21 (DDX21) as well as to the host cell 7SK small nuclear ribonucleoprotein (7SK snRNP) complex, an important regulator of the positive transcription elongation factor b (P-TEFb). The co-immunoprecipitation of AnkG with DDX21 is probably mediated by salt bridges and is independent of AnkG-7SK snRNP binding, and vice versa. It is known that DDX21 facilitates the release of P-TEFb from the 7SK snRNP complex. Consistent with the documented function of released P-TEFb in RNA Pol II pause release, RNA sequencing experiments confirmed AnkG-mediated transcriptional reprogramming and showed that expression of genes involved in apoptosis, trafficking, and transcription are influenced by AnkG. Importantly, DDX21 and P-TEFb are both essential for AnkG-mediated inhibition of host cell apoptosis, emphasizing the significance of the interaction of AnkG with both, the DDX21 protein and the 7SK RNA. In line with a critical function of AnkG in pathogenesis, the AnkG deletion C. burnetii strain was severely affected in its ability to inhibit host cell apoptosis and to generate a replicative C. burnetii-containing vacuole. In conclusion, the interference with the activity of regulatory host cell RNAs mediated by a bacterial effector protein represent a novel mechanism through which C. burnetii modulates host cell transcription, thereby enhancing permissiveness to bacterial infection.
CRIS-Team Scopus Importer:2022-02-25

The C-type lectin receptor Mincle binds to Streptococcus pneumoniae but plays a limited role in the anti-pneumococcal innate immune response - Rabes, Anne; Zimmermann, Stephanie; Reppe, Katrin; Lang, Roland; Seeberger, Peter H.; Suttorp, Norbert; Witzenrath, Martin; Lepenies, Bernd; Opitz, Bastian (PLoS ONE, 2015)
The innate immune system employs C-type lectin receptors (CLRs) to recognize carbohydrate structures on pathogens and self-antigens. The Macrophage-inducible C-type lectin (Mincle) is a FcR?-coupled CLR that was shown to bind to mycobacterial cord factor as well as certain fungal species. However, since CLR functions during bacterial infections have not yet been investigated thoroughly, we aimed to examine their function in Streptococcus pneumonia infection. Binding studies using a library of recombinantly expressed CLR-Fc fusion proteins indicated a specific, Ca2+-dependent, and serotype-specific binding of Mincle to S. pneumonia. Subsequent experiments with different Mincle-expressing cells as well as Mincle-deficient mice, however, revealed a limited role of this receptor in bacterial phagocytosis, neutrophil-mediated killing, cytokine production, and antibacterial immune response during pneumonia. Collectively, our results indicate that Mincle is able to recognize S. pneumonia but is not required for the anti-pneumococcal innate immune response.
EVALuna2:7656

The early bird catches the IL-2 in C-type lectin receptor-dependent activation of dendritic cells - Blamberg, Robert; Lang, Roland (Science Signaling, 2023)
The transcriptional response of macrophages and dendritic cells to stimulation of pattern recognition receptors can be unexpectedly distinct. In this issue of Science Signaling, Watanabe et al. demonstrate that IL-2 is differentially induced by the closely related C-type lectin receptors Dectin-2 and Mincle and reveal early signaling through the adaptor protein FcRγ as a critical mechanism.
CRIS-Team Scopus Importer:2023-03-24

The Essential Thioredoxin Reductase of the Human Pathogenic Mold Aspergillus fumigatus Is a Promising Antifungal Target - Binder, Jasmin; Shadkchan, Yana; Osherov, Nir; Krappmann, Sven (Frontiers in Microbiology, 2020)
The identification of cellular targets for antifungal compounds is a cornerstone for the development of novel antimycotics, for which a significant need exists due to increasing numbers of susceptible patients, emerging pathogens, and evolving resistance. For the human pathogenic mold Aspergillus fumigatus, the causative agent of the opportunistic disease aspergillosis, only a limited number of established targets and corresponding drugs are available. Among several targets that were postulated from a variety of experimental approaches, the conserved thioredoxin reductase (TrxR) activity encoded by the trxR gene was assessed in this study. Its essentiality could be confirmed following a conditional TetOFF promoter replacement strategy. Relevance of the trxR gene product for oxidative stress resistance was revealed and, most importantly, its requirement for full virulence of A. fumigatus in two different models of infection resembling invasive aspergillosis. Our findings complement the idea of targeting the reductase component of the fungal thioredoxin system for antifungal therapy.
CRIS-Team Scopus Importer:2020-07-24
Keywords: aspergillosis; conditional promoter replacement; essentiality; TetOFF; thioredoxin

The exception that proves the rule: Virulence gene expression at the onset of Plasmodium falciparum blood stage infections - Wichers-Misterek, Jan Stephan; Krumkamp, Ralf; Held, Jana; von Thien, Heidrun; Wittmann, Irene; Höppner, Yannick Daniel; Ruge, Julia M.; Moser, Kara; Dara, Antoine; Strauss, Jan; Esen, Meral; Fendel, Rolf; et al. (PLoS Pathogens, 2023)
Controlled human malaria infections (CHMI) are a valuable tool to study parasite gene expression in vivo under defined conditions. In previous studies, virulence gene expression was analyzed in samples from volunteers infected with the Plasmodium falciparum (Pf) NF54 isolate, which is of African origin. Here, we provide an in-depth investigation of parasite virulence gene expression in malaria-naïve European volunteers undergoing CHMI with the genetically distinct Pf 7G8 clone, originating in Brazil. Differential expression of var genes, encoding major virulence factors of Pf, PfEMP1s, was assessed in ex vivo parasite samples as well as in parasites from the in vitro cell bank culture that was used to generate the sporozoites (SPZ) for CHMI (Sanaria PfSPZ Challenge (7G8)). We report broad activation of mainly B-type subtelomeric located var genes at the onset of a 7G8 blood stage infection in naïve volunteers, mirroring the NF54 expression study and suggesting that the expression of virulence-associated genes is generally reset during transmission from the mosquito to the human host. However, in 7G8 parasites, we additionally detected a continuously expressed single C-type variant, Pf7G8_040025600, that was most highly expressed in both pre-mosquito cell bank and volunteer samples, suggesting that 7G8, unlike NF54, maintains expression of some previously expressed var variants during transmission. This suggests that in a new host, the parasite may preferentially express the variants that previously allowed successful infection and transmission.
CRIS-Team Scopus Importer:2023-07-21

The Extracellular Domains of IgG1 and T Cell-Derived IL-4/IL-13 Are Critical for the Polyclonal Memory IgE Response In Vivo - Turqueti-Neves, Adriana; Otte, Manuel; Schwartz, Christian; Schmitt, Michaela; Lindner, Cornelia; Pabst, Oliver; Yu, Philipp; Vöhringer, David (Plos Biology, 2015)
IgE-mediated activation of mast cells and basophils contributes to protective immunity against helminths but also causes allergic responses. The development and persistence of IgE responses are poorly understood, which is in part due to the low number of IgE-producing cells. Here, we used next generation sequencing to uncover a striking overlap between the IgE and IgG1 repertoires in helminth-infected or OVA/alum-immunized wild-type BALB/c mice. The memory IgE response after secondary infection induced a strong increase of IgE+ plasma cells in spleen and lymph nodes. In contrast, germinal center B cells did not increase during secondary infection. Unexpectedly, the memory IgE response was lost in mice where the extracellular part of IgG1 had been replaced with IgE sequences. Adoptive transfer studies revealed that IgG1+ B cells were required and sufficient to constitute the memory IgE response in recipient mice. T cell-derived IL-4/IL-13 was required for the memory IgE response but not for expansion of B cells from memory mice. Together, our results reveal a close relationship between the IgE and IgG1 repertoires in vivo and demonstrate that the memory IgE response is mainly conserved at the level of memory IgG1+ B cells. Therefore, targeting the generation and survival of allergen-specific IgG1+ B cells could lead to development of new therapeutic strategies to treat chronic allergic disorders.
EVALuna2:25871

The high and lows of type 2 asthma and mouse models - Fallon, Padraic G.; Schwartz, Christian (Journal of Allergy and Clinical Immunology, 2019)
CRIS-Team Scopus Importer:2019-12-31
Keywords: allergic airway disease; Asthma; mouse models; type 2 inflammation

The histone methyltransferase DOT1B is dispensable for stage differentiation and macrophage infection of Leishmania mexicana - Eisenhuth, Nicole; Rauh, Elisa Theres; Mitnacht, Melina; Debus, Andrea; Schleicher, Ulrike; Butter, Falk; Pruzinova, Katerina; Volf, Petr; Janzen, Christian J. (Frontiers in Cellular and Infection Microbiology, 2024)
Conserved histone methyltransferases of the DOT1 family are involved in replication regulation, cell cycle progression, stage differentiation, and gene regulation in trypanosomatids. However, the specific functions of these enzymes depend on the host evasion strategies of the parasites. In this study, we investigated the role of DOT1B in Leishmania mexicana, focusing on life cycle progression and infectivity. In contrast to Trypanosoma brucei, in which DOT1B is essential for the differentiation of mammal-infective bloodstream forms to insect procyclic forms, L. mexicana DOT1B (LmxDOT1B) is not critical for the differentiation of promastigotes to amastigotes in vitro. Additionally, there are no significant differences in the ability to infect or differentiate in macrophages or sand fly vectors between the LmxDOT1B-depleted and control strains. These findings highlight the divergence of the function of DOT1B in these related parasites, suggesting genus-specific adaptations in the use of histone modifications for life cycle progression and host adaptation processes.
CRIS-Team Scopus Importer:2025-04-01
Keywords: differentiation; DOT1; histone methyltransferase; Leishmania mexicana; sand fly; virulence

The immunomicrotope of Leishmania control and persistence - Bogdan, Christian; islam, Noor-A-kasida; Barinberg, David; Soulat, Didier; Schleicher, Ulrike; Rai, Baplu (Trends in Parasitology, 2024)
Leishmania is an intracellular protozoan transmitted by sand fly vectors; it causes cutaneous, mucocutaneous, or visceral disease. Its growth and survival are impeded by type 1 T helper cell responses, which entail interferon (IFN)-γ-mediated macrophage activation. Leishmania partially escapes this host defense by triggering immune cell and cytokine responses that favor parasite replication rather than killing. Novel methods for in situ analyses have revealed that the pathways of immune control and microbial evasion are strongly influenced by the tissue context, the micro milieu factors, and the metabolism at the site of infection, which we collectively term the ‘immunomicrotope’. Understanding the components and the impact of the immunomicrotope will enable the development of novel strategies for the treatment of chronic leishmaniasis.
CRIS-Team Scopus Importer:2024-09-13
Keywords: evasion; immunity; Leishmania parasites; leishmaniasis; micro milieu factors; persistence

The impact of the type 1 and type 2 T Helper cell concept on novel vaccine design with emphasis on protection against Leishmania Parasites - Bogdan, Christian; Röllinghoff, Martin (De Gruyter Mouton, 2012)
CRIS-Team Scopus Importer:2024-02-26

The infectious propagules of Aspergillus fumigatus are coated with antimicrobial peptides - Dümig, Michaela; Binder, Jasmin; Gaculenko, Anastasia; Daul, Franziska; Winandy, Lex; Hasenberg, Mike; Gunzer, Matthias; Fischer, Reinhard; Künzler, Markus; Krappmann, Sven (Cellular Microbiology, 2021)
Fungal spores are unique cells that mediate dispersal and survival in the environment. For pathogenic fungi encountering a susceptible host, these specialised structures may serve as infectious particles. The main causative agent of the opportunistic disease aspergillosis, Aspergillus fumigatus, produces asexual spores, the conidia, that become dissipated by air flows or water currents but also serve as propagules to infect a susceptible host. We demonstrate that the defX gene of this mould encodes putative antimicrobial peptides resembling cysteine-stabilised (CS)αβ defensins that are expressed in a specific spatial and temporal manner in the course of asexual spore formation. Localisation studies on strains expressing a fluorescent proxy or tagged defX alleles expose that these antimicrobial peptides are secreted to coat the conidial surface. Deletion mutants reveal that the spore-associated defX gene products delay the growth of Gram-positive Staphylococcus aureus and demonstrate that the defX gene and presumably its encoded spore-associated defensins confer a growth advantage to the fungal opponent over bacterial competitors. These findings have implications with respect to the ecological niche of A. fumigatus that serves as a ‘virulence school’ for this human pathogenic mould; further relevance is given for the infectious process resulting in aspergillosis, considering competition with the host microbiome or co-infecting microorganisms to break colonisation resistance at host surfaces.
CRIS-Team Scopus Importer:2021-03-12
Keywords: aspergillosis; defensin-like peptide; fungal virulence

The inhibition of the apoptosis pathway by the Coxiella burnetii effector protein CaeA requires the EK repetition motif, but is independent of survivin - Bisle, Stephanie; Klingenbeck, Leonie; Borges, Vitor; Sobotta, Katharina; Schulze-Luehrmann, Jan; Menge, Christian; Heydel, Carsten; Gomes, Joao Paulo; Lührmann, Anja (Virulence, 2016)
ABSRTACT Coxiella burnetii is an obligate intracellular bacterium that causes Query (Q) fever, a zoonotic disease. It requires a functional type IV secretion system (T4SS) which translocate bacterial effector proteins into the host cell cytoplasm and thereby facilitates bacterial replication. To date, more than 130 effector proteins have been identified, but their functions remain largely unknown. Recently, we demonstrated that one of these proteins, CaeA (CBU1524) localized to the host cell nucleus and inhibited intrinsic apoptosis of HEK293 or CHO cells. In the present study we addressed the question whether CaeA also affects the extrinsic apoptosis pathway. Ectopic expression of CaeA reduced extrinsic apoptosis and prevented the cleavage of the executioner caspase 7, but did not impair the activation of initiator caspase 9. CaeA expression resulted in an up-regulation of survivin (an inhibitor of activated caspases), which, however, was not causal for the anti-apoptotic effect of CaeA. Comparing the sequence of CaeA from 25 different C. burnetii isolates we identified an EK (glutamic acid/ lysine) repetition motif as a site of high genetic variability. The EK motif of CaeA was essential for the anti-apoptotic activity of CaeA. From these data, we conclude that the C. burnetii effector protein CaeA interferes with the intrinsic and extrinsic apoptosis pathway. The process requires the EK repetition motif of CaeA, but is independent of the upregulated expression of survivin.
EVALuna2:7711

The Innate Immune Response to Infection Induces Erythropoietin-Dependent Replenishment of the Dendritic Cell Compartment - Einwächter, Henrik; Heiseke, Alexander; Schlitzer, Andreas; Gasteiger, Georg; Adler, Heiko; Vöhringer, David; Manz, Markus G.; Ruzsics, Zsolt; Dölken, Lars; Koszinowski, Ulrich H.; Sparwasser, Tim; Reindl, Wolfgang; et al. (Frontiers in Immunology, 2020)
Dendritic cells (DC) play a key role in the adaptive immune response due to their ability to present antigens and stimulate naïve T cells. Many bacteria and viruses can efficiently target DC, resulting in impairment of their immunostimulatory function or elimination. Hence, the DC compartment requires replenishment following infection to ensure continued operational readiness of the adaptive immune system. Here, we investigated the molecular and cellular mechanisms of inflammation-induced DC generation. We found that infection with viral and bacterial pathogens as well as Toll-like receptor 9 (TLR9) ligation with CpG-oligodeoxynucleotide (CpG-ODN) expanded an erythropoietin (EPO)-dependent TER119+CD11a+ cell population in the spleen that had the capacity to differentiate into TER119+CD11chigh and TER119−CD11chigh cells both in vitro and in vivo. TER119+CD11chigh cells contributed to the conventional DC pool in the spleen and specifically increased in lymph nodes draining the site of local inflammation. Our results reveal a so far undescribed inflammatory EPO-dependent pathway of DC differentiation and establish a mechanistic link between innate immune recognition of potential immunosuppressive pathogens and the maintenance of the DC pool during and after infection.
CRIS-Team Scopus Importer:2020-08-28
Keywords: dendritic cell; erythropoietin; extramedullary hematopoiesis; infection; inflammation; TER119; toll-like receptor

The interplay between dendritic cells and CD8 T lymphocytes is a crucial component of SARS-CoV-2 immunity - Buttenschön, Jonas; Mattner, Jochen (Cellular & Molecular Immunology, 2021)
CRIS-Team Scopus Importer:2021-01-15

The killing of macrophages by Corynebacterium ulcerans - Hacker, Elena; Ott, Lisa; Schulze-Luehrmann, Jan; Lührmann, Anja; Wiesmann, Veit; Wittenberg, Thomas; Burkovski, Andreas (Virulence, 2016)
EVALuna2:7696

The master regulator MAT1-1-1 of fungal mating binds to its targets via a conserved motif in the human pathogen Aspergillus fumigatus - Ramsak, Barbara; Markau, Jessica; Pazen, Tobias; Dahlmann, Tim A.; Krappmann, Sven; Kück, Ulrich (G3 : Genes, Genomes, Genetics, 2021)
Mating-type transcription factors are master regulators of sexually related signal transduction pathways in fungi; however, their recognition of specific DNA sequences from target genes is widely undetermined. Here, we identified and characterized the DNA-binding sequence of the MAT1-1-1 alpha-box domain transcription factor from the human pathogen Aspergillus fumigatus. In order to explore MAT1-1-1 DNA-binding targets, we used the previously reported MAT1-1-1 binding motif from Penicillium chrysogenum, in a bioinformatics approach. We identified 18 A. fumigatus genes carrying the MAT1.1 sequence in their upstream region, among them genes for the a-pheromone precursor (PpgA), G-protein-coupled pheromone receptor (PreA), and for TomA, an unidentified protein. To validate our prediction further, quantification of transcript levels showed a decrease in expression of ppgA, tomA, and others in a MAT1-1 deletion strain. For a functional analysis of the binding sites, truncated variants of the A. fumigatus MAT1-1-1 gene were introduced into Escherichia coli for heterologous expression. The yield of recombinant protein was further optimized for the AfMAT1-1-178–235 variant that harbors an extended alpha-box domain. AfMAT1-1-178–235 bound to a subset of the most strongly upregulated genes: ppgA, preA, and tomA. The DNA-binding specificity was confirmed by testing mutated binding sequences, as well as performing competition experiments with specific and non-specific sequences. Finally, equilibrium dissociation constants of 1.83 6 0.1 and 1.45 6 0.26 mM were determined for AfMAT1-1-178–235 and fusion protein GST-AfMAT1-1-178–235. Collectively, these findings provide further insights into AfMAT1-1-1-mediated gene expression and imply that alpha-box domain regulators from other members of Eurotiales control fungal development in a conserved manner.
CRIS-Team Scopus Importer:2021-03-26
Keywords: DNA-binding motif; Escherichia coli protein synthesis; Human pathogen Aspergillus fumigatus; Mating type; Transcription factor

The novel Aspergillus fumigatus MAT1-2-4 mating-type gene is required for mating and cleistothecia formation - Yu, Yidong; Amich, Jorge; Will, Christine; Eagle, Carly E.; Dyer, Paul S.; Krappmann, Sven (Fungal Genetics and Biology, 2017)
Sexual propagation accompanied by recombination and the formation of spore-containing fruiting bodies is a cornerstone of fungal genetics and biology. In the human pathogen Aspergillus fumigatus sexual identity has previously been shown to be determined by MAT1-1-1 or MAT1-2-1 genes which act as transcriptional regulators and are present within idiomorphs found at the MAT locus. We here report the identification and first characterization of a further novel gene, termed MAT1-2-4, that is present in the MAT1-2 idiomorph of A. fumigatus. A mating-type swapping strategy was used to achieve an unbiased deletion of the MAT1-2-4 gene with no impact on MAT1-2-1 gene expression. Phenotypical characterization of the resulting strain revealed an inability to mate with the compatible MAT1-1 progenitor, demonstrating that the MAT1-2-4 gene product is a genuine mating-type factor required for correct sexual development. A GPI-anchored protein of unknown function was identified as interaction partner. However, no functional role in the mating process or ascosporogenesis could be demonstrated by deletion analysis for this latter protein, although a role in heterokaryon formation is suggested. Bioinformatic analysis also demonstrated the presence of MAT1-2-4 homologues in some, but not all, other Aspergillus species and the evolutionary origins and implications of the MAT1-2-4 gene are discussed.
EVALuna2:7737

The opportunistic pathogen Aspergillus fumigatus coats its infectious propagules with antimicrobial peptides - Duemig, Michaela; Binder, Johannes; Gaculenko, Anastasia; Daul, F.; Hasenberg, M.; Gunzer, M.; Krappmann, Sven (2018)
EVALuna2:213342

The P. falciparum alternative histones Pf H2A.Z and Pf H2B.Z are dynamically acetylated and antagonized by PfSir2 histone deacetylases at heterochromatin boundaries - Azizan, Suffian; Selvarajah, Shamista A.; Tang, Jingyi; Jeninga, Myriam; Schulz, Danae; Pareek, Kapil; Herr, Tamara; Day, Karen P.; De Koning-Ward, Tania F.; Petter, Michaela; Duffy, Michael F. (mBio, 2023)
The Plasmodium falciparum alternative histones Pf H2A.Z and Pf H2B.Z are enriched in the same nucleosomes in intergenic euchromatin but depleted from heterochromatin. They occupy most promoters but are only dynamically associated with expression at var genes. In other organisms, acetylation of H2A.Z is important for its functions in gene expression and chromatin structure. Here, we show that acetylated Pf H2A.Z and Pf H2B.Z are dynamically associated with gene expression at promoters. In addition, acetylated Pf H2A.Z and Pf H2B.Z are antagonized by the sirtuin class III histone deacetylases (HDAC) PfSir2A and B at heterochromatin boundaries and encroach upon heterochromatin in parasites lacking PfSir2A or B. However, the majority of acetylated Pf H2A.Z and Pf H2B.Z are deacetylated by class I or II HDACs. Acetylated Pf H2A.Z and Pf H2B.Z are also dynamically associated with promoter activity of both canonical upstream var gene promoters and var gene introns. These findings suggest that both acetylated Pf H2A.Z and Pf H2B.Z play critical roles in gene expression and contribute to maintenance of chromatin structure at the boundaries of subtelomeric, facultative heterochromatin, critical for the variegated expression of genes that enable rapid adaptation to altered host environments.
CRIS-Team Scopus Importer:2024-12-16
Keywords: chromatin; epigenetics; malaria; regulation of gene expression; variant histones

The Putative Bromodomain Protein PfBDP7 of the Human Malaria Parasite Plasmodium Falciparum Cooperates With PfBDP1 in the Silencing of Variant Surface Antigen Expression - Quinn, Jennifer; Jeninga, Myriam; Limm, Katharina; Pareek, Kapil; Meißgeier, Tina; Bachmann, Anna; Duffy, Michael F.; Petter, Michaela (Frontiers in Cell and Developmental Biology, 2022)
Epigenetic regulation is a critical mechanism in controlling virulence, differentiation, and survival of the human malaria parasite Plasmodium (P.) falciparum. Bromodomain proteins contribute to this process by binding to acetylated lysine residues of histones and thereby targeting the gene regulatory machinery to gene promoters. A protein complex containing the P. falciparum bromodomain proteins (PfBDP) 1 and PfBDP2 (BDP1/BDP2 core complex) was previously shown to play an essential role for the correct transcription of invasion related genes. Here, we performed a functional characterization of a third component of this complex, which we dubbed PfBDP7, because structural modelling predicted a typical bromodomain fold. We confirmed that PfBDP7 is a nuclear protein that interacts with PfBDP1 at invasion gene promoters in mature schizont stage parasites and contributes to their transcription. Although partial depletion of PfBDP7 showed no significant effect on parasite viability, conditional knock down of either PfBDP7 or PfBDP1 resulted in the de-repression of variant surface antigens (VSA), which are important pathogenicity factors. This de-repression was evident both on mRNA and protein level. To understand the underlying mechanism, we mapped the genome wide binding sites of PfBDP7 by ChIPseq and showed that in early schizonts, PfBDP7 and PfBDP1 are commonly enriched in heterochromatic regions across the gene body of all VSA families, including genes coding for PfEMP1, RIFIN, STEVOR, and PfMC-2TM. This suggests that PfBDP7 and PfBDP1 contribute to the silencing of VSAs by associating with heterochromatin. In conclusion, we identified PfBDP7 as a chromatin binding protein that is a constitutive part of the P. falciparum BDP1/BDP2 core complex and established PfBDP1 and PfBDP7 as novel players in the silencing of heterochromatin regulated virulence gene families of the malaria parasite P. falciparum.
CRIS-Team Scopus Importer:2022-05-06
Keywords: bromodomain; chromatin; malaria; P. falciparum; variant surface antigens

The regulatory and transcriptional landscape associated with carbon utilization in a filamentous fungus - Wu, Vincent W.; Thieme, Nils; Huberman, Lori B.; Dietschmann, Axel; Kowbel, David J.; Lee, Juna; Calhoun, Sara; Singan, Vasanth R.; Lipzen, Anna; Xiong, Yi; Monti, Remo; Blow, Matthew J.; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2020)
Filamentous fungi, such as Neurospora crassa, are very efficient in deconstructing plant biomass by the secretion of an arsenal of plant cell wall-degrading enzymes, by remodeling metabolism to accommodate production of secreted enzymes, and by enabling transport and intracellular utilization of plant biomass components. Although a number of enzymes and transcriptional regulators involved in plant biomass utilization have been identified, how filamentous fungi sense and integrate nutritional information encoded in the plant cell wall into a regulatory hierarchy for optimal utilization of complex carbon sources is not understood. Here, we performed transcriptional profiling of N. crassa on 40 different carbon sources, including plant biomass, to provide data on how fungi sense simple to complex carbohydrates. From these data, we identified regulatory factors in N. crassa and characterized one (PDR-2) associated with pectin utilization and one with pectin/hemicellulose utilization (ARA-1). Using in vitro DNA affinity purification sequencing (DAP-seq), we identified direct targets of transcription factors involved in regulating genes encoding plant cell wall-degrading enzymes. In particular, our data clarified the role of the transcription factor VIB-1 in the regulation of genes encoding plant cell wall-degrading enzymes and nutrient scavenging and revealed a major role of the carbon catabolite repressor CRE-1 in regulating the expression of major facilitator transporter genes. These data contribute to a more complete understanding of cross talk between transcription factors and their target genes, which are involved in regulating nutrient sensing and plant biomass utilization on a global level.
CRIS-Team Scopus Importer:2020-03-27
Keywords: DAP-seq; Nutrient; Plant biomass deconstruction; RNA-seq; Sensing; Transcriptional networks

The Role of Adaptor Proteins in the Biology of Natural Killer T (NKT) Cells - Gerth, Evelyn; Mattner, Jochen (Frontiers in Immunology, 2019)
Adaptor proteins contribute to the selection, differentiation and activation of natural killer T (NKT) cells, an innate(-like) lymphocyte population endowed with powerful immunomodulatory properties. Distinct from conventional T lymphocytes NKT cells preferentially home to the liver, undergo a thymic maturation and differentiation process and recognize glycolipid antigens presented by the MHC class I-like molecule CD1d on antigen presenting cells. NKT cells express a semi-invariant T cell receptor (TCR), which combines the V alpha 14-J alpha 18 chain with a V beta 2, V beta 7, or V beta 8 chain in mice and the V alpha 24 chain with the V beta 11 chain in humans. The avidity of interactions between their TCR, the presented glycolipid antigen and CD1d govern the selection and differentiation of NKT cells. Compared to TCR ligation on conventional T cells engagement of the NKT cell TCR delivers substantially stronger signals, which trigger the unique NKT cell developmental program. Furthermore, NKT cells express a panoply of primarily inhibitory NK cell receptors (NKRs) that control their self-reactivity and avoid autoimmune activation. Adaptor proteins influence NKT cell biology through the integration of TCR, NKR and/or SLAM (signaling lymphocyte-activation molecule) receptor signals or the variation of CD1d-restricted antigen presentation. TCR and NKR ligation engage the SH2 domain-containing leukocyte protein of 76kDa slp-76 whereas the SLAM associated protein SAP serves as adaptor for the SLAM receptor family. Indeed, the selection and differentiation of NKT cells selectively requires co-stimulation via SLAM receptors. Furthermore, SAP deficiency causes X-linked lymphoproliferative disease with multiple immune defects including a lack of circulating NKT cells. While a deletion of slp-76 leads to a complete loss of all peripheral T cell populations, mutations in the SH2 domain of slp-76 selectively affect NKT cell biology. Furthermore, adaptor proteins influence the expression and trafficking of CD1d in antigen presenting cells and subsequently selection and activation of NKT cells. Adaptor protein complex 3 (AP-3), for example, is required for the efficient presentation of glycolipid antigens which require internalization and processing. Thus, our review will focus on the complex contribution of adaptor proteins to the delivery of TCR, NKR and SLAM receptor signals in the unique biology of NKT cells and CD1d-restricted antigen presentation.
CRIS-Team WoS Importer:2019-07-09

The role of lipids in host microbe interactions - Lang, Roland; Mattner, Jochen (Frontiers in Bioscience, 2017)
Lipids are one of the major subcellular constituents and serve as signal molecules, energy sources, metabolic precursors and structural membrane components in various organisms. The function of lipids can be modified by multiple biochemical processes such as (de-)phosphorylation or (de-)glycosylation, and the organization of fatty acids into distinct cellular pools and subcellular compartments plays a pivotal role for the morphology and function of various cell populations. Thus, lipids regulate, for example, phagosome formation and maturation within host cells and thus, are critical for the elimination of microbial pathogens. Vice versa, microbial pathogens can manipulate the lipid composition of phagosomal membranes in host cells, and thus avoid their delivery to phagolysosomes. Lipids of microbial origin belong also to the strongest and most versatile inducers of mammalian immune responses upon engagement of distinct receptors on myeloid and lymphoid cells. Furthermore, microbial lipid toxins can induce membrane injuries and cell death. Thus, we will review here selected examples for mutual host-microbe interactions within the broad and divergent universe of lipids in microbial defense, tissue injury and immune evasion.
EVALuna2:7757

The Role of Programmed Necrosis in Colorectal Cancer - Yu, Yidong; Gámez Belmonte, Maria de los Reyes; Patankar, Jay; Liebing, Eva; Becker, Christoph (Cancers, 2022)
Simple Summary Necrosis is a type of cell death characterized by plasma membrane rupture and the induction of inflammation. This review focuses on colorectal cancer and outlines the role of programmed necrosis in tumor development. Potential strategies for anti-tumor treatment via targeting programmed necrosis are also discussed. For quite a long time, necrosis was considered a chaotic and unorganized form of cell death. However, studies conducted during the past few decades unveiled multiple types of programmed necrosis, such as necroptosis, pyroptosis and ferroptosis. These types of programmed necrosis have been shown to play crucial roles in mediating pathological processes, including tumorigenesis. Almost all key mediators, such as RIPK3 and MLKL in necroptosis, GSDMD and caspase 1/11 in pyroptosis and GPX4 in ferroptosis, are highly expressed in intestinal epithelial cells (IECs). An aberrant increase or decrease in programmed necrosis in IECs has been connected to intestinal disorders. Here, we review the pathways of programmed necrosis and the specific consequences of regulated necrosis in colorectal cancer (CRC) development. Translational aspects of programmed necrosis induction as a novel therapeutic alternative against CRC are also discussed.
CRIS-Team WoS Importer:2022-09-16

The role of the chemokine receptor CCR8 in migration and effector function of innate lymphoid cells type 2 - Knipfer, Lisa; Schulz-Kuhnt, Anja; Symowski, Cornelia; Vöhringer, David; Neurath, Markus; Atreya, I.; Wirtz, Stefan (EUROPEAN JOURNAL OF IMMUNOLOGY, 2019)
CRIS-Team WoS Importer:2019-10-08

THE ROLE OF TYPE 2 IMMUNITY IN SKIN REGENERATIVE RESPONSES - Satzinger, Sabrina; Vöhringer, David; Roers, Axel; Eming, Sabine A. (WOUND REPAIR AND REGENERATION, 2020)
CRIS-Team WoS Importer:2020-04-21

The sialyltransferase ST3Gal-IV guides murine T-cell progenitors to the thymus - Sitte, Selina; Doehler, Daniela; Sperandio, Markus; Marth, Jamey D.; Vöhringer, David (Blood Advances, 2020)
T lymphocytes are important players in beneficial and detrimental immune responses. In contrast to other lymphocyte populations that develop in the bone marrow, T-cell precursors need to migrate to the thymus for further development. The interaction of P-selectin and P-selectin glycoprotein ligand-1 (PSGL-1) is crucial for thymic entry of T-cell precursors during settings of T-cell lineage reconstitution. PSGL-1 has to be sialylated to function as a ligand for P-selectin, and the sialyltransferase ST3Gal-IV might play a critical role in this process. We therefore investigated the role of ST3Gal-IV for T-cell development using competitive mixed bone marrow chimeric mice. We found that ST3Gal-IV is dispensable for homing and engraftment of hematopoietic precursors in the bone marrow. However, ST3Gal-IV deficiency affects seeding of the thymus by early T-cell progenitors, leading to impaired restoration of the peripheral T-cell compartment. This defect could be restored by ectopic retroviral expression of ST3Gal-IV in hematopoietic stem cells derived from ST3Gal-IV-deficient donor mice. Our findings show that ST3Gal-IV plays a critical and nonredundant role for efficient T-cell lineage reconstitution after bone marrow transplantation.
CRIS-Team WoS Importer:2020-05-29

The Transcription Factor FRA-1/AP-1 Controls Lipocalin-2 Expression and Inflammation in Sepsis Model - Cao, Shan; Schnelzer, Anne; Hannemann, Nicole; Schett, Georg; Soulat, Didier; Bozec, Aline (Frontiers in Immunology, 2021)
Sepsis is a life-threatening condition characterized by excessive inflammation in its early phase. This is followed by an aberrant resolution phase associated to a prolonged period of immune suppression that can ultimately lead to multiple organ dysfunctions. This immunosuppression can be mediated by the functional reprogramming of gene transcription in monocytes/macrophages in response to prolonged lipopolysaccharide (LPS) exposure. Surprisingly, there is no report on the role of AP-1 transcription factors in this reprogramming process. Herein, we used the endotoxin tolerance model on murine bone marrow-derived macrophages in which tolerant cells stimulated twice with LPS were compared to naïve cells stimulated once. Out of all AP-1 transcription factors tested, Fosl1 gene stood out because of its unique regulation in tolerized cells. Moreover, we could correlate FRA-1 expression to the expression of an essential anti-inflammatory molecule involved in sepsis response, Lipocalin 2 aka NGAL. Identical results were obtained in human PBMC following the endotoxin tolerance model. When using FRA-1 deficient macrophages, we could confirm that FRA-1 regulates NGAL expression during the tolerant state. Interestingly, ChIP-seq and ChIP-qPCR revealed the binding of FRA-1 on Lcn2 promoter after LPS stimulation in these cells. Finally, we used an in vivo septic model of consecutive injection of LPS, in which the second stimulation is performed before the resolution of inflammation, in wild type and FRA-1 deficient mice. NGAL secretion was elevated in lung, spleen and serum of wild type tolerant mice, whereas it was significantly lower in tolerant FRA-1 deficient mice. Moreover, an increased inflammatory state likely dependent of the low level of NGAL was observed in these FRA-1 deficient mice. This was characterized by an increase of neutrophil infiltration in lung and an increase of apoptotic follicular cells in spleen. This suggests that FRA-1 expression supports resolution of inflammation in this model. Collectively, our data indicate that FRA-1 is involved in myeloid cell tolerance responses by mediating the functional reprogramming of Lcn2 transcription in response to prolonged LPS exposure. In conclusion, FRA-1 may have a protective role in the tolerance response of sepsis through the regulation of NGAL, leading to resolution of inflammation.
CRIS-Team Scopus Importer:2021-11-19
Keywords: AP-1/Fra-1; endotoxin tolerance; lipocalin-2; macrophage; sepsis; transcription factor

The ubiquitin-like modifier FAT10 lowers type I interferons and enhances interferon-gamma after viral infection - Mah, M. M.; Basler, M.; Groettrup, M. (EUROPEAN JOURNAL OF IMMUNOLOGY, 2019)
CRIS-Team WoS Importer:2019-10-08

Three-dimensional light sheet fluorescence microscopy of lungs to dissect local host immune-aspergillus fumigatus interactions - Amich, Jorge; Mokhtari, Zeinab; Strobel, Marlene; Vialetto, Elena; Sheta, Dalia; Yu, Yidong; Hartweg, Julia; Kalleda, Natarajaswamy; Jarick, Katja J.; Brede, Christian; Jordán-Garrote, Ana Laura; Thusek, Sina; et al. (Mbio, 2020)
Aspergillus fumigatus is an opportunistic fungal pathogen that can cause life-threatening invasive lung infections in immunodeficient patients. The cellular and molecular processes of infection during onset, establishment, and progression of A. fumigatus infections are highly complex and depend on both fungal attributes and the immune status of the host. Therefore, preclinical animal models are of paramount importance to investigate and gain better insight into the infection process. Yet, despite their extensive use, commonly employed murine models of invasive pulmonary aspergillosis are not well understood due to analytical limitations. Here, we present quantitative light sheet fluorescence microscopy (LSFM) to describe fungal growth and the local immune response in whole lungs at cellular resolution within its anatomical context. We analyzed three very common murine models of pulmonary aspergillosis based on immunosuppression with corticosteroids, chemotherapy-induced leukopenia, or myeloablative irradiation. LSFM uncovered distinct architectures of fungal growth and degrees of tissue invasion in each model. Furthermore, LSFM revealed the spatial distribution, interaction, and activation of two key immune cell populations in antifungal defense: alveolar macrophages and polymorphonuclear neutrophils. Interestingly, the patterns of fungal growth correlated with the detected effects of the immunosuppressive regimens on the local immune cell populations. Moreover, LSFM demonstrates that the commonly used in-tranasal route of spore administration did not result in complete intra-alveolar deposition, as about 80% of fungal growth occurred outside the alveolar space. Hence, characterization by LSFM is more rigorous than by previously used methods employing murine models of invasive pulmonary aspergillosis and pinpoints their strengths and limitations. IMPORTANCE The use of animal models of infection is essential to advance our understanding of the complex host-pathogen interactions that take place during Aspergillus fumigatus lung infections. As in the case of humans, mice need to suffer an immune imbalance in order to become susceptible to invasive pulmonary aspergillosis (IPA), the most serious infection caused by A. fumigatus. There are several immunosuppressive regimens that are routinely used to investigate fungal growth and/or immune responses in murine models of invasive pulmonary aspergillosis. However, the precise consequences of the use of each immunosuppressive model for the local immune populations and for fungal growth are not completely understood. Here, to pin down the scenarios involving commonly used IPA models, we employed light sheet fluorescence microscopy (LSFM) to analyze whole lungs at cellular resolution. Our results will be valuable to optimize and refine animal models to maximize their use in future research.
CRIS-Team Scopus Importer:2020-03-17
Keywords: Aspergillus fumigatus; Host immune response; Host-pathogen interactions; In vivo fungal growth; Invasive aspergillosis; Light sheet fluorescence microscopy; Lung immunity; Lung infection; Microscopy/imaging; Murine models of invasive pulmonary aspergillosis; Whole-organ imaging

TNF is required for upregulation of Mincle expression and adjuvant activity in response to mycobacterial glycolipids. - Schick, J.; Lang, Roland; Schäfer, Johanna; Schleicher, Ulrike (EUROPEAN JOURNAL OF IMMUNOLOGY, 2019)
CRIS-Team WoS Importer:2019-10-08

TNF-Mediated Restriction of Arginase 1 Expression in Myeloid Cells Triggers Type 2 NO Synthase Activity at the Site of Infection - Schleicher, Ulrike; Paduch, Katrin; Debus, Andrea; Obermeyer, Stephanie; Koenig, Till; Kling, Jessica C.; Ribechini, Eliana; Dudziak, Diana; Mougiakakos, Dimitrios; Murray, Peter J.; Ostuni, Renato; Koerner, Heinrich; et al. (Cell Reports, 2016)
Neutralization or deletion of tumor necrosis factor (TNF) causes loss of control of intracellular pathogens in mice and humans, but the underlying mechanisms are incompletely understood. Here, we found that TNF antagonized alternative activation of macrophages and dendritic cells by IL-4. TNF inhibited IL-4-induced arginase 1 (Arg1) expression by decreasing histone acetylation, without affecting STAT6 phosphorylation and nuclear translocation. In Leishmania major-infected C57BL/6 wild-type mice, type 2 nitric oxide (NO) synthase (NOS2) was detected in inflammatory dendritic cells or macrophages, some of which co-expressed Arg1. In TNF-deficient mice, Arg1 was hyperexpressed, causing an impaired production of NO in situ. A similar phenotype was seen in L. major-infected BALB/c mice. Arg1 deletion in hematopoietic cells protected these mice from an otherwise lethal disease, although their disease-mediating T cell response (Th2, Treg) was maintained. Thus, deletion or TNF-mediated restriction of Arg1 unleashes the production of NO by NOS2, which is critical for pathogen control.
EVALuna2:7700

TNF promotes DECTIN2 family C-type lectin receptor expression in human macrophages. - Haberkamp, Carl; Allabauer, Ida; Blaha, Niklas; Bodendorfer, Barbara; Cunningham, Sarah; Hörning, André; Lang, Roland (Journal of Leukocyte Biology, 2023)
TNF blockade constitutes an effective therapy for inflammatory bowel disease, yet increases the risk for infection, including active tuberculosis. The DECTIN2 family C-type lectin receptors MINCLE, MCL, and DECTIN2 sense mycobacterial ligands and activate myeloid cells. In mice, upregulation of DECTIN2 family C-type lectin receptor after stimulation with Mycobacterium bovis Bacille Calmette-Guérin requires TNF. Here, we investigated whether TNF controls inducible C-type lectin receptor expression in human myeloid cells. Monocyte-derived macrophages were stimulated with Bacille Calmette-Guérin and the TLR4 ligand lipopolysaccharide, and expression of C-type lectin receptor was analyzed. Bacille Calmette-Guérin and lipopolysaccharide strongly upregulated messenger RNA expression of DECTIN2 family C-type lectin receptor but not of DECTIN1. Bacille Calmette-Guérin and lipopolysaccharide also induced robust production of TNF. Recombinant TNF was sufficient to upregulate expression of DECTIN2 family C-type lectin receptor. Blocking TNF with the TNFR2-Fc fusion protein etanercept abrogated, as expected, the effect of recombinant TNF and impaired induction of DECTIN2 family C-type lectin receptor by Bacille Calmette-Guérin and lipopolysaccharide. Flow cytometry confirmed upregulation of MCL at the protein level by recombinant TNF and showed inhibition of Bacille Calmette-Guérin-induced MCL by etanercept. To investigate the impact of TNF on C-type lectin receptor expression in vivo, we analyzed peripheral blood mononuclear cells of patients with inflammatory bowel disease and observed downregulation of MINCLE and MCL expression after therapeutic TNF blockade. Together, TNF is sufficient to upregulate DECTIN2 family C-type lectin receptor in human myeloid cells and contributes to this process after encounter with Bacille Calmette-Guérin or lipopolysaccharide. Impaired C-type lectin receptor expression in patients receiving TNF blockade may dampen the sensing of microbes and defense against infection.
EVALuna2:531674
Keywords: MINCLE; MCL; DECTIN2; TNF blockade; mycobacteria; inflammatory bowel disease

Toll-like receptor 2 and mincle cooperatively sense corynebacterial cell wall glycolipids - Schick, Judith; Etschel, Philipp; Bailo, Rebeca; Ott, Lisa; Bhatt, Apoorva; Lepenies, Bernd; Kirschning, Carsten; Burkovski, Andreas; Lang, Roland (Infection and Immunity, 2017)
EVALuna2:7744

TomA, the target of MAT1-1 in Aspergillus fumigatus, is required for cleistothecia formation presumably in a mating-type-specific manner - Pazen, Tobias; Ramsak, B.; Kueck, U.; Krappmann, Sven (MYCOSES, 2022)
Mating-type transcription factors are master regulators of sexually related signal transduction pathways in fungi; however, their recognition of specific DNA sequences from target genes is widely undetermined. Here, we identified and characterized the DNA-binding sequence of the MAT1-1-1 alpha-box domain transcription factor from the human pathogen Aspergillus fumigatus. In order to explore MAT1-1-1 DNA-binding targets, we used the previously reported MAT1-1-1 binding motif from Penicillium chrysogenum, in a bioinformatics approach. We identified 18 A. fumigatus genes carrying the MAT1.1 sequence in their upstream region, among them genes for the α-pheromone precursor (PpgA), G-protein-coupled pheromone receptor (PreA), and for TomA, an unidentified protein. To validate our prediction further, quantification of transcript levels showed a decrease in expression of ppgA, tomA, and others in a MAT1-1 deletion strain. For a functional analysis of the binding sites, truncated variants of the A. fumigatus MAT1-1-1 gene were introduced into Escherichia coli for heterologous expression. The yield of recombinant protein was further optimized for the AfMAT1-1-178–235 variant that harbors an extended alpha-box domain. AfMAT1-1-178–235 bound to a subset of the most strongly upregulated genes: ppgA, preA, and tomA. The DNA-binding specificity was confirmed by testing mutated binding sequences, as well as performing competition experiments with specific and non-specific sequences. Finally, equilibrium dissociation constants of 1.83 ± 0.1 and 1.45 ± 0.26 µM were determined for AfMAT1-1-178–235 and fusion protein GST-AfMAT1-1-178–235. Collectively, these findings provide further insights into AfMAT1-1-1-mediated gene expression and imply that alpha-box domain regulators from other members of Eurotiales control fungal development in a conserved manner.<br
CRIS-Team WoS Importer:2022-09-23

Transcriptional response of Aspergillus fumigatus to copper and the role of the Cu chaperones - Anabosi, Duaa; Meir, Zohar; Shadkchan, Yana; Handelman, Mariana; Abou-Kandil, Ammar; Yap, Annie; Urlings, Daniel; Gold, Morgan S.; Krappmann, Sven; Haas, Hubertus; Osherov, Nir (Virulence, 2021)
Aspergillus fumigatus is the leading cause of life-threatening invasive mold infections in immunocompromised individuals. This ubiquitous saprophyte possesses several natural attributes allowing it to evade the immune system, including the ability to withstand high toxic Cu concentrations within the phagosomes of macrophages and neutrophils. We previously established that at high levels, Cu binds and activates the A. fumigatus transcription factor AceA, which upregulates the expression of the Cu exporter CrpA to expel excess Cu. Deletion of aceA or crpA result in extreme Cu sensitivity and attenuated virulence. To identify other elements participating in resistance to Cu, we performed a genome-wide analysis of the transcriptome by RNAseq to analyze the AceA-dependent response of A. fumigatus to excess Cu. We deleted key genes whose transcription was strongly upregulated by high Cu, including those encoding homologs of the three Cu chaperones cox17, atx1 and ccs1. Detailed analysis of these genes indicates that in A. fumigatus, cox17 is an essential gene with a possible role in respiration, the atxA gene product participates in reductive iron uptake and ccsA encodes the Cu chaperone activating A. fumigatus Sod1. Interestingly, although the ccsA-null strain was extremely sensitive to high Cu and oxidative stress, it was not attenuated in virulence in a mouse model of invasive pulmonary aspergillosis. Our work provides (i) a detailed view of the genome-wide transcriptional response of A. fumigatus to excess Cu, (ii) identification of the AceA-dependent transcriptome and (iii) analysis of the roles of the three Cu chaperones cox17, atxA and ccsA.
CRIS-Team Scopus Importer:2021-09-10
Keywords: Aspergillus fumigatus; Cu chaperones; Cu transcriptome; oxidative stress; virulence

Transcription factor Fra-1 targets arginase-1 to enhance macrophage-mediated inflammation in arthritis - Hannemann, Nicole; Cao, Shan; Eriksson, Daniel; Schnelzer, Anne; Jordan, Jutta; Eberhardt, Martin; Schleicher, Ulrike; Rech, Jürgen; Uebe, Steffen; Ekici, Arif Bülent; Canete, Juan D.; Chen, Xiaoxiang; et al. (Journal of Clinical Investigation, 2019)
The polarization of macrophages is regulated by transcription factors, such as NF-κB and activator protein 1 (AP-1). In this manuscript, we delineated the role of the transcription factor Fos-related antigen 1 (Fra-1) during macrophage activation and development of arthritis. Network level interaction analysis of microarray data derived from Fra-1- or Fra-2-deficient macrophages revealed a central role of Fra-1, but not of Fra-2, in orchestrating the expression of genes related to wound response, Toll-like receptor activation, and interleukin signaling. ChIP sequencing and standard ChIP analyses of macrophages identified arginase 1 (Arg1) as a target of Fra-1. Luciferase reporter assays revealed that Fra-1 downregulated Arg1 expression by direct binding to the promoter region. Using macrophage-specific Fra-1- or Fra-2-deficient mice, we observed enhanced expression and activity of Arg1 and a reduction of arthritis in the absence of Fra-1, but not of Fra-2. This phenotype was reversed by treatment with the arginase inhibitor Nω-hydroxy-nor-arginine, while -arginine supplementation increased arginase activity and alleviated arthritis, supporting the notion that reduced arthritis in macrophage-specific Fra-1-deficient mice resulted from enhanced Arg1 expression and activity. Moreover, patients with active rheumatoid arthritis (RA) showed increased Fra-1 expression in the peripheral blood and elevated Fra-1 protein in synovial macrophages compared with RA patients in remission. In addition, the Fra-1/ARG1 ratio in synovial macrophages was related to RA disease activity. In conclusion, these data suggest that Fra-1 orchestrates the inflammatory state of macrophages by inhibition of Arg1 expression and thereby impedes the resolution of inflammation.
CRIS-Team Scopus Importer:2019-07-16

Transcriptome and histone epigenome of Plasmodium vivax salivary-gland sporozoites point to tight regulatory control and mechanisms for liver-stage differentiation in relapsing malaria - Muller, Ivo; Jex, Aaron R.; Kappe, Stefan H.I.; Mikolajczak, Sebastian A.; Sattabongkot, Jetsumon; Patrapuvich, Rapatbhorn; Lindner, Scott; Flannery, Erika L.; Koepfli, Cristian; Ansell, Brendan; Lerch, Anita; Emery-Corbin, Samantha J.; et al. (International Journal For Parasitology, 2019)
Plasmodium vivax is the key obstacle to malaria elimination in Asia and Latin America, largely attributed to its ability to form resilient hypnozoites (sleeper cells) in the host liver that escape treatment and cause relapsing infections. The decision to form hypnozoites is made early in the liver infection and may already be set in sporozoites prior to invasion. To better understand these early stages of infection, we undertook a comprehensive transcriptomic and histone epigenetic characterization of P. vivax sporozoites. Through comparisons with recently published proteomic data for the P. vivax sporozoite, our study found that although highly transcribed, transcripts associated with functions needed for early infection of the vertebrate host are not detectable as proteins and may be regulated through translational repression. We identified differential transcription between the sporozoite and published transcriptomes of asexual blood stages and mixed versus hypnozoite-enriched liver stages. These comparisons point to multiple layers of transcriptional, post-transcriptional and post-translational control that appear active in sporozoites and to a lesser extent hypnozoites, but are largely absent in replicating liver schizonts or mixed blood stages. We also characterised histone epigenetic modifications in the P. vivax sporozoite and explored their role in regulating transcription. Collectively, these data support the hypothesis that the sporozoite is a tightly programmed stage to infect the human host and identify mechanisms for hypnozoite formation that may be further explored in liver stage models.
CRIS-Team Scopus Importer:2019-05-21
Keywords: CHiP-Seq; Dormancy; Hypnozoite; Plasmodium vivax; RNA-seq; Sporozoite; Transcriptome

Trauma as a Trigger Factor for the First clinical Manifestation of cutaneous Leishmaniasis - Hiernickel, J.; Bogdan, Christian; Erfurt-Berge, Cornelia (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2019)
CRIS-Team WoS Importer:2019-05-17

Treatment-resistant nodular scleritis Therapieresistente noduläre Skleritis - Hübner, L.; Mardin, Christian; Held, Jürgen; Tappe, D.; Hammer, Christian; Bergua, Antonio (Ophthalmologe, 2022)
CRIS-Team Scopus Importer:2022-03-18

Trehalose diester glycolipids are superior to the monoesters in binding to Mincle, activation of macrophages in vitro and adjuvant activity in vivo - Huber, Alexandra; Kallerup, Rie S.; Korsholm, Karen S.; Franzyk, Henrik; Lepenies, Bernd; Christensen, Dennis; Foged, Camilla; Lang, Roland (Innate Immunity, 2016)
The T-cell adjuvanticity of mycobacterial cord factor trehalose 6,6'-dimycolate (TDM) is well established. The identification of the C-type lectin Mincle on innate immune cells as the receptor for TDM and its synthetic analogue trehalose 6,6'-dibehenate (TDB) has raised interest in development of synthetic Mincle ligands as novel adjuvants. Trehalose mono- (TMXs) and diesters (TDXs) with symmetrically shortened acyl chains [denoted by X: arachidate (A), stearate (S), palmitate (P), and myristate (M)] were tested. Upon stimulation of murine macrophages, G-CSF secretion and NO production were strongly augmented by all TDXs tested, in a wide concentration range. In contrast, the TMXs triggered macrophage activation only at high concentrations. Macrophage activation by all TDXs required Mincle, but was independent of MyD88. The superior capacity of TDXs for activating macrophages was paralleled by direct binding of TDXs, but not of TMXs, to a Mincle-Fc fusion protein. Insertion of a short polyethylene glycol between the sugar and acyl chain in TDS reduced Mincle-binding and macrophage activation. Immunization of mice with cationic liposomes containing the analogues demonstrated the superior adjuvant activity of trehalose diesters. Overall, immune activation in vitro and in vivo by trehalose esters of simple fatty acids requires two acyl chains of length and involves Mincle.
EVALuna2:7717

Trehalose dimycolate interferes with FcγR-mediated phagosome maturation through Mincle, SHP-1 and FcγRIIB signalling. - Patin, Emmanuel C.; Geffken, Anna C.; Willcocks, Sam; Leschczyk, Christoph; Haas, Albert; Nimmerjahn, Falk; Lang, Roland; Ward, Theresa H.; Schaible, Ulrich E. (PLoS ONE, 2017)
The causative agent of tuberculosis, Mycobacterium tuberculosis (M. tuberculosis), contains an abundant cell wall glycolipid and a crucial virulence factor, trehalose-6,6'-dimycolate (TDM). TDM causes delay of phagosome maturation and thus promotes survival of mycobacteria inside host macrophages by a not fully understood mechanism. TDM signals through the Monocyte-INducible C-type LEctin (Mincle), a recently identified pattern recognition receptor. Here we show that recruitment of Mincle by TDM coupled to immunoglobulin (Ig)G-opsonised beads during Fcγ receptor (FcγR)-mediated phagocytosis interferes with phagosome maturation. In addition, modulation of phagosome maturation by TDM requires SH2-domain-containing inositol polyphosphate 5' phosphatase (SHP-1) and the FcγRIIB, which strongly suggests inhibitory downstream signalling of Mincle during phagosome formation. Overall, our study reveals important mechanisms contributing to the virulence of TDM.

Tularemia lymphadenitis. An emerging differential diagnosis of necrotizing granulomatous cervical lymphadenitis - Strehl, Johanna; Schoerner, Christoph; Hartmann, Arndt; Agaimy, A. (Pathologe, 2014)
Tularemia is emerging as an important differential diagnosis of necrotizing granulomatous lymphadenitis, particularly in the head and neck region. The causal organism, Francisella tularensis is a Gram-negative coccoid bacterium. Tularemia usually presents with necrotizing granulomatous purulent lymphadenitis featuring multiple mostly small granulomas with geographic necrosis bordered by palisades of histiocytes. Diagnosis is mainly based on these characteristic but non-pathognomonic histological features in conjunction with negative tests for mycobacterial infections and serological confirmation of tularemia-specific antibodies or detection by polymerase chain reaction (PCR). This article describes our experiences with five patients with tularemia lymphadenitis and gives an overview of the diverse histopathological features and the differential diagnosis of this uncommon but possibly underrecognized disease.
EVALuna2:6582

Tumor location determines tissue-specific recruitment of tumor-associated macrophages and antibody-dependent immunotherapy response - Lehmann, Birgit; Biburger, Markus; Brückner, Christin; Ipsen Escobedo, Andrea; Gordan, Sina; Lehmann, Christian; Vöhringer, David; Winkler, Thomas; Schaft, Niels; Dudziak, Diana; Sirbu, Horia; Nimmerjahn, Falk; et al. (Science immunology, 2017)
Despite recent advances in activating immune cells to target tumors, the presence of some immune cells, such as tumor-associated macrophages (TAMs) or tumor-associated neutrophils (TANs), may promote rather than inhibit tumor growth. However, it remains unclear how antibody-dependent tumor immunotherapies, such as cytotoxic or checkpoint control antibodies, affect different TAM or TAN populations, which abundantly express activating Fcγ receptors. In this study, we show that the tissue environment determines which cellular effector pathways are responsible for antibody-dependent tumor immunotherapy. Although TAMs derived from Ly6Chigh monocytes recruited by the CCL2-CCR2 axis were critical for tumor immunotherapy of skin tumors, the destruction of lung tumors was CCL2-independent and required the presence of colony-stimulating factor 2–dependent tissue-resident macrophages. Our findings suggest that TAMs may have a dual role not only in promoting tumor growth in certain tissue environments on the one hand but also in contributing to tumor cell destruction during antibody-mediated immunotherapy on the other hand.
EVALuna2:15237
Keywords: Cancer; Macrophages; Tumor associated macrophages; Antibodies; Tumor therapy; Immunotherapy

Tuning of adaptive immune responses by TNF at the level of C-type lectin receptor expression - Blamberg, Robert; Lang, Roland (EUROPEAN JOURNAL OF IMMUNOLOGY, 2022)
CRIS-Team WoS Importer:2023-01-27

Two Cases of Severe Tick-Borne Encephalitis in Rituximab-Treated Patients in Germany: Implications for Diagnosis and Prevention - Steininger, Philipp; Bobinger, Tobias; Dietrich, Wenke; Lee, De-Hyung; Knott, Michael; Bogdan, Christian; Korn, Klaus; Lang, Roland (Open Forum Infectious Diseases, 2017)
Rituximab (RTX) has become a standard therapy for certain B cell malignancies and autoimmune diseases. We report 2 RTX-treated patients who developed severe tick-borne encephalitis virus (TBEV) infection. The inability to generate new antibody responses renders RTX-treated patients susceptible to TBEV, impedes laboratory diagnosis, and necessitates preventive vaccination in endemic areas.
EVALuna2:22593

Two cases of successful treatment of multilesional cutaneous leishmaniasis with liposomal amphotericin B - Butsch, Florian; Faulde, Michael; Debus, Andrea; Bogdan, Christian; Von Stebut, Esther (Journal der Deutschen Dermatologischen Gesellschaft, 2013)
CRIS-Team Scopus Importer:2024-02-26

Type 2 immunity regulates dermal white adipocyte function - Satzinger, S.; Willenborg, S.; Ding, X.; Vöhringer, David; Roers, A.; Eming, S. A. (EXPERIMENTAL DERMATOLOGY, 2022)
CRIS-Team WoS Importer:2022-03-04

Type 2 Immunity Regulates Dermal White Adipose Tissue Function - Satzinger, Sabrina; Willenborg, Sebastian; Ding, Xiaolei; Klose, Christoph S.N.; Radtke, Daniel; Vöhringer, David; Eming, Sabine A. (Journal of Investigative Dermatology, 2023)
Type 2 immune responses have been increasingly linked with tissue maintenance, regeneration, and metabolic homeostasis. The molecular basis of regulator and effector mechanisms of type 2 immunity in skin regeneration and homeostasis is still lacking. In this study, we analyzed the role of IL-4Rα signaling in the regeneration of diverse cellular compartments in the skin. Mutants with global IL-4Rα deficiency showed two major phenotypes: first, a pronounced atrophy of the interfollicular epidermis, and second, a significant increase in dermal white adipose tissue thickness in mice aged 3 weeks (postnatal day 21) compared with littermate controls. Notably, IL-4Rα deficiency decreased the activation of hormone-sensitive lipase, a rate-limiting step in lipolysis. Immunohistochemical and FACS analysis in IL-4/enhanced GFP reporter mice showed that IL-4 expression peaked on postnatal day 21 and that eosinophils are the predominant IL-4–expressing cells. Eosinophil-deficient mice recapitulated the lipolytic-defective dermal white adipose tissue phenotype of Il4ra-deficient mice, showing that eosinophils are necessary for dermal white adipose tissue lipolysis. Collectively, we provide mechanistic insights into the regulation of interfollicular epidermis and hormone-sensitive lipase–mediated lipolysis in dermal white adipose tissue in early life by IL-4Rα, and our findings show that eosinophils play a critical role in this process.
CRIS-Team Scopus Importer:2023-07-21

Type I Interferon Signaling Is Required for CpG-Oligodesoxynucleotide-Induced Control ofLeishmania major, but Not for Spontaneous Cure of Subcutaneous Primary or SecondaryL. majorInfection - Schleicher, Ulrike; Liese, Jan; Justies, Nicole; Mischke, Thomas; Haeberlein, Simone; Sebald, Heidi; Kalinke, Ulrich; Weiss, Siegfried; Bogdan, Christian (Frontiers in Immunology, 2018)
We previously showed that in mice infected withLeishmania majortype I interferons (IFNs) initiate the innate immune response to the parasite at day 1 and 2 of infection. Here, we investigated which type I IFN subtypes are expressed during the first 8 weeks ofL. majorinfection and whether type I IFNs are essential for a protective immune response and clinical cure of the disease. In self-healing C57BL/6 mice infected with a high dose ofL. major, IFN-α4, IFN-α5, IFN-α11, IFN-α13, and IFN-β mRNA were most prominently regulated during the course of infection. In C57BL/6 mice deficient for IFN-β or the IFN-α/β-receptor chain 1 (IFNAR1), development of skin lesions and parasite loads in skin, draining lymph node, and spleen was indistinguishable from wild-type (WT) mice. In line with the clinical findings, C57BL/6 IFN-β-/-, IFNAR1-/-, and WT mice exhibited similar mRNA expression levels of IFN-γ, interleukin (IL)-4, IL-12, IL-13, inducible nitric oxide synthase, and arginase 1 during the acute and late phase of the infection. Also, myeloid dendritic cells from WT and IFNAR1-/-mice produced comparable amounts of IL-12p40/p70 protein upon exposure toL. major in vitro. In non-healing BALB/c WT mice, the mRNAs of IFN-α subtypes (α2, α4, α5, α6, and α9) were rapidly induced after high-doseL. majorinfection. However, genetic deletion of IFNAR1 or IFN-β did not alter the progressive course of infection seen in WT BALB/c mice. Finally, we tested whether type I IFNs and/or IL-12 are required for the prophylactic effect of CpG-oligodesoxynucleotides (ODN) in BALB/c mice. Local and systemic administration of CpG-ODN 1668 protected WT and IFN-β-/-mice equally well from progressive leishmaniasis. By contrast, the protective effect of CpG-ODN 1668 was lost in BALB/c IFNAR1-/-(despite a sustained suppression of IL-4) and in BALB/c IL-12p35-/-mice. From these data, we conclude that IFN-β and IFNAR1 signaling are dispensable for a curative immune response toL. majorin C57BL/6 mice and irrelevant for disease development in BALB/c mice, whereas IL-12 and IFN-α subtypes are essential for the disease prevention by CpG-ODNs in this mouse strain.
EVALuna2:33302

Uncertainty due to different recommendations on pneumococcal vaccination in adults Frage - Antwort - Falkenhorst, Gerhard; Bogdan, Christian (Internistische Praxis, 2018)
CRIS-Team Scopus Importer:2024-02-26

Unimpaired Responses to Vaccination With Protein Antigen Plus Adjuvant in Mice With Kit-Independent Mast Cell Deficiency - Schubert, Nadja; Lisenko, Katharina; Auerbach, Christian; Weitzmann, Anke; Ghouse, Shanawaz Mohammed; Muhandes, Lina; Haase, Christa; Haering, Tobias; Schulze, Livia; Vöhringer, David; Gunzer, Florian; Mueller, Werner; et al. (Frontiers in Immunology, 2018)
Innate inflammatory responses are crucial for induction and regulation of T cell and antibody responses. Mast cell (MC)-deficient Kit mutant mice showed impaired adaptive immunity, suggesting that MCs provide essential adjuvant activities, and pharmacological MC activation was proposed as a new adjuvant principle. However, the Kit mutations result in complex alterations of the immune system in addition to MC deficiency. We revisited the role of MCs in vaccination responses using Mcpt5-Cre R26DTA/DTA and Cpa3Cre/+ mice that lack connective tissue MCs or all MCs, respectively, but feature an otherwise normal immune system. These animals showed no impairment of T and B cell responses to intradermal vaccination with protein antigen plus complete Freund's adjuvant. Moreover, we demonstrate that the adjuvant effects of the MC secretagogue c48/80 in intradermal or mucosal immunization are independent of the presence of MCs. We hence find no evidence for a regulation by MCs of adaptive immune responses to protein antigens. The finding that immunological MC functions differ from those suggested by experiments in Kit mutants, emphasizes the importance of rigorous tests in Kit-independent MC-deficiency models.
EVALuna2:36391

Unique characteristics of AQP4-specific T cells in patients with AQP4+neuromyelitis optica spectrum disorder (NMOSD) - Saggau, C.; Bacher, P.; Esser, D.; Leypoldt, F.; Wandinger, K. -P.; Paul, F.; Martin, R.; Fillatreau, S.; Schober, Kilian; Busch, D.; Stuerner, K.; Dargvainiene, J.; et al. (EUROPEAN JOURNAL OF IMMUNOLOGY, 2022)
CRIS-Team WoS Importer:2023-01-27

Unique roles of co-receptor-bound LCK in helper and cytotoxic T cells - Horkova, Veronika; Drobek, Ales; Paprckova, Darina; Niederlova, Veronika; Prasai, Avishek; Uleri, Valeria; Glatzova, Daniela; Kraller, Markus; Cesnekova, Michaela; Janusova, Sarka; Salyova, Eva; Tsyklauri, Oksana; et al. (Nature Immunology, 2023)
The kinase LCK and CD4/CD8 co-receptors are crucial components of the T cell antigen receptor (TCR) signaling machinery, leading to key T cell fate decisions. Despite decades of research, the roles of CD4–LCK and CD8–LCK interactions in TCR triggering in vivo remain unknown. In this study, we created animal models expressing endogenous levels of modified LCK to resolve whether and how co-receptor-bound LCK drives TCR signaling. We demonstrated that the role of LCK depends on the co-receptor to which it is bound. The CD8-bound LCK is largely dispensable for antiviral and antitumor activity of cytotoxic T cells in mice; however, it facilitates CD8+ T cell responses to suboptimal antigens in a kinase-dependent manner. By contrast, the CD4-bound LCK is required for efficient development and function of helper T cells via a kinase-independent stabilization of surface CD4. Overall, our findings reveal the role of co-receptor-bound LCK in T cell biology, show that CD4- and CD8-bound LCK drive T cell development and effector immune responses using qualitatively different mechanisms and identify the co-receptor–LCK interactions as promising targets for immunomodulation.
CRIS-Team Scopus Importer:2023-01-13

Usage of 1,3-?-D-Glucan for Early Detection of Invasive Mycoses and Outcome Parameter in Immunocompromised Critically Ill Patients - Lahmer, Tobias; Held, Jürgen; Rasch, Sebastian; Schnappauf, Christopher; Beitz, Analena; Schmid, Roland M.; Huber, Wolfgang (Mycopathologia, 2016)
Invasive fungal disease (IFD) remains a significant cause of morbidity and mortality in critically ill patients.Examination of 1,3-?-D-glucan (BDG) for IFD and as outcome parameter in immunocompromised critically ill patients with septic shock.Thirty-two (69 %) out of 46 included patients had BDG beyond the cutoff of >80 pg/ml (mean 320 pg/ml). Twelve (37 %) had findings of Aspergillus spp. in BAL (mean BDG 413 pg/ml). EORTC/MSG guidelines classified these as probable invasive aspergillosis (IA)/IFD. Five (16 %) had candidaemia (mean BDG level 361 pg/ml). Sensitivity of 78 % (95 % CI 58-88 %) and specificity of 68 % (95 % CI 52-77 %) for IFD were found on the BDG Fungitell assay. In detail, a sensitivity of 73 % (95 % 58-84 %) and specificity of 83 % (95 % CI 68-93 %) for IA and a sensitivity of 77 % (CI 95 % 62-87 %) and specificity 53 % (95 % CI 37-73 %) for candidaemia were found. APACHE II, SOFA score and mortality rate were in the elevated BDG group significantly altered (26 vs. 21, p < 0.003; 15 vs. 13, p < 0.006; 72 vs. 50 %, p < 0.004).1,3-?-D-glucan assay is helpful for early detection of IFD; moreover, elevated BDG levels can be used as a predictor for outcome in immunocompromised critically ill patients as presented in our study.
EVALuna2:7722

Usefulness of 1,3 Beta-D-Glucan Detection in non-HIV Immunocompromised Mechanical Ventilated Critically Ill Patients with ARDS and Suspected Pneumocystis jirovecii Pneumonia - Lahmer, Tobias; Da Costa, Clarissa Prazeres; Held, Jürgen; Rasch, Sebastian; Ehmer, Ursula; Schmid, Roland M.; Huber, Wolfgang (Mycopathologia, 2017)
INTRODUCTION: Pneumocystis jirovecii pneumonia (PCP) is a major cause of disease in immunocompromised individuals. Diagnosis is typically obtained by microscopy and/or PCR. For ambiguous PCR results, we evaluated the new biomarker 1,3-Beta-D-Glucan (BDG). METHODS: BDG serum levels were assessed and correlated to PCR results in immunosuppressed patients with ARDS. RESULTS: 11 (22%) out of 50 patients had suspected PCP. APACHE II (26 vs. 24; p < 0.002), SOFA score (16 vs. 14; p < 0.010) and mortality rate (34 vs. 69% p < 0.004; 34 vs. 80% p < 0.003) were significantly altered in patients with positive (pPCR) and slightly positive (spPCR) PCJ PCR as compared to patients with no-PCP (nPCP). BDG levels were significantly lower in patients with nPCP (86; 30-315 pg/ml) than in patients with pPCR (589; 356-1000 pg/ml; p < 0.001) and spPCP (398; 297-516 pg/ml; p < 0.004) referring to the cutoff in this study for PCP of 275 pg/ml. An overall sensitivity (S) of 92% (95% CI 86-96%) and specificity (SP) of 84% (95% CI 79-85%) for PCP were found for the BDG Fungitell assay. In detail, S of 98% (95% CI 94-100%) and SP of 86% (95% CI 82-92%) for pPCP and S of 98% (95% CI 96-100%) and SP of 88% (95% CI 86-96%) for spPCO were found. CONCLUSION: Serum BDG levels were strongly elevated in PCP, and the negative predictive value is high. BDG could be used as a preliminary test for patients with suspected PCP, especially in patients with slightly positive PCR results.
EVALuna2:33416

Using colistin as a trojan horse: Inactivation of gram-negative bacteria with chlorophyllin - Richter, Peter; Krüger, Marcus; Prasad, Binod; Gastiger, Susanne; Bodenschatz, Mona; Wieder, Florian; Burkovski, Andreas; Geißdörfer, Walter; Lebert, Michael; Strauch, Sebastian M. (Antibiotics, 2019)
Colistin (polymyxin E) is a membrane-destabilizing antibiotic used against Gram-negative bacteria. We have recently reported that the outer membrane prevents the uptake of antibacterial chlorophyllin into Gram-negative cells. In this study, we used sub-toxic concentrations of colistin to weaken this barrier for a combination treatment of Escherichia coli and Salmonella enterica serovar Typhimurium with chlorophyllin. In the presence of 0.25 µg/mL colistin, chlorophyllin was able to inactivate both bacteria strains at concentrations of 5-10 mg/L for E. coli and 0.5-1 mg/L for S. Typhimurium, which showed a higher overall susceptibility to chlorophyllin treatment. In accordance with a previous study, chlorophyllin has proven antibacterial activity both as a photosensitizer, illuminated with 12 mW/cm2, and in darkness. Our data clearly confirmed the relevance of the outer membrane in protection against xenobiotics. Combination treatment with colistin broadens chlorophyllin’s application spectrum against Gram-negatives and gives rise to the assumption that chlorophyllin together with cell membrane-destabilizing substances may become a promising approach in bacteria control. Furthermore, we demonstrated that colistin acts as a door opener even for the photodynamic inactivation of colistin-resistant (mcr-1-positive) E. coli cells by chlorophyllin, which could help us to overcome this antimicrobial resistance.
CRIS-Team Scopus Importer:2019-10-25
Keywords: Antibiotic resistance; Bacteria; Chlorophyll; Combination therapy; Mcr-1; Photosensitization

Using multimodal information for the segmentation of fluorescent micrographs with application to Virology and microbiology - Held, Christian; Wenzel, Jens; Webel, Rike; Marschall, Manfred; Palmisano, Ralf; Wittenberg, Thomas; et al. (Proc*s 2011 Annual International Conference of the IEEE Engineering in Medicine and Biology Society,EMBC,, 2011)
In order to improve reproducibility and objectivity of fluorescence microscopy based experiments and to enable the evaluation of large datasets, flexible segmentation methods are required which are able to adapt to different stainings and cell types. This adaption is usually achieved by the manual adjustment of the segmentation methods parameters, which is time consuming and challenging for biologists with no knowledge on image processing. To avoid this, parameters of the presented methods automatically adapt to user generated ground truth to determine the best method and the optimal parameter setup. These settings can then be used for segmentation of the remaining images. As robust segmentation methods form the core of such a system, the currently used watershed transform based segmentation routine is replaced by a fast marching level set based segmentation routine which incorporates knowledge on the cell nuclei. Our evaluations reveal that incorporation of multimodal information improves segmentation quality for the presented fluorescent datasets. © 2011 IEE
UnivIS-Import:2015-04-14:Pub.2011.med.IKMI.LHMMIPDR.usingm
Keywords: Fluorescence Microscopy; Digital Pathology; image analyis

USP18 lack in microglia causes destructive interferonopathy of the mouse brain - Goldmann, Tobias; Zeller, Nicolas; Raasch, Jenni; Kierdorf, Katrin; Frenzel, Kathrin; Ketscher, Lars; Basters, Anja; Staszewski, Ori; Brendecke, Stefanie M.; Spiess, Alena; Tay, Tuan Leng; Kreutz, Clemens; et al. (EMBO Journal, 2015)
Microglia are tissue macrophages of the central nervous system (CNS) that control tissue homeostasis. Microglia dysregulation is thought to be causal for a group of neuropsychiatric, neurodegenerative and neuroinflammatory diseases, called "microgliopathies". However, how the intracellular stimulation machinery in microglia is controlled is poorly understood. Here, we identified the ubiquitin-specific protease (Usp) 18 in white matter microglia that essentially contributes to microglial quiescence. We further found that microglial Usp18 negatively regulates the activation of Stat1 and concomitant induction of interferon-induced genes, thereby terminating IFN signaling. The Usp18-mediated control was independent from its catalytic activity but instead required the interaction with Ifnar2. Additionally, the absence of Ifnar1 restored microglial activation, indicating a tonic IFN signal which needs to be negatively controlled by Usp18 under non-diseased conditions. These results identify Usp18 as a critical negative regulator of microglia activation and demonstrate a protective role of Usp18 for microglia function by regulating the Ifnar pathway. The findings establish Usp18 as a new molecule preventing destructive microgliopathy.
EVALuna2:7686

Vaccinate for Immunodeficiency Application Instructions for Vaccinations recommended by the Permanent Vaccination Commission. (II) Vaccinate for 1. Primary Immunodeficiency Diseases and 2. HIV-Infection - Ehl, Stephan; Bogdan, Christian; Niehues, Tim; Burchard, Gerd; Baumann, Ulrich; Hecht, Jane; Koch, Judith; Neubert, Jennifer; Wiese-Posselt, Miriam; Zepp, Fred (Bundesgesundheitsblatt, Gesundheitsforschung, Gesundheitsschutz, 2018)
EVALuna2:36427

Vaccinate Patients with Immunodeficiency Instructions for Use of Vaccines recommended by the Standing Vaccination Commission (IV) Vaccination for Patients with Autoimmune Diseases, other chronic inflammatory Diseases and under immunomodulatory Therapy - Wagner, Norbert; Assmus, Frauke; Arendt, Gabriele; Baum, Erika; Baumann, Ulrich; Bogdan, Christian; Burchard, Gerd; Foell, Dirk; Garbe, Edeltraut; Hecht, Jane; Mueller-Ladner, Ulf; Niehues, Tim; et al. (Bundesgesundheitsblatt, Gesundheitsforschung, Gesundheitsschutz, 2019)
CRIS-Team WoS Importer:2019-04-16

Vaccination in Patients with Immunodeficiency Instructions for use of the Vaccinations recommended by the Standing Committee on Vaccination (II) Vaccination for 1. Primary Immunodeficiency Diseases and 2. HIV Infection (vol 61, pg 1034, 2018) - Ehl, Stephan; Bogdan, Christian; Niehues, Tim; Burchard, Gerd; Baumann, Ulrich; Hecht, Jane; Koch, Judith; Neubert, Jennifer; Wiese-Posselt, Miriam; Zepp, Fred (Bundesgesundheitsblatt, Gesundheitsforschung, Gesundheitsschutz, 2018)
Erratum zu:Bundesgesundheitsbl (2018)10.1007/s00103-018-2761-8In der Originalpublikation dieses Beitrags fehlt ein Hinweis zu Lebendimpfungen bei Patienten mit Storungen im Bereich der Toll-like-Rezeptor-Signaltransduktion.Am Ende des letzten Absatzes unter Punk 3.6Defekte der ...
EVALuna2:36426

Verunsicherung durch unterschiedliche empfehlungen zur pneumokokkenimpfung erwachsener - Falkenhorst, Gerhard; Bogdan, Christian (Tägliche Praxis, 2020)
CRIS-Team Scopus Importer:2020-10-09

When green and red mycology meet: Impressions from an interdisciplinary forum on virulence mechanisms of phyto- and human-pathogenic fungi - Yu, Yidong; Hube, Bernhard; Kämper, Jörg; Meyer, Vera; Krappmann, Sven (Virulence, 2017)
Fungal infections pose a constant threat to plants and humans, but detailed knowledge about pathogenesis, immunity, or virulence is rather scarce. Due to the fact that a certain overlap in the armoury of infection exists between plant- and human-pathogenic fungi, an interdisciplinary forum was held in October 2016 at the Institute for Clinical Microbiology, Immunology and Hygiene in Erlangen under the organisational umbrella from two special interest groups of German microbial societies. Scientific exchange and intense discussion of this timely topic was fostered by bringing together renowned experts in their respective fields to present their thoughts and recent findings in the course of a plenary lecture and six themed sessions, accompanied by oral and poster contributions of young researchers. By targeting the topic of fungal virulence mechanisms from various angles and in the context of plant and human hosts, some common grounds and exciting perspectives could be deduced during this vibrant scientific event.
EVALuna2:7738

Whipple's disease mimicking rheumatoid arthritis can cause misdiagnosis and treatment failure - Glaser, Cornelia; Rieg, Siegbert; Wiech, Thorsten; Scholz, Christine; Endres, Dominique; Stich, Oliver; Hasselblatt, Peter; Geißdörfer, Walter; Bogdan, Christian; Serr, Annerose; Haecker, Georg; Voll, Reinhard E.; et al. (Orphanet Journal of Rare Diseases, 2017)
Whipple's disease, a rare chronic infectious disorder caused by Tropheryma whipplei, may present with predominant joint manifestations mimicking rheumatoid arthritis (RA).A retrospective single-center cohort study of seven patients was performed. Clinical symptoms were assessed by review of medical charts and Whipple's disease was diagnosed by periodic-acid-Schiff-stain and/or Tropheryma whipplei-specific polymerase-chain-reaction.Median age at disease onset was 54 years, six patients were male. Median time to diagnosis was 5 years. All patients presented with polyarthritis with a predominantly symmetric pattern. Three had erosive arthritis. Affected joints were: wrists (5/7), metacarpophalangeal joints (MCPs) (5/7), knees (5/7), proximal interphalangeal joints (PIPs) (3/7), hips (2/7), elbow (2/7), shoulder (2/7). All patients had increased C-reactive-protein concentrations, while rheumatoid factor and anti-CCP-antibodies were absent, and were initially (mis)classified as RA-patients according to EULAR/ACR-criteria (median DAS28 4.3). Six patients received antirheumatic treatment consisting of prednisone with methotrexate and/or leflunomide, three were additionally treated with at least one biologic agent (abatacept, adalimumab, etanercept, rituximab, tocilizumab). Most patients showed insufficient treatment response. In all patients Tropheryma whipplei was detected in synovial fluid by polymerase-chain-reaction; in three patients the diagnosis of Whipple's disease was further ascertained by periodic-acid-Schiff-staining. Gastrointestinal symptoms and other extra-articular manifestations were absent, mild or non-specific. Treatment was initiated with trimethoprin/sulfamethoxazole in five and doxycycline/hydroxychloroquine in two patients and had to be adapted in five patients. Finally, all patients had good treatment responses with improvement of arthritis and extra-articular manifestations.Whipple's disease is rare and can mimic rheumatoid arthritis. Especially patients with seronegative rheumatoid arthritis with a prolonged disease course and insufficient treatment response should be reevaluated for Whipple's disease.
EVALuna2:7750

Whole-genome analysis of vancomycin-resistant Enterococcus faecium causing nosocomial outbreaks suggests the occurrence of few endemic clonal lineages in Bavaria, Germany - Eisenberger, David; Tuschak, Christian; Werner, Markus; Bogdan, Christian; Bollinger, Thomas; Hossain, Hamid; Friedrich, Petra; Hussein, Ziyad; Pöhlmann, Christoph; Würstl, Benjamin; Nickel, Silke; Lehner-Reindl, Verena; et al. (Journal of Antimicrobial Chemotherapy, 2020)
OBJECTIVES: Infections caused by vancomycin-resistant Enterococcus faecium (VREfm) represent a major public health concern due to limited treatment options. Among invasive isolates of VREfm, ST117, ST80 and ST78 represent the most frequently detected STs by MLST in Germany. In this study, we investigated the genetic diversity of isolates of VREfm recovered from different nosocomial outbreaks in Bavaria, Germany, by WGS. METHODS: Between January 2018 and April 2019, 99 non-replicate isolates of VREfm originating from nosocomial outbreaks at eight different hospitals in Bavaria were investigated for genetic diversity by WGS. In detail, complex types (CTs) were identified by core-genome MLST. Furthermore, an SNP analysis was performed for all VREfm strains. RESULTS: Most of the isolates of this study (76%) belonged to three major clonal groups, which occurred in at least three hospitals: ST80/CT1065 vanB (n = 45; six hospitals), ST117/CT71 vanB (n = 11; four hospitals) and ST78/CT894like vanA (n = 19; three hospitals). Moreover, isolates of the predominant lineage ST80/CT1065 vanB showed a maximum difference of 36 SNPs as revealed by SNP analysis. CONCLUSIONS: Whole-genome analysis of VREfm causing nosocomial outbreaks suggests the occurrence of few endemic clonal lineages in Bavarian hospital settings, namely ST80/CT1065 vanB, ST117/CT71 vanB and ST78/CT894like vanA. Further studies are needed for a better understanding of the factors affecting the successful spread of the above-mentioned lineages.
CRIS-Team Scopus Importer:2020-06-02

β-(1→3)-D-glucan- and mannan-guided early termination of antifungal therapy in ICU patients: a randomized controlled study - Erb, Timothy; Mihai, Sidonia; Strauss, Richard; Herbst, Larissa; Castellanos, Ixchel; Diesch, Katharina; Cipa, Franziska; Bihlmaier, Karl; Lang, Anne-Katharina; Ganslmayer, Marion; Willam, Carsten; Bremer, Frank Felix; et al. (Antimicrobial Agents and Chemotherapy, 2023)
Candida spp. are frequently encountered in specimens from ICUs. However, most of these detections represent colonization. Nevertheless, clinical practice shows that a considerable proportion of these patients will receive antifungal therapy (AT). β-(1→3)-D-glucan (BDG) and mannan are fungal biomarkers with high negative predictive values. We aimed to examine whether biomarker-guided discontinuation of AT can reduce the antifungal consumption. Therefore, we conducted a prospective, randomized intervention study between 1 April 2019 and 31 March 2020. All adult ICU patients with a newly started systemic AT but without fungal infection were eligible for inclusion. Enrolled patients were randomized into an intervention and a control group. In both groups, serum BDG and mannan were determined on days 1 and 2 of AT. If all measurements were negative, AT was discontinued in the intervention group. The primary endpoint was antifungal use. The study was terminated after 12 months. Until this time-point, 41 patients had been included. In the intervention group (n = 19), AT was stopped in only two patients because all others showed either positive BDG and∕or mannan levels. One of these two patients developed candidemia and AT had to be restarted. There was no significant difference in the primary and secondary endpoints. In summary, the strategy of using two negative BDG and mannan levels to stop AT failed to reduce antifungal consumption in our cohort. Indeed, there will inevitably be patients with invasive candidiasis in whom necessary AT is discontinued. The optimal patient population, biomarker set, and termination criteria are critical to the success of biomarker-based termination strategies.
CRIS-Team Scopus Importer:2023-12-15
Keywords: antibiotic stewardship; antifungal therapy; biomarker; Candida infection; candidemia; candidosis; discontinuation; fungal infection

Identification of Rosellinia species as producers of cyclodepsipeptide PF1022 A and resurrection of the genus Dematophora as inferred from polythetic taxonomy - Wittstein, K.; Cordsmeier, A.; Lambert, C.; Wendt, L.; Sir, E. B.; Weber, J.; Wurzler, N.; Petrini, L. E.; Stadler, M. (Studies in Mycology, 2020)
Rosellinia (Xylariaceae) is a large, cosmopolitan genus comprising over 130 species that have been defined based mainly on the morphology of their sexual morphs. The genus comprises both lignicolous and saprotrophic species that are frequently isolated as endophytes from healthy host plants, and important plant pathogens. In order to evaluate the utility of molecular phylogeny and secondary metabolite profiling to achieve a better basis for their classification, a set of strains was selected for a multi-locus phylogeny inferred from a combination of the sequences of the internal transcribed spacer region (ITS), the large subunit (LSU) of the nuclear rDNA, beta-tubulin (TUB2) and the second largest subunit of the RNA polymerase II (RPB2). Concurrently, various strains were surveyed for production of secondary metabolites. Metabolite profiling relied on methods with high performance liquid chromatography with diode array and mass spectrometric detection (HPLC-DAD/MS) as well as preparative isolation of the major components after re-fermentation followed by structure elucidation using nuclear magnetic resonance (NMR) spectroscopy and high resolution mass spectrometry (HR-MS). Two new and nine known isopimarane diterpenoids were identified during our mycochemical studies of two selected Dematophora strains and the metabolites were tested for biological activity. In addition, the nematicidal cyclodepsipeptide PF1022 A was purified and identified from a culture of Rosellinia corticium, which is the first time that this endophyte-derived drug precursor has been identified unambiguously from an ascospore-derived isolate of a Rosellinia species. While the results of this first HPLC profiling were largely inconclusive regarding the utility of secondary metabolites as genus-specific chemotaxonomic markers, the phylogeny clearly showed that species featuring a dematophora-like asexual morph were included in a well-defined clade, for which the genus Dematophora is resurrected. Dematophora now comprises all previously known important plant pathogens in the genus such as D. arcuata, D. bunodes, D. necatrix and D. pepo, while Rosellinia s. str. comprises those species that are known to have a geniculosporium-like or nodulisporium-like asexual morph, or where the asexual morph remains unknown. The extensive morphological studies of L.E. Petrini served as a basis to transfer several further species from Rosellinia to Dematophora, based on the morphology of their asexual morphs. However, most species of Rosellinia and allies still need to be recollected in fresh state, cultured, and studied for their morphology and their phylogenetic affinities before the infrageneric relationships can be clarified.
CRIS-Team Scopus Importer:2020-03-10
Keywords: Dematophora; Genus resurrection; Isopimarane diterpenoids; PF1022A; Polythetic taxonomy; Rosellinia; Xylariaceae

State of Medical Mycology at German Academic Medical Centres: A Survey of the German-Speaking Mycological Society (DMYKG) and the Paul-Ehrlich-Society for Chemotherapy (PEG). - Groll, Andreas H.; Gordon, Kathrin; Buchheidt, Dieter; Willinger, Birgit; Heinz, Werner J.; Kurzai, Oliver; Rickerts, Volker; Cornely, Oliver A. (Mycoses, 2021)
BACKGROUND: Little is known about the infrastructure to translate advances in the management of patients at risk to develop invasive opportunistic fungal diseases. To assess the current state of Medical Mycology support in Germany, we conducted a survey among all 36 academic medical centres. METHODS: The survey consisted of a 3-pages questionnaire sent out in the first half of 2019. Information included details of infrastructure, education and teaching; consultation services and interdisciplinary conferences; research activities and participation in network groups; radiology, microbiology and pharmacology support; publication activity; and European Confederation for Medical Mycology (ECMM) Excellence Center designation, if assigned. RESULTS: Information was returned from 24 centres (67%). Thirteen institutions (54%) reported an independent infectious disease, and two a separate Medical Mycology department (8%); a Medical Mycology working group was reported for nine institutions (38%). An infectious disease consultation service was existent in 16 institutions (67%) and a multidisciplinary conference in 13 (54%). Fifteen institutions reported a separate study office with activities in infectious disease studies (63%). Laboratory capability for fungal identification and susceptibility testing was confirmed by all 24 institutions; testing of galactomannan by 23 (96%), cryptococcal antigen by 21 (88%), ß-D-Glucan by 9 (38%), and panfungal and Pneumocystis PCR by 21 and 22 (88% and 92%), respectively. Therapeutic drug monitoring of voriconazole was reported to be available in 15 (63%) institutions with a turnaround of ≤24 h during weekdays in 10 (42%). Two of the 24 University hospitals (8%) reported ECMM Diamond Excellence Status. CONCLUSIONS: The results of this survey document the continuing need to improve the availability of specialised Medical Mycology support in German academic medical centres.
EVALuna2:470705